Abnormal epigenetic modification of lysosome and lipid regulating genes in Alzheimer's disease. - Ruan, Tingting; Ling, Yunxiang; Wu, Can; Niu, Yanfang; Liu, Guili; Xu, Chunshuang; Lv, Zhongyue; Yuan, Yalan; Zhou, Xinkai; Wang, Qinwen; Xu, Shujun (J Alzheimers Dis, 2025)
BackgroundAbnormal lipid metabolism has been identified as a potential pathogenic mechanism of Alzheimer's disease (AD), which might be epigenetically regulated. Lysosomes are critical organelles for lipid metabolism. However, the epigenetic modifications of lysosome and lipid regulating genes remain unclear in AD patients.ObjectiveExplore the role of abnormal epigenetic modifications, especially methylation of lysosome and lipid metabolism-related genes in AD.MethodsMethylation beadchip and MALDI-TOF mass spectrometry were used to detect genome-wide DNA methylation levels and validate key gene methylation, respectively. Clinical data were collected from all participants. Associations between clinical biochemical characteristics and altered DNA methylation in AD patients were analyzed, and a risk factor model of AD was established.Results41 differentially methylated positions (DMPs) corresponding to 33 genes were identified in AD patients, with 18 hypermethylated and 23 hypomethylated positions. Significant alterations were observed in lipid regulating genes () and lysosomal transmembrane gene (). Clinical analysis revealed that TP, ALB, IB, ADA, ALP, HCY, GLU, TC, BUN, HDL-C, LDL-C, and APOA1 levels were significantly higher in AD patients, whereas A/G and DB levels were lower. hypermethylation was further verified and found to correlate with TC, HDL-C, LDL-C, APOA1, IB, and HCY. The AUC of the AD risk model, which integrated clinical lipid markers and methylation, reached 0.9519 (< 0.0001).ConclusionsAbnormal epigenetic regulation of lysosomal gene and lipid dyshomeostasis were high-risk factors in AD. Methylation modifications of lysosome and lipid regulating genes might be key processes in AD pathogenesis.

Association among cardiorespiratory fitness, plasma biomarkers of pathology and astrocyte reactivity, and cognition in autosomal-dominant Alzheimer's disease. - Guzmán-Vélez, Edmarie; Aguillón, David; Rivera-Hernández, Angelys; Baena, Ana Y; Londoño-Sotomayor, Natalia; Picard, Glen; Kramer, Arthur F; Arnold, Steven E; Caraballo-Gracia, Domingo I; Taylor, J Andrew; Quiroz, Yakeel T (J Alzheimers Dis, 2025)
BackgroundHigh cardiorespiratory fitness has been associated with greater neuroplasticity, and slower neurodegeneration and cognitive decline in healthy adults. Yet, less is known about whether low-to-intermediate cardiorespiratory fitness is associated with lower markers of disease progression in the preclinical stage of Alzheimer's disease (AD).ObjectiveWe investigated whether cardiorespiratory fitness was associated with plasma biomarkers for AD-related pathology, neural injury and astrocyte reactivity, and episodic memory in Presenilin-1 E280A carriers without dementia from the world's largest kindred with autosomal-dominant AD.MethodsTwenty-seven mutation carriers (25 cognitively unimpaired, 2 with mild cognitive impairment; ages: μ=30.22 years, SD = 5.24; 74% female) participated in the study. Participants underwent a graded aerobic fitness test to assess cardiorespiratory fitness, measured in maximum metabolic equivalent of task (MET). Plasma biomarkers included amyloid 42/40, phosphorylated tau-181, neurofilament light chain, and glial fibrillary acidic protein. Participants completed the Consortium to Establish a Registry for AD word list learning and delayed recall. We conducted multiple linear regressions controlling for age, sex, and years of education.ResultsFourteen participants' MET values were indicative of low cardiorespiratory fitness (< MET), and 13 participants' MET values of intermediate cardiorespiratory fitness (9-14 MET). METs were not associated with age, biomarkers, or episodic memory.ConclusionsOur findings suggest that low-to-intermediate cardiorespiratory fitness may not be associated with biomarkers for AD-related pathology, neural injury and astrocyte reactivity, or memory in people at genetic risk for dementia. Longitudinal studies and randomized-controlled trials are needed to better understand the relationships among cardiorespiratory fitness and AD progression.

Brain-penetrant histone deacetylase inhibitor RG2833 improves spatial memory in females of an Alzheimer's disease rat model. - Ndukwe, Kelechi; Serrano, Peter A; Rockwell, Patricia; Xie, Lei; Figueiredo-Pereira, Maria E (J Alzheimers Dis, 2025)
BACKGROUND: Nearly two-thirds of Alzheimer's disease (AD) patients are women. Therapeutics for women are critical to lowering their elevated risk of developing this major cause of adult dementia. Moreover, targeting epigenetic processes such as histone acetylation that regulate multiple cellular pathways is advantageous given the multifactorial nature of AD. Histone acetylation takes part in memory consolidation, and its disruption is linked to AD. OBJECTIVE: Determine whether the investigational drug RG2833 has repurposing potential for AD. RG2833 is a histone deacetylase HDAC1/3 inhibitor that is orally bioavailable and permeates the blood-brain-barrier. METHODS: RG2833 effects were determined on cognition, transcriptome, and AD-like pathology in 11-month TgF344-AD female and male rats. Treatment started early in the course of pathology when therapeutic intervention is predicted to be most effective. RESULTS: RG2833-treatment of 11-month TgF344-AD rats: (1) Significantly improved hippocampal-dependent spatial memory in females but not males. (2) Upregulated expression of immediate early genes, such as Arc, Egr1 and c-Fos, and other genes involved in synaptic plasticity and memory consolidation in females. Remarkably, out of 17,168 genes analyzed for each sex, no significant changes in gene expression were detected in males at p < 0.05, false discovery rate <0.05, and fold-change equal or > 1.5. (3) Failed to improve amyloid beta accumulation and microgliosis in female and male TgF344-AD rats. CONCLUSIONS: Our study highlights the potential of histone-modifying therapeutics such as RG2833 to improve cognitive behavior and drive the expression of immediate early, synaptic plasticity and memory consolidation genes, especially in female AD patients.

EEG biomarkers for Alzheimer's disease: A novel automated pipeline for detecting and monitoring disease progression. - Simmatis, Leif Er; Russo, Emma E; Steininger, Tayo; Riddell, Haleigh; Chen, Evelyn; Chiu, Queenny; Lin, Michelle; Oh, Donghun; Taheri, Porsha; Harmsen, Irene E; Samuel, Nardin (J Alzheimers Dis, 2025)
BackgroundAlzheimer's disease (AD) is a neurodegenerative disorder that profoundly alters brain function and organization. Currently, there is a lack of validated functional biomarkers to aid in diagnosing and classifying AD. Therefore, there is a pressing need for early, accurate, non-invasive, and accessible methods to detect and characterize disease progression. Electroencephalography (EEG) has emerged as a minimally invasive technique to quantify functional changes in neural activity associated with AD. However, challenges such as poor signal-to-noise ratio-particularly for resting-state (rsEEG) recordings-and issues with standardization have hindered its broader application.ObjectiveTo conduct a pilot analysis of our custom automated preprocessing and feature extraction pipeline to identify indicators of AD and correlates of disease progression.MethodsWe analyzed data from 36 individuals with AD and 29 healthy participants recorded using a standard 19-channel EEG and features were processed using our custom end-t-end pipeline. Various features encompassing amplitude, power, connectivity, complexity, and microstates were extracted. Unsupervised machine learning (uniform manifold approximation and projection) and supervised learning (random forest classifiers with nested cross-validation) were used to characterize the dataset and identify differences between AD and healthy groups.ResultsOur pipeline successfully detected several new and previously established EEG-based measures indicative of AD status and progression, demonstrating strong external validity.ConclusionsOur findings suggest that this automated approach provides a promising initial framework for implementing EEG biomarkers in the AD patient population, paving the way for improved diagnostic and monitoring strategies.

Factors associated with a healthy diet and willingness to change dietary behavior in older adults at increased risk of dementia. - Blotenberg, Iris; Zülke, Andrea E; Luppa, Melanie; Wittmann, Felix; Fankhänel, Thomas; Weise, Solveig; Döhring, Juliane; Escales, Catharina; Kosilek, Robert P; Michel, Irina; Brettschneider, Christian; Oey, Anke; et al. (J Alzheimers Dis, 2025)
BackgroundHealthy dietary patterns have been linked to reduced risks for cardiovascular diseases and dementia, making nutrition an essential part of a comprehensive approach for dementia prevention. Knowledge about factors associated with a healthy diet in people with increased dementia risk is scarce.ObjectiveTo analyze dietary habits and associated factors in older adults with increased dementia risk in Germany.MethodsWe used baseline-data of the AgeWell.de-trial (n = 1001, %= 52.2, M= 69.0, SD = 4.9). Nutrition was assessed using a composite score, comprising 11 components covered by national recommendations for a healthy diet (range = 0-11 points). Linear regressions assessed associations of sociodemographic, social, health-related and psychological factors with consumption of a healthy diet. Further, we assessed stages of change based on the transtheoretical model of behavior change.ResultsConsumption of a healthy diet was moderate (Median = 4, IQR = 2). Female sex (b = 0.64, 95% CI: 0.41, 0.88), higher levels of motivation for healthy eating (b = 0.22, 95% CI: 0.10, 0.34) and higher self-efficacy (b = 0.33, 95% CI: 0.20, 0.46) were linked to a healthy diet. Regarding the stages of behavior change, the majority were in the maintenance stage (45.2%), followed by the contemplation (21.5%) and precontemplation (21.2%) stages.ConclusionsResults suggest room for improvement regarding a healthy diet in our sample. Lifestyle-based interventions in older adults should be tailored towards current levels of motivation and self-efficacy of participants. Including modules targeting motivation and self-efficacy might help maximize intervention effectiveness.

Lifespan of male and female APP/PS1 and APP mouse models of Alzheimer's disease. - Roberts, Hannah; Fang, Yimin; Quinn, Kathleen; Hill, Tiarra; Peck, Mackenzie R; Bartke, Andrzej; Hascup, Kevin N; Hascup, Erin R (J Alzheimers Dis, 2025)
Alzheimer's disease (AD) disproportionately affects women, yet most preclinical research studies are male-centric. We performed lifespan analyses of male and female AD mouse models (APP/PS1 and APP) and their shared genetic background control (C57BL/6). Survival curves support significant sex differences between genotypes. Minimal longevity revealed increased age in male APP/PS1, and decreased age in male APP mice. Maximal longevity revealed an increased average age in males. Furthermore, median lifespan differed between sex and genotype. This study supports dimorphic survival in two mouse models of AD, emphasizing the need to examine mechanisms and treatments in both sexes.

Performance of a smell identification test versus the Mini-Mental Status Exam for the detection of dementia and cognitive impairment among persons with cognitive concerns in primary care. - Luchsinger, Jose A; Teresi, Jeanne A; Valdez, Lenfis; Rosario, Dahiana; de Miguel, Maria; Taylor, Delphine; Singer, Jessica; Chang, Nancy; Fuller, William S; Boquín, Cyrus; Silver, Stephanie; Eimicke, Joseph P; et al. (J Alzheimers Dis, 2025)
BackgroundOdor identification deficits predict Alzheimer's disease (AD) in epidemiological studies.ObjectiveTo compare the accuracy of a short odor identification test with a short cognitive screening test for the detection of dementia and cognitive impairment in elderly persons with cognitive concerns.MethodsThis was a cross-sectional study of 600 participants 65 years and older, without known mild cognitive impairment (MCI) or dementia, with cognitive concerns, attending primary care practices in New York City. The odor identification test was the Brief Smell Identification Test (BSIT). The comparator test was the Mini Mental Status Exam II (MMSE). Cognitive diagnoses were made using the National Alzheimer's Coordinating Center Uniform Data set (NACC-UDS) version 3 forms with slight modifications. Test performance was compared using Receiver Operating Characteristic analyses.ResultsThe mean age was 72.65 ± 6.31 years, 73.3% were female, 63.3% were Hispanic, 13.5% non-Hispanic Black, and 20.8% non-Hispanic White; 23.5% were classified as normal cognition, 27.7% as cognitive impairment-not mild cognitive impairment (MCI), 31.2% as amnestic MCI, 5.7% as non-amnestic MCI, and 12% as dementia. The MMSE was superior to the BSIT in detecting dementia and any cognitive impairment. Combining abnormal scores in the BSIT (≤8) to MMSE (≤24) improved the MMSE's specificity and positive predictive value (PPV) in detecting cognitive impairment.ConclusionsThe MMSE was superior to the BSIT in detecting dementia and cognitive impairment in primary care but using both tests improved specificity and PPV for identifying persons with subjective complaints needing further cognitive and biomarker evaluation.

Acute Hyperglycemia Induced by Hyperglycemic Clamp Affects Plasma Amyloid-β in Type 2 Diabetes. - Rolandsson, Olov; Tornevi, Andreas; Steneberg, Pär; Edlund, Helena; Olsson, Tommy; Andreasson, Ulf; Zetterberg, Henrik; Blennow, Kaj (J Alzheimers Dis, 2024)
BACKGROUND: Individuals with type 2 diabetes (T2D) have an increased risk of cognitive symptoms and Alzheimer's disease (AD). Mis-metabolism with aggregation of amyloid-β peptides (Aβ) play a key role in AD pathophysiology. Therefore, human studies on Aβ metabolism and T2D are warranted. OBJECTIVE: The objective of this study was to examine whether acute hyperglycemia affects plasma Aβ1-40 and Aβ1-42 concentrations in individuals with T2D and matched controls. METHODS: Ten participants with T2D and 11 controls (median age, 69 years; range, 66-72 years) underwent hyperglycemic clamp and placebo clamp (saline infusion) in a randomized order, each lasting 4 hours. Aβ1-40, Aβ1-42, and insulin-degrading enzyme (IDE) plasma concentrations were measured in blood samples taken at 0 and 4 hours of each clamp. Linear mixed-effect regression models were used to evaluate the 4-hour changes in Aβ1-40 and Aβ1-42 concentrations, adjusting for body mass index, estimated glomerular filtration rate, and 4-hour change in insulin concentration. RESULTS: At baseline, Aβ1-40 and Aβ1-42 concentrations did not differ between the two groups. During the hyperglycemic clamp, Aβ decreased in the control group, compared to the placebo clamp (Aβ1-40: p = 0.034, Aβ1-42: p = 0.020), IDE increased (p = 0.016) during the hyperglycemic clamp, whereas no significant changes in either Aβ or IDE was noted in the T2D group. CONCLUSIONS: Clamp-induced hyperglycemia was associated with increased IDE levels and enhanced Aβ40 and Aβ42 clearance in controls, but not in individuals with T2D. We hypothesize that insulin-degrading enzyme was inhibited during hyperglycemic conditions in people with T2D.
Keywords: Aged; Amyloid beta-Peptides; Blood Glucose; Diabetes Mellitus, Type 2; Female; Glucose Clamp Technique; Humans; Hyperglycemia; Insulysin; Male; Peptide Fragments

African Ancestry Individuals with Higher Educational Attainment Are Resilient to Alzheimer's Disease Measured by pTau181. - Rajabli, Farid; Seixas, Azizi A; Akgun, Bilcag; Adams, Larry D; Inciute, Jovita; Hamilton, Kara L; Whithead, Patrice G; Konidari, Ioanna; Gu, Tianjie; Arvizu, Jamie; Golightly, Charles G; Starks, Takiyah D; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Cognitive and functional abilities in individuals with Alzheimer's disease (AD) pathology (ADP) are highly variable. Factors contributing to this variability are not well understood. Previous research indicates that higher educational attainment (EA) correlates with reduced cognitive impairments among those with ADP. While cognitive and functional impairments are correlated, they are distinguishable in their manifestations. OBJECTIVE: To investigate whether levels of education are associated with functional impairments among those with ADP. METHODS: This research involved 410 African American (AA) individuals (Institutional Review Boards 20070307, 01/27/2023) to ascertain whether EA correlates with functional resilience and if this effect varies between APOE ɛ4 carriers and non-carriers. Utilizing EA as a cognitive reserve proxy, CDR-FUNC as a functional difficulties measure, and blood pTau181 as an ADP proxy, the non-parametric Mann-Whitney U test assessed the relationship between EA and CDR-FUNC in individuals with advanced pTau181 levels. RESULTS: The results showed that EA correlated with functional difficulties in AA individuals with high levels of pTau181, such that individuals with high EA are more likely to have better functional ability compared to those with lower EA (W = 730.5, p = 0.0007). Additionally, we found that the effect of high EA on functional resilience was stronger in ɛ4 non-carriers compared to ɛ4 carriers (W = 555.5, p = 0.022). CONCLUSION: This study extends the role of cognitive reserve and EA to functional performance showing that cognitive reserve influences the association between ADP burden and functional difficulties. Interestingly, this protective effect seems less pronounced in carriers of the strong genetic risk allele ɛ4.
Keywords: Alzheimer Disease; Apolipoprotein E4; Cognitive Dysfunction; Educational Status; Humans; Resilience, Psychological

Alterations in Synaptic Connectivity and Synaptic Transmission in Alzheimer's Disease with High Physical Activity. - Wu, Can; Ruan, Tingting; Yuan, Yalan; Xu, Chunshuang; Du, Lijuan; Wang, Fang; Xu, Shujun (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is a progressive neurodegeneration disease. Physical activity is one of the most promising modifiable lifestyles that can be effective in slowing down the progression of AD at an early stage. OBJECTIVE: Explore the molecular processes impaired in AD that were conversely preserved and enhanced by physical activity. METHODS: Integrated transcriptomic analyses were performed in datasets that contain AD patients and elders with different degrees of physical activity. The changes of the hub genes were validated through analyzing another two datasets. The expression of the hub genes was further detected in the hippocampus and cortexes of APP/PS1 transgenic mice with or without physical activity by Quantitative polymerase chain reaction (qPCR). RESULTS: Cross-comparison highlighted 195 DEGs displaying opposed regulation patterns between AD and high physical activity (HPA). The common DEGs were predominantly involved in synaptic vesicle recycling and synaptic transmission, largely downregulated in AD patients but upregulated in the elders with HPA. Two key modules and four hub genes that were related to synaptic vesicle turnover were obtained from the PPI network. The expression of these hub genes (SYT1, SYT4, SH3GL2, and AP2M1) was significantly decreased in AD transgenic mice and was reversed by HPA training. CONCLUSIONS: HPA may reverse AD pathology by upregulating a range of synaptic vesicle transport related proteins which might improve the efficiency of synaptic vesicle turnover and facilitate inter-neuronal information transfer. The study provides novel insights into the mechanisms underlining the protective effects of HPA on AD.

Alzheimer's Disease Immunotherapy: Current Strategies and Future Prospects. - Aljassabi, Ali; Zieneldien, Tarek; Kim, Janice; Regmi, Deepika; Cao, Chuanhai (J Alzheimers Dis, 2024)
Alzheimer's disease (AD) is an extremely complex and heterogeneous pathology influenced by many factors contributing to its onset and progression, including aging, amyloid-beta (Aβ) plaques, tau fibril accumulation, inflammation, etc. Despite promising advances in drug development, there is no cure for AD. Although there have been substantial advancements in understanding the pathogenesis of AD, there have been over 200 unsuccessful clinical trials in the past decade. In recent years, immunotherapies have been at the forefront of these efforts. Immunotherapy alludes to the immunological field that strives to identify disease treatments via the enhancement, suppression, or induction of immune responses. Interestingly, immunotherapy in AD is a relatively new approach for non-infectious disease. At present, antibody therapy (passive immunotherapy) that targets anti-Aβ aimed to prevent the fibrillization of Aβ peptides and disrupt pre-existing fibrils is a predominant AD immunotherapy due to the continuous failure of active immunotherapy for AD. The most rational and safe strategies will be those targeting the toxic molecule without triggering an abnormal immune response, offering therapeutic advantages, thus making clinical trial design more efficient. This review offers a concise overview of immunotherapeutic strategies, including active and passive immunotherapy for AD. Our review encompasses approved methods and those presently under investigation in clinical trials, while elucidating the recent challenges, complications, successes, and potential treatments. Thus, immunotherapies targeting Aβ throughout the disease progression using a mutant oligomer-Aβ stimulated dendritic cell vaccine may offer a promising therapy in AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Humans; Immunization, Passive; Immunotherapy; Inflammation

Amnestic Syndrome in Memory Clinics: Similar Morphological Brain Patterns in Older Adults with and without Alzheimer's Disease. - Lalive, Hadrien M; Griffa, Alessandra; Carlier, Sabrina; Nasuti, Mirco; Di Noto, Tommaso; Maréchal, Bénédicte; Rouaud, Olivier; Allali, Gilles (J Alzheimers Dis, 2024)
BACKGROUND: Amnestic syndrome of the hippocampal type (ASHT) in Memory Clinics is a presentation common to Alzheimer's disease (AD). However, ASHT can be found in other neurodegenerative disorders. OBJECTIVE: To compare brain morphometry including hippocampal volumes between amnestic older adults with and without AD pathology and investigate their relationship with memory performance and cerebrospinal fluid (CSF) biomarkers. METHODS: Brain morphometry of 92 consecutive patients (72.5±6.8 years old; 39% female) with Free and Cued Selective Recall Reminding Test (FCSRT) total recall < 40/48 was assessed with an automated algorithm and compared between AD and non-AD patients, as defined by CSF biomarkers. RESULTS: AD and non-AD patients presented comparable brain morphology. Total recall was associated to hippocampal volume irrespectively from AD pathology. CONCLUSIONS: Brain morphometry, including hippocampal volumes, is similar between AD and non-AD older adults with ASHT evaluated in a Memory Clinic, underlying the importance of using molecular biomarkers for the diagnosis of AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amnesia; Amyloid beta-Peptides; Biomarkers; Brain; Female; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Mental Recall; Neuropsychological Tests; Organ Size

The Association Between Neuropathological Lesions and Body Mass Index Is Independent of Cognitive Abilities. - Ururahy, Raul Dos Reis; do Val, Marina Scott; Ciciliati, Aline Maria Macagnan; Leite, Renata Elaine Paraizo; Paes, Vitor Ribeiro; Rodrigues, Roberta Diehl; Grinberg, Lea Tenenholz; Pasqualucci, Carlos Augusto; Jacob Filho, Wilson; Suemoto, Claudia Kimie (J Alzheimers Dis, 2024)
BACKGROUND: The association of moderate and severe dementia with low body mass index (BMI) is well described, but weight decline seems to also occur in individuals with preclinical neuropathologies. Considering that up to one-fifth of individuals with normal cognition meet the criteria for a dementia-related neuropathological diagnosis, autopsy studies are key to detecting preclinical neurodegenerative and cerebrovascular diseases that could be underlying weight changes. OBJECTIVE: We investigated the association between dementia-related brain lesions and BMI and evaluated whether the cognitive function was a mediator of this association. METHODS: In 1,170 participants, sociodemographic data, clinical history, and cognitive post-mortem evaluation were assessed with an informant. Neuropathological evaluation was performed in all cases. Linear regression models were used to investigate the association between neuropathological lesions (exposure variable) and BMI (outcome) adjusted for demographic, clinical, and cognitive variables in the whole sample, and in only those with normal cognition. Corrections for multiple comparisons were performed. In addition, a mediation analysis was performed to investigate the direct and indirect effects of cognitive abilities on the association between neuropathology and BMI. RESULTS: Individuals with lower BMI had a higher burden of neuropathological lesions and poorer cognitive abilities. Only neurofibrillary tangles (NFT) and neuropathological comorbidity were associated with low BMI, while other neurodegenerative and cerebrovascular lesions were not. NFT were indirectly associated with BMI through cognitive abilities, and also directly, even in participants with normal cognition. CONCLUSIONS: Neurofibrillary tangles were directly associated with low BMI even in individuals with preclinical Alzheimer's disease.

Association Between Urinary Glyphosate Exposure and Cognitive Impairment in Older Adults from NHANES 2013-2014. - Ren, Jiawen; Yu, Yongquan; Wang, Yucheng; Dong, Yu; Shen, Xiaobing (J Alzheimers Dis, 2024)
BACKGROUND: Glyphosate is the most commonly used herbicide with potential neurotoxicity. However, limited epidemical evidence is found in the relationship between glyphosate and cognitive impairment, especially in the cognitive-disrupting sensitive elderly populations. OBJECTIVE: This study aimed to examine the association of urinary glyphosate exposure with cognitive impairment in the United State (US) older adults. METHODS: Cognitive impairment was determined by the following four tests: the Consortium to Establish a Registry for Alzheimer's disease (CERAD) Immediate Recall test (IR), the CERAD Delayed Recall tests (DR), the Animal Fluency (AF) test and the Digit Substitution test (DSST). Survey weighted logistic regression and restricted cubic splines were applied to evaluate and visualize the association between glyphosate and cognitive impairment. RESULTS: A total of 465 elderly adults were identified in the National Health and Nutrition Examination Survey (NHANES) 2013-2014 cycle, and among them, 83.87% individuals had detectable urinary levels of glyphosate (0.628 ng/mL in average). After adjusting for the potential covariates, glyphosate was significantly linked to increased DR and AF impairment, and the corresponding ORs were 1.52 (1.01 to 2.30, p = 0.049) and 1.69 (1.11 to 2.59, p = 0.019), respectively. No significant association was identified between glyphosate and IR or DSST impairment. The RCS plot further confirmed the linear and positive relationships between glyphosate and DR and AF impairment. CONCLUSIONS: These findings suggested that exposure to glyphosate might be associated with declined cognitive function in the elderly, and it might be prudent to evaluate cognitive outcomes for aged individuals with glyphosate exposures.
Keywords: Aged; Alzheimer Disease; Cognition; Cognition Disorders; Cognitive Dysfunction; Glyphosate; Humans; Nutrition Surveys

Associations Between Music and Dance Relationships, Rhythmic Proficiency, and Spatiotemporal Movement Modulation Ability in Adults with and without Mild Cognitive Impairment. - Slusarenko, Alexandra; Rosenberg, Michael C; Kazanski, Meghan E; McKay, J Lucas; Emmery, Laura; Kesar, Trisha M; Hackney, Madeleine E (J Alzheimers Dis, 2024)
BACKGROUND: Personalized dance-based movement therapies may improve cognitive and motor function in individuals with mild cognitive impairment (MCI), a precursor to Alzheimer's disease. While age- and MCI-related deficits reduce individuals' abilities to perform dance-like rhythmic movement sequences (RMS)-spatial and temporal modifications to movement-it remains unclear how individuals' relationships to dance and music affect their ability to perform RMS. OBJECTIVE: Characterize associations between RMS performance and music or dance relationships, as well as the ability to perceive rhythm and meter (rhythmic proficiency) in adults with and without MCI. METHODS: We used wearable inertial sensors to evaluate the ability of 12 young adults (YA; age = 23.9±4.2 years; 9F), 26 older adults without MCI (OA; age = 68.1±8.5 years; 16F), and 18 adults with MCI (MCI; age = 70.8±6.2 years; 10F) to accurately perform spatial, temporal, and spatiotemporal RMS. To quantify self-reported music and dance relationships and rhythmic proficiency, we developed Music (MRQ) and Dance Relationship Questionnaires (DRQ), and a rhythm assessment (RA), respectively. We correlated MRQ, DRQ, and RA scores against RMS performance for each group separately. RESULTS: The OA and YA groups exhibited better MRQ and RA scores than the MCI group (p < 0.006). Better MRQ and RA scores were associated with better temporal RMS performance for only the YA and OA groups (r2 = 0.18-0.41; p < 0.045). DRQ scores were not associated with RMS performance in any group. CONCLUSIONS: Cognitive deficits in adults with MCI likely limit the extent to which music relationships or rhythmic proficiency improve the ability to perform temporal aspects of movements performed during dance-based therapies.

BACE1 Inhibitors for Alzheimer's Disease: Current Challenges and Future Perspectives. - Coimbra, Judite R M; Resende, Rosa; Custódio, José B A; Salvador, Jorge A R; Santos, Armanda E (J Alzheimers Dis, 2024)
Disease-modifying therapies (DMT) for Alzheimer's disease (AD) are highly longed-for. In this quest, anti-amyloid therapies take center stage supported by genetic facts that highlight an imbalance between production and clearance of amyloid-β peptide (Aβ) in AD patients. Indeed, evidence from basic research, human genetic and biomarker studies, suggests the accumulation of Aβ as a driver of AD pathogenesis and progression. The aspartic protease β-site AβPP cleaving enzyme (BACE1) is the initiator for Aβ production. Underpinning a critical role for BACE1 in AD pathophysiology are the elevated BACE1 concentration and activity observed in the brain and body fluids of AD patients. Therefore, BACE1 is a prime drug target for reducing Aβ levels in early AD. Small-molecule BACE1 inhibitors have been extensively developed for the last 20 years. However, clinical trials with these molecules have been discontinued for futility or safety reasons. Most of the observed adverse side effects were due to other aspartic proteases cross-inhibition, including the homologue BACE2, and to mechanism-based toxicity since BACE1 has substrates with important roles for synaptic plasticity and synaptic homeostasis besides amyloid-β protein precursor (AβPP). Despite these setbacks, BACE1 persists as a well-validated therapeutic target for which a specific inhibitor with high substrate selectivity may yet to be found. In this review we provide an overview of the evolution in BACE1 inhibitors design pinpointing the molecules that reached advanced phases of clinical trials and the liabilities that precluded adequate trial effects. Finally, we ponder on the challenges that anti-amyloid therapies must overcome to achieve clinical success.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid Precursor Protein Secretases; Animals; Aspartic Acid Endopeptidases; Enzyme Inhibitors; Humans

Blood-Based mtDNA Quantification Indicates Population-Specific Differences Associated with Alzheimer's Disease-Related Risk. - Gorham, Isabelle K; Reid, Danielle Marie; Sun, Jie; Zhou, Zhengyang; Barber, Robert C; Phillips, Nicole R (J Alzheimers Dis, 2024)
BACKGROUND: Age is known to be the biggest risk factor for Alzheimer's disease (AD), and Mexican Americans (MAs), who are one of the fastest-aging populations in the United States, are at a uniquely elevated risk. Mitochondrial stress and dysfunction are key players in the progression of AD and are also known to be impacted by lifestyle and environmental exposures/stressors. OBJECTIVE: This study aimed to identify population-specific differences in indicators of mitochondrial stress and dysfunction associated with AD risk that are detectable in the blood. METHODS: Examining blood from both non-Hispanic white (NHW) and MA participants (N = 527, MA n = 284, NHW n = 243), mitochondrial DNA (mtDNA) and nuclear DNA (nDNA) copy numbers were assessed through quantitative PCR. Data was stratified by population and sample type, and multiple linear regression analyses were performed to identify factors that may influence this phenotype of mitochondrial dysfunction. RESULTS: In the MA cohort, there was a significant relationship between cellular mtDNA:nDNA ratio and body mass index, CDR sum of boxes score, the APOEɛ2/ɛ3 genotype, and education. Further, there was a significant relationship between cell-free mtDNA copy number and both education and CDR sum score. In the NHW cohort, there was a significant relationship between cellular mtDNA:nDNA ratio and both age and CDR sum score. Age was associated with cell-free mtDNA in the NHW cohort. CONCLUSIONS: This evidence supports the existence of population-based differences in the factors that are predictive of this blood-based phenotype of mitochondrial dysfunction, which may be indicative of cognitive decline and AD risk.

Computational Evaluation of the Potential Pharmacological Activity of Salen-Type Ligands in Alzheimer's Disease. - Puentes-Díaz, Nicolás; Chaparro, Diego; Reyes-Marquez, Viviana; Morales-Morales, David; Flores-Gaspar, Areli; Alí-Torres, Jorge (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is the most common form of dementia representing from 60% to 70% of the cases globally. It is a multifactorial disease that, among its many pathological characteristics, has been found to provoke the metal ion dysregulation in the brain, along with an increase in the oxidative stress. There is proof that metallic complexes formed by the amyloid-β peptide (Aβ) and extraneuronal copper can catalyze the production of reactive oxygen species, leading to an increase in oxidative stress, promoting neuronal death. Due to this interaction, bioavailable copper has become an important redox active target to consider within the search protocols of multifunctional agents for AD's treatment. OBJECTIVE: In this study, we examined by using bioinformatics and electronic structure calculations the potential application of 44 salen-type copper chelating ligands and 12 further proposed molecules as possible multifunctional agents in the context of AD. METHODS: The candidates were evaluated by combining bioinformatic tools and electronic structure calculations, which allowed us to classify the molecules as potential antioxidants, redistributor-like compounds, and the newly proposed suppressor mechanism. RESULTS: This evaluation demonstrate that salen-type ligands exhibit properties suitable for interfering in the chain of copper-induced oxidative stress reactions present in AD and potential redistributor and suppressor activity for copper ions. Finally, a novel set of plausible candidates is proposed and evaluated. CONCLUSION: According to the evaluated criteria, a subset of 13 salen-type candidates was found to exhibit promissory pharmacological properties in the AD framework and were classified according to three plausible action mechanisms.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Antioxidants; Chelating Agents; Computational Biology; Copper; Humans; Ligands; Oxidative Stress

Dementia Ideal Care: Ecosystem Map of Best Practices and Care Pathways Enhanced by Technology and Community. - Dombrowski, Wen; Mims, Adrienne; Kremer, Ian; Cano Desandes, Pedro; Rodrigo-Herrero, Silvia; Epps, Fayron; Snow, Teepa; Gutierrez, Myrna; Nasta, Anil; Epperly, Mikele Bunce; Manaloto, Katrina; Hansen, Jennie Chin (J Alzheimers Dis, 2024)
BACKGROUND: Globally, much work has been done by nonprofit, private, and academic groups to develop best practices for the care of people living with dementia (PLWD), including Alzheimer's disease. However, these best practices reside in disparate repositories and tend to focus on one phase of the patient journey or one relevant group. OBJECTIVE: To fill this gap, we developed a Dementia Ideal Care Map that everyone in the dementia ecosystem can use as an actionable tool for awareness, policy development, funding, research, training, service delivery, and technology design. The intended audience includes (and not limited to) policymakers, academia, industry, technology developers, health system leaders, clinicians, social service providers, patient advocates, PLWD, their families, and communities at large. METHODS: A search was conducted for published dementia care best practices and quality measures, which were then summarized in a visual diagram. The draft diagram was analyzed to identify barriers to ideal care. Then, additional processes, services, technologies, and quality measures to overcome those challenges were brainstormed. Feedback was then obtained from experts. RESULTS: The Dementia Ideal Care Map summarizes the ecosystem of over 200 best practices, nearly 100 technology enablers, other infrastructure, and enhanced care pathways in one comprehensive diagram. It includes psychosocial interventions, care partner support, community-based organizations; awareness, risk reduction; initial detection, diagnosis, ongoing medical care; governments, payers, health systems, businesses, data, research, and training. CONCLUSIONS: Dementia Ideal Care Map is a practical tool for planning and coordinating dementia care. This visualized ecosystem approach can be applied to other conditions.
Keywords: Delivery of Health Care; Dementia; Humans; Practice Guidelines as Topic

Exploring the Genetic Heterogeneity of Alzheimer's Disease: Evidence for Genetic Subtypes. - Elman, Jeremy A; Schork, Nicholas J; Rangan, Aaditya V (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) exhibits considerable phenotypic heterogeneity, suggesting the potential existence of subtypes. AD is under substantial genetic influence, thus identifying systematic variation in genetic risk may provide insights into disease origins. OBJECTIVE: We investigated genetic heterogeneity in AD risk through a multi-step analysis. METHODS: We performed principal component analysis (PCA) on AD-associated variants in the UK Biobank (AD cases = 2,739, controls = 5,478) to assess structured genetic heterogeneity. Subsequently, a biclustering algorithm searched for distinct disease-specific genetic signatures among subsets of cases. Replication tests were conducted using the Alzheimer's Disease Neuroimaging Initiative (ADNI) dataset (AD cases = 500, controls = 470). We categorized a separate set of ADNI individuals with mild cognitive impairment (MCI; n = 399) into genetic subtypes and examined cognitive, amyloid, and tau trajectories. RESULTS: PCA revealed three distinct clusters ("constellations") driven primarily by different correlation patterns in a region of strong LD surrounding the MAPT locus. Constellations contained a mixture of cases and controls, reflecting disease-relevant but not disease-specific structure. We found two disease-specific biclusters among AD cases. Pathway analysis linked bicluster-associated variants to neuron morphogenesis and outgrowth. Disease-relevant and disease-specific structure replicated in ADNI, and bicluster 2 exhibited increased cerebrospinal fluid p-tau and cognitive decline over time. CONCLUSIONS: This study unveils a hierarchical structure of AD genetic risk. Disease-relevant constellations may represent haplotype structure that does not increase risk directly but may alter the relative importance of other genetic risk factors. Biclusters may represent distinct AD genetic subtypes. This structure is replicable and relates to differential pathological accumulation and cognitive decline over time.

FACEmemory®, an Innovative Online Platform for Episodic Memory Pre-Screening: Findings from the First 3,000 Participants. - Alegret, Montserrat; García-Gutiérrez, Fernando; Muñoz, Nathalia; Espinosa, Ana; Ortega, Gemma; Lleonart, Núria; Rodríguez, Isabel; Rosende-Roca, Maitee; Pytel, Vanesa; Cantero-Fortiz, Yahveth; Rentz, Dorene M; Marquié, Marta; et al. (J Alzheimers Dis, 2024)
BACKGROUND: The FACEmemory® online platform comprises a complex memory test and sociodemographic, medical, and family questions. This is the first study of a completely self-administered memory test with voice recognition, pre-tested in a memory clinic, sensitive to Alzheimer's disease, using information and communication technologies, and offered freely worldwide. OBJECTIVE: To investigate the demographic and clinical variables associated with the total FACEmemory score, and to identify distinct patterns of memory performance on FACEmemory. METHODS: Data from the first 3,000 subjects who completed the FACEmemory test were analyzed. Descriptive analyses were applied to demographic, FACEmemory, and medical and family variables; t-test and chi-square analyses were used to compare participants with preserved versus impaired performance on FACEmemory (cut-off = 32); multiple linear regression was used to identify variables that modulate FACEmemory performance; and machine learning techniques were applied to identify different memory patterns. RESULTS: Participants had a mean age of 50.57 years and 13.65 years of schooling; 64.07% were women, and 82.10% reported memory complaints with worries. The group with impaired FACEmemory performance (20.40%) was older, had less schooling, and had a higher prevalence of hypertension, diabetes, dyslipidemia, and family history of neurodegenerative disease than the group with preserved performance. Age, schooling, sex, country, and completion of the medical and family history questionnaire were associated with the FACEmemory score. Finally, machine learning techniques identified four patterns of FACEmemory performance: normal, dysexecutive, storage, and completely impaired. CONCLUSIONS: FACEmemory is a promising tool for assessing memory in people with subjective memory complaints and for raising awareness about cognitive decline in the community.

First Biodistribution Study of [68Ga]Ga-NOTA-Insulin Following Intranasal Administration in Adult Vervet Monkeys. - Solingapuram Sai, Kiran Kumar; Erichsen, Jennifer M; Gollapelli, Krishna K; Krizan, Ivan; Miller, Mack; Bansode, Avinash; Jorgensen, Mathew J; Register, Thomas; Cazzola, Charles; Gandhi, Reenal; Suman, Julie; Craft, Suzanne (J Alzheimers Dis, 2024)
BACKGROUND: Intranasal insulin (INI) is being explored as a treatment for Alzheimer's disease (AD). Improved memory, functional ability, and cerebrospinal fluid (CSF) AD biomarker profiles have been observed following INI administration. However, the method of intranasal delivery may significantly affect outcomes. OBJECTIVE: To show reliable delivery of insulin to the brain using the Aptar Cartridge Pump System (CPS) intranasal delivery system. METHODS: To visualize INI biodistribution, we developed a novel PET radiotracer, Gallium 68-radiolabeled (NOTA-conjugated) insulin, [68Ga]Ga-NOTA-insulin. We used the Aptar CPS to administer [68Ga]Ga-NOTA-insulin to anesthetized healthy adult vervet monkeys and measured brain regional activity and whole-body dosimetry following PET/CT scans. RESULTS: We observed brain penetration of [68Ga]Ga-NOTA-insulin following intranasal administration with the Aptar CPS. Radioactive uptake was seen in multiple regions, including the amygdala, putamen, hypothalamus, hippocampus, and choroid plexus. A safety profile and whole-body dosimetry were also established in a second cohort of vervets. Safety was confirmed: vitals remained stable, blood glucose levels were unchanged, and no organ was exposed to more than 2.5 mSv of radioactivity. Extrapolations from vervet organ distribution allowed for estimation of the [68Ga]Ga-NOTA-insulin absorbed dose in humans, and the maximum dose of [68Ga]Ga-NOTA-insulin that can be safely administered to humans was determined to be 185 MBq. CONCLUSIONS: The use of [68Ga]Ga-NOTA-insulin as a PET radiotracer is safe and effective for observing brain uptake in vervet monkeys. Further, the Aptar CPS successfully targets [68Ga]Ga-NOTA-insulin to the brain. The data will be essential in guiding future studies of intranasal [68Ga]Ga-NOTA-insulin administration in humans.
Keywords: Administration, Intranasal; Animals; Brain; Chlorocebus aethiops; Female; Gallium Radioisotopes; Heterocyclic Compounds; Heterocyclic Compounds, 1-Ring; Insulin; Male; Positron Emission Tomography Computed Tomography; Positron-Emission Tomography; Radiopharmaceuticals; Tissue Distribution

Frontal Cortex Lipid Alterations During the Onset of Alzheimer's Disease. - Moreno-Rodriguez, Marta; Perez, Sylvia E; Martinez-Gardeazabal, Jonatan; Manuel, Iván; Malek-Ahmadi, Michael; Rodríguez-Puertas, Rafael; Mufson, Elliott J (J Alzheimers Dis, 2024)
BACKGROUND: Although sporadic Alzheimer's disease (AD) is a neurodegenerative disorder of unknown etiology, familial AD is associated with specific gene mutations. A commonality between these forms of AD is that both display multiple pathogenic events including cholinergic and lipid dysregulation. OBJECTIVE: We aimed to identify the relevant lipids and the activity of their related receptors in the frontal cortex and correlating them with cognition during the progression of AD. METHODS: MALDI-mass spectrometry imaging (MSI) and functional autoradiography was used to evaluate the distribution of phospholipids/sphingolipids and the activity of cannabinoid 1 (CB1), sphingosine 1-phosphate 1 (S1P1), and muscarinic M2/M4 receptors in the frontal cortex (FC) of people that come to autopsy with premortem clinical diagnosis of AD, mild cognitive impairment (MCI), and no cognitive impairment (NCI). RESULTS: MALDI-MSI revealed an increase in myelin-related lipids, such as diacylglycerol (DG) 36:1, DG 38:5, and phosphatidic acid (PA) 40:6 in the white matter (WM) in MCI compared to NCI, and a downregulation of WM phosphatidylinositol (PI) 38:4 and PI 38:5 levels in AD compared to NCI. Elevated levels of phosphatidylcholine (PC) 32:1, PC 34:0, and sphingomyelin 38:1 were observed in discrete lipid accumulations in the FC supragranular layers during disease progression. Muscarinic M2/M4 receptor activation in layers V-VI decreased in AD compared to MCI. CB1 receptor activity was upregulated in layers V-VI, while S1P1 was downregulated within WM in AD relative to NCI. CONCLUSIONS: FC WM lipidomic alterations are associated with myelin dyshomeostasis in prodromal AD, suggesting WM lipid maintenance as a potential therapeutic target for dementia.

The funnel effect of reserves prompted by leisure activities across the Alzheimer's disease continuum. - Serra, Laura; Bonarota, Sabrina; Di Domenico, Carlotta; Caruso, Giulia; Giulietti, Giovanni; Rizzuti, Martina; Assogna, Martina; Rodini, Marta; Mencarelli, Lucia; Di Lorenzo, Francesco; Koch, Giacomo; Fadda, Lucia; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Reserves' mechanisms explain inconsistencies between accumulation of neuropathological damage and clinical manifestations. Leisure activities are believed to promote reserves. OBJECTIVE: This study evaluates whether cognitive, social, and physical leisure activities performed over life-span predict current cognitive functioning in normal aging and Alzheimer's disease (AD) continuum. METHODS: 35 AD, 24 amnestic-Mild Cognitive Impairment (a-MCI) patients, 21 individuals with subjective cognitive complaint (SCD), and 25 controls underwent a questionnaire developed to quantify leisure activities in different life periods, the Addenbrooke's Cognitive Examination-Revised (ACE-R), and T1-weighted 3T-MRI scans for brain volumetrics and cortical thickness quantification. Partial/total leisure activities' scores and demographic and brain variables were entered as predictors, while ACE-R scores as dependent variables in linear regression analyses. RESULTS: Current level of cognition was predicted by (i) social and physical activities performed in middle age and current cognitive activity in AD; (ii) cognitive and social activities performed in middle age, current age and cortical thickness in a-MCI; (iii) recreational activities the set of lifetime, current age, and brain features in SCD; (iv) education and the set of lifetime leisure activities over lifespan in controls. CONCLUSIONS: This study shows a funnel effect due to gradual reduction of stimulatory activities in the transition from healthy aging to AD. Reserve indices taking into account different types of stimulatory activities allow to capture even smallest residual effects of reserves accumulated over lifespan, until their complete depletion at advanced AD stages. These results may help target tailored interventions during normal and pathological aging.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Brain; Cognition; Cognitive Dysfunction; Cognitive Reserve; Female; Humans; Leisure Activities; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Surveys and Questionnaires

Impaired Skeletal Development by Disruption of Presenilin-1 in Pigs and Generation of Novel Pig Models for Alzheimer's Disease. - Uh, Kyungjun; Monarch, Kaylynn; Reese, Emily D; Rodriguez, Katherine; Yoon, Junchul; Spate, Lee D; Samuel, Melissa S; Koh, Sehwon; Chen, Paula R; Jarome, Timothy J; Allen, Timothy A; Prather, Randall S; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Presenilin 1 (PSEN1) is one of the genes linked to the prevalence of early onset Alzheimer's disease. In mice, inactivation of Psen1 leads to developmental defects, including vertebral malformation and neural development. However, little is known about the role of PSEN1 during the development in other species. OBJECTIVE: To investigate the role of PSEN1 in vertebral development and the pathogenic mechanism of neurodegeneration using a pig model. METHODS: CRISPR/Cas9 system was used to generate pigs with different mutations flanking exon 9 of PSEN1, including those with a deleted exon 9 (Δexon9). Vertebral malformations in PSEN1 mutant pigs were examined by X-ray, micro-CT and micro-MRI. Neuronal cells from the brains of PSEN1 mutant pigs were analyzed by immunoflourescence, followed by image analysis including morphometric evaluation via image J and 3D reconstruction. RESULTS: Pigs with a PSEN1 null mutation (Δexon9-12) died shortly after birth and had significant axial skeletal defects, whereas pigs carrying at least one Δexon9 allele developed normally and remained healthy. Effects of the null mutation on abnormal skeletal development were also observed in fetuses at day 40 of gestation. Abnormal distribution of astrocytes and microglia in the brain was detected in two PSEN1 mutant pigs examined compared to age-matched control pigs. The founder pigs were bred to establish and age PSEN1ΔE9/+ pigs to study their relevance to clinical Alzheimer's diseases. CONCLUSIONS: PSEN1 has a critical role for normal vertebral development and PSEN1 mutant pigs serves as novel resources to study Alzheimer's disease.

Improving Healthcare Quality and Clinical Outcomes for Persons with Dementia in the Sub-Acute Hospital Through Person-Centered Care Practice. - Chenoweth, Lynn; Burley, Claire; Cook, Jacquelene; Cheah, Seong-Leang; Reyes, Patricia; Maiden, Genevieve; McGuire, Jane; McCade, Donna; Brodaty, Henry; Sukhapure, Mayouri; Harrison, Fleur; Williams, Anna (J Alzheimers Dis, 2024)
BACKGROUND: Person-centered care is considered beneficial for persons with dementia. OBJECTIVE: To evaluate the impact of a person-centered knowledge translation intervention on the quality of healthcare and outcomes for persons with dementia. METHODS: Over nine months, sub-acute hospital nursing, allied health, and medical staff (n = 90) participated in online and/or face-to-face person-centered education and were supported by senior nursing, allied health, and medical staff champions (n = 8) to implement person-centered healthcare. The quality of healthcare service, ward climate and care delivery were evaluated pre/post study intervention. In the week following hospital admission (Time 1) and week of discharge (Time 3), agitation incidence (co-primary outcome) was assessed in participants with dementia (n = 80). Participant delirium (co-primary outcome), accidents/injuries, psychotropic medicines, length of stay, readmission and discharge destination (secondary outcomes) were compared with a retrospective group (n = 77) matched on demographics, cognition and function in activities of daily living. RESULTS: Improvements occurred post-intervention in service quality by 17.5% (p = 0.369, phi = 0.08), ward climate by 18.1% (p = 0.291, phi = 0.08), and care quality by 50% (p = 0.000, phi = 0.37). Participant agitation did not change from Time 1 to Time 3 (p = 0.223). Relative to the retrospective group, significant reductions occurred in participant delirium (p = 0.000, phi = 0.73), incidents/injuries (p = 0.000, phi = 0.99), psychotropic medicine use (p = 0.030, phi = 0.09), and hospital readmissions within 30 days (p = 0.002, phi = 0.25), but not in discharge to home (p = 0.171). CONCLUSIONS: When person-centered healthcare knowledge is translated through staff education and practice support, persons with dementia can experience improved healthcare services and clinical outcomes, while healthcare services can benefit through reductions in unplanned service use.

The Inflammation-Induced Dysregulation of Reelin Homeostasis Hypothesis of Alzheimer's Disease. - Reive, Brady S; Lau, Victor; Sánchez-Lafuente, Carla L; Henri-Bhargava, Alexandre; Kalynchuk, Lisa E; Tremblay, Marie-Ève; Caruncho, Hector J (J Alzheimers Dis, 2024)
Alzheimer's disease (AD) accounts for most dementia cases, but we lack a complete understanding of the mechanisms responsible for the core pathology associated with the disease (e.g., amyloid plaque and neurofibrillary tangles). Inflammation has been identified as a key contributor of AD pathology, with recent evidence pointing towards Reelin dysregulation as being associated with inflammation. Here we describe Reelin signaling and outline existing research involving Reelin signaling in AD and inflammation. Research is described pertaining to the inflammatory and immunological functions of Reelin before we propose a mechanism through which inflammation renders Reelin susceptible to dysregulation resulting in the induction and exacerbation of AD pathology. Based on this hypothesis, it is predicted that disorders of both inflammation (including peripheral inflammation and neuroinflammation) and Reelin dysregulation (including disorders associated with upregulated Reelin expression and disorders of Reelin downregulation) have elevated risk of developing AD. We conclude with a description of AD risk in various disorders involving Reelin dysregulation and inflammation.
Keywords: Alzheimer Disease; Animals; Cell Adhesion Molecules, Neuronal; Extracellular Matrix Proteins; Homeostasis; Humans; Inflammation; Nerve Tissue Proteins; Reelin Protein; Serine Endopeptidases; Signal Transduction

An Insertion Within SIRPβ1 Shows a Dual Effect Over Alzheimer's Disease Cognitive Decline Altering the Microglial Response. - García-Alberca, José María; de Rojas, Itziar; Sanchez-Mejias, Elisabeth; Garrido-Martín, Diego; Gonzalez-Palma, Laura; Jimenez, Sebastian; Pino-Angeles, Almudena; Cruz-Gamero, Jose Manuel; Mendoza, Silvia; Alarcón-Martín, Emilio; Muñoz-Castro, Clara; Real, Luis Miguel; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Microglial dysfunction plays a causative role in Alzheimer's disease (AD) pathogenesis. Here we focus on a germline insertion/deletion variant mapping SIRPβ1, a surface receptor that triggers amyloid-β(Aβ) phagocytosis via TYROBP. OBJECTIVE: To analyze the impact of this copy-number variant in SIRPβ1 expression and how it affects AD molecular etiology. METHODS: Copy-number variant proxy rs2209313 was evaluated in GERALD and GR@ACE longitudinal series. Hippocampal specimens of genotyped AD patients were also examined. SIRPβ1 isoform-specific phagocytosis assays were performed in HEK393T cells. RESULTS: The insertion alters the SIRPβ1 protein isoform landscape compromising its ability to bind oligomeric Aβ and its affinity for TYROBP. SIRPβ1 Dup/Dup patients with mild cognitive impairment show an increased cerebrospinal fluid t-Tau/Aβ ratio (p = 0.018) and a higher risk to develop AD (OR = 1.678, p = 0.018). MRIs showed that Dup/Dup patients exhibited a worse initial response to AD. At the moment of diagnosis, all patients showed equivalent Mini-Mental State Examination scores. However, AD patients with the duplication had less hippocampal degeneration (p < 0.001) and fewer white matter hyperintensities. In contrast, longitudinal studies indicate that patients bearing the duplication allele show a slower cognitive decline (p = 0.013). Transcriptional analysis also shows that the SIRPβ1 duplication allele correlates with higher TREM2 expression and an increased microglial activation. CONCLUSIONS: The SIRPβ1 internal duplication has opposite effects over MCI-to-Dementia conversion risk and AD progression, affecting microglial response to Aβ. Given the pharmacological approaches focused on the TREM2-TYROBP axis, we believe that SIRPβ1 structural variant might be considered as a potential modulator of this causative pathway.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Humans; Microglia; Phagocytosis; Receptors, Cell Surface

Long Non-Coding RNA Profile in Genetic Symptomatic and Presymptomatic Frontotemporal Dementia: A GENFI Study. - Serpente, Maria; Fenoglio, Chiara; Arcaro, Marina; Carandini, Tiziana; Sacchi, Luca; Pintus, Manuela; Rotondo, Emanuela; Borracci, Vittoria; Ghezzi, Laura; Bouzigues, Arabella; Russell, Lucy L; Foster, Phoebe H; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Long non-coding RNAs (lncRNAs) play crucial roles in gene regulation and are implicated in neurodegenerative diseases, including frontotemporal dementia (FTD). However, their expression patterns and potential as biomarkers in genetic FTD involving Chromosome 9 Open Reading Frame (C9ORF72), Microtubule Associated Protein Tau (MAPT), and Progranulin (GRN) genes are not well understood. OBJECTIVE: This study aimed to profile the expression levels of lncRNAs in peripheral blood mononuclear cells collected within the GENetic Frontotemporal dementia Initiative (GENFI). METHODS: Fifty-three lncRNAs were analyzed with the OpenArray Custom panel, in 131 patients with mutations in C9ORF72, MAPT, and GRN, including 68 symptomatic mutation carriers (SMC) and 63 presymptomatic mutation carriers (PMC), compared with 40 non-carrier controls (NC). RESULTS: Thirty-eight lncRNAs were detectable; the relative expression of NEAT1 and NORAD was significantly higher in C9ORF72 SMC as compared with NC. GAS5 expression was instead significantly lower in the GRN group versus NC. MAPT carriers showed no significant deregulations. No significant differences were observed in PMC. Disease duration did not correlate with lncRNA expression. CONCLUSIONS: NEAT1 and NORAD are upregulated in C9ORF72 SMC and GAS5 levels are downregulated in GRN SMC, underlining lncRNAs' relevance in FTD and their potential for biomarker development. Further validation and mechanistic studies are crucial for clinical implications.

Lucidity in the Deeply Forgetful: A Scoping Review. - Ross, John Paul; Post, Stephen G; Scheinfeld, Laurel (J Alzheimers Dis, 2024)
BACKGROUND: Even in severe states of Alzheimer's disease and related dementias (ADRD), accounts of an unexpected or paradoxical return of awareness and lucidity have been reported in some patients, documented formally, and studied. OBJECTIVE: A scoping review was undertaken to survey the literature on the topic. METHODS: Five databases were searched using pertinent search terms. Results were deduplicated and subsequently screened by title and abstract for relevance. Remaining reports were read and included or excluded using specific inclusion criteria. 30 results consisted of a mix of perspective papers, case reports, qualitative surveys of caregivers, law journal comments, and mechanistic speculation. RESULTS: An equal mix of primary and secondary research was identified. CONCLUSIONS: The papers collected in this review provide a valuable methodological outline for researching the topic of lucid episodes in ADRD. The verified legitimacy and simultaneous inexplicability of these events promote philosophical discussion, mechanistic investigations, and sorely needed research in the field of ADRD.
Keywords: Alzheimer Disease; Caregivers; Cognition; Humans

Memory consolidation, temporal and parietal atrophy, and metabolism in amyloid-β positive and negative mild cognitive impairment. - Keith, Cierra M; Haut, Marc W; Vieira Ligo Teixeira, Camila; Mehta, Rashi I; Phelps, Holly; Ward, Melanie; Miller, Mark; Navia, R Osvaldo; Coleman, Michelle M; Marano, Gary; Wang, Xiaofei; Pockl, Stephanie; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is classically characterized by alterations in memory consolidation. With the advent of diagnostic biomarkers, some patients clinically diagnosed with AD display biomarkers inconsistent with the diagnosis. OBJECTIVE: We aimed to explore differences in memory consolidation and neurodegeneration of the temporal and parietal lobes as a function of amyloid-β status in amnestic mild cognitive impairment (aMCI). METHODS: We examined differences in memory consolidation and neurodegeneration between patients diagnosed with amyloid-β positive aMCI (Aβ+ N = 78), amyloid-β negative aMCI (Aβ- N = 48), and healthy participants (HP; N = 41), within a well-characterized clinical cohort. RESULTS: Aβ+ exhibited more pronounced consolidation impairments compared to Aβ-, while Aβ- faced more consolidation challenges than HP. Both Aβ+ and Aβ- were similar in hippocampal volume and entorhinal thickness, but Aβ+ had thinner inferior parietal cortex than Aβ-. Using F-fluoro-deoxyglucose-positron emission tomography, metabolism in both temporal and parietal regions was lower in Aβ+ relative to Aβ-. CONCLUSIONS: These findings suggest pathologies other than AD likely contribute to memory consolidation difficulties in aMCI, and neurodegeneration of the parietal cortex in combination with hypometabolism may contribute to more pronounced consolidation problems in Aβ+.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Atrophy; Cognitive Dysfunction; Female; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Memory Consolidation; Middle Aged; Neuropsychological Tests; Parietal Lobe; Positron-Emission Tomography; Temporal Lobe

Mendelian Randomization of Blood Metabolites Suggests Circulating Glutamine Protects Against Late-Onset Alzheimer's Disease. - Ramadan, Ferris A; Arani, Gayatri; Jafri, Ayan; Thompson, Tingting; Bland, Victoria L; Renquist, Benjamin; Raichlen, David A; Alexander, Gene E; Klimentidis, Yann C (J Alzheimers Dis, 2024)
BACKGROUND: Late-onset Alzheimer's disease (LOAD) represents a growing health burden. Previous studies suggest that blood metabolite levels influence risk of LOAD. OBJECTIVE: We used a genetics-based study design which may overcome limitations of other epidemiological studies to assess the influence of metabolite levels on LOAD risk. METHODS: We applied Mendelian randomization (MR) to evaluate bi-directional causal effects using summary statistics from the largest genome-wide association studies (GWAS) of 249 blood metabolites (n = 115,082) and GWAS of LOAD (ncase = 21,982, ncontrol = 41,944). RESULTS: MR analysis of metabolites as exposures revealed a negative association of genetically-predicted glutamine levels with LOAD (Odds Ratio (OR) = 0.83, 95% CI = 0.73, 0.92) that was consistent in multiple sensitivity analyses. We also identified a positive association of genetically-predicted free cholesterol levels in small LDL (OR = 1.79, 95% CI = 1.36, 2.22) on LOAD. Using genetically-predicted LOAD as the exposure, we identified associations with phospholipids to total lipids ratio in large LDL (OR = 0.96, 95% CI = 0.94, 0.98), but not with glutamine, suggesting that the relationship between glutamine and LOAD is unidirectional. CONCLUSIONS: Our findings support previous evidence that higher circulating levels of glutamine may be a target for protection against LOAD.

Music Therapy as a Complementary Treatment in Patients with Dementia Associated to Alzheimer's Disease: A Systematic Review. - Rossi, Eleonora; Marrosu, Francesco; Saba, Luca (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is a complex condition that affects various aspects of a patient's life. Music therapy may be considered a beneficial supplementary tool to traditional therapies, that not fully address the range of AD manifestations. OBJECTIVE: The purpose of this systematic review is to investigate whether music therapy can have a positive impact on AD patients and on which symptoms. METHODS: The main research databases employed have been PubMed and Cochrane, using the keywords "dementia", "music therapy", "Alzheimer", "fMRI", "music", and "EEG". RESULTS: After removing duplicates and irrelevant studies, 23 were screened using set criteria, resulting in the final inclusion of 15 studies. The total number of participants included in these studies has been of 1,196 patients. For the fMRI analysis the search resulted in 28 studies on PubMed, two of which were included in the research; the total number of participants was of 124 individuals. The studies conducted with EEG were found using PubMed. The initial search resulted in 15 studies, but after a more accurate evaluation only 2 have been included in the analysis. CONCLUSIONS: Even though the data currently available is not sufficient to draw conclusions supported by robust statistical power, the impact of music therapy on AD neuropsychiatric symptoms deserves great interest. Further research should be ushered, possibly multicentric studies, led with neuroimaging and other recent techniques, which can eventually open views on the music role in improving the cognitive status in AD.
Keywords: Alzheimer Disease; Humans; Music Therapy

Optimizing the Implementation of a Lifestyle Dementia Prevention Intervention for Older Patients in an Academic Healthcare System. - Mace, Ryan A; Lyons, Christopher; Cohen, Joshua E; Ritchie, Christine; Bartels, Stephen; Okereke, Olivia I; Hoeppner, Bettina B; Brewer, Judson A; Vranceanu, Ana-Maria (J Alzheimers Dis, 2024)
BACKGROUND: Interventions that promote healthy lifestyles are critical for the prevention of Alzheimer's disease and Alzheimer's disease related dementias (AD/ADRD). However, knowledge of the best practices for implementing AD/ADRD prevention in healthcare settings remains limited. OBJECTIVE: We aimed to qualitatively identify barriers and facilitators to implementing a clinical trial of a novel lifestyle intervention (My Healthy Brain) in our medical center for older patients with subjective cognitive decline who are at-risk for AD/ADRD. METHODS: We conducted focus groups with 26 healthcare professionals (e.g., physicians, psychology, nursing) from 5 clinics that treat older patients (e.g., memory care, psychiatry). Our qualitative analysis integrated two implementation frameworks to systematically capture barriers and facilitators to AD/ADRD prevention (Consolidated Framework for Implementation Science Research) that impact implementation outcomes of acceptability, appropriateness, and feasibility (Proctor's framework). RESULTS: We found widespread support for an RCT of My Healthy Brain and AD/ADRD prevention. Participants identified barriers related to patients (stigma, technological skills), providers (dismissiveness of "worried well," doubting capacity for behavior change), clinics (limited time and resources), and the larger healthcare system (underemphasis on prevention). Implementation strategies guided by Expert Recommendations for Implementing Change (ERIC) included: developing tailored materials, training staff, obtaining buy-in from leadership, addressing stigmatized language and practices, identifying "champions," and integrating with workflows and resources. CONCLUSIONS: The results will inform our recruitment, enrollment, and retention procedures to implement the first randomized clinical trial of My Healthy Brain. Our study provides a blueprint for addressing multi-level barriers to the implementation of AD/ADRD prevention for older patients in medical settings.
Keywords: Academic Medical Centers; Aged; Alzheimer Disease; Cognitive Dysfunction; Dementia; Female; Focus Groups; Health Personnel; Humans; Life Style; Male

Pharmacologic and Nutritional Interventions for Early Alzheimer's Disease: A Systematic Review and Network Meta-Analysis of Randomized Controlled Trials. - Zeng, Baoqi; Tang, Chunbian; Wang, Junjian; Yang, Qingqing; Ren, Qingcuo; Liu, Xiaozhi (J Alzheimers Dis, 2024)
BACKGROUND: Early intervention is essential for meaningful disease modification in Alzheimer's disease (AD). OBJECTIVE: We aimed to determine the efficacy and safety of pharmacologic and nutritional interventions for early AD. METHODS: PubMed, Embase, the Cochrane Library, and ClinicalTrials.gov were searched from database inception until 1 September 2023. We included randomized controlled trials that evaluated the efficacy of interventions in early AD. Only interventions that demonstrated efficacy compared to placebo were included in the network meta-analysis (NMA). Then we performed frequentist fixed-effects NMA to rank the interventions. GRADE criteria were used to evaluate the level of evidence. RESULTS: Fifty-eight trials including a total of 33,864 participants and 48 interventions were eligible for inclusion. Among the 48 interventions analyzed, only 6 (12.5%) treatments- ranging from low to high certainty- showed significant improvement in cognitive decline compared to placebo. High certainty evidence indicated that donanemab (standardized mean difference [SMD] -0.239, 95% confidence interval [CI] -0.343 to -0.134) and lecanemab (SMD -0.194, 95% CI -0.279 to -0.108) moderately slowed the clinical progression in patients with amyloid pathology. Additionally, methylphenidate, donepezil, LipiDiDiet, and aducanumab with low certainty showed significant improvement in cognitive decline compared to placebo. However, there was no significant difference in serious adverse events as reported between the six interventions and placebo. CONCLUSIONS: Only 12.5% of interventions studied demonstrated efficacy in reducing cognitive impairment in early AD. Donanemab and lecanemab have the potential to moderately slow the clinical progression in patients with amyloid pathology. Further evidence is required for early intervention in AD.
Keywords: Alzheimer Disease; Humans; Network Meta-Analysis; Randomized Controlled Trials as Topic

Research Participants' Perspectives on Precision Diagnostics for Alzheimer's Disease. - Smith, Hadley Stevens; Robinson, Jill O; Levchenko, Ariel; Pereira, Stacey; Pascual, Belen; Bradbury, Kathleen; Arbones, Victoria; Fong, Jamie; Shulman, Joshua M; McGuire, Amy L; Masdeu, Joseph (J Alzheimers Dis, 2024)
BACKGROUND: Understanding research participants' responses to learning Alzheimer's disease (AD) risk information is important to inform clinical implementation of precision diagnostics given rapid advances in disease modifying therapies. OBJECTIVE: We assessed participants' perspectives on the meaning of their amyloid positron emission tomography (PET) imaging results for their health, self-efficacy to understand their results, psychological impact of learning their results, experience receiving their results from the clinical team, and interest in genetic testing for AD risk. METHODS: We surveyed individuals who were being clinically evaluated for AD and received PET imaging six weeks after the return of results. We analyzed responses to close-ended survey items by PET result using Fisher's exact test and qualitatively coded open-ended responses. RESULTS: A total of 88 participants completed surveys, most of whom had mild cognitive impairment due to AD (38.6%), AD (28.4%), or were cognitively unimpaired (21.6%). Participants subjectively understood their results (25.3% strongly agreed, 41.8% agreed), which could help them plan (16.5% strongly agreed, 49.4% agreed). Participants with a negative PET result (n = 25) reported feelings of relief (Fisher's exact p < 0.001) and happiness (p < 0.001) more frequently than those with a positive result. Most participants felt that they were treated respectfully and were comfortable voicing concerns during the disclosure process. Genetic testing was anticipated to be useful for medical care decisions (48.2%) and to inform family members about AD risk (42.9%). CONCLUSIONS: Participants had high subjective understanding and self-efficacy around their PET results and did not experience negative psychological effects. Interest in genetic testing was high.
Keywords: Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Cognitive Dysfunction; Emotions; Humans; Positron-Emission Tomography

A Scoping Review of Alzheimers Disease Hypotheses: An Array of Uni- and Multi-Factorial Theories. - Duchesne, Simon; Rousseau, Louis-Simon; Belzile-Marsolais, Florence; Welch, Laurie-Ann; Cournoyer, Béatrice; Arseneau, Marianne; Lapierre, Véronick; Poulin, Sara-Maude; Potvin, Olivier; Hudon, Carol (J Alzheimers Dis, 2024)
BACKGROUND: There is a common agreement that Alzheimers disease (AD) is inherently complex; otherwise, a general disagreement remains on its etiological underpinning, with numerous alternative hypotheses having been proposed. OBJECTIVE: To perform a scoping review of original manuscripts describing hypotheses and theories of AD published in the past decades. RESULTS: We reviewed 131 original manuscripts that fulfilled our inclusion criteria out of more than 13,807 references extracted from open databases. Each entry was characterized as having a single or multifactorial focus and assigned to one of 15 theoretical groupings. Impact was tracked using open citation tools. RESULTS: Three stages can be discerned in terms of hypotheses generation, with three quarter of studies proposing a hypothesis characterized as being single-focus. The most important theoretical groupings were the Amyloid group, followed by Metabolism and Mitochondrial dysfunction, then Infections and Cerebrovascular. Lately, evidence towards Genetics and especially Gut/Brain interactions came to the fore. CONCLUSIONS: When viewed together, these multi-faceted reports reinforce the notion that AD affects multiple sub-cellular, cellular, anatomical, and physiological systems at the same time but at varying degree between individuals. The challenge of providing a comprehensive view of all systems and their interactions remains, alongside ways to manage this inherent complexity.
Keywords: Alzheimer Disease; Brain; Humans

Small RNA Profiles of Brain Tissue-Derived Extracellular Vesicles in Alzheimer's Disease. - Huang, Yiyao; Driedonks, Tom A P; Cheng, Lesley; Turchinovich, Andrey; Pletniková, Olga; Redding-Ochoa, Javier; Troncoso, Juan C; Hill, Andrew F; Mahairaki, Vasiliki; Zheng, Lei; Witwer, Kenneth W (J Alzheimers Dis, 2024)
BACKGROUND: Extracellular vesicles (EVs) and non-coding RNAs (ncRNAs) are emerging contributors to Alzheimer's disease (AD) pathophysiology. Differential abundance of ncRNAs carried by EVs may provide valuable insights into underlying disease mechanisms. Brain tissue-derived EVs (bdEVs) are particularly relevant, as they may offer valuable insights about the tissue of origin. However, there is limited research on diverse ncRNA species in bdEVs in AD. OBJECTIVE: This study explored whether the non-coding RNA composition of EVs isolated from post-mortem brain tissue is related to AD pathogenesis. METHODS: bdEVs from age-matched late-stage AD patients (n = 23) and controls (n = 10) that had been separated and characterized in our previous study were used for RNA extraction, small RNA sequencing, and qPCR verification. RESULTS: Significant differences of non-coding RNAs between AD and controls were found, especially for miRNAs and tRNAs. AD pathology-related miRNA and tRNA differences of bdEVs partially matched expression differences in source brain tissues. AD pathology had a more prominent association than biological sex with bdEV miRNA and tRNA components in late-stage AD brains. CONCLUSIONS: Our study provides further evidence that EV non-coding RNAs from human brain tissue, including but not limited to miRNAs, may be altered and contribute to AD pathogenesis.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Extracellular Vesicles; Female; Humans; Male; MicroRNAs; RNA, Small Untranslated; RNA, Transfer; RNA, Untranslated

Symptomatic Clusters Related to Amyloid Positivity in Cognitively Unimpaired Individuals. - Sannemann, Lena; Bartels, Claudia; Brosseron, Frederic; Buerger, Katharina; Fliessbach, Klaus; Freiesleben, Silka Dawn; Frommann, Ingo; Glanz, Wenzel; Heneka, Michael T; Janowitz, Daniel; Kilimann, Ingo; Kleineidam, Luca; et al. (J Alzheimers Dis, 2024)
BACKGROUND: The NIA-AA Research Framework on Alzheimer's disease (AD) proposes a transitional stage (stage 2) characterized by subtle cognitive decline, subjective cognitive decline (SCD) and mild neurobehavioral symptoms (NPS). OBJECTIVE: To identify participant clusters based on stage 2 features and assess their association with amyloid positivity in cognitively unimpaired individuals. METHODS: We included baseline data of N = 338 cognitively unimpaired participants from the DELCODE cohort with data on cerebrospinal fluid biomarkers for AD. Classification into the AD continuum (i.e., amyloid positivity, A+) was based on Aβ42/40 status. Neuropsychological test data were used to assess subtle objective cognitive dysfunction (OBJ), the subjective cognitive decline interview (SCD-I) was used to detect SCD, and the Neuropsychiatric Inventory Questionnaire (NPI-Q) was used to assess NPS. A two-step cluster analysis was carried out and differences in AD biomarkers between clusters were analyzed. RESULTS: We identified three distinct participant clusters based on presented symptoms. The highest rate of A+ participants (47.6% ) was found in a cluster characterized by both OBJ and SCD. A cluster of participants that presented with SCD and NPS (A+:26.6% ) and a cluster of participants with overall few symptoms (A+:19.7% ) showed amyloid positivity in a range that was not higher than the expected A+ rate for the age group. Across the full sample, participants with a combination of SCD and OBJ in the memory domain showed a lower Aβ42/ptau181 ratio compared to those with neither SCD nor OBJ. CONCLUSIONS: The cluster characterized by participants with OBJ and concomitant SCD was enriched for amyloid pathology.

Targeting Caspases 3/6 and Cathepsins L/B May Decrease Laminopathy-Induced Apoptosis in Alzheimer's Disease. - Rustamzadeh, Auob; Tafakhori, Abbas; Ariaei, Armin; Heydari, Mahdi; Shah-Abadi, Mehran Ebrahimi; Seif, Farhad (J Alzheimers Dis, 2024)
BACKGROUND: Laminopathy is a pathological manifestation observed in Alzheimer's disease (AD), leading to neuronal apoptosis. OBJECTIVE: Our objective was to assess inhibitors of enzymes involved in laminopathy. METHODS: The mRNA expression of the cathepsins L and B, caspases 3 and 6, lamins b1 and b2, granzymes A and B, and lamins A and C were extracted and analyzed from GSE5281 and GSE28146 datasets. A total of 145 ligands were selected for molecular docking. Subsequently, 10 ns and 100 ns atomistic molecular dynamics (MD) and Martini 3 were performed with NAMD for two selected ligands (PubChem id: 608841 and ChEMBL id: 550872). RESULTS: The mRNA expression level highlighted caspase 6 and lamin A/C upregulation in the hippocampus of the AD samples, in contrast to cathepsin B, lamin b2, and caspase 3. Moreover, there was a strong correlation between the expression level of cathepsin B, lamin A/C, and caspase 6 in the AD group. The MD results suggested molecule with ChEMBL id of 550872 had higher free binding energy, while in longer simulation the molecule with PubChem id of 608841 was suggested to be more stable in complex with the receptor. CONCLUSIONS: Our findings suggest that lamins A/C, cathepsins B/L, caspase 6, and lamin B2 are associated with laminopathy as potential factors contributing to apoptosis in AD. We propose that simultaneous inhibition of caspases 6 and cathepsins L may decrease the rate of apoptosis triggered by lamin degradation. Nevertheless, further studies are required to confirm these observations due to the lack of in vivo findings.
Keywords: Alzheimer Disease; Apoptosis; Caspase 3; Caspase 6; Cathepsin B; Cathepsin L; Hippocampus; Humans; Lamin Type A; Laminopathies; Male; Molecular Docking Simulation

Accumulation of pTau231 at the Postsynaptic Density in Early Alzheimer's Disease. - Lilek, Jaclyn; Ajroud, Kaouther; Feldman, Alexander Z; Krishnamachari, Sesha; Ghourchian, Shadi; Gefen, Tamar; Spencer, Callen L; Kawles, Allegra; Mao, Qinwen; Tranovich, Jessica F; Jack, Clifford R; Mesulam, M-Marsel; et al. (J Alzheimers Dis, 2023)

The Anti-Amyloid Monoclonal Antibody Lecanemab: 16 Cautionary Notes. - Kepp, Kasper P; Sensi, Stefano L; Johnsen, Kasper B; Barrio, Jorge R; Høilund-Carlsen, Poul F; Neve, Rachael L; Alavi, Abass; Herrup, Karl; Perry, George; Robakis, Nikolaos K; Vissel, Bryce; Espay, Alberto J (J Alzheimers Dis, 2023)
After the CLARITY-AD clinical trial results of lecanemab were interpreted as positive, and supporting the amyloid hypothesis, the drug received accelerated Food and Drug Administration approval. However, we argue that benefits of lecanemab treatment are uncertain and may yield net harm for some patients, and that the data do not support the amyloid hypothesis. We note potential biases from inclusion, unblinding, dropouts, and other issues. Given substantial adverse effects and subgroup heterogeneity, we conclude that lecanemab's efficacy is not clinically meaningful, consistent with numerous analyses suggesting that amyloid-β and its derivatives are not the main causative agents of Alzheimer's disease dementia.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloidogenic Proteins; Antibodies, Monoclonal; Humans; United States

Association of Sarcopenia and Its Defining Components with the Degree of Cognitive Impairment in a Memory Clinic Population. - Larsson, LE; Wang, Rui; Cederholm, Tommy; Wiggenraad, Fleur; Rydén, Marie; Hagman, Göran; Hellénius, Mai-Lis; Kivipelto, Miia; Thunborg, Charlotta (J Alzheimers Dis, 2023)
BACKGROUND: Sarcopenia and cognitive impairment are two leading causes of disabilities. OBJECTIVE: The objective was to examine the prevalence of sarcopenia and investigate the association between sarcopenia diagnostic components (muscle strength, muscle mass, and physical performance) and cognitive impairment in memory clinic patients. METHODS: 368 patients were included (age 59.0±7.25 years, women: 58.7%), displaying three clinical phenotypes of cognitive impairments, i.e., subjective cognitive impairment (SCI, 57%), mild cognitive impairment (MCI, 26%), and Alzheimer's disease (AD, 17%). Sarcopenia was defined according to diagnostic algorithm recommended by the European Working Group on Sarcopenia in Older People. Components of sarcopenia were grip strength, bioelectrical impedance analysis, and gait speed. They were further aggregated into a score (0-3 points) by counting the numbers of limited components. Multi-nominal logistic regression was applied. RESULTS: Probable sarcopenia (i.e., reduced grip strength) was observed in 9.6% of the patients, and 3.5% were diagnosed with sarcopenia. Patients with faster gait speed showed less likelihood of MCI (odds ratio [OR]: 0.24, 95% confidence interval [CI]: 0.06-0.90) and AD (OR: 0.12, 95% CI: 0.03-0.60). One or more limited sarcopenia components was associated with worse cognitive function. After adjusting for potential confounders, the association remained significant only for AD (OR 4.29, 95% CI 1.45-11.92). CONCLUSION: The results indicate a connection between the sarcopenia components and cognitive impairments. Limitations in the sarcopenia measures, especially slow walking speed, were related to poorer cognitive outcomes. More investigationsare required to further verify the causal relationship between sarcopenia and cognitive outcomes.

Associations Between Local Area Deprivation and Physical Activity Participation in People with Cognitive Impairment in the North East of England. - Mc Ardle, Ríona; Hamilton, Calum; Del Din, Silvia; Kingston, Andrew; Robinson, Louise; Galna, Brook; Thomas, Alan J; Rochester, Lynn (J Alzheimers Dis, 2023)
BACKGROUND: Promoting physical activity, such as habitual walking behaviors, in people with cognitive impairment may support their ability to remain independent with a good quality of life for longer. However, people with cognitive impairment participate in less physical activity compared to cognitively unimpaired older adults. The local area in which people live may significantly impact abilities to participate in physical activity. For example, people who live in more deprived areas may have less safe and walkable routes. OBJECTIVE: To examine this further, this study aimed to explore associations between local area deprivation and physical activity in people with cognitive impairment and cognitively unimpaired older adults (controls). METHODS: 87 participants with cognitive impairment (mild cognitive impairment or dementia) and 27 older adult controls from the North East of England were included in this analysis. Participants wore a tri-axial wearable accelerometer (AX3, Axivity) on their lower backs continuously for seven days. The primary physical activity outcome was daily step count. Individuals' neighborhoods were linked to UK government area deprivation statistics. Hierarchical Bayesian models assessed the association between local area deprivation and daily step count in people with cognitive impairment and controls. RESULTS: Key findings indicated that there was no association between local area deprivation and daily step count in people with cognitive impairment, but higher deprivation was associated with lower daily steps for controls. CONCLUSION: These findings suggest that cognitive impairment may be associated with lower participation in physical activity which supersedes the influence of local area deprivation observed in normal aging.

Associations of the Harvard Automated Phone Task and Alzheimer's Disease Pathology in Cognitively Normal Older Adults: Preliminary Findings. - Gonzalez, Christopher; Mimmack, Kayden J; Amariglio, Rebecca E; Becker, J Alex; Chhatwal, Jasmeer P; Fitzpatrick, Colleen D; Gatchel, Jennifer R; Johnson, Keith A; Katz, Zoe S; Kuppe, Madeline K; Locascio, Joseph J; Udeogu, Onyinye J; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Detecting clinically meaningful changes in instrumental activities of daily living (IADL) at the earliest stages of Alzheimer's disease (AD) is critical. OBJECTIVE: The objective of this exploratory study was to examine the cross-sectional relationship between a performance-based IADL test, the Harvard Automated Phone Task (APT), and cerebral tau and amyloid burden in cognitively normal (CN) older adults. METHODS: Seventy-seven CN participants underwent flortaucipir tau and Pittsburgh Compound B amyloid PET. IADL were assessed using the three Harvard APT tasks: prescription refill (APT-Script), health insurance company call (APT-PCP), and bank transaction (APT-Bank). Linear regression models were used to determine associations between each APT task and entorhinal cortex, inferior temporal, or precuneus tau with or without an interaction with amyloid. RESULTS: Significant associations were found between APT-Bank task rate and interaction between amyloid and entorhinal cortex tau, and APT-PCP task and interactions between amyloid and inferior temporal and precuneus tau. No significant associations were found between the APT tasks and tau or amyloid alone. CONCLUSION: Our preliminary findings suggest an association between a simulated real-life IADL test and interactions of amyloid and several regions of early tau accumulation in CN older adults. However, some analyses were underpowered due to the small number of participants with elevated amyloid, and findings should be interpreted with caution. Future studies will further explore these associations cross-sectionally and longitudinally in order to determine whether the Harvard APT can serve as a reliable IADL outcome measure for preclinical AD prevention trials and ultimately in the clinic setting.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Amyloidogenic Proteins; Cognitive Dysfunction; Entorhinal Cortex; Humans; Positron-Emission Tomography; tau Proteins

Cardiorespiratory Fitness Attenuates the Deleterious Effects of Sleep Apnea on Cerebral Structure and Perfusion in the Wisconsin Sleep Cohort Study. - Edmunds, Kyle J; Driscoll, Ira; Hagen, Erika W; Barnet, Jodi H; Ravelo, Laurel A; Plante, David T; Gaitán, Julian M; Lose, Sarah R; Motovylyak, Alice; Bendlin, Barbara B; Okonkwo, Ozioma C; Peppard, Paul E (J Alzheimers Dis, 2023)
BACKGROUND: Emerging evidence suggests that age-related changes in cerebral health may be sensitive to vascular risk modifiers, such as physical activity and sleep. OBJECTIVE: We examine whether cardiorespiratory fitness modifies the association of obstructive sleep apnea (OSA) severity with MRI-assessed measures of cerebral structure and perfusion. METHODS: Using data from a cross-sectional sample of participants (n = 129, 51% female, age range 49.6-85.3 years) in the Wisconsin Sleep Cohort study, we estimated linear models of MRI-assessed total and regional gray matter (GM) and white matter (WM) volumes, WM hyperintensity (WMH:ICV ratio), total lesion volume, and arterial spin labeling (ASL) cerebral blood flow (CBF), using an estimated measure of cardiorespiratory fitness (CRF) and OSA severity as predictors. Participants' sleep was assessed using overnight in-laboratory polysomnography, and OSA severity was measured using the apnea-hypopnea index (AHI), or the mean number of recorded apnea and hypopnea events per hour of sleep. The mean±SD time difference between PSG data collection and MRI data collection was 1.7±1.5 years (range: [0, 4.9 years]). RESULTS: OSA severity was associated with reduced total GM volume (β=-0.064; SE = 0.023; p = 0.007), greater total WM lesion volume (interaction p = 0.023), and greater WMHs (interaction p = 0.017) in less-fit subjects. Perfusion models revealed significant differences in the association of AHI and regional CBF between fitness groups (interaction ps <  0.05). CONCLUSION: This work provides new evidence for the protective role of cardiorespiratory fitness against the deleterious effects of OSA on brain aging in late-middle age to older adults.

Cerebral Gray and White Matter Monogalactosyl Diglyceride Levels Rise with the Progression of Alzheimer's Disease. - Blusztajn, Jan Krzysztof; Aytan, Nurgul; Rajendiran, Thekkelnaycke; Mellott, Tiffany J; Soni, Tanu; Burant, Charles F; Serrano, Geidy E; Beach, Thomas G; Lin, Honghuang; Stein, Thor D (J Alzheimers Dis, 2023)
BACKGROUND: Multiple studies have reported brain lipidomic abnormalities in Alzheimer's disease (AD) that affect glycerophospholipids, sphingolipids, and fatty acids. However, there is no consensus regarding the nature of these abnormalities, and it is unclear if they relate to disease progression. OBJECTIVE: Monogalactosyl diglycerides (MGDGs) are a class of lipids which have been recently detected in the human brain. We sought to measure their levels in postmortem human brain and determine if these levels correlate with the progression of the AD-related traits. METHODS: We measured MGDGs by ultrahigh performance liquid chromatography tandem mass spectrometry in postmortem dorsolateral prefrontal cortex gray matter and subcortical corona radiata white matter samples derived from three cohorts of participants: the Framingham Heart Study, the Boston University Alzheimer's Disease Research Center, and the Arizona Study of Aging and Neurodegenerative Disorders/Brain and Body Donation Program (total n = 288). RESULTS: We detected 40 molecular species of MGDGs (including diacyl and alkyl/acyl compounds) and found that the levels of 29 of them, as well as total MGDG levels, are positively associated with AD-related traits including pathologically confirmed AD diagnosis, clinical dementia rating, Braak and Braak stage, neuritic plaque score, phospho-Tau AT8 immunostaining density, levels of phospho-Tau396 and levels of Aβ40. Increased MGDG levels were present in both gray and white matter, indicating that they are widespread and likely associated with myelin-producing oligodendrocytes-the principal cell type of white matter. CONCLUSIONS: Our data implicate the MGDG metabolic defect as a central correlate of clinical and pathological progression in AD.

Cleveland Clinic Cognitive Battery (C3B): Normative, Reliability, and Validation Studies of a Self-Administered Computerized Tool for Screening Cognitive Dysfunction in Primary Care. - Rao, Stephen M; Galioto, Rachel; Sokolowski, Megan; Pierce, Madelyn; Penn, Lisa; Sturtevant, Anna; Skugor, Blazenka; Anstead, Brent; Leverenz, James B; Schindler, David; Blum, David; Alberts, Jay L; et al. (J Alzheimers Dis, 2023)
BACKGROUND: The self-administered iPad-based Cleveland Clinic Cognitive Battery (C3B) was designed specifically for the efficient screening of cognitive functioning of older adults in a primary care setting. OBJECTIVE: 1) Generate regression-based norms from healthy participants to enable demographic corrections to facilitate clinical interpretation; 2) estimate test-retest reliability and practice effects; 3) examine ability to discriminate mild cognitive impairment (MCI) from healthy aging; 4) d etermine validity of screening in a distracting clinical environment; and 5) determine completion rates and patient satisfaction in a primary care setting. METHODS: Study 1 (S1) recruited a stratified sample of 428 healthy adults, ages 18-89, to generate regression-based equations. S2 assessed 2-week test-retest reliability and practice effects in 30 healthy elders. S3 recruited 30 MCI patients and 30 demographically-matched healthy controls. In S4, 30 healthy elders self-administered the C3B in a distracting environment and in a quiet private room in counterbalanced order. In a demonstration project, 470 consecutive primary care patients were administered the C3B as part of routine clinical care (S5). RESULTS: C3B performance was primarily influenced by age, education, and race (S1), had acceptably high test-retest reliability and minimal practice effects (S2), discriminated MCI from healthy controls (S3), was not negatively impacted by a distracting clinical environment (S4), had high completion rates (>92%) and positive ratings from primary care patients (S5). CONCLUSION: The C3B is a computerized cognitive screening tool that is reliable, validated, self-administered, and is conducive to integration into a busy primary care clinical workflow for detecting MCI, early Alzheimer's disease, and other related dementias.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cognition; Cognitive Dysfunction; Humans; Middle Aged; Neuropsychological Tests; Primary Health Care; Reproducibility of Results; Young Adult

Coexistence of Amyotrophic Lateral Sclerosis and Alzheimer's Disease: Case Report and Review of the Literature. - Verde, Federico; Aiello, Edoardo Nicolò; Adobbati, Laura; Poletti, Barbara; Solca, Federica; Tiloca, Cinzia; Sangalli, Davide; Maranzano, Alessio; Muscio, Cristina; Ratti, Antonia; Zago, Stefano; Ticozzi, Nicola; et al. (J Alzheimers Dis, 2023)
We describe a case of amyotrophic lateral sclerosis (ALS) associated with Alzheimer's disease (AD) and review the literature about the coexistence of the two entities, highlighting the following: mean age at onset is 63.8 years, with slight female predominance; ALS tends to manifest after cognitive impairment and often begins in the bulbar region; average disease duration is 3 years; cognitive phenotype is mostly amnestic; the pattern of brain involvement is, in most cases, consistent with AD. Our case and the reviewed ones suggest that patients with ALS and dementia lacking unequivocal features of FTD should undergo additional examinations in order to recognize AD.
Keywords: Alzheimer Disease; Amyotrophic Lateral Sclerosis; Brain; Cognitive Dysfunction; Female; Frontotemporal Dementia; Humans; Male

Cognitive and Neuropsychological Profiles in Alzheimer's Disease and Primary Age-Related Tauopathy and the Influence of Comorbid Neuropathologies. - Walker, Jamie M; Gonzales, Mitzi M; Goette, William; Farrell, Kurt; White Iii, Charles L; Crary, John F; Richardson, Timothy E (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease neuropathologic change (ADNC) is defined by the progression of both hyperphosphorylated-tau (p-tau) and amyloid-β (Aβ) and is the most common underlying cause of dementia worldwide. Primary age-related tauopathy (PART), an Aβ-negative tauopathy largely confined to the medial temporal lobe, is increasingly being recognized as an entity separate from ADNC with diverging clinical, genetic, neuroanatomic, and radiologic profiles. OBJECTIVE: The specific clinical correlates of PART are largely unknown; we aimed to identify cognitive and neuropsychological differences between PART, ADNC, and subjects with no tauopathy (NT). METHODS: We compared 2,884 subjects with autopsy-confirmed intermediate-high stage ADNC to 208 subjects with definite PART (Braak stage I-IV, Thal phase 0, CERAD NP score "absent") and 178 NT subjects from the National Alzheimer's Coordinating Center dataset. RESULTS: PART subjects were older than either ADNC or NT patients. The ADNC cohort had more frequent neuropathological comorbidities as well as APOE ɛ4 alleles than the PART or NT cohort, and less frequent APOE ɛ2 alleles than either group. Clinically, ADNC patients performed significantly worse than NT or PART subjects across cognitive measures, but PART subjects had selective deficits in measures of processing speed, executive function, and visuospatial function, although additional cognitive measures were further impaired in the presence of neuropathologic comorbidities. In isolated cases of PART with Braak stage III-IV, there are additional deficits in measures of language. CONCLUSION: Overall, these findings demonstrate underlying cognitive features specifically associated with PART, and reinforce the concept that PART is a distinct entity from ADNC.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Cognition; Executive Function; Humans; Tauopathies

COVID-19 as a Risk Factor for Alzheimer's Disease. - Golzari-Sorkheh, Mahdieh; Weaver, Donald F; Reed, Mark A (J Alzheimers Dis, 2023)
Severe acute respiratory disease coronavirus 2 (SARS-CoV-2) is responsible for the coronavirus disease 2019 (COVID-19) pandemic. Although a primarily respiratory disease, recent reports indicate that it also affects the central nervous system (CNS). Over 25% of COVID-19 patients report neurological symptoms such as memory loss, anosmia, hyposmia, confusion, and headaches. The neurological outcomes may be a result of viral entry into the CNS and/or resulting neuroinflammation, both of which underlie an elevated risk for Alzheimer's disease (AD). Herein, we ask: Is COVID-19 a risk factor for AD? To answer, we identify the literature and review mechanisms by which COVID-19-mediated neuroinflammation can contribute to the development of AD, evaluate the effects of acute versus chronic phases of infection, and lastly, discuss potential therapeutics to address the rising rates of COVID-19 neurological sequelae.
Keywords: Alzheimer Disease; COVID-19; Humans; Nervous System Diseases; Neuroinflammatory Diseases; Risk Factors; SARS-CoV-2

Deep Reinforcement Learning-Based Retinal Imaging in Alzheimer's Disease: Potential and Perspectives. - Hui, Herbert Y H; Ran, An Ran; Dai, Jia Jia; Cheung, Carol Y (J Alzheimers Dis, 2023)
Alzheimer's disease (AD) remains a global health challenge in the 21st century due to its increasing prevalence as the major cause of dementia. State-of-the-art artificial intelligence (AI)-based tests could potentially improve population-based strategies to detect and manage AD. Current retinal imaging demonstrates immense potential as a non-invasive screening measure for AD, by studying qualitative and quantitative changes in the neuronal and vascular structures of the retina that are often associated with degenerative changes in the brain. On the other hand, the tremendous success of AI, especially deep learning, in recent years has encouraged its incorporation with retinal imaging for predicting systemic diseases. Further development in deep reinforcement learning (DRL), defined as a subfield of machine learning that combines deep learning and reinforcement learning, also prompts the question of how it can work hand in hand with retinal imaging as a viable tool for automated prediction of AD. This review aims to discuss potential applications of DRL in using retinal imaging to study AD, and their synergistic application to unlock other possibilities, such as AD detection and prediction of AD progression. Challenges and future directions, such as the use of inverse DRL in defining reward function, lack of standardization in retinal imaging, and data availability, will also be addressed to bridge gaps for its transition into clinical use.
Keywords: Alzheimer Disease; Artificial Intelligence; Humans; Machine Learning; Magnetic Resonance Imaging; Retina

Detecting Anosognosia from the Prodromal Stage of Alzheimer's Disease. - Guieysse, Thomas; Lamothe, Roxane; Houot, Marion; Razafimahatratra, Solofo; Medani, Takfarinas; Lejeune, François-Xavier; Dreyfus, Gérard; Klarsfeld, André; Pantazis, Dimitrios; Koechlin, Etienne; Andrade, Katia (J Alzheimers Dis, 2023)
BACKGROUND: Though not originally developed for this purpose, the Healthy Aging Brain Care Monitor (HABC-M) seems a valuable instrument for assessing anosognosia in Alzheimer's disease (AD). OBJECTIVES: Our study aimed at 1) investigating the validity of the HABC-M (31 items), and its cognitive, psychological, and functional subscales, in discriminating AD patients from controls; 2) exploring whether the HABC-M discrepancy scores between the self-reports of patients/controls in these different domains and the respective ratings provided by their caregivers/informants correlate with an online measure of self-awareness; 3) determining whether the caregiver burden level, also derived from the HABC-M, could add additional support for detecting anosognosia. METHODS: The HABC-M was administered to 30 AD patients and 30 healthy controls, and to their caregivers/informants. A measure of online awareness was established from subjects' estimation of their performances in a computerized experiment. RESULTS: The HABC-M discrepancy scores distinguished AD patients from controls. The cognitive subscale discriminated the two groups from the prodromal AD stage, with an AUC of 0.88 [95% CI: 0.78;0.97]. Adding the caregiver burden level raised it to 0.94 [0.86;0.99]. Significant correlations between the HABC-M and online discrepancy scores were observed in the patients group, providing convergent validity of these methods. CONCLUSIONS: The cognitive HABC-M (six items) can detect anosognosia across the AD spectrum. The caregiver burden (four items) may corroborate the suspicion of anosognosia. The short-hybrid scale, built from these 10 items instead of the usual 31, showed the highest sensitivity for detecting anosognosia from the prodromal AD stage, which may further help with timely diagnosis.
Keywords: Agnosia; Alzheimer Disease; Brain; Caregivers; Humans; Neuropsychological Tests; Prodromal Symptoms

Diagnostic Performance of Cerebrospinal Fluid Neurofilament Light Chain and Soluble Amyloid-β Protein Precursor β in the Subcortical Small Vessel Type of Dementia. - Axelsson Andrén, Elin; Kettunen, Petronella; Bjerke, Maria; Rolstad, Sindre; Zetterberg, Henrik; Blennow, Kaj; Wallin, Anders; Svensson, Johan (J Alzheimers Dis, 2023)
BACKGROUND: The subcortical small vessel type of dementia (SSVD) is a common subtype of vascular dementia, but there is a lack of disease-specific cerebrospinal fluid (CSF) biomarkers. OBJECTIVE: We investigated whether CSF concentrations of neurofilament light chain (NFL), soluble amyloid-β protein precursor α (sAβPPα), sAβPPβ, and CSF/serum albumin ratio could separate SSVD from healthy controls, Alzheimer's disease (AD), and mixed dementia (combined AD and SSVD). METHODS: This was a mono-center study of patients with SSVD (n = 38), AD (n = 121), mixed dementia (n = 62), and controls (n = 96). The CSF biomarkers were measured using immunoassays, and their independent contribution to the separation between groups were evaluated using the Wald test. Then, the area under the receiver operating characteristics curve (AUROC) and 95% confidence intervals (CIs) were calculated. RESULTS: Elevated neurofilament light chain (NFL) and decreased sAβPPβ independently separated SSVD from controls, and sAβPPβ also distinguished SSVD from AD and mixed dementia. The combination of NFL and sAβPPβ discriminated SSVD from controls with high accuracy (AUROC 0.903, 95% CI: 0.834-0.972). Additionally, sAβPPβ combined with the core AD biomarkers (amyloid-β42, total tau, and phosphorylated tau181) had a high ability to separate SSVD from AD (AUROC 0.886, 95% CI: 0.830-0.942) and mixed dementia (AUROC 0.903, 95% CI: 0.838-0.968). CONCLUSIONS: The high accuracy of NFL and sAβPPβ to separate SSVD from controls supports that SSVD is a specific diagnostic entity. Moreover, SSVD was distinguished from AD and mixed dementia using sAβPPβ in combination with the core AD biomarkers.

Different Trajectories of Apathy and Depression Among Subjective Cognitive Impairment Individuals with or without Conversion to Dementia: Results from the Memento Cohort in France. - Bogdan, Anamaria; Fabre, Roxane; Desmidt, Thomas; Golebiowski, Jérôme; Topin, Jérémie; Bethus, Ingrid; Hanon, Olivier; Boutoleau-Bretonnière, Claire; Wagemann, Nathalie; Annweiler, Cedric; Ousset, Pierre-Jean; Godefroy, Olivier; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Apathy and depression are two early behavioral symptoms in Alzheimer's disease (AD) and related disorders that often occur prior to the onset of cognitive decline and memory disturbances. Both have been associated with an increased risk of conversion to dementia, with a distinct neuropathology. OBJECTIVE: The assessment of the trajectories of apathy and depression and their independent impact on dementia conversion. METHODS: Apathy and Depression were measured using the Neuropsychiatric Inventory for caregiver (NPI) and clinician (NPI-C), among the nondemented individuals reporting subjective cognitive decline (SCD) at baseline. They were followed up over a 60-month period. Some converted to dementia, according to the methodology carried out by the French Memento Cohort. RESULTS: Among individuals with SCD (n = 2,323), the levels of apathy and depression were low and did not evolve significantly over the 60-month period, despite a trend in apathy increasing as of month 24. Regarding SCD individuals who converted to dementia within the 60-month period (n = 27), the prevalence of depression remained globally steady, while the levels of apathy increased over time. CONCLUSION: Apathy and depression have different trajectories among individuals with SCD and apathy alone is more likely-compared to depression-to be associated with conversion to dementia.

Effect of Lecanemab in Early Alzheimer's Disease: Mechanistic Interpretation in the Amyloid Cascade Hypothesis 2.0 Perspective. - Volloch, Vladimir; Rits-Volloch, Sophia (J Alzheimers Dis, 2023)
In clinical trials, lecanemab and donanemab showed statistically significant yet marginal slowdown of Alzheimer's disease (AD)-associated cognitive decline. This could be due to their sub-optimal design and/or deployment; alternatively, their limited efficiency could be intrinsic. Distinguishing between the two is of great importance considering the acute need of efficient AD therapy and tremendous resources being invested in its pursuit. The present study analyzes the mode of operation of lecanemab and donanemab within the framework of recently proposed Amyloid Cascade Hypothesis 2.0 and concludes that the second possibility is correct. It suggests that substantial improvement of the efficiency of these drugs in symptomatic AD is unlikely and proposes the alternative therapeutic strategy.
Keywords: Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Amyloidogenic Proteins; Humans

Elevated Pure Tone Thresholds Are Associated with Altered Microstructure in Cortical Areas Related to Auditory Processing and Attentional Allocation. - McEvoy, Linda K; Bergstrom, Jaclyn; Hagler, Donald J; Wing, David; Reas, Emilie T (J Alzheimers Dis, 2023)
BACKGROUND: Hearing loss is associated with cognitive decline and increased risk for Alzheimer's disease, but the basis of this association is not understood. OBJECTIVE: To determine whether hearing impairment is associated with advanced brain aging or altered microstructure in areas involved with auditory and cognitive processing. METHODS: 130 participants, (mean 76.4±7.3 years; 65% women) of the Rancho Bernardo Study of Healthy Aging had a screening audiogram in 2003-2005 and brain magnetic resonance imaging in 2014-2016. Hearing ability was defined as the average pure tone threshold (PTA) at 500, 1000, 2000, and 4000 Hz in the better-hearing ear. Brain-predicted age difference (Brain-pad) was calculated as the difference between brain-predicted age based on a validated structural imaging biomarker of brain age, and chronological age. Regional diffusion metrics in temporal and frontal cortex regions were obtained from diffusion-weighted MRIs. Linear regression analyses adjusted for age, gender, education, and health-related measures. RESULTS: PTAs were not associated with brain-PAD (β= 0.09; 95% CI: -0.084 to 0.243; p = 0.34). PTAs were associated with reduced restricted diffusion and increased free water diffusion primarily in right hemisphere temporal and frontal areas (restricted diffusion: βs = -0.21 to -0.30; 95% CIs from -0.48 to -0.02; ps <  0.03; free water: βs = 0.18 to 0.26; 95% CIs 0.01 to 0.438; ps <  0.04). CONCLUSIONS: Hearing impairment is not associated with advanced brain aging but is associated with differences in brain regions involved with auditory processing and attentional control. It is thus possible that increased dementia risk associated with hearing impairment arises, in part, from compensatory brain changes that may decrease resilience.

Etiology and Clinical Significance of Network Hyperexcitability in Alzheimer's Disease: Unanswered Questions and Next Steps. - Samudra, Niyatee; Ranasinghe, Kamalini; Kirsch, Heidi; Rankin, Katherine; Miller, Bruce (J Alzheimers Dis, 2023)
Cortical network hyperexcitability related to synaptic dysfunction in Alzheimer's disease (AD) is a potential target for therapeutic intervention. In recent years, there has been increased interest in the prevalence of silent seizures and interictal epileptiform discharges (IEDs, or seizure tendency), with both entities collectively termed "subclinical epileptiform activity" (SEA), on neurophysiologic studies in AD patients. SEA has been demonstrated to be common in AD, with prevalence estimates ranging between 22-54%. Converging lines of basic and clinical evidence imply that modifying a hyperexcitable state results in an improvement in cognition. In particular, though these results require further confirmation, post-hoc findings from a recent phase II clinical trial suggest a therapeutic effect with levetiracetam administration in patients with AD and IEDs. Here, we review key unanswered questions as well as potential clinical trial avenues. Specifically, we discuss postulated mechanisms and treatment of hyperexcitability in patients with AD, which are of interest in designing future disease-modifying therapies. Criteria to prompt screening and optimal screening methodology for hyperexcitability have yet to be defined, as does timing and personalization of therapeutic intervention.
Keywords: Alzheimer Disease; Causality; Clinical Relevance; Electroencephalography; Humans; Levetiracetam; Seizures

Evaluation of Blood-Based Plasma Biomarkers as Potential Markers of Amyloid Burden in Preclinical Alzheimer's Disease. - Winston, Charisse N; Langford, Oliver; Levin, Natalie; Raman, Rema; Yarasheski, Kevin; West, Tim; Abdel-Latif, Sara; Donohue, Michael; Nakamura, Akinori; Toba, Kenji; Masters, Colin L; Doecke, James; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Participant eligibility for the A4 Study was determined by amyloid PET imaging. Given the disadvantages of amyloid PET imaging in accessibility and cost, blood-based biomarkers may serve as a sufficient biomarker and more cost-effective screening tool for patient enrollment into preclinical AD trials. OBJECTIVE: To determine if a blood-based screening test can adequately identify amyloid burden in participants screened into a preclinical AD trial. METHODS: In this cross-sectional study, 224 participants from the A4 Study received an amyloid PET scan (18Florbetapir) within 90 days of blood sample collection. Blood samples from all study participants were processed within 2 h after phlebotomy. Plasma amyloid measures were quantified by Shimazdu and C2 N Diagnostics using mass spectrometry-based platforms. A corresponding subset of blood samples (n = 100) was processed within 24 h after phlebotomy and analyzed by C2 N. RESULTS: Plasma Aβ42/Aβ40 demonstrated the highest association for Aβ accumulation in the brain with an AUC 0.76 (95%CI = 0.69, 0.82) at C2 N and 0.80 (95%CI = 0.75, 0.86) at Shimadzu. Blood samples processed to plasma within 2 h after phlebotomy provided a better prediction of amyloid PET status than blood samples processed within 24 h (AUC 0.80 versus 0.64; p < 0.001). Age, sex, and APOE ɛ4 carrier status did not the diagnostic performance of plasma Aβ42/Aβ40 to predict amyloid PET positivity in A4 Study participants. CONCLUSION: Plasma Aβ42/Aβ40 may serve as a potential biomarker for predicting elevated amyloid in the brain. Utilizing blood testing over PET imaging may improve screening efficiency into clinical trials.
Keywords: Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Amyloidogenic Proteins; Biomarkers; Cross-Sectional Studies; Humans; Peptide Fragments; Positron-Emission Tomography

Exercise-Related Physical Activity Relates to Brain Volumes in 10,125 Individuals. - Raji, Cyrus A; Meysami, Somayeh; Hashemi, Sam; Garg, Saurabh; Akbari, Nasrin; Ahmed, Gouda; Chodakiewitz, Yosef Gavriel; Nguyen, Thanh Duc; Niotis, Kellyann; Merrill, David A; Attariwala, Rajpaul (J Alzheimers Dis, 2023)
BACKGROUND: The potential neuroprotective effects of regular physical activity on brain structure are unclear, despite links between activity and reduced dementia risk. OBJECTIVE: To investigate the relationships between regular moderate to vigorous physical activity and quantified brain volumes on magnetic resonance neuroimaging. METHODS: A total of 10,125 healthy participants underwent whole-body MRI scans, with brain sequences including isotropic MP-RAGE. Three deep learning models analyzed axial, sagittal, and coronal views from the scans. Moderate to vigorous physical activity, defined by activities increasing respiration and pulse rate for at least 10 continuous minutes, was modeled with brain volumes via partial correlations. Analyses adjusted for age, sex, and total intracranial volume, and a 5% Benjamini-Hochberg False Discovery Rate addressed multiple comparisons. RESULTS: Participant average age was 52.98±13.04 years (range 18-97) and 52.3% were biologically male. Of these, 7,606 (75.1%) reported engaging in moderate or vigorous physical activity approximately 4.05±3.43 days per week. Those with vigorous activity were slightly younger (p < 0.00001), and fewer women compared to men engaged in such activities (p = 3.76e-15). Adjusting for age, sex, body mass index, and multiple comparisons, increased days of moderate to vigorous activity correlated with larger normalized brain volumes in multiple regions including: total gray matter (Partial R = 0.05, p = 1.22e-7), white matter (Partial R = 0.06, p = 9.34e-11), hippocampus (Partial R = 0.05, p = 5.96e-7), and frontal, parietal, and occipital lobes (Partial R = 0.04, p≤1.06e-5). CONCLUSIONS: Exercise-related physical activity is associated with increased brain volumes, indicating potential neuroprotective effects.

Exposure to World Trade Center Dust Exacerbates Cognitive Impairment and Evokes a Central and Peripheral Pro-Inflammatory Transcriptional Profile in an Animal Model of Alzheimer's Disease. - Iban-Arias, Ruth; Trageser, Kyle J; Yang, Eun-Jeong; Griggs, Elizabeth; Radu, Aurelian; Naughton, Sean; Al Rahim, Md; Tatsunori, Oguchi; Raval, Urdhva; Palmieri, Joshua; Huang, Zerlina; Chen, Lung-Chi; et al. (J Alzheimers Dis, 2023)
BACKGROUND: The terrorist attacks on September 11, 2001, on the World Trade Center (WTC) led to intense fires and a massive dense cloud of toxic gases and suspended pulverized debris. In the subsequent years, following the attack and cleanup efforts, a cluster of chronic health conditions emerged among First Responders (FR) who were at Ground Zero for prolonged periods and were repeatedly exposed to high levels of WTC particulate matter (WTCPM). Among those are neurological complications which may increase the risk for the development of Alzheimer's disease (AD) later in life. OBJECTIVE: We hypothesize that WTCPM dust exposure affects the immune cross-talking between the periphery and central nervous systems that may induce brain permeability ultimately promoting AD-type phenotype. METHODS: 5XFAD and wild-type mice were intranasally administered with WTCPM dust collected at Ground Zero within 72 h after the attacks. Y-maze assay and novel object recognition behavioral tests were performed for working memory deficits and learning and recognition memory, respectively. Transcriptomic analysis in the blood and hippocampus was performed and confirmed by RT qPCR. RESULTS: Mice exposed to WTCPM dust exhibited a significant impairment in spatial and recognition short and long-term memory. Furthermore, the transcriptomic analysis in the hippocampal formation and blood revealed significant changes in genes related to immune-inflammatory responses, and blood-brain barrier disruption. CONCLUSION: These studies suggest a putative peripheral-brain immune inflammatory cross-talking that may potentiate cognitive decline, identifying for the first time key steps which may be therapeutically targetable in future studies in WTC FR.
Keywords: Alzheimer Disease; Animals; Cognitive Dysfunction; Dust; Mice; Models, Animal; September 11 Terrorist Attacks

Impact of Hearing Aids on Progression of Cognitive Decline, Depression, and Quality of Life Among People with Cognitive Impairment and Dementia. - Atef, Roaa Zayed; Michalowsky, Bernhard; Raedke, Anika; Platen, Moritz; Mohr, Wiebke; Mühlichen, Franka; Thyrian, Jochen René; Hoffmann, Wolfgang (J Alzheimers Dis, 2023)
BACKGROUND: Hearing loss is common in people with dementia (PwD) and a modifiable risk factor for cognitive decline. Recent studies revealed that hearing loss could cause social isolation and depression, which is associated with health-related quality of life (HRQoL). However, there is a lack of knowledge about the impact of the utilization of hearing aids on these outcomes. OBJECTIVE: To assess whether hearing aids use might be positively associated with the progression of cognitive function, depression, and HRQoL among PwD. METHODS: We analyzed two-year follow-up data from 258 PwD (≥70 years, living at home). Cognitive decline was measured with Mini-Mental Status Examination (MMSE), depression using Geriatric Depression Scale (GDS), and HRQoL with Quality of Life in Alzheimer's Disease Scale (QoL-AD). The impact of hearing aid utilization on the progression of outcomes was assessed using multivariate regression models. RESULTS: 123 patients had hearing loss (47.7%), from which n = 54 (43.9%) used hearing aids. Patients with hearing loss were older and had a lower HRQoL than those without hearing loss. Use of hearing aids in patients with hearing loss was associated with a lower increase in depressive symptoms (b = -0.74, CI95 -1.48 --0.01, p = 0.047) over time as compared to those not using hearing aids. There was no effect on PwD's cognition, and the association with higher HRQoL was significant after one, but not consistently over two years. CONCLUSION: Early detection and intervention of presbycusis using hearing aids might improve mental health and HRQoL in dementia.
Keywords: Aged; Cognitive Dysfunction; Deafness; Dementia; Depression; Hearing Aids; Humans; Presbycusis; Quality of Life

Impaired Early Insulin Response to Glucose Load Predicts Episodic Memory Decline: A 10-Year Population-Based Cohort Follow-Up of 45-74-Year-Old Men and Women. - Toppala, Sini; Ekblad, Laura L; Viitanen, Matti; Rinne, Juha O; Jula, Antti (J Alzheimers Dis, 2023)
BACKGROUND: Diabetes increases the risk for cognitive decline, but the mechanisms behind this association remain unknown. Impaired early insulin secretion in elderly men and insulin resistance, both of which are pathophysiological features of type 2 diabetes, have previously been linked to Alzheimer's disease. OBJECTIVE: To examine if the early insulin response to oral glucose load predicts cognitive performance after 10 years in men and women aged 45-74 years. METHODS: This study was based on a subpopulation of the Health 2000 Survey, a Finnish nationwide, population-based health examination study, and its follow-up, the Health 2011 Study. In total, 961 45-74-year-old individuals (mean age at baseline 55.6 years, 55.8% women) were examined. An oral glucose tolerance test was performed in 2001-2002, and early insulin response was defined as the ratio of the 30-min increment in insulin concentration to that of glucose concentration. Cognitive function was evaluated at baseline and follow-up with categorical verbal fluency, word-list learning, and word-list delayed recall. Statistical analyses were performed using multivariable linear models adjusted for age, sex, education, APOE&z.epsi;4 genotype, vascular risk factors including diabetes, and depressive symptoms. RESULTS: A lower early insulin response to glucose load predicted lower performance (β: 0.21, p = 0.03) and greater decline (β: 0.19, p = 0.03) in the word-list delayed recall test. Baseline early insulin response did not predict verbal fluency or word-list learning (all p-values≥0.13). CONCLUSION: Our results suggest that decreased early insulin secretion predicts episodic memory decline in middle-aged to elderly men and women.

Implication of Circulating Extracellular Vesicles-Bound Amyloid-β42 Oligomers in the Progression of Alzheimer's Disease. - M.R. BenKhedher; Haddad, Mohamed; Fülöp, Tamás; Laurin, Danielle; Ramassamy, Charles (J Alzheimers Dis, 2023)
BACKGROUND: The perplex interrelation between circulating extracellular vesicles (cEVs) and amyloid-β (Aβ) deposits in the context of Alzheimer's disease (AD) is poorly understood. OBJECTIVE: This study aims to 1) analyze the possible cross-linkage of the neurotoxic amyloid-β oligomers (oAβ) to the human cEVs, 2) identify cEVs corona proteins associated with oAβ binding, and 3) analyze the distribution and expression of targeted cEVs proteins in preclinical participants converted to AD 5 years later (Pre-AD). METHODS: cEVs were isolated from 15 Pre-AD participants and 15 healthy controls selected from the Canadian Study of Health and Aging. Biochemical, clinical, lipid, and inflammatory profiles were measured. oAβ and cEVs interaction was determined by nanoparticle tracking analysis and proteinase K digestion. cEVs bound proteins were determined by ELISA. RESULTS: oAβ were trapped by cEVs and were topologically bound to their external surface. We identified surface-exposed proteins functionally able to conjugate oAβ including apolipoprotein J (apoJ), apoE and RAGE, with apoJ being 30- to 130-fold higher than RAGE and apoE, respectively. The expression of cEVs apoJ was significantly lower in Pre-AD up to 5 years before AD onset. CONCLUSION: Our findings suggest that cEVs might participate in oAβ clearance and that early dysregulation of cEVs could increase the risk of conversion to AD.

Klotho Gene Expression Is Decreased in Peripheral Blood Mononuclear Cells in Patients with Alzheimer's Disease and Frontotemporal Dementia. - Sorrentino, Federica; Fenoglio, Chiara; Sacchi, Luca; Serpente, Maria; Arighi, Andrea; Carandini, Tiziana; Arosio, Beatrice; Ferri, Evelyn; Arcaro, Marina; Visconte, Caterina; Rotondo, Emanuela; Scarpini, Elio; et al. (J Alzheimers Dis, 2023)
BACKGROUND: The longevity gene Klotho (KL) was recently associated with neurodegenerative diseases including Alzheimer's disease (AD). Its role in the brain has not been completely elucidated, although evidence suggests that KL-VS heterozygosity is associated with a reduced risk of AD in Apolipoprotein E ɛ4 carriers. Conversely, no data about genetic association with frontotemporal dementia (FTD) are available so far. OBJECTIVE: To investigate the involvement of KL in AD and FTD by the determination of the genetic frequency of KL-VS variant and the expression analysis of KL gene. METHODS: A population consisting of 438 patients and 240 age-matched controls was enrolled for the study. KL-VS and APOE genotypes were assessed by allelic discrimination through a QuantStudio 12K system. KL gene expression analysis was performed in a restricted cohort of patients consisting of 43 AD patients, 41 FTD patients and 19 controls. KL gene expression was assessed in peripheral blood mononuclear cells with specific TaqMan assay. Statistical analysis was performed using GraphPad 9 Prims software. RESULTS: KL-VS frequency was comparable to the ones found in literature and no differences were found in both allelic and genotypic frequencies between patients and controls were found. Conversely, KL expression levels were significantly lower in AD and FTD patients compared with controls (mean fold regulation - 4.286 and - 6.561 versus controls in AD and FTD, respectively, p = 0.0037). CONCLUSION: This is the first study investigating KL in FTD. We showed a decreased expression of the gene in AD and FTD, independent of the genotype, suggesting a role of Klotho in common steps during neurodegeneration.

The Lipid Invasion Model: Growing Evidence for This New Explanation of Alzheimer's Disease. - Rudge, Jonathan D'Arcy (J Alzheimers Dis, 2023)
The Lipid Invasion Model (LIM) is a new hypothesis for Alzheimer's disease (AD) which argues that AD is a result of external lipid invasion to the brain, following damage to the blood-brain barrier (BBB). The LIM provides a comprehensive explanation of the observed neuropathologies associated with the disease, including the lipid irregularities first described by Alois Alzheimer himself, and accounts for the wide range of risk factors now identified with AD, all of which are also associated with damage to the BBB. This article summarizes the main arguments of the LIM, and new evidence and arguments in support of it. The LIM incorporates and extends the amyloid hypothesis, the current main explanation of the disease, but argues that the greatest cause of late-onset AD is not amyloid-β (Aβ) but bad cholesterol and free fatty acids, let into the brain by a damaged BBB. It suggests that the focus on Aβ is the reason why we have made so little progress in treating the disease in the last 30 years. As well as offering new perspectives for further research into the diagnosis, prevention, and treatment of AD, based on protecting and repairing the BBB, the LIM provides potential new insights into other neurodegenerative diseases such as Parkinson's disease and amyotrophic lateral sclerosis/motor neuron disease.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Blood-Brain Barrier; Brain; Cholesterol; Humans

Longitudinal White and Gray Matter Response to Precision Medicine-Guided Intervention for Alzheimer's Disease. - Chwa, Won Jong; Raji, Cyrus A; Toups, Kat; Hathaway, Ann; Gordon, Deborah; Chung, Henrianna; Boyd, Alan; Hill, Benjamin D; Hausman-Cohen, Sharon; Attarha, Mouna; Jarrett, Michael; Bredesen, Dale E (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) is a debilitating condition that is widely known to adversely affect gray matter (GM) and white matter (WM) tracts within the brain. Recently, precision medicine has shown promise in alleviating the clinical and gross morphological trajectories of patients with AD. However, regional morphological changes have not yet been adequately characterized. OBJECTIVE: Investigate regional morphological responses to a precision medicine-guided intervention with regards to white and gray matter in AD and mild cognitive impairment (MCI). METHODS: Clinical and neuroimaging data were compiled over a 9-month period from 25 individuals who were diagnosed with AD or MCI receiving individualized treatment plans. Structural T1-weighted MRI scans underwent segmentation and volumetric quantifications via Neuroreader. Longitudinal changes were calculated via annualized percent change of WM or GM ratios. RESULTS: Montreal Cognitive Assessment scores (p < 0.001) and various domains of the Computerized Neurocognitive Screening Vital Signs significantly improved from baseline to 9-month follow-up. There was regional variability in WM and GM atrophy or hypertrophy, but none of these observed changes were statistically significant after correction for multiple comparisons.
Keywords: Alzheimer Disease; Atrophy; Brain; Cognitive Dysfunction; Gray Matter; Humans; Magnetic Resonance Imaging; Precision Medicine; White Matter

Microglial Imaging in Alzheimer's Disease and Its Relationship to Brain Amyloid: A Human 18F-GE180 PET Study. - Yang, Zhengshi; Banks, Sarah J; Ritter, Aaron R; Cummings, Jeffrey L; Sreenivasan, Karthik; Kinney, Jefferson W; Caldwell, Jessica K; Wong, Christina G; Miller, Justin B; Cordes, Dietmar (J Alzheimers Dis, 2023)
BACKGROUND: Emerging evidence suggests a potential causal role of neuroinflammation in Alzheimer's disease (AD). Using positron emission tomography (PET) to image overexpressed 18 kDA translocator protein (TSPO) by activated microglia has gained increasing interest. The uptake of 18F-GE180 TSPO PET was observed to co-localize with inflammatory markers and have a two-stage association with amyloid PET in mice. Very few studies evaluated the diagnostic power of 18F-GE180 PET in AD population and its interpretation in human remains controversial about whether it is a marker of microglial activation or merely reflects disrupted blood-brain barrier integrity in humans. OBJECTIVE: The goal of this study was to study human GE180 from the perspective of the previous animal observations. METHODS: With data from twenty-four participants having 18F-GE180 and 18F-AV45 PET scans, we evaluated the group differences of 18F-GE180 uptake between participants with and without cognitive impairment. An association analysis of 18F-GE180 and 18F-AV45 was then conducted to test if the relationship in humans is consistent with the two-stage association in AD mouse model. RESULTS: Elevated 18F-GE180 was observed in participants with cognitive impairment compared to those with normal cognition. No regions showed reduced 18F-GE180 uptake. Consistent with mouse model, a two-stage association between 18F-GE180 and 18F-AV45 was observed. CONCLUSIONS: 18F-GE180 PET imaging showed promising utility in detecting pathological alterations in a symptomatic AD population. Consistent two-stage association between 18F-GE180 and amyloid PET in human and mouse suggested that 18F-GE180 uptake in human might be considerably influenced by microglial activation.

Mindfulness Prevents Depression and Psychopathology in Elderly People with Mild to Moderate Alzheimer's Disease: A Randomized Clinical Trial. - Quintana-Hernández, Domingo J; Rojas-Hernández, Jaime; Santana-Del Pino, Angelo; Céspedes Suárez, Carmen; Pellejero Silva, Mónica; Miró-Barrachina, María Teresa; Ibáñez Fernández, Ignacio; Estupiñán López, José Antonio; Borkel, Lucas F (J Alzheimers Dis, 2023)
BACKGROUND: This longitudinal study addressed whether mindfulness practice prevents psychological and behavioral symptoms, especially mood disorders, in Alzheimer's disease (AD). OBJECTIVE: To assess the incidence of depression in the course of AD and to determine which non-pharmacological treatment (NPT) is most effective in preventing psychopathological symptoms. METHODS: We conducted a longitudinal, non-inferiority and equivalence randomized clinical trial, repeated-measures design, with a control group and three experimental treatments: mindfulness, cognitive stimulation, and relaxation. Each experimental group performed three weekly sessions for two years. The pharmacological treatment of all participants was donepezil (10 mg). Participants were patients with probable AD without diagnosed depression from the public neurology services of the Canary Health Service, Spain. Psychological evaluation was performed using the Geriatric Depression Scale (GDS), Hamilton Depression Rating Scale (HDRS), and Neuropsychiatric Inventory (NPI-Q). The statistical analysis included only patients who attended at least 75% of the sessions. A nonparametric, repeated-measures analysis was performed with Kruskal-Wallis H test and between-group differences with Mann-Whitney U test with Bonferroni correction (p < 0.008). Effect size was calculated with partial eta-squared. RESULTS: The results showed significant differences with large effect sizes (η2p>0.14) between mindfulness and the rest of the experimental groups as well as the control in the GDS, HDRS, and NPI-Q scales. CONCLUSION: Compared to the other experimental groups, only mindfulness prevented the onset of depression and other psychopathologies in early-stage AD. Based on its effectiveness in maintaining cognitive functions and preventing psychopathology, we recommend mindfulness as the first-choice NPT for mild to moderate AD.
Keywords: Aged; Alzheimer Disease; Depression; Donepezil; Humans; Longitudinal Studies; Mindfulness

Mitochondria Profoundly Influence Apolipoprotein E Biology. - Gabrielli, Alexander P; Weidling, Ian; Ranjan, Amol; Wang, Xiaowan; Novikova, Lesya; Chowdhury, Subir Roy; Menta, Blaise; Berkowicz, Alexandra; Wilkins, Heather M; Peterson, Kenneth R; Swerdlow, Russell H (J Alzheimers Dis, 2023)
BACKGROUND: Mitochondria can trigger Alzheimer's disease (AD)-associated molecular phenomena, but how mitochondria impact apolipoprotein E (APOE; apoE) is not well known. OBJECTIVE: Consider whether and how mitochondrial biology influences APOE and apoE biology. METHODS: We measured APOE expression in human SH-SY5Y neuronal cells with different forms of mitochondrial dysfunction including total, chronic mitochondrial DNA (mtDNA) depletion (ρ0 cells); acute, partial mtDNA depletion; and toxin-induced mitochondrial dysfunction. We further assessed intracellular and secreted apoE protein levels in the ρ0 cells and interrogated the impact of transcription factors and stress signaling pathways known to influence APOE expression. RESULTS: SH-SY5Y ρ0 cells exhibited a 65-fold increase in APOE mRNA, an 8-fold increase in secreted apoE protein, and increased intracellular apoE protein. Other models of primary mitochondrial dysfunction including partial mtDNA-depletion, toxin-induced respiratory chain inhibition, and chemical-induced manipulations of the mitochondrial membrane potential similarly increased SH-SY5Y cell APOE mRNA. We explored potential mediators and found in the ρ0 cells knock-down of the C/EBPα and NFE2L2 (Nrf2) transcription factors reduced APOE mRNA. The activity of two mitogen-activated protein kinases, JNK and ERK, also strongly influenced ρ0 cell APOE mRNA levels. CONCLUSION: Primary mitochondrial dysfunction either directly or indirectly activates APOE expression in a neuronal cell model by altering transcription factors and stress signaling pathways. These studies demonstrate mitochondrial biology can influence the biology of the APOE gene and apoE protein, which are implicated in AD.
Keywords: Alzheimer Disease; Apolipoproteins E; Biology; Cell Line, Tumor; DNA, Mitochondrial; Humans; Mitochondria; Neuroblastoma; RNA, Messenger; Transcription Factors

MRI Visible Perivascular Spaces and the Risk of Incident Mild Cognitive Impairment in a Community Sample. - Pase, Matthew P; Pinheiro, Adlin; Rowsthorn, Ella; Demissie, Serkalem; Hurmez, Saoresho; Aparicio, Hugo; Rodriguez-Lara, Frances; Gonzales, Mitzi M; Beiser, Alexa; DeCarli, Charles; Seshadri, Sudha; Romero, Jose Rafael (J Alzheimers Dis, 2023)
BACKGROUND: Magnetic resonance imaging (MRI) visible perivascular spaces (PVS) are associated with the risk of incident dementia but their association with the early stages of cognitive impairment remains equivocal. OBJECTIVE: We examined the association between MRI visible PVS and the risk of incident mild cognitive impairment (MCI) in the community-based Framingham Heart Study (FHS). METHODS: FHS participants aged at least 50 years free of stroke, cognitive impairment, and dementia at the time of MRI were included. PVS were rated according to severity in the basal ganglia and centrum semiovale (CSO) using established criteria. Cox regression analyses were used to relate PVS to incident MCI adjusted for demographic and cardiovascular variables. RESULTS: The mean age of the sample (1,314 participants) at MRI was 68 years (SD, 9; 54% women). There were 263 cases of incident MCI over a median 7.4 years follow-up (max, 19.8 years). MCI risk increased with higher PVS severity in the CSO. Relative to persons with the lowest severity rating, persons with the highest severity rating in the CSO had a higher risk of incident MCI (hazard ratio [HR] = 2.55; 95% confidence interval [CI], 1.48-4.37; p = 0.0007). In secondary analysis, this association seemed stronger in women. Risk of incident MCI was nominally higher for participants with the highest severity grade of PVS in the basal ganglia, though not statistically significant relative to the lowest grade (HR = 2.19; 95% CI, 0.78-6.14; p = 0.14). CONCLUSIONS: PVS burden in the CSO may be a risk marker for early cognitive impairment.

Multi-Site Cross-Site Inter-Rater and Test-Retest Reliability and Construct Validity of the MarkVCID White Matter Hyperintensity Growth and Regression Protocol. - Bahrani, Ahmed A; Abner, Erin L; DeCarli, Charles S; Barber, Justin M; Sutton, Abigail C; Maillard, Pauline; Sandoval, Francisco; Arfanakis, Konstantinos; Yang, Yung-Chuan; Evia, Arnold M; Schneider, Julie A; Habes, Mohamad; et al. (J Alzheimers Dis, 2023)
BACKGROUND: White matter hyperintensities (WMH) that occur in the setting of vascular cognitive impairment and dementia (VCID) may be dynamic increasing or decreasing volumes or stable over time. Quantifying such changes may prove useful as a biomarker for clinical trials designed to address vascular cognitive-impairment and dementia and Alzheimer's Disease. OBJECTIVE: Conducting multi-site cross-site inter-rater and test-retest reliability of the MarkVCID white matter hyperintensity growth and regression protocol. METHODS: The NINDS-supported MarkVCID Consortium evaluated a neuroimaging biomarker developed to track WMH change. Test-retest and cross-site inter-rater reliability of the protocol were assessed. Cognitive test scores were analyzed in relation to WMH changes to explore its construct validity. RESULTS: ICC values for test-retest reliability of WMH growth and regression were 0.969 and 0.937 respectively, while for cross-site inter-rater ICC values for WMH growth and regression were 0.995 and 0.990 respectively. Word list long-delay free-recall was negatively associated with WMH growth (p < 0.028) but was not associated with WMH regression. CONCLUSIONS: The present data demonstrate robust ICC validity of a WMH growth/regression protocol over a one-year period as measured by cross-site inter-rater and test-retest reliability. These data suggest that this approach may serve an important role in clinical trials of disease-modifying agents for VCID that may preferentially affect WMH growth, stability, or regression.

Neuroinflammation: A Common Pathway in Alzheimer's Disease and Epilepsy. - Liew, Yee; Retinasamy, Thaarvena; Arulsamy, Alina; Ali, Idrish; Jones, Nigel C; O'Brien, Terence J; Shaikh, Mohd Farooq (J Alzheimers Dis, 2023)
BACKGROUND: Neuroinflammation is an innate immunological response of the central nervous system that may be induced by a brain insult and chronic neurodegenerative conditions. Recent research has shown that neuroinflammation may contribute to the initiation of Alzheimer's disease (AD) pathogenesis and associated epileptogenesis. OBJECTIVE: This systematic review aimed to investigate the available literature on the shared molecular mechanisms of neuroinflammation in AD and epilepsy. METHODS: The search included in this systematic review was obtained from 5 established databases. A total of 2,760 articles were screened according to inclusion criteria. Articles related to the modulation of the inflammatory biomarkers commonly associated with the progression of AD and epilepsy in all populations were included in this review. RESULTS: Only 7 articles met these criteria and were chosen for further analysis. Selected studies include both in vitro and in vivo research conducted on rodents. Several neuroinflammatory biomarkers were reported to be involved in the cross-talk between AD and epilepsy. CONCLUSION: Neuroinflammation was directly associated with the advancement of AD and epilepsy in populations compared to those with either AD or epilepsy. However, more studies focusing on common inflammatory biomarkers are required to develop standardized monitoring guidelines to prevent the manifestation of epilepsy and delay the progression of AD in patients.
Keywords: Alzheimer Disease; Biomarkers; Brain; Epilepsy; Humans; Neuroinflammatory Diseases

Neuropathology of Anti-Amyloid-β Immunotherapy: A Case Report. - Castellani, Rudolph J; Shanes, Elisheva; McCord, Matthew; Reish, Nicholas J; Flanagan, Margaret E; Mesulam, M-Marsel; Jamshidi, Pouya (J Alzheimers Dis, 2023)
Host responses to anti-amyloid-β (Aβ) antibody therapy are evident in neuroimaging changes and clinical symptoms in a subset of clinical trial subjects receiving such therapy. The pathological basis for the imaging changes and clinical symptoms is not known, nor is the precise mechanism of Aβ clearing. We report the autopsy findings in a 65-year-old woman who received three open label infusions of the experimental anti-Aβ drug lecanemab over about one month. Four days after the last infusion, she was treated with tissue plasminogen activator for acute stroke symptoms and died several days later with multifocal hemorrhage. Neuropathological examination demonstrated histiocytic vasculitis involving blood vessels with cerebral amyloid angiopathy. Fragmentation and phagocytosis of vascular Aβ were present throughout the cerebral cortex. Phagocytosis of parenchymal Aβ plaques was noted. Changes suggestive of Aβ and phosphorylated tau "clearing" were also noted. The findings overall suggest that anti-Aβ treatment stimulated a host response to Aβ, i.e., target engagement. The findings also provide evidence that amyloid-related imaging abnormalities might be indicative of an Aβ phagocytic syndrome within cerebral vasculature and parenchymal brain tissue in some cases.

Noninvasive Gamma Sensory Stimulation May Reduce White Matter and Myelin Loss in Alzheimer's Disease. - Da, Xiao; Hempel, Evan; Ou, Yangming; Rowe, Olivia Elizabeth; Malchano, Zach; Hajós, Mihály; Kern, Ralph; Megerian, Jonathan Thomas; Cimenser, Aylin (J Alzheimers Dis, 2023)
BACKGROUND: Patients with Alzheimer's disease (AD) demonstrate progressive white matter atrophy and myelin loss. Restoring myelin content or preventing demyelination has been suggested as a therapeutic approach for AD. OBJECTIVE: Herein, we investigate the effects of non-invasive, combined visual and auditory gamma-sensory stimulation on white matter atrophy and myelin content loss in patients with AD. METHODS: In this study, we used the magnetic resonance imaging (MRI) data from the OVERTURE study (NCT03556280), a randomized, controlled, clinical trial in which active treatment participants received daily, non-invasive, combined visual and auditory, 40 Hz stimulation for six months. A subset of OVERTURE participants who meet the inclusion criteria for detailed white matter (N = 38) and myelin content (N = 36) assessments are included in the analysis. White matter volume assessments were performed using T1-weighted MRI, and myelin content assessments were performed using T1-weighted/T2-weighted MRI. Treatment effects on white matter atrophy and myelin content loss were assessed. RESULTS: Combined visual and auditory gamma-sensory stimulation treatment is associated with reduced total and regional white matter atrophy and myelin content loss in active treatment participants compared to sham treatment participants. Across white matter structures evaluated, the most significant changes were observed in the entorhinal region. CONCLUSIONS: The study results suggest that combined visual and auditory gamma-sensory stimulation may modulate neuronal network function in AD in part by reducing white matter atrophy and myelin content loss. Furthermore, the entorhinal region MRI outcomes may have significant implications for early disease intervention, considering the crucial afferent connections to the hippocampus and entorhinal cortex.

Observed Improvement in Cognition During a Personalized Lifestyle Intervention in People with Cognitive Decline. - Sandison, Heather; Callan, Nini G L; Rao, Rammohan V; Phipps, John; Bradley, Ryan (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) is a chronic condition marked by progressive objective cognitive impairment (OCI). No monotherapy has substantially altered disease progression, suggesting the disease is multifactorial and may require a multimodal therapeutic approach. OBJECTIVE: We sought to determine if cognitive function in a sample with OCI would change in response to a multimodal, individualized care plan based on potential contributors to cognitive decline (e.g., nutritional status, infection, etc.). METHODS: Participants (n = 34) were recruited from the San Diego, CA area. The multimodal intervention included lifestyle changes (i.e., movement, diet, and stress management), nutraceutical support, and medications. It was delivered pragmatically over four clinical visits, and outcome measures were gathered at four study visits, occurring at baseline, one, three, and six months (primary endpoint). Study participants received weekly phone calls for nutrition support throughout study participation. Outcome measures included the Cambridge Brain Sciences (CBS) battery, and the Montreal Cognitive Assessment (MoCA). RESULTS: At 6 months, mean MoCA scores improved from 19.6±3.1 to 21.7±6.2 (p = 0.013). Significant improvement was observed in mean scores of the CBS memory domain [25.2 (SD 23.3) to 35.8 (SD 26.9); p < 0.01] and CBS overall composite cognition score [24.5 (SD 16.1) to 29.7 (SD 20.5); p = 0.02]. All CBS domains improved. CONCLUSION: Multiple measures of cognitive function improved after six months of intervention. Our results support the feasibility and impact of a multimodal, individualized treatment approach to OCI, warranting further research.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; California; Cognition; Cognitive Dysfunction; Diet, Healthy; Dietary Supplements; Disease Progression; Exercise; Feasibility Studies; Female; Healthy Lifestyle; Humans; Infections; Male; Memory; Middle Aged; Nutritional Status; Pragmatic Clinical Trials as Topic; Reproducibility of Results; Stress, Psychological; Time Factors; Treatment Outcome; Verbal Behavior

Pathogenomic Signature and Aberrant Neurogenic Events in Experimental Cerebral Ischemic Stroke: A Neurotranscriptomic-Based Implication for Dementia. - Roshan, Syed Aasish; Elangovan, Gayathri; Gunaseelan, Dharani; Jayachandran, Swaminathan K; Kandasamy, Mahesh; Anusuyadevi, Muthuswamy (J Alzheimers Dis, 2023)
BACKGROUND: Cerebral ischemic stroke is caused due to neurovascular damage or thrombosis, leading to neuronal dysfunction, neuroinflammation, neurodegeneration, and regenerative failure responsible for neurological deficits and dementia. The valid therapeutic targets against cerebral stroke remain obscure. Thus, insight into neuropathomechanisms resulting from the aberrant expression of genes appears to be crucial. OBJECTIVE: In this study, we have elucidated how neurogenesis-related genes are altered in experimental stroke brains from the available transcriptome profiles in correlation with transcriptome profiles of human postmortem stroke brain tissues. METHODS: The transcriptome datasets available on the middle cerebral artery occlusion (MCAo) rat brains were obtained from the Gene Expression Omnibus, National Center for Biotechnology Information. Of the available datasets, 97 samples were subjected to the meta-analysis using the network analyst tool followed by Cytoscape-based enrichment mapping analysis. The key differentially expressed genes (DEGs) were validated and compared with transcriptome profiling of human stroke brains. RESULTS: Results revealed 939 genes are differently expressed in the brains of the MCAo rat model of stroke, in which 30 genes are key markers of neural stem cells, and regulators of neurogenic processes. Its convergence with DEGs from human stroke brains has revealed common targets. CONCLUSION: This study has established a panel of highly important DEGs to signify the potential therapeutic targets for neuroregenerative strategy against pathogenic events associated with cerebral stroke. The outcome of the findings can be translated to mitigate neuroregeneration failure seen in various neurological and metabolic disease manifestations with neurocognitive impairments.
Keywords: Animals; Brain; Dementia; Humans; Infarction, Middle Cerebral Artery; Ischemic Stroke; Neurogenesis; Rats; Stroke

Physical Activity for Cognitive Health: A Model for Intervention Design for People Experiencing Cognitive Concerns and Symptoms of Depression or Anxiety. - Curran, Eleanor; Palmer, Victoria J; Ellis, Kathryn A; Chong, Terence W H; Rego, Thomas; Cox, Kay L; Anstey, Kaarin J; Westphal, Alissa; Moorhead, Rebecca; Southam, Jenny; Lai, Rhoda; You, Emily; et al. (J Alzheimers Dis, 2023)
BACKGROUND: People experiencing cognitive concerns and symptoms of depression or anxiety are at risk for Alzheimer's disease and dementia. We know physical activity can benefit cognition but understanding how to best support engagement is an ongoing challenge. Evidence-based conceptual models of factors underpinning physical activity engagement in target populations can inform intervention tailoring to address this challenge. OBJECTIVE: This study (part of a pragmatic physical activity implementation trial) aimed to develop a specified model of physical activity engagement in people experiencing depressive or anxiety symptoms and cognitive concerns, to enable optimized dementia risk reduction intervention tailoring. METHODS: We employed a qualitative design, triangulating data from three sources: semi-structured individual interviews with people experiencing cognitive concerns and mild to moderate depressive or anxiety symptoms; review of published evidence; and the Capability, Opportunity and Motivation system of behavior, an existing behavioral science model. Findings were integrated to develop a contextualized model of mechanisms of action for optimizing engagement. RESULTS: Twenty-one participants were interviewed, and 24 relevant papers included. Convergent and complementary themes extended understanding of intervention needs. Findings highlighted emotional regulation, capacities to enact intentions despite barriers, and confidence in existing skills as areas of population-specific need that have not previously been emphasized. The final model provides specificity, directionality, and linked approaches for intervention tailoring. CONCLUSION: This study demonstrated that people experiencing cognitive concerns and symptoms of depression or anxiety require different interventions to improve physical activity engagement. The novel model can enable more precise intervention tailoring, and, ultimately, benefits for a key at-risk population.

Plasma Glial Fibrillary Acidic Protein Is Associated with 18F-SMBT-1 PET: Two Putative Astrocyte Reactivity Biomarkers for Alzheimer's Disease. - Chatterjee, Pratishtha; Doré, Vincent; Pedrini, Steve; Krishnadas, Natasha; Thota, Rohith; Bourgeat, Pierrick; Ikonomovic, Milos D; Rainey-Smith, Stephanie R; Burnham, Samantha C; Fowler, Christopher; Taddei, Kevin; Mulligan, Rachel; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Astrocyte reactivity is an early event along the Alzheimer's disease (AD) continuum. Plasma glial fibrillary acidic protein (GFAP), posited to reflect astrocyte reactivity, is elevated across the AD continuum from preclinical to dementia stages. Monoamine oxidase-B (MAO-B) is also elevated in reactive astrocytes observed using 18F-SMBT-1 PET in AD. OBJECTIVE: The objective of this study was to evaluate the association between the abovementioned astrocyte reactivity biomarkers. METHODS: Plasma GFAP and Aβ were measured using the Simoa® platform in participants who underwent brain 18F-SMBT-1 and Aβ-PET imaging, comprising 54 healthy control (13 Aβ-PET+ and 41 Aβ-PET-), 11 mild cognitively impaired (3 Aβ-PET+ and 8 Aβ-PET-) and 6 probable AD (5 Aβ-PET+ and 1 Aβ-PET-) individuals. Linear regressions were used to assess associations of interest. RESULTS: Plasma GFAP was associated with 18F-SMBT-1 signal in brain regions prone to early Aβ deposition in AD, such as the supramarginal gyrus (SG), posterior cingulate (PC), lateral temporal (LT) and lateral occipital cortex (LO). After adjusting for age, sex, APOE ɛ4 genotype, and soluble Aβ (plasma Aβ42/40 ratio), plasma GFAP was associated with 18F-SMBT-1 signal in the SG, PC, LT, LO, and superior parietal cortex (SP). On adjusting for age, sex, APOE ɛ4 genotype and insoluble Aβ (Aβ-PET), plasma GFAP was associated with 18F-SMBT-1 signal in the SG. CONCLUSION: There is an association between plasma GFAP and regional 18F-SMBT-1 PET, and this association appears to be dependent on brain Aβ load.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Astrocytes; Biomarkers; Brain; Cognitive Dysfunction; Glial Fibrillary Acidic Protein; Humans; Positron-Emission Tomography; tau Proteins

Poor Oral Health as a Risk Factor for Dementia in a Swedish Population: A Cohort Study with 40 Years of Follow-Up. - He, Fei; Luo, Huizi; Yin, Li; Roosaar, Ann; Axéll, Tony; Zhao, Hongwei; Ye, Weimin (J Alzheimers Dis, 2023)
BACKGROUND: Whether poor oral health is associated with dementia risk remains unclear. OBJECTIVE: We conducted a cohort study of 14,439 participants who were followed up for up to 40 years in Uppsala County, central Sweden, aiming to explore the association between poor oral health, namely the number of tooth loss, dental plaque status, and oral mucosal lesions, and the risk of dementia. METHODS: We used Cox proportional hazards regression model to derive cause-specific hazard ratios (HR) and corresponding 95% confidence intervals (CI), while adjusting for baseline potential confounders as well as a time-varying covariate, Charlson's Comorbidity Index score. RESULTS: Dementia risk was substantially higher among those with a higher number of tooth loss; compared to the group with tooth loss 0-10, the HRs were 1.21 (95% CI: 1.02, 1.42), 1.17 (95% CI: 0.97, 1.40), and 1.30 (95% CI: 1.09, 1.54) respectively for groups with increasing number of tooth loss. There was some evidence of dose-risk association in this study, with a HR of 1.10 (1.04, 1.18) comparing adjacent groups (ptrend = 0.001). In a stratified analysis by attained age, tooth loss was more pronouncedly associated with the risk of dementia onset before age 80 (those with 21-32 versus 0-10 lost teeth, HR = 1.82, (95% CI: 1.32, 2.51); HR = 1.22 (95% CI: 1.10, 1.35) comparing adjacent groups, ptrend < 0.001). CONCLUSION: In summary, there are some indications that poor oral health, as indicated by more tooth loss, is positively associated with an increased risk of dementia, especially for dementia onset before age 80.
Keywords: Aged, 80 and over; Cohort Studies; Dementia; Follow-Up Studies; Humans; Oral Health; Risk Factors; Sweden; Tooth Loss

Posttraumatic Stress and Traumatic Brain Injury: Cognition, Behavior, and Neuroimaging Markers in Vietnam Veterans. - Marcolini, Sofia; Rojczyk, Philine; Seitz-Holland, Johanna; Koerte, Inga K; Alosco, Michael L; Bouix, Sylvain (J Alzheimers Dis, 2023)
BACKGROUND: Posttraumatic stress disorder (PTSD) and traumatic brain injury (TBI) are common in Veterans and linked to behavioral disturbances, increased risk of cognitive decline, and Alzheimer's disease. OBJECTIVE: We studied the synergistic effects of PTSD and TBI on behavioral, cognitive, and neuroimaging measures in Vietnam war Veterans. METHODS: Data were acquired at baseline and after about one-year from male Veterans categorized into: PTSD, TBI, PTSD+TBI, and Veteran controls without PTSD or TBI. We applied manual tractography to examine white matter microstructure of three fiber tracts: uncinate fasciculus (N = 91), cingulum (N = 87), and inferior longitudinal fasciculus (N = 95). ANCOVAs were used to compare Veterans' baseline behavioral and cognitive functioning (N = 285), white matter microstructure, amyloid-β (N = 230), and tau PET (N = 120). Additional ANCOVAs examined scores' differences from baseline to follow-up. RESULTS: Veterans with PTSD and PTSD+TBI, but not Veterans with TBI only, exhibited poorer behavioral and cognitive functioning at baseline than controls. The groups did not differ in baseline white matter, amyloid-β, or tau, nor in behavioral and cognitive functioning, and tau accumulation change. Progression of white matter abnormalities of the uncinate fasciculus in Veterans with PTSD compared to controls was observed; analyses in TBI and PTSD+TBI were not run due to insufficient sample size. CONCLUSIONS: PTSD and PTSD+TBI negatively affect behavioral and cognitive functioning, while TBI does not contribute independently. Whether progressive decline in uncinate fasciculus microstructure in Veterans with PTSD might account for cognitive decline should be further studied. Findings did not support an association between PTSD, TBI, and Alzheimer's disease pathology based on amyloid and tau PET.

The Potential Role of Selection Bias in the Association Between Coronary Atherosclerosis and Cognitive Impairment. - Yahagi-Estevam, Maristella; Farias-Itao, Daniela Souza; Leite, Renata Elaine Paraizo; Rodriguez, Roberta Diehl; Pasqualucci, Carlos Augusto; Nitrini, Ricardo; Jacob-Filho, Wilson; Power, Melinda C; Suemoto, Claudia Kimie (J Alzheimers Dis, 2023)
BACKGROUND: Coronary atherosclerosis assessed in vivo was associated with cognitive impairment; however, conflicting findings have been reported in autopsy samples. OBJECTIVE: Our aims were to assess the association between atherosclerotic stenosis in the coronary arteries and cognitive impairment and to investigate the possibility of selection bias in an autopsy study. METHODS: Coronary arteries were collected, and the largest luminal stenosis was measured. Sociodemographic, clinical, and cognitive information were reported by a reliable next-of-kin. The association was tested using logistic and linear regressions adjusted for sociodemographic and clinical variables. We restricted the sample to individuals that were born in 1935 or earlier and stratified the analysis by cause of death to investigate the role of selection bias. RESULTS: In 253 participants (mean age = 78.0±8.5 years old, 48% male), stenosis was not associated with cognitive impairment (OR = 0.85, 95% CI = 0.69; 1.06, p = 0.15). In individuals who were born before 1936 in the absence of cardiovascular disease as the cause of death, greater stenosis was associated with cognitive impairment (OR = 4.02, 95% CI = 1.39; 11.6, p = 0.01). On the other hand, this association was not present among those born in 1935 or earlier who died of cardiovascular diseases (OR = 0.83, 95% CI = 0.60; 1.16, p = 0.28). CONCLUSION: We found that higher coronary stenosis was associated with cognitive impairment only in individuals born in 1935 or earlier and who had not died from cardiovascular diseases. Selection bias may be an important issue when investigating risk factors for chronic degenerative diseases in older individuals using autopsy samples.

Precision Medicine Approach to Alzheimer's Disease: Rationale and Implications. - Bredesen, Dale E; Toups, Kat; Hathaway, Ann; Gordon, Deborah; Chung, Henrianna; Raji, Cyrus; Boyd, Alan; Hill, Benjamin D; Hausman-Cohen, Sharon; Attarha, Mouna; Chwa, Won Jong; Kurakin, Alexei; et al. (J Alzheimers Dis, 2023)
The neurodegenerative disease field has enjoyed extremely limited success in the development of effective therapeutics. One potential reason is the lack of disease models that yield accurate predictions and optimal therapeutic targets. Standard clinical trials have pre-determined a single treatment modality, which may be unrelated to the primary drivers of neurodegeneration. Recent proof-of-concept clinical trials using a precision medicine approach suggest a new model of Alzheimer's disease (AD) as a chronic innate encephalitis that creates a network insufficiency. Identifying and addressing the multiple potential contributors to cognitive decline for each patient may represent a more effective strategy. Here we review the rationale for a precision medicine approach in prevention and treatment of cognitive decline associated with AD. Results and implications from recent proof-of-concept clinical trials are presented. Randomized controlled trials, with much larger patient numbers, are likely to be significant to establishing precision medicine protocols as a standard of care for prevention and treatment of cognitive decline. Furthermore, combining this approach with the pharmaceutical approach offers the potential for enhanced outcomes. However, incorporating precision medicine approaches into everyday evaluation and care, as well as future clinical trials, would require fundamental changes in trial design, IRB considerations, funding considerations, laboratory evaluation, personalized treatment plans, treatment teams, and ultimately in reimbursement guidelines. Nonetheless, precision medicine approaches to AD, based on a novel model of AD pathophysiology, offer promise that has not been realized to date with monotherapeutic approaches.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Humans; Neurodegenerative Diseases; Precision Medicine

Progression from Prodromal Alzheimer's Disease to Mild Alzheimer's Disease Dementia in the Verubecestat APECS Study: Adjudicating Diagnostic Transitions. - Voss, Tiffini; Kost, James; Mercer, Swati Pal; Furtek, Christine; Randolph, Christopher; Lines, Christopher; Egan, Michael F; Cummings, Jeffrey L (J Alzheimers Dis, 2023)
BACKGROUND: Delay of progression from prodromal Alzheimer's disease (AD) to dementia is an important outcome in AD trials. Centralized adjudication is intended to improve the consistency of dementia diagnosis but has not been scrutinized. OBJECTIVE: To evaluate centralized adjudication for determining progression to dementia compared with Site Investigator opinion or change in Clinical Dementia Rating (CDR). METHODS: We used data from the 2-year APECS trial of verubecestat versus placebo in 1,451 prodromal AD participants. Cases were triggered for central adjudication if: 1) the Site Investigator judged the participant had progressed to dementia, or 2) the participant's CDR sum-of-boxes score increased ≥2 points from baseline. Post-hoc analyses were performed on pooled treatment-group data to compare methods of assessing progression. RESULTS: 581/1,451 (40% ) participants had changes triggering adjudication and most (83% ) were confirmed as progression to dementia. Only 66% of those who met CDR criteria (regardless of whether they also met Site Investigator criteria) were adjudicated to have progressed to dementia and just 15% of those who met only CDR criteria were adjudicated to have progressed, representing 5% of progressors. In contrast, 99% of those who met Site Investigator criteria (regardless of whether they also met CDR criteria) were adjudicated to have progressed, and the same was true for those who met only Site Investigator criteria. CONCLUSION: A positive Site Investigator opinion is an excellent predictor for a positive adjudication decision regarding onset of dementia. Conversely, sole use of CDR sum-of-boxes change ≥2 is inadequate. The benefit of centralized adjudication appears doubtful.

Psychopharmacological Medication Use in Frontotemporal Dementia at the Time of Diagnosis: Comparison with Alzheimer's Disease. - Katisko, Kasper; Krüger, Johanna; Soppela, Helmi; Hartikainen, Päivi; Haapasalo, Annakaisa; Remes, Anne M; Solje, Eino (J Alzheimers Dis, 2023)
BACKGROUND: Due to the significant presence of neuropsychiatric symptoms in patients with frontotemporal dementia (FTD) spectrum disorders, psychiatric misdiagnoses, diagnostic delay, and use of psychiatric treatments are common prior to the FTD diagnosis. Furthermore, treatment of diagnosed FTD patients mainly relies on off-label psychopharmacological approaches. Currently, limited real-world data are available regarding the actual use of psychopharmacological medications in FTD. OBJECTIVE: To evaluate psychopharmacological medication use at the time of FTD diagnosis. METHODS: Psychopharmacological medication use was evaluated in a Finnish FTD cohort containing 222 FTD patients, including the major clinical disease phenotypes (behavioral, language, and motor variants) and genetic patients carrying the C9orf72 repeat expansion. A cohort of 214 Alzheimer's disease (AD) patients was used as a neurodegenerative disease reference group. RESULTS: Active use of psychopharmacological medications at the time of diagnosis was significantly more common in FTD compared to AD, especially in the case of antidepressants (26.1% versus 15.0%, OR = 2.01, p = 0.008), antipsychotics (23.9% versus 9.3%, OR = 3.15, p < 0.001), and mood-stabilizers (6.3% versus 1.9%, OR = 2.93, p = 0.085; not statistically significant), whereas the use of cholinesterase inhibitors or memantine was nearly nonexistent in FTD patients. Female gender and behavioral variant of FTD phenotype alongside with depressive and psychotic symptoms were the most prominent factors associating with the use of these medications among the FTD spectrum patients. CONCLUSION: Use of off-label psychopharmacological medication and polypharmacy is substantially common at the time of FTD diagnosis. This likely reflects the challenges in using symptom-driven treatment approaches, especially prior to the eventual diagnosis.
Keywords: Alzheimer Disease; Delayed Diagnosis; Female; Frontotemporal Dementia; Humans; Memantine; Neurodegenerative Diseases

Refining Risk for Alzheimer's Disease Among Heterozygous APOEɛ4 Carriers. - Patel, Smita; Wei, Jun; Shi, Zhuqing; Rifkin, Andrew S; Zheng, S Lilly; Gelfman, Elizabeth; Duggan, David; Helfand, Brian T; Hulick, Peter J; Xu, Jianfeng (J Alzheimers Dis, 2023)
In a large population-based cohort, we show not all heterozygous APOEɛ4 carriers are at increased risk for Alzheimer's disease (AD); a significantly higher AD proportion was only found for ɛ3/ɛ4, not ɛ2/ɛ4. Among ɛ3/ɛ4 carriers (24% in the cohort), the AD proportion differed considerably by polygenic risk score (PRS). In particular, the AD proportion was lower than the entire cohort for subjects in the bottom 20-percentile PRS and was higher than that of homozygous ɛ4 carriers for subjects at the top 5th-percentile PRS. Family history was no longer a significant predictor of AD risk after adjusting APOE and PRS.
Keywords: Alzheimer Disease; Apolipoprotein E4; Apolipoproteins E; Heterozygote; Homozygote; Humans

Reliability and Validity of Self-Reported Vascular Risk Factors: Hypertension, Diabetes, and Heart Disease, in a Multi-Ethnic Community Based Study of Aging and Dementia. - Lee, Annie J; Sanchez, Didi; Reyes-Dumeyer, Dolly; Brickman, Adam M; Lantigua, Rafael A; Vardarajan, Badri N; Mayeux, Richard (J Alzheimers Dis, 2023)
BACKGROUND: Queries for the presence of cardiovascular and cerebrovascular risk factors are typically assessed through self-report. However, the reliability and validity of self-reported cardiovascular and cerebrovascular risk factors remains inconsistent in aging research. OBJECTIVE: To determine the reliability and validity of the most frequently self-reported vascular risk factors: hypertension, diabetes, and heart disease. METHODS: 1,870 individuals aged 65 years or older among African Americans, Caribbean Hispanics, and white non-Hispanic individuals were recruited as part of a community study of aging and dementia. We assessed the reliability, validity, sensitivity, specificity, and percent agreement of self-reported hypertension, diabetes, and heart disease, in comparison with direct measures of blood pressure, hemoglobin A1c (HbA1c), and medication use. The analyses were subsequently stratified by age, sex, education, and ethnic group. RESULTS: Reliability of self-reported for hypertension, diabetes, and heart disease was excellent. Agreement between self-reports and clinical measures was moderate for hypertension (kappa: 0.58), good for diabetes (kappa: 0.76-0.79), and moderate for heart disease (kappa: 0.45) differing slightly by age, sex, education, and ethnic group. Sensitivity and specificity for hypertension was 88.6% -78.1%, for diabetes was 87.7% -92.0% (HbA1c ≥6.5%) or 92.7% -92.8% (HbA1c ≥7%), and for heart disease was 85.8% -75.5%. Percent agreement of self-reported was 87.0% for hypertension, 91.6% -92.6% for diabetes, and 77.4% for heart disease. CONCLUSION: Ascertainment of self-reported histories of hypertension, diabetes, and heart disease are reliable and valid compared to direct measurements or medication use.

A Remotely Coached Multimodal Lifestyle Intervention for Alzheimer's Disease Ameliorates Functional and Cognitive Outcomes. - Roach, Jared C; Rapozo, Molly K; Hara, Junko; Glusman, Gwênlyn; Lovejoy, Jennifer; Shankle, William R; Hood, Leroy (J Alzheimers Dis, 2023)
BACKGROUND: Comprehensive treatment of Alzheimer's disease and related dementias (ADRD) requires not only pharmacologic treatment but also management of existing medical conditions and lifestyle modifications including diet, cognitive training, and exercise. Personalized, multimodal therapies are needed to best prevent and treat Alzheimer's disease (AD). OBJECTIVE: The Coaching for Cognition in Alzheimer's (COCOA) trial was a prospective randomized controlled trial to test the hypothesis that a remotely coached multimodal lifestyle intervention would improve early-stage AD. METHODS: Participants with early-stage AD were randomized into two arms. Arm 1 (N = 24) received standard of care. Arm 2 (N = 31) additionally received telephonic personalized coaching for multiple lifestyle interventions. The primary outcome was a test of the hypothesis that the Memory Performance Index (MPI) change over time would be better in the intervention arm than in the control arm. The Functional Assessment Staging Test was assessed for a secondary outcome. COCOA collected psychometric, clinical, lifestyle, genomic, proteomic, metabolomic, and microbiome data at multiple timepoints (dynamic dense data) across two years for each participant. RESULTS: The intervention arm ameliorated 2.1 [1.0] MPI points (mean [SD], p = 0.016) compared to the control over the two-year intervention. No important adverse events or side effects were observed. CONCLUSION: Multimodal lifestyle interventions are effective for ameliorating cognitive decline and have a larger effect size than pharmacological interventions. Dietary changes and exercise are likely to be beneficial components of multimodal interventions in many individuals. Remote coaching is an effective intervention for early stage ADRD. Remote interventions were effective during the COVID pandemic.

The Role of Interferon-α in Neurodegenerative Diseases: A Systematic Review. - Hui, Brendan Su Mee; Zhi, Lee Rui; Retinasamy, Thaarvena; Arulsamy, Alina; Law, Christine Shing Wei; Shaikh, Mohd Farooq; Yeong, Keng Yoon (J Alzheimers Dis, 2023)
BACKGROUND: Neurodegenerative diseases (NDs) impose significant financial and healthcare burden on populations all over the world. The prevalence and incidence of NDs have been observed to increase dramatically with age. Hence, the number of reported cases is projected to increase in the future, as life spans continues to rise. Despite this, there is limited effective treatment against most NDs. Interferons (IFNs), a family of cytokines, have been suggested as a promising therapeutic target for NDs, particularly IFN-α, which governs various pathological pathways in different NDs. OBJECTIVE: This systematic review aimed to critically appraise the currently available literature on the pathological role of IFN-α in neurodegeneration/NDs. METHODS: Three databases, Scopus, PubMed, and Ovid Medline, were utilized for the literature search. RESULTS: A total of 77 journal articles were selected for critical evaluation, based on the inclusion and exclusion criteria. The studies selected and elucidated in this current systematic review have showed that IFN-α may play a deleterious role in neurodegenerative diseases through its strong association with the inflammatory processes resulting in mainly neurocognitive impairments. IFN-α may be displaying its neurotoxic function via various mechanisms such as abnormal calcium mineralization, activation of STAT1-dependent mechanisms, and increased quinolinic acid production. CONCLUSION: The exact role IFN-α in these neurodegenerative diseases have yet to be determine due to a lack in more recent evidence, thereby creating a variability in the role of IFN-α. Future investigations should thus be conducted, so that the role played by IFN-α in neurodegenerative diseases could be delineated.
Keywords: Cytokines; Databases, Factual; Humans; Interferon-alpha; Neurodegenerative Diseases

TDP-43 Pathology in the Setting of Intermediate and High Alzheimer's Disease Neuropathologic Changes: A Preliminary Evaluation Across Ethnoracial Groups. - Huie, Emily Z; Escudero, Anthony; Saito, Naomi; Harvey, Danielle; Nguyen, My-Le; Lucot, Katherine L; LaGrande, Jayne; Mungas, Dan; DeCarli, Charles; Lamar, Melissa; Schneider, Julie A; Kapasi, Alifiya; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Transactive Response DNA Binding Protein 43 kDa (TDP-43) pathology is frequently found in cases with Alzheimer's disease (AD). TDP-43 pathology is associated with hippocampal atrophy and greater AD severity denoted by cognition and clinical representation. Current TDP-43 pathology studies are predominantly based on non-Hispanic White cohorts. OBJECTIVE: We sought to evaluate the presence of TDP-43 pathology across ethnoracial groups utilizing the National Alzheimer's Coordinating Center; a database containing data from over 29 institutions across the United States. Cases (N = 1,135: Hispanics/Latinos = 29, African Americans/Black Americans = 51, Asians/Asian Americans = 10, American Indians/Alaskan Natives = 2, non-Hispanic White = 1,043) with intermediate/high AD having data on TDP-43 pathology in the amygdala, hippocampus, entorhinal cortex, and neocortex. METHODS: TDP-43 pathology frequency in each neuroanatomic region among ethnoracial groups were compared using generalized linear mixed effects models with center as a random effect adjusting for age at death, education, and gender. RESULTS: Although groups were imbalanced, there was no significant difference across ethnoracial groups based on TDP-43 pathology (p = 0.84). With respect to neuroanatomical regions evaluated, there were no significant differences across ethnoracial groups (p-values > 0.06). There were also no significant differences for age at death and gender ratios across ethnoracial groups based on TDP-43 pathology. Although not statistically significant, TDP-43 pathology was present less often in Hispanic/Latinos (34%) when compared to non-Hispanic Whites (46%). CONCLUSION: While this is a preliminary evaluation, it highlights the need for diverse cohorts and on TDP-43 pathology research across ethnoracial groups. This is the first study to our knowledge having a focus on the neuroanatomical distribution of TDP-43 deposits in Hispanic/Latino decedents with AD.

Timing of Alzheimer's Disease by Intellectual Disability Level in Down Syndrome. - Hartley, Sigan L; Fleming, Victoria; Schworer, Emily K; Peven, Jamie; Handen, Benjamin L; Krinsky-McHale, Sharon; Hom, Christy; Lee, Laisze; Tudorascu, Dana L; Laymon, Charles; Minhas, Davneet; Luo, Weiquan; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Trisomy 21 causes Down syndrome (DS) and is a recognized cause of early-onset Alzheimer's disease (AD). OBJECTIVE: The current study sought to determine if premorbid intellectual disability level (ID) was associated with variability in age-trajectories of AD biomarkers and cognitive impairments. General linear mixed models compared the age-trajectory of the AD biomarkers PET Aβ and tau and cognitive decline across premorbid ID levels (mild, moderate, and severe/profound), in models controlling trisomy type, APOE status, biological sex, and site. METHODS: Analyses involved adults with DS from the Alzheimer's Biomarkers Consortium-Down Syndrome. Participants completed measures of memory, mental status, and visuospatial ability. Premorbid ID level was based on IQ or mental age scores prior to dementia concerns. PET was acquired using [11C] PiB for Aβ, and [18F] AV-1451 for tau. RESULTS: Cognitive data was available for 361 participants with a mean age of 45.22 (SD = 9.92) and PET biomarker data was available for 154 participants. There was not a significant effect of premorbid ID level by age on cognitive outcomes. There was not a significant effect of premorbid ID by age on PET Aβ or on tau PET. There was not a significant difference in age at time of study visit of those with mild cognitive impairment-DS or dementia by premorbid ID level. CONCLUSION: Findings provide robust evidence of a similar time course in AD trajectory across premorbid ID levels, laying the groundwork for the inclusion of individuals with DS with a variety of IQ levels in clinical AD trials.

Two-Year Changes in Physical Activity and Concurrent Changes in Cognitive Function in a Cohort of Adults with Metabolic Syndrome. - Rognoni, Teresa; Fernández-Matarrubia, Marta; Martínez-González, Miguel Ángel; Salas-Salvadó, Jordi; Corella, Dolores; Castañer, Olga; Martínez, J Alfredo; Alonso-Gómez, Ángel M; Gómez-Gracia, Enrique; Vioque, Jesús; Romaguera, Dora; López-Miranda, José; et al. (J Alzheimers Dis, 2023)
BACKGROUND: It has been proposed that physical activity (PA) could prevent cognitive decline. OBJECTIVE: To evaluate the association between changes in PA and changes in cognitive function in a cohort of adults with metabolic syndrome. METHODS: Longitudinal observational study including 5,500 adults (mean age 65 years, SD = 5; women = 49.3%) with metabolic syndrome. Participants underwent physical activity measurements and cognitive evaluation at baseline and at two-years of follow-up. PA was quantified using the Minnesota questionnaire-shortened version. Cognitive function was evaluated using a battery of tests: Mini-Mental Test Examination, Clock Drawing Test, Trail Making Test A and B, Verbal Fluency Test, and Digit Span. The primary outcome was change in cognition at two-year follow-up, as measured through the Global Composite Score (GCS) of all neuropsychological tests. Multivariable-adjusted linear regression models were fitted with baseline PA and their changes as the main exposures and changes in cognitive function as the outcome. RESULTS: No significant association was found between PA levels (or their changes) and changes in cognitive function, as measured by the GCS. A greater increase in PA levels was associated with a more favorable two-year change in performance on the Trail Making Test A (Q4 versus Q1: b = -2.15, 95% CI -4.25 to -0.05; p-trend = 0.024). No significant association was found for other neuropsychological test. CONCLUSION: Our results do not support an association between increases in PA and the evolution of the global cognitive function at two-year follow-up, but they suggested a possible beneficial effect of PA on attentional function in older adults.

Understanding the Involvement of microRNAs in Mitochondrial Dysfunction and Their Role as Potential Biomarkers and Therapeutic Targets in Parkinson's Disease. - Tryphena, Kamatham Pushpa; Anuradha, Urati; Kumar, Rohith; Rajan, Shruti; Srivastava, Saurabh; Singh, Shashi Bala; Khatri, Dharmendra Kumar (J Alzheimers Dis, 2023)
Parkinson's disease (PD) is the second most common neurodegenerative disease, affecting the elderly worldwide and causing significant movement impairments. The goal of PD treatment is to restore dopamine levels in the striatum and regulate movement symptoms. The lack of specific biomarkers for early diagnosis, as well as medication aimed at addressing the pathogenic mechanisms to decelerate the progression of dopaminergic neurodegeneration, are key roadblocks in the management of PD. Various pathogenic processes have been identified to be involved in the progression of PD, with mitochondrial dysfunction being a major contributor to the disease's pathogenesis. The regulation of mitochondrial functions is influenced by a variety of factors, including epigenetics. microRNAs (miRNAs) are epigenetic modulators involved in the regulation of gene expression and regulate a variety of proteins that essential for proper mitochondrial functioning. They are found to be dysregulated in PD, as evidenced by biological samples from PD patients and in vitro and in vivo research. In this article, we attempt to provide an overview of several miRNAs linked to mitochondrial dysfunction and their potential as diagnostic biomarkers and therapeutic targets in PD.
Keywords: Aged; Biomarkers; Humans; MicroRNAs; Mitochondria; Neurodegenerative Diseases; Parkinson Disease

Untangling the Role of TREM2 in Conjugation with Microglia in Neuronal Dysfunction: A Hypothesis on a Novel Pathway in the Pathophysiology of Alzheimer's Disease. - Basha, Sk Chand; Ramaiah, Mekala Janaki; Kosagisharaf, Jagannatha Rao (J Alzheimers Dis, 2023)
Alzheimer's disease (AD) is a complex neurodegenerative disorder involving heterogenous pathophysiological characteristics, which has become a challenge to therapeutics. The major pathophysiology of AD comprises amyloid-β (Aβ), tau, oxidative stress, and apoptosis. Recent studies indicate the significance of Triggering receptor expressed on myeloid cells 2 (TREM2) and its mutant variants in AD. TREM2 are the transmembrane receptors of microglial cells that performs a broad range of physiological cell processes. Phagocytosis of Aβ is one of the physiological roles of TREM2, which plays a pivotal role in AD progression. R47H, a mutant variant of TREM2, increases the risk of AD by impairing TREM2-Aβ binding. Inconclusive evidence regarding the TREM2 signaling cascade mechanism of Aβ phagocytosis motivates the current review to propose a new hypothesis. The review systematically assesses the cross talk between TREM2 and other AD pathological domains and the influence of TREM2 on amyloid and tau seeding. Disease associated microglia (DAM), a novel state of microglia with unique transcriptional and functional signatures reported in neurodegenerative conditions, also depend on the TREM2 pathway for its differentiation. DAM is suggested to have a neuroprotective role. We hypothesize that TREM2, along with its signaling adaptors and endogenous proteins, play a key role in ameliorating Aβ clearance. We indicate that TREM2 has the potential to ameliorate the Aβ burden, though with differential clearance ability and may act as a potential therapeutic target.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Humans; Membrane Glycoproteins; Microglia; Neurons; Receptors, Immunologic

Validation of a Multivariate Prediction Model of the Clinical Progression of Alzheimer's Disease in a Community-Dwelling Multiethnic Cohort. - Stallard, Eric; Kociolek, Anton; Jin, Zhezhen; Ryu, Hyunnam; Lee, Seonjoo; Cosentino, Stephanie; Zhu, Carolyn; Gu, Yian; Fernandez, Kayri; Hernandez, Michelle; Kinosian, Bruce; Stern, Yaakov (J Alzheimers Dis, 2023)
BACKGROUND: The major aims of the three Predictors Studies have been to further our understanding of Alzheimer's disease (AD) progression sufficiently to predict the length of time from disease onset to major disease outcomes in individual patients with AD. OBJECTIVES: To validate a longitudinal Grade of Membership (L-GoM) prediction algorithm developed using clinic-based, mainly white patients from the Predictors 2 Study in a statistically representative community-based sample of Hispanic (N = 211) and non-Hispanic (N = 62) older adults (with 60 males and 213 females) from the Predictors 3 Study and extend the algorithm to mild cognitive impairment (MCI). METHODS: The L-GoM model was applied to data collected at the initial Predictors 3 visit for 150 subjects with AD and 123 with MCI. Participants were followed annually for up to seven years. Observed rates of survival and need for full-time care (FTC) were compared to those predicted by the algorithm. RESULTS: Initial MCI/AD severity in Predictors 3 was substantially higher than among clinic-based AD patients enrolled at the specialized Alzheimer's centers in Predictors 2. The observed survival and need for FTC followed the L-GoM model trajectories in individuals with MCI or AD, except for N = 32 subjects who were initially diagnosed with AD but reverted to a non-AD diagnosis on follow-up. CONCLUSION: These findings indicate that the L-GoM model is applicable to community-dwelling, multiethnic older adults with AD. They extend the use of the model to the prediction of outcomes for MCI. They also justify release of our L-GoM calculator at this time.

Alteration of Gut Microbiota in Alzheimer's Disease and Their Relation to the Cognitive Impairment. - Khedr, Eman M; Omeran, Nehad; Karam-Allah Ramadan, Haidi; Ahmed, Gellan K; Abdelwarith, Ahmed M (J Alzheimers Dis, 2022)
BACKGROUND: Dysbiosis of gut microbiota has been reported to be enrolled in the pathogenesis of Alzheimer's disease (AD). However, there is a lack of relevant studies on this topic in Egyptian patients with AD. OBJECTIVE: To investigate different species of gut microbiota in Egyptian patients with AD and correlate microbiota bacterial abundance with clinical data. METHODS: The study included 25 patients with AD and 25 healthy volunteers as age and sex-matched controls. Clinical data was taken for each patient, including medical history and examination; Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) were assessed for each participant. Bacterial DNA was extracted from stool, and abundance quantified via qPCR using 16S rRNA group-specific primers. RESULTS: Akkermansia, Enterobacteria, Bacteroidetes, Bacillus cereus, Prevotella, and Clostridium cluster IV were more abundant in the AD group than in the control group, although there was significantly less abundance of Bifidobacterium spp., Firmicutes, and Actinobacteria in patients with AD than in controls, whereas no such significance was found for lactic acid bacteria between both groups. Lactic acid bacteria and Prevotella abundance was negatively correlated with cognitive impairment (p = 0.03 with MMSE, and p = 0.03 with MoCA). Prevotella abundance was positively correlated with age of onset and duration of illness and negatively correlated with smoking and coronary heart disease (p = 0.007, p = 0.03, p = 0.035, and p = 0.047, respectively). CONCLUSION: The current work highlighted a significant relationship between AD and gut microbiota dysbiosis. A higher abundance of Prevotella species and lactic acid bacteria was correlated with cognition.
Keywords: Alzheimer Disease; Bacteria; Cognitive Dysfunction; Dysbiosis; Gastrointestinal Microbiome; Humans; RNA, Ribosomal, 16S

Association Between Plasma Biomarkers of Amyloid, Tau, and Neurodegeneration with Cerebral Microbleeds. - McCarter, Stuart J; Lesnick, Timothy G; Lowe, Val J; Rabinstein, Alejandro A; Przybelski, Scott A; Algeciras-Schimnich, Alicia; Ramanan, Vijay K; Jack, Clifford R; Petersen, Ronald C; Knopman, David S; Boeve, Bradley F; Kantarci, Kejal; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Cerebral microbleeds (CMBs) are a common vascular pathology associated with future intracerebral hemorrhage. Plasma biomarkers of amyloid, tau, and neurodegeneration may provide a screening avenue to identify those with CMBs, but evidence is conflicting. OBJECTIVE: To determine the association between plasma biomarkers (Aβ40, Aβ42, t-tau, p-tau181, p-tau217, neurofilament light chain (NfL)) and CMBs in a population-based study of aging and whether these biomarkers predict higher signal on Aβ-PET imaging in patients with multiple CMBs. METHODS: 712 participants from the Mayo Clinic Study of Aging with T2 * GRE MRI and plasma biomarkers were included. Biomarkers were analyzed utilizing Simoa (Aβ40, Aβ42, t-tau, NfL) or Meso Scale Discovery (p-tau181, p-tau217) platforms. Cross-sectional associations between CMBs, plasma biomarkers and Aβ-PET were evaluated using hurdle models and multivariable regression models. RESULTS: Among the 188 (26%) individuals with≥1 CMB, a lower plasma Aβ42/Aβ40 ratio was associated with more CMBs after adjusting for covariables (IRR 568.5 95% CI 2.8-116,127). No other biomarkers were associated with risk or number CMBs. In 81 individuals with≥2 CMBs, higher plasma t-tau, p-tau181, and p-tau217 all were associated with higher Aβ-PET signal, with plasma p-tau217 having the strongest predictive value (r2 0.603, AIC -53.0). CONCLUSION: Lower plasma Aβ42/Aβ40 ratio and higher plasma p-tau217 were associated with brain amyloidosis in individuals with CMBs from the general population. Our results suggest that in individuals with multiple CMBs and/or lobar intracranial hemorrhage that a lower plasma Aβ42/Aβ40 ratio or elevated p-tau217 may indicate underlying cerebral amyloid angiopathy.

Association of Brain Volume and Retinal Thickness in the Early Stages of Alzheimer's Disease. - Mathew, Sunu; WuDunn, Darrell; Mackay, Devin D; Vosmeier, Aaron; Tallman, Eileen F; Deardorff, Rachael; Harris, Alon; Farlow, Martin R; Brosch, Jared R; Gao, Sujuan; Apostolova, Liana G; Saykin, Andrew J; et al. (J Alzheimers Dis, 2022)
BACKGROUND: The eye has been considered a 'window to the brain,' and several neurological diseases including neurodegenerative conditions like Alzheimer's disease (AD) also show changes in the retina. OBJECTIVE: To investigate retinal nerve fiber layer (RNFL) thickness and its association with brain volume via magnetic resonance imaging (MRI) in older adults with subjective or objective cognitive decline. METHODS: 75 participants underwent ophthalmological and neurological evaluation including optical coherence tomography and MRI (28 cognitively normal subjects, 26 with subjective cognitive decline, 17 patients diagnosed with mild cognitive impairment, and 4 with AD). Differences in demographics, thickness of RNFL, and brain volume were assessed using ANCOVA, while partial Pearson correlations, covaried for age and sex, were used to compare thickness of the peripapillary RNFL with brain volumes, with p < 0.05 considered statistically significant. RESULTS: Mean RNFL thickness was significantly correlated with brain volumes, including global volume (right eye r = 0.235 p = 0.046, left eye r = 0.244, p = 0.037), temporal lobe (right eye r = 0.242 p = 0.039, left eye r = 0.290, p = 0.013), hippocampal (right eye r = 0.320 p = 0.005, left eye r = 0.306, p = 0.008), amygdala (left eye r = 0.332, p = 0.004), and occipital lobe (right eye r = 0.264 p = 0.024) volumes. CONCLUSION: RNFL thickness in both eyes was positively associated with brain volumes in subjects with subjective and objective cognitive decline. The RNFL, however, did not correlate with the disease, but the small sample number makes it important to conduct larger studies. RNFL thickness may be a useful non-invasive and inexpensive tool for detection of brain neurodegeneration and may assist with diagnosis and monitoring of progression and treatment in AD.

Association of Carotid Intima Media Thickening with Future Brain Region Specific Amyloid-β Burden. - Baradaran, Hediyeh; Peloso, Gina M; Polak, Joseph F; Killiany, Ronald J; Ghosh, Saptaparni; DeCarli, Charles S; Thibault, Emma G; Sperling, Reisa A; Johnson, Keith A; Beiser, Alexa; Romero, Jose R; Seshadri, Sudha (J Alzheimers Dis, 2022)
BACKGROUND: Carotid atherosclerosis is associated with cognitive impairment and dementia, though there is limited evidence of a direct link between carotid disease and amyloid-β (Aβ) burden. OBJECTIVE: We studied the association of baseline and progressive carotid intima media thickness (CIMT) with Aβ on 11C-Pittsburgh Compound B (PiB) to determine if those with carotid atherosclerosis would have higher Aβ burden. METHODS: We studied 47 participants from the Framingham Offspring cohort with carotid ultrasounds measuring CIMT at their 6th clinic examination (aged 49.5±5.7 years) and an average of 9.6 years later, and PiB imaging measuring Aβ on average 22.1 years post baseline. We used multivariate linear regression analyses to relate baseline, follow-up, mean, and progression of internal carotid artery (ICA) and common carotid artery (CCA) CIMT to Aβ in brain regions associated with Alzheimer's disease (AD) and related dementias (ADRD), adjusting for age, sex, and other vascular risk factors. RESULTS: Participants with higher mean ICA IMT had more Aβ in the precuneus (beta±standard error [β±SE]: 0.466±0.171 mm, p = 0.01) and the frontal, lateral, and retrosplenial regions (β±SE: 0.392±0.164 mm, p = 0.022) after adjusting for age, sex, vascular risk factors, and medication use. We did not find an association between any CCA IMT measures and Aβ or progression of ICA or CCA IMT and Aβ. CONCLUSION: Carotid atherosclerosis, as measured by ICA IMT, is associated with increased Aβ burden later in life. These findings support a link between vascular disease and AD/ADRD pathophysiology.

Association of Cholinergic Basal Forebrain Volume and Functional Connectivity with Markers of Inflammatory Response in the Alzheimer's Disease Spectrum. - Teipel, Stefan J; Dyrba, Martin; Ballarini, Tommaso; Brosseron, Frederic; Bruno, Davide; Buerger, Katharina; Cosma, Nicoleta-Carmen; Dechent, Peter; Dobisch, Laura; Düzel, Emrah; Ewers, Michael; Fliessbach, Klaus; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Inflammation has been described as a key pathogenic event in Alzheimer's disease (AD), downstream of amyloid and tau pathology. Preclinical and clinical data suggest that the cholinergic basal forebrain may moderate inflammatory response to different pathologies. OBJECTIVE: To study the association of cholinergic basal forebrain volume and functional connectivity with measures of neuroinflammation in people from the AD spectrum. METHODS: We studied 261 cases from the DELCODE cohort, including people with subjective cognitive decline, mild cognitive impairment, AD dementia, first degree relatives, and healthy controls. Using Bayesian ANCOVA, we tested associations of MRI indices of cholinergic basal forebrain volume and functional connectivity with cerebrospinal fluid (CSF) levels of sTREM2 as a marker of microglia activation, and serum levels of complement C3. Using Bayesian elastic net regression, we determined associations between basal forebrain measures and a large inflammation marker panel from CSF and serum. RESULTS: We found anecdotal to moderate evidence in favor of the absence of an effect of basal forebrain volume and functional connectivity on CSF sTREM2 and serum C3 levels both in Aβ42/ptau-positive and negative cases. Bayesian elastic net regression identified several CSF and serum markers of inflammation that were associated with basal forebrain volume and functional connectivity. The effect sizes were moderate to small. CONCLUSION: Our data-driven analyses generate the hypothesis that cholinergic basal forebrain may be involved in the neuroinflammation response to Aβ42 and phospho-tau pathology in people from the AD spectrum. This hypothesis needs to be tested in independent samples.
Keywords: Aged; Alzheimer Disease; Basal Forebrain; Biomarkers; Cholinergic Agents; Cognitive Dysfunction; Cohort Studies; Female; Humans; Inflammation; Magnetic Resonance Imaging; Male

Associations Between Vascular Risk Factor and Perivascular Spaces in Adults with Intact Cognition, Mild Cognitive Impairment, and Dementia. - Rundek, Tatjana; Del Brutto, Victor; Goryawala, Mohammed; Dong, Chuanhui; Agudelo, Christian; Saporta, Anita Seixas; Merritt, Stacy; Camargo, Christian; Ariko, Taylor; Loewenstein, David A; Duara, Ranjan; Haq, Ihtsham (J Alzheimers Dis, 2022)
BACKGROUND: Perivascular spaces (PVS) are fluid-filled compartments surrounding small intracerebral vessels that transport fluid and clear waste. OBJECTIVE: We examined associations between PVS count, vascular and neurodegenerative risk factors, and cognitive status among the predominantly Hispanic participants of the FL-VIP Study of Alzheimer's Disease Risk. METHODS: Using brain MRI (n = 228), we counted PVS in single axial image through the basal ganglia (BG) and centrum semiovale (CSO). PVS per region were scored as 0 (none), 1 (<10), 2 (11-20), 3 (21-40), and 4 (>40). Generalized linear models examined PVS associations with vascular risk factors and a composite vascular comorbidity risk (VASCom) score. RESULTS: Our sample (mean age 72±8 years, 61% women, 60% Hispanic, mean education 15±4 years, 33% APOE4 carriers) was 59% hypertensive, 21% diabetic, 66% hypercholesteremic, and 30% obese. Mean VASCom score was 2.3±1.6. PVS scores ranged from 0-4 in the BG (mean 1.3±0.7) and CSO (mean 1.2±0.9), and 0-7 combined (mean 2.5±1.4). In multivariable regression models, BG PVS was associated with age (β= 0.03/year, p <  0.0001), Hispanic ethnicity (β= 0.29, p = 0.01), education (β= 0.04/year, p = 0.04), and coronary bypass surgery (β= 0.93, p = 0.02). CSO PVS only associated with age (β= 0.03/year, p <  0.01). APOE4 and amyloid-β were not associated with PVS. CONCLUSION: BG PVS may be a marker of subclinical cerebrovascular disease. Further research is needed to validate associations and identify mechanisms linking BG PVS and cerebrovascular disease markers. PVS may be a marker of neurodegeneration despite our negative preliminary findings and more research is warranted. The association between BG PVS and Hispanic ethnicity also requires further investigation.

Behavioral and Psychological Symptoms of Dementia in Different Dementia Disorders: A Large-Scale Study of 10,000 Individuals. - Schwertner, Emilia; Pereira, Joana B; Xu, Hong; Secnik, Juraj; Winblad, Bengt; Eriksdotter, Maria; Nägga, Katarina; Religa, Dorota (J Alzheimers Dis, 2022)
BACKGROUND: The majority of individuals with dementia will suffer from behavioral and psychological symptoms of dementia (BPSD). These symptoms contribute to functional impairment and caregiver burden. OBJECTIVE: To characterize BPSD in Alzheimer's disease (AD), vascular dementia (VaD), mixed (Mixed) dementia, Parkinson's disease dementia (PDD), dementia with Lewy bodies (DLB), frontotemporal dementia (FTD), and unspecified dementia in individuals residing in long-term care facilities. METHODS: We included 10,405 individuals with dementia living in long-term care facilities from the Swedish registry for cognitive/dementia disorders (SveDem) and the Swedish BPSD registry. BPSD was assessed with the Neuropsychiatric Inventory - Nursing Home Version (NPI-NH). Multivariate logistic regression models were used to evaluate the associations between dementia diagnoses and different BPSDs. RESULTS: The most common symptoms were aberrant motor behavior, agitation, and irritability. Compared to AD, we found a lower risk of delusions (in FTD, unspecified dementia), hallucinations (FTD), agitation (VaD, PDD, unspecified dementia), elation/euphoria (DLB), anxiety (Mixed, VaD, unspecified dementia), disinhibition (in PDD), irritability (in DLB, FTD, unspecified dementia), aberrant motor behavior (Mixed, VaD, unspecified dementia), and sleep and night-time behavior changes (unspecified dementia). Higher risk of delusions (DLB), hallucinations (DLB, PDD), apathy (VaD, FTD), disinhibition (FTD), and appetite and eating abnormalities (FTD) were also found in comparison to AD. CONCLUSION: Although individuals in our sample were diagnosed with different dementia disorders, they all exhibited aberrant motor behavior, agitation, and irritability. This suggests common underlying psychosocial or biological mechanisms. We recommend prioritizing these symptoms while planning interventions in long-term care facilities.
Keywords: Alzheimer Disease; Behavioral Symptoms; Dementia, Vascular; Frontotemporal Dementia; Hallucinations; Humans; Parkinson Disease

Brain Tissue-Derived Extracellular Vesicles in Alzheimer's Disease Display Altered Key Protein Levels Including Cell Type-Specific Markers. - Huang, Yiyao; Driedonks, Tom A P; Cheng, Lesley; Rajapaksha, Harinda; Routenberg, David A; Nagaraj, Rajini; Redding, Javier; Arab, Tanina; Powell, Bonita H; Pletniková, Olga; Troncoso, Juan C; Zheng, Lei; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Brain tissue-derived extracellular vesicles (bdEVs) play neurodegenerative and protective roles, including in Alzheimer's disease (AD). Extracellular vesicles (EVs) may also leave the brain to betray the state of the CNS in the periphery. Only a few studies have profiled the proteome of bdEVs and source brain tissue. Additionally, studies focusing on bdEV cell type-specific surface markers are rare. OBJECTIVE: We aimed to reveal the pathological mechanisms inside the brain by profiling the tissue and bdEV proteomes in AD patients. In addition, to indicate targets for capturing and molecular profiling of bdEVs in the periphery, CNS cell-specific markers were profiled on the intact bdEV surface. METHODS: bdEVs were separated and followed by EV counting and sizing. Brain tissue and bdEVs from age-matched AD patients and controls were then proteomically profiled. Total tau (t-tau), phosphorylated tau (p-tau), and antioxidant peroxiredoxins (PRDX) 1 and 6 were measured by immunoassay in an independent bdEV separation. Neuron, microglia, astrocyte, and endothelia markers were detected on intact EVs by multiplexed ELISA. RESULTS: Overall, concentration of recovered bdEVs was not affected by AD. Proteome differences between AD and control were more pronounced for bdEVs than for brain tissue. Levels of t-tau, p-tau, PRDX1, and PRDX6 were significantly elevated in AD bdEVs compared with controls. Release of certain cell-specific bdEV markers was increased in AD. CONCLUSION: Several bdEV proteins are involved in AD mechanisms and may be used for disease monitoring. The identified CNS cell markers may be useful tools for peripheral bdEV capture.

Cancer and Vascular Comorbidity Effects on Dementia Risk and Neuropathology in the Oldest-Old. - Lachner, Christian; Day, Gregory S; Camsari, Gamze Balci; Kouri, Naomi; Ertekin-Taner, Nilufer; Boeve, Bradley F; Labuzan, Sydney A; Lucas, John A; Thompson, E Aubrey; Siddiqui, Habeeba; Crook, Julia E; Cabrera-Rodriguez, Janisse N; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Dementia, vascular disease, and cancer increase with age, enabling complex comorbid interactions. Understanding vascular and cancer contributions to dementia risk and neuropathology in oldest-old may improve risk modification and outcomes. OBJECTIVE: Investigate vascular and cancer contributions to dementia and neuropathology in oldest-old. METHODS: Longitudinal clinicopathologic study of prospectively followed Mayo Clinic participants dying≥95 years-old who underwent autopsy. Participants were stratified by dementia status and compared according to demographics, vascular risk factors, cancer, and neuropathology. RESULTS: Participants (n = 161; 83% female; 99% non-Hispanic whites)≥95 years (95-106 years-old) with/without dementia did not differ based on demographics. APOE ɛ2 frequency was higher in no dementia (20/72 [28%]) versus dementia (11/88 [12%]; p = 0.03), but APOE ɛ4 frequency did not differ. Coronary artery disease was more frequent in no dementia (31/72 [43%]) versus dementia (23/89 [26%]; p = 0.03) associated with 56% lower dementia odds (odds ratio [OR] = 0.44 [confidence interval (CI) = 0.19-0.98]; p = 0.04) and fewer neuritic/diffuse plaques. Diabetes had an 8-fold increase in dementia odds (OR = 8.42 [CI = 1.39-163]; p = 0.02). Diabetes associated with higher cerebrovascular disease (Dickson score; p = 0.05). Cancer associated with 63% lower dementia odds (OR = 0.37 [CI = 0.17-0.78]; p <  0.01) and lower Braak stage (p = 0.01). CONCLUSION: Cancer exposure in the oldest-old was associated with lower odds of dementia and tangle pathology, whereas history of coronary artery disease was associated with lower odds of dementia and amyloid-β plaque pathology. History of diabetes mellitus was associated with increased odds of dementia and cerebrovascular disease pathology. Cancer-related mechanisms and vascular risk factor reduction strategies may alter dementia risk and neuropathology in oldest-old.

"Captive by the Uncertainty"-Experiences with Anticipatory Guidance for People Living with Dementia and Their Caregivers at a Specialty Dementia Clinic. - Shafir, Adi; Ritchie, Christine S; Garrett, Sarah B; Bernstein Sideman, Alissa; Naasan, Georges; Merrilees, Jennifer; Widera, Eric; Flint, Lynn; Harrison, Krista L (J Alzheimers Dis, 2022)
BACKGROUND: After a diagnosis of Alzheimer's disease and related disorders, people living with dementia (PWD) and caregivers wonder what disease trajectory to expect and how to plan for functional and cognitive decline. This qualitative study aimed to identify patient and caregiver experiences receiving anticipatory guidance about dementia from a specialty dementia clinic. OBJECTIVE: To examine PWD and caregiver perspectives on receiving anticipatory guidance from a specialty dementia clinic. METHODS: We conducted semi-structured interviews with PWD, and active and bereaved family caregivers, recruited from a specialty dementia clinic. Interviews were recorded, transcribed, and systematically summarized. Thematic analysis identified anticipatory guidance received from clinical or non-clinical sources and areas where respondents wanted additional guidance. RESULTS: Of 40 participants, 9 were PWD, 16 were active caregivers, and 15 were bereaved caregivers. PWD had a mean age of 75 and were primarily male (n = 6/9); caregivers had a mean age of 67 and were primarily female (n = 21/31). Participants felt they received incomplete or "hesitant" guidance on prognosis and expected disease course via their clinicians and filled the gap with information they found via the internet, books, and support groups. They appreciated guidance on behavioral, safety, and communication issues from clinicians, but found more timely and advance guidance from other non-clinical sources. Guidance on legal and financial planning was primarily identified through non-clinical sources. CONCLUSION: PWD and caregivers want more information about expected disease course, prognosis, and help planning after diagnosis. Clinicians have an opportunity to improve anticipatory guidance communication and subsequent care provision.
Keywords: Aged; Alzheimer Disease; Caregivers; Dementia; Female; Humans; Male; Qualitative Research; Uncertainty

Caregiver Tele-Assistance for Reduction of Emotional Distress During the COVID-19 Pandemic. Psychological Support to Caregivers of People with Dementia: The Italian Experience. - Rotondo, Emanuela; Galimberti, Daniela; Mercurio, Matteo; Giardinieri, Giulia; Forti, Sara; Vimercati, Roberto; Borracci, Vittoria; Fumagalli, Giorgio G; Pietroboni, Anna M; Carandini, Tiziana; Nobili, Alessandro; Scarpini, Elio; et al. (J Alzheimers Dis, 2022)
BACKGROUND: COVID-19 pandemic worsened vulnerability of patients with dementia (PWD). This new reality associated with government restriction and isolation worsened stress burden and psychological frailties in PWD caregivers. OBJECTIVE: To give tele-psychological support to caregivers and evaluate the effect of this intervention by quantifying stress burden and quality of life during the first COVID-19 lockdown. METHODS: 50 caregivers were divided into two groups: "Caregiver-focused group" (Cg) and "Patient-focused group" (Pg). Both groups received telephone contact every 2 weeks over a 28-week period, but the content of the call was different: in Cg, caregivers answered questions about the state of the PWD but also explored their own emotional state, stress burden, and quality of life. In Pg instead, telephone contacts were focused only on the PWD, and no evaluation regarding the caregiver mood or state of stress was made. Psychometric scales were administered to evaluate COVID-19 impact, stress burden, and quality of life. RESULTS: Considering the time of intervention, from baseline (W0) to W28, Zarit Burden Interview and Quality of Life-caregiver questionnaires remained unchanged in Cg as compared with baseline (p > 0.05), whereas they worsened significantly in Pg (p < 0.01), showing increased stress over time and decreased quality of life in this group. Moreover, Impact on Event Scale values improved over the weeks in Cg (p = 0.015), while they remained unchanged in Pg (p = 0.483). CONCLUSION: Caregivers who received telephone support about their mood and stress burden did not worsen their psychological state during the time of intervention, as did instead those who did not get such support.
Keywords: Aged; Aged, 80 and over; Caregiver Burden; Caregivers; COVID-19; Dementia; Female; Humans; Italy; Male; Middle Aged; Psychological Distress; Psychosocial Support Systems; Quality of Life; Surveys and Questionnaires; Telephone

Characterization of Mild Cognitive Impairment and Dementia among Community-Dwelling Mexican Americans and Non-Hispanic Whites. - O'Bryant, Sid E; Petersen, Melissa; Hall, James; Johnson, Leigh A; Barber, Robert; Phillips, Nicole; Braskie, Meredith N; Yaffe, Kristine; Rissman, Robert; Toga, Arthur (J Alzheimers Dis, 2022)
BACKGROUND: Despite tremendous advancements in the field, our understanding of mild cognitive impairment (MCI) and Alzheimer's disease (AD) among Mexican Americans remains limited. OBJECTIVE: The aim of this study was to characterize MCI and dementia among Mexican Americans and non-Hispanic whites. METHODS: Baseline data were analyzed from n = 1,705 (n = 890 Mexican American; n = 815 non-Hispanic white) participants enrolled in the Health and Aging Brain Study-Health Disparities (HABS-HD). RESULTS: Among Mexican Americans, age (OR = 1.07), depression (OR = 1.09), and MRI-based neurodegeneration (OR = 0.01) were associated with dementia, but none of these factors were associated with MCI. Among non-Hispanic whites, male gender (OR = 0.33), neighborhood deprivation (OR = 1.34), depression (OR = 1.09), and MRI-based neurodegeneration (OR = 0.03) were associated with MCI, while depression (OR = 1.09) and APOEɛ4 genotype (OR = 4.38) were associated with dementia. CONCLUSION: Findings from this study revealed that the demographic, clinical, sociocultural and biomarker characteristics of MCI and dementia are different among Mexican Americans as compared to non-Hispanic whites.

Chronic Renin-Angiotensin System Activation Induced Neuroinflammation: Common Mechanisms Underlying Hypertension and Dementia? - Tran, Shirley; Kuruppu, Sanjaya; Rajapakse, Niwanthi W (J Alzheimers Dis, 2022)
Hypertension is a major risk factor for the pathogenesis of vascular dementia and Alzheimer's disease. Chronic activation of the renin-angiotensin system (RAS) contributes substantially to neuroinflammation. We propose that neuroinflammation arising from chronic RAS activation can initiate and potentiate the onset of hypertension and related dementia. Neuroinflammation induced by chronic activation of the RAS plays a key role in the pathogenesis of dementia. Increased levels of pro-inflammatory cytokines tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and transforming growth factor (TGF)-β have been reported in brain tissue of vascular dementia patients and animal models of vascular dementia induced by either angiotensin II infusion or transverse aortic coarctation. It is proposed that neuronal cell death and synaptic dysfunction induced by neuroinflammation lead to cognitive impairment in dementia. The neuroprotective RAS pathway, regulated by angiotensin-converting enzyme 2 (ACE2) which converts angiotensin II into angiotensin-(1-7), can attenuate hypertension and dementia. Furthermore, the use of anti-hypertensive medications in preventing dementia or cognitive decline in hypertensive patients and animal models of dementia have mostly been beneficial. Current evidence suggests a strong link between RAS induced neuroinflammation and the onset of hypertension and dementia, which warrants further investigation. Strategies to counteract an overactive RAS and enhance the neuroprotective arm of the RAS may help prevent or improve cognitive impairment associated with hypertension.
Keywords: Angiotensin I; Angiotensin II; Animals; Antihypertensive Agents; Brain; Cytokines; Dementia, Vascular; Humans; Hypertension; Inflammation; Peptide Fragments; Renin-Angiotensin System

Clinical and Imaging Determinants of Neurocognitive Disorders in Post-Acute COVID-19 Patients with Cognitive Complaints. - Andriuta, Daniela; Si-Ahmed, Cherifa; Roussel, Martine; Constans, Jean-Marc; Makki, Malek; Aarabi, Ardalan; Basille, Damien; Andrejak, Claire; Godefroy, Olivier (J Alzheimers Dis, 2022)
BACKGROUND: Neurocognitive disorders (NCDs) are a part of the post-acute coronavirus disease (COVID-19) syndrome. No study has specifically evaluated NCDs in post-acute COVID-19 patients with cognitive complaints or their MRI determinants. OBJECTIVE: To characterize NCDs in post-acute COVID-19 patients with cognitive complaints. The secondary objectives were to assess their clinical and MRI determinants. METHODS: We included 46 patients with a post-acute COVID-19 cognitive complaint referred to the Amiens University Hospital Memory Center. They underwent a neuropsychological assessment and 36 had cerebral MRI. The G3 overall summary score was the sum of the mean z scores for the executive function, language, and action speed domains. Neuropsychological profiles were compared in a general linear model. Clinical determinants were analyzed by stepwise linear regression. White matter hyperintensities (WMH) masks were analyzed using parcel-based WMH symptom mapping to identify the locations of WMHs associated with cognitive performance. RESULTS: Repeated ANOVA showed a group effect (p = 0.0001) due to overall lower performance for patients and a domain effect (p = 0.0001) due to a lower (p = 0.007) action speed score. The G3 overall summary score was significantly associated with solely the requirement for oxygen (R2 = 0.319, p = 0.031). WHMs were associated with the G3 overall summary score in the following structures, all right-sided (p < 0.01): superior frontal region, postcentral region, cingulum, cortico-spinal tract, inferior longitudinal fasciculus, internal capsule, and posterior segment of the arcuate fasciculus. CONCLUSION: Post-acute COVID-19 patients with cognitive complaints had NCD, with prominent action slowing, significantly associated with the acute phase oxygen requirement and a right-sided WMH structure pattern.
Keywords: Cognition; COVID-19; Humans; Leukoaraiosis; Magnetic Resonance Imaging; Neurocognitive Disorders; Neuropsychological Tests; Oxygen; White Matter

Cognitive Decline Risk Stratification in People with Late-Onset Epilepsy of Unknown Etiology: An Electroencephalographic Connectivity and Graph Theory Pilot Study. - Costa, Cinzia; Vecchio, Fabrizio; Romoli, Michele; Miraglia, Francesca; Nardi Cesarini, Elena; Alù, Francesca; Calabresi, Paolo; Rossini, Paolo Maria (J Alzheimers Dis, 2022)
BACKGROUND: Although people with late onset epilepsy of unknown etiology (LOEU) are at higher risk of cognitive decline compared to the general population, we still lack affordable tools to predict and stratify their risk of dementia. OBJECTIVE: This pilot-study investigates the potential application of electroencephalography (EEG) network small-world (SW) properties in predicting cognitive decline among patients with LOEU. METHODS: People diagnosed with LOEU and normal cognitive examination at the time of epilepsy diagnosis were included. Cerebrospinal fluid biomarkers, brain imaging, and neuropsychological assessment were performed at the time of epilepsy diagnosis. Baseline EEG was analyzed for SW properties. Patients were followed-up over time with neuropsychological testing to define the trajectory of cognitive decline. RESULTS: Over 5.1 years of follow-up, among 24 patients diagnosed with LOEU, 62.5% were female, mean age was 65.3 years, thirteen developed mild cognitive impairment (MCI), and four developed dementia. Patients with LOEU developing MCI had lower values of SW coefficients in the delta (p = 0.03) band and higher SW values in the alpha frequency bands (p = 0.02) compared to patients having normal cognition at last follow-up. The two separate ANOVAs, for low and alpha bands, confirmed an interaction between SW and cognitive decline at follow-up. A similar gradient was confirmed for patients developing dementia compared to those with normal cognitive function as well as to those developing MCI. CONCLUSION: Baseline EEG analysis through SW is worth investigating as an affordable, widely available tool to stratify LOEU patients for their risk of cognitive decline.
Keywords: Aged; Cognitive Dysfunction; Dementia; Electroencephalography; Epilepsy; Female; Humans; Male; Neuropsychological Tests; Pilot Projects; Risk Assessment

Dementia Research on Facebook and Twitter: Current Practice and Challenges. - Hrincu, Viorica; An, Zijian; Joseph, Kenneth; Jiang, Yu Fei; Robillard, Julie M (J Alzheimers Dis, 2022)
BACKGROUND: Social media is a powerful tool for engaging diverse audiences in dementia research. However, there is little data summarizing current content exchange in this context. OBJECTIVE: To inform ethical dementia research engagement on social media, we characterized current practices by analyzing public social media posts. METHODS: We retrieved Facebook (2-year period, N = 7,896) and Twitter (1-year period, N = 9,323) posts containing dementia research-related keywords using manual and machine learning-based search strategies. We performed qualitative and quantitative content and sentiment analyses on random samples (10%) of the posts. RESULTS: Top Facebook users were advocacy (45%) and health organizations (25%). On Twitter, academics/researchers were the largest user group. Prevention was the most frequently coded theme (Facebook 30%; Twitter 26%), followed by treatment (Facebook 15%; Twitter 18%). Diagnostics had the highest Facebook engagement. Sharing knowledge was the primary form of content exchange (Facebook 63%; Twitter 80%). Most shared journal articles were peer-reviewed and open access. Emotional tone was overall more positive on Facebook. Justice was a prominent ethics topic regarding inequalities related to identity and intersecting modes of marginalization in dementia research. CONCLUSION: The findings indicate the importance of social media as an engagement tool of current topics in health research and reveal areas of potential for increased engagement. These data can inform consensus-based best practices for ethical social media application in dementia research.
Keywords: Dementia; Humans; Social Media

Demonstration of Clinical Meaningfulness of the Integrated Alzheimer's Disease Rating Scale (iADRS): Association Between Change in iADRS Scores and Patient and Caregiver Health Outcomes. - Wessels, Alette M; Belger, Mark; Johnston, Joseph A; Yu, Youying; Rentz, Dorene M; Dowsett, Sherie A; Chandler, Julie (J Alzheimers Dis, 2022)
BACKGROUND: The integrated Alzheimer's Disease Rating Scale (iADRS) is a validated cognitive/functional composite that effectively captures cognitive and functional decline over a broad spectrum of disease. The clinical meaningfulness of change on iADRS can be supported by establishing an association with changes on important health outcome measures. OBJECTIVE: To evaluate the relationship between change on the iADRS and changes in health outcomes in individuals with mild cognitive impairment (MCI) due to Alzheimer's disease (AD), or mild or moderate AD dementia using placebo data from four AD clinical trials and data from one AD observational study. METHODS: Analysis of covariate (ANCOVA) models were used to estimate the relationship between 18-month change on the iADRS and changes on health outcome measures (related to cost, quality of life, and caregiver burden). The regression coefficients for the iADRS were used to compute impact of natural disease progression and disease-modifying treatment on health outcomes. Additional ANCOVAs were conducted to understand whether cognition and/or function was the underlying explanation of any association between iADRS and health outcome change. RESULTS: Across datasets and disease stages, a worsening on the iADRS was significantly associated with increased societal costs, caregiver burden (time and distress) and worsening in measures of patient quality of life. CONCLUSION: Decline on the iADRS was associated with worsening in health outcome measures. These findings suggest that the iADRS can be used in clinical trials as a proxy measure of clinically meaningful outcomes of AD progression.
Keywords: Alzheimer Disease; Caregivers; Clinical Trials as Topic; Cognitive Dysfunction; Humans; Observational Studies as Topic; Outcome Assessment, Health Care; Quality of Life

Diabetic Retinopathy Predicts Risk of Alzheimer's Disease: A Danish Registry-Based Nationwide Cohort Study. - Pedersen, Frederik Nørregaard; Stokholm, Lonny; Pouwer, Frans; Hass Rubin, Katrine; Peto, Tunde; Frydkjær-Olsen, Ulrik; Thykjær, Anne Suhr; Andersen, Nis; Andresen, Jens; Bek, Toke; La Cour, Morten; Heegaard, Steffen; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Retinal neurodegeneration is evident in early diabetic retinopathy (DR) which may be associated with other neurodegenerative diseases like Alzheimer's disease (AD). OBJECTIVE: To investigate diabetes and DR as a risk marker of present and incident AD. METHODS: A register-based cohort study was performed. We included 134,327 persons with diabetes above 60 years of age, who had attended DR screening, and 651,936 age- and gender-matched persons without diabetes. RESULTS: At baseline, the prevalence of AD was 0.7% and 1.3% among patients with and without diabetes, respectively. In a multivariable regression model, patients with diabetes were less likely to have AD at baseline (adjusted OR 0.63, 95% CI 0.59-0.68). During follow-up, incident AD was registered for 1473 (0.35%) and 6,899 (0.34%) persons with and without diabetes, respectively. Compared to persons without diabetes, persons with diabetes and no DR had a lower risk to develop AD (adjusted HR 0.87, 95% CI 0.81-0.93), while persons with diabetes and DR had higher risk of AD (adjusted HR 1.24, 95% CI 1.08-1.43). When persons with diabetes and no DR were used as references, a higher risk of incident AD was observed in persons with DR (adjusted HR 1.34, 95% CI 1.18-1.53). CONCLUSION: Individuals with diabetes without DR were less likely to develop AD compared to persons without diabetes. However, individuals with DR had a 34% higher risk of incident AD, which raise the question whether screening for cognitive impairment should be done among individuals with DR.
Keywords: Alzheimer Disease; Cohort Studies; Denmark; Diabetes Mellitus; Diabetic Retinopathy; Humans; Registries; Risk Factors

Digital Technologies to Prevent Social Isolation and Loneliness in Dementia: A Systematic Review. - Rai, Harleen Kaur; Kernaghan, David; Schoonmade, Linda; Egan, Kieren J; Pot, Anne Margriet (J Alzheimers Dis, 2022)
BACKGROUND: Dementia poses significant and sustained challenges to global society. Diagnosis can lead to increased feelings of loneliness and social isolation. People with dementia living alone are particularly at risk. Considering the growing number of technologies proposed to aid people with dementia address social isolation and loneliness, we reviewed the existing literature. OBJECTIVE: To collate and summarize current evidence for digital technologies to prevent social isolation and loneliness for people with dementia. METHODS: Following the PRISMA guidelines, we systematically searched five databases to identify studies of digital technologies designed to support or prevent social isolation or loneliness for people with dementia. Pre-specified outcomes included social isolation, loneliness, and quality of life. We used deductive thematic analysis to synthesize the major themes emerging from the studies. RESULTS: Ten studies met our inclusion criteria where all studies reported improvements in quality of life and seven reported benefits regarding social inclusion or a reduction in loneliness. Technologies were varied across purpose, delivery format, theoretical models, and levels of personalization. Two studies clearly described the involvement of people with dementia in the study design and five technologies were available outside the research context. CONCLUSION: There is limited- but increasing- evidence that technologies hold potential to improve quality of life and reduce isolation/loneliness for people with dementia. Results presented are largely based in small-scale research studies. Involvement of people with dementia was limited and few research concepts are reaching implementation. Closer collaboration with people with dementia to provide affordable, inclusive, and person-centered solutions is urgently required.
Keywords: Dementia; Digital Technology; Humans; Loneliness; Quality of Life; Social Isolation

Does Loss of Integrity of the Cingulum Bundle Link Amyloid-β Accumulation and Neurodegeneration in Alzheimer's Disease? - Vlegels, Naomi; Ossenkoppele, Rik; van der Flier, Wiesje M; Koek, Huiberdina L; Reijmer, Yael D; Wisse, Laura Em; Biessels, Geert Jan (J Alzheimers Dis, 2022)
BACKGROUND: Alzheimer's disease is characterized by the accumulation of amyloid-β (Aβ) into plaques, aggregation of tau into neurofibrillary tangles, and neurodegenerative processes including atrophy. However, there is a poorly understood spatial discordance between initial Aβ deposition and local neurodegeneration. OBJECTIVE: Here, we test the hypothesis that the cingulum bundle links Aβ deposition in the cingulate cortex to medial temporal lobe (MTL) atrophy. METHODS: 21 participants with mild cognitive impairment (MCI) from the UMC Utrecht memory clinic (UMCU, discovery sample) and 37 participants with MCI from Alzheimer's Disease Neuroimaging Initiative (ADNI, replication sample) with available Aβ-PET scan, T1-weighted and diffusion-weighted MRI were included. Aβ load of the cingulate cortex was measured by the standardized uptake value ratio (SUVR), white matter integrity of the cingulum bundle was assessed by mean diffusivity and atrophy of the MTL by normalized MTL volume. Relationships were tested with linear mixed models, to accommodate multiple measures for each participant. RESULTS: We found at most a weak association between cingulate Aβ and MTL volume (added R2 <0.06), primarily for the posterior hippocampus. In neither sample, white matter integrity of the cingulum bundle was associated with cingulate Aβ or MTL volume (added R2 <0.01). Various sensitivity analyses (Aβ-positive individuals only, posterior cingulate SUVR, MTL sub region volume) provided similar results. CONCLUSION: These findings, consistent in two independent cohorts, do not support our hypothesis that loss of white matter integrity of the cingulum is a connecting factor between cingulate gyrus Aβ deposition and MTL atrophy.

Glucometabolic Changes Are Associated with Structural Gray Matter Alterations in Prodromal Dementia. - Gentreau, Mélissa; Reynes, Christelle; Sabatier, Robert; Maller, Jerome J; Meslin, Chantal; Deverdun, Jeremy; Le Bars, Emmanuelle; Raymond, Michel; Berticat, Claire; Artero, Sylvaine (J Alzheimers Dis, 2022)
BACKGROUND: Glucometabolic changes, such as high glycemic load (GL) diet and insulin resistance (IR), are potential risk factor of Alzheimer's disease (AD). Yet, the effect of these factors on brain alterations that contribute to AD pathology has not been clearly demonstrated. OBJECTIVE: We aimed to assess the relationship of GL and IR with gray matter volumes involved in prodromal dementia. METHODS: GL and Triglyceride-Glucose (TyG) index, an IR surrogate marker, were calculated in 497 participants who underwent magnetic resonance imaging (MRI). The gray matter volumes most related to prodromal dementia/mild cognitive impairment (diagnosed in 18/158 participants during the 7-year follow-up) were identified using a data-driven machine learning algorithm. RESULTS: Higher GL diet was associated with reduced amygdala volume. The TyG index was negatively associated with the hippocampus, amygdala, and putamen volumes. CONCLUSION: These results suggest that GL and IR are associated with lower gray matter volumes in brain regions involved in AD pathology.

Impaired Experience-Dependent Refinement of Place Cells in a Rat Model of Alzheimer's Disease. - Broussard, John I; Redell, John B; Maynard, Mark E; Zhao, Jing; Moore, Anthony; Mills, Rachel W; Hood, Kimberly N; Underwood, Erica; Roysam, Badrinath; Dash, Pramod K (J Alzheimers Dis, 2022)
BACKGROUND: Hippocampal place cells play an integral role in generating spatial maps. Impaired spatial memory is a characteristic pathology of Alzheimer's disease (AD), yet it remains unclear how AD influences the properties of hippocampal place cells. OBJECTIVE: To record electrophysiological activity in hippocampal CA1 neurons in freely-moving 18-month-old male TgF344-AD and age-matched wild-type (WT) littermates to examine place cell properties. METHODS: We implanted 32-channel electrode arrays into the CA1 subfield of 18-month-old male WT and TgF344-AD (n = 6/group) rats. Ten days after implantation, single unit activity in an open field arena was recorded across days. The spatial information content, in-field firing rate, and stability of each place cell was compared across groups. Pathology was assessed by immunohistochemical staining, and a deep neural network approach was used to count cell profiles. RESULTS: Aged TgF344-AD rats exhibited hippocampal amyloid-β deposition, and a significant increase in Iba1 immunoreactivity and microglia cell counts. Place cells from WT and TgF344-AD rat showed equivalent spatial information, in-field firing rates, and place field stability when initially exposed to the arena. However, by day 3, the place cells in aged WT rats showed characteristic spatial tuning as evidenced by higher spatial information content, stability, and in-field firing rates, an effect not seen in TgF344-AD rats. CONCLUSION: These findings support the notion that altered electrophysiological properties of place cells may contribute to the learning and memory deficits observed in AD.

Importance of Accounting for Regional Differences in Modifiable Risk Factors for Alzheimer's Disease and Related Dementias: The Case for Tailored Interventions. - Hoffmann, Coles M; Nianogo, Roch A; Yaffe, Kristine; Rosenwohl-Mack, Amy; Carrasco, Anna; Barnes, Deborah E (J Alzheimers Dis, 2022)
BACKGROUND: We recently estimated that 36.9% of Alzheimer's disease and related dementias (ADRD) cases in the US may be attributable to modifiable risk factors, but it is not known whether national estimates generalize to specific states or regions. OBJECTIVE: To compare national estimates of modifiable risk factors of ADRD to California, overall and by sex and race/ethnicity, and to estimate number of cases potentially preventable by reducing the prevalence of key risk factors by 25%. METHODS: Adults ≥18 years who participated in the Behavioral Risk Factor Surveillance Survey in California (n = 9,836) and the US (n = 378,615). We calculated population attributable risks (PARs) for eight risk factors (physical inactivity, current smoking, depression, low education, diabetes mellitus, midlife obesity, midlife hypertension, and hearing loss) and compared estimates in California and the U.S. RESULTS: In California, overall, 28.9% of ADRD cases were potentially attributable to the combination of risk factors, compared to 36.9% in the U.S. The top three risk factors were the same in California and the U.S., although their relative importance differed (low education [CA:14.9%; U.S.:11.7% ], midlife obesity [CA:14.9%; U.S.:17.7% ], and physical inactivity [CA:10.3%; U.S.:11.8% ]). The number of ADRD cases attributable to the combined risk factors was 199,246 in California and 2,287,683 in the U.S. If the combined risk factors were reduced by 25%, we could potentially prevent more than 40,000 cases in California and 445,000 cases in the U.S. CONCLUSION: Our findings highlight the importance of examining risk factors of ADRD regionally, and within sex and race/ethnic groups to tailor dementia risk reduction strategies.

Improved Prediction of Amyloid-β and Tau Burden Using Hippocampal Surface Multivariate Morphometry Statistics and Sparse Coding. - Wu, Jianfeng; Su, Yi; Zhu, Wenhui; Jalili Mallak, Negar; Lepore, Natasha; Reiman, Eric M; Caselli, Richard J; Thompson, Paul M; Chen, Kewei; Wang, Yalin (J Alzheimers Dis, 2022)
BACKGROUND: Amyloid-β (Aβ) plaques and tau protein tangles in the brain are the defining 'A' and 'T' hallmarks of Alzheimer's disease (AD), and together with structural atrophy detectable on brain magnetic resonance imaging (MRI) scans as one of the neurodegenerative ('N') biomarkers comprise the "ATN framework" of AD. Current methods to detect Aβ/tau pathology include cerebrospinal fluid (invasive), positron emission tomography (PET; costly and not widely available), and blood-based biomarkers (promising but mainly still in development). OBJECTIVE: To develop a non-invasive and widely available structural MRI-based framework to quantitatively predict the amyloid and tau measurements. METHODS: With MRI-based hippocampal multivariate morphometry statistics (MMS) features, we apply our Patch Analysis-based Surface Correntropy-induced Sparse coding and max-pooling (PASCS-MP) method combined with the ridge regression model to individual amyloid/tau measure prediction. RESULTS: We evaluate our framework on amyloid PET/MRI and tau PET/MRI datasets from the Alzheimer's Disease Neuroimaging Initiative. Each subject has one pair consisting of a PET image and MRI scan, collected at about the same time. Experimental results suggest that amyloid/tau measurements predicted with our PASCP-MP representations are closer to the real values than the measures derived from other approaches, such as hippocampal surface area, volume, and shape morphometry features based on spherical harmonics. CONCLUSION: The MMS-based PASCP-MP is an efficient tool that can bridge hippocampal atrophy with amyloid and tau pathology and thus help assess disease burden, progression, and treatment effects.

Insulin-Like Growth Factor, Inflammation, and MRI Markers of Alzheimer's Disease in Predominantly Middle-Aged Adults. - Wittfeld, Katharina; Raman, Mekala R; Conner, Sarah C; Aslam, Asra; Teumer, Alexander; Nauck, Matthias; Hosten, Norbert; Habes, Mohamad; DeCarli, Charles; Vasan, Ramachandran S; Beiser, Alexa S; Himali, Jayandra J; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Insulin-like growth factor 1 (IGF-1) signaling has been implicated in Alzheimer's disease pathogenesis, and further evidence suggests inflammation can be a moderator of this association. However, most research to date has been conducted on older adults. OBJECTIVE: To investigate the association of serum IGF-1 and IGF binding protein 3 (IGFBP-3) concentrations with MRI markers of Alzheimer's disease in predominantly middle-aged adults, and further assess moderation by chronic inflammation. METHODS: We included participants from the Framingham Heart Study (n = 1,852, mean age 46±8, 46% men) and the Study of Health in Pomerania (n = 674, mean age 50±13, 42% men) with available serum IGF-1, IFGBP-3, as well as brain MRI. IGF-1 and IFGBP-3 were related to MRI outcomes (i.e., total brain, cortical gray matter, white matter, white matter hyperintensities (WMH), and hippocampal volumes) using multivariable regression models adjusting for potential confounders. Subgroup analyses by C-reactive protein (CRP) concentrations were also performed. Cohort-specific summary statistics were meta-analyzed using random-effects models and corrected for multiple comparisons. RESULTS: Meta-analysis results revealed that higher IGF-1 concentrations were associated with lower WMH (estimate [β] [95% CI], -0.05 [-0.09, -0.02], p = 0.006) and larger hippocampal volumes (0.07 [0.02, 0.12], p = 0.01), independent of vascular risk factors. These associations occurred predominantly in individuals with CRP concentrations < 75th percentile. We did not observe associations between IGFBP-3 and MRI outcomes. CONCLUSION: Our findings suggest that IGF-1-related signaling may be implicated in brain health as early as midlife.

Integrating the Synergy of the Gut Microbiome into Regenerative Medicine: Relevance to Neurological Disorders. - Preethy, Senthilkumar; Ranganathan, Natarajan; Raghavan, Kadalraja; Dedeepiya, Vidyasagar Devaprasad; Ikewaki, Nobunao; Abraham, Samuel J K (J Alzheimers Dis, 2022)
A new paradigm of cell therapy-based approaches as a solution to several diseases caused by damage or loss of cells/tissues leading to organ failure heralded the birth of a new branch in medicine called regenerative medicine (RM), which was further fueled by in vitro cell expansion and tissue engineering (TE) technologies, including the ability to grow embryonic stem cells, induce pluripotent stem cells, and so on. RM addresses organ failure by repair, regeneration, or restoration, rejuvenation using cells, stem cells, or progenitor cells as tools having added cell-derived products also as a tool, and extracellular matrix component-based support, either direct or indirect (e.g., matrix induced autologous chondrocyte implantation) using scaffolds. Now, the main objective of RM is to solve the functional loss of cells that have evolved from cells as tools to cell-derived factors and scaffolds per se as tools. In this context, an important yet indispensable group of cells that constitute the major portion of the human body in terms of the number of cells having several essential roles to play, both directly and indirectly, starting from digestion and the immune system to the growing evidence of influencing neuronal function, aging, and carcinogenesis has been ignored. We would like to focus on these in this review as they should essentially be considered as a tool of RM, especially for neurological disorders for their vital role. What we are indicating is the second genome or the gut microbiome.
Keywords: Gastrointestinal Microbiome; Humans; Nervous System Diseases; Regenerative Medicine; Stem Cells; Tissue Engineering

Late-Onset Alcohol Abuse as a Presenting Symptom of Neurodegenerative Diseases. - de Paula França Resende, Elisa; Ketelle, Robin; Karydas, Anna; Allen, Isabel; Grinberg, Lea T; Spina, Salvatore; Seeley, William W; Perry, David C; Miller, Bruce; Naasan, Georges (J Alzheimers Dis, 2022)
BACKGROUND: The association between lifetime alcohol abuse and a higher risk to develop dementia is well known. However, it is unknown whether older adults who begin abusing alcohol late in life have an underlying neurodegenerative disease. OBJECTIVE: Identify the frequency of lifelong alcohol abuse (L-AA), late-onset alcohol abuse (LO-AA), and alcohol abuse as a first symptom of dementia (AA-FS) in patients with neurodegenerative diseases. METHODS: Cross-sectional retrospective study of patients evaluated at an academic referral center with a clinical diagnosis of behavioral variant frontotemporal dementia (bvFTD), Alzheimer-type dementia (AD), and semantic variant primary progressive aphasia (svPPA) (n = 1,518). The presence of alcohol abuse was screened with the National Alzheimer's Coordinating Center questionnaire. L-AA was defined as onset <  40 years, LO-AA as onset ≥40 years, and AA-FS was defined when the abuse started within the first three years from symptom onset. RESULTS: The frequency of LO-AA was 2.2% (n = 33/1,518). LO-AA was significantly more frequent in patients with bvFTD than AD (7.5%, n = 13/173 versus 1.3%, n = 16/1,254, CI:1.0;11.4%), but not svPPA (4.4%, n = 4/91, CI: -4.4;10.7%). Similarly, AA-FS was more frequent in bvFTD patients than AD (5.7%, n = 10/173 versus 0.7%, n = 9/1,254, CI:0.5% ;9.5%), but not svPPA (2.2%, n = 2/91, CI:-2.4;9.1%). CONCLUSION: LO-AA can be a presenting symptom of dementia, especially bvFTD. Alcohol abuse onset later in life should prompt a clinical investigation into the possibility of an underlying neurodegenerative process because delay in diagnosis and treatment may increase patient and caregiver burden. The results need to be interpreted with caution due to the limitations of the study.

Mild Cognitive Impairment, Reversion Rates, and Associated Factors: Comparison of Two Diagnostic Approaches. - Overton, Marieclaire; Sjögren, Benjamin; Elmståhl, Sölve; Rosso, Aldana (J Alzheimers Dis, 2022)
BACKGROUND: As mild cognitive impairment (MCI) is typically used to identify prodromal stages of dementia, it is essential to identify MCI criteria with high diagnostic stability and prediction of dementia. Moreover, further investigation into pinpointing key factors for reversion is required to foresee future prognosis of MCI patients accurately. OBJECTIVE: To explore disparities in diagnostic stability by examining reversion rates produced by two operationalizations of the MCI definition: the widely applied Petersen criteria and a version of the Neuropsychological (NP) criteria and to identify cognitive, lifestyle, and health related factors for reversion. METHODS: MCI was retrospectively classified in a sample from the Swedish community-based study Good Aging in Skåne with the Petersen criteria (n = 744, median follow-up = 7.0 years) and the NP criteria (n = 375, median follow-up, 6.7 years), respectively. Poisson regression models estimated the effect of various factors on the likelihood of incident reversion. RESULTS: Reversion rates were 323/744 (43.4%, 95% confidence intervals (CI): 39.8; 47.0) and 181/375 (48.3% 95% CI: 43.2; 53.5) for the Petersen criteria and NP criteria, respectively. Participants with impairment in a single cognitive domain, regular alcohol consumption, living with someone, older age, and lower body mass index had a higher likelihood of reverting to normal. CONCLUSION: Reversion rates were similar for Petersen and NP criteria indicating that one definition is not superior to the other regarding diagnostic stability. Additionally, the results highlight important aspects such as multiple domain MCI, cohabitation, and the role of alcohol on predicting the trajectory of those diagnosed with MCI.

Noninvasive Antemortem Detection of Retinal Prions by a Fluorescent Tracer. - Aguilar-Calvo, Patricia; Sevillano, Alejandro M; Rasool, Suhail; Cao, Kevin J; Randolph, Lyndsay M; Rissman, Robert A; Sarraf, Stella T; Yang, Jerry; Sigurdson, Christina J (J Alzheimers Dis, 2022)
BACKGROUND: Neurodegenerative diseases are widespread yet challenging to diagnose and stage antemortem. As an extension of the central nervous system, the eye harbors retina ganglion cells vulnerable to degeneration, and visual symptoms are often an early manifestation of neurodegenerative disease. OBJECTIVE: Here we test whether prion protein aggregates could be detected in the eyes of live mice using an amyloid-binding fluorescent probe and high-resolution retinal microscopy. METHODS: We performed retinal imaging on an experimental mouse model of prion-associated cerebral amyloid angiopathy in a longitudinal study. An amyloid-binding fluorophore was intravenously administered, and retinal imaging was performed at timepoints corresponding to early, mid-, and terminal prion disease. Retinal amyloid deposits were quantified and compared to the amyloid load in the brain. RESULTS: We report that by mid-prion disease (50% timepoint), discrete fluorescent foci appeared adjacent to the optic disc. By later timepoints, the fluorescent foci partly surrounded the optic disc and tracked along retinal vasculature. CONCLUSION: The progression of perivascular amyloid can be directly monitored in the eye by live imaging, illustrating the utility of this technology for diagnosing and monitoring the progression of cerebral amyloid-angiopathy.

Plasma Amyloid and in vivo Brain Amyloid in Late Middle-Aged Hispanics. - Rippon, Brady; Palta, Priya; Tahmi, Mouna; Sherwood, Greysi; Soto, Luisa; Cespedes, Sandino; Mesen, Yanette; He, Hengda; Laing, Krystal; Moreno, Herman; Teresi, Jeanne; Razlighi, Qolamreza; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Determining amyloid positivity is possible with cerebrospinal fluid and brain imaging of amyloid, but these methods are invasive and expensive. OBJECTIVE: To relate plasma amyloid-β (Aβ), measured using Single-molecule array (Simoatrademark) assays, to in vivo brain Aβ, measured using positron emission tomography (PET), examine the accuracy of plasma Aβ to predict brain Aβ positivity, and the relation of APOE ɛ4 with plasma Aβ. METHODS: We performed a cross-sectional analysis in a cohort of 345 late middle-aged Hispanic men and women (age 64 years, 72% women). Our primary plasma variable was Aβ 42/Aβ 40 ratio measured with Simoa. Brain Aβ burden was measured as global SUVR with 18F-Florbetaben PET examined continuously and categorically. RESULTS: Plasma Aβ 42/Aβ 40 ratio was inversely associated with global Aβ SUVR (β= -0.13, 95% Confidence Interval (CI): -0.23, -0.03; p = 0.013) and Aβ positivity (Odds Ratio: 0.59, 95% CI: 0.38, 0.91; p = 0.016), independent of demographics and APOE ɛ4. ROC curves (AUC = 0.73, 95% CI: 0.64, 0.82; p <  0.0001) showed that the optimal threshold for plasma Aβ 42/Aβ 40 ratio in relation to brain Aβ positivity was 0.060 with a sensitivity of 82.4% and specificity of 62.8% . APOE ɛ4 carriers had lower Aβ 42/Aβ 40 ratio and a higher Aβ positivity determined with the Aβ 42/Aβ 40 ratio threshold of 0.060. CONCLUSION: Plasma Aβ 42/Aβ 40 ratio assayed using Simoa is weakly correlated with in vivo brain amyloid and has limited accuracy in screening for amyloid positivity and for studying risk factors of brain amyloid burden when in vivo imaging is not feasible.

Polygenic Scores of Alzheimer's Disease Risk Genes Add Only Modestly to APOE in Explaining Variation in Amyloid PET Burden. - Ramanan, Vijay K; Heckman, Michael G; Przybelski, Scott A; Lesnick, Timothy G; Lowe, Val J; Graff-Radford, Jonathan; Mielke, M; Jack, Clifford R; Knopman, David S; Petersen, Ronald C; Ross, Owen A; Vemuri, Prashanthi (J Alzheimers Dis, 2022)
BACKGROUND: Brain accumulation of amyloid-β is a hallmark event in Alzheimer's disease (AD) whose underlying mechanisms are incompletely understood. Case-control genome-wide association studies have implicated numerous genetic variants in risk of clinically diagnosed AD dementia. OBJECTIVE: To test for associations between case-control AD risk variants and amyloid PET burden in older adults, and to assess whether a polygenic measure encompassing these factors would account for a large proportion of the unexplained variance in amyloid PET levels in the wider population. METHODS: We analyzed data from the Mayo Clinic Study of Aging (MCSA) and the Alzheimer's Disease Neuroimaging Initiative (ADNI). Global cortical amyloid PET burden was the primary outcome. The 38 gene variants from Wightman et al. (2021) were analyzed as predictors, with PRSice-2 used to assess the collective phenotypic variance explained. RESULTS: Known AD risk variants in APOE, PICALM, CR1, and CLU were associated with amyloid PET levels. In aggregate, the AD risk variants were strongly associated with amyloid PET levels in the MCSA (p = 1.51×10-50) and ADNI (p = 3.21×10-64). However, in both cohorts the non-APOE variants uniquely contributed only modestly (MCSA = 2.1%, ADNI = 4.4%) to explaining variation in amyloid PET levels. CONCLUSION: Additional case-control AD risk variants added only modestly to APOE in accounting for individual variation in amyloid PET burden, results which were consistent across independent cohorts with distinct recruitment strategies and subject characteristics. Our findings suggest that advancing precision medicine for dementia may require integration of strategies complementing case-control approaches, including biomarker-specific genetic associations, gene-by-environment interactions, and markers of disease progression and heterogeneity.

Precision Medicine Approach to Alzheimer's Disease: Successful Pilot Project. - Toups, Kat; Hathaway, Ann; Gordon, Deborah; Chung, Henrianna; Raji, Cyrus; Boyd, Alan; Hill, Benjamin D; Hausman-Cohen, Sharon; Attarha, Mouna; Chwa, Won Jong; Jarrett, Michael; Bredesen, Dale E (J Alzheimers Dis, 2022)
BACKGROUND: Effective therapeutics for Alzheimer's disease are needed. However, previous clinical trials have pre-determined a single treatment modality, such as a drug candidate or therapeutic procedure, which may be unrelated to the primary drivers of the neurodegenerative process. Therefore, increasing data set size to include the potential contributors to cognitive decline for each patient, and addressing the identified potential contributors, may represent a more effective strategy. OBJECTIVE: To determine whether a precision medicine approach to Alzheimer's disease and mild cognitive impairment is effective enough in a proof-of-concept trial to warrant a larger, randomized, controlled clinical trial. METHODS: Twenty-five patients with dementia or mild cognitive impairment, with Montreal Cognitive Assessment (MoCA) scores of 19 or higher, were evaluated for markers of inflammation, chronic infection, dysbiosis, insulin resistance, protein glycation, vascular disease, nocturnal hypoxemia, hormone insufficiency or dysregulation, nutrient deficiency, toxin or toxicant exposure, and other biochemical parameters associated with cognitive decline. Brain magnetic resonance imaging with volumetrics was performed at baseline and study conclusion. Patients were treated for nine months with a personalized, precision medicine protocol, and cognition was assessed at t = 0, 3, 6, and 9 months. RESULTS: All outcome measures revealed improvement: statistically significant improvement in MoCA scores, CNS Vital Signs Neurocognitive Index, and Alzheimer's Questionnaire Change score were documented. No serious adverse events were recorded. MRI volumetrics also improved. CONCLUSION: Based on the cognitive improvements observed in this study, a larger, randomized, controlled trial of the precision medicine therapeutic approach described herein is warranted.

Proteomic Profiles of Neurodegeneration Among Mexican Americans and Non-Hispanic Whites in the HABS-HD Study. - O'Bryant, Sid E; Zhang, Fan; Petersen, Melissa; Hall, James R; Johnson, Leigh A; Yaffe, Kristine; Braskie, Meredith; Vig, Rocky; Toga, Arthur W; Rissman, Robert A (J Alzheimers Dis, 2022)
BACKGROUND: Hispanics are expected to experience the largest increase in Alzheimer's disease (AD) and AD related dementias over the next several decades. However, few studies have examined biomarkers of AD among Mexican Americans, the largest segment of the U.S. Hispanic population. OBJECTIVE: We sought to examine proteomic profiles of an MRI-based marker of neurodegeneration from the AT(N) framework among a multi-ethnic, community-dwelling cohort. METHODS: Community-dwelling Mexican Americans and non-Hispanic white adults and elders were recruited. All participants underwent comprehensive assessments including an interview, functional exam, clinical labs, informant interview, neuropsychological testing, and 3T MRI of the brain. A neurodegeneration MRI meta-ROI biomarker for the AT(N) framework was calculated. RESULTS: Data was examined from n = 1,291 participants. Proteomic profiles were highly accurate for detecting neurodegeneration (i.e., N+) among both Mexican Americans (AUC = 1.0) and non-Hispanic whites (AUC = 0.98). The proteomic profile of N + was different between ethnic groups. Further analyses revealed that the proteomic profiles of N + varied by diagnostic status (control, MCI, dementia) and ethnicity (Mexican American versus non-Hispanic whites) though diagnostic accuracy was high for all classifications. CONCLUSION: A proteomic profile of neurodegeneration has tremendous value and point towards novel diagnostic and intervention opportunities. The current findings demonstrate that the underlying biological factors associated with neurodegeneration are different between Mexican Americans versus non-Hispanic whites as well as at different levels of disease progression.

Psychosis as a Treatment Target in Dementia: A Roadmap for Designing Interventions. - Agüera-Ortiz, Luis; Babulal, Ganesh M; Bruneau, Marie-Andrée; Creese, Byron; D'Antonio, Fabrizia; Fischer, Corinne E; Gatchel, Jennifer R; Ismail, Zahinoor; Kumar, Sanjeev; McGeown, William J; Mortby, Moyra E; Nuñez, Nicolas A; et al. (J Alzheimers Dis, 2022)
Psychotic phenomena are among the most severe and disruptive symptoms of dementias and appear in 30% to 50% of patients. They are associated with a worse evolution and great suffering to patients and caregivers. Their current treatments obtain limited results and are not free of adverse effects, which are sometimes serious. It is therefore crucial to develop new treatments that can improve this situation. We review available data that could enlighten the future design of clinical trials with psychosis in dementia as main target. Along with an explanation of its prevalence in the common diseases that cause dementia, we present proposals aimed at improving the definition of symptoms and what should be included and excluded in clinical trials. A review of the available information regarding the neurobiological basis of symptoms, in terms of pathology, neuroimaging, and genomics, is provided as a guide towards new therapeutic targets. The correct evaluation of symptoms is transcendental in any therapeutic trial and these aspects are extensively addressed. Finally, a critical overview of existing pharmacological and non-pharmacological treatments is made, revealing the unmet needs, in terms of efficacy and safety. Our work emphasizes the need for better definition and measurement of psychotic symptoms in dementias in order to highlight their differences with symptoms that appear in non-dementing diseases such as schizophrenia. Advances in neurobiology should illuminate the development of new, more effective and safer molecules for which this review can serve as a roadmap in the design of future clinical trials.
Keywords: Caregivers; Dementia; Hallucinations; Humans; Psychotic Disorders; Schizophrenia

The Relationship Between Prior Cancer Diagnosis and All-Cause Dementia Progression Among US Adults. - Fowler, Mackenzie E; Wright, Nicole C; Triebel, Kristen; Rocque, Gabrielle B; Irvin, Ryan; Kennedy, Richard E (J Alzheimers Dis, 2022)
BACKGROUND: Cancer-related cognitive impairment (CRCI), a frequent effect of cancer and its treatments, shares common cognitive symptoms with dementia syndromes. Cross-sectional studies demonstrate an inverse relationship between cancer and dementia. However, the longitudinal relationship between dementia decline and cancer has not been investigated. OBJECTIVE: To evaluate the association between cancer and longitudinal progression of dementia. METHODS: We extracted electronic health record data from July 2003 to February 2020 from a single academic medical center. We identified dementia and cancer history prior to dementia using ICD-9/10 codes. We measured cognitive decline with the Alabama Brief Cognitive Screener (ABCs). We used adjusted linear mixed models to estimate baseline cognition and rate of progression by cancer history, including differences by race. RESULTS: The study included 3,809 participants with dementia, of which 672 (17.6%) had cancer history. Those with cancer history had higher baseline cognition (β: 0.62, 95% CI: -0.02-1.25), but similar rate of decline. Non-Hispanic Blacks had lower cognitive scores at baseline and throughout follow-up regardless of cancer status compared to non-Hispanic Whites and other races/ethnicities with and without cancer history. CONCLUSION: In this longitudinal retrospective study, participants with cancer history demonstrate better cognition at dementia diagnosis and no difference in cognitive decline than those without cancer history. Smoking and comorbidities attenuate this association and results indicate non-Hispanic Blacks have worse cognitive outcomes in dementia regardless of cancer history than other race/ethnicity groups. Further exploration of the role of smoking, comorbidities, and race/ethnicity on cancer and dementia-related cognitive decline is needed.

Risk of Alzheimer's Disease Following Influenza Vaccination: A Claims-Based Cohort Study Using Propensity Score Matching. - Bukhbinder, Avram S; Ling, Yaobin; Hasan, Omar; Jiang, Xiaoqian; Kim, Yejin; Phelps, Kamal N; Schmandt, Rosemarie E; Amran, Albert; Coburn, Ryan; Ramesh, Srivathsan; Xiao, Qian; Schulz, Paul E (J Alzheimers Dis, 2022)
BACKGROUND: Prior studies have found a reduced risk of dementia of any etiology following influenza vaccination in selected populations, including veterans and patients with serious chronic health conditions. However, the effect of influenza vaccination on Alzheimer's disease (AD) risk in a general cohort of older US adults has not been characterized. OBJECTIVE: To compare the risk of incident AD between patients with and without prior influenza vaccination in a large US claims database. METHODS: Deidentified claims data spanning September 1, 2009 through August 31, 2019 were used. Eligible patients were free of dementia during the 6-year look-back period and≥65 years old by the start of follow-up. Propensity-score matching (PSM) was used to create flu-vaccinated and flu-unvaccinated cohorts with similar baseline demographics, medication usage, and comorbidities. Relative risk (RR) and absolute risk reduction (ARR) were estimated to assess the effect of influenza vaccination on AD risk during the 4-year follow-up. RESULTS: From the unmatched sample of eligible patients (n = 2,356,479), PSM produced a sample of 935,887 flu-vaccinated-unvaccinated matched pairs. The matched sample was 73.7 (SD, 8.7) years of age and 56.9% female, with median follow-up of 46 (IQR, 29-48) months; 5.1% (n = 47,889) of the flu-vaccinated patients and 8.5% (n = 79,630) of the flu-unvaccinated patients developed AD during follow-up. The RR was 0.60 (95% CI, 0.59-0.61) and ARR was 0.034 (95% CI, 0.033-0.035), corresponding to a number needed to treat of 29.4. CONCLUSION: This study demonstrates that influenza vaccination is associated with reduced AD risk in a nationwide sample of US adults aged 65 and older.
Keywords: Adult; Aged; Alzheimer Disease; Chronic Disease; Cohort Studies; Female; Humans; Influenza, Human; Male; Middle Aged; Propensity Score; Vaccination

Safety and Efficacy of Monoclonal Antibodies for Alzheimer's Disease: A Systematic Review and Meta-Analysis of Published and Unpublished Clinical Trials. - Lacorte, Eleonora; Ancidoni, Antonio; Zaccaria, Valerio; Remoli, Giulia; Tariciotti, Leonardo; Bellomo, Guido; Sciancalepore, Francesco; Corbo, Massimo; Lombardo, Flavia L; Bacigalupo, Ilaria; Canevelli, Marco; Piscopo, Paola; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Monoclonal antibodies (mAbs) are currently among the most investigated targets for potential disease-modifying therapies in Alzheimer's disease (AD). OBJECTIVE: Our objectives were to identify all registered trials investigating mAbs in MCI due to AD or AD at any stage, retrieve available published and unpublished data from all registered trials, and analyze data on safety and efficacy outcomes. METHODS: A systematic search of all registered trials on ClinicalTrials.gov and EUCT was performed. Available results were searched on both platforms and on PubMed, ISI Web of Knowledge, and The Cochrane Library. RESULTS: Overall, 101 studies were identified on 27 mAbs. Results were available for 50 trials investigating 12 mAbs. For 18 trials, data were available from both published and unpublished sources, for 21 trials only from published sources, and for 11 trials only from unpublished sources. Meta-analyses of amyloid-related imaging abnormalities (ARIA) events showed overall risk ratios of 10.65 for ARIA-E and of 1.75 for ARIA-H. The meta-analysis of PET-SUVR showed an overall significant effect of mAbs in reducing amyloid (SMD -0.88), but when considering clinical efficacy, data on CDR-SB showed that treated patients had a statistically significant but clinically non-relevant lower worsening (MD -0.15). CONCLUSION: Our results suggest that the risk-benefit profile of mAbs remains unclear. Research should focus on clarifying the effect of amyloid on cognitive decline, providing data on treatment response rate, and accounting for minimal clinically important difference. Research on mAbs should also investigate the possible long-term impact of ARIA events, including potential factors predicting their onset.
Keywords: Alzheimer Disease; Amyloid; Amyloidogenic Proteins; Amyloidosis; Antibodies, Monoclonal; Cognitive Dysfunction; Humans

Serum Levels of α-Klotho Are Correlated with Cerebrospinal Fluid Levels and Predict Measures of Cognitive Function. - Kundu, Payel; Zimmerman, Benjamin; Quinn, Joseph F; Kaye, Jeffrey; Mattek, Nora; Westaway, Shawn K; Raber, Jacob (J Alzheimers Dis, 2022)
BACKGROUND: α-klotho might play a role in neurodegenerative diseases. OBJECTIVE: To determine levels of α-klotho and apoE in serum and cerebrospinal fluid (CSF) samples and their relationship with the Mini-Mental State Examination (MMSE) and Clinical Dementia Rating (CDR). METHODS: All subjects were between age 39 to 83+ (n = 94). CDR and MMSE were administered to all participants. CSF was collected in the early afternoon by lumbar puncture. RESULTS: Serum and CSF levels of α-klotho are positively correlated and both predict scores on the MMSE and CDR, regardless of sex or apoE4 status. CONCLUSION: Our results demonstrate that α-klotho may be an important biomarker of cognitive health and neurodegeneration, and that relatively non-invasive sampling of α-klotho from serum is likely highly reflective of CSF levels.

Sex Differences in Behavior and Molecular Pathology in the 5XFAD Model. - Sil, Annesha; Erfani, Arina; Lamb, Nicola; Copland, Rachel; Riedel, Gernot; Platt, Bettina (J Alzheimers Dis, 2022)
BACKGROUND: The prevalence of Alzheimer's disease (AD) is greater in women compared to men, but the reasons for this remain unknown. This sex difference has been widely neglected in experimental studies using transgenic mouse models of AD. OBJECTIVE: Here, we studied behavior and molecular pathology of 5-month-old 5XFAD mice, which express mutated human amyloid precursor protein and presenilin-1 on a C57BL/6J background, versus their wild-type littermate controls, to compare both sex- and genotype-dependent differences. METHODS: A novel behavioral paradigm was utilized (OF-NO-SI), comprising activity measures (Open Field, OF) arena, followed by Novel Object exploration (NO) and Social Interaction (SI) of a sex-matched conspecific. Each segment consisted of two repeated trials to assess between-trial habituation. Subsequently, brain pathology (amyloid load, stress response and inflammation markers, synaptic integrity, trophic support) was assessed using qPCR and western blotting. RESULTS: Female 5XFAD mice had higher levels of human APP and amyloid-β and heightened inflammation versus males. These markers correlated with hyperactivity observed in both sexes, yet only female 5XFAD mice presented with subtle deficits in object and social exploration. Male animals had higher expression of stress markers and neurotrophic factors irrespective of genotype, this correlated with cognitive performance. CONCLUSION: The impact of sex on AD-relevant phenotypes is in line with human data and emphasizes the necessity of appropriate study design and reporting. Differential molecular profiles observed in male versus female mice offer insights into possible protective mechanisms, and hence treatment strategies.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Disease Models, Animal; Female; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Pathology, Molecular; Presenilin-1; Sex Characteristics

Sex-Specific Patterns of Body Mass Index Relationship with White Matter Connectivity. - Rahmani, Farzaneh; Wang, Qing; McKay, Nicole S; Keefe, Sarah; Hantler, Nancy; Hornbeck, Russ; Wang, Yong; Hassenstab, Jason; Schindler, Suzanne; Xiong, Chengjie; Morris, John C; Benzinger, Tammie L S; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Obesity is an increasingly recognized modifiable risk factor for Alzheimer's disease (AD). Increased body mass index (BMI) is related to distinct changes in white matter (WM) fiber density and connectivity. OBJECTIVE: We investigated whether sex differentially affects the relationship between BMI and WM structural connectivity. METHODS: A cross-sectional sample of 231 cognitively normal participants were enrolled from the Knight Alzheimer Disease Research Center. Connectome analyses were done with diffusion data reconstructed using q-space diffeomorphic reconstruction to obtain the spin distribution function and tracts were selected using a deterministic fiber tracking algorithm. RESULTS: We identified an inverse relationship between higher BMI and lower connectivity in the associational fibers of the temporal lobe in overweight and obese men. Normal to overweight women showed a significant positive association between BMI and connectivity in a wide array of WM fibers, an association that reversed in obese and morbidly obese women. Interaction analyses revealed that with increasing BMI, women showed higher WM connectivity in the bilateral frontoparietal and parahippocampal parts of the cingulum, while men showed lower connectivity in right sided corticostriatal and corticopontine tracts. Subgroup analyses demonstrated comparable results in participants with and without positron emission tomography or cerebrospinal fluid evidence of brain amyloidosis, indicating that the relationship between BMI and structural connectivity in men and women is independent of AD biomarker status. CONCLUSION: BMI influences structural connectivity of WM differently in men and women across BMI categories and this relationship does not vary as a function of preclinical AD.

Shortening of Saccades as a Possible Easy-to-Use Biomarker to Detect Risk of Alzheimer's Disease. - Hannonen, Sanna; Andberg, Sami; Kärkkäinen, Virve; Rusanen, Minna; Lehtola, Juha-Matti; Saari, Toni; Korhonen, Ville; Hokkanen, Laura; Hallikainen, Merja; Hänninen, Tuomo; Leinonen, Ville; Kaarniranta, Kai; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Wide-ranging functional defects in eye movements have been reported in Alzheimer's disease (AD) dementia. The detection of abnormal eye movements and reading problems may identify persons at risk of AD when clear clinical symptoms are lacking. OBJECTIVE: To examine whether computer-based eye-tracking (ET) analysis of King-Devick (KD) test results differentiates cognitively healthy persons from persons with minor problems in cognitive testing or diagnosed mild AD. METHODS: We recruited 78 participants (57 non-demented, 21 with mild AD) who underwent neurological examination, the Consortium to Establish a Registry for Alzheimer's Disease neuropsychological test battery (CERAD-NB), and a Clinical Dementia Rating (CDR) interview. The non-demented participants were further divided into control (normal CERAD subtests, mean MMSE = 28) and objective mild cognitive impairment (MCI; decline in at least one CERAD memory score, mean MMSE = 27) groups. The KD reading test was performed using computer-based ET. The total time used for the reading test, errors made, fixation and saccade durations, and saccade amplitudes were analyzed. RESULTS: We found significant differences between the control, objective MCI, and AD groups in regard to the mean saccade amplitude (3.58, 3.33, and 3.21 ms, respectively, p < 0.03) and duration (27.1, 25.3, and 24.8 ms, respectively, p < 0.05). The KD error scores in the AD group differed significantly (p < 0.01) from the other groups. CONCLUSION: Computed ET analysis of the KD test may help detect persons with objective MCI early when clear clinical symptoms are lacking. The portable device for ET is easy to use in primary health care memory clinics.
Keywords: Alzheimer Disease; Biomarkers; Cognitive Dysfunction; Humans; Neuropsychological Tests; Saccades

Single Nucleus Transcriptome Data from Alzheimer's Disease Mouse Models Yield New Insight into Pathophysiology. - Weller, Andrew E; Ferraro, Thomas N; Doyle, Glenn A; Reiner, Benjamin C; Crist, Richard C; Berrettini, Wade H (J Alzheimers Dis, 2022)
BACKGROUND: 5XFAD humanized mutant mice and Trem2 knockout (T2KO) mice are two mouse models relevant to the study of Alzheimer's disease (AD)-related pathology. OBJECTIVE: To determine hippocampal transcriptomic and polyadenylation site usage alterations caused by genetic mutations engineered in 5XFAD and T2KO mice. METHODS: Employing a publicly available single-nucleus RNA sequencing dataset, we used Seurat and Sierra analytic programs to identify differentially expressed genes (DEGs) and differential transcript usage (DTU), respectively, in hippocampal cell types from each of the two mouse models. We analyzed cell type-specific DEGs further using Ingenuity Pathway Analysis (IPA). RESULTS: We identified several DEGs in both neuronal and glial cell subtypes in comparisons of wild type (WT) versus 5XFAD and WT versus T2KO mice, including Ttr, Fth1, Pcsk1n, Malat1, Rpl37, Rtn1, Sepw1, Uba52, Mbp, Arl6ip5, Gm26917, Vwa1, and Pgrmc1. We also observed DTU in common between the two comparisons in neuronal and glial subtypes, specifically in the genes Prnp, Rbm4b, Pnisr, Opcml, Cpne7, Adgrb1, Gabarapl2, Ubb, Ndfip1, Car11, and Stmn4. IPA identified 3 statistically significant canonical pathways that appeared in multiple cell types and that overlapped between 5XFAD and T2KO comparisons to WT, including 'FXR/RXR Activation', 'LXR/RXR Activation', and 'Acute Phase Response Signaling'. CONCLUSION: DEG, DTU, and IPA findings, derived from two different mouse models of AD, highlight the importance of energy imbalance and inflammatory processes in specific hippocampal cell types, including subtypes of neurons and glial cells, in the development of AD-related pathology. Additional studies are needed to further characterize these findings.

The Spectrum of Alzheimer-Type Pathology in Cognitively Normal Individuals. - Walker, Jamie M; Dehkordi, Shiva Kazempour; Schaffert, Jeff; Goette, William; White Iii, Charles L; Richardson, Timothy E; Zare, Habil (J Alzheimers Dis, 2022)
BACKGROUND: The strongest risk factor for the development of Alzheimer's disease (AD) is age. The progression of Braak stage and Thal phase with age has been demonstrated. However, prior studies did not include cognitive status. OBJECTIVE: We set out to define normative values for Alzheimer-type pathologic changes in individuals without cognitive decline, and then define levels that would qualify them to be resistant to or resilient against these changes. METHODS: Utilizing neuropathology data obtained from the National Alzheimer's Coordinating Center (NACC), we demonstrate the age-related progression of Alzheimer-type pathologic changes in cognitively normal individuals (CDR = 0, n = 542). With plots generated from these data, we establish standard lines that may be utilized to measure the extent to which an individual's Alzheimer-type pathology varies from the estimated normal range of pathology. RESULTS: Although Braak stage and Thal phase progressively increase with age in cognitively normal individuals, the Consortium to Establish a Registry for Alzheimer's Disease neuritic plaque score and Alzheimer's disease neuropathologic change remain at low levels. CONCLUSION: These findings suggest that an increasing burden of neuritic plaques is a strong predictor of cognitive decline, whereas, neurofibrillary degeneration and amyloid-β (diffuse) plaque deposition, both to some degree, are normal pathologic changes of aging that occur in almost all individuals regardless of cognitive status. Furthermore, we have defined the amount of neuropathologic change in cognitively normal individuals that would qualify them to be "resilient" against the pathology (significantly above the normative values for age, but still cognitively normal) or "resistant" to the development of pathology (significantly below the normative values for age).

Supplementation With Carotenoids, Omega-3 Fatty Acids, and Vitamin E Has a Positive Effect on the Symptoms and Progression of Alzheimer's Disease. - Nolan, John M; Power, Rebecca; Howard, Alan N; Bergin, Paula; Roche, Warren; Prado-Cabrero, Alfonso; Pope, George; Cooke, John; Power, Tommy; Mulcahy, Riona (J Alzheimers Dis, 2022)
BACKGROUND: Preliminary work by our center has reported behavior and functional benefits in patients with Alzheimer's disease (AD) following targeted micronutritional supplementation. OBJECTIVE: To build on the existing exploratory research and investigate the impact of these micronutrients on the natural progression of AD in a randomized controlled trial. METHODS: Patients with mild-moderate AD consumed daily 1 g fish oil (of which 500 mg DHA, 150 mg EPA), 22 mg carotenoids (10 mg lutein, 10 mg meso-zeaxanthin, 2 mg zeaxanthin), and 15 mg vitamin E or placebo for 12 months in a double-blind, placebo-controlled, randomized clinical trial. Carotenoids, ω-3FAs, and vitamin E were quantified in blood. Carotenoids were also measured in skin. AD severity was measured using the mini-mental state examination and dementia severity rating scale tools. Behavior, mood, and memory were measured using an informant-based questionnaire. RESULTS: Following 12 months of supplementation, the active group (n = 50) compared to the placebo group (n = 27), demonstrated statistically significant improvements in skin carotenoid measurements, blood carotenoids, ω-3FAs, and vitamin E concentrations (p <  0.05, for all). The active group also performed better in objective measures of AD severity (i.e., memory and mood), with a statistically significant difference reported in the clinical collateral for memory (p <  0.001). CONCLUSION: Exponential increases in the prevalence of AD and its relentless progressive nature is driving the need for interventions that help to ameliorate symptoms and improve quality of life in AD patients. Given the positive outcomes demonstrated in this trial, this combined micronutrient dietary supplement should be considered in the overall management of AD.

Traumatic Brain Injury and Risk of Alzheimer's Disease and Related Dementias in the Population. - Mielke, Michelle M; Ransom, Jeanine E; Mandrekar, Jay; Turcano, Pierpaolo; Savica, Rodolfo; Brown, Allen W (J Alzheimers Dis, 2022)
BACKGROUND: Epidemiological studies examining associations between traumatic brain injury (TBI) and Alzheimer's disease and related dementias (ADRD) have yielded conflicting results, which may be due methodological differences. OBJECTIVE: To examine the relationship between the presence and severity of TBI and risk of ADRD using a population-based cohort with medical record abstraction for confirmation of TBI and ADRD. METHODS: All TBI events among Olmsted County, Minnesota residents aged >  40 years from 1985-1999 were confirmed by manual review and classified by severity. Each TBI case was randomly matched to two age-, sex-, and non-head injury population-based referents without TBI. For TBI events with non-head trauma, the Trauma Mortality Prediction Model was applied to assign an overall measure of non-head injury severity and corresponding referents were matched on this variable. Medical records were manually abstracted to confirm ADRD diagnosis. Cox proportional hazards models examined the relationship between TBI and severity with risk of ADRD. RESULTS: A total of 1,418 residents had a confirmed TBI (865 Possible, 450 Probable, and 103 Definite) and were matched to 2,836 referents. When combining all TBI severities, the risk of any ADRD was significantly higher for those with a confirmed TBI compared to referents (HR = 1.32, 95% CI: 1.11, 1.58). Stratifying by TBI severity, Probable (HR = 1.42, 95% CI: 1.05, 1.92) and Possible (HR = 1.29, 95% CI: 1.02-1.62) TBI was associated with an increased risk of ADRD, but not Definite TBI (HR = 1.22, 95% CI: 0.68, 2.18). CONCLUSION: Our analyses support including TBI as a potential risk factor for developing ADRD.

Undiagnosed Dementia Is Associated with Poor Physical Function in Older Adults. - McGrath, Ryan; Robinson-Lane, Sheria G; Klawitter, Lukus; Rhee, Yeong; Hamm, Jeremy M; McCourt, Mark E; Parker, Kelly; Hackney, Kyle J (J Alzheimers Dis, 2022)
BACKGROUND: Older adults with a cognitive impairment, including those not yet diagnosed, may have deficits in their physical function. OBJECTIVE: We sought to determine the associations of cognitive impairment consistent with dementia (CICD) diagnosis status on handgrip strength, gait speed, and functional disability in older adults. METHODS: The analytical sample included 8,383 adults aged ≥65-years without history of stroke, cancers, neurological conditions, or brain damage who participated in at least one-wave of the 2010-2016 waves of the Health and Retirement Study. A handgrip dynamometer measured handgrip strength. Men with handgrip strength RESULTS: Persons with undiagnosed CICD had 1.37 (95% confidence interval (CI): 1.04-1.80) greater odds for weakness and 2.02 (CI: 1.39-2.94) greater odds for slow gait speed. Older adults with diagnosed CICD had 2.29 (CI: 1.32-3.97) greater odds for slowness and 1.85 (CI: 1.19-2.90) greater odds for functional disability. CONCLUSION: Screening for CICD could be recommended when defects in physical function are observed in older adults.

Visually Identified Tau 18F-MK6240 PET Patterns in Symptomatic Alzheimer's Disease. - Krishnadas, Natasha; Huang, Kun; Schultz, Stephanie A; Doré, Vincent; Bourgeat, Pierrick; Goh, Anita M Y; Lamb, Fiona; Bozinovski, Svetlana; Burnham, Samantha C; Robertson, Joanne S; Laws, Simon M; Maruff, Paul; et al. (J Alzheimers Dis, 2022)
BACKGROUND: In Alzheimer's disease, heterogeneity has been observed in the postmortem distribution of tau neurofibrillary tangles. Visualizing the topography of tau in vivo may facilitate clinical trials and clinical practice. OBJECTIVE: This study aimed to investigate whether tau distribution patterns that are limited to mesial temporal lobe (MTL)/limbic regions, and those that spare MTL regions, can be visually identified using 18F-MK6240, and whether these patterns are associated with different demographic and cognitive profiles. METHODS: Tau 18F-MK6240 PET images of 151 amyloid-β positive participants with mild cognitive impairment (MCI) and dementia were visually rated as: tau negative, limbic predominant (LP), MTL-sparing, and Typical by two readers. Groups were evaluated for differences in age, APOE ɛ4 carriage, hippocampal volumes, and cognition (MMSE, composite memory and non-memory scores). Voxel-wise contrasts were also performed. RESULTS: Visual rating resulted in 59.6% classified as Typical, 17.9% as MTL-sparing, 9.9% LP, and 12.6% as tau negative. Intra-rater and inter-rater reliability was strong (Cohen's kappa values of 0.89 and 0.86 respectively). Tracer retention in a "hook"-like distribution on sagittal sequences was observed in the LP and Typical groups. The visually classified MTL-sparing group had lower APOE ɛ4 carriage and relatively preserved hippocampal volumes. Higher MTL tau was associated with greater amnestic cognitive impairment. High cortical tau was associated with greater impairments on non-memory domains of cognition, and individuals with high cortical tau were more likely to have dementia than MCI. CONCLUSION: Tau distribution patterns can be visually identified using 18F-MK6240 PET and are associated with differences in APOE ɛ4 carriage, hippocampal volumes, and cognition.

Weight Loss and Alzheimer's Disease in Down Syndrome. - Fleming, Victoria; Helsel, Brian C; Ptomey, Lauren T; Rosas, H Diana; Handen, Benjamin; Laymon, Charles; Christian, Bradley T; Head, Elizabeth; Mapstone, Mark; Lai, Florence; Krinsky-McHale, Sharon; Zaman, Shahid; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Virtually all adults with Down syndrome (DS) develop Alzheimer's disease (AD) pathology, but research gaps remain in understanding early signs of AD in DS. OBJECTIVE: The goal of the present study was to determine if unintentional weight loss is part of AD in DS. The specific aims were to: 1) examine relation between chronological age, weight, AD pathology, and AD-related cognitive decline were assessed in a large cohort of adults with DS, and 2) determine if baseline PET amyloid-β (Aβ) and tau PET status (-versus+) and/or decline in memory and mental status were associated with weight loss prior to AD progression. METHODS: Analyses included 261 adults with DS. PET data were acquired using [11C] PiB for Aβ and [18F] AV-1451 for tau. Body mass index (BMI) was calculated from weight and height. Direct measures assessed dementia and memory. Clinical AD status was determined using a case consensus process. Percent weight decline across 16-20 months was assessed in a subset of participants (n = 77). RESULTS: Polynomial regressions indicated an 0.23 kg/m2 decrease in BMI per year beginning at age 36.5 years, which occurs alongside the period during which Aβ and tau increase and memory and mental status decline. At a within-person level, elevated Aβ, decline in memory and mental status were associated with higher percent weight loss across 16-20 months. CONCLUSION: Unintentional weight loss occurs alongside Aβ deposition and prior to onset of AD dementia, and thus may be a useful sign of AD in DS.

APOE4 Copy Number-Dependent Proteomic Changes in the Cerebrospinal Fluid. - Berger, Miles; Cooter, Mary; Roesler, Alexander S; Chung, Stacey; Park, John; Modliszewski, Jennifer L; VanDusen, Keith W; Thompson, J Will; Moseley, Arthur; Devinney, Michael J; Smani, Shayan; Hall, Ashley; et al. (J Alzheimers Dis, 2021)
BACKGROUND: APOE4 has been hypothesized to increase Alzheimer's disease risk by increasing neuroinflammation, though the specific neuroinflammatory pathways involved are unclear. OBJECTIVE: Characterize cerebrospinal fluid (CSF) proteomic changes related to APOE4 copy number. METHODS: We analyzed targeted proteomic data from ADNI CSF samples using a linear regression model adjusting for age, sex, and APOE4 copy number, and additional linear models also adjusting for AD clinical status or for CSF Aβ, tau, or p-tau levels. False discovery rate was used to correct for multiple comparisons correction. RESULTS: Increasing APOE4 copy number was associated with a significant decrease in a CRP peptide level across all five models (q < 0.05 for each), and with significant increases in ALDOA, CH3L1 (YKL-40), and FABPH peptide levels (q < 0.05 for each) except when controlling for AD clinical status or neurodegeneration biomarkers (i.e., CSF tau or p-tau). In all models except the one controlling for CSF Aβ levels, though not statistically significant, there was a consistent inverse direction of association between APOE4 copy number and the levels of all 24 peptides from all 8 different complement proteins measured. The odds of this happening by chance for 24 unrelated peptides would be less than 1 in 16 million. CONCLUSION: Increasing APOE4 copy number was associated with decreased CSF CRP levels across all models, and increased CSF ALDOA, CH3L1, and FABH levels when controlling for CSF Aβ levels. Increased APOE4 copy number may also be associated with decreased CSF complement pathway protein levels, a hypothesis for investigation in future studies.
Keywords: Aged; Alzheimer Disease; Apolipoprotein E4; Biomarkers; Chitinase-3-Like Protein 1; DNA Copy Number Variations; Female; Fructose-Bisphosphate Aldolase; Humans; Male; Proteomics; Receptors, Immunologic

Assessing the Progression of Alzheimer's Disease in Real-World Settings in Three European Countries. - Lladó, Albert; Froelich, Lutz; Khandker, Rezaul K; Roset, Montserrat; Black, Christopher M; Lara, Nuria; Chekani, Farid; Ambegaonkar, Baishali M (J Alzheimers Dis, 2021)
BACKGROUND: There exists considerable variation in disease progression rates among patients with Alzheimer's disease (AD). OBJECTIVE: The primary objective of this observational study is to assess the progression of AD by characterizing cognitive, functional, and behavioral changes during the follow-up period between 6 and 24 months. METHODS: A longitudinal prospective study with community-dwelling patients with an established clinical diagnosis of AD of mild to moderate severity was conducted in Germany, Spain and the UK. A sample of 616 patients from 69 sites was included. RESULTS: Patients had a mean of 1.9 years (SD = 1.9) since AD diagnosis at study inclusion. Cognitive symptoms were reported to have first occurred a mean of 1.1 years (SD = 1.7) prior to AD diagnosis and 1.4 (SD = 1.8) years prior to AD treatment. Patients initially diagnosed with mild and moderate AD spent a median (95%CI) of 3.7 (2.8; 4.4) and 11.1 (6.1, 'not reached') years until progression to moderate and severe AD, respectively, according to the Mini-Mental State Examination (MMSE) scores. A mixed model developed for cognitive, functional, and neuropsychiatric scores, obtained from study patients at baseline and during follow-up period, showed progressive deterioration of AD patients over time. CONCLUSION: The study showed a deterioration of cognitive, functional, and neuropsychiatric functions during the follow-up period. Cognitive deterioration was slightly faster in patients with moderate AD compared to mild AD. The duration of moderate AD can be overestimated due to the use of retrospective data, lack of availability of MMSE scores in clinical charts and exclusion of patients at time of institutionalization.
Keywords: Alzheimer Disease; Cholinesterase Inhibitors; Cognition Disorders; Disease Progression; Europe; Germany; Humans; Institutionalization; Neuropsychological Tests; Spain

Association Between the APOEɛ2/ɛ4 Genotype and Alzheimer's Disease and Mild Cognitive Impairment Among African Americans. - Ren, Dianxu; Lopez, Oscar L; Lingler, Jennifer H; Conley, Yvette (J Alzheimers Dis, 2021)
We examined the association between APOEɛ2/ɛ4 with incident Alzheimer's disease (AD) and mild cognitive impairment (MCI) among African Americans using the national dataset from the National Alzheimer's Coordinating Center (NACC) from 2005 to September 2019. Compared to ɛ3/ɛ3 carriers, ɛ2/ɛ4 carriers exhibited a similar risk of incident AD (adjusted hazard ratio [aHR] = 0.85, 95% CI [0.39, 1.84]) among the AD cohort and similar risk of incident MCI (aHR = 0.88, 95% CI [0.51, 1.50]) among the MCI cohort. Our findings suggest that, unlike the increased risk of AD and MCI in non-Latino whites, APOEɛ2/ɛ4 genotype is not associated with the incidence of AD and MCI among African Americans.

Association of Midlife Depressive Symptoms with Regional Amyloid-β and Tau in the Framingham Heart Study. - Gonzales, Mitzi M; Samra, Jasmeet; O'Donnell, Adrienne; Mackin, R Scott; Salinas, Joel; Jacob, Mini; Satizabal, Claudia L; Aparicio, Hugo J; Thibault, Emma G; Sanchez, Justin S; Finney, Rebecca; Rubinstein, Zoe B; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Depressive symptoms predict increased risk for dementia decades before the emergence of cognitive symptoms. Studies in older adults provide preliminary evidence for an association between depressive symptoms and amyloid-β (Aβ) and tau accumulation. It is unknown if similar alterations are observed in midlife when preventive strategies may be most effective. OBJECTIVE: The study aim was to evaluate the association between depressive symptoms and cerebral Aβ and tau in a predominately middle-aged cohort with examination of the apolipoprotein (APOE) ɛ4 allele as a moderator. METHODS: Participants included 201 adults (mean age 53±8 years) who underwent 11C-Pittsburgh Compound B amyloid and 18F-Flortaucipir tau positron emission tomography (PET) imaging. Depressive symptoms were evaluated with the Center for Epidemiological Studies Depression Scale (CES-D) at the time of PET imaging, as well as eight years prior. Associations between depressive symptoms at both timepoints, as well as depression (CES-D≥16), with regional Aβ and tau PET retention were evaluated with linear regression adjusting for age and sex. Interactions with the APOE ɛ4 allele were explored. RESULTS: Depressive symptoms and depression were not associated with PET outcomes in the overall sample. However, among APOE ɛ4 allele carriers, there was a significant cross-sectional association between depressive symptoms and increased tau PET uptake in the entorhinal cortex (β= 0.446, SE = 0.155, p = 0.006) and amygdala (β= 0.350, SE = 0.133, p = 0.012). CONCLUSION: Although longitudinal studies are necessary, the results suggest that APOE ɛ4 carriers with depressive symptoms may present with higher susceptibility to early tau accumulation in regions integral to affective regulation and memory consolidation.

B Vitamins Prevent Iron-Associated Brain Atrophy and Domain-Specific Effects of Iron, Copper, Aluminum, and Silicon on Cognition in Mild Cognitive Impairment. - Jakubowski, Hieronim; Zioła-Frankowska, Anetta; Frankowski, Marcin; Perła-Kaján, Joanna; Refsum, Helga; de Jager, Celeste A; Smith, A David (J Alzheimers Dis, 2021)

The Behavioral and Psychological Symptoms of Dementia in Down Syndrome Scale (BPSD-DS II): Optimization and Further Validation. - Dekker, Alain D; Ulgiati, Aurora M; Groen, Henk; Boxelaar, Vincent A; Sacco, Silvia; Falquero, Ségolène; Carfi, Angelo; di Paola, Antonella; Benejam, Bessy; Valldeneu, Silvia; Fopma, Roelie; Oosterik, Marjo; et al. (J Alzheimers Dis, 2021)
BACKGROUND: People with Down syndrome (DS) are at high risk to develop Alzheimer's disease dementia (AD). Behavioral and psychological symptoms of dementia (BPSD) are common and may also serve as early signals for dementia. However, comprehensive evaluation scales for BPSD, adapted to DS, are lacking. Therefore, we previously developed the BPSD-DS scale to identify behavioral changes between the last six months and pre-existing life-long characteristic behavior. OBJECTIVE: To optimize and further study the scale (discriminative ability and reliability) in a large representative DS study population. METHODS: Optimization was based on item irrelevance and clinical experiences obtained in the initial study. Using the shortened and refined BPSD-DS II, informant interviews were conducted to evaluate 524 individuals with DS grouped according to dementia status: no dementia (DS, N = 292), questionable dementia (DS + Q, N = 119), and clinically diagnosed dementia (DS + AD, N = 113). RESULTS: Comparing item change scores between groups revealed prominent changes in frequency and severity for anxious, sleep-related, irritable, restless/stereotypic, apathetic, depressive, and eating/drinking behavior. For most items, the proportion of individuals displaying an increased frequency was highest in DS + AD, intermediate in DS + Q, and lowest in DS. For various items within sections about anxious, sleep-related, irritable, apathetic, and depressive behaviors, the proportion of individuals showing an increased frequency was already substantial in DS + Q, suggesting that these changes may serve as early signals of AD in DS. Reliability data were promising. CONCLUSION: The optimized scale yields largely similar results as obtained with the initial version. Systematically evaluating BPSD in DS may increase understanding of changes among caregivers and (timely) adaptation of care/treatment.
Keywords: Adult; Aged; Anxiety; Dementia; Down Syndrome; Female; Humans; Irritable Mood; Male; Middle Aged; Reproducibility of Results; Symptom Assessment

Clinical Approach of Low-Dose Whole-Brain Ionizing Radiation Treatment in Alzheimer's Disease Dementia Patients. - Chung, Mijoo; Rhee, Hak Young; Chung, Weon Kuu (J Alzheimers Dis, 2021)
Our research team recently published two relevant papers. In one study, we have seen the acute effect of low-dose ionizing irradiation (LDIR) did not reduce the amyloid-β (Aβ) protein concentration in brain tissue, yet significantly improved synaptic degeneration and neuronal loss in the hippocampus and cerebral cortex. Surprisingly, in another study, we could see late effect that the LDIR-treated mice showed significantly improved learning and memory skills compared with those in the sham group. In addition, Aβ concentrations were significantly decreased in brain tissue. Furthermore, the pro-inflammatory cytokine tumor necrosis factor-α was decreased and the anti-inflammatory cytokine transforming growth factor-β was increased in the brain tissue of 5xFAD mice treated with LDIR. Definitive clinical results for the safety and efficacy of LDIR have not yet been published and, despite the promising outcomes reported during preclinical studies, LDIR can only be applied to patients with Alzheimer's disease dementia when clinical results are made available. In addition, in the case of LDIR, additional large-scale clinical studies are necessary to determine the severity of Alzheimer's disease dementia, indications for LDIR, the total dose to be irradiated, fraction size, and intervals of LDIR treatment. The purpose of this review is to summarize the mechanism of LDIR based on existing preclinical results in a way that is useful for conducting subsequent clinical research.
Keywords: Alzheimer Disease; Animals; Brain; Cranial Irradiation; Humans

The Cognition and Flow Study: A Feasibility Randomized Controlled Trial of the Effects of Cognitive Training on Cerebral Blood Flow. - Beishon, Lucy C; Panerai, Ronney B; Budgeon, Charley; Subramaniam, Hari; Mukaetova-Ladinska, Elizabeta; Robinson, Thompson G; Haunton, Victoria J (J Alzheimers Dis, 2021)
BACKGROUND: Cognitive training (CT) has demonstrated benefits for healthy older adults (HG) and mild cognitive impairment (MCI), but the effects on vascular function are unknown. OBJECTIVE: This is a feasibility trial investigating the effects of CT on cerebral blood flow velocity (CBFv). METHODS: Twenty HG, 24 with Alzheimer's disease (AD), and 12 with MCI were randomized to 12 weeks of multi-domain CT or control. Outcomes included: cognition (Addenbrooke's Cognitive Examination III), mood, quality of life (QoL), physical, and neurovascular function (transcranial Doppler ultrasonography measured task activation of CBFv responses). Data are presented as mean difference (MD) and 95% confidence interval (CI). RESULTS: 47 participants completed the trial. There were three dropouts from the training arm in the AD group, and one in the HG group. The intervention was acceptable and feasible to the majority of participants with a high completion rate (89%). The dropout rate was higher among participants with dementia. Few changes were identified on secondary analyses, but QoL was significantly improved in HG post-training (MD: 4.83 [95% CI: 1.13, 8.54]). CBFv response rate was not significantly different in HG (MD: 1.84 [95% CI: -4.81, 1.12]), but a significant increase was seen in the patient group (MD: 1.79 [95% CI: 0.005, 3.58]), requiring sample sizes of 56 and 84 participants respectively for a fully-powered trial. CONCLUSION: A 12-week CT program was acceptable and feasible in HG, AD, and MCI. CT may be associated with alterations in vascular physiology which require further investigation in an appropriately powered randomized controlled trial.

Cognition at Each Stage of Lewy Body Disease with Co-occurring Alzheimer's Disease Pathology. - Ryman, Sephira G; Yutsis, Maya; Tian, Lu; Henderson, Victor W; Montine, Thomas J; Salmon, David P; Galasko, Douglas; Poston, Kathleen L (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease neuropathologic change (ADNC) may contribute to dementia in patients with Lewy body disease (LBD) pathology. OBJECTIVE: To examine how co-occurring ADNC impacts domain specific cognitive impairments at each pathologic stage (brainstem, limbic, cerebral cortical) of LBD. METHODS: 2,433 participants with antemortem longitudinal neuropsychological assessment and postmortem neuropathological assessment from the National Alzheimer's Coordinating Center's Uniform Data Set were characterized based on the evaluation of ADNC and LBD. Longitudinal mixed-models were used to derive measures of cumulative cognitive deficit for each cognitive domain at each pathologic stage of LBD (brainstem, limbic, and cerebral cortical). RESULTS: 111 participants with a pathologic diagnosis of LBD, 741 participants with combined LBD and ADNC, 1,357 participants with ADNC only, and 224 with no pathology (healthy controls) were included in the analyses. In the executive/visuospatial domain, combined LBD and ADNC showed worse deficits than LBD only when Lewy bodies were confined to the brainstem, but no difference when Lewy bodies extended to the limbic or cerebral cortical regions. The cerebral cortical LBD only group exhibited greater executive/visuospatial deficits than the ADNC only group. By contrast, the ADNC only group and the combined pathology group both demonstrated significantly greater cumulative memory deficits relative to Lewy body disease only, regardless of stage. CONCLUSION: The impact of co-occurring ADNC on antemortem cumulative cognitive deficits varies not only by domain but also on the pathological stage of Lewy bodies. Our findings stress the cognitive impact of different patterns of neuropathological progression in Lewy body diseases.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Cognitive Dysfunction; Female; Humans; Lewy Body Disease; Male

Cognitive Effects of the BET Protein Inhibitor Apabetalone: A Prespecified Montreal Cognitive Assessment Analysis Nested in the BETonMACE Randomized Controlled Trial. - Cummings, Jeffrey; Schwartz, Gregory G; Nicholls, Stephen J; Khan, Aziz; Halliday, Chris; Toth, Peter P; Sweeney, Michael; Johansson, Jan O; Wong, Norman C W; Kulikowski, Ewelina; Kalantar-Zadeh, Kamyar; Lebioda, Kenneth; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Epigenetic changes may contribute importantly to cognitive decline in late life including Alzheimer's disease (AD) and vascular dementia (VaD). Bromodomain and extra-terminal (BET) proteins are epigenetic "readers" that may distort normal gene expression and contribute to chronic disorders. OBJECTIVE: To assess the effects of apabetalone, a small molecule BET protein inhibitor, on cognitive performance of patients 70 years or older participating in a randomized trial of patients at high risk for major cardiovascular events (MACE). METHODS: The Montreal Cognitive Assessment (MoCA) was performed on all patients 70 years or older at the time of randomization. 464 participants were randomized to apabetalone or placebo in the cognition sub-study. In a prespecified analysis, participants were assigned to one of three groups: MoCA score≥26 (normal performance), MoCA score 25-22 (mild cognitive impairment), and MoCA score≤21 (dementia). Exposure to apabetalone was equivalent in the treatment groups in each MoCA-defined group. RESULTS: Apabetalone was associated with an increased total MoCA score in participants with baseline MoCA score of≤21 (p = 0.02). There was no significant difference in change from baseline in the treatment groups with higher MoCA scores. In the cognition study, more patients randomized to apabetalone discontinued study drug for adverse effects (11.3% versus 7.9%). CONCLUSION: In this randomized controlled study, apabetalone was associated with improved cognition as measured by MoCA scores in those with baseline scores of 21 or less. BET protein inhibitors warrant further investigation for late life cognitive disorders.
Keywords: Aged; Cardiovascular Diseases; Cognitive Dysfunction; Epigenesis, Genetic; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Quinazolinones

Could Altered Evoked Pain Responsiveness Be a Phenotypic Biomarker for Alzheimer's Disease Risk? A Cross-Sectional Analysis of Cognitively Healthy Individuals. - Romano, Raymond R; Carter, Michael A; Dietrich, Mary S; Cowan, Ronald L; Bruehl, Stephen P; Monroe, Todd B (J Alzheimers Dis, 2021)
BACKGROUND: This study evaluated whether the apolipoprotein ɛ4 (APOE4) allele, a genetic marker associated with increased risk of developing late-onset Alzheimer's disease (AD), was associated with differences in evoked pain responsiveness in cognitively healthy subjects. OBJECTIVE: The aim was to determine whether individuals at increased risk of late-onset AD based on APOE allele genotype differ phenotypically in their response to experimentally-induced painful stimuli compared to those who do not have at least one copy of the ɛ4 allele. METHODS: Forty-nine cognitively healthy subjects aged 30-89 years old with the APOE4 allele (n = 12) and without (n = 37) were assessed for group differences in pain thresholds and affective (unpleasantness) responses to experimentally-induced thermal pain stimuli. RESULTS: Statistically significant main effects of APOE4 status were observed for both the temperature at which three different pain intensity percepts were reached (p = 0.040) and the level of unpleasantness associated with each (p = 0.014). APOE4 positive participants displayed lower overall pain sensitivity than those who were APOE4 negative and also greater overall levels of pain unpleasantness regardless of intensity level. CONCLUSION: Cognitively healthy APOE4 carriers at increased risk of late-onset AD demonstrated reduced thermal pain sensitivity but greater unpleasantness to thermal pain stimuli relative to individuals at lower risk of late-onset AD. These results suggest that altered evoked pain perception could potentially be used as a phenotypic biomarker of late-onset AD risk prior to disease onset. Additional studies of this issue may be warranted.
Keywords: Adult; Aged; Aged, 80 and over; Alleles; Alzheimer Disease; Apolipoprotein E4; Biomarkers; Cross-Sectional Studies; Female; Genetic Association Studies; Hot Temperature; Humans; Male; Middle Aged; Pain Perception; Phenotype; Risk Factors

COVID-19: Association Between Increase of Behavioral and Psychological Symptoms of Dementia During Lockdown and Caregivers' Poor Mental Health. - Pongan, Elodie; Dorey, Jean-Michel; Borg, Céline; Getenet, Jean Claude; Bachelet, Romain; Lourioux, Charles; Laurent, Bernard; Rey, Romain; Rouch, Isabelle (J Alzheimers Dis, 2021)
BACKGROUND: From March 2020, the support and care systems for caregivers and people with dementia (PWD) were suspended or dramatically changed due to the lockdown during the world pandemic of COVID-19. Thus, these changes in living conditions have had deleterious consequences on the behavior of PWD and subsequently on their caregivers' mental health, the two being linked. OBJECTIVE: Our study aimed to examine changes in behavior among PWD and to look for associations between the evolution of behavioral and psychological symptoms of dementia (BPSD) and caregivers' mental health in the context of COVID-19. METHODS: The study was conducted among caregivers of PWD living at home in France. Caregivers were interviewed via an anonymous cross-sectional online survey during the first lockdown between April 15 and June 15, 2020. RESULTS: Three hundred and eighty-nine caregivers accompanying a relative living at home participated in the study; 43.3%of the PWD presented a worsening of BPSD during the lockdown. With multivariate logistic regressions, a significant association was observed between "more BPSD" and burden, anxiety and depression, between "BPSD equivalent" and anxiety and depression, and between "emerging BPSD" and only depression. CONCLUSION: The lockdown seems to have an impact on behavioral disorders in PWD and these disorders are associated with poorer mental health of caregivers. Our findings suggest attention should be given to caregivers of PWD who have BPSD before lockdown and the need for continued consultations and professional help in case of new lockdowns.
Keywords: Aged; Aged, 80 and over; Caregivers; Communicable Disease Control; COVID-19; Cross-Sectional Studies; Dementia; Female; France; Humans; Male; Mental Disorders; Mental Health; Middle Aged; Surveys and Questionnaires

Current Status and Challenges of Stem Cell Treatment for Alzheimer's Disease. - Pacheco-Herrero, Mar; Soto-Rojas, Luis O; Reyes-Sabater, Heidy; Garcés-Ramirez, Linda; de la Cruz López, Fidel; Villanueva-Fierro, Ignacio; Luna-Muñoz, José (J Alzheimers Dis, 2021)
Neurodegenerative diseases called tauopathies, such as Alzheimer's disease (AD), frontotemporal dementia, progressive supranuclear palsy, and Parkinson's disease, among others, are characterized by the pathological processing and accumulation of tau protein. AD is the most prevalent neurodegenerative disease and is characterized by two lesions: neurofibrillary tangles (NFTs) and neuritic plaques. The presence of NFTs in the hippocampus and neocortex in early and advanced stages, respectively, correlates with the patient's cognitive deterioration. So far, no drugs can prevent, decrease, or limit neuronal death due to abnormal pathological tau accumulation. Among potential non-pharmacological treatments, physical exercise has been shown to stimulate the development of stem cells (SCs) and may be useful in early stages. However, this does not prevent neuronal death from the massive accumulation of NFTs. In recent years, SCs therapies have emerged as a promising tool to repopulate areas involved in cognition in neurodegenerative diseases. Unfortunately, protocols for SCs therapy are still being developed and the mechanism of action of such therapy remains unclear. In this review, we show the advances and limitations of SCs therapy. Finally, we provide a critical analysis of its clinical use for AD.
Keywords: Alzheimer Disease; Amyloid; Government Regulation; Hippocampus; Humans; Neocortex; Neurofibrillary Tangles; Plaque, Amyloid; Stem Cells; tau Proteins

Dementia and Parkinson's Disease: Risk Factors for 30-Day Mortality in Nursing Home Residents with COVID-19. - Rutten, Jeanine J S; van Kooten, Janine; van Loon, Anouk M; van Buul, Laura W; Joling, Karlijn J; Smalbrugge, Martin; Hertogh, Cees M P M (J Alzheimers Dis, 2021)
BACKGROUND: The COVID-19 pandemic has led to high mortality rates in nursing homes (NHs) in Europe. For adequate risk management and good prognostications, it is essential to identify mortality risk factors. OBJECTIVE: This study aimed to determine whether previously identified risk factors for 30-day mortality in Dutch NH residents with COVID-19 are unique to COVID-19. METHODS: In this cohort study, we included 1,294 NH residents with COVID-19 (cases) and 17,999 NH residents without COVID-19 (controls, from the pre-COVID-19 period). We used descriptive statistics and Cox proportional hazard models to compare mortality rates in residents with and without COVID-19, categorized by risk factors. RESULTS: Cases had a more than 18 times higher hazard of death within 30 days compared to controls (HR 18, 95%CI: 16-20). For residents with COVID-19, being male, having dementia, and having Parkinson's disease (PD) were all associated with a higher 30-day mortality (HR 1.8 versus 1.3 versus 1.7). Being male was also associated with a higher mortality (HR 1.7) in the control group, whereas having dementia and PD were not. COVID-19 symptomatology was very similar for residents with and without dementia or PD, except for delirium and malaise which was more frequent in residents with dementia. CONCLUSION: Dementia and PD were significant additional risk factors for mortality in Dutch NH residents with COVID-19, whereas male gender was not unique to residents with COVID-19. The frailty of PD and dementia in NH residents with COVID-19 are relevant to consider in prognostication, communication, and care planning with residents and their families.

Diet May Moderate the Relationship Between Arterial Stiffness and Cognitive Performance in Older Adults. - Gauci, Sarah; Young, Lauren M; White, David J; Reddan, Jeffery M; Lassemillante, Annie-Claude; Meyer, Denny; Pipingas, Andrew; Scholey, Andrew (J Alzheimers Dis, 2021)
BACKGROUND: Cognitive decline is influenced by various factors including diet, cardiovascular disease, and glucose control. However, the combined effect of these risk factors on cognitive performance is yet to be fully understood. OBJECTIVE: The current study aimed to explore the inter-relationship between these risk factors and cognitive performance in older adults at risk of future cognitive decline. METHODS: The sample comprised 163 (Age: M = 65.23 years, SD = 6.50) participants. Food Frequency Questionnaire data was used to score diet quality and adherence to the Western Style Diet (WSD) and Prudent Style Diet (PSD). Glucose control was gauged by serum levels of glycated hemoglobin (HbA1c) and arterial stiffness was measured using carotid to femoral pulse wave velocity. Cognitive performance was assessed using two subtests of the Swinburne University Computerized Cognitive Assessment Battery (SUCCAB) and Rey's Verbal Learning Test (RVLT). RESULTS: Diet quality, adherence to the WSD or PSD, and glucose control were not significantly related to cognitive outcomes. However, a significant negative association was found between arterial stiffness and the spatial working memory subtest of SUCCAB (β= -0.21, p <  0.05). Arterial stiffness also significantly interacted with the PSD to impact total recall (F change (1,134) = 5.37, p <  0.05) and the composite score of RVLT (F change (1,134) = 4.03, p <  0.05). CONCLUSION: In this sample of older adults at risk of cognitive decline, diet alone was not found to predict cognitive performance; however, it was found to moderate the relationship between arterial stiffness and cognition.

Droplet Degeneration of Hippocampal and Cortical Neurons Signifies the Beginning of Neuritic Plaque Formation. - Streit, Wolfgang J; Rotter, Jonas; Winter, Karsten; Müller, Wolf; Khoshbouei, Habibeh; Bechmann, Ingo (J Alzheimers Dis, 2021)
BACKGROUND: Neuritic plaques contain neural and microglial elements, and amyloid-β protein (Aβ), but their pathogenesis remains unknown. OBJECTIVE: Elucidate neuritic plaque pathogenesis. METHODS: Histochemical visualization of hyperphosphorylated-tau positive (p-tau+) structures, microglia, Aβ, and iron. RESULTS: Disintegration of large projection neurons in human hippocampus and neocortex presents as droplet degeneration: pretangle neurons break up into spheres of numerous p-tau+ droplets of various sizes, which marks the beginning of neuritic plaques. These droplet spheres develop in the absence of colocalized Aβ deposits but once formed become encased in diffuse Aβ with great specificity. In contrast, neurofibrillary tangles often do not colocalize with Aβ. Double-labelling for p-tau and microglia showed a lack of microglial activation or phagocytosis of p-tau+ degeneration droplets but revealed massive upregulation of ferritin in microglia suggesting presence of high levels of free iron. Perl's Prussian blue produced positive staining of microglia, droplet spheres, and Aβ plaque cores supporting the suggestion that droplet degeneration of pretangle neurons in the hippocampus and cortex represents ferroptosis, which is accompanied by the release of neuronal iron extracellularly. CONCLUSION: Age-related iron accumulation and ferroptosis in the CNS likely trigger at least two endogenous mechanisms of neuroprotective iron sequestration and chelation, microglial ferritin expression and Aβ deposition, respectively, both contributing to the formation of neuritic plaques. Since neurofibrillary tangles and Aβ deposits colocalize infrequently, tangle formation likely does not involve release of neuronal iron extracellularly. In human brain, targeted deposition of Aβ occurs specifically in response to ongoing ferroptotic droplet degeneration thereby producing neuritic plaques.

Effects of High Definition-Transcranial Direct Current Stimulation on Local GABA and Glutamate Levels Among Older Adults with and without Mild Cognitive Impairment: An Exploratory Study. - Lengu, Ketrin; Ryan, Shannon; Peltier, Scott J; Tyszkowski, Troy; Kairys, Anson; Giordani, Bruno; Hampstead, Benjamin M (J Alzheimers Dis, 2021)
BACKGROUND: Prior research, primarily with young adults, suggests transcranial direct current stimulation (tDCS) effects are driven by the primary excitatory and/or inhibitory neurotransmitters, glutamate, and gamma-aminobutyric acid (GABA), respectively. OBJECTIVE: We examined the neurometabolic mechanisms of tDCS in older adults with and without mild cognitive impairment (MCI). METHODS: We used data from a double-blind, cross-over, randomized controlled trial (NCT01958437) in 32 older adults to evaluate high definition (HD)-tDCS-induced changes in glutamate and GABA via magnetic resonance spectroscopy (MRS). Participants underwent MRS following two counterbalanced HD-tDCS sessions (one active, one sham) that targeted the right superior parietal cortex (center anode at P2) and delivered 2mA for 20 minutes. RESULTS: Relative to sham, and when co-varying for MRS voxel overlap and right superior parietal volume, active HD-tDCS significantly increased GABA and decreased the ratio of glutamate to GABA. No changes were observed in a left prefrontal control MRS voxel. Although we did not find a significant correlation between strength of delivered current (measured via MRI-based computational modeling) and neurometabolite change, there was a robust positive relationship between the volume of right superior parietal cortex and neurometabolite change. CONCLUSION: Our preliminary findings of increased GABA and reduced glutamate/GABA ratio raise the possibility that (HD-)tDCS effects differ by age. Moreover, age- and disease-related regional brain volume loss may be especially important to consider when planning future studies. Replication would emphasize the importance of developing population-specific tDCS parameters that consider structural and physiologic changes associated with "normal" and pathological aging.

Egocentric and Allocentric Spatial Memory in Mild Cognitive Impairment with Real-World and Virtual Navigation Tasks: A Systematic Review. - Tuena, Cosimo; Mancuso, Valentina; Stramba-Badiale, Chiara; Pedroli, Elisa; Stramba-Badiale, Marco; Riva, Giuseppe; Repetto, Claudia (J Alzheimers Dis, 2021)
BACKGROUND: Spatial navigation is the ability to estimate one's position on the basis of environmental and self-motion cues. Spatial memory is the cognitive substrate underlying navigation and relies on two different reference frames: egocentric and allocentric. These spatial frames are prone to decline with aging and impairment is even more pronounced in Alzheimer's disease (AD) or in mild cognitive impairment (MCI). OBJECTIVE: To conduct a systematic review of experimental studies investigating which MCI population and tasks are used to evaluate spatial memory and how allocentric and egocentric deficits are impaired in MCI after navigation. METHODS: PRISMA and PICO guidelines were applied to carry out the systematic search. Down and Black checklist was used to assess methodological quality. RESULTS: Our results showed that amnestic MCI and AD pathology are the most investigated typologies; both egocentric and allocentric memory are impaired in MCI individuals, and MCI due to AD biomarkers has specific encoding and retrieval impairments; secondly, spatial navigation is principally investigated with the hidden goal task (virtual and real-world version), and among studies involving virtual reality, the privileged setting consists of non-immersive technology; thirdly, despite subtle differences, real-world and virtual versions showed good overlap for the assessment of MCI spatial memory. CONCLUSION: Considering that MCI is a subclinical entity with potential risk for conversion to dementia, investigating spatial memory deficits with navigation tasks might be crucial to make accurate diagnosis and rehabilitation.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Humans; Spatial Memory; Spatial Navigation

Elevated Norepinephrine Metabolism Gauges Alzheimer's Disease-Related Pathology and Memory Decline. - Riphagen, Joost M; van Egroo, Maxime; Jacobs, Heidi I L (J Alzheimers Dis, 2021)
The noradrenergic (NE) locus coeruleus (LC) is vulnerable to hyperphosphorylated tau, and dysregulated NE-metabolism is linked to greater tau and disease progression. We investigated whether elevated NE-metabolism alone predicts memory decline or whether concomitant presence of tau and amyloid-β is required. Among 114 memory clinic participants, time trends (max. six years) showed dose-response declines in learning across groups with elevated NE-metabolite 3-methoxy-4-hydroxyphenylethyleneglycol (MHPG) with no, one, or two Alzheimer's disease biomarkers; and no decline in the low MHPG group. Elevated MHPG is required and sufficient to detect learning declines, supporting a pathophysiologic model including the LC-NE system contributing to initial Alzheimer's disease-related processes.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Cohort Studies; Disease Progression; Female; Humans; Learning; Locus Coeruleus; Male; Memory Disorders; Methoxyhydroxyphenylglycol; Middle Aged; Neuropsychological Tests; Norepinephrine; Predictive Value of Tests; tau Proteins

Five-Year Change in Body Mass Index Predicts Conversion to Mild Cognitive Impairment or Dementia Only in APOE ɛ4 Allele Carriers. - Kadey, Kylie R; Woodard, John L; Moll, Allison C; Nielson, Kristy A; Smith, J Carson; Durgerian, Sally; Rao, Stephen M (J Alzheimers Dis, 2021)
BACKGROUND: Body mass index (BMI) has been identified as an important modifiable lifestyle risk factor for dementia, but less is known about how BMI might interact with Apolipoprotein E ɛ4 (APOE ɛ4) carrier status to predict conversion to mild cognitive impairment (MCI) and dementia. OBJECTIVE: The aim of this study was to investigate the interaction between APOE ɛ4 status and baseline (bBMI) and five-year BMI change (ΔBMI) on conversion to MCI or dementia in initially cognitively healthy older adults. METHODS: The associations between bBMI, ΔBMI, APOE ɛ4 status, and conversion to MCI or dementia were investigated among 1,289 cognitively healthy elders from the National Alzheimer's Coordinating Center (NACC) database. RESULTS: After five years, significantly more carriers (30.6%) converted to MCI or dementia than noncarriers (17.6%), p <  0.001, OR = 2.06. Neither bBMI (OR = 0.99, 95%CI = 0.96-1.02) nor the bBMI by APOE interaction (OR = 1.02, 95%CI = 0.96-1.08) predicted conversion. Although ΔBMI also did not significantly predict conversion (OR = 0.90, 95%CI = 0.78-1.04), the interaction between ΔBMI and carrier status was significant (OR = 0.72, 95%CI = 0.53-0.98). For carriers only, each one-unit decline in BMI over five years was associated with a 27%increase in the odds of conversion (OR = 0.73, 95%CI = 0.57-0.94). CONCLUSION: A decline in BMI over five years, but not bBMI, was strongly associated with conversion to MCI or dementia only for APOE ɛ4 carriers. Interventions and behaviors aimed at maintaining body mass may be important for long term cognitive health in older adults at genetic risk for AD.

How Do Persons with Young and Late Onset Dementia Die? - Roβmeier, Carola; Hartmann, Julia; Riedl, Lina; Dorn, Bianca; Fischer, Julia; Hartmann, Florentine; Egert-Schwender, Silvia; Kehl, Victoria; Schneider-Schelte, Helga; Jox, Ralf J; Dinkel, Andreas; Diehl-Schmid, Janine (J Alzheimers Dis, 2021)
BACKGROUND: End of life symptoms and symptom management as well as the quality of dying (QoD) of persons with advanced dementia (PWAD) have not yet been systematically studied in Germany. OBJECTIVE: 1) To investigate symptoms, treatment and care at the end of life, advance care planning, and circumstances of death of recently deceased PWAD; 2) To determine whether there are differences between young and late onset dementia (YOD and LOD). METHODS: The study was performed in the context of the project EPYLOGE (IssuEs in Palliative care for persons in advanced and terminal stages of Young-onset and Late-Onset dementia in Germany). Closest relatives of recently deceased patients with advanced YOD (N = 46) and LOD (N = 54) living at home or in long term care were interviewed. RESULTS: Circumstances of death, symptoms, and treatment appeared to be similar between YOD and LOD, except that persons with LOD had significantly more somatic comorbidities and were admitted to hospital in the last three months of life more often than persons with LOD. At end of life, 60% of PWAD appeared to be "at peace". Difficulty swallowing, gurgling, shortness of breath, and discomfort were observed most frequently. Large interindividual differences in suffering and QoD were present. Determinants of QoD were not identified. CONCLUSION: Our findings suggest that low QoD was caused by inadequate recognition and/or insufficient treatment of burdensome physical and emotional symptoms. PWADs' needs should be assessed regularly, and strategies focusing on treatment and implementing support for both the patient and caregiver must be established.
Keywords: Advance Care Planning; Age of Onset; Aged; Aged, 80 and over; Caregivers; Dementia; Female; Humans; Long-Term Care; Male; Palliative Care; Quality of Life

Hypoxia, Oxidative Stress, and Inflammation: Three Faces of Neurodegenerative Diseases. - Merelli, Amalia; Repetto, Marisa; Lazarowski, Alberto; Auzmendi, Jerónimo (J Alzheimers Dis, 2021)
The cerebral hypoxia-ischemia can induce a wide spectrum of biologic responses that include depolarization, excitotoxicity, oxidative stress, inflammation, and apoptosis, and result in neurodegeneration. Several adaptive and survival endogenous mechanisms can also be activated giving an opportunity for the affected cells to remain alive, waiting for helper signals that avoid apoptosis. These signals appear to help cells, depending on intensity, chronicity, and proximity to the central hypoxic area of the affected tissue. These mechanisms are present not only in a large list of brain pathologies affecting commonly older individuals, but also in other pathologies such as refractory epilepsies, encephalopathies, or brain trauma, where neurodegenerative features such as cognitive and/or motor deficits sequelae can be developed. The hypoxia inducible factor 1α (HIF-1α) is a master transcription factor driving a wide spectrum cellular response. HIF-1α may induce erythropoietin (EPO) receptor overexpression, which provides the therapeutic opportunity to administer pharmacological doses of EPO to rescue and/or repair affected brain tissue. Intranasal administration of EPO combined with other antioxidant and anti-inflammatory compounds could become an effective therapeutic alternative, to avoid and/or slow down neurodegenerative deterioration without producing adverse peripheral effects.
Keywords: Animals; Apoptosis; Brain; Erythropoietin; Humans; Hypoxia; Inflammation Mediators; Neurodegenerative Diseases; Oxidative Stress

The Impact of a Global Pandemic on People Living with Dementia and Their Care Partners: Analysis of 417 Lived Experience Reports. - Tam, Mallorie T; Dosso, Jill A; Robillard, Julie M (J Alzheimers Dis, 2021)
BACKGROUND: The COVID-19 pandemic is impacting the physical and emotional health of older adults living with dementia and their care partners. OBJECTIVE: Using a patient-centered approach, we explored the experiences and needs of people living with dementia and their care partners during the COVID-19 pandemic as part of an ongoing evaluation of dementia support services in British Columbia, Canada. METHODS: A survey instrument was developed around the priorities identified in the context of the COVID-19 and Dementia Task Force convened by the Alzheimer Society of Canada. RESULTS: A total of 417 surveys were analyzed. Overall, respondents were able to access information that was helpful for maintaining their own health and managing a period of social distancing. Care partners reported a number of serious concerns, including the inability to visit the person that they care for in long-term or palliative care. Participants also reported that the pandemic increased their levels of stress overall and that they felt lonelier and more isolated than they did before the pandemic. The use of technology was reported as a way to connect socially with their loved ones, with the majority of participants connecting with others at least twice per week. CONCLUSION: Looking at the complex effects of a global pandemic through the experiences of people living with dementia and their care partners is vital to inform healthcare priorities to restore their quality of life and health and better prepare for the future.
Keywords: Adaptation, Psychological; Aged; Alzheimer Disease; British Columbia; Caregivers; COVID-19; Disabled Persons; Female; Humans; Loneliness; Male; Needs Assessment; Psychosocial Support Systems; Social Isolation; Social Support; Stress, Psychological; Surveys and Questionnaires

Impact of Social Isolation on People with Dementia and Their Family Caregivers. - Azevedo, Lílian Viana Dos Santos; Calandri, Ismael Luis; Slachevsky, Andrea; Graviotto, Héctor Gastón; Vieira, Maria Carolina Santos; Andrade, Caíssa Bezerra de; Rossetti, Adriana Peredo; Generoso, Alana Barroso; Carmona, Karoline Carvalho; Pinto, Ludmilla Aparecida Cardoso; Sorbara, Marcos; Pinto, Alejandra; et al. (J Alzheimers Dis, 2021)
BACKGROUND: People with dementia and their family caregivers may face a great burden through social isolation due to the COVID-19 pandemic, which can be manifested as various behavioral and clinical symptoms. OBJECTIVE: To investigate the impacts of social isolation due to the COVID-19 pandemic on individuals with dementia and their family caregivers. METHODS: Two semi-structured questionnaires were applied via telephone to family caregivers of people diagnosed with dementia in three cities in Argentina, Brazil, and Chile, in order to assess clinical and behavioral changes in people with dementia and in their caregivers. RESULTS: In general, 321 interviews were conducted. A significant decline in memory function has been reported among 53.0%of people with dementia. In addition, 31.2%of individuals with dementia felt sadder and 37.4%had increased anxiety symptoms. These symptoms of anxiety were greater in individuals with mild to moderate dementia, while symptoms of agitation were greater in individuals with severe dementia. Moreover, compulsive-obsessive behavior, hallucinations, increased forgetfulness, altered appetite, and increased difficulty in activities of daily living were reported more frequently among individuals with moderate to severe dementia. Caregivers reported feeling more tired and overwhelmed during this period and these symptoms were also influenced by the severity of dementia. CONCLUSION: Social isolation during the COVID-19 pandemic triggered a series of negative behavioral repercussions, both for people with dementia and for their family caregivers in these three South American countries.
Keywords: Activities of Daily Living; Adult; Aged; Aged, 80 and over; Argentina; Brazil; Caregivers; Chile; COVID-19; Dementia; Female; Humans; Male; Middle Aged; Pandemics; Physical Distancing; Social Isolation; Surveys and Questionnaires

Implementing Delirium Prevention in the Era of COVID-19. - Radhakrishnan, Nila S; Mufti, Mariam; Ortiz, Daniel; Maye, Suzanne T; Melara, Jennifer; Lim, Duke; Rosenberg, Eric I; Price, Catherine C (J Alzheimers Dis, 2021)
Patients admitted with COVID-19 can develop delirium due to predisposing factors, isolation, and the illness itself. Standard delirium prevention methods focus on interaction and stimulation. It can be challenging to deliver these methods of care in COVID settings where it is necessary to increase patient isolation. This paper presents a typical clinical vignette of representative patients in a tertiary care hospital and how a medical team modified an evidence-based delirium prevention model to deliver high-quality care to COVID-19 patients. The implemented model focuses on four areas of delirium-prevention: Mobility, Sleep, Cognitive Stimulation, and Nutrition. Future studies will be needed to track quantitative outcome measures.
Keywords: Aged; Alzheimer Disease; COVID-19; Delirium; Humans; Male

Improving the Diagnosis of the Frontal Variant of Alzheimer's Disease with the DAPHNE Scale. - Lehingue, Elsa; Gueniat, Julien; Jourdaa, Sandra; Hardouin, Jean BenoÎt; Pallardy, Amandine; Courtemanche, Hélène; Rocher, Laetitia; Etcharry-Bouyx, Frédérique; Auriacombe, Sophie; Mollion, Hélène; Formaglio, Maıté; Rouaud, Olivier; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The frontal variant of Alzheimer's disease (fAD) is poorly understood and poorly defined. The diagnosis remains challenging. The main differential diagnosis is the behavioral variant of frontotemporal degeneration (bvFTD). For fAD, there is some dissociation between the clinical frontal presentation and imaging and neuropathological studies, which do not always find a specific involvement of the frontal lobes. DAPHNE is a behavioral scale, which demonstrated excellent performance to distinguish between bvFTD and AD. OBJECTIVE: The aim of the present study was to assess the reliability of this new tool to improve the clinical diagnosis of fAD. METHODS: Twenty fAD patients and their caregivers were prospectively included and were compared with 36 bvFTD and 22 AD patients. RESULTS: The three main behavioral disorders in the fAD patients were apathy, loss of empathy, and disinhibition. Three disorders were discriminant because they were less frequent and less severe in the fAD patients than in the bvFTD patients, namely hyperorality, neglect, and perseverations. This specific pattern of behavioral disorders was corroborated by SPECT or 18FDG PET-CT scan that showed that patients with fAD could have a medial frontal hypoperfusion, whereas in bvFTD patients the orbitofrontal cortex was the main involved region, with more diffuse hypoperfusion. CONCLUSION: We demonstrated that DAPHNE had good sensitivity and good specificity to discriminate between the three groups and in particular between fAD and bvFTD patients. DAPHNE is a quick tool that could help clinicians in memory clinics not only to differentiate bvFTD from typical AD but also from fAD.
Keywords: Aged; Alzheimer Disease; Cohort Studies; Diagnosis, Differential; Female; Frontal Lobe; Frontotemporal Dementia; Humans; Male; Middle Aged; Neuropsychological Tests

In Vivo Amyloid, Neurodegeneration, and Verbal Learning in Late Middle-Aged Hispanics. - Tahmi, Mouna; Rippon, Brady; Palta, Priya; Sherwood, Greysi; Hernandez, Gabriela; Soto, Luisa; Ceballos, Fernando; Pardo, Michelle; Laing, Krystal; Igwe, Kay; He, Hengda; Teresi, Jeanne A; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The National Institute on Aging (NIA)/Alzheimer's Association (AA) 2018 framework conceptualizes Alzheimer's disease (AD) biologically. Evidence of brain amyloid by biomarkers defines AD pathologic change and the Alzheimer's continuum. The presence of tau or neurodegeneration in the absence of amyloid defines non-AD pathologic change. OBJECTIVE: To examine the relation of in vivo amyloid and neurodegeneration with verbal learning, one of the cognitive abilities affected early in AD, in late middle age. METHODS: This was a cross-sectional study of amyloid and neurodegeneration biomarkers in a community-based cohort of 350 late-middle aged Hispanics without dementia (mean age: 64.15±3.34; 72.0%women). Amyloid (A) was measured as global standardized uptake value ratio (SUVR) with 18F-Florbetaben positron emission tomography (PET). Neurodegeneration (N) was ascertained as cortical thickness (CT) in AD signature areas using brain magnetic resonance imaging. We examined A/N continuously, categorically, by A/N profiles, and profile categories. The amyloid threshold for positivity was defined using the K means method. The CT threshold was defined as 2 standard deviations below the mean CT. Verbal learning was ascertained using total recall and delayed recall in the Buschke Selective Reminding test (SRT). RESULTS: Higher cortical thickness was associated with higher performance in SRT delayed recall. Amyloid SUVR was not related to SRT performance. The low CT category was associated with lower performance in SRT delayed recall, while Amyloid categories were not related to any SRT score. The non-AD pathologic change group (A-N+) performed worse in SRT delayed recall compared to the Normal A/N profile group (A-N-). CONCLUSION: In late middle-aged Hispanics without dementia, non-AD pathologic change, but not the Alzheimer's continuum, was related to verbal learning.

Infectious Disease Burden and the Risk of Alzheimer's Disease: A Population-Based Study. - Douros, Antonios; Santella, Christina; Dell'Aniello, Sophie; Azoulay, Laurent; Renoux, Christel; Suissa, Samy; Brassard, Paul (J Alzheimers Dis, 2021)
BACKGROUND: Previous studies suggested a link between various infectious pathogens and the development of Alzheimer's disease (AD), posing the question whether infectious disease could present a novel modifiable risk factor. OBJECTIVE: To assess whether infectious disease burden due to clinically apparent infections is associated with an increased risk of AD. METHODS: We conducted a population-based nested case-control study using the United Kingdom Clinical Practice Research Datalink. We included all dementia-free subjects ≥50 years of age enrolling in the database between January 1988 and December 2017. Each case of AD identified during follow-up was matched with up to 40 controls. Conditional logistic regression estimated adjusted odds ratios (ORs) with 95% confidence intervals (CIs) of AD associated with ≥1 infection diagnosed >  2 years before the index date compared with no infection during the study period. We further stratified by time since first infection and cumulative number of infections. RESULTS: The cohort included overall 4,262,092 individuals (mean age at cohort entry 60.4 years; 52% female). During a median follow-up of 10.5 years, 40,455 cases of AD were matched to 1,610,502 controls. Compared with having no burden of infectious disease, having a burden of infectious disease was associated with an increase in the risk of AD (OR, 1.05; 95% CI, 1.02 to 1.08). The risk increased with longer time since first infection, peaking after 12-30 years (OR, 1.11; 95% CI, 1.05-1.17). The risk did not increase with cumulative number of infections. CONCLUSION: The overall risk of AD associated with infectious disease burden was small but increased gradually with longer time since first infection.

Life Course Air Pollution Exposure and Cognitive Decline: Modelled Historical Air Pollution Data and the Lothian Birth Cohort 1936. - Russ, Tom C; Cherrie, Mark P C; Dibben, Chris; Tomlinson, Sam; Reis, Stefan; Dragosits, Ulrike; Vieno, Massimo; Beck, Rachel; Carnell, Ed; Shortt, Niamh K; Muniz-Terrera, Graciela; Redmond, Paul; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Air pollution has been consistently linked with dementia and cognitive decline. However, it is unclear whether risk is accumulated through long-term exposure or whether there are sensitive/critical periods. A key barrier to clarifying this relationship is the dearth of historical air pollution data. OBJECTIVE: To demonstrate the feasibility of modelling historical air pollution data and using them in epidemiologicalmodels. METHODS: Using the EMEP4UK atmospheric chemistry transport model, we modelled historical fine particulate matter (PM2.5) concentrations for the years 1935, 1950, 1970, 1980, and 1990 and combined these with contemporary modelled data from 2001 to estimate life course exposure in 572 participants in the Lothian Birth Cohort 1936 with lifetime residential history recorded. Linear regression and latent growth models were constructed using cognitive ability (IQ) measured by the Moray House Test at the ages of 11, 70, 76, and 79 years to explore the effects of historical air pollution exposure. Covariates included sex, IQ at age 11 years, social class, and smoking. RESULTS: Higher air pollution modelled for 1935 (when participants would have been in utero) was associated with worse change in IQ from age 11-70 years (β = -0.006, SE = 0.002, p = 0.03) but not cognitive trajectories from age 70-79 years (p > 0.05). There was no support for other critical/sensitive periods of exposure or an accumulation of risk (all p > 0.05). CONCLUSION: The life course paradigm is essential in understanding cognitive decline and this is the first study to examine life course air pollution exposure in relation to cognitive health.
Keywords: Adolescent; Adult; Aged; Air Pollution; Child; Cognitive Dysfunction; Environmental Exposure; Female; History, 20th Century; Humans; Linear Models; Male; Middle Aged; Particulate Matter; Scotland; Young Adult

Longitudinal Trajectories in Cortical Thickness and Volume Atrophy: Superior Cognitive Performance Does Not Protect Against Brain Atrophy in Older Adults. - Gardener, Samantha L; Weinborn, Michael; Sohrabi, Hamid R; Doecke, James D; Bourgeat, Pierrick; Rainey-Smith, Stephanie R; Shen, Kai-Kai; Fripp, Jurgen; Taddei, Kevin; Maruff, Paul; Salvado, Olivier; Savage, Greg; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Previous research has identified a small subgroup of older adults that maintain a high level of cognitive functioning well into advanced age. Investigation of those with superior cognitive performance (SCP) for their age is important, as age-related decline has previously been thought to be inevitable. OBJECTIVE: Preservation of cortical thickness and volume was evaluated in 76 older adults with SCP and 100 typical older adults (TOAs) assessed up to five times over six years. METHODS: Regions of interest (ROIs) found to have been associated with super-aging status (a construct similar to SCP status) in previous literature were investigated, followed by a discovery phase analyses of additional regions. SCPs were aged 70 + at baseline, scoring at/above normative memory (CVLT-II) levels for demographically similar individuals aged 30-44 years old, and in the unimpaired range for all other cognitive domains over the course of the study. RESULTS: In linear mixed models, following adjustment for multiple comparisons, there were no significant differences between rates of thinning or volume atrophy between SCPs and TOAs in previously identified ROIs, or the discovery phase analyses. With only amyloid-β negative individuals in the analyses, again there were no significant differences between SCPs and TOAs. CONCLUSION: The increased methodological rigor in classifying groups, together with the influence of cognitive reserve, are discussed as potential factors accounting for our findings as compared to the extant literature on those with superior cognitive performance for their age.

Longitudinally Increasing Elevated Asymmetric Flortaucipir Binding in a Cognitively Unimpaired Amyloid-Negative Older Individual. - Schwarz, Christopher G; Knopman, David S; Ramanan, Vijay K; Lowe, Val J; Wiste, Heather J; Cogswell, Petrice M; Utianski, Rene L; Senjem, Matthew L; Gunter, Jeffrey R; Vemuri, Prashanthi; Petersen, Ronald C; Jack, Clifford R (J Alzheimers Dis, 2021)
We present the case of a cognitively unimpaired 77-year-old man with elevated, asymmetric, and longitudinally increasing Flortaucipir tau PET despite normal (visually negative) amyloid PET. His atypical tau PET signal persisted and globally increased in a follow-up scan five years later. Across eight years of observations, temporoparietal atrophy was observed consistent with tau PET patterns, but he retained the cognitively unimpaired classification. Altogether, his atypical tau PET signal is not explained by any known risk factors or alternative pathologies, and other imaging findings were not remarkable. He remains enrolled for further observation.

Metabolites Associated with Early Cognitive Changes Implicated in Alzheimer's Disease. - Darst, Burcu F; Huo, Zhiguang; Jonaitis, Erin M; Koscik, Rebecca L; Clark, Lindsay R; Lu, Qiongshi; Kremen, William S; Franz, Carol E; Rana, Brinda; Lyons, Michael J; Hogan, Kirk J; Zhao, Jinying; et al. (J Alzheimers Dis, 2021)

Mortality After Ischemic Stroke in Patients with Alzheimer's Disease Dementia and Other Dementia Disorders. - Zupanic, Eva; von Euler, Mia; Winblad, Bengt; Xu, Hong; Secnik, Juraj; Kramberger, Milica Gregoric; Religa, Dorota; Norrving, Bo; Garcia-Ptacek, Sara (J Alzheimers Dis, 2021)
BACKGROUND: Stroke and dementia are interrelated diseases and risk for both increases with age. Even though stroke incidence and age-standardized death rates have decreased due to prevention of stroke risk factors, increased utilization of reperfusion therapies, and other changes in healthcare, the absolute numbers are increasing due to population growth and aging. OBJECTIVE: To analyze predictors of death after stroke in patients with dementia and investigate possible time and treatment trends. METHODS: A national longitudinal cohort study 2007-2017 using Swedish national registries. We compared 12,629 ischemic stroke events in patients with dementia with matched 57,954 stroke events in non-dementia controls in different aspects of patient care and mortality. Relationship between dementia status and dementia type (Alzheimer's disease and mixed dementia, vascular dementia, other dementias) and death was analyzed using Cox regressions. RESULTS: Differences in receiving intravenous thrombolysis between patients with and without dementia disappeared after the year 2015 (administered to 11.1% dementia versus 12.3% non-dementia patients, p = 0.117). One year after stroke, nearly 50% dementia and 30% non-dementia patients had died. After adjustment for demographics, mobility, nursing home placement, and comorbidity index, dementia was an independent predictor of death compared with non-dementia patients (HR 1.26 [1.23-1.29]). CONCLUSION: Dementia before ischemic stroke is an independent predictor of death. Over time, early and delayed mortality in patients with dementia remained increased, regardless of dementia type. Patients with≤80 years with prior Alzheimer's disease or mixed dementia had higher mortality rates after stroke compared to patients with prior vascular dementia.
Keywords: Aged; Aged, 80 and over; Comorbidity; Dementia; Female; Fibrinolytic Agents; Humans; Incidence; Ischemic Stroke; Male; Registries; Survival Rate; Sweden; Thrombolytic Therapy

Multiple Neurodegenerative Pathologies in an Alzheimer's Disease Patient Treated with Fornical Deep Brain Stimulation. - White, Bartholomew; Lyketsos, Constantine G; Rosenberg, Paul B; Oh, Esther S; Chen, Liam (J Alzheimers Dis, 2021)
As an established treatment for movement disorders, deep brain stimulation (DBS) has been adapted for the treatment of Alzheimer's disease (AD) by modulating fornix activity. Although it is generally regarded as a safe intervention in patients over 65 years of age, the complex neurophysiology and interconnection within circuits connected to the fornix warrants a careful ongoing evaluation of the true benefit and risk potential of DBS on slowing cognitive decline in AD patients. Here we report on a patient who died long after being implanted with a DBS device who donated her brain for neuropathologic study. The autopsy confirmed multiple proteinopathies including AD-related change, diffuse neocortical Lewy body disease, TDP-43 proteinopathy, and a nonspecific tauopathy. We discuss the possible mechanisms of these overlapping neurodegenerative disorders and caution that future studies of DBS for AD will need to take these findings into consideration.

Needs of Dementia Family Caregivers in Spain During the COVID-19 Pandemic. - Carcavilla, Nuria; Pozo, Ana Sofía; González, Belén; Moral-Cuesta, Débora; Roldán, José Joaquín; Erice, Victoria; Remírez, Ana de Ganuza (J Alzheimers Dis, 2021)
We explored the experience from caregivers of people with dementia (PwD) during mandatory confinement due to the COVID-19 pandemic in Spain. An online survey, which studied the perceptions of the main problems and consequences experienced during confinement, was answered by 106 family caregivers of PwD. Results showed that family caregivers of PwD experienced psychological problems, like anxiety, mood, sleep, or eating disorders during confinement and felt less supported when they had to handle challenging behaviors or offer meaningful activities. An innovative multi-tiered supportive approach is needed which considers a post-pandemic reality and ensures the continuity of quality care for PwD and their family careers.
Keywords: Adaptation, Psychological; Aged; Aged, 80 and over; Alzheimer Disease; Anxiety Disorders; Caregivers; COVID-19; Feeding and Eating Disorders; Female; Humans; Male; Middle Aged; Mood Disorders; Needs Assessment; Sleep Wake Disorders; Social Isolation; Social Support; Spain

Neuropsychiatric Symptoms in Patients with Dementia Associated with Increased Psychological Distress in Caregivers During the COVID-19 Pandemic. - Borelli, Wyllians Vendramini; Augustin, Marina Coutinho; de Oliveira, Paola Bell Felix; Reggiani, Lorenzo Casagrande; Bandeira-de-Mello, Renato Gorga; Schumacher-Schuh, Artur Francisco; Chaves, Marcia Lorena Fagundes; Castilhos, Raphael Machado (J Alzheimers Dis, 2021)
BACKGROUND: The social isolation imposed by COVID-19 pandemic can have a major impact on the mental health of dementia patients and their caregivers. OBJECTIVE: We aim to evaluate the neurological decline of patients with dementia and the caregivers' burden during the pandemic. METHODS: We performed a cross-sectional study. Caregivers of dementia patients following in the outpatient clinic were included. A structured telephone interview composed of the Neuropsychiatric Inventory Questionnaire (NPI-Q), Zarit Burden Interview (ZBI), Beck Depression (BDI) and Anxiety (BAI) Inventories to address cognitive, behavioral, and functional changes associated with social distancing during the Sars-Cov-2 outbreak. Patients were divided in two groups according to caregivers' report: with perceived Altered Cognition (AC) and Stable Cognition (SC). RESULTS: A total of 58 patients (median age: 57 years [21-87], 58.6%females) and caregivers (median age: 76.5 years [55-89], 79.3%females) were included. Cognitive decline was shown by most patients (53.4%), as well as behavioral symptoms (48.3%), especially apathy/depression (24.1%), and functional decline (34.5%). The AC group (n = 31) presented increased behavioral (67.7%versus 25.9%, p = 0.002) and functional (61.3%versus 3.7%, p < 0.001) changes when compared to the SC group. In the AC group, ZBI, BDI, NPI-Q caregiver distress, and NPI-Q patient's severity of symptoms scores were worse than the SC group (p < 0.005 for all). CONCLUSION: Patients' neuropsychiatric worsening and caregiver burden were frequent during the pandemic. Worsening of cognition was associated with increased caregivers' psychological distress.
Keywords: Adult; Aged; Aged, 80 and over; Brazil; Caregivers; COVID-19; Cross-Sectional Studies; Dementia; Female; Humans; Male; Mental Disorders; Middle Aged; Outpatient Clinics, Hospital; Pandemics; Psychological Distress; Social Isolation; Young Adult

Niemann-Pick Type C 1 (NPC1) and NPC2 Gene Variability in Demented Patients with Evidence of Brain Amyloid Deposition. - Sorrentino, Federica; Arighi, Andrea; Serpente, Maria; Arosio, Beatrice; Arcaro, Marina; Visconte, Caterina; Rotondo, Emanuela; Vimercati, Roberto; Ferri, Evelyn; Fumagalli, Giorgio G; Pietroboni, Anna M; Carandini, Tiziana; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Variants in Niemann-Pick Type C genes (NPC1 and NPC2) have been suggested to play a role as risk or disease modifying factors for Alzheimer's disease (AD). OBJECTIVE: The aim of this study was to analyze NPC1 and NPC2 variability in demented patients with evidence of brain amyloid-β 1-42 (Aβ) deposition and to correlate genetic data with clinical phenotypes. METHODS: A targeted Next Generation Sequencing panel was customized to screen NPC1, NPC2, and main genes related to neurodegenerative dementias in a cohort of 136 demented patients with cerebrospinal fluid (CSF) low Aβ levels or positive PET with Aβ tracer and 200 non-demented geriatric subjects. RESULTS: Seven patients were carriers of NPC variants in heterozygosis. Four of them displayed pathogenic variants previously found in NPC patients and one AD patient had a novel variant. The latter was absent in 200 non-demented elderly subjects. Five of seven patients (70%) exhibited psychiatric symptoms at onset or later as compared with 43%in non-carriers (p >  0.05). CONCLUSION: The frequency of NPC1 and NPC2 heterozygous variants in patients with CSF evidence of Aβ deposition is higher than in the general population.

Paraoxonase 1, B Vitamins Supplementation, and Mild Cognitive Impairment. - Perła-Kaján, Joanna; Włoczkowska, Olga; Zioła-Frankowska, Anetta; Frankowski, Marcin; David Smith, A; de Jager, Celeste A; Refsum, Helga; Jakubowski, Hieronim (J Alzheimers Dis, 2021)
BACKGROUND: Identification of modifiable risk factors that affect cognitive decline is important for the development of preventive and treatment strategies. Status of paraoxonase 1 (PON1), a high-density lipoprotein-associated enzyme, may play a role in the development of neurological diseases, including Alzheimer's disease. OBJECTIVE: We tested a hypothesis that PON1 status predicts cognition in individuals with mild cognitive impairment (MCI). METHODS: Individuals with MCI (n = 196, 76.8-years-old, 60% women) participating in a randomized, double-blind placebo-controlled trial (VITACOG) were assigned to receive a daily dose of folic acid (0.8 mg), vitamin B12 (0.5 mg) and B6 (20 mg) (n = 95) or placebo (n = 101) for 2 years. Cognition was analyzed by neuropsychological tests. Brain atrophy was quantified in a subset of participants (n = 168) by MRI. PON1 status, including PON1 Q192R genotype, was determined by quantifying enzymatic activity of PON1 using paraoxon and phenyl acetate as substrates. RESULTS: In the placebo group, baseline phenylacetate hydrolase (PhAcase) activity of PON1 (but not paraoxonase activity or PON1 Q192R genotype) was significantly associated with global cognition (Mini-Mental State Examination, MMSE; Telephone Inventory for Cognitive Status-modified, TICS-m), verbal episodic memory (Hopkins Verbal Learning Test-revised: Total Recall, HVLT-TR; Delayed Recall, HVLT-DR), and attention/processing speed (Trail Making A and Symbol Digits Modalities Test, SDMT) at the end of study. In addition to PhAcase, baseline iron and triglycerides predicted MMSE, baseline fatty acids predicted SDMT, baseline anti-N-Hcy-protein autoantibodies predicted TICS-m, SDMT, Trail Making A, while BDNF V66M genotype predicted HVLT-TR and HVLT-DR scores at the end of study. B-vitamins abrogated associations of PON1 and other variables with cognition. CONCLUSION: PON1 is a new factor associated with impaired cognition that can be ameliorated by B-vitamins in individuals with MCI.

Plasma Biomarkers of Alzheimer's Disease in African Americans. - Deniz, Kaancan; Ho, Charlotte C G; Malphrus, Kimberly G; Reddy, Joseph S; Nguyen, Thuy; Carnwath, Troy P; Crook, Julia E; Lucas, John A; Graff-Radford, Neill R; Carrasquillo, Minerva M; Ertekin-Taner, Nilufer (J Alzheimers Dis, 2021)
BACKGROUND/OBJECTIVE: The aim of this study was to determine if plasma concentrations of 5 surrogate markers of Alzheimer's disease (AD) pathology and neuroinflammation are associated with disease status in African Americans. METHODS: We evaluated 321 African Americans (159 AD, 162 controls) from the Florida Consortium for African-American Alzheimer's Disease Studies (FCA3DS). Five plasma proteins reflecting AD neuropathology or inflammation (Aβ42, tau, IL6, IL10, TNFα) were tested for associations with AD, age, sex, APOE and MAPT genotypes, and for pairwise correlations. RESULTS: Plasma tau levels were higher in AD when adjusted for biological and technical covariates. APOEɛ4 was associated with lower plasma Aβ42 and tau levels. Older age was associated with higher plasma Aβ42, tau, and TNFα. Females had lower IL10 levels. Inflammatory proteins had strong pairwise correlations amongst themselves and with Aβ42. CONCLUSION: We identified effects of demographic and genetic variants on five potential plasma biomarkers in African Americans. Plasma inflammatory biomarkers and Aβ42 may reflect correlated pathologies and elevated plasma tau may be a biomarker of AD in this population.
Keywords: African Americans; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Case-Control Studies; Female; Humans; Interleukin-10; Interleukin-6; Male; Middle Aged; Peptide Fragments; tau Proteins; Tumor Necrosis Factor-alpha

Plasma Neurofilament Light Chain Predicts Cognitive Progression in Prodromal and Clinical Dementia with Lewy Bodies. - Pilotto, Andrea; Imarisio, Alberto; Carrarini, Claudia; Russo, Mirella; Masciocchi, Stefano; Gipponi, Stefano; Cottini, Elisabetta; Aarsland, Dag; Zetterberg, Henrik; Ashton, Nicholas J; Hye, Abdul; Bonanni, Laura; et al. (J Alzheimers Dis, 2021)
Plasma neurofilament light chain (NfL) is a marker of neuronal damage in different neurological disorders and might predict disease progression in dementia with Lewy bodies (DLB). The study enrolled 45 controls and 44 DLB patients (including 17 prodromal cases) who underwent an extensive assessment at baseline and at 2 years follow-up. At baseline, plasma NfL levels were higher in both probable DLB and prodromal cases compared to controls. Plasma NfL emerged as the best predictor of cognitive decline compared to age, sex, and baseline severity variables. The study supports the role of plasma NfL as a useful prognostic biomarker from the early stages of DLB.

Plasma Total-Tau and Neurofilament Light Chain as Diagnostic Biomarkers of Alzheimer's Disease Dementia and Mild Cognitive Impairment in Adults with Down Syndrome. - Petersen, Melissa E; Rafii, Michael S; Zhang, Fan; Hall, James; Julovich, David; Ances, Beau M; Schupf, Nicole; Krinsky-McHale, Sharon J; Mapstone, Mark; Silverman, Wayne; Lott, Ira; Klunk, William; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The need for diagnostic biomarkers of cognitive decline is particularly important among aging adults with Down syndrome (DS). Growing empirical support has identified the utility of plasma derived biomarkers among neurotypical adults with mild cognitive impairment (MCI) and Alzheimer's disease (AD); however, the application of such biomarkers has been limited among the DS population. OBJECTIVE: This study aimed to investigate the cross-sectional diagnostic performance of plasma neurofilament light chain (Nf-L) and total-tau, individually and in combination among a cohort of DS adults. METHODS: Plasma samples were analyzed from n = 305 (n = 225 cognitively stable (CS); n = 44 MCI-DS; n = 36 DS-AD) participants enrolled in the Alzheimer's Biomarker Consortium -Down Syndrome. RESULTS: In distinguishing DS-AD participants from CS, Nf-L alone produced an AUC of 90%, total-tau alone reached 74%, and combined reached an AUC of 86%. When age and gender were included, AUC increased to 93%. Higher values of Nf-L, total-tau, and age were all shown to be associated with increased risk for DS-AD. When distinguishing MCI-DS participants from CS, Nf-L alone produced an AUC of 65%, while total-tau alone reached 56%. A combined model with Nf-L, total-tau, age, and gender produced an AUC of 87%. Both higher values in age and total-tau were found to increase risk for MCI-DS; Nf-L levels were not associated with increased risk for MCI-DS. CONCLUSION: Advanced assay techniques make total-tau and particularly Nf-L useful biomarkers of both AD pathology and clinical status in DS and have the potential to serve as outcome measures in clinical trials for future disease-modifying drugs.

Polyphenols as Potential Metal Chelation Compounds Against Alzheimer's Disease. - Lakey-Beitia, Johant; Burillo, Andrea M; La Penna, Giovanni; Hegde, Muralidhar L; Rao, K S (J Alzheimers Dis, 2021)
Alzheimer's disease (AD) is the most common neurodegenerative disease affecting more than 50 million people worldwide. The pathology of this multifactorial disease is primarily characterized by the formation of amyloid-β (Aβ) aggregates; however, other etiological factors including metal dyshomeostasis, specifically copper (Cu), zinc (Zn), and iron (Fe), play critical role in disease progression. Because these transition metal ions are important for cellular function, their imbalance can cause oxidative stress that leads to cellular death and eventual cognitive decay. Importantly, these transition metal ions can interact with the amyloid-β protein precursor (AβPP) and Aβ42 peptide, affecting Aβ aggregation and increasing its neurotoxicity. Considering how metal dyshomeostasis may substantially contribute to AD, this review discusses polyphenols and the underlying chemical principles that may enable them to act as natural chelators. Furthermore, polyphenols have various therapeutic effects, including antioxidant activity, metal chelation, mitochondrial function, and anti-amyloidogenic activity. These combined therapeutic effects of polyphenols make them strong candidates for a moderate chelation-based therapy for AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Antioxidants; Chelating Agents; Copper; Humans; Oxidative Stress; Polyphenols; Zinc

Predictors of Mild Cognitive Impairment Stability, Progression, or Reversion in the Lothian Birth Cohort 1936. - Welstead, Miles; Luciano, Michelle; Muniz-Terrera, Graciela; Saunders, Stina; Mullin, Donncha S; Russ, Tom C (J Alzheimers Dis, 2021)
BACKGROUND: Mild cognitive impairment (MCI) describes a borderland between healthy cognition and dementia. Progression to and reversion from MCI is relatively common but more research is required to understand the factors affecting this fluidity and improve clinical care interventions. OBJECTIVE: We explore these transitions in MCI status and their predictive factors over a six-year period in a highly-phenotyped longitudinal study, the Lothian Birth Cohort 1936. METHODS: MCI status was derived in the LBC1936 at ages 76 (n = 567) and 82 years (n = 341) using NIA-AA diagnostic guidelines. Progressions and reversions between healthy cognition and MCI over the follow-up period were assessed. Multinomial logistic regression assessed the effect of various predictors on the likelihood of progressing, reverting, or maintaining cognitive status. RESULTS: Of the 292 participants who completed both time points, 41 (14%) participants had MCI at T1 and 56 (19%) at T2. Over the follow-up period, 74%remained cognitively healthy, 12%transitioned to MCI, 7%reverted to healthy cognition, and 7%maintained their baseline MCI status. Findings indicated that membership of these transition groups was affected by age, cardiovascular disease, and number of depressive symptoms. CONCLUSION: Findings that higher baseline depressive symptoms increase the likelihood of reverting from MCI to healthy cognition indicate that there may be an important role for the treatment of depression for those with MCI. However, further research is required to identify prevention strategies for those at high risk of MCI and inform effective interventions that increase the likelihood of reversion to, and maintenance of healthy cognition.

Proteome Profiling Identified Amyloid-β Protein Precursor as a Novel Binding Partner and Modulator of VGLUT1. - Zhou, Jin-Wu; Zhao, Man; Rang, Wen-Liang; Zhang, Xiao-Yan; Liu, Zhen-Ming; Zhang, Liang-Ren; Wang, Tong-Xing; Wu, Chu-Tse; Cheng, Xiao-Rui; Zhou, Wen-Xia (J Alzheimers Dis, 2021)
BACKGROUND: The toxicity of excessive glutamate release has been implicated in various acute and chronic neurodegenerative conditions. Vesicular glutamate transporters (VGLUTs) are the major mediators for the uptake of glutamate into synaptic vesicles. However, the dynamics and mechanism of this process in glutamatergic neurons are still largely unknown. OBJECTIVE: This study aimed to investigate the candidate protein partners of VGLUT1 and their regulatory roles in the vesicles in rat brain. METHODS: Pull down assay, co-immunoprecipitation assay, or split-ubiquitin membrane yeast two hybrid screening coupled with nanoRPLC-MS/MS were used to identify the candidate protein partners of VGLUT1 in the vesicles in rat brain. The in vitro and in vivo models were used to test effects of AβPP, Atp6ap2, Gja1, and Synataxin on VGLUT1 expression. RESULTS: A total of 255 and 225 proteins and 172 known genes were identified in the pull down assay, co-immunoprecipitation assay, or split-ubiquitin yeast two-hybrid screening respectively. The physiological interactions of SV2A, Syntaxin 12, Gja1, AβPP, and Atp6ap2 to VGLUT1 were further confirmed. Knockdown of Atp6ap2, Gja1, and Synataxin increased VGLUT1 mRNA expression and only knockdown of AβPP increased both mRNA and protein levels of VGLUT1 in PC12 cells. The regulatory function of AβPP on VGLUT1 expression was further confirmed in the in vitro and in vivo models. CONCLUSION: These results elucidate that the AβPP and VGLUT1 interacts at vesicular level and AβPP plays a role in the regulation of VGLUT1 expression which is essential for maintaining vesicular activities.

Quality of Life in Advanced Dementia with Late Onset, Young Onset, and Very Young Onset. - Hartmann, Julia; Roßmeier, Carola; Riedl, Lina; Dorn, Bianca; Fischer, Julia; Slawik, Till; Fleischhaker, Mareike; Hartmann, Florentine; Egert-Schwender, Silvia; Kehl, Victoria; Haller, Bernhard; Schneider-Schelte, Helga; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Advanced stages of dementia are characterized by severe cognitive and physical impairment. It has not yet been investigated whether persons with young onset dementia (YOD) and late onset dementia (LOD) differ in advanced disease stages. OBJECTIVES: To compare quality of life (QoL) between persons with advanced YOD and LOD; to explore the determinants of QoL; to investigate whether YOD and LOD differ with regard to symptoms and care. METHODS: The study was performed in the context of EPYLOGE (IssuEs in Palliative care for persons in advanced and terminal stages of YOD and LOD in Germany). Persons with advanced dementia (PWAD) were assessed and caregivers were interviewed. QoL was measured with the proxy rating Quality of Life in Late Stage Dementia (QUALID) scale. RESULTS: 93 persons with YOD and 98 with LOD were included. No significant differences in QoL were detected. Determinants of QoL were similar in YOD and LOD. Behavioral and psychological symptoms of dementia (BPSD), suffering and other distressing symptoms were associated with a lower QoL. In YOD but not in LOD antipsychotic treatment was associated with low QoL. The group of persons who were younger than 65 years at the time of the study visit experienced significantly more distressing symptoms than older PWAD. CONCLUSION: Overall, persons with advanced YOD do not appear to be disadvantaged compared to old and oldest PWAD. Special attention, however, must be paid to the group of the very young persons who seem to be particularly vulnerable.
Keywords: Adult; Age of Onset; Aged; Aged, 80 and over; Antipsychotic Agents; Behavioral Symptoms; Caregivers; Dementia; Disease Progression; Female; Germany; Home Care Services; Humans; Individuality; Male; Middle Aged; Pain; Palliative Care; Psychotropic Drugs; Quality of Life

Race/Ethnic Disparities in Mild Cognitive Impairment and Dementia: The Northern Manhattan Study. - Wright, Clinton B; DeRosa, Janet T; Moon, Michelle P; Strobino, Kevin; DeCarli, Charles; Cheung, Ying Kuen; Assuras, Stephanie; Levin, Bonnie; Stern, Yaakov; Sun, Xiaoyan; Rundek, Tatjana; Elkind, Mitchell S V; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Variability in dementia rates across racial and ethnic groups has been estimated at 60%. Studies suggest disparities in Caribbean Hispanic and Black populations, but community-based data are limited. OBJECTIVE: Estimate the prevalence of mild cognitive impairment (MCI) and dementia in the racially and ethnically diverse community-based Northern Manhattan Study cohort and examine sociodemographic, vascular risk factor, and brain imaging correlates. METHODS: Cases of MCI and dementia were adjudicated by a team of neuropsychologists and neurologists and prevalence was estimated across race/ethnic groups. Ordinal proportional odds models were used to estimate race/ethnic differences in the prevalence of MCI or dementia adjusting for sociodemographic variables (model 1), model 1 plus potentially modifiable vascular risk factors (model 2), and model 1 plus structural imaging markers of brain integrity (model 3). RESULTS: There were 989 participants with cognitive outcome determinations (mean age 69±9 years; 68% Hispanic, 16% Black, 14% White; 62% women; mean (±SD) follow-up five (±0.6) years). Hispanic and Black participants had greater likelihood of MCI (20%) and dementia (5%) than White participants accounting for age and education differences. Hispanic participants had greater odds of MCI or dementia than both White and Black participants adjusting for sociodemographic variables, vascular risk factors, and brain imaging factors. White matter hyperintensity burden was significantly associated with greater odds of MCI or dementia (OR = 1.3, 1.1 to 1.6), but there was no significant interaction by race/ethnicity. CONCLUSION: In this diverse community-based cohort, cross-sectional data revealed significant race/ethnic disparities in the prevalence of MCI and dementia. Longer follow-up and incidence data are needed to further clarify these relationships.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Cohort Studies; Cross-Sectional Studies; Dementia; Ethnicity; Female; Humans; Male; Middle Aged; New York City; Prevalence

Reliability of Telephone and Videoconference Methods of Cognitive Assessment in Older Adults with and without Dementia. - Hunter, Matthew B; Jenkins, Natalie; Dolan, Clare; Pullen, Hannah; Ritchie, Craig; Muniz-Terrera, Graciela (J Alzheimers Dis, 2021)
BACKGROUND: Telephone and videoconference administration of cognitive tests introduce additional sources of variance compared to in-person testing. Reviews of test-retest reliability have included mixed neurocognitive and psychiatric populations with limited consideration of methodological and statistical contributions. OBJECTIVE: We reviewed reliability estimates from comparison studies of older adults with and without dementia, considering test-retest analyses and study methods. METHODS: Medline, Embase, PsycINFO, and Web of Science were systematically searched from 1 January 2000 to 9 June 2020 for original articles comparing telephone or videoconference administered cognitive instruments to in-person administration in older adults with and without dementia or mild cognitive impairment. RESULTS: Of 4,125 articles, 23 were included: 11 telephone (N = 2 dementia cohorts) and 12 videoconference (N = 4 dementia cohorts). Telephone administered subtest scores trended in the same direction as in-person with comparable means. Person-level data were scarce. Data on dementia was only available for MMSE, with resulting subtle modality bias. MMSE, SMMSE, Letter Fluency, and HVLT-R in healthy to mild-moderate Alzheimer's disease were particularly reliable for videoconference administration. Other tests show promise but require more observations and comprehensive analyses. Most studies used high-speed stable videoconferencing hardware resulting in a lack of ecological validity for home administration. CONCLUSION: Remote administration is often consistent with in-person administration but variable and limited at the person/test level. Improved statistical design and inclusion of dementia related cohorts in telephone studies is recommended. Reliability evidence is stronger for videoconferencing but with limited applicability to home administration and severe dementia. Improved reporting of administrative procedures is recommended.
Keywords: Aged; Aged, 80 and over; Cognition; Cognitive Dysfunction; Dementia; Geriatric Assessment; Humans; Neuropsychological Tests; Remote Consultation; Reproducibility of Results; Telephone; Videoconferencing

The Right Temporal Variant of Frontotemporal Dementia Is Not Genetically Sporadic: A Case Series. - Ulugut Erkoyun, Hulya; van der Lee, Sven J; Nijmeijer, Bas; van Spaendonk, Rosalina; Nelissen, Anne; Scarioni, Marta; Dijkstra, Anke; Samancı, Bedia; Gürvit, Hakan; Yıldırım, Zerrin; Tepgeç, Fatih; Bilgic, Basar; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Right temporal variant frontotemporal dementia (rtvFTD) has been generally considered as a right sided variant of semantic variant primary progressive aphasia (svPPA), which is a genetically sporadic disorder. Recently, we have shown that rtvFTD has a unique clinical syndrome compared to svPPA and behavioral variant frontotemporal dementia. OBJECTIVE: We challenge the assumption that rtvFTD is a sporadic, non-familial variant of FTD by identifying potential autosomal dominant inheritance and related genes in rtvFTD. METHODS: We collected all subjects with a diagnosis of FTD or primary progressive aphasia who had undergone genetic screening (n = 284) and subsequently who had a genetic variant (n = 48) with a diagnosis of rtvFTD (n = 6) in 2 specialized memory clinics. RESULTS: Genetic variants in FTD related genes were found in 33% of genetically screened rtvFTD cases; including MAPT (n = 4), GRN (n = 1), and TARDBP (n = 1) genes, whereas only one svPPA case had a genetic variant in our combined cohorts. Additionally, 4 out of 6 rtvFTD subjects had a strong family history for dementia. CONCLUSION: Our results demonstrate that rtvFTD, unlike svPPA, is not a pure sporadic, but a heterogeneous potential genetic variant of FTD, and screening for genetic causes for FTD should be performed in patients with rtvFTD.
Keywords: Aphasia, Primary Progressive; DNA-Binding Proteins; Female; Frontotemporal Dementia; Functional Laterality; Genetic Testing; Genetic Variation; Gyrus Cinguli; Humans; Male; Middle Aged; Progranulins; tau Proteins

Risk Variants in Three Alzheimer's Disease Genes Show Association with EEG Endophenotypes. - Macedo, Ana; Gómez, Carlos; Rebelo, Miguel Ângelo; Poza, Jesús; Gomes, Iva; Martins, Sandra; Maturana-Candelas, Aarón; Pablo, Víctor Gutiérrez-de; Durães, Luis; Sousa, Patrícia; Figueruelo, Manuel; Rodriguez, Maria; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Dementia due to Alzheimer's disease (AD) is a complex neurodegenerative disorder, which much of heritability remains unexplained. At the clinical level, one of the most common physiological alterations is the slowing of oscillatory brain activity, measurable by electroencephalography (EEG). Relative power (RP) at the conventional frequency bands (i.e., delta, theta, alpha, beta-1, and beta-2) can be considered as AD endophenotypes. OBJECTIVE: The aim of this work is to analyze the association between sixteen genes previously related with AD: APOE, PICALM, CLU, BCHE, CETP, CR1, SLC6A3, GRIN2 β, SORL1, TOMM40, GSK3 β, UNC5C, OPRD1, NAV2, HOMER2, and IL1RAP, and the slowing of the brain activity, assessed by means of RP at the aforementioned frequency bands. METHODS: An Iberian cohort of 45 elderly controls, 45 individuals with mild cognitive impairment, and 109 AD patients in the three stages of the disease was considered. Genomic information and brain activity of each subject were analyzed. RESULTS: The slowing of brain activity was observed in carriers of risk alleles in IL1RAP (rs10212109, rs9823517, rs4687150), UNC5C (rs17024131), and NAV2 (rs1425227, rs862785) genes, regardless of the disease status and situation towards the strongest risk factors: age, sex, and APOE ɛ4 presence. CONCLUSION: Endophenotypes reduce the complexity of the general phenotype and genetic variants with a major effect on those specific traits may be then identified. The found associations in this work are novel and may contribute to the comprehension of AD pathogenesis, each with a different biological role, and influencing multiple factors involved in brain physiology.

Sleep Deprivation, a Link Between Post-Traumatic Stress Disorder and Alzheimer's Disease. - Delic, Vedad; Ratliff, Whitney A; Citron, Bruce A (J Alzheimers Dis, 2021)
An estimated 5 million Americans are living with Alzheimer's disease (AD), and there is also a significant impact on caregivers, with an additional 16 million Americans providing unpaid care for individuals with AD and other dementias. These numbers are projected to increase in the coming years. While AD is still without a cure, continued research efforts have led to better understanding of pathology and potential risk factors that could be exploited to slow disease progression. A bidirectional relationship between sleep deprivation and AD has been suggested and is well supported by both human and animal studies. Even brief episodes of inadequate sleep have been shown to cause an increase in amyloidβ and tau proteins, both well-established contributors toAD pathology. Sleep deprivation is also the most common consequence of post-traumatic stress disorder (PTSD). Patients with PTSD frequently present with sleep disturbances and also develop dementia at twice the rate of the general population accounting for a disproportionate representation of AD among U.S. Veterans. The goal of this review is to highlight the relationship triad between sleep deprivation, AD, and PTSD as well as their impact on molecular mechanisms driving AD pathology.
Keywords: Alzheimer Disease; Animals; Humans; Sleep Deprivation; Stress Disorders, Post-Traumatic

Substance Use-Related Cognitive Decline in Families with Autosomal Dominant Alzheimer's Disease: A Cohort Study. - Ramos, Claudia; Villalba, Camilo; García, Jenny; Lanata, Serggio; López, Hugo; Aguillón, David; Cordano, Christian; Madrigal, Lucía; Aguirre-Acevedo, Daniel C; Lopera, Francisco (J Alzheimers Dis, 2021)
BACKGROUND: Cigarette smoking is a known risk factor for Alzheimer's disease (AD). However, the association between neurodegeneration and other substances has not been fully determined. It is of vital importance to evaluate this relationship in populations at high risk of dementia. Since substance use possibly modifies the progression rate of cognitive decline, we studied this association in a unique and well-phenotyped cohort from the University of Antioquia: carriers of the PSEN1-E280A genetic variant. OBJECTIVE: To determine the association between substance use and cognitive decline in carriers of the PSEN1-E280A genetic variant. METHODS: A retrospective cohort study was conducted with 94 carriers and 69 noncarriers recruited between January 2019 and April 2020. A psychiatrist interviewed the participants using the Consumption of Alcohol, Cigarettes and other Substances questionnaire. The participants were also submitted to cognitive evaluation. The relationship between cognitive decline and substance use was explored through a mixed effects regression model. RESULTS: There was an association between cigarettes and better performance on tasks related to perceptual organization, verbal fluency, and memory in carriers. Alcohol had a positive or negative effect on memory according to the type of alcoholic beverage. Results on marijuana use were no conclusive. Coffee was associated with progressive improvements in executive function and verbal fluency. CONCLUSION: Cigarette and alcohol were associated with an improvement of some cognitive assessments, possibly by a survival bias. In addition, coffee was related to improvements in executive function and language; therefore, its short-term neuroprotective potential should be studied.

Sustained Hippocampal Neural Plasticity Questions the Reproducibility of an Amyloid-β-Induced Alzheimer's Disease Model. - Paulo, Sara L; Ribeiro-Rodrigues, Leonor; Rodrigues, Rui S; Mateus, Joana M; Fonseca-Gomes, João; Soares, Rita; Diógenes, Maria J; Solá, Susana; Sebastião, Ana M; Ribeiro, Filipa F; Xapelli, Sara (J Alzheimers Dis, 2021)
BACKGROUND: The use of Alzheimer's disease (AD) models obtained by intracerebral infusion of amyloid-β (Aβ) has been increasingly reported in recent years. Nonetheless, these models may present important challenges. OBJECTIVE: We have focused on canonical mechanisms of hippocampal-related neural plasticity to characterize a rat model obtained by an intracerebroventricular (icv) injection of soluble amyloid-β42 (Aβ42). METHODS: Animal behavior was evaluated in the elevated plus maze, Y-Maze spontaneous or forced alternation, Morris water maze, and open field, starting 2 weeks post-Aβ42 infusion. Hippocampal neurogenesis was assessed 3 weeks after Aβ42 injection. Aβ deposition, tropomyosin receptor kinase B levels, and neuroinflammation were appraised at 3 and 14 days post-Aβ42 administration. RESULTS: We found that immature neuronal dendritic morphology was abnormally enhanced, but proliferation and neuronal differentiation in the dentate gyrus was conserved one month after Aβ42 injection. Surprisingly, animal behavior did not reveal changes in cognitive performance nor in locomotor and anxious-related activity. Brain-derived neurotrophic factor related-signaling was also unchanged at 3 and 14 days post-Aβ icv injection. Likewise, astrocytic and microglial markers of neuroinflammation in the hippocampus were unaltered in these time points. CONCLUSION: Taken together, our data emphasize a high variability and lack of behavioral reproducibility associated with these Aβ injection-based models, as well as the need for its further optimization, aiming at addressing the gap between preclinical AD models and the human disorder.

Taking the A Train? Limited Consistency of Aβ42 and the Aβ42/40 Ratio in the AT(N) Classification. - Gouilly, Dominique; Tisserand, Camille; Nogueira, Leonor; Saint-Lary, Laura; Rousseau, Vanessa; Benaiteau, Marie; Rafiq, Marie; Carlier, Jasmine; Milongo-Rigal, Emilie; Pagès, Jean-Christophe; Pariente, Jérémie (J Alzheimers Dis, 2021)
The consistency of cerebrospinal fluid amyloid-β (Aβ)42/40 ratio and Aβ 42 has not been assessed in the AT(N) classification system. We analyzed the classification changes of the dichotomized amyloid status (A+/A-) in 363 patients tested for Alzheimer's disease biomarkers after Aβ 42 was superseded by the Aβ 42/40 ratio. The consistency of Aβ 42 and the Aβ 42/40 ratio was very low. Notably, the proportions of "false" A+T-patients were considerable (74-91%) and corresponded mostly to patients not clinically diagnosed with Alzheimer's disease. Our results suggest that the interchangeability of Aβ 42/40 ratio and Aβ 42 is limited for classifying patients in clinical setting using the AT(N) scheme.

TAR DNA-Binding Protein 43 Is Associated with Rate of Memory and Functional and Global Cognitive Decline in the Decade Prior to Death. - Buciuc, Marina; Tosakulwong, Nirubol; Machulda, Mary M; Whitwell, Jennifer L; Weigand, Stephen D; Murray, Melissa E; Ross Reichard, R; Parisi, Joseph E; Dickson, Dennis W; Boeve, Bradley F; Knopman, David S; Petersen, Ronald C; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Transactive response DNA-binding protein of 43 kDa (TDP-43) is associated with memory impairment and overall cognitive decline. It is unclear how TDP-43 contributes to the rate of clinical decline. OBJECTIVE: To determine whether cross-sectional and longitudinal cognitive and functional decline are associated with anatomical distribution of TDP-43 in the brain. METHODS: Longitudinal clinical-neuropathologic autopsy cohort study of 385 initially cognitively normal/mildly impaired older adults prospectively followed until death. We investigated how TDP-43, amyloid-β (Aβ), tau neurofibrillary tangles (NFT), Lewy body disease (LBD), age, sex, and genetics are associated with clinical scores and rates of their longitudinal decline. RESULTS: Of 385 participants, 260 (68%) had no TDP-43, 32 (8%) TDP-43 limited to amygdala, and 93 (24%) TDP-43 in the hippocampus and beyond. Higher TDP-43 and Braak NFT stages independently were associated with faster decline in global cognition, functional performance measured by Clinical Dementia Rating scale, and naming and episodic memory, whereas older age was associated with slower rate of cognitive, psychiatric, and functional decline. Cross-sectionally the following associations were found: higher TDP-43 and Braak NFT - worse performance; higher Aβ burden - worse global cognition, more behavioral changes, the latter also with higher LBD; older age - worse naming, lower frequency of behavioral changes; female sex - more impaired naming and better preserved episodic memory. There were no genetic associations. CONCLUSION: The association of TDP-43 distribution with decline in cognitive and functional performance suggests that TDP-43 is playing a role in the clinical progression to dementia. Further characterization of clinical features associated with TDP-43 can facilitate establishment of antemortem diagnosis.

Thrombin Signaling Contributes to High Glucose-Induced Injury of Human Brain Microvascular Endothelial Cells. - Rao, Haripriya V; Bihaqi, Syed W; Iannucci, Jaclyn; Sen, Abhik; Grammas, Paula (J Alzheimers Dis, 2021)
BACKGROUND: Diabetes is one of the strongest disease-related risk factors for Alzheimer's disease (AD). In diabetics, hyperglycemia-induced microvascular complications are the major cause of end-organ injury, contributing to morbidity and mortality. Microvascular pathology is also an important and early feature of AD. The cerebral microvasculature may be a point of convergence of both diseases. Several lines of evidence also implicate thrombin in AD as well as in diabetes. OBJECTIVE: Our objective was to investigate the role of thrombin in glucose-induced brain microvascular endothelial injury. METHODS: Cultured Human brain microvascular endothelial cells (HBMVECs) were treated with 30 mM glucose±100 nM thrombin and±250 nM Dabigatran or inhibitors of PAR1, p38MAPK, MMP2, or MMP9. Cytotoxicity and thrombin activity assays on supernatants and western blotting for protein expression in lysates were performed. RESULTS: reatment of HBMVECs with 30 mM glucose increased thrombin activity and expression of inflammatory proteins TNFα, IL-6, and MMPs 2 and 9; this elevation was reduced by the thrombin inhibitor dabigatran. Direct treatment of brain endothelial cells with thrombin upregulated p38MAPK and CREB, and induced TNFα, IL6, MMP2, and MMP9 as well as oxidative stress proteins NOX4 and iNOS. Inhibition of thrombin, thrombin receptor PAR1 or p38MAPK decrease expression of inflammatory and oxidative stress proteins, implying that thrombin may play a central role in glucose-induced endothelial injury. CONCLUSION: Since preventing brain endothelial injury would preserve blood-brain barrier integrity, prevent neuroinflammation, and retain intact functioning of the neurovascular unit, inhibiting thrombin, or its downstream signaling effectors, could be a therapeutic strategy for mitigating diabetes-induced dementia.

Time Trends of Cerebrospinal Fluid Biomarkers of Neurodegeneration in Idiopathic Normal Pressure Hydrocephalus. - Lukkarinen, Heikki; Tesseur, Ina; Pemberton, Darrel; van der Ark, Peter; Timmers, Maarten; Slemmon, Randy; Janssens, Luc; Streffer, Johannes; Van Nueten, Luc; Bottelbergs, Astrid; Rauramaa, Tuomas; Koivisto, Anne M; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Longitudinal changes in cerebrospinal fluid (CSF) biomarkers are seldom studied. Furthermore, data on biomarker gradient between lumbar (L-) and ventricular (V-) compartments seems to be discordant. OBJECTIVE: To examine alteration of CSF biomarkers reflecting Alzheimer's disease (AD)-related amyloid-β (Aβ) aggregation, tau pathology, neurodegeneration, and early synaptic degeneration by CSF shunt surgery in idiopathic normal pressure hydrocephalus (iNPH) in relation to AD-related changes in brain biopsy. In addition, biomarker levels in L- and V-CSF were compared. METHODS: L-CSF was collected prior to shunt placement and, together with V-CSF, 3-73 months after surgery. Thereafter, additional CSF sampling took place at 3, 6, and 18 months after the baseline sample from 26 iNPH patients with confirmed Aβ plaques in frontal cortical brain biopsy and 13 iNPH patients without Aβ pathology. CSF Amyloid-β42 (Aβ42), total tau (T-tau), phosphorylated tau (P-tau181), neurofilament light (NFL), and neurogranin (NRGN) were analyzed with customized ELISAs. RESULTS: All biomarkers but Aβ42 increased notably by 140-810% in L-CSF after CSF diversion and then stabilized. Aβ42 instead showed divergent longitudinal decrease between Aβ-positive and -negative patients in L-CSF, and thereafter increase in Aβ-negative iNPH patients in both L- and V-CSF. All five biomarkers correlated highly between V-CSF and L-CSF (Aβ42 R = 0.87, T-tau R = 0.83, P-tau R = 0.92, NFL R = 0.94, NRGN R = 0.9; all p <  0.0001) but were systematically lower in V-CSF (Aβ42 14 %, T-tau 22%, P-tau 20%, NFL 32%, NRGN 19%). With APOE genotype-grouping, only Aβ42 showed higher concentration in non-carriers of allele ɛ4. CONCLUSION: Longitudinal follow up shows that after an initial post-surgery increase, T-tau, P-tau, and NRGN are stable in iNPH patients regardless of brain biopsy Aβ pathology, while NFL normalized toward its pre-shunt levels. Aβ42 as biomarker seems to be the least affected by the surgical procedure or shunt and may be the best predictor of AD risk in iNPH patients. All biomarker concentrations were lower in V- than L-CSF yet showing strong correlations.

Upregulation of Local Hepcidin Contributes to Iron Accumulation in Alzheimer's Disease Brains. - Chaudhary, Suman; Ashok, Ajay; McDonald, Dallas; Wise, Aaron S; Kritikos, Alexander E; Rana, Neil A; Harding, Clifford V; Singh, Neena (J Alzheimers Dis, 2021)
BACKGROUND: Accumulation of iron is a consistent feature of Alzheimer's disease (AD) brains. The underlying cause, however, remains debatable. OBJECTIVE: To explore whether local hepcidin synthesized by brain cells contributes to iron accumulation in AD brains. METHODS: Brain tissue from the cingulate cortex of 33 cases of AD pre-assigned to Braak stage I-VI, 6 cases of non-dementia, and 15 cases of non-AD dementia were analyzed for transcriptional upregulation of hepcidin by RT-qPCR and RT-PCR. Change in the expression of ferritin, ferroportin (Fpn), microglial activation marker Iba1, IL-6, and TGFβ2 was determined by western blotting. Total tissue iron was determined by colorimetry. RESULTS: Significant transcriptional upregulation of hepcidin was observed in Braak stage III-VI relative to Braak stage I and II, non-AD dementia, and non-dementia samples. Ferritin was increased in Braak stage V, and a significant increase in tissue iron was evident in Braak stage III-VI. The expression of Iba1 and IL-6 was also increased in Braak stage III-VI relative to Braak stage I and II and non-AD dementia samples. Amyloid-β plaques were absent in most Braak stage I and II samples, and present in Braak stage III-VI samples with few exceptions. CONCLUSION: These observations suggest that upregulation of brain hepcidin is mediated by IL-6, a known transcriptional activator of hepcidin. The consequent downregulation of Fpn on neuronal and other cells results in accumulation of iron in AD brains. The increase in hepcidin is disease-specific, and increases with disease progression, implicating AD-specific pathology in the accumulation of iron.

An Active Lifestyle Is Associated with Better Cognitive Function Over Time in APOE ɛ4 Non-Carriers. - Fernández-Matarrubia, Marta; Goni, Leticia; Rognoni, Teresa; Razquin, Cristina; Fernández-Lázaro, César Ignacio; Bes-Rastrollo, Maira; Martínez-González, Miguel Ángel; Toledo, Estefanía (J Alzheimers Dis, 2020)
BACKGROUND: Available evidence on the association of physical activity (PA) or sedentary behavior with cognitive decline is inconclusive. OBJECTIVE: To assess the association between an active lifestyle score and leisure-time physical activity (LTPA) and changes in cognitive function in the Seguimiento Universidad de Navarra (SUN) prospective cohort. METHODS: Cognitive function was evaluated in a subsample of 806 participants of the SUN cohort study using the validated Telephone Interview for Cognitive Status-modified (STICS-m) questionnaire at baseline and after 6 years. LTPA was evaluated with a previously validated 17-item self-administered questionnaire and with information on sedentary lifestyles. We also calculated a multidimensional 8-item PA score. Multivariable linear regression analysis evaluated the association between PA and changes in cognitive function and its interaction by APOE genotype. RESULTS: Mean age of participants was 66 (SD 5.3) years and 69.7% were male. When stratifying by APOE variants, no significant associations between the active lifestyle score or LTPA and changes in cognitive performance over time were found among APOE ɛ4 carriers. However, we observed that a higher adherence to an active lifestyle (high versus low PA score β= 0.76 95% CI 0.15,1.36; p trend = 0.011) and a high LTPA (Q4 versus Q1 β= 0.63; 95% CI -0.01,1.26; p trend = 0.030) were associated with more favorable changes in cognitive function over time among APOE ɛ4 non-carriers with statistically significant interactions in both cases (p for interaction = 0.042 for PA score, and p = 0.039 for LTPA). CONCLUSION: The results of the present study suggest that an active lifestyle is associated with a better status of cognitive function over time only among APOE ɛ4 non-carriers.

Age-Related Intraneuronal Aggregation of Amyloid-β in Endosomes, Mitochondria, Autophagosomes, and Lysosomes. - Brewer, Gregory J; Herrera, Robert A; Philipp, Stephan; Sosna, Justyna; Reyes-Ruiz, Jorge Mauricio; Glabe, Charles G (J Alzheimers Dis, 2020)
This work provides new insight into the age-related basis of Alzheimer's disease (AD), the composition of intraneuronal amyloid (iAβ), and the mechanism of an age-related increase in iAβ in adult AD-model mouse neurons. A new end-specific antibody for Aβ45 and another for aggregated forms of Aβ provide new insight into the composition of iAβ and the mechanism of accumulation in old adult neurons from the 3xTg-AD model mouse. iAβ levels containing aggregates of Aβ45 increased 30-50-fold in neurons from young to old age and were further stimulated upon glutamate treatment. iAβ was 8 times more abundant in 3xTg-AD than non-transgenic neurons with imaged particle sizes following the same log-log distribution, suggesting a similar snow-ball mechanism of intracellular biogenesis. Pathologically misfolded and mislocalized Alz50 tau colocalized with iAβ and rapidly increased following a brief metabolic stress with glutamate. AβPP-CTF, Aβ45, and aggregated Aβ colocalized most strongly with mitochondria and endosomes and less with lysosomes and autophagosomes. Differences in iAβ by sex were minor. These results suggest that incomplete carboxyl-terminal trimming of long Aβs by gamma-secretase produced large intracellular deposits which limited completion of autophagy in aged neurons. Understanding the mechanism of age-related changes in iAβ processing may lead to application of countermeasures to prolong dementia-free health span.

Alzheimer's Disease-Like Neurodegeneration in Porphyromonas gingivalis Infected Neurons with Persistent Expression of Active Gingipains. - Haditsch, Ursula; Roth, Theresa; Rodriguez, Leo; Hancock, Sandy; Cecere, Thomas; Nguyen, Mai; Arastu-Kapur, Shirin; Broce, Sean; Raha, Debasish; Lynch, Casey C; Holsinger, Leslie J; Dominy, Stephen S; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Porphyromonas gingivalis (P. gingivalis) and its gingipain virulence factors have been identified as pathogenic effectors in Alzheimer's disease (AD). In a recent study we demonstrated the presence of gingipains in over 90% of postmortem AD brains, with gingipains localizing to the cytoplasm of neurons. However, infection of neurons by P. gingivalis has not been previously reported. OBJECTIVE: To demonstrate intraneuronal P. gingivalis and gingipain expression in vitro after infecting neurons derived from human inducible pluripotent stem cells (iPSC) with P. gingivalis for 24, 48, and 72 h. METHODS: Infection was characterized by transmission electron microscopy, confocal microscopy, and bacterial colony forming unit assays. Gingipain expression was monitored by immunofluorescence and RT-qPCR, and protease activity monitored with activity-based probes. Neurodegenerative endpoints were assessed by immunofluorescence, western blot, and ELISA. RESULTS: Neurons survived the initial infection and showed time dependent, infection induced cell death. P. gingivalis was found free in the cytoplasm or in lysosomes. Infected neurons displayed an accumulation of autophagic vacuoles and multivesicular bodies. Tau protein was strongly degraded, and phosphorylation increased at T231. Over time, the density of presynaptic boutons was decreased. CONCLUSION: P. gingivalis can invade and persist in mature neurons. Infected neurons display signs of AD-like neuropathology including the accumulation of autophagic vacuoles and multivesicular bodies, cytoskeleton disruption, an increase in phospho-tau/tau ratio, and synapse loss. Infection of iPSC-derived mature neurons by P. gingivalis provides a novel model system to study the cellular mechanisms leading to AD and to investigate the potential of new therapeutic approaches.

Amyloid-β Causes Mitochondrial Dysfunction via a Ca2+-Driven Upregulation of Oxidative Phosphorylation and Superoxide Production in Cerebrovascular Endothelial Cells. - Quintana, Dominic D; Garcia, Jorge A; Anantula, Yamini; Rellick, Stephanie L; Engler-Chiurazzi, Elizabeth B; Sarkar, Saumyendra N; Brown, Candice M; Simpkins, James W (J Alzheimers Dis, 2020)
Cerebrovascular pathology is pervasive in Alzheimer's disease (AD), yet it is unknown whether cerebrovascular dysfunction contributes to the progression or etiology of AD. In human subjects and in animal models of AD, cerebral hypoperfusion and hypometabolism are reported to manifest during the early stages of the disease and persist for its duration. Amyloid-β is known to cause cellular injury in both neurons and endothelial cells by inducing the production of reactive oxygen species and disrupting intracellular Ca2+ homeostasis. We present a mechanism for mitochondrial degeneration caused by the production of mitochondrial superoxide, which is driven by increased mitochondrial Ca2+ uptake. We found that persistent superoxide production injures mitochondria and disrupts electron transport in cerebrovascular endothelial cells. These observations provide a mechanism for the mitochondrial deficits that contribute to cerebrovascular dysfunction in patients with AD.

APOE4 Status is Related to Differences in Memory-Related Brain Function in Asymptomatic Older Adults with Family History of Alzheimer's Disease: Baseline Analysis of the PREVENT-AD Task Functional MRI Dataset. - Rabipour, Sheida; Rajagopal, Sricharana; Yu, Elsa; Pasvanis, Stamatoula; Lafaille-Magnan, Marie-Elyse; Breitner, John; Rajah, M Natasha (J Alzheimers Dis, 2020)
BACKGROUND: Episodic memory decline is one of the earliest symptoms of late-onset Alzheimer's disease (AD). Older adults with the apolipoprotein E ɛ4 (+APOE4) genetic risk factor for AD may exhibit altered patterns of memory-related brain activity years prior to initial symptom onset. OBJECTIVE: Here we report the baseline episodic memory task functional MRI results from the PRe-symptomatic EValuation of Experimental or Novel Treatments for Alzheimer's Disease cohort in Montreal, Canada, in which 327 healthy older adults were scanned within 15 years of their parent's conversion to AD. METHODS: Volunteers were scanned as they encoded and retrieved object-location spatial source associations. The task was designed to discriminate between brain activity related to spatial source recollection and object-only (recognition) memory. We used multivariate partial least squares (PLS) to test the hypothesis that +APOE4 adults with family history of AD would exhibit altered patterns of brain activity in the recollection-related memory network, comprised of medial frontal, parietal, and medial temporal cortices, compared to APOE4 non-carriers (-APOE4). We also examined group differences in the correlation between event-related brain activity and memory performance. RESULTS: We found group similarities in memory performance and in task-related brain activity in the recollection network, but differences in brain activity-behavior correlations in ventral occipito-temporal, medial temporal, and medial prefrontal cortices during episodic encoding. CONCLUSION: These findings are consistent with previous literature on the influence of APOE4 on brain activity and provide new perspective on potential gene-based differences in brain-behavior relationships in people with first-degree family history of AD.

Association of Peripheral Insulin Resistance and Other Markers of Type 2 Diabetes Mellitus with Brain Amyloid Deposition in Healthy Individuals at Risk of Dementia. - Pekkala, Timo; Hall, Anette; Mangialasche, Francesca; Kemppainen, Nina; Mecocci, Patrizia; Ngandu, Tiia; Rinne, Juha O; Soininen, Hilkka; Tuomilehto, Jaakko; Kivipelto, Miia; Solomon, Alina (J Alzheimers Dis, 2020)
We explored the association of type 2 diabetes related blood markers with brain amyloid accumulation on PiB-PET scans in 41 participants from the FINGER PET sub-study. We built logistic regression models for brain amyloid status with12 plasma markers of glucose and lipid metabolism, controlled for diabetes and APOEɛ4 carrier status. Lower levels of insulin, insulin resistance index (HOMA-IR), C-peptide, and plasminogen activator (PAI-1) were associated with amyloid positive status, although the results were not significant after adjusting for multiple testing. None of the models found evidence for associations between amyloid status and fasting glucose or HbA1c.

Brain Volume Predicts Behavioral and Psychological Symptoms in Alzheimer's Disease. - Boublay, Nawele; Bouet, Romain; Dorey, Jean-Michel; Padovan, Catherine; Makaroff, Zaza; Federico, Denis; Gallice, Isabelle; Barrellon, Marie-Odile; Robert, Philippe; Moreaud, Olivier; Rouch, Isabelle; Krolak-Salmon, Pierre (J Alzheimers Dis, 2020)
BACKGROUND: Behavioral and psychological symptoms of dementia (BPSD) are frequent and troublesome for patients and caregivers. Considering possible preventive approaches, a better understanding of underlying neural correlates of BPSD is crucial. OBJECTIVE: The aim is to assess whether brain regional volume predicts behavioral changes in mild AD. METHODS: This work took part from the PACO study, a multicenter and prospective study that included 252 patients with mild AD from 2009 to 2014. Fifty-three patients were retained. Forty healthy matched control subjects from the ADNI cohort were included as controls. Voxel-based morphometry analysis was conducted to assess regional brain volume using baseline MRI scans as a predictor of future behavioral changes over a period of 18 months. Behavior was assessed at baseline and longitudinally at 6-month intervals using the shortened form of the Neuropsychiatric Inventory (NPI). RESULTS: The volume of 23 brain structures in frontal, temporal, parietal, occipital, subcortical regions and cerebellum predicted the evolution of NPI scores. Frontal volume was the most powerful predictor with frontal gyri, anterior cingulate cortex, and orbital gyri being particularly involved. CONCLUSION: To our knowledge, this is the first study assessing regional brain volumes as predictors of behavioral changes considered at earlier stages of AD. Up to 23 brain structures were associated with an increased risk of developing BPSD. Frontal lobe volume was the strongest predictor of future evolution of NPI. The involvement of multiple structures in the prediction of behavior suggests a role of the main large-scale networks involved in cognition.

Cognitive Impairment Is a Common Comorbidity in Deceased COVID-19 Patients: A Hospital-Based Retrospective Cohort Study. - Martín-Jiménez, Paloma; Muñoz-García, Mariana I; Seoane, David; Roca-Rodríguez, Lucas; García-Reyne, Ana; Lalueza, Antonio; Maestro, Guillermo; Folgueira, Dolores; Blanco-Palmero, Víctor A; Herrero-San Martín, Alejandro; Llamas-Velasco, Sara; Pérez-Martínez, David A; et al. (J Alzheimers Dis, 2020)
We analyzed the frequency of cognitive impairment (CI) in deceased COVID-19 patients at a tertiary hospital in Spain. Among the 477 adult cases who died after admission from March 1 to March 31, 2020, 281 had confirmed COVID-19. CI (21.1% dementia and 8.9% mild cognitive impairment) was a common comorbidity. Subjects with CI were older, tended to live in nursing homes, had shorter time from symptom onset to death, and were rarely admitted to the ICU, receiving palliative care more often. CI is a frequent comorbidity in deceased COVID-19 subjects and is associated with differences in care.
Keywords: Adolescent; Adult; Age Factors; Aged; Aged, 80 and over; Cognitive Dysfunction; Comorbidity; COVID-19; Female; Hospital Mortality; Hospitals; Humans; Male; Middle Aged; Palliative Care; Patient Admission; Retrospective Studies; Spain; Young Adult

Comorbidity of Cerebrovascular and Alzheimer's Disease in Aging. - Xia, Ying; Yassi, Nawaf; Raniga, Parnesh; Bourgeat, Pierrick; Desmond, Patricia; Doecke, James; Ames, David; Laws, Simon M; Fowler, Christopher; Rainey-Smith, Stephanie R; Martins, Ralph; Maruff, Paul; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Cerebrovascular disease often coexists with Alzheimer's disease (AD). While both diseases share common risk factors, their interrelationship remains unclear. Increasing the understanding of how cerebrovascular changes interact with AD is essential to develop therapeutic strategies and refine biomarkers for early diagnosis. OBJECTIVE: We investigate the prevalence and risk factors for the comorbidity of amyloid-β (Aβ) and cerebrovascular disease in the Australian Imaging, Biomarkers and Lifestyle Study of Ageing, and further examine their cross-sectional association. METHODS: A total of 598 participants (422 cognitively normal, 89 with mild cognitive impairment, 87 with AD) underwent positron emission tomography and structural magnetic resonance imaging for assessment of Aβ deposition and cerebrovascular disease. Individuals were categorized based on the comorbidity status of Aβ and cerebrovascular disease (V) as Aβ-V-, Aβ-V+, Aβ+V-, or Aβ+V+. RESULTS: Advancing age was associated with greater likelihood of cerebrovascular disease, high Aβ load and their comorbidity. Apolipoprotein E ɛ4 carriage was only associated with Aβ positivity. Greater total and regional WMH burden were observed in participants with AD. However, no association were observed between Aβ and WMH measures after stratification by clinical classification, suggesting that the observed association between AD and cerebrovascular disease was driven by the common risk factor of age. CONCLUSION: Our observations demonstrate common comorbid condition of Aβ and cerebrovascular disease in later life. While our study did not demonstrate a convincing cross-sectional association between Aβ and WMH burden, future longitudinal studies are required to further confirm this.

Concentration-Dependent Activity of Hydromethylthionine on Clinical Decline and Brain Atrophy in a Randomized Controlled Trial in Behavioral Variant Frontotemporal Dementia. - Shiells, Helen; Schelter, Bjoern O; Bentham, Peter; Baddeley, Thomas C; Rubino, Christopher M; Ganesan, Harish; Hammel, Jeffrey; Vuksanovic, Vesna; Staff, Roger T; Murray, Alison D; Bracoud, Luc; Wischik, Damon J; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Hydromethylthionine is a potent inhibitor of pathological aggregation of tau and TDP-43 proteins. OBJECTIVE: To compare hydromethylthionine treatment effects at two doses and to determine how drug exposure is related to treatment response in bvFTD. METHODS: We undertook a 52-week Phase III study in 220 bvFTD patients randomized to compare hydromethylthionine at 200 mg/day and 8 mg/day (intended as a control). The principal outcomes were change on the Addenbrookes Cognitive Examination - Revised (ACE-R), the Functional Activities Questionnaire (FAQ), and whole brain volume. Secondary outcomes included Modified Clinical Global Impression of Change (Modified-CGIC). A population pharmacokinetic exposure-response analysis was undertaken in 175 of the patients with available blood samples and outcome data using a discriminatory plasma assay for the parent drug. RESULTS: There were no significant differences between the two doses as randomized. There were steep concentration-response relationships for plasma levels in the range 0.3-0.6 ng/ml at the 8 mg/day dose on clinical and MRI outcomes. There were significant exposure-dependent differences at 8 mg/day for FAQ, Modified-CGIC, and whole brain atrophy comparing patients with plasma levels greater than 0.346 ng/ml with having minimal drug exposure. The exposure-response is biphasic with worse outcomes at the high concentrations produced by 200 mg/day. CONCLUSIONS: Hydromethylthionine has a similar concentration-response profile for effects on clinical decline and brain atrophy at the 8 mg/day dose in bvFTD as recently reported in AD. Treatment responses in bvFTD are predicted to be maximal at doses in the range 20-60 mg/day. A confirmatory placebo-controlled trial is now planned.

The Contribution of Vascular Pathology Toward Cognitive Impairment in Older Individuals with Intermediate Braak Stage Tau Pathology. - Robinson, Andrew C; Roncaroli, Federico; Chew-Graham, Stephen; Davidson, Yvonne S; Minshull, James; Horan, Michael A; Payton, Antony; Pendleton, Neil; Mann, David M A (J Alzheimers Dis, 2020)
BACKGROUND: The pathological features of Alzheimer's disease (AD) are well described but little is known as to how both neurodegeneration and vascular changes might interact in causing cognitive impairment. OBJECTIVE: The present study aims to investigate relationships between vascular and AD pathology in cognitively healthy and cognitively impaired individuals with a particular emphasis on those at intermediate Braak tau stages. METHODS: We investigated the interplay between Braak tau stage and measures of vascular pathology as described by the vascular cognitive impairment neuropathology guidelines (VCING) in 185 brains from the Brains for Dementia Research programme and The University of Manchester Longitudinal Study of Cognition in Healthy Old Age. VCING asserts that at least one large (>10 mm) infarct, moderate/severe occipital leptomeningeal cerebral amyloid angiopathy, and moderate/severe arteriosclerosis in occipital white matter accurately predicts the contribution of cerebrovascular pathology to cognitive impairment. RESULTS: We found that the extent of arteriosclerosis in the occipital white matter did not differ between cognitive groups at intermediate (III-IV) Braak stages whereas moderate/severe leptomeningeal occipital cerebral amyloid angiopathy was greater in cognitively impaired than normal individuals at Braak stage III-IV. This finding remained significant after controlling for effects of age, sex, CERAD score, Thal phase, presence/severity of primary age-related tauopathy, presence/severity of limbic-predominant age-related TDP43 encephalopathy and small vessel disease in basal ganglia. CONCLUSION: Interventions targeting cerebral amyloid angiopathy may contribute to delay the onset of cognitive impairment in individuals with intermediate Alzheimer's type pathology.

Costs of Early Stage Alzheimer's Disease in the United States: Cross-Sectional Analysis of a Prospective Cohort Study (GERAS-US)1. - Robinson, Rebecca L; Rentz, Dorene M; Andrews, Jeffrey Scott; Zagar, Anthony; Kim, Yongin; Bruemmer, Valerie; Schwartz, Ronald L; Ye, Wenyu; Fillit, Howard M (J Alzheimers Dis, 2020)
BACKGROUND: Costs associated with early stages of Alzheimer's disease (AD; mild cognitive impairment [MCI] and mild dementia [MILD]) are understudied. OBJECTIVE: To compare costs associated with MCI and MILD due to AD in the United States. METHODS: Data included baseline patient/study partner medical history, healthcare resource utilization, and outcome assessments as part of a prospective cohort study. Direct, indirect, and total societal costs were derived by applying standardized unit costs to resources for the 1-month pre-baseline period (USD2017). Costs/month for MCI and MILD cohorts were compared using analysis of variance models. To strengthen the confidence of diagnosis, amyloid-β (Aβ) tests were included and analyses were replicated stratifying within each cohort by amyloid status [+ /-]. RESULTS: Patients (N = 1327) with MILD versus MCI had higher total societal costs/month ($4243 versus $2816; p < 0.001). These costs were not significantly different within each severity cohort by amyloid status. The largest fraction of overall costs were informal caregiver costs (45.1%) for the MILD cohort, whereas direct medical patient costs were the largest for the MCI cohort (39.0%). Correspondingly, caregiver time spent on basic activities of daily living (ADLs), instrumental ADLs, and supervision time was twice as high for MILD versus MCI (all p < 0.001). CONCLUSION: Early AD poses a financial burden, and despite higher functioning among those with MCI, caregivers were significantly impacted. The major cost driver was the patient's clinical cognitive-functional status and not amyloid status. Differences were primarily due to rising need for caregiver support.

Day-to-Day Home Blood Pressure Variability is Associated with Cerebral Small Vessel Disease Burden in a Memory Clinic Population. - de Heus, Rianne A A; Reumers, Stacha F I; van der Have, Alba; Tumelaire, Maxime; Tully, Phillip J; Claassen, Jurgen A H R (J Alzheimers Dis, 2020)
BACKGROUND: High visit-to-visit blood pressure variability (BPV) has been associated with cognitive decline and cerebral small vessel disease (cSVD), in particular cerebrovascular lesions. Whether day-to-day BPV also relates to cSVD has not been investigated. OBJECTIVE: To investigate the cross-sectional association between day-to-day BPV and total cSVD MRI burden in older memory clinic patients. METHODS: We included outpatients referred to our memory clinic, who underwent cerebral MRI as part of their diagnostic assessment. We determined the validated total cSVD score (ranging from 0-4) by combining four markers of cSVD that were visually rated. Home blood pressure (BP) measurements were performed for one week, twice a day, according to international guidelines. BPV was defined as the within-subject coefficient of variation (CV; standard deviation/mean BP*100). We used multivariable ordinal logistic regression analyses adjusted for age, sex, smoking, diabetes, antihypertensive medication, history of cardiovascular disease, and mean BP. RESULTS: For 82 patients (aged 71.2±7.9 years), mean home BP was 140/79±15/9 mmHg. Dementia and mild cognitive impairment were diagnosed in 46% and 34%, respectively. 78% had one or more markers of cSVD. Systolic CV was associated with cSVD burden (adjusted odds ratio per point increase in CV = 1.29, 95% confidence interval = 1.04-1.60, p = 0.022). There were no differences in diastolic CV and mean BP between the cSVD groups. When we differentiated between morning and evening BP, only evening BPV remained significantly associated with total cSVD burden. CONCLUSION: Day-to-day systolic BPV is associated with cSVD burden in memory clinic patients. Future research should indicate whether lowering BPV should be included in BP management in older people with memory complaints.

Dementia Care in Times of COVID-19: Experience at Fundació ACE in Barcelona, Spain. - Benaque, Alba; Gurruchaga, Miren Jone; Abdelnour, Carla; Hernandez, Isabel; Cañabate, Pilar; Alegret, Montserrat; Rodríguez, Isabel; Rosende-Roca, Maitee; Tartari, Juan Pablo; Esteban, Ester; López, Rogelio; Gil, Silvia; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Fundació ACE is a non-profit organization providing care based on a holistic model to persons with cognitive disorders and their families for 25 years in Barcelona, Spain. Delivering care to this vulnerable population amidst the COVID-19 pandemic has represented a major challenge to our institution. OBJECTIVE: To share our experience in adapting our model of care to the new situation to ensure continuity of care. METHODS: We detail the sequence of events and the actions taken within Fundació ACE to swiftly adapt our face-to-face model of care to one based on telemedicine consultations. We characterize individuals under follow-up by the Memory Unit from 2017 to 2019 and compare the number of weekly visits in 2020 performed before and after the lockdown was imposed. RESULTS: The total number of individuals being actively followed by Fundació ACE Memory Unit grew from 6,928 in 2017 to 8,147 in 2019. Among those newly diagnosed in 2019, most patients had mild cognitive impairment or mild dementia (42% and 25%, respectively). Weekly visits dropped by 60% following the suspension of face-to-face activity. However, by April 24 we were able to perform 78% of the visits we averaged in the weeks before confinement began. DISCUSSION: We have shown that Fundació ACE model of care has been able to successfully adapt to a health and social critical situation as COVID-19 pandemic. Overall, we were able to guarantee the continuity of care while preserving the safety of patients, families, and professionals. We also seized the opportunity to improve our model of care.
Keywords: Aged; Aged, 80 and over; Betacoronavirus; Coronavirus Infections; COVID-19; Dementia; Female; Follow-Up Studies; Holistic Health; Humans; Male; Pandemics; Patient-Centered Care; Pneumonia, Viral; SARS-CoV-2; Spain; Telemedicine

Dickkopf-1 Overexpression in vitro Nominates Candidate Blood Biomarkers Relating to Alzheimer's Disease Pathology. - Shi, Liu; Winchester, Laura M; Liu, Benjamine Y; Killick, Richard; Ribe, Elena M; Westwood, Sarah; Baird, Alison L; Buckley, Noel J; Hong, Shengjun; Dobricic, Valerija; Kilpert, Fabian; Franke, Andre; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Previous studies suggest that Dickkopf-1 (DKK1), an inhibitor of Wnt signaling, plays a role in amyloid-induced toxicity and hence Alzheimer's disease (AD). However, the effect of DKK1 expression on protein expression, and whether such proteins are altered in disease, is unknown. OBJECTIVE: We aim to test whether DKK1 induced protein signature obtained in vitro were associated with markers of AD pathology as used in the amyloid/tau/neurodegeneration (ATN) framework as well as with clinical outcomes. METHODS: We first overexpressed DKK1 in HEK293A cells and quantified 1,128 proteins in cell lysates using aptamer capture arrays (SomaScan) to obtain a protein signature induced by DKK1. We then used the same assay to measure the DKK1-signature proteins in human plasma in two large cohorts, EMIF (n = 785) and ANM (n = 677). RESULTS: We identified a 100-protein signature induced by DKK1 in vitro. Subsets of proteins, along with age and apolipoprotein E ɛ4 genotype distinguished amyloid pathology (A + T-N-, A+T+N-, A+T-N+, and A+T+N+) from no AD pathology (A-T-N-) with an area under the curve of 0.72, 0.81, 0.88, and 0.85, respectively. Furthermore, we found that some signature proteins (e.g., Complement C3 and albumin) were associated with cognitive score and AD diagnosis in both cohorts. CONCLUSIONS: Our results add further evidence for a role of DKK regulation of Wnt signaling in AD and suggest that DKK1 induced signature proteins obtained in vitro could reflect theATNframework as well as predict disease severity and progression in vivo.

The Effects of Confinement on Neuropsychiatric Symptoms in Alzheimer's Disease During the COVID-19 Crisis. - Boutoleau-Bretonnière, Claire; Pouclet-Courtemanche, Hélene; Gillet, Aurelie; Bernard, Amelie; Deruet, Anne Laure; Gouraud, Ines; Mazoue, Aurelien; Lamy, Estelle; Rocher, Laetitia; Kapogiannis, Dimitrios; El Haj, Mohamad (J Alzheimers Dis, 2020)
BACKGROUND: Neuropsychiatric symptoms, such as depression, anxiety, apathy, agitation, and hallucinations, are frequent in Alzheimer's disease (AD) and their prevalence tends to increase with external stressors. OBJECTIVE: We offer the first investigation of the effects of confinement during the COVID-19 crisis on neuropsychiatric symptoms in patients with AD. METHODS: We contacted caregivers of 38 patients with AD who were confined to their homes for nearly two months and asked them to report whether patients experienced any change in neuropsychiatric symptoms during, compared to before, the confinement and rate its severity and impact on themselves using the Neuropsychiatric Inventory-Questionnaire. RESULTS: Among the 38 patients, only 10 demonstrated neuropsychiatric changes during the confinement. Cognitive function of these 10 patients, assessed with the Mini-Mental State Examination, was worse than that of patients who did not demonstrate neuropsychiatric changes. Interestingly, among the 10 patients with neuropsychiatric changes, the duration of confinement significantly correlated with the severity of symptoms as well as with their caregivers' distress. DISCUSSION: The confinement seems to impact neuropsychiatric symptomatology in AD patients with low baseline cognitive function.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Betacoronavirus; Cohort Studies; Coronavirus Infections; COVID-19; Female; Humans; Male; Mental Disorders; Mental Status and Dementia Tests; Middle Aged; Pandemics; Pneumonia, Viral; Quarantine; SARS-CoV-2

Effects of LDL Cholesterol and Statin Use on Verbal Learning and Memory in Older Adults at Genetic Risk for Alzheimer's Disease. - Wroolie, Tonita; Roat-Shumway, Siena; Watson, Katie; Reiman, Eric; Rasgon, Natalie (J Alzheimers Dis, 2020)
BACKGROUND: The apolipoprotein epsilon 4 (APOE4) allele is a well-established genetic risk factor for Alzheimer's disease (AD). However, there are mixed findings as to how the APOE4 allele modifies the effects of both higher low-density lipoprotein cholesterol (LDL) and statin use on cognitive functioning. OBJECTIVE: This study sought to examine the effects of LDL levels and statin use on verbal learning and memory, as modified by the presence of the APOE4 allele, in a sample of cognitively unimpaired, older adults at risk for AD. METHODS: Neuropsychological, LDL, statin use, and APOE4 data were extracted from an ongoing longitudinal study at the Banner Alzheimer's Institute in Arizona. Participants were cognitively unimpaired based on Mini-Mental State Examination scores within a normal range, aged 47-75, with a family history of probable AD in at least one first-degree relative. RESULTS: In the whole sample, higher LDL was associated with worse immediate verbal memory in APOE4 non-carriers, but did not have an effect on immediate verbal memory in APOE4 carriers. In APOE4 non-carriers, statin use was associated with better verbal learning, but did not have an effect on verbal learning in APOE4 carriers. Among women, higher LDL in APOE4 carriers was associated with worse verbal learning than in APOE4 non-carriers, and statin use in APOE4 non-carriers was associated with better verbal learning and immediate and delayed verbal memory but worse performances on these tasks in APOE4 carriers. CONCLUSION: LDL and statin use may have differential effects on verbal learning and/or memory depending on genetic risk for AD. Women appear to be particularly vulnerable to statin use depending on their APOE4 status.

Environmental Nanoparticles, SARS-CoV-2 Brain Involvement, and Potential Acceleration of Alzheimer's and Parkinson's Diseases in Young Urbanites Exposed to Air Pollution. - Calderón-Garcidueñas, Lilian; Torres-Jardón, Ricardo; Franco-Lira, Maricela; Kulesza, Randy; González-Maciel, Angelica; Reynoso-Robles, Rafael; Brito-Aguilar, Rafael; García-Arreola, Berenice; Revueltas-Ficachi, Paula; Barrera-Velázquez, Juana Adriana; García-Alonso, Griselda; García-Rojas, Edgar; et al. (J Alzheimers Dis, 2020)
Alzheimer's and Parkinson's diseases (AD, PD) have a pediatric and young adult onset in Metropolitan Mexico City (MMC). The SARS-CoV-2 neurotropic RNA virus is triggering neurological complications and deep concern regarding acceleration of neuroinflammatory and neurodegenerative processes already in progress. This review, based on our MMC experience, will discuss two major issues: 1) why residents chronically exposed to air pollution are likely to be more susceptible to SARS-CoV-2 systemic and brain effects and 2) why young people with AD and PD already in progress will accelerate neurodegenerative processes. Secondary mental consequences of social distancing and isolation, fear, financial insecurity, violence, poor health support, and lack of understanding of the complex crisis are expected in MMC residents infected or free of SARS-CoV-2. MMC residents with pre-SARS-CoV-2 accumulation of misfolded proteins diagnostic of AD and PD and metal-rich, magnetic nanoparticles damaging key neural organelles are an ideal host for neurotropic SARS-CoV-2 RNA virus invading the body through the same portals damaged by nanoparticles: nasal olfactory epithelium, the gastrointestinal tract, and the alveolar-capillary portal. We urgently need MMC multicenter retrospective-prospective neurological and psychiatric population follow-up and intervention strategies in place in case of acceleration of neurodegenerative processes, increased risk of suicide, and mental disease worsening. Identification of vulnerable populations and continuous effort to lower air pollution ought to be critical steps.
Keywords: Adult; Air Pollution; Alzheimer Disease; Brain Diseases; Coronavirus Infections; COVID-19; Disease Progression; Environmental Pollutants; Humans; Middle Aged; Nanoparticles; Pandemics; Parkinson Disease; Pneumonia, Viral; Suicide; Urban Population

Examining Cognitive Decline Across Black and White Participants in the Harvard Aging Brain Study. - Amariglio, Rebecca E; Buckley, Rachel F; Rabin, Jennifer S; Papp, Kathryn V; Quiroz, Yakeel T; Mormino, Elizabeth C; Sparks, Kathryn P; Johnson, Keith A; Rentz, Dorene M; Sperling, Reisa A (J Alzheimers Dis, 2020)
BACKGROUND: Black Americans are approximately twice as likely to develop dementia as compared to White Americans and the magnitude of this disparity is often attributed to a variety of factors that include psychosocial and vascular risk factors. However, less is known about the potential contribution of Alzheimer's disease pathological differences. OBJECTIVE: To examine potential differences incross-sectional and longitudinal cognitive performance in black and white participants who were clinically normal at baseline. METHODS: 296 participants (48 African-American/black participants) underwent MRI and amyloid PET at baseline. Linear mixed models were used to examine the main effects of race, years of education, reading ability, Framingham Heart Study cardiovascular risk score (FHS-CVD), white matter hyperintensities (WMH), and amyloid (Aβ) burden on the Preclinical Alzheimer Cognitive Composite-5 (PACC5). RESULTS: Lower levels of educationalattainment and reading ability were found for blacks compared to whites. By contrast, no differences in FHS-CVD, WMH, or Aβ were found by racial group. Baseline differences in PACC5 score were attenuated after adjusting for educationalfactors, vascular factors, and Aβ, but remained lower for blacks compared to whites (β= -0.24, p = 0.014). Further, blacks demonstrated a faster rate of PACC5 decline longitudinally compared to whites (β  = -0.055, p = 0.025) after adjusting for covariates. CONCLUSION: Accounting for educationalfactors, vascular factors, and Aβ burden diminished, but did not eliminate, racial differences in PACC5 performance longitudinally. Understanding potential differences in longitudinal cognitive outcomes by race may be important for upcoming secondary prevention trials.

Exploration of Plasma Lipids in Mild Cognitive Impairment due to Alzheimer's Disease. - Bergland, Anne Katrine; Proitsi, Petroula; Kirsebom, Bjørn-Eivind; Soennesyn, Hogne; Hye, Abdul; Larsen, Alf Inge; Xu, Jin; Legido-Quigley, Cristina; Rajendran, Lawrence; Fladby, Tormod; Aarsland, Dag (J Alzheimers Dis, 2020)
BACKGROUND: Lipids have important structural roles in cell membranes and changes to these membrane lipids may influence β- and γ-secretase activities and thus contribute to Alzheimer's disease (AD) pathology. OBJECTIVE: To explore baseline plasma lipid profiling in participants with mild cognitive impairment (MCI) with and without AD pathology. METHODS: We analyzed 261 plasma lipid profiles using reversed phase chromatography mass spectrometry in cerebrospinal fluid amyloid positive (Aβ+) or negative (Aβ-) participants with MCI as compared to controls. Additionally, we analyzed the potential associations of plasma lipid profiles with performance on neuropsychological tests at baseline and after two years. RESULTS: Sphingomyelin (SM) concentrations, particularly, SM(d43:2), were lower in MCI Aβ+ individuals compared to controls. Further, SM(d43:2) was also nominally reduced in MCI Aβ+ individuals compared to MCI Aβ-. No plasma lipids were associated with performance on neuropsychological tests at baseline or between the two time points after correction for multiple testing. CONCLUSION: Reduced plasma concentrations of SM were associated with AD.

Fascicle- and Glucose-Specific Deterioration in White Matter Energy Supply in Alzheimer's Disease. - Roy, Maggie; Rheault, François; Croteau, Etienne; Castellano, Christian-Alexandre; Fortier, Mélanie; St-Pierre, Valérie; Houde, Jean-Christophe; Turcotte, Éric E; Bocti, Christian; Fülöp, Tamás; Cunnane, Stephen C; Descoteaux, Maxime (J Alzheimers Dis, 2020)
BACKGROUND: White matter energy supply to oligodendrocytes and the axonal compartment is crucial for normal axonal function. Although gray matter glucose hypometabolism is extensively reported in Alzheimer's disease (AD), glucose and ketones, the brain's two main fuels, are rarely quantified in white matter in AD. OBJECTIVE: Using adual-tracer PET method combined with a fascicle-specific diffusion MRI approach, robust to white matter hyper intensities and crossing fibers, we aimed to quantify both glucose and ketone metabolismin specific white matter fascicles associated with mild cognitive impairment (MCI; n = 51) and AD (n = 13) compared to cognitively healthy age-matched controls (Controls; n = 14). METHODS: Eight white matter fascicles of the limbic lobe and corpus callosum were extracted and analyzed into fascicle profiles of five sections. Glucose (18F-fluorodeoxyglucose) and ketone (11C-acetoacetate) uptake rates, corrected for partial volume effect, were calculated along each fascicle. RESULTS: The only fascicle with significantly lower glucose uptake in AD compared to Controls was the left posterior cingulate segment of the cingulum (-22%; p = 0.016). Non-significantly lower glucose uptake in this fascicle was also observed in MCI. In contrast to glucose, ketone uptake was either unchanged or higher in sections of the fornix and parahippocampal segment of the cingulum in AD. CONCLUSION: To our knowledge, this is the first report of brain fuel uptake calculated along white matter fascicles in humans. Energetic deterioration in white matter in AD appears to be specific to glucose and occurs first in the posterior cingulum.

Gait Disturbances are Associated with Increased Cognitive Impairment and Cerebrospinal Fluid Tau Levels in a Memory Clinic Cohort. - Muurling, Marijn; Rhodius-Meester, Hanneke F M; Pärkkä, Juha; van Gils, Mark; Frederiksen, Kristian S; Bruun, Marie; Hasselbalch, Steen G; Soininen, Hilkka; Herukka, Sanna-Kaisa; Hallikainen, Merja; Teunissen, Charlotte E; Visser, Pieter Jelle; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Gait analysis with accelerometers is a relatively inexpensive and easy to use method to potentially support clinical diagnoses of Alzheimer's disease and other dementias. It is not clear, however, which gait features are most informative and how these measures relate to Alzheimer's disease pathology. OBJECTIVE: In this study, we tested if calculated features of gait 1) differ between cognitively normal subjects (CN), mild cognitive impairment (MCI) patients, and dementia patients, 2) are correlated with cerebrospinal fluid (CSF) biomarkers related to Alzheimer's disease, and 3) predict cognitive decline. METHODS: Gait was measured using tri-axial accelerometers attached to the fifth lumbar vertebra (L5) in 58 CN, 58 MCI, and 26 dementia participants, while performing a walk and dual task. Ten gait features were calculated from the vertical L5 accelerations, following principal component analysis clustered in four domains, namely pace, rhythm, time variability, and length variability. Cognitive decline over time was measured using MMSE, and CSF biomarkers were available in a sub-group. RESULTS: Linear mixed models showed that dementia patients had lower pace scores than MCI patients and CN subjects (p < 0.05). In addition, we found associations between the rhythm domain and CSF-tau, especially in the dual task. Gait was not associated with CSF Aβ42 levels and cognitive decline over time as measured with the MMSE. CONCLUSION: These findings suggest that gait-particularly measures related to pace and rhythm-are altered in dementia and have a direct link with measures of neurodegeneration.

Gene Ontology Curation of Neuroinflammation Biology Improves the Interpretation of Alzheimer's Disease Gene Expression Data. - Kramarz, Barbara; Huntley, Rachael P; Rodríguez-López, Milagros; Roncaglia, Paola; Saverimuttu, Shirin C C; Parkinson, Helen; Bandopadhyay, Rina; Martin, Maria-Jesus; Orchard, Sandra; Hooper, Nigel M; Brough, David; Lovering, Ruth C (J Alzheimers Dis, 2020)
BACKGROUND: Gene Ontology (GO) is a major bioinformatic resource used for analysis of large biomedical datasets, for example from genome-wide association studies, applied universally across biological fields, including Alzheimer's disease (AD) research. OBJECTIVE: We aim to demonstrate the applicability of GO for interpretation of AD datasets to improve the understanding of the underlying molecular disease mechanisms, including the involvement of inflammatory pathways and dysregulated microRNAs (miRs). METHODS: We have undertaken a systematic full article GO annotation approach focused on microglial proteins implicated in AD and the miRs regulating their expression. PANTHER was used for enrichment analysis of previously published AD data. Cytoscape was used for visualizing and analyzing miR-target interactions captured from published experimental evidence. RESULTS: We contributed 3,084 new annotations for 494 entities, i.e., on average six new annotations per entity. This included a total of 1,352 annotations for 40 prioritized microglial proteins implicated in AD and 66 miRs regulating their expression, yielding an average of twelve annotations per prioritized entity. The updated GO resource was then used to re-analyze previously published data. The re-analysis showed novel processes associated with AD-related genes, not identified in the original study, such as 'gliogenesis', 'regulation of neuron projection development', or 'response to cytokine', demonstrating enhanced applicability of GO for neuroscience research. CONCLUSIONS: This study highlights ongoing development of the neurobiological aspects of GO and demonstrates the value of biocuration activities in the area, thus helping to delineate the molecular bases of AD to aid the development of diagnostic tools and treatments.

The GSM BPN-15606 as a Potential Candidate for Preventative Therapy in Alzheimer's Disease. - Prikhodko, Olga; Rynearson, Kevin D; Sekhon, Travis; Mante, Mike M; Nguyen, Phuong D; Rissman, Robert A; Tanzi, Rudolph E; Wagner, Steven L (J Alzheimers Dis, 2020)
BACKGROUND: In the amyloid hypothesis of Alzheimer's disease (AD), the dysregulation of amyloid-β protein (Aβ) production and clearance leads to amyloid deposits, tau tangles, neuronal loss, and cognitive dysfunction. Thus far, therapies targeting the enzymes responsible for Aβ production have been found ineffective or having significant side effects. OBJECTIVE: To test whether a γ-secretase modulator, BPN-15606, is an effective disease-modifying or preventative treatment in the PSAPP mouse model of AD. METHODS: We treated pre-plaque (3-month-old) and post-plaque (6-month-old) PSAPP AD transgenic mice for 3 months and examined behavioral, biochemical, and pathological end points. RESULTS: BPN-15606 attenuated cognitive impairment and reduced amyloid plaque load, microgliosis, and astrogliosis associated with the AD phenotype of PSAPP mice when administered to pre-plaque (3-month-old) but was ineffective when administered to post-plaque (6-month-old) mice. No treatment-related toxicity was observed. CONCLUSION: BPN-15606 appears efficacious when administered prior to significant pathology.

The Impact of Amyloid-β or Tau on Cognitive Change in the Presence of Severe Cerebrovascular Disease. - Jang, Hyemin; Kim, Hee Jin; Sim Choe, Yeong; Kim, Soo-Jong; Park, Seongbeom; Kim, Yeshin; Woon Kim, Ko; Hyoung Lyoo, Chul; Cho, Hanna; Hoon Ryu, Young; Choi, Jae Yong; DeCarli, Charles; et al. (J Alzheimers Dis, 2020)
BACKGROUND: As Alzheimer's disease (AD) and cerebral small vessel disease (CSVD) commonly coexist, the interaction between two has been of the considerable interest. OBJECTIVE: We determined whether the association of Aβ and tau with cognitive decline differs by the presence of significant CSVD. METHODS: We included 60 subcortical vascular cognitive impairment (SVCI) from Samsung Medical Center and 82 Alzheimer's disease-related cognitive impairment (ADCI) from ADNI, who underwent Aβ (florbetaben or florbetapir) and tau (flortaucipir, FTP) PET imaging. They were retrospectively assessed for 5.0±3.9 and 5.6±1.9 years with Clinical Dementia Rating-sum of boxes (CDR-SB)/Mini-Mental State Examination (MMSE). Mixed effects models were used to investigate the interaction between Aβ/tau and group on CDR-SB/MMSE changes. RESULTS: The frequency of Aβ positivity (45% versus 54.9%, p = 0.556) and mean global FTP SUVR (1.17±0.21 versus 1.16±0.17, p = 0.702) were not different between the two groups. We found a significant interaction effect of Aβ positivity and SVCI group on CDR-SB increase/MMSE decrease (p = 0.013/p <  0.001) change, and a significant interaction effect of global FTP uptake and SVCI group on CDR-SB increase/MMSE decrease (p <  0.001 and p = 0.030) change. Finally, the interaction effects of regional tau and group were prominent in the Braak III/IV (p = 0.001) and V/VI (p = 0.003) not in Braak I/II region (p = 0.398). CONCLUSION: The association between Aβ/tau and cognitive decline is stronger in SVCI than in ADCI. Therefore, our findings suggested that Aβ positivity or tau burden (particularly in the Braak III/IV or V/VI regions) and CSVD might synergistically affect cognitive decline.

Individual Differences in the Effects of Physical Activity on Cognitive Function in People with Mild to Moderate Dementia. - Uijen, Iris L; Aaronson, Justine A; Karssemeijer, Esther G A; Olde Rikkert, Marcel G M; Kessels, Roy P C (J Alzheimers Dis, 2020)
The aim of this study was to investigate whether the effect of physical activity on cognitive function in persons with dementia is moderated by patient characteristics as Apolipoprotein E and dementia type. We included 101 individuals with dementia and calculated the reliable change index to determine the change in global cognition, executive function, episodic memory, working memory, and processing speed before and after a 12-week exercise training. We found a higher treatment-related benefit in episodic memory in persons with non-Alzheimer's disease compared to persons with Alzheimer's disease, and in executive function in individuals with better baseline cognitive function.

Influence of Comorbidity of Cerebrovascular Disease and Amyloid-β on Alzheimer's Disease. - Yassi, Nawaf; Hilal, Saima; Xia, Ying; Lim, Yen Ying; Watson, Rosie; Kuijf, Hugo; Fowler, Christopher; Yates, Paul; Maruff, Paul; Martins, Ralph; Ames, David; Chen, Christopher; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Quantifying the contribution of cerebrovascular disease to the clinical and pathological profile of Alzheimer's disease is challenging. OBJECTIVE: We aimed to determine the influence of cerebrovascular disease, amyloid-β (Aβ), and their comorbidity on cognitive decline, hippocampal atrophy, and Aβ deposition, by evaluating data from the Australian Imaging, Biomarker and Lifestyle Study of Ageing. METHODS: Two-hundred and eighteen participants underwent Aβ PET, MRI, and cognitive assessment at 18-month intervals for up to 90 months. Aβ status was determined on baseline PET. Participants were also classified as V + on baseline MRI if they had≥1 large cortical infarcts, subcortical infarcts, or cortical cerebral microinfarcts; or white matter hyperintensity volume greater than the 90th percentile of healthy controls. Linear mixed models were conducted comparing slopes of change in cognition, hippocampal volume, and Aβ load between the four resultant groups. RESULTS: Mean age at baseline was 74 years (range 59-96). One-hundred and fifteen participants were cognitively normal, 54 had mild cognitive impairment, and 49 had Alzheimer's disease. Compared to the Aβ-/V- group, the Aβ+/V- and Aβ+/V+groups showed significantly faster cognitive decline and hippocampal atrophy over 90 months. V + status was associated with greater cognitive decline (Cohen's d = 0.85, p < 0.001) and hippocampal atrophy (d = 2.05, p < 0.001) in the Aβ+group but not in the Aβ- group. V + status was not associated with Aβ accumulation in any group. CONCLUSION: Comorbidity of cerebrovascular disease and Aβ was associated with cognitive decline and neurodegeneration. Cerebrovascular disease was not associated with the rate of Aβ accumulation.

Mitochondrial DNA Manipulations Affect Tau Oligomerization. - Weidling, Ian W; Wilkins, Heather M; Koppel, Scott J; Hutfles, Lewis; Wang, Xiaowan; Kalani, Anuradha; Menta, Blaise W; Ryan, Benjamin; Perez-Ortiz, Judit; Gamblin, T Chris; Swerdlow, Russell H (J Alzheimers Dis, 2020)
BACKGROUND: Mitochondrial dysfunction and tau aggregation occur in Alzheimer's disease (AD), and exposing cells or rodents to mitochondrial toxins alters their tau. OBJECTIVE: To further explore how mitochondria influence tau, we measured tau oligomer levels in human neuronal SH-SY5Y cells with different mitochondrial DNA (mtDNA) manipulations. METHODS: Specifically, we analyzed cells undergoing ethidium bromide-induced acute mtDNA depletion, ρ0 cells with chronic mtDNA depletion, and cytoplasmic hybrid (cybrid) cell lines containing mtDNA from AD subjects. RESULTS: We found cytochrome oxidase activity was particularly sensitive to acute mtDNA depletion, evidence of metabolic re-programming in the ρ0 cells, and a relatively reduced mtDNA content in cybrids generated through AD subject mitochondrial transfer. In each case tau oligomer levels increased, and acutely depleted and AD cybrid cells also showed a monomer to oligomer shift. CONCLUSION: We conclude a cell's mtDNA affects tau oligomerization. Overlapping tau changes across three mtDNA-manipulated models establishes the reproducibility of the phenomenon, and its presence in AD cybrids supports its AD-relevance.

A Narrative Review of Alzheimer's Disease Stigma. - Rosin, Eric R; Blasco, Drew; Pilozzi, Alexander R; Yang, Lawrence H; Huang, Xudong (J Alzheimers Dis, 2020)
As the most common form of senile dementia, Alzheimer's disease (AD) is accompanied by a great deal of uncertainty which can lead to fear and stigma for those identified with this devastating disease. As the AD definition evolves from a syndromal to a biological construct, and early diagnoses becomes more commonplace, more confusion and stigma may result. We conducted a narrative review of the literature on AD stigma to consolidate information on this body of research. From the perspective of several stigma theories, we identified relevant studies to inform our understanding of the way in which implementation of the new framework for a biological based AD diagnosis may have resulted in new and emerging stigma. Herein, we discuss the emergence of new AD stigma as our understanding of the definition of the disease changes. We further propose recommendations for future research to reduce the stigma associated with AD.

Neurobiology of COVID-19. - Fotuhi, Majid; Mian, Ali; Meysami, Somayeh; Raji, Cyrus A (J Alzheimers Dis, 2020)
Anosmia, stroke, paralysis, cranial nerve deficits, encephalopathy, delirium, meningitis, and seizures are some of the neurological complications in patients with coronavirus disease-19 (COVID-19) which is caused by acute respiratory syndrome coronavirus 2 (SARS-Cov2). There remains a challenge to determine the extent to which neurological abnormalities in COVID-19 are caused by SARS-Cov2 itself, the exaggerated cytokine response it triggers, and/or the resulting hypercoagulapathy and formation of blood clots in blood vessels throughout the body and the brain. In this article, we review the reports that address neurological manifestations in patients with COVID-19 who may present with acute neurological symptoms (e.g., stroke), even without typical respiratory symptoms such as fever, cough, or shortness of breath. Next, we discuss the different neurobiological processes and mechanisms that may underlie the link between SARS-Cov2 and COVID-19 in the brain, cranial nerves, peripheral nerves, and muscles. Finally, we propose a basic "NeuroCovid" classification scheme that integrates these concepts and highlights some of the short-term challenges for the practice of neurology today and the long-term sequalae of COVID-19 such as depression, OCD, insomnia, cognitive decline, accelerated aging, Parkinson's disease, or Alzheimer's disease in the future. In doing so, we intend to provide a basis from which to build on future hypotheses and investigations regarding SARS-Cov2 and the nervous system.
Keywords: Betacoronavirus; Brain; Coronavirus Infections; COVID-19; Humans; Inflammation Mediators; Nervous System Diseases; Pandemics; Pneumonia, Viral; SARS-CoV-2

Neuroimaging in Vascular Cognitive Impairment and Dementia: A Systematic Review. - Frantellizzi, Viviana; Pani, Arianna; Ricci, Maria; Locuratolo, Nicoletta; Fattapposta, Francesco; De Vincentis, Giuseppe (J Alzheimers Dis, 2020)
Cerebrovascular diseases are well established causes of cognitive impairment. Different etiologic entities, such as vascular dementia (VaD), vascular cognitive impairment, subcortical (ischemic) VaD, and vascular cognitive disorder, are included in the umbrella definition of vascular cognitive impairment and dementia (VCID). Because of the variability of VCID clinical presentation, there is no agreement on criteria defining the neuropathological threshold of this disorder. In fact, VCID is characterized by cerebral hemodynamic alteration which ranges from decreased cerebral blood flow to small vessels disease and involves a multifactorial process that leads to demyelination and gliosis, including blood-brain barrier disruption, hypoxia, and hypoperfusion, oxidative stress, neuroinflammation and alteration on neurovascular unit coupling, cerebral microbleeds, or superficial siderosis. Numerous criteria for the definition of VaD have been described: the National Institute of Neurological Disorders and Stroke Association Internationale pour Recherche'-et-l'Enseignement en Neurosciences criteria, the State of California Alzheimer's Disease Diagnostic and Treatment Centers criteria, DSM-V criteria, the Diagnostic Criteria for Vascular Cognitive Disorders (a VASCOG Statement), and Vascular Impairment of Cognition Classification Consensus Study. Neuroimaging is fundamental for definition and diagnosis of VCID and should be used to assess the extent, location, and type of vascular lesions. MRI is the most sensible technique, especially if used according to standardized protocols, even if CT plays an important role in several conditions. Functional neuroimaging, in particular functional MRI and PET, may facilitate differential diagnosis among different forms of dementia. This systematic review aims to explore the state of the art and future perspective of non-invasive diagnostics of VCID.

New BACE1 Chimeric Peptide Inhibitors Selectively Prevent AβPPβ Cleavage Decreasing Amyloid-β Production and Accumulation in Alzheimer's Disease Models. - Resende, Rosa; Ferreira-Marques, Marisa; Moreira, Patrícia; Coimbra, Judite R M; Baptista, Salete J; Isidoro, Ciro; Salvador, Jorge A R; Dinis, Teresa C P; Pereira, Cláudia F; Santos, Armanda E (J Alzheimers Dis, 2020)
BACKGROUND: A disease-modifying therapy for Alzheimer's disease (AD) is still an unmet clinical need. The formation of amyloid-β (Aβ) requires the initial cleavage of the amyloid-β protein precursor (AβPP) by BACE1 (beta-site AβPP cleaving enzyme 1), which is a prime therapeutic target for AD. OBJECTIVE: We aimed to design and develop a selective BACE1 inhibitor suitable to AD treatment. METHODS: The new BACE1 inhibitors consist on a chimeric peptide including a sequence related to the human Swedish mutant form of AβPP (AβPPswe) conjugated with the TAT carrier that facilitates cell membrane permeation and the crossing of the blood-brain barrier. Additionally to the chimeric peptide in the L-form, we developed a D-retro in verso chimeric peptide. The latter strategy, never used with BACE1 inhibitors, is considered to favor a significantly higher half-life and lower immunogenicity. RESULTS: We found that both chimeric peptides inhibit recombinant BACE1 activity and decrease Aβ40/42 production in Neuro-2a (N2A) cells expressing AβPPswe without inducing cytotoxicity. The intraperitoneal administration of these peptides to 3xTg-AD mice decreased plasma and brain Aβ40/42 levels, as well as brain soluble AβPPβ production. Also, a reduction of insoluble Aβ was observed in the brain after chronic treatment. Noteworthy, the chimeric peptides selectively inhibited the AβPPβ cleavage relatively to the proteolysis of other BACE1 substrates such as close homologue of L1 (CHL1) and seizure-related gene 6 (SEZ6). CONCLUSIONS: Overall these new BACE1 chimeric peptideshold promising potential as a selective disease-modifying therapy for AD.

Non-Coding RNAs Based Molecular Links in Type 2 Diabetes, Ischemic Stroke, and Vascular Dementia. - Vijayan, Murali; Reddy, P Hemachandra (J Alzheimers Dis, 2020)
This article reviews recent advances in the study of microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and their functions in type 2 diabetes mellitus (T2DM), ischemic stroke (IS), and vascular dementia (VaD). miRNAs and lncRNAs are gene regulation markers that both regulate translational aspects of a wide range of proteins and biological processes in healthy and disease states. Recent studies from our laboratory and others have revealed that miRNAs and lncRNAs expressed differently are potential therapeutic targets for neurological diseases, especially T2DM, IS, VaD, and Alzheimer's disease (AD). Currently, the effect of aging in T2DM, IS, and VaD and the cellular and molecular pathways are largely unknown. In this article, we highlight results from the works on the molecular connections between T2DM and IS, and IS and VaD. In each disease, we also summarize the pathophysiology and the differential expressions of miRNAs and lncRNAs. Based on current research findings, we hypothesize that 1) T2DM bi-directionally and age-dependently induces IS and VaD, and 2) these changes are precursors to the onset of dementia in elderly people. Research into these hypotheses is required to examine further whether research efforts on reducing T2DM, IS, and VaD may affect dementia and/or delay the AD disease process in the aged population.

Normal Pressure Hydrocephalus in Down Syndrome: The Report of Two Cases. - Marano, Massimo; Pompucci, Angelo; Motolese, Francesco; Rossi, Mariagrazia; Coletta, Ernesto; Di Lazzaro, Vincenzo; Fasano, Alfonso; Petrella, Gianpaolo (J Alzheimers Dis, 2020)
Down syndrome (DS) is the most common cause of intellectual disability in infants and has a well-known relationship with the Alzheimer's disease. The association between DS and the other pathologies of senescence, such as normal pressure hydrocephalus (NPH), has been poorly investigated. This series included two DS patients with NPH. In both cases, NPH symptoms were initially misdiagnosed as DS associated senescence. Patients were treated with ventricular-peritoneal shunt, showing a sustained improvement (1 and 4 years of follow-up). To our knowledge, this is the first description of the occurrence of NPH in adult patients with DS and surgical outcomes.

Novel Markers of Angiogenesis in the Setting of Cognitive Impairment and Dementia. - Callahan, Christopher M; Apostolova, Liana G; Gao, Sujuan; Risacher, Shannon L; Case, Jamie; Saykin, Andrew J; Lane, Kathleen A; Swinford, Cecily G; Yoder, Mervin C (J Alzheimers Dis, 2020)
BACKGROUND: Aberrant angiogenesis may play a role in the development of Alzheimer's disease and related dementia. OBJECTIVE: To explore the relationship between angiogenesis activity and evidence of neurodegeneration among older adults. METHODS: Cross-sectional study of 49 older adults clinically characterized as cognitively normal, mild cognitive impairment, or early Alzheimer's disease. In addition to neuroimaging, we completed assays on peripheral blood, including: vascular endothelial growth factor, tumor necrosis factor, fibroblast growth factor, and amyloid-β peptide 40. We used advanced polychromatic flow cytometry to phenotype circulating mononuclear cells to assess angiogenesis activity. RESULTS: Although we documented differences in cognitive performance, structural changes on neuroimaging, and burden of amyloid and tau on positron emission tomography, angiogenesis activity did not vary by group. Interestingly, VEGF levels were shown to be increased among subjects with mild cognitive impairment. In ANCOVA models controlling for age, sex, intracranial volume, and monocyte subpopulations, angiogenesis activity was correlated with increased white matter hyperintensities. CONCLUSION: We demonstrate a significant association between angiogenesis activity and cerebrovascular disease. To better understand the potential of angiogenesis as an intervention target, longitudinal studies are needed.

Older Patients with Alzheimer's Disease-Related Cortical Atrophy Who Develop Post-Operative Delirium May Be at Increased Risk of Long-Term Cognitive Decline After Surgery. - Racine, Annie M; Touroutoglou, Alexandra; Abrantes, Tatiana; Wong, Bonnie; Fong, Tamara G; Cavallari, Michele; Travison, Thomas G; Gou, Yun; Marcantonio, Edward R; Alsop, David C; Jones, Richard N; Inouye, Sharon K; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Older surgical patients with Alzheimer's disease (AD) dementia and delirium are at increased risk for accelerated long-term cognitive decline. OBJECTIVE: Investigate associations between a probabilistic marker of preclinical AD, delirium, and long-term cognitive decline. METHODS: The Successful Aging after Elective Surgery cohort includes older adults (≥70 years) without dementia who underwent elective surgery. 140 patients underwent preoperative magnetic resonance imaging and had≥6 months cognitive follow-up. Cortical thickness was measured in 'AD-Signature' regions. Delirium was evaluated each postoperative day by the Confusion Assessment Method. Cognitive performance was assessed using a detailed neuropsychological battery at baseline; months 1, 2, and 6; and every 6 months thereafter until 36 months. Using either a General Cognitive Performance composite (GCP) or individual test scores as outcomes, we performed linear mixed effects models to examine main effects of AD-signature atrophy and the interaction of AD-signature atrophy and delirium on slopes of cognitive change from post-operative months 2-36. RESULTS: Reduced baseline AD-signature cortical thickness was associated with greater 36-month cognitive decline in GCP (standardized beta coefficient, β = -0.030, 95% confidence interval [-0.060, -0.001]). Patients who developed delirium who also had thinner AD signature cortex showed greater decline on a verbal learning test (β = -0.100 [-0.192, -0.007]). CONCLUSION: Patients with the greatest baseline AD-related cortical atrophy who develop delirium after elective surgery appear to experience the greatest long-term cognitive decline. Thus, atrophy suggestive of preclinical AD and the development of delirium may be high-risk indicators for long-term cognitive decline following surgery.

Optimizing Use of Neuroimaging Tools in Evaluation of Prodromal Alzheimer's Disease and Related Disorders. - Raji, Cyrus A; Torosyan, Nare; Silverman, Daniel H S (J Alzheimers Dis, 2020)
Alzheimer's disease (AD) is the most common neurodegenerative disease and is characterized by preclinical, pre-dementia, and dementia phases. Progression of the disease leads to cognitive decline and is associated with loss of functional independence, personality changes, and behavioral disturbances. Current guidelines for AD diagnosis include the use of neuroimaging tools as biomarkers for identifying and monitoring pathological changes. Various imaging modalities, namely magnetic resonance imaging (MRI), fluorodeoxyglucose-positron emission tomography (FDG-PET) and PET with amyloid-beta tracers are available to facilitate early accurate diagnoses. Enhancing diagnosis in the early stages of the disease can allow for timely interventions that can delay progression of the disease. This paper will discuss the characteristic findings associated with each of the imaging tools for patients with AD, with a focus on FDG-PET due to its established accuracy in assisting with the differential diagnosis of dementia and discussion of other methods including MRI. Diagnostically-relevant features to aid clinicians in making a differential diagnosis will also be pointed out and multimodal imaging will be reviewed. We also discuss the role of quantification software in interpretation of brain imaging. Lastly, to guide evaluation of patients presenting with cognitive deficits, an algorithm for optimal integration of these imaging tools will be shared. Molecular imaging modalities used in dementia evaluations hold promise toward identifying AD-related pathology before symptoms are fully in evidence. The work describes state of the art functional and molecular imaging methods for AD. It will also overview a clinically applicable quantitative method for reproducible assessments of such scans in the early identification of AD.

Is the p3 Peptide (Aβ17-40, Aβ17-42) Relevant to the Pathology of Alzheimer's Disease?1. - Kuhn, Ariel J; Raskatov, Jevgenij (J Alzheimers Dis, 2020)
Despite the vast heterogeneity of amyloid plaques isolated from the brains of those with Alzheimer's Disease (AD), the basis of the Amyloid Cascade Hypothesis targets a single peptide, the amyloid-β (Aβ) peptide. The countless therapeutic efforts targeting the production and aggregation of this specific peptide have been met with disappointment, leaving many to question the role of Aβ in AD. An alternative cleavage product of the Amyloid-β protein precursor, called the p3 peptide, which has also been isolated from the brains of AD patients, has been largely absent from most Aβ-related studies. Typically referred to as non-amyloidogenic and even suggested as neuroprotective, the p3 peptide has garnered little attention aside from some conflicting findings on cytotoxicity and potential self-assembly to form higher order aggregates. Herein, we report an extensive analysis of the findings surrounding p3 and offer some evidence as to why it may not be as innocuous as previously suggested.

Plasma High Density Lipoprotein Small Subclass is Reduced in Alzheimer's Disease Patients and Correlates with Cognitive Performance. - Pedrini, Steve; Hone, Eugene; Gupta, Veer B; James, Ian; Teimouri, Elham; Bush, Ashley I; Rowe, Christopher C; Villemagne, Victor L; Ames, David; Masters, Colin L; Rainey-Smith, Stephanie; Verdile, Giuseppe; et al. (J Alzheimers Dis, 2020)
BACKGROUND: The link between cholesterol and Alzheimer's disease (AD) has received much attention, as evidence suggests high levels of cholesterol might be an AD risk factor. The carriage of cholesterol and lipids through the body is mediated via lipoproteins, some of which, particularly apolipoprotein E (ApoE), are intimately linked with AD. In humans, high density lipoprotein (HDL) is regarded as a "good" lipid complex due to its ability to enable clearance of excess cholesterol via 'cholesterol reverse transport', although its activities in the pathogenesis of AD are poorly understood. There are several subclasses of HDL; these range from the newly formed small HDL, to much larger HDL. OBJECTIVE: We examined the major subclasses of HDL in healthy controls, mild cognitively impaired, and AD patients who were not taking statins to determine whether there were HDL profile differences between the groups, and whether HDL subclass levels correlated with plasma amyloid-β (Aβ) levels or brain Aβ deposition. METHODS: Samples from AIBL cohort were used in this study. HDL subclass levels were assessed by Lipoprint while Aβ1-42 levels were assessed by ELISA. Brain Aβ deposition was assessed by PET scan. Statistical analysis was performed using parametric and non-parametric tests. RESULTS: We found that small HDL subclass is reduced in AD patients and it correlates with cognitive performance while plasma Aβ concentrations do not correlate with lipid profile or HDL subfraction levels. CONCLUSION: Our data indicate that AD patients exhibit altered plasma HDL profile and that HDL subclasses correlate with cognitive performances.

Potential Novel Role of COVID-19 in Alzheimer's Disease and Preventative Mitigation Strategies. - Naughton, Sean X; Raval, Urdhva; Pasinetti, Giulio M (J Alzheimers Dis, 2020)
There are a number of potential implications for the field of Alzheimer's disease (AD) stemming from the global spread of SARS-CoV-2. Neuroinflammation is known to be a prominent feature of neurodegeneration and plays a major role in AD pathology. Immune response and excessive inflammation in COVID-19 may also accelerate the progression of brain inflammatory neurodegeneration, and elderly individuals are more susceptible to severe outcomes after SARS-CoV-2 infection. Individuals with type 2 diabetes (T2D) are at an increased risk for AD as well as severe outcomes after SARS-CoV-2 infection. Genetic and socioeconomic factors influencing the rates of T2D, AD, and COVID-19 severity may create an exceptionally high-risk profile for certain demographics such as African Americans and Hispanic Americans. Type I interferon response plays an important role in both host response to viral infection, as well as AD pathology and may be a sensible therapeutic target in both AD and COVID-19.
Keywords: Aged; Alzheimer Disease; Betacoronavirus; Coronavirus Infections; COVID-19; Diabetes Mellitus, Type 2; Humans; Interferon Type I; Pandemics; Pneumonia, Viral; SARS-CoV-2; Synapses

Potential of FTIR Spectroscopy Applied to Exosomes for Alzheimer's Disease Discrimination: A Pilot Study. - Martins, Tânia Soares; Magalhães, Sandra; Rosa, Ilka Martins; Vogelgsang, Jonathan; Wiltfang, Jens; Delgadillo, Ivonne; Catita, José; da Cruz E Silva, Odete A B; Nunes, Alexandra; Henriques, Ana Gabriela (J Alzheimers Dis, 2020)
Alzheimer's disease (AD) diagnosis is based on psychological and imaging tests but can also include monitoring cerebrospinal fluid (CSF) biomarkers. However, CSF based-neurochemical approaches are expensive and invasive, limiting their use to well-equipped settings. In contrast, blood-based biomarkers are minimally invasive, cost-effective, and a widely accessible alternative. Blood-derived exosomes have recently emerged as a reliable AD biomarker source, carrying disease-specific cargo. Fourier-transformed infrared (FTIR) spectroscopy meets the criteria for an ideal diagnostic methodology since it is rapid, easy to implement, and has high reproducibility. This metabolome-based technique is useful for diagnosing a broad range of diseases, although to our knowledge, no reports for FTIR spectroscopy applied to exosomes in AD exist. In this ground-breaking pilot study, FTIR spectra of serum and serum-derived exosomes from two independent cohorts were acquired and analyzed using multivariate analysis. The regional UA-cohort includes 9 individuals, clinically diagnosed with AD, mean age of 78.7 years old; and the UMG-cohort comprises 12 individuals, clinically diagnosed with AD (based on molecular and/or imaging data), mean age of 73.2 years old. Unsupervised principal component analysis of FTIR spectra of serum-derived exosomes revealed higher discriminatory value for AD cases when compared to serum as a whole. Consistently, the partial least-squares analysis revealed that serum-derived exosomes present higher correlations than serum. In addition, the second derivative peak area calculation also revealed significant differences among Controls and AD cases. The results obtained suggest that this methodology can discriminate cases from Controls and thus be potential useful to assist in AD clinical diagnosis.

The Relationship Between Anxiety and Incident Agitation in Alzheimer's Disease. - Liu, Kathy Y; Costello, Harry; Reeves, Suzanne; Howard, Robert (J Alzheimers Dis, 2020)
BACKGROUND: Agitation in Alzheimer's disease (AD) has been hypothesized to be an expression of anxiety, but whether anxiety early in the course of dementia could be a risk factor for developing later agitation is unknown. OBJECTIVE: We used the Alzheimer's Disease Neuroimaging Initiative (ADNI) database to examine the longitudinal relationship between anxiety and incident agitation in individuals with a diagnosis of AD at baseline or during follow-up. METHODS: Longitudinal neuropsychiatric symptom data from AD individuals who were agitation-free at study baseline (N = 272) were analyzed using mixed effects regression models to test the longitudinal relationship between baseline and incident anxiety with incident agitation. RESULTS: Anxiety at baseline was not associated with subsequent agitation, but there was a positive linear relationship between incident anxiety and agitation over the study duration. Baseline apathy and delusions were consistently associated with subsequent agitation and greater disease severity and illness duration also appeared to be risk factors for agitation. CONCLUSION: Our findings support the concept that anxiety and agitation are likely to be distinct rather than equivalent constructs in mild-moderate AD. Future longitudinal cohort studies are needed to replicate these findings and further characterize potential risk factors for agitation, such as apathy and delusions.

The Rhythmicity of Clock Genes is Disrupted in the Choroid Plexus of the APP/PS1 Mouse Model of Alzheimer's Disease. - Furtado, André; Astaburuaga, Rosario; Costa, Ana; Duarte, Ana C; Gonçalves, Isabel; Cipolla-Neto, José; Lemos, Manuel C; Carro, Eva; Relógio, Angela; Santos, Cecília R A; Quintela, Telma (J Alzheimers Dis, 2020)
BACKGROUND: The choroid plexus (CP), which constitutes the blood-cerebrospinal fluid barrier, was recently identified as an important component of the circadian clock system. OBJECTIVE: The fact that circadian rhythm disruption is closely associated to Alzheimer's disease (AD) led us to investigate whether AD pathology can contribute to disturbances of the circadian clock in the CP. METHODS: For this purpose, we evaluated the expression of core-clock genes at different time points, in 6- and 12-month-old female and male APP/PS1 mouse models of AD. In addition, we also assessed the effect of melatonin pre-treatment in vitro before amyloid-β stimulus in the daily pattern of brain and muscle Arnt-like protein 1 (Bmal1) expression. RESULTS: Our results showed a dysregulation of circadian rhythmicity of Bmal1 expression in female and male APP/PS1 transgenic 12-month-old mice and of Period 2 (Per2) expression in male mice. Besides, a significant circadian pattern of Bmal1 occurs in the intermittent melatonin pre-treatment group, showing that melatonin can reset the CP circadian clock. CONCLUSION: These results demonstrated a connection between AD and the disruption of circadian rhythm in the CP, representing an attractive target for disease prevention and/or treatment.

Role of Executive Functions in the Conversion from Mild Cognitive Impairment to Dementia. - Junquera Fernández, Almudena; García-Zamora, Estefanía; Olazarán Rodríguez, Javier; Parra Rodríguez, Mario A; Fernández-Guinea, Sara (J Alzheimers Dis, 2020)
BACKGROUND: Recent research pointed to executive dysfunction as a potential early predictor of the progression of mild cognitive impairment (MCI)-dementia in Alzheimer's clinical syndrome (ACS). Such cognitive impairments account for functional impairments in instrumental activities of daily living (IADL). OBJECTIVE: The present study analyzes the contributions of executive functions to predict MCI-dementia progression in ACS. METHODS: We assessed 145 participants, 51 cognitively unimpaired and 94 MCI. The latter were divided using the traditional, memory-based MCI classification (single domain amnestic, multidomain amnestic, and non-amnestic). Eight tests assessing executive functions were administered at baseline and at 1-year follow-up, together with cognitive screening tools and IADL measures. MCI patients were reclassified based on the outcomes from a K-mean cluster analysis which identified three groups. A simple lineal regression model was used to examine whether the classification based on executive functioning could more accurately predict progression to dementia a year later. RESULTS: Clusters based on executive function deficits explained a significant proportion of the variance linked to MCI-dementia conversion, even after controlling for the severity of MCI at baseline (F(1, 68) = 116.25, p = 0.000, R2 = 0.63). Classical memory-based MCI classification failed to predict such a conversion (F(1, 68) = 5.09, p = 0.955, R2 = 0.07). Switching, categories generation, and planning were the executive functions that best distinguished between MCI converters and stable. CONCLUSION: MCI with a dysexecutive phenotype significantly predicts conversion to dementia in ACS a year later. Switching abilities and verbal fluency (categories) must be evaluated in MCI patients to assess risk of future dementia.

Soluble TREM2 and Inflammatory Proteins in Alzheimer's Disease Cerebrospinal Fluid. - Rauchmann, Boris-Stephan; Sadlon, Angélique; Perneczky, Robert (J Alzheimers Dis, 2020)
The present study explores the associations of soluble TREM2, an important regulator of microglial activity linked to Alzheimer's disease (AD), with other known inflammatory proteins in cerebrospinal fluid (CSF). We studied 303 participants, including 89 controls, 135 mild cognitive impairment, and 79 AD dementia patients. Using established CSF biomarkers, subjects were classified according to the National Institute on Aging-Alzheimer's Association research framework, which groups markers into those of amyloid-β deposition (A), tau pathology (T), and neurodegeneration (N). TNFR1, TNFR2, TGF-β1, TGFβ2, IL-9, TNF-α, ICAM1, and VCAM1 showed significant concentration differences between the ATN groups, with higher concentrations in more advanced disease categories. sTREM2 was positively associated with the pro-inflammatory proteins TNF-α, TNFR1, TNFR2, ICAM1, VCAM1, and IP-10 and negatively with IL-21; also, positive associations with the anti-inflammatory proteins TGFβ1, IL-10, and IL-9 were found. Pathway enrichment analysis highlighted the involvement of sTREM2 in key functional clusters including immunoglobulin and cytokine production and cellular response to lipopolysaccharides, cytokines, and steroid hormones. Our work provides further evidence in support of TREM2 as amarker of neuroinflammatory response in AD.

Specific Neuropsychiatric Symptoms Are Associated with Faster Progression in Alzheimer's Disease: Results of the Prospective Dementia Registry (PRODEM-Austria). - Defrancesco, Michaela; Marksteiner, Josef; Kemmler, Georg; Dal-Bianco, Peter; Ransmayr, Gerhard; Benke, Thomas; Mosbacher, Jochen; Höller, Yvonne; Schmidt, Reinhold (J Alzheimers Dis, 2020)
BACKGROUND: Neuropsychiatric symptoms (NPS) occur frequently in the course of Alzheimer's disease (AD) and are suspected to be associated with a faster dementia progression. Numerous reports have defined specific subsyndromes, summarized in clusters of items of the Neuropsychiatric Inventory (NPI). OBJECTIVE: This study investigated the influence of specific NPI subsyndromes and clinical patient characteristics on dementia progression. METHODS: Data of the prospective registry on dementia in Austria (PRODEM) were retrospectively analyzed. Cognitive functioning was determined at baseline and 2 yearly follow-up visits using the Mini-Mental State Examination (MMSE) and the Consortium to Establish a Registry for Alzheimer's dementia neuropsychological test battery (CERAD). To assess NPS, the NPI was used: NPI items were classified in three subsyndromes (psychotic cluster, behavioral cluster, emotional cluster). RESULTS: Out of the 662 included patients (mean age 76.4±8.4 years), 43% completed follow-up visits for two years. Significant correlation between higher scores in all three subsyndromes and worse cognitive performance were found for MMSE score, naming, and verbal fluency. Results of linear mixed model analysis revealed lower age and higher scores in the psychotic cluster as significant predictors of changes in MMSE with time. CONCLUSION: In this study, we report the influence of psychotic subsyndromes and lower age on faster MMSE decline in early AD. These results emphasize the importance of not only assessing but also differentiating neuropsychiatric symptoms in subsyndromes in the early stages of AD as a possible predictor of disease progression.

Structural Brain Changes in Pre-Clinical FTD MAPT Mutation Carriers. - Domínguez-Vivero, Clara; Wu, Liwen; Lee, Seonjoo; Manoochehri, Masood; Cines, Sarah; Brickman, Adam M; Rizvi, Batool; Chesebro, Anthony; Gazes, Yunglin; Fallon, Emer; Lynch, Timothy; Heidebrink, Judith L; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Frontotemporal dementia (FTD) is the second most common cause of early-onset neurodegenerative dementia. Several studies have focused on early imaging changes in FTD patients, but once subjects meet full criteria for the FTD diagnosis, structural changes are generally widespread. OBJECTIVE: This study aims to determine the earliest structural brain changes in asymptomatic MAPT MUTATION carriers. METHODS: This is a cross-sectional multicenter study comparing global and regional brain volume and white matter integrity in a group of MAPT mutation preclinical carriers and controls. Participants belong to multiple generations of six families with five MAPT mutations. All participants underwent a medical examination, neuropsychological tests, genetic analysis, and a magnetic resonance scan (3T, scout, T1-weighted image followed by EPI (BOLD), MPRAGE, DTI, FLAIR, and ASL sequences). RESULTS: Volumes of five cortical and subcortical areas were strongly correlated with mutation status: temporal lobe (left amygdala, left temporal pole), cingulate cortex (left rostral anterior cingulate gyrus, right posterior cingulate), and the lingual gyrus in the occipital lobe. We did not find significant differences in whole brain volume, white matter hyperintensities volume, and white matter integrity using DTI analysis. CONCLUSION: Temporal lobe, cingulate cortex and the lingual gyrus seem to be early targets of the disease and may serve as biomarkers for FTD prior to overt symptom onset.

Structural Brain Magnetic Resonance Imaging to Rule Out Comorbid Pathology in the Assessment of Alzheimer's Disease Dementia: Findings from the Ontario Neurodegenerative Disease Research Initiative (ONDRI) Study and Clinical Trials Over the Past 10 Years. - Kapoor, Arunima; Bartha, Robert; Black, Sandra E; Borrie, Michael; Freedman, Morris; Gao, Fuqiang; Herrmann, Nathan; Mandzia, Jennifer; Ozzoude, Miracle; Ramirez, Joel; Scott, Christopher J M; Symons, Sean; et al. (J Alzheimers Dis, 2020)
BACKGROUND/OBJECTIVE: Structural brain magnetic resonance imaging (MRI) is not mandatory in Alzheimer's disease (AD) research or clinical guidelines. We aimed to explore the use of structural brain MRI in AD/mild cognitive impairment (MCI) trials over the past 10 years and determine the frequency with which inclusion of standardized structural MRI acquisitions detects comorbid vascular and non-vascular pathologies. METHODS: We systematically searched ClinicalTrials.gov for AD clinical trials to determine their neuroimaging criteria and then used data from an AD/MCI cohort who underwent standardized MRI protocols, to determine type and incidence of clinically relevant comorbid pathologies. RESULTS: Of 210 AD clinical trials, 105 (50%) included structural brain imaging in their eligibility criteria. Only 58 (27.6%) required MRI. 16,479 of 53,755 (30.7%) AD participants were in trials requiring MRI. In the observational AD/MCI cohort, 141 patients met clinical criteria; 22 (15.6%) had relevant MRI findings, of which 15 (10.6%) were exclusionary for the study. DISCUSSION: In AD clinical trials over the last 10 years, over two-thirds of participants could have been enrolled without brain MRI and half without even a brain CT. In a study sample, relevant comorbid pathology was found in 15% of participants, despite careful screening. Standardized structural MRI should be incorporated into NIA-AA diagnostic guidelines (when available) and research frameworks routinely to reduce diagnostic heterogeneity.

Using Machine Learning to Predict Dementia from Neuropsychiatric Symptom and Neuroimaging Data. - Gill, Sascha; Mouches, Pauline; Hu, Sophie; Rajashekar, Deepthi; MacMaster, Frank P; Smith, Eric E; Forkert, Nils D; Ismail, Zahinoor (J Alzheimers Dis, 2020)
BACKGROUND: Machine learning (ML) is a promising technique for patient-specific prediction of mild cognitive impairment (MCI) and dementia development. Neuropsychiatric symptoms (NPS) might improve the accuracy of ML models but have barely been used for this purpose. OBJECTIVES: To investigate if baseline mild behavioral impairment (MBI) status used for NPS quantification along with brain morphology features are predictive of follow-up diagnosis, median 40 months later in patients with normal cognition (NC) or MCI. METHOD: Baseline neuroimaging, neuropsychiatric, and clinical data from 102 individuals with NC and 239 with MCI were extracted from the Alzheimer's Disease Neuroimaging Initiative database. Neuropsychiatric inventory questionnaire items were transformed to MBI domains using a published algorithm. Diagnosis at latest follow-up was used as the outcome variable and ground truth classification. A logistic model tree classifier combined with information gain feature selection was trained to predict follow-up diagnosis. RESULTS: In the binary classification (NC versus MCI/AD), the optimal ML model required only two features from over 200, MBI total score and left hippocampal volume. These features correctly classified participants as remaining normal or developing cognitive impairment with 84.4% accuracy (area under the receiver operating characteristics curve [ROC-AUC] = 0.86). Seven features were selected for the three-class model (NC versus MCI versus dementia) achieving an accuracy of 58.8% (ROC-AUC=0.73). CONCLUSION: Baseline NPS, categorized for MBI domain and duration, have prognostic utility in addition to brain morphology measures for predicting diagnosis change using ML. MBI total score, followed by impulse dyscontrol and affective dysregulation were most predictive of future diagnosis.

Validation of Plasma Proteomic Biomarkers Relating to Brain Amyloid Burden in the EMIF-Alzheimer's Disease Multimodal Biomarker Discovery Cohort. - Westwood, Sarah; Baird, Alison L; Anand, Sneha N; Nevado-Holgado, Alejo J; Kormilitzin, Andrey; Shi, Liu; Hye, Abdul; Ashton, Nicholas J; Morgan, Angharad R; Bos, Isabelle; Vos, Stephanie J B; Baker, Susan; et al. (J Alzheimers Dis, 2020)
We have previously investigated, discovered, and replicated plasma protein biomarkers for use to triage potential trials participants for PET or cerebrospinal fluid measures of Alzheimer's disease (AD) pathology. This study sought to undertake validation of these candidate plasma biomarkers in a large, multi-center sample collection. Targeted plasma analyses of 34 proteins with prior evidence for prediction of in vivo pathology were conducted in up to 1,000 samples from cognitively healthy elderly individuals, people with mild cognitive impairment, and in patients with AD-type dementia, selected from the EMIF-AD catalogue. Proteins were measured using Luminex xMAP, ELISA, and Meso Scale Discovery assays. Seven proteins replicated in their ability to predict in vivo amyloid pathology. These proteins form a biomarker panel that, along with age, could significantly discriminate between individuals with high and low amyloid pathology with an area under the curve of 0.74. The performance of this biomarker panel remained consistent when tested in apolipoprotein E ɛ4 non-carrier individuals only. This blood-based panel is biologically relevant, measurable using practical immunocapture arrays, and could significantly reduce the cost incurred to clinical trials through screen failure.

Alzheimer's and Parkinson's Diseases and the Risk of Cancer: A Cohort Study. - Ording, Anne G; Veres, Katalin; Horváth-Puhó, Erzsébet; Glymour, M Maria; Rørth, Mikael; Henderson, Victor W; Sørensen, Henrik T (J Alzheimers Dis, 2019)
Observational studies have shown inverse associations between neurological diseases, particularly dementia, and subsequent cancer risk, but is unknown whether this association is valid or arises from bias. We conducted a Danish nationwide cohort study using population-based health registries (1980-2012). The study included patients with dementia (n = 173,434) and with Parkinson's disease (n = 28,835). We followed patients for 10 years to assess subsequent cancer diagnoses. We computed absolute reduction in cancer risk attributable to dementia or Parkinson's disease (expected minus the observed number of cancer cases divided by the person time) and standardized incidence rate ratios (SIRs) as the observed to expected number of cancers, based on sex-, age-, and calendar year-standardized national incidence rates. During 10 years, the reduction in cancer cases were 79.9 per 10,000 person-years for Alzheimer's disease [SIR = 0.68 (95% CI: 0.66, 0.70)], 74.4 per 10,000 person-years for vascular dementia [SIR = 0.71 (95% CI: 0.67, 0.74)], 55.8 per 10,000 person-years [SIR = 0.77 (95% CI: 0.75, 0.78)] for all-cause dementia, and 4.0 per 10,000 person-years [SIR = 0.98 (95% CI: 0.95, 1.02) for Parkinson's disease. Associations were nearly similar for solid tumors diagnosed at localized, regional, or distant stages. We found an inverse association between dementia and cancer risk, with similar associations when considering only cancers diagnosed at distant stage. The cancer risk varied by type of dementia, with a gradient toward a stronger protective effect associated with Alzheimer's disease and vascular dementia, which may favor a biological explanation. Overall results do not show an inverse association between Parkinson's disease and cancer.

Amyloidogenic Nanoplaques in Blood Serum of Patients with Alzheimer's Disease Revealed by Time-Resolved Thioflavin T Fluorescence Intensity Fluctuation Analysis. - Tiiman, Ann; Jelic, Vesna; Jarvet, Jüri; Järemo, Petter; Bogdanovic, Nenad; Rigler, Rudolf; Terenius, Lars; Gräslund, Astrid; Vukojević, Vladana (J Alzheimers Dis, 2019)
BACKGROUND: Biomarkers are central to current research on molecular mechanisms underlying Alzheimer's disease (AD). Their further development is of paramount importance for understanding pathophysiological processes that eventually lead to disease onset. Biomarkers are also crucial for early disease detection, before clinical manifestation, and for development of new disease modifying therapies. OBJECTIVE: The overall aim of this work is to develop a minimally invasive method for fast, ultra-sensitive and cost-effective detection of structurally modified peptide/protein self-assemblies in the peripheral blood and in other biological fluids. Specifically, we focus here on using this method to detect structured amyloidogenic oligomeric aggregates in the blood serum of apparently healthy individuals and patients in early AD stage, and measure their concentration and size. METHODS: Time-resolved detection of Thioflavin T (ThT) fluorescence intensity fluctuations in a sub-femtoliter observation volume element was used to identify in blood serum ThT-active structured amyloidogenic oligomeric aggregates, hereafter called nanoplaques, and measure with single-particle sensitivity their concentration and size. RESULTS: The concentration and size of structured amyloidogenic nanoplaques are significantly higher in the blood serum of individuals diagnosed with AD than in control subjects. CONCLUSION: A new method with the ultimate, single-particle sensitivity was successfully developed. The proposed approach neither relies on the use of immune-based probes, nor on the use of radiotracers, signal-amplification or protein separation techniques, and provides a minimally invasive test for fast and cost-effective early determination of structurally modified peptides/proteins in the peripheral blood, as shown here, but also in other biological fluids.

APOE ɛ4 Carriers Show Delayed Recovery of Verbal Memory and Smaller Entorhinal Volume in the First Year After Ischemic Stroke. - Werden, Emilio; Khlif, Mohamed Salah; Bird, Laura J; Cumming, Toby; Bradshaw, Jennifer; Khan, Wasim; Pase, Matthew; Restrepo, Carolina; Veldsman, Michele; Egorova, Natalia; Patel, Sheila K; Gottlieb, Elie; et al. (J Alzheimers Dis, 2019)
BACKGROUND: The apolipoprotein E (APOE) gene ɛ4 allele is a risk factor for Alzheimer's disease and cardiovascular disease. However, its relationship with cognition and brain volume after stroke is not clear. OBJECTIVE: We compared cognition and medial temporal lobe volumes in APOEɛ4 carriers and non-carriers in the first year after ischemic stroke. METHODS: We sampled 20 APOEɛ4 carriers and 20 non-carriers from a larger cohort of 135 ischemic stroke participants in the longitudinal CANVAS study. Participants were matched on a range of demographic and stroke characteristics. We used linear mixed-effect models to compare cognitive domain z-scores (attention, processing speed, executive function, verbal and visual memory, language, visuospatial function) and regional medial temporal lobe volumes (hippocampal, entorhinal cortex) between groups at each time-point (three, 12-months post-stroke), and within groups across time-points. APOE gene single nucleotide polymorphisms (SNPs; rs7412, rs429358) were genotyped on venous blood. RESULTS: APOEɛ4 carriers and non-carriers did not differ on any demographic, clinical, or stroke variable. Carriers performed worse than non-carriers in verbal memory at three months post-stroke (p = 0.046), but were better in executive function at 12 months (p = 0.035). Carriers demonstrated a significant improvement in verbal memory (p = 0.012) and executive function (p = 0.015) between time-points. Non-carriers demonstrated a significant improvement in visual memory (p = 0.0005). Carriers had smaller bilateral entorhinal cortex volumes (p <  0.05), and larger-right-sided and contralesional hippocampal volumes, at both time-points (p <  0.05). CONCLUSION: APOE ɛ4 is associated with delayed recovery of verbal memory function and reduced entorhinal cortex volumes in the first year after ischemic stroke.

Association between Adipokines and Biomarkers of Alzheimer's Disease: A Cross-Sectional Study. - Letra, Liliana; Matafome, Paulo; Rodrigues, Tiago; Duro, Diana; Lemos, Raquel; Baldeiras, Ines; Patrício, Miguel; Castelo-Branco, Miguel; Caetano, Gina; Seiça, Raquel; Santana, Isabel (J Alzheimers Dis, 2019)
BACKGROUND: Adipose tissue dysfunction has been implicated in the pathophysiology of Alzheimer's disease. However, the involvement of adipokines, particularly adiponectin, remains unclear. OBJECTIVE: To compare serum and cerebrospinal fluid (CSF) levels of adiponectin, leptin and leptin-to-adiponectin ratio in patients within the spectrum of Alzheimer's disease and evaluate their relationship with classical biomarkers and their value as markers of progression. METHODS: Amnestic mild cognitive impairment (MCI, n = 71) and Alzheimer's dementia (AD, n = 53) subjects were consecutively recruited for serum and CSF adiponectin and leptin determination using an analytically validated commercial enzyme-linked immunosorbent assay (ELISA). Correlations were explored using adjusted Spearman's correlation coefficients. A logistic regression model and ROC analysis were performed to evaluate the staging predictive value of adipokines. RESULTS: Serum adiponectin was 33% higher in AD when compared to MCI patients. Adiponectin CSF levels, similar in both groups, were positively correlated with Aβ42 and cognitive function, though only in women. The area under the ROC curve was 0.673 (95% CI:0.57-0.78) for serum adiponectin as predictor of dementia stage and the cut-off 10.85μg/ml maximized the sum of specificity (87%) and sensitivity (44%). CONCLUSION: Although longitudinal studies are required, we hypothesize that higher serum adiponectin in AD patients constitutes a strategy to compensate possible central signaling defects. In addition, adiponectin might be specifically assigned to neuroprotective functions in women and eventually involved in the female-biased incidence of Alzheimer's disease.

Cerebrospinal Fluid Level of Aquaporin4: A New Window on Glymphatic System Involvement in Neurodegenerative Disease? - Arighi, Andrea; Di Cristofori, Andrea; Fenoglio, Chiara; Borsa, Stefano; D'Anca, Marianna; Fumagalli, Giorgio Giulio; Locatelli, Marco; Carrabba, Giorgio; Pietroboni, Anna Margherita; Ghezzi, Laura; Carandini, Tiziana; Colombi, Annalisa; et al. (J Alzheimers Dis, 2019)
Aquaporin4 (AQP4) is a water channel protein located at astrocyte foot processes that plays a role in glymphatic system, a highly organized fluid transport pathway which seems to be involved in Alzheimer's disease (AD) and normal pressure hydrocephalus (NPH) pathophysiology. Cerebrospinal fluid (CSF) AQP4 levels were determined in 11 patients with AD, 10 patients with NPH, and 9 controls. We found significantly reduced AQP4 in AD patients, a trend in reduction in NPH patients, and a correlation between AQP4 and amyloid-β CSF levels. This study indicates the potential role of AQP4 and glymphatic system in neurodegenerative diseases pathophysiology.

Choroid Plexus Acts as Gatekeeper for TREM2, Abnormal Accumulation of ApoE, and Fibrillary Tau in Alzheimer's Disease and in Down Syndrome Dementia. - Raha-Chowdhury, Ruma; Henderson, James W; Raha, Animesh Alexander; Vuono, Romina; Bickerton, Anastasia; Jones, Elizabeth; Fincham, Robert; Allinson, Kieren; Holland, Anthony; Zaman, Shahid H (J Alzheimers Dis, 2019)
BACKGROUND: Genetic factors that influence Alzheimer's disease (AD) risk include mutations in TREM2 and allelic variants of Apolipoprotein E, influencing AD pathology in the general population and in Down syndrome (DS). Evidence shows that dysfunction of the choroid plexus may compromise the blood-cerebrospinal fluid (CSF) barrier, altering secretary, transport and immune function that can affect AD pathology. OBJECTIVE: To investigate the genotype and phenotype of DS individuals in relation to choroid plexus damage and blood-CSF barrier leakage to identify markers that could facilitate early diagnosis of AD in DS. METHODS: To assess allele frequency and haplotype associations ApoE, Tau, TREM2, and HLA-DR were analyzed by SNP analysis in DS participants (n = 47) and controls (n = 50). The corresponding plasma protein levels were measured by ELISA. Postmortem brains from DS, AD, and age-matched controls were analyzed by immunohistochemistry. RESULTS: Haplotype analysis showed that individuals with Tau H1/H1 and ApoEɛ4 genotypes were more prevalent among DS participants with an earlier diagnosis of dementia (17%) compared to H1/H2 haplotypes (6%). Plasma TREM2 levels decreased whereas phospho-tau levels increased with age in DS. In AD and DS brain, insoluble tau and ApoE were found to accumulate in the choroid plexus. CONCLUSION: Accumulation of tau and ApoE in the choroid plexus may increase the oligomerization rate of Aβ42 and impair tau trafficking, leading to AD pathology. We have identified a high-risk haplotype: ApoEɛ4, Tau/H1, and TREM2/T, that manifests age-related changes potentially opening a window for treatment many years prior to the manifestation of the AD dementia.

Circulating and Extracellular Vesicles Levels of N-(1-Carboxymethyl)-L-Lysine (CML) Differentiate Early to Moderate Alzheimer's Disease. - Haddad, Mohamed; Perrotte, Morgane; Landri, Sarra; Lepage, Aurelie; Fülöp, Tamás; Ramassamy, Charles (J Alzheimers Dis, 2019)
BACKGROUND: Both advanced glycation end products (AGEs) N-(1-carboxymethyl)-L-lysine (CML) and pentosidine were found in the brain from Alzheimer's disease (AD) patients and were associated with the neuropathological hallmarks of AD. In AD patients, the circulating level of both AGEs remains unknown. Moreover, their levels in peripheral extracellular vesicles (EVs) and their association with AD remain to be determined. Finally, it is not known if neuronal cells can release AGEs via EVs and propagate AGEs. OBJECTIVE: To determine the levels of circulating CML and pentosidine during the progression of AD. Moreover, their levels in circulating EVs were determined and their association with the clinical cognitive scores were analyzed. Finally, we have studied the possibility that neuronal cells eliminate and transfer these AGEs through EVs. METHODS: CML and pentosidine levels were measured in serum and in circulating EVs. Released-EVs from SK-N-SH neuronal cells were isolated and CML levels were also determined. RESULTS: The levels of CML in albumin-free serum proteins were higher in the early stage of AD while the levels of pentosidine remained unchanged. In contrast, the levels of CML in the EVs were lower in the moderate stage of AD. Interestingly, the levels of CML in serum were negatively correlated with the clinical cognitive scores MMSE and MoCA. For the first time, we were able to demonstrate that CML was present in EVs released from neuronal cells in culture. CONCLUSION: Peripheral and circulating EVs levels of CML can differentiate early to moderate AD. In the brain, neuronal CML can propagate from cells-to-cells via EVs.

Education Moderates the Relation Between APOE ɛ4 and Memory in Nondemented Non-Hispanic Black Older Adults. - Vonk, Jet M J; Rentería, Miguel Arce; Medina, Valerie M; Pericak-Vance, Margaret A; Byrd, Goldie S; Haines, Jonathan; Brickman, Adam M; Manly, Jennifer J (J Alzheimers Dis, 2019)
BACKGROUND: The APOEɛ4 allele is a well-known risk factor for Alzheimer's disease (AD). Previous research argues that higher education helps to preserve cognition in older adults with AD pathology because of its key role in cognitive reserve and resilience. OBJECTIVE: To test if higher educational level buffers the effect of APOEɛ4 on cognition among older non-Hispanic Blacks. METHODS: Participants were 849 non-demented older non-Hispanic Blacks (38.3% APOEɛ4+), who underwent a comprehensive neuropsychological evaluation. Multiple linear regression models tested the relationship between APOEɛ4 status and twelve cognitive measures with education (up to high school and beyond high school) as a moderator. RESULTS: Education buffered the effects of the APOEɛ4 allele, such that there was no impact of APOEɛ4 status on word-list memory retention and working memory among participants with more than a high school degree. This pattern was not observed for ten other cognitive measures of verbal and visual episodic memory, semantic memory, executive function, and processing speed-although a similar trend was observed for switching ability in executive functioning. The buffering effect of education was stronger among women than men. CONCLUSION: Our findings suggest that genetic effects on late-life cognition may be modified by environmental factors such as educational attainment. These results are consistent with the framework of cognitive reserve such that engaging in cognitively enriching activities and acquiring skills and knowledge with more years of education may increase the capacity to maintain cognitive function despite high genetic risk for impairment.

Exercise Training in Amnestic Mild Cognitive Impairment: A One-Year Randomized Controlled Trial. - Tarumi, Takashi; Rossetti, Heidi; Thomas, Binu P; Harris, Thomas; Tseng, Benjamin Y; Turner, Marcel; Wang, Ciwen; German, Zohre; Martin-Cook, Kristin; Stowe, Ann M; Womack, Kyle B; Mathews, Dana; et al. (J Alzheimers Dis, 2019)
BACKGROUND: The current evidence is inconclusive to support the benefits of aerobic exercise training (AET) for preventing neurocognitive decline in patients with amnestic mild cognitive impairment (aMCI). OBJECTIVE: To examine the effect of a progressive, moderate-to-high intensity AET program on memory and executive function, brain volume, and cortical amyloid-β (Aβ) plaque deposition in aMCI patients. METHODS: This is a proof-of-concept trial that randomized 70 aMCI patients to 12 months of AET or stretching and toning (SAT, active control) interventions. Primary neuropsychological outcomes were assessed by using the California Verbal Learning Test-second edition (CVLT-II) and the Delis-Kaplan Executive Function System (D-KEFS). Secondary outcomes were the global and hippocampal brain volumes and the mean cortical and precuneus Aβ deposition. RESULTS: Baseline cognitive scores were similar between the groups. Memory and executive function performance improved over time but did not differ between the AET and SAT groups. Brain volume decreased and precuneus Aβ plaque deposition increased over time but did not differ between the groups. Cardiorespiratory fitness was significantly improved in the AET compared with SAT group. In amyloid positive patients, AET was associated with reduced hippocampal atrophy when compared with the SAT group. CONCLUSION: The AET and SAT groups both showed evidence of slightly improved neuropsychological scores in previously sedentary aMCI patients. However, these interventions did not prevent brain atrophy or increases in cortical Aβ deposition over 12 months. In amyloid positive patients, AET reduced hippocampal atrophy when compared with the SAT group.

Geographical Variation in the Diagnostic Rate and Quality of Dementia Diagnoses. - Zakarias, Johanne Købstrup; Jensen-Dahm, Christina; Nørgaard, Ane; Roos, Peter; Gasse, Christiane; Phung, Thien Kieu Thi; Waldemar, Gunhild (J Alzheimers Dis, 2019)
BACKGROUND: Early and accurate diagnosis of dementia opens the door to appropriate treatment, support, and counseling. Despite availability of evidence-based guidelines for diagnostic evaluation of dementia, the diagnostic rate in people with dementia is low and the quality of dementia diagnoses is unknown. OBJECTIVE: The overall aim of this register-based study was to analyze the quality of diagnostic evaluation of dementia by assessing nationwide geographical variations in a range of indicators. METHODS: A register-based cross-sectional study of the entire Danish population aged 65 years or older in 2015 was conducted. The surrogate indicators for diagnostic quality included 1) prevalence rates of dementia diagnoses, 2) incidence rates of dementia diagnoses, 3) age at first diagnosis of dementia, 4) medical specialty responsible for diagnosis, 5) diagnostic rate of dementia subtypes, and 6) use of anti-dementia medication. The indicators were compared across the five Danish regions. RESULTS: The national prevalence and incidence of registered dementia diagnoses was 3.0% and 0.5%, respectively. The proportion of patients diagnosed at a dementia specialist department ranged from 60.9% to 90.5% across the five regions, subtype specific diagnosis ranged from 45.3% to 75.5%, and use of anti-dementia medication ranged from 29.2% to 58.3%. CONCLUSION: The observed geographical variations in dementia diagnoses and treatment indicate inequality in the access to appropriate diagnostic evaluation and care for patients with dementia. Our findings call for more awareness of the benefits of timely diagnosis and for improvement in the quality of diagnostic evaluation of dementia.

Impaired Glucose Tolerance and Reduced Plasma Insulin Precede Decreased AKT Phosphorylation and GLUT3 Translocation in the Hippocampus of Old 3xTg-AD Mice. - Griffith, Chelsea M; Macklin, Lauren N; Cai, Yan; Sharp, Andrew A; Yan, Xiao-Xin; Reagan, Lawrence P; Strader, April D; Rose, Gregory M; Patrylo, Peter R (J Alzheimers Dis, 2019)
Several studies have demonstrated that mouse models of Alzheimer's disease (AD) can exhibit impaired peripheral glucose tolerance. Further, in the APP/PS1 mouse model, this is observed prior to the appearance of AD-related neuropathology (e.g., amyloid-β plaques; Aβ) or cognitive impairment. In the current study, we examined whether impaired glucose tolerance also preceded AD-like changes in the triple transgenic model of AD (3xTg-AD). Glucose tolerance testing (GTT), insulin ELISAs, and insulin tolerance testing (ITT) were performed at ages prior to (1-3 months and 6-8 months old) and post-pathology (16-18 months old). Additionally, we examined for altered insulin signaling in the hippocampus. Western blots were used to evaluate the two-primary insulin signaling pathways: PI3K/AKT and MAPK/ERK. Since the PI3K/AKT pathway affects several downstream targets associated with metabolism (e.g., GSK3, glucose transporters), western blots were used to examine possible alterations in the expression, translocation, or activation of these targets. We found that 3xTg-AD mice display impaired glucose tolerance as early as 1 month of age, concomitant with a decrease in plasma insulin levels well prior to the detection of plaques (∼14 months old), aggregates of hyperphosphorylated tau (∼18 months old), and cognitive decline (≥18 months old). These alterations in peripheral metabolism were seen at all time points examined. In comparison, PI3K/AKT, but not MAPK/ERK, signaling was altered in the hippocampus only in 18-20-month-old 3xTg-AD mice, a time point at which there was a reduction in GLUT3 translocation to the plasma membrane. Taken together, our results provide further evidence that disruptions in energy metabolism may represent a foundational step in the development of AD.

Improved Differential Diagnosis of Alzheimer's Disease by Integrating ELISA and Mass Spectrometry-Based Cerebrospinal Fluid Biomarkers. - Khoonsari, Payam Emami; Shevchenko, Ganna; Herman, Stephanie; Remnestål, Julia; Giedraitis, Vilmantas; Brundin, RoseMarie; Degerman Gunnarsson, Malin; Kilander, Lena; Zetterberg, Henrik; Nilsson, Peter; Lannfelt, Lars; Ingelsson, Martin; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Alzheimer's disease (AD) is diagnosed based on a clinical evaluation as well as analyses of classical biomarkers: Aβ42, total tau (t-tau), and phosphorylated tau (p-tau) in cerebrospinal fluid (CSF). Although the sensitivities and specificities of the classical biomarkers are fairly good for detection of AD, there is still a need to develop novel biochemical markers for early detection of AD. OBJECTIVE: We explored if integration of novel proteins with classical biomarkers in CSF can better discriminate AD from non-AD subjects. METHODS: We applied ELISA, mass spectrometry, and multivariate modeling to investigate classical biomarkers and the CSF proteome in subjects (n = 206) with 76 AD patients, 74 mild cognitive impairment (MCI) patients, 11 frontotemporal dementia (FTD) patients, and 45 non-dementia controls. The MCI patients were followed for 4-9 years and 21 of these converted to AD, whereas 53 remained stable. RESULTS: By combining classical CSF biomarkers with twelve novel markers, the area of the ROC curves (AUROCS) of distinguishing AD and MCI/AD converters from non-AD were 93% and 96%, respectively. The FTDs and non-dementia controls were identified versus all other groups with AUROCS of 96% and 87%, respectively. CONCLUSIONS: Integration of new and classical CSF biomarkers in a model-based approach can improve the identification of AD, FTD, and non-dementia control subjects.

Intraneuronal Tau Misfolding Induced by Extracellular Amyloid-β Oligomers. - Rudenko, Lauren K; Wallrabe, Horst; Periasamy, Ammasi; Siller, Karsten H; Svindrych, Zdenek; Seward, Matthew E; Best, Merci N; Bloom, George S (J Alzheimers Dis, 2019)
Abnormal folding and aggregation of the microtubule-associated protein, tau, is a hallmark of several neurodegenerative disorders, including Alzheimer's disease (AD). Although normal tau is an intrinsically disordered protein, it does exhibit tertiary structure whereby the N- and C-termini are often in close proximity to each other and to the contiguous microtubule-binding repeat domains that extend C-terminally from the middle of the protein. Unfolding of this paperclip-like conformation might precede formation of toxic tau oligomers and filaments, like those found in AD brain. While there are many ways to monitor tau aggregation, methods to monitor changes in tau folding are not well established. Using full length human 2N4R tau doubly labeled with the Förster resonance energy transfer (FRET) compatible fluorescent proteins, Venus and Teal, on the N- and C-termini, respectively (Venus-Tau-Teal), intensity and lifetime FRET measurements were able to distinguish folded from unfolded tau in living cells independently of tau-tau intermolecular interactions. When expression was restricted to low levels in which tau-tau aggregation was minimized, Venus-Tau-Teal was sensitive to microtubule binding, phosphorylation, and pathogenic oligomers. Of particular interest is our finding that amyloid-β oligomers (AβOs) trigger Venus-Tau-Teal unfolding in cultured mouse neurons. We thus provide direct experimental evidence that AβOs convert normally folded tau into a conformation thought to predominate in toxic tau aggregates. This finding provides further evidence for a mechanistic connection between Aβ and tau at seminal stages of AD pathogenesis.

Maintain Your Brain: Protocol of a 3-Year Randomized Controlled Trial of a Personalized Multi-Modal Digital Health Intervention to Prevent Cognitive Decline Among Community Dwelling 55 to 77 Year Olds. - Heffernan, Megan; Andrews, Gavin; Fiatarone Singh, Maria A; Valenzuela, Michael; Anstey, Kaarin J; Maeder, Anthony J; McNeil, John; Jorm, Louisa; Lautenschlager, Nicola T; Sachdev, Perminder S; Ginige, Jeewani A; Hobbs, Megan J; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Maintain Your Brain (MYB) is a randomized controlled trial of an online multi-modal lifestyle intervention targeting modifiable dementia risk factors with its primary aim being to reduce cognitive decline in an older age cohort. METHODS: MYB aims to recruit 8,500 non-demented community dwelling 55 to 77 year olds from the Sax Institute's 45 and Up Study in New South Wales, Australia. Participants will be screened for risk factors related to four modules that comprise the MYB intervention: physical activity, nutrition, mental health, and cognitive training. Targeting risk factors will enable interventions to be personalized so that participants receive the most appropriate modules. MYB will run for three years and up to four modules will be delivered sequentially each quarter during year one. Upon completing a module, participants will continue to receive less frequent booster activities for their eligible modules (except for the mental health module) until the end of the trial. DISCUSSION: MYB will be the largest internet-based trial to attempt to prevent cognitive decline and potentially dementia. If successful, MYB will provide a model for not just effective intervention among older adults, but an intervention that is scalable for broad use.

Midlife Insulin Resistance as a Predictor for Late-Life Cognitive Function and Cerebrovascular Lesions. - Toppala, Sini; Ekblad, Laura L; Lötjönen, Jyrki; Helin, Semi; Hurme, Saija; Johansson, Jarkko; Jula, Antti; Karrasch, Mira; Koikkalainen, Juha; Laine, Hanna; Parkkola, Riitta; Viitanen, Matti; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Type 2 diabetes (T2DM) increases the risk for Alzheimer's disease (AD) but not for AD neuropathology. The association between T2DM and AD is assumed to be mediated through vascular mechanisms. However, insulin resistance (IR), the hallmark of T2DM, has been shown to associate with AD neuropathology and cognitive decline. OBJECTIVE: To evaluate if midlife IR predicts late-life cognitive performance and cerebrovascular lesions (white matter hyperintensities and total vascular burden), and whether cerebrovascular lesions and brain amyloid load are associated with cognitive functioning. METHODS: This exposure-to-control follow-up study examined 60 volunteers without dementia (mean age 70.9 years) with neurocognitive testing, brain 3T-MRI and amyloid-PET imaging. The volunteers were recruited from the Finnish Health 2000 survey (n = 6062) to attend follow-up examinations in 2014-2016 according to their insulin sensitivity in 2000 and their APOE genotype. The exposure group (n = 30) had IR in 2000 and the 30 controls had normal insulin sensitivity. There were 15 APOEɛ4 carriers per group. Statistical analyses were performed with multivariable linear models. RESULTS: At follow-up the IR+group performed worse on executive functions (p = 0.02) and processing speed (p = 0.007) than the IR- group. The groups did not differ in cerebrovascular lesions. No associations were found between cerebrovascular lesions and neurocognitive test scores. Brain amyloid deposition associated with slower processing speed. CONCLUSION: Midlife IR predicted poorer executive functions and slower processing speed, but not cerebrovascular lesions. Brain amyloid deposition was associated with slower processing speed. The association between midlife IR and late-life cognition might not be mediated through cerebrovascular lesions measured here.

Molecular Basis of Alzheimer's Disease: Focus on Mitochondria. - Oliver, Darryll M A; Reddy, P Hemachandra (J Alzheimers Dis, 2019)
Alzheimer's disease (AD) is a progressive neurodegenerative disease, characterized by memory loss and multiple cognitive impairments. With the increased aging population, AD is a major health concern in society. Morphological and pathological studies revealed that AD is associated with the loss of synapses, defective mitochondria, and the proliferation of reactive astrocytes and microglia, in addition to the presence amyloid-β and phosphorylated tau in learning and memory regions of the brain in AD patients. AD occurs in two forms: early-onset familial and late-onset sporadic. Genetic mutations in APP, PS1, and PS2 loci cause familial AD. Multiple factors are reported to be involved in late-onset AD, including APOE4 genotype, polymorphisms in several gene loci and type 2 diabetes, traumatic brain injury, stroke, and age-related factors, including increased reactive oxygen species production and dysfunction in mitochondria. It is widely accepted that synaptic damage and mitochondrial dysfunction are early events in disease process. The purpose of this article is to highlight molecular triggers to the disease process. This article also reviews factors, including age, gender, lifestyle, epigenetic factors, and type 2 diabetes, that are involved in late-onset AD. This article also discusses recent developments in research of mitochondrial structure, function, physiology, dynamics, biogenesis, mitophagy, and mitochondrial DNA changes in healthy and diseased states.

Neuronal Exosome-Derived Human Tau is Toxic to Recipient Mouse Neurons in vivo. - Winston, Charisse N; Aulston, Brent; Rockenstein, Edward M; Adame, Anthony; Prikhodko, Olga; Dave, Kishan N; Mishra, Priyanka; Rissman, Robert A; Yuan, Shauna H (J Alzheimers Dis, 2019)
Progressive accumulation of aggregation-prone proteins, amyloid-β (Aβ) and hyperphosphorylated tau (p-tau), are the defining hallmarks of Alzheimer's disease (AD). The mechanisms by which Aβ and p-tau are transmitted throughout the diseased brain are not yet completely understood. Interest in exosome research has grown dramatically over the past few years, specifically due to their potential role as biomarkers for staging of neurodegenerative diseases, including AD. Despite their diagnostic utility, the pathogenic potential of exosomes has yet to be fully elucidated. In this study, we use a series of recombinant tau antibodies to characterize a new model of human tau in vivo. Exosome suspensions derived from neuronally-differentiated, human induced pluripotent stem cells that express the repeat domain of tau P301L and V337M mutations (NiPSCEs) were injected into the wild-type mouse brain and pathological changes were characterized by immunostaining at one- (1 m) and two-month (2 m) post-injection. We found that tau inclusions were present throughout the brain at 2 m post-injection, which were detectable using antibodies raised against full-length tau (K9JA) and misfolded tau (MC1). Furthermore, we found that phosphorylated tau immunoreactivity was elevated 1 m post-injection, which was surprisingly normalized after 2 m. Finally, we observed extensive degeneration of neuronal dendrites in both ipsilateral and contralateral hippocampi in NiPSCE treated mice. In summary, we demonstrate that exosomes are sufficient to cause long-distance propagation of tau pathology and neurodegeneration in vivo. These novel findings support an active role of exosomes in AD pathogenesis.

The Pathology of Rapid Cognitive Decline in Clinically Diagnosed Alzheimer's Disease. - Nance, Christin; Ritter, Aaron; Miller, Justin B; Lapin, Brittany; Banks, Sarah J (J Alzheimers Dis, 2019)
BACKGROUND: Variable rate of cognitive decline among individuals with Alzheimer's disease (AD) is an important consideration for disease management, but risk factors for rapid cognitive decline (RCD) are without consensus. OBJECTIVE: To investigate demographic, clinical, and pathological differences between RCD and normal rates of cognitive decline (NCD) in AD. METHODS: Neuropsychology test and autopsy data was pulled from the National Alzheimer's Coordinating Center database from individuals with a clinical diagnosis of AD. Individuals with average decline of 3 or more points on the Mini-Mental Status Examination (MMSE) per year over 3 years were labeled RCD; all others were NCD. RESULTS: Sixty individuals identified as RCD; 230 as NCD. These neuropsychology tests differed at baseline (RCD versus NCD): WMS-LM Immediate Recall (4.35[3.39] versus 6.31[3.97], p < 0.001), Animal Naming (12.1[4.83] versus 13.9[4.83], p = 0.007), TMT Part B (187[86.1] versus 159[79.0], p = 0.02), WAIS-Digit Symbol (29.5[11.3] versus 29.5[11.3], p = 0.04), and the BNT (21.5[7.05] versus 23.6[5.09], p = 0.04). RCD had more thyroid disease (30% versus 16%, p = 0.01) and greater usage of AD medication at baseline (80% versus 62%, p = 0.01). RCD had more severe cerebral amyloid angiopathy (1.62(1.0) versus1.13(1.0), p = 0.002), more neocortical Lewy bodies (20% versus 10%, p = 0.04), and more atrophy (1.54[0.92] versus 1.17[0.83], p = 0.04). A model combining select variables was significant above chance (χ2 = 25.8, p = 0.002), but not to clinical utility (AUC < 0.70; 95% CI). CONCLUSION: Individuals with RCD have more severe pathology, more comorbidities, and lower baseline neuropsychology test scores of language and executive function.

Stem Cell-Derived Neurons as Cellular Models of Sporadic Alzheimer's Disease. - Foveau, Bénédicte; Correia, Ana Sofia; Hébert, Sébastien S; Rainone, Sara; Potvin, Olivier; Kergoat, Marie-Jeanne; Belleville, Sylvie; Duchesne, Simon; LeBlanc, Andréa C (J Alzheimers Dis, 2019)
Alzheimer's disease (AD) occurs as either an autosomal dominant inherited disease or sporadically. While familial mutant genes can be expressed in cells or in animal models to assess dysregulated functions, sporadic AD cannot be replicated in models given our lack of understanding of causality. Furthermore, the study of sporadic forms of AD is difficult given the inaccessibility of brain tissues in living individuals and the manifestation of symptoms years after the onset of disease. Here, the objective was to assess if induced pluripotent stem cell-derived neurons from well-ascertained sporadic AD individuals could represent potential cellular models to determine the underlying molecular mechanisms of disease. We used cryopreserved peripheral blood mononuclear cells from three well-ascertained sporadic AD and three non-cognitively impaired (NCI) individuals of the CIMA-Q cohort to obtain iPSC-derived neurons. Microtubule associated protein 2 was decreased in AD neurons, whereas expression of AD-associated amyloid precursor protein, tau, and amyloid-β peptide was similar in AD and NCI individuals. RNA sequencing identified several upregulated and downregulated mRNAs in AD relative to NCI neurons. Of these, complement Factor H (CFH), signal regulatory protein beta1 (SIRPB1), and insulin like growth factor binding protein 5 (IGFBP5) were previously associated with AD. In addition, several transcription factors not previously associated with AD, but involved in neuronal proliferation and differentiation were differentially expressed. The results identify novel avenues for the study of the underlying causes of sporadic AD and support the establishment of additional lines to identify mechanisms of disease in sporadic AD individuals.

Subjective Cognitive Decline May Be a Stronger Predictor of Incident Dementia in Women than in Men. - Heser, Kathrin; Kleineidam, Luca; Wiese, Birgitt; Oey, Anke; Roehr, Susanne; Pabst, Alexander; Kaduszkiewicz, Hanna; van den Bussche, Hendrik; Brettschneider, Christian; König, Hans-Helmut; Weyerer, Siegfried; Werle, Jochen; et al. (J Alzheimers Dis, 2019)
BACKGROUND/OBJECTIVE: Subjective cognitive decline (SCD) has often been associated with an increased risk for subsequent dementia. However, sex-specific associations are understudied until now. METHODS: Cross-sectional and longitudinal associations over a follow-up period of up to 13 years were investigated in a sample of participants without objective cognitive impairment at baseline (n = 2,422, mean age = 79.63 years). Logistic regression and Cox proportional hazards models were conducted. RESULTS: Women less frequently reported SCD without worries (p <  0.001), but tended to report more often SCD with worries (p = 0.082) at baseline compared to men. In models adjusted for age, education, cognitive status, and depressive symptoms, SCD at baseline increased the risk for subsequent dementia (p <  0.001), and this effect was less pronounced in males (interaction sex×SCD: p = 0.022). Stratified analyses showed that SCD increased the risk for subsequent dementia in women (HR = 1.77, p <  0.001), but not in men (HR = 1.07, p = 0.682). Similar results were found in analyses with SCD without and with worries, except that SCD with worries also predicted subsequent Alzheimer's disease (AD) in men (p = 0.037). CONCLUSION: At baseline, men reported more SCD without worries and women tended to report more SCD with worries. SCD in women was more strongly associated with subsequent dementia. SCD without and with worries was related to incident dementia and AD in women, whereas in men only SCD with worries increased the risk for AD, but not for all-cause dementia.

Telomere Shortening in the Alzheimer's Disease Neuroimaging Initiative Cohort. - Nudelman, Kelly N H; Lin, Jue; Lane, Kathleen A; Nho, Kwangsik; Kim, Sungeun; Faber, Kelley M; Risacher, Shannon L; Foroud, Tatiana M; Gao, Sujuan; Davis, Justin W; Weiner, Michael W; Saykin, Andrew J (J Alzheimers Dis, 2019)
BACKGROUND: Although shorter telomeres have been associated with Alzheimer's disease (AD), it is unclear whether longitudinal change in telomere length is associated with AD progression. OBJECTIVE: To investigate the association of telomere length change with AD diagnosis and progression. METHODS: In 653 individuals from the Alzheimer's Disease Neuroimaging Initiative (ADNI) cohort, T/S ratio (telomere versus single copy gene), a proxy of telomere length, was measured for up to five visits per participant (N = 1918 samples post-QC) using quantitative PCR (qPCR). T/S ratio was adjusted for batch effects and DNA storage time. A mixed effects model was used to evaluate association of telomere length with AD diagnostic group and interaction of age and diagnosis. Another mixed effects model was used to compare T/S ratio changes pre- to post-conversion to MCI or AD to telomere change in participants with stable diagnoses. RESULTS: Shorter telomeres were associated with older age (Effect Size (ES) = -0.23) and male sex (ES = -0.26). Neither baseline T/S ratio (ES = -0.036) nor T/S ratio change (ES = 0.046) differed significantly between AD diagnostic groups. MCI/AD converters showed greater, but non-significant, telomere shortening compared to non-converters (ES = -0.186). CONCLUSIONS: Although AD compared to controls showed small, non-significant effects for baseline T/S ratio and T/S ratio shortening, we did observe a larger, though still non-significant effect for greater telomere shortening in converters compared to non-converters. Although our results do not support telomere shortening as a robust biomarker of AD progression, further investigation in larger samples and for subgroups of participants may be informative.

Tracking Cognitive Performance in the General Population and in Patients with Mild Cognitive Impairment with a Self-Applied Computerized Test (Brain on Track). - Ruano, Luis; Severo, Milton; Sousa, Andreia; Ruano, Catarina; Branco, Mariana; Barreto, Rui; Moreira, Sandra; Araújo, Natália; Pinto, Paula; Pais, Joana; Lunet, Nuno; Cruz, Vítor Tedim (J Alzheimers Dis, 2019)
Repeated measurements could be helpful to identify patients with early cognitive decline. We compare the variation of cognitive performance over one year in patients with mild cognitive impairment (MCI) and healthy individuals using the Brain on Track self-applied computerized test (BoT). The study was initiated 30 patients with probable MCI and 377 controls from a population-based cohort, who performed the BoT test from home every three months for one year. The scores were compared using a linear mixed-effects model. All participants increased their scores in the first tests, after 120 days MCI patients started to decline, with a statistically significant higher rate. The area under the curve to detect MCI was 0.94. We identified a significant decline in cognitive performance over one year in patients with MCI using BoT and the test presented a high discriminative ability.

Two Year Outcomes, Cognitive and Behavioral Markers of Decline in Healthy, Cognitively Normal Older Persons with Global Deterioration Scale Stage 2 (Subjective Cognitive Decline with Impairment). - Reisberg, Barry; Torossian, Carol; Shulman, Melanie B; Monteiro, Isabel; Boksay, Istvan; Golomb, James; Guillo Benarous, Francoise; Ulysse, Anaztasia; Oo, Thet; Vedvyas, Alok; Rao, Julia A; Marsh, Karyn; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Little is known with respect to behavioral markers of subjective cognitive decline (SCD), a condition initially described in association with Global Deterioration Scale (GDS) stage 2. OBJECTIVE: Two-year interval behavioral markers were investigated herein. METHODS: Subjects from a published 7-year outcome study of GDS stage 2 subjects were selected. This study had demonstrated a hazard ratio of 4.5 for progression of GDS stage 2, in comparison with GDS stage 1 (no subjective or objective cognitive decline) subjects, after controlling for demographic and temporal variables. Because GDS 2 subjects have previously demonstrated impairment in comparison with healthy persons free of complaints, we herein suggest the terminology "SCD(I)" for these persons. 98 SCD(I) persons, 63 women and 35 men, mean baseline age, 67.12±8.75 years, with a mean educational background of 15.55±2.60 years, and mean baseline MMSE scores of 28.9±1.24 were followed for 2.13±0.30 years. RESULTS: Observed annual decline on the GDS was 6.701% per annum, very close to a 1986 published estimate. At follow up, the MMSE, and 7 of 8 psychometric tests did not decline significantly. Of 21 Hamilton Depression Scale items, 2 improved and the remainder were unchanged. Anxieties declined from multiple perspectives. The Brief Cognitive Rating Scale (BCRS) declined significantly (p < 0.001), with component declines in Remote memory (p < 0.01), and Functioning/self-care (p = 0.01). CONCLUSION: SCD(I) persons decline at an annual rate of approximately 6.7% /year from several recent studies. The BCRS assessments and the Digit Symbol Substitution Test can be sensitive measures for future studies of progression mitigation.

An UNC5C Allele Predicts Cognitive Decline and Hippocampal Atrophy in Clinically Normal Older Adults. - Yang, Hyun-Sik; Chhatwal, Jasmeer P; Xu, Jishu; White, Charles C; Hanseeuw, Bernard; Rabin, Jennifer S; Papp, Kathryn V; Buckley, Rachel F; Schultz, Aaron P; Properzi, Michael J; Gatchel, Jennifer R; Amariglio, Rebecca E; et al. (J Alzheimers Dis, 2019)
BACKGROUND: The UNC5C rs3846455G allele has been linked to poor cognitive resilience against age-related neuropathologies, but this association remains to be replicated, and the allele's effect on hippocampal neurodegeneration needs to be examined. OBJECTIVE: To further validate the association between rs3846455G and faster cognitive decline, especially among cognitively normal older adults, and to assess whether rs3846455G predicts accelerated hippocampal volume loss in older adults. METHODS: We assessed participants in the Harvard Aging Brain Study (HABS), a longitudinal cohort study of older adults who were clinically normal at baseline. To avoid bias from population admixture, analyses were limited to participants of European descent with longitudinal neuroimaging data (n = 174). Linear mixed effect models were used to examine the effect of rs3846455G on longitudinal change of the Preclinical Alzheimer Cognitive Composite (PACC) and MRI-measured bilateral hippocampal volume, adjusting for baseline amyloid-β (Aβ) measured by the cortical Pittsburgh Compound B PET distributed volume ratio. We also tested whether hippocampal atrophy mediates the association between rs3846455G and greater PACC decline through a mediation analysis. RESULTS: rs3846455G was associated with greater PACC decline (β= -0.087/year, 95% CI -0.169 to -0.005, p = 0.039) after controlling for baseline Aβ. Further, rs3846455G predicted accelerated hippocampal atrophy after controlling for baseline Aβ (β= -57.3 mm3/year, 95% CI -102.8 to -11.9, p = 0.014). The association between rs3846455G and greater PACC decline was partially mediated by accelerated hippocampal atrophy (mediated effect (relative scale) = -0.014, 95% CI -0.032 to -6.0×10-4, p = 0.039). CONCLUSION: UNC5C rs3846455G predicts greater cognitive decline and accelerated hippocampal atrophy in clinically normal older adults.

Vascular Burden Score Impacts Cognition Independent of Amyloid PET and MRI Measures of Alzheimer's Disease and Vascular Brain Injury. - DeCarli, Charles; Villeneuve, Sylvia; Maillard, Pauline; Harvey, Danielle; Singh, Baljeet; Carmichael, Owen; Fletcher, Evan; Olichney, John; Farias, Sarah; Jagust, William; Reed, Bruce; Mungas, Dan (J Alzheimers Dis, 2019)
BACKGROUND/OBJECTIVE: To determine the impact of vascular burden on rates of decline in episodic memory and executive function. We hypothesize that greater vascular burden will have an additive negative impact on cognition after accounting for baseline cognitive impairment, positron emission tomography (PET) amyloid burden, and magnetic resonance imaging (MRI) measures. METHODS: Individuals were followed an average of 5 years with serial cognitive assessments. Predictor variables include vascular burden score (VBS), quantitative brain MRI assessment, and amyloid imaging. Subjects consisted of 65 individuals, 53% of whom were male, aged 73.2±7.2 years on average with an average of 15.5±3.3 years of educational achievement. RESULTS: Baseline cognitive impairment was significantly associated poorer episodic memory (p < 0.0001), smaller hippocampal volume (p < 0.0001), smaller brain volume (p = 0.0026), and greater global Pittsburg Imaging Compound B (PiB) index (p = 0.0008). Greater amyloid burden was associated with greater decline in episodic memory over time (β= -0.20±0.07, p < 0.005). VBS was significantly associated with the level of executive function performance (β= -0.14±0.05, p < 0.005) and there was a significant negative interaction between VBS, cognitive impairment, and PiB index (β= -0.065±0.03, p = 0.03). CONCLUSIONS: Our results find a significant influence of VBS independent of standard MRI measures and cerebral amyloid burden on executive function. In addition, VBS reduced the amount of cerebral amyloid burden needed to result in cognitive impairment. We conclude that the systemic effects of vascular disease as reflected by the VBS independently influence cognitive ability.

Why Is Amyloid-β PET Requested After Performing Cerebrospinal Fluid Biomarkers? - Reimand, Juhan; Groot, Colin; Teunissen, Charlotte E; Windhorst, Albert D; Boellaard, Ronald; Barkhof, Frederik; Nazarenko, Sergei; van der Flier, Wiesje M; van Berckel, Bart N M; Scheltens, Philip; Ossenkoppele, Rik; Bouwman, Femke (J Alzheimers Dis, 2019)
BACKGROUND: Amyloid-β PET and cerebrospinal fluid (CSF) Aβ42 are considered interchangeable for clinical diagnosis of Alzheimer's disease. OBJECTIVE: To explore the clinical reasoning for requesting additional amyloid-β PET after performing CSF biomarkers. METHODS: We retrospectively identified 72 memory clinic patients who underwent amyloid-β PET after CSF biomarkers analysis for clinical diagnostic evaluation between 2011 and 2019. We performed patient chart reviews to identify factors which led to additional amyloid-β PET. Additionally, we assessed accordance with appropriate-use-criteria (AUC) for amyloid-β PET. RESULTS: Mean patient age was 62.0 (SD = 8.1) and mean Mini-Mental State Exam score was 23.6 (SD = 3.8). CSF analysis conflicting with the clinical diagnosis was the most frequent reason for requesting an amyloid-β PET scan (n = 53, 74%), followed by incongruent MRI (n = 16, 22%), unusual clinical presentation (n = 11, 15%) and young age (n = 8, 11%). An amyloid-β PET scan was rarely (n = 5, 7%) requested in patients with a CSF Aβ+/tau+ status. Fifteen (47%) patients with a post-PET diagnosis of AD had a predominantly non-amnestic presentation. In n = 11 (15%) cases, the reason that the clinician requested amyloid-β was not covered by AUC. This happened most often (n = 7) when previous CSF analysis did not support current clinical diagnosis, which led to requesting amyloid-β PET. CONCLUSION: In this single-center study, the main reason for requesting an amyloid-β PET scan after performing CSF biomarkers was the occurrence of a mismatch between the primary clinical diagnosis and CSF Aβ/tau results.

ABC Transporters Are Key Players in Alzheimer's Disease. - Pereira, Cátia D; Martins, Filipa; Wiltfang, Jens; da Cruz E Silva, Odete A B; Rebelo, Sandra (J Alzheimers Dis, 2018)
Human ATP-binding cassette (ABC) transporters mediate a critical function in the cell, namely the transport of molecules across lipid membranes. Associated to their ubiquitous tissue distribution, they are key players in cellular homeostasis but also potential causative or contributing factors for many pathologies, including Alzheimer's disease (AD). In the central nervous system (CNS), numerous ABC transporters are present throughout the brain parenchyma and especially at the blood-brain barrier (BBB). AD is a neurodegenerative disorder mainly characterized by extracellular deposition of amyloid-β (Aβ) peptides and intracellular accumulation of hyperphosphorylated forms of tau protein. Besides being degraded via proteolytic and phagocytic processes mediated by brain parenchymal cells, a major mechanism for eliminating cerebral Aβ is through its transport across the BBB into the peripheral blood. In fact, many AD cases are associated with impaired Aβ clearance. Consistently, several studies have recently uncovered important roles for ABC transporters in AD pathophysiology. Hence, this review focuses on the relevance of ABC transporters in CNS homeostasis by highlighting AD as a strong example of the deleterious consequences that might result from the former's altered expression and/or activity in the brain. The potentiality of human ABC transporters as novel pharmacological targets for both the diagnosis and therapeutics of AD is emphasized.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; ATP-Binding Cassette Transporters; Blood-Brain Barrier; Humans

Abnormalities of Resting State Cortical EEG Rhythms in Subjects with Mild Cognitive Impairment Due to Alzheimer's and Lewy Body Diseases. - Babiloni, Claudio; Del Percio, Claudio; Lizio, Roberta; Noce, Giuseppe; Lopez, Susanna; Soricelli, Andrea; Ferri, Raffaele; Pascarelli, Maria Teresa; Catania, Valentina; Nobili, Flavio; Arnaldi, Dario; Famá, Francesco; et al. (J Alzheimers Dis, 2018)
The present study tested the hypothesis that cortical sources of resting state eyes-closed electroencephalographic (rsEEG) rhythms reveal different abnormalities in cortical neural synchronization in groups of patients with mild cognitive impairment due to Alzheimer's disease (ADMCI) and dementia with Lewy bodies (DLBMCI) as compared to cognitively normal elderly (Nold) subjects. Clinical and rsEEG data in 30 ADMCI, 23 DLBMCI, and 30 Nold subjects were available in an international archive. Age, gender, and education were carefully matched in the three groups. The Mini-Mental State Evaluation (MMSE) score was matched between the ADMCI and DLBMCI groups. Individual alpha frequency peak (IAF) was used to determine the delta, theta, alpha1, alpha2, and alpha3 frequency band ranges. Fixed beta1, beta2, and gamma bands were also considered. eLORETA estimated the rsEEG cortical sources. Receiver operating characteristic curve (ROCC) classified these sources across individuals. Compared to Nold, IAF showed marked slowing in DLBMCI and moderate in ADMCI. Furthermore, the posterior alpha 2 and alpha 3 source activities were more abnormal in the ADMCI than the DLBMCI group, while widespread delta source activities were more abnormal in the DLBMCI than the ADMCI group. The posterior delta and alpha sources correlated with the MMSE score and correctly classified the Nold and MCI individuals (area under the ROCC >0.85). In conclusion, the ADMCI and DLBMCI patients showed different features of cortical neural synchronization at delta and alpha frequencies underpinning brain arousal and vigilance in the quiet wakefulness. Future prospective cross-validation studies will have to test the clinical validity of these rsEEG markers.

Acute Stroke Care in Dementia: A Cohort Study from the Swedish Dementia and Stroke Registries. - Zupanic, Eva; Kåreholt, Ingemar; Norrving, Bo; Secnik, Juraj; von Euler, Mia; Winblad, Bengt; Religa, Dorota; Kramberger, Milica Gregoric; Johnell, Kristina; Eriksdotter, Maria; Garcia-Ptacek, Sara (J Alzheimers Dis, 2018)
BACKGROUND: Previous studies have shown that patients with dementia receive less testing and treatment for stroke. OBJECTIVES: Our aim was to investigate hospital management of acute ischemic stroke in patients with and without dementia. METHODS: Retrospective analysis of prospectively collected data 2010-2014 from the Swedish national dementia registry (SveDem) and the Swedish national stroke registry (Riksstroke). Patients with dementia who suffered an acute ischemic stroke (AIS) (n = 1,356) were compared with matched non-dementia AIS patients (n = 6,755). Outcomes included length of stay in a stroke unit, total length of hospitalization, and utilization of diagnostic tests and assessments. RESULTS: The median age at stroke onset was 83 years. While patients with dementia were equally likely to be directly admitted to a stroke unit as their non-dementia counterparts, their stroke unit and total hospitalization length were shorter (10.5 versus 11.2 days and 11.6 versus 13.5, respectively, p < 0.001). Dementia patients were less likely to receive carotid ultrasound (OR 0.36, 95% CI [0.30-0.42]) or undergo assessments by the interdisciplinary team members (physiotherapists, speech therapists, occupational therapists; p < 0.05 for all adjusted models). However, a similar proportion of patients received CT imaging (97.4% versus 98.6%, p = 0.001) and a swallowing assessment (90.7% versus 91.8%, p = 0.218). CONCLUSIONS: Patients with dementia who suffer an ischemic stroke have equal access to direct stroke unit care compared to non-dementia patients; however, on average, their stay in a stroke unit and total hospitalization are shorter. Dementia patients are also less likely to receive specific diagnostic tests and assessments by the interdisciplinary stroke team.

Advanced Circadian Timing and Sleep Fragmentation Differentially Impact on Memory Complaint Subtype in Subjective Cognitive Decline. - Manousakis, Jessica E; Scovelle, Anna J; Rajaratnam, Shantha M W; Naismith, Sharon L; Anderson, Clare (J Alzheimers Dis, 2018)
BACKGROUND: Increased sleep fragmentation and advanced circadian timing are hallmark phenotypes associated with increased age-related cognitive decline. Subjective cognitive decline (SCD) is considered a prodromal stage of neurodegeneration and dementia; however, little is known about how sleep and circadian timing impact on memory complaints in SCD. OBJECTIVE: To determine how sleep and circadian timing impact on memory complaint subtypes in older adults with SCD. METHODS: Twenty-five older adults with SCD (mean age = 69.97, SD = 5.33) completed the Memory Functioning Questionnaire to characterize their memory complaints. They also underwent neuropsychological assessment, and completed 1 week of at-home monitoring of sleep with actigraphy and sleep diaries. This was followed by a two-night laboratory visit with overnight polysomnography and a dim light melatonin onset assessment to measure circadian timing. RESULTS: Advanced circadian timing was associated with greater memory complaints, specifically poorer memory of past events (r = -0.688, p = 0.002), greater perceived decline over time (r = -0.568, p = 0.022), and increased reliance on mnemonic tools (r = -0.657, p = 0.004). Increased sleep fragmentation was associated with reduced self-reported memory decline (r = 0.529, p = 0.014), and reduced concern about everyday forgetfulness (r = 0.435, p = 0.038). CONCLUSION: Advanced circadian timing was associated with a number of subjective memory complaints and symptoms. By contrast, sleep fragmentation was linked to lowered perceptions of cognitive decline, and less concern about memory failures. As circadian disruption is apparent in both MCI and Alzheimer's disease, and plays a key role in cognitive function, our findings further support a circadian intervention as a potential therapeutic tool for cognitive decline.

Age-Dependent Decrease of Mitochondrial Complex II Activity in a Familial Mouse Model for Alzheimer's Disease. - Emmerzaal, Tim L; Rodenburg, Richard J; Tanila, Heikki; Verweij, Vivienne; Kiliaan, Amanda J; Kozicz, Tamas (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a severe neurodegenerative disorder for which the exact etiology is largely unknown. An increasingly recognized and investigated notion is the pathogenic role of mitochondrial dysfunction in AD. We assessed mitochondrial oxidative-phosphorylation (OXPHOS) enzyme activities in the APPswe/PS1ΔE9 mouse model from 4.5 to 14 months of age. We show an age-dependent decrease in mitochondrial complex-II activity starting at 9 months in APP/PS1 mice. Other enzymes of the OXPHOS do not show any alterations. Since amyloid-β (Aβ) plaques are already present from 4 months of age, mitochondrial dysfunction likely occurs downstream of Aβ pathology in this mouse model.

Albuminuria and Microalbuminuria as Predictors of Cognitive Performance in a General Population: An 11-Year Follow-Up Study. - Ekblad, Laura L; Toppala, Sini; Johansson, Jouni K; Koskinen, Seppo; Sundvall, Jouko; Rinne, Juha O; Puukka, Pauli; Viitanen, Matti; Jula, Antti (J Alzheimers Dis, 2018)
Microalbuminuria, defined as urine albumin-to-creatinine ratio (UACR)>3.0 mg/mmol and ≤ 30 mg/mmol, is an early marker of endothelial damage of the renal glomeruli. Recent research suggests an association among microalbuminuria, albuminuria (UACR > 3.0 mg/mmol), and cognitive impairment. Previous studies on microalbuminuria, albuminuria, and cognition in the middle-aged have not provided repeated cognitive testing at different time-points. We hypothesized that albuminuria (micro- plus macroalbuminuria) and microalbuminuria would predict cognitive decline independently of previously reported risk factors for cognitive decline, including cardiovascular risk factors. In addition, we hypothesized that UACR levels even below the cut-off for microalbuminuria might be associated with cognitive functioning. These hypotheses were tested in the Finnish nationwide, population-based Health 2000 Survey (n = 5,921, mean age 52.6, 55.0% women), and its follow-up, Health 2011 (n = 3,687, mean age at baseline 49.3, 55.6% women). Linear regression analysis was used to determine the associations between measures of albuminuria and cognitive performance. Cognitive functions were assessed with verbal fluency, word-list learning, word-list delayed recall (at baseline and at follow-up), and with simple and visual choice reaction time tests (at baseline only). Here, we show that micro- plus macroalbuminuria associated with poorer word-list learning and a slower reaction time at baseline, with poorer word-list learning at follow-up, and with a steeper decline in word-list learning during 11 years after multivariate adjustments. Also, higher continuous UACR consistently associated with poorer verbal fluency at levels below microalbuminuria. These results suggest that UACR might have value in evaluating the risk for cognitive decline.
Keywords: Adult; Aged; Albuminuria; Cognition; Cognitive Dysfunction; Creatinine; Cross-Sectional Studies; Female; Finland; Follow-Up Studies; Humans; Kidney; Linear Models; Male; Middle Aged; Multivariate Analysis; Neuropsychological Tests; Risk Factors

Allocentric and Egocentric Spatial Processing in Middle-Aged Adults at High Risk of Late-Onset Alzheimer's Disease: The PREVENT Dementia Study. - Ritchie, Karen; Carrière, Isabelle; Howett, David; Su, Li; Hornberger, Michael; O'Brien, John T; Ritchie, Craig W; Chan, Dennis (J Alzheimers Dis, 2018)
Impairments in spatial processing due to hippocampal degeneration have been observed in the years immediately preceding the diagnosis of Alzheimer's disease (AD) dementia. The demonstration of changes in spatial processing in preceding decades would provide a cognitive marker for pre-clinical AD and an outcome measure for early intervention trials. The present study examined allocentric and egocentric spatial processing in relation to future dementia risk in a middle-aged cohort. The CAIDE Dementia Risk Score (DRS) was calculated for 188 persons aged 40 to 59, of whom 94 had a parent with dementia. Participants underwent the Four Mountains Test (4MT) of allocentric spatial processing, the Virtual Reality Supermarket Trolley Task (VRSTT) of egocentric spatial processing, and 3T MRI scans. A significant negative association was found between the DRS and 4MT (Spearman correlation - 0.26, p = 0.0006), but not with the VRSTT. The 4MT was also found to be a better predictor of risk than tests of episodic memory, verbal fluency, or executive functioning. The results suggest that allocentric rather than egocentric processing may be a potential indicator of risk for late-onset AD, consistent with the hypothesis that the earliest cognitive changes in AD are driven by tau-related degeneration in the medial temporal lobe rather than amyloid-only deposition in the medial parietal lobe.

Alterations of Effective Connectivity Patterns in Mild Cognitive Impairment: An MEG Study. - Gómez, Carlos; Juan-Cruz, Celia; Poza, Jesús; Ruiz-Gómez, Saúl J; Gomez-Pilar, Javier; Núñez, Pablo; García, María; Fernández, Alberto; Hornero, Roberto (J Alzheimers Dis, 2018)
Neuroimaging techniques have demonstrated over the years their ability to characterize the brain abnormalities associated with different neurodegenerative diseases. Among all these techniques, magnetoencephalography (MEG) stands out by its high temporal resolution and noninvasiveness. The aim of the present study is to explore the coupling patterns of resting-state MEG activity in subjects with mild cognitive impairment (MCI). To achieve this goal, five minutes of spontaneous MEG activity were acquired with a 148-channel whole-head magnetometer from 18 MCI patients and 26 healthy controls. Inter-channel relationships were investigated by means of two complementary coupling measures: coherence and Granger causality. Coherence is a classical method of functional connectivity, while Granger causality quantifies effective (or causal) connectivity. Both measures were calculated in the five conventional frequency bands: delta (δ, 1-4 Hz), theta (θ, 4-8 Hz), alpha (α, 8-13 Hz), beta (β, 13-30 Hz), and gamma (γ, 30-45 Hz). Our results showed that connectivity values were lower for MCI patients than for controls in all frequency bands. However, only Granger causality revealed statistically significant differences between groups (p-values < 0.05, FDR corrected Mann-Whitney U-test), mainly in the beta band. Our results support the role of MCI as a disconnection syndrome, which elicits early alterations in effective connectivity patterns. These findings can be helpful to identify the neural substrates involved in prodromal stages of dementia.

Altered microRNA, mRNA, and Protein Expression of Neurodegeneration-Related Biomarkers and Their Transcriptional and Epigenetic Modifiers in a Human Tau Transgenic Mouse Model in Response to Developmental Lead Exposure. - Masoud, Anwar M; Bihaqi, Syed W; Alansi, Bothaina; Dash, Miriam; Subaiea, Gehad M; Renehan, William E; Zawia, Nasser H (J Alzheimers Dis, 2018)
Amyloid deposits originating from the amyloid-β protein precursor (AβPP) and aggregates of the microtubule associated protein tau (MAPT) are the hallmarks of Alzheimer's disease (AD). Animal studies have demonstrated a link between early life exposure to lead (Pb) and latent overexpression of the AβPP and MAPT genes and their products via epigenetic reprogramming. The present study monitored APP gene and epigenetic mediators and transcription factors known to regulate it. Western blot analysis and quantitative polymerase chain reaction (qPCR) were used to study the mRNA, miRNA, and proteins levels of AβPP, specificity protein 1 (SP1; a transcriptional regulator of amyloid and tau pathway), and epigenetic intermediates namely: DNA methyltransferase (DNMT) 1, DNMT3a and Methyl- CpG protein binding 2 (MeCP2) in the cerebral cortex of transgenic mice (Knock-in for human MAPT). These transgenic mice were developmentally exposed to Pb and the impact on mRNA, miRNA, and protein levels was scrutinized on postnatal days (PND) 20 and 50. The data revealed a consistent inverse relationship between miRNA and protein levels for SP1 and AβPP both in the basal and exposed conditions, which may influence the levels of their corresponding proteins. On the other hand, the relationship between miRNA and protein levels was not correlative for DNMT1 and DNMT3a. MeCP2 miRNA protein levels corresponded only following environmental exposure. These results suggest that developmental exposure to Pb and subsequent AβPP protein levels may be controlled through transcriptional regulators and epigenetic mechanisms that mainly involve miRNA regulation.

Alzheimer's Amyloid-β is an Antimicrobial Peptide: A Review of the Evidence. - Gosztyla, Maya L; Brothers, Holly M; Robinson, Stephen R (J Alzheimers Dis, 2018)
The amyloid-β (Aβ) peptide has long been considered to be the driving force behind Alzheimer's disease (AD). However, clinical trials that have successfully reduced Aβ burden in the brain have not slowed the cognitive decline, and in some instances, have resulted in adverse outcomes. While these results can be interpreted in different ways, a more nuanced picture of Aβ is emerging that takes into account the facts that the peptide is evolutionarily conserved and is present throughout life in cognitively normal individuals. Recent evidence indicates a role for Aβ as an antimicrobial peptide (AMP), a class of innate immune defense molecule that utilizes fibrillation to protect the host from a wide range of infectious agents. In humans and in animal models, infection of the brain frequently leads to increased amyloidogenic processing of the amyloid-β protein precursor (AβPP) and resultant fibrillary aggregates of Aβ. Evidence from in vitro and in vivo studies demonstrates that Aβ oligomers have potent, broad-spectrum antimicrobial properties by forming fibrils that entrap pathogens and disrupt cell membranes. Importantly, overexpression of Aβ confers increased resistance to infection from both bacteria and viruses. The antimicrobial role of Aβ may explain why increased rates of infection have been observed in some of the AD clinical trials that depleted Aβ. Perhaps progress toward a cure for AD will accelerate once treatment strategies begin to take into account the likely physiological functions of this enigmatic peptide.

Alzheimer's Disease: A Journey from Amyloid Peptides and Oxidative Stress, to Biomarker Technologies and Disease Prevention Strategies-Gains from AIBL and DIAN Cohort Studies. - Martins, Ralph N; Villemagne, Victor; Sohrabi, Hamid R; Chatterjee, Pratishtha; Shah, Tejal M; Verdile, Giuseppe; Fraser, Paul; Taddei, Kevin; Gupta, Veer B; Rainey-Smith, Stephanie R; Hone, Eugene; Pedrini, Steve; et al. (J Alzheimers Dis, 2018)
Worldwide there are over 46 million people living with dementia, and this number is expected to double every 20 years reaching about 131 million by 2050. The cost to the community and government health systems, as well as the stress on families and carers is incalculable. Over three decades of research into this disease have been undertaken by several research groups in Australia, including work by our original research group in Western Australia which was involved in the discovery and sequencing of the amyloid-β peptide (also known as Aβ or A4 peptide) extracted from cerebral amyloid plaques. This review discusses the journey from the discovery of the Aβ peptide in Alzheimer's disease (AD) brain to the establishment of pre-clinical AD using PET amyloid tracers, a method now serving as the gold standard for developing peripheral diagnostic approaches in the blood and the eye. The latter developments for early diagnosis have been largely achieved through the establishment of the Australian Imaging Biomarker and Lifestyle research group that has followed 1,100 Australians for 11 years. AIBL has also been instrumental in providing insight into the role of the major genetic risk factor apolipoprotein E ɛ4, as well as better understanding the role of lifestyle factors particularly diet, physical activity and sleep to cognitive decline and the accumulation of cerebral Aβ.

Alzheimer's Disease Biomarkers Have Distinct Associations with Specific Hippocampal Subfield Volumes. - Müller-Ehrenberg, Lisa; Riphagen, Joost M; Verhey, Frans R J; Sack, Alexander T; Jacobs, Heidi I L (J Alzheimers Dis, 2018)
Measures of amyloid-β (Aβ) and phosphorylated tau (p-tau) concentrations in cerebrospinal fluid are extensively used for diagnostic and research purposes in Alzheimer's disease (AD) as correlates of cortical thinning and cognitive outcomes. The present study investigated the relationship of Aβ and p-tau with hippocampal subfield volumes Cornu Ammonis (CA) 1-4, dentate gyrus (DG), and subiculum. Subfields were segmented from T1-weighted images from the ADNI-population using FreeSurfer v6. Linear and polynomial regression models revealed distinct associations of Aβ and p-tau with subfield volumes. Aβ had a quadratic relationship with all hippocampal subfield volumes and the inflection point was higher than the validated cut-off for Aβ. For p-tau the relationships were linear, except for CA3, in which it was quadratic. For the CA1 and CA3, these quadratic relationships with Aβ were only observed when p-tau was low. Amyloid and p-tau contributed equally to the explained variance in CA4 and DG volume. Subicular volume was best explained by Aβ alone. These biomarker relationships with hippocampal subfield volumes seem to mirror the hippocampal-specific topography of Aβ and tau reported in neuropathological staging models. In addition, using continuous values of Aβ reveals positive patterns with imaging markers for individuals around the positivity threshold that would be masked when using dichotomized biomarker groups, which can be important for early detection and accurate inclusion of potential participants at risk for AD in clinical trials.

Alzheimer's Disease Computer-Aided Diagnosis: Histogram-Based Analysis of Regional MRI Volumes for Feature Selection and Classification. - Ruiz, Elena; Ramírez, Javier; Górriz, Juan Manuel; Casillas, Jorge (J Alzheimers Dis, 2018)
This paper proposes a novel fully automatic computer-aided diagnosis (CAD) system for the early detection of Alzheimer's disease (AD) based on supervised machine learning methods. The novelty of the approach, which is based on histogram analysis, is twofold: 1) a feature extraction process that aims to detect differences in brain regions of interest (ROIs) relevant for the recognition of subjects with AD and 2) an original greedy algorithm that predicts the severity of the effects of AD on these regions. This algorithm takes account of the progressive nature of AD that affects the brain structure with different levels of severity, i.e., the loss of gray matter in AD is found first in memory-related areas of the brain such as the hippocampus. Moreover, the proposed feature extraction process generates a reduced set of attributes which allows the use of general-purpose classification machine learning algorithms. In particular, the proposed feature extraction approach assesses the ROI image separability between classes in order to identify the ones with greater discriminant power. These regions will have the highest influence in the classification decision at the final stage. Several experiments were carried out on segmented magnetic resonance images from the Alzheimer's Disease Neuroimaging Initiative (ADNI) in order to show the benefits of the overall method. The proposed CAD system achieved competitive classification results in a highly efficient and straightforward way.

Alzheimer's Disease Progression: Factors Influencing Cognitive Decline. - Ferrari, Camilla; Lombardi, Gemma; Polito, Cristina; Lucidi, Giulia; Bagnoli, Silvia; Piaceri, Irene; Nacmias, Benedetta; Berti, Valentina; Rizzuto, Debora; Fratiglioni, Laura; Sorbi, Sandro (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) patients present high variability in the rate of cognitive decline. Despite the wide knowledge on factors influencing dementia risk, little is known on what accounts for AD progression. Previous studies on this topic have mainly analyzed each factor separately without taking into account the interaction between genetic and non-genetic factors. OBJECTIVE: The aim of the present study is to evaluate the role of demographic, clinical, therapeutic, and genetic factors and their interaction on cognitive decline among newly diagnosed AD patients. METHODS: We retrospectively selected 160 AD patients diagnosed at the Neurology Unit of Careggi University Hospital of Florence. We evaluated the occurrence of rapid cognitive changes defined as the worsening of more than four points at the Mini-Mental State Examination after 2-year follow up period. RESULTS: Among the 160 AD patients, 50% presented rapid disease progression. Extrapyramidal signs at disease onset were predictors of worse outcome (OR 2.2), especially among Apolipoprotein E (APOE) ɛ4 allele carriers, while the presence of family history for dementia decreased the risk of rapid progression by about 50%. Higher educated ɛ4-carriers showed a slower AD progression. We identified the chronic use of aspirin as potential secondary preventative strategy for the non ɛ4-carriers. CONCLUSION: At dementia onset, some clinical and demographic data can be predictors of future progression. The outcomes of the present study support the already hypothesized interaction between genetic and non-genetic factors during disease course and suggest genetic-based approaches.
Keywords: Aged; Aged, 80 and over; Alleles; Alzheimer Disease; Apolipoprotein E4; Aspirin; Cognitive Dysfunction; Disease Progression; Female; Heterozygote; Humans; Italy; Male; Middle Aged; Neuropsychological Tests; Retrospective Studies; Secondary Prevention

Alzheimer's Disease, Visual Search, and Instrumental Activities of Daily Living: A Review and a New Perspective on Attention and Eye Movements. - Ramzaoui, Hanane; Faure, Sylvane; Spotorno, Sara (J Alzheimers Dis, 2018)
Many instrumental activities of daily living (IADLs), like cooking and managing finances and medications, involve finding efficiently and in a timely manner one or several objects within complex environments. They may thus be disrupted by visual search deficits. These deficits, present in Alzheimer's disease (AD) from its early stages, arise from impairments in multiple attentional and memory mechanisms. A growing body of research on visual search in AD has examined several factors underlying search impairments in simple arrays. Little is known about how AD patients search in real-world scenes and in real settings, and about how such impairments affect patients' functional autonomy. Here, we review studies on visuospatial attention and visual search in AD. We then consider why analysis of patients' oculomotor behavior is promising to improve understanding of the specific search deficits in AD, and of their role in impairing IADL performance. We also highlight why paradigms developed in research on real-world scenes and real settings in healthy individuals are valuable to investigate visual search in AD. Finally, we indicate future research directions that may offer new insights to improve visual search abilities and autonomy in AD patients.

Antemortem-Postmortem Correlation of Florbetapir (18F) PET Amyloid Imaging with Quantitative Biochemical Measures of Aβ42 but not Aβ40. - Beach, Thomas G; Maarouf, Chera L; Intorcia, Anthony; Sue, Lucia I; Serrano, Geidy E; Lu, Ming; Joshi, Abhinay; Pontecorvo, Michael J; Roher, Alex E (J Alzheimers Dis, 2018)
Amyloid imaging demonstrates the in vivo presence of amyloid-β (Aβ) deposits in the aging human brain but it is still unknown which structural forms and modifications of Aβ are detected. In Alzheimer's disease, most amyloid deposits are predominantly composed of Aβ ending at amino acid residues Val40 or Ala42. It has been reported that Aβ40 is largely restricted to neuritic plaques while Aβ42 may be deposited in amyloid plaques of all types, and is often the sole component of diffuse plaques. The distinction is important as it is mainly the neuritic plaques that correlate with cognitive impairment while diffuse plaques may be the initial type of Aβ deposited. Whether PET amyloid ligands such as florbetapir-18F (Amyvid) are partially or wholly selective for brain deposits of Aβ40 or Aβ42 is currently unknown. We compared antemortem florbetapir PET cortical/cerebellar signal intensity (SUVr) of 55 subjects with postmortem biochemical (ELISA) measurements employing specific antibodies against Aβ40 and Aβ42. Spearman's univariable correlations were significant for both Aβ40 and Aβ42, but were much stronger for Aβ42. Multiple linear regression showed significance only for Aβ42. These results suggest that florbetapir binds only weakly, if at all, to Aβ40. This may be in part due to the higher likelihood for Aβ42 to be present in a β-pleated sheet tertiary structure, or to differences between Aβ40 and Aβ42 in β-pleated sheet tertiary or quaternary structure.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Amyloidosis; Aniline Compounds; Autopsy; Brain; Ethylene Glycols; Humans; Linear Models; Peptide Fragments; Plaque, Amyloid; Positron-Emission Tomography

Antibodies to Multiple Receptors are Associated with Neuropsychiatric Symptoms and Mortality in Alzheimer's Disease: A Longitudinal Study. - Giil, Lasse M; Aarsland, Dag; Hellton, Kristoffer; Lund, Anders; Heidecke, Harald; Schulze-Forster, Kai; Riemekasten, Gabriela; Vik-Mo, Audun Osland; Kristoffersen, Einar K; Vedeler, Christian A; Nordrehaug, Jan Erik (J Alzheimers Dis, 2018)
BACKGROUND: Endogenous antibodies to signaling molecules and receptors (Abs) are associated with Alzheimer's disease (AD). OBJECTIVES: To investigate the association of 33 Abs to dopaminergic, serotoninergic, muscarinic, adrenergic, vascular, and immune receptors with cognitive, neuropsychiatric, and mortality outcomes. METHODS: Ninety-one patients with mild AD were followed annually for 5 years with the Mini-Mental State Examination (MMSE) and the Neuropsychiatric Inventory (NPI; composite outcomes: "psychosis" (item 1 + 2), "mood" (item 4 + 5 + 7), and "agitation" (item 3 + 8 + 9)). Abs were quantified in sera obtained at baseline by ELISA and reduced to principal components (PCs). Associations between Abs and outcomes were assessed by a mixed model (MMSE decline), zero-inflated fixed effects count models (composite NPI scores), and Cox regression (mortality). The resulting p-values were adjusted for multiple testing according to a false discovery rate of 0.05 (Benjamini-Hochberg). RESULTS: The measured levels of the 33 Abs formed four PCs. PC1 (dopaminergic and serotonergic Abs) was associated with increased mortality (Hazard ratio 2.57, p < 0.001), PC2 (serotonergic, immune, and vascular Abs) with decreased agitation symptoms (β - 0.19, p < 0.001), and PC3 (cholinergic receptor Abs) with increased mood symptoms (β 0.04, p = 0.002), over time. There were no associations between Abs and MMSE decline. CONCLUSION: The associations between Abs, mortality, and neuropsychiatric symptoms reported in this cohort are intriguing. They cannot, however, be generalized. Validation in independent sample sets is required.

Apparent Cognitive Decline as Revealed by an Executive Function Test within a Cohort of Elderly Individuals Self-Reporting Normal Cognitive Performance. - Shea, Thomas B; Remington, Ruth (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) can be preceded by subtle memory decline that can last a decade or more before progressing to what would be diagnosed as the mild cognitive impairment stage. During this early stage of decline, individuals and even their caregivers can fail to perceive any serious difficulty or need to consult a physician. Herein, we present evidence in support of these concerns, and demonstrate how this can interfere not only with clinical trials of AD but also those involving cognitive performance of elderly individuals without intentional reference to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Cognitive Dysfunction; Cohort Studies; Executive Function; Female; Humans; Male; Memory; Neuropsychological Tests; Self Report

Argyrophilic Grain Pathology in Frontotemporal Lobar Degeneration: Demographic, Clinical, Neuropathological, and Genetic Features. - Gil, María José; Manzano, María Sagrario; Cuadrado, María Luz; Fernández, Cristina; Góméz, Elena; Matesanz, Carmen; Calero, Miguel; Rábano, Alberto (J Alzheimers Dis, 2018)
Frontotemporal lobar degeneration (FTLD) is a clinically, pathologically, and genetically heterogeneous group of disorders that affect the frontal and temporal lobes of the brain. FTLD classification distinguishes three main neuropathological groups: FTLD-tau, FTLD-TDP, and FTLD-FUS. As a four-repeat tauopathy, argyrophilic grain disease (AGD) is included in the FTLD-tau group. AGD may also appear in association with other neuropathological disorders. We describe the demographic, clinical, neuropathological, and genetic characteristics of a series of FTLD cases presenting with AGD. For this purpose, a clinico-pathological study of 71 autopsy-confirmed FTLD cases from different tissue banks was performed. AGD was found in 52.1% of FTLD cases. The presence of AGD increased with the increasing age (up to 88.9% in cases older than 80 years; p < 0.001) and was associated with higher ages at onset (p < 0.001) and death (p < 0.001). In AGD cases, progressive supranuclear palsy (PSP) was the most frequent clinical diagnosis (29.7%) and gait disturbance was the most common symptom (64.5%); behavioral and language symptoms were less frequent as compared with non-AGD cases (p = 0.055; p = 0.012). PSP was the most frequent neuropathological diagnosis among cases with AGD (32.4%). This group also showed less brain atrophy (p = 0.094) and higher prevalence of Alzheimer (p = 0.002) and vascular pathology (p = 0.047) as compared to the non-AGD group. We also observed that H1/H1 genotype was overrepresented in AGD cases (p = 0.018) and that there was no association with any specific APOE allele. A subanalysis of PSP cases according to the AGD status was carried out, yielding no significant differences.

Assessing Mild Cognitive Impairment Progression using a Spherical Brain Mapping of Magnetic Resonance Imaging. - Martinez-Murcia, Francisco Jesus; Górriz, Juan Manuel; Ramírez, Javier; Segovia, Fermín; Salas-Gonzalez, Diego; Castillo-Barnes, Diego; Ortiz, Andrés (J Alzheimers Dis, 2018)
BACKGROUND: The early diagnosis of Alzheimer's Disease (AD), particularly in its prodromal stage, mild cognitive impairment (MCI), still remains a challenge. Many computational tools have been developed to successfully explore and predict the disease progression. In this context, the Spherical Brain Mapping (SBM) proved its ability in detecting differences between AD and aged subjects without symptoms of dementia. Being a very visual tool, its application in predicting MCI conversion to AD could be of great help to understand neurodegeneration and the disease progression. OBJECTIVE: In this work, we aim at predicting the conversion of MCI affected subjects to AD more than 6 months in advance of their conversion session and understanding the progression of the disease by predicting neuropsychological test outcomes from MRI data. METHODS: In order to do so, SBM is applied to a series of MRI scans from the Alzheimer's Disease Neuroimaging Initiative (ADNI). The resulting spherical brain maps show statistical and morphological information of the brain in a bidimensional plane, performing at the same time a significant feature reduction that provides a feature vector used in classification analysis. RESULTS: The study achieves up to 92.3% accuracy in the AD versus normal controls (CTL) detection, and up to a 77.6% in detection a of MCI conversions when trained with AD and CTL subjects. The prediction of neuropsychological test outcomes achieved R2 rates up to more than 0.5. Significant regions according to t-test and correlation analysis match reported brain areas in the literature. CONCLUSION: The results prove that Spherical Brain Mapping offers good ability to predict conversion patterns and cognitive state, at the same time that provides an additional aid for visualizing a two-dimensional abstraction map of the brain.

The Association Between Frontotemporal Lobar Degeneration and Bullous Pemphigoid. - Katisko, Kasper; Kokkonen, Nina; Krüger, Johanna; Hartikainen, Päivi; Koivisto, Anne M; Helisalmi, Seppo; Korhonen, Ville E; Kokki, Merja; Tuusa, Jussi; Herukka, Sanna-Kaisa; Solje, Eino; Haapasalo, Annakaisa; et al. (J Alzheimers Dis, 2018)
Recent studies have shown an epidemiological and immunological association between bullous pemphigoid (BP) and several neurological or psychiatric diseases. Here, our aim was for the first time to specify whether an association exists between BP and frontotemporal lobar degeneration (FTLD). Medical histories of FTLD patients (N = 196) were screened for clinical comorbidity, and BP180 and BP230 autoantibodies were analyzed in the sera of FTLD patients (N = 70, including 24 C9orf72 repeat expansion carriers) by BP180-NC16A-ELISA and BP230-ELISA. One FTLD patient (C9orf72 repeat expansion carrier) had a comorbid diagnosis of BP. Increased levels of serum BP180 autoantibodies (cutoff value >9 U/ml) were detected more often in FTLD patients (10.0%) than in controls (4.9%). Moreover, elevated levels of both BP180 and BP230 autoantibodies were found more often in C9orf72 repeat expansion-carrying FTLD than non-carrying patients or controls. However, none of these differences reached a statistical significance likely due to our limited cohort size. In conclusion, our findings suggest that subset of FTLD patients especially with the C9orf72 repeat expansion may have an immunological association with BP.

Association between Peripheral Leptin and Adiponectin Levels and Cognitive Decline in Patients with Neurocognitive Disorders ≥65 Years. - Gilbert, Thomas; Roche, Sylvain; Blond, Emilie; Bar, Jean-Yves; Drai, Jocelyne; Cuerq, Charlotte; Haution-Bitker, Marine; Ecochard, René; Bonnefoy, Marc (J Alzheimers Dis, 2018)
BACKGROUND: There is evidence that adipokines have roles in brain functioning and cognitive decline. OBJECTIVE: Assess the role of leptin and adiponectin levels in predicting changes in neuro-cognitive disorders (NCD). METHODS: The study included 205 patients over 65 years of age presenting for a one-day hospitalization for current assessment of cognitive function. Peripheral blood leptin and adiponectin levels were measured at admission. Demographic variables, body mass index (BMI), and history of hypertension were also recorded. Cognitive function was assessed by the Mini-Mental State Examination (MMSE) at admission and at later scheduled visits over a median follow-up period of 14.5 months. Conventional univariate comparisons were made between diagnosis groups (Alzheimer's disease (AD), mild NCD, vascular/mixed dementia). Changes in MMSE scores over time were examined with regard to the above variables using a linear mixed model. RESULTS: The mean BMI was significantly lower (by 2 kg/m2, p = 0.01) in patients with AD than in patients with either mild-NCD or vascular/mixed dementia. Leptin levels were significantly higher (p = 0.043) and adiponectin levels significantly lower (p = 0.045) in patients with mild-NCD than in patients with major-NCD (AD or vascular/mixed dementia). However, the mixed model suggested no influence of the baseline levels of these two biomarkers on the course of cognitive decline. CONCLUSION: The present study confirms the associations between leptin and adiponectin and AD or AD-related disorders but did not confirm that these peptides may be used as predictive biomarkers of cognitive decline.

Association of Cerebrospinal Fluid (CSF) Insulin with Cognitive Performance and CSF Biomarkers of Alzheimer's Disease. - Geijselaers, Stefan L C; Aalten, Pauline; Ramakers, Inez H G B; De Deyn, Peter Paul; Heijboer, Annemieke C; Koek, Huiberdina L; OldeRikkert, Marcel G M; Papma, Janne M; Reesink, Fransje E; Smits, Lieke L; Stehouwer, Coen D A; Teunissen, Charlotte E; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Abnormal insulin signaling in the brain has been linked to Alzheimer's disease (AD). OBJECTIVE: To evaluate whether cerebrospinal fluid (CSF) insulin levels are associated with cognitive performance and CSF amyloid-β and Tau. Additionally, we explore whether any such association differs by sex or APOE ɛ4 genotype. METHODS: From 258 individuals participating in the Parelsnoer Institute Neurodegenerative Diseases, a nationwide multicenter memory clinic population, we selected 138 individuals (mean age 66±9 years, 65.2% male) diagnosed with subjective cognitive impairment (n = 45), amnestic mild cognitive impairment (n = 44), or AD (n = 49), who completed a neuropsychological assessment, including tests of global cognition and memory performance, and who underwent lumbar puncture. We measured CSF levels of insulin, amyloid-β1-42, total (t-)Tau, and phosphorylated (p-)Tau. RESULTS: CSF insulin levels did not differ between the diagnostic groups (p = 0.136). Across the whole study population, CSF insulin was unrelated to cognitive performance and CSF biomarkers of AD, after adjustment for age, sex, body mass index, diabetes status, and clinic site (all p≥0.131). Importantly, however, we observed effect modification by sex and APOE ɛ4 genotype. Specifically, among women, higher insulin levels in the CSF were associated with worse global cognition (standardized regression coefficient -0.483; p = 0.008) and higher p-Tau levels (0.353; p = 0.040). Among non-carriers of the APOE ɛ4 allele, higher CSF insulin was associated with higher t-Tau (0.287; p = 0.008) and p-Tau (0.246; p = 0.029). CONCLUSION: Our findings provide further evidence for a relationship between brain insulin signaling and AD pathology. It also highlights the need to consider sex and APOE ɛ4 genotype when assessing the role of insulin.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Brain; Cognition Disorders; Female; Humans; Insulin; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptide Fragments; Signal Transduction; tau Proteins

Associations of Dietary Protein and Fiber Intake with Brain and Blood Amyloid-β. - Fernando, W M A D Binosha; Rainey-Smith, Stephanie R; Gardener, Samantha L; Villemagne, Victor L; Burnham, Samantha C; Macaulay, S Lance; Brown, Belinda M; Gupta, Veer Bala; Sohrabi, Hamid R; Weinborn, Michael; Taddei, Kevin; Laws, Simon M; et al. (J Alzheimers Dis, 2018)
Accumulating evidence suggests a diet high in protein and fiber may confer some protection against Alzheimer's disease (AD). However, no human studies to-date have assessed the relationship between protein and fiber intake, and plasma and brain amyloid-β (Aβ). Consequently, this cross-sectional study, investigated the association of self-reported dietary intakes of protein and fiber, with plasma and brain Aβ burden (n = 541, and n = 162 respectively), in a well-characterized cohort of cognitively normal older adults, drawn from the larger Australian Imaging, Biomarkers and Lifestyle (AIBL) study of aging. We observed 12.59 and 8.43 higher odds of 'high' brain Aβ burden (PiB PET SUVR≥1.5) if protein intake fell in the lowest and middle tertile, respectively, compared to the highest tertile (p = 0.008; p = 0.013). Thus, in this cohort, the more protein consumed, the less likelihood of 'high' Aβ burden in the brain. No other significant associations were observed. The results of this study highlight the potentially protective impact of high dietary protein intake on brain Aβ burden in older adults, before objective memory decline is apparent. While longitudinal validation is required, these findings may assist in the development of dietary approaches aimed at preventing or delaying AD onset.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Australia; Biomarkers; Brain; Cognition; Cohort Studies; Cross-Sectional Studies; Dietary Fiber; Dietary Proteins; Female; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography

Automated Multi-Atlas Segmentation of Hippocampal and Extrahippocampal Subregions in Alzheimer's Disease at 3T and 7T: What Atlas Composition Works Best? - Xie, Long; Shinohara, Russell T; Ittyerah, Ranjit; Kuijf, Hugo J; Pluta, John B; Blom, Kim; Kooistra, Minke; Reijmer, Yael D; Koek, Huiberdina L; Zwanenburg, Jaco J M; Wang, Hongzhi; Luijten, Peter R; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Multi-atlas segmentation, a popular technique implemented in the Automated Segmentation of Hippocampal Subfields (ASHS) software, utilizes multiple expert-labelled images ("atlases") to delineate medial temporal lobe substructures. This multi-atlas method is increasingly being employed in early Alzheimer's disease (AD) research, it is therefore becoming important to know how the construction of the atlas set in terms of proportions of controls and patients with mild cognitive impairment (MCI) and/or AD affects segmentation accuracy. OBJECTIVE: To evaluate whether the proportion of controls in the training sets affects the segmentation accuracy of both controls and patients with MCI and/or early AD at 3T and 7T. METHODS: We performed cross-validation experiments varying the proportion of control subjects in the training set, ranging from a patient-only to a control-only set. Segmentation accuracy of the test set was evaluated by the Dice similarity coeffiecient (DSC). A two-stage statistical analysis was applied to determine whether atlas composition is linked to segmentation accuracy in control subjects and patients, for 3T and 7T. RESULTS: The different atlas compositions did not significantly affect segmentation accuracy at 3T and for patients at 7T. For controls at 7T, including more control subjects in the training set significantly improves the segmentation accuracy, but only marginally, with the maximum of 0.0003 DSC improvement per percent increment of control subject in the training set. CONCLUSION: ASHS is robust in this study, and the results indicate that future studies investigating hippocampal subfields in early AD populations can be flexible in the selection of their atlas compositions.

Aβ42/Aβ40 and Aβ42/Aβ38 Ratios Are Associated with Measures of Gait Variability and Activities of Daily Living in Mild Alzheimer's Disease: A Pilot Study. - Koychev, Ivan; Galna, Brook; Zetterberg, Henrik; Lawson, Jennifer; Zamboni, Giovanna; Ridha, Basil H; Rowe, James B; Thomas, Alan; Howard, Robert; Malhotra, Paresh; Ritchie, Craig; Lovestone, Simon; et al. (J Alzheimers Dis, 2018)
Gait disturbances are some of the earliest changes in dementia and their monitoring presents an opportunity for early diagnosis. The exact relationship between gait and well-established biomarkers of Alzheimer's disease (AD) remains to be clarified. In this study we compared gait-related measures with cerebrospinal fluid (CSF) markers of AD pathology. We recruited seventeen participants with mild AD in a multi-site study and performed gait assessment as well as lumbar punctures to obtain CSF. CSF Aβ42/Aβ40 and Aβ42/Aβ38 correlated positively with measures of variability (step time and step length) in the clinic-based assessments. This was driven by a negative relationship between gait variability and Aβ40 and Aβ38 but not Aβ42.The amyloid ratios and gait variability measures were also associated with more severe functional impairment. We interpret these data as an indication that increasing amyloid production (i.e., increasing Aβ40 and Aβ38) is associated with diminishing cognitive-motor control of gait. These preliminary results suggest that the two amyloid ratios may be a marker of the earliest disturbances in the interplay between cognitive and motor control which characterize dementia.

The Behavioral and Psychological Symptoms of Dementia in Down Syndrome (BPSD-DS) Scale: Comprehensive Assessment of Psychopathology in Down Syndrome. - Dekker, Alain D; Sacco, Silvia; Carfi, Angelo; Benejam, Bessy; Vermeiren, Yannick; Beugelsdijk, Gonny; Schippers, Mieke; Hassefras, Lyanne; Eleveld, José; Grefelman, Sharina; Fopma, Roelie; Bomer-Veenboer, Monique; et al. (J Alzheimers Dis, 2018)
People with Down syndrome (DS) are prone to develop Alzheimer's disease (AD). Behavioral and psychological symptoms of dementia (BPSD) are core features, but have not been comprehensively evaluated in DS. In a European multidisciplinary study, the novel Behavioral and Psychological Symptoms of Dementia in Down Syndrome (BPSD-DS) scale was developed to identify frequency and severity of behavioral changes taking account of life-long characteristic behavior. 83 behavioral items in 12 clinically defined sections were evaluated. The central aim was to identify items that change in relation to the dementia status, and thus may differentiate between diagnostic groups. Structured interviews were conducted with informants of persons with DS without dementia (DS, n = 149), with questionable dementia (DS+Q, n = 65), and with diagnosed dementia (DS+AD, n = 67). First exploratory data suggest promising interrater, test-retest, and internal consistency reliability measures. Concerning item relevance, group comparisons revealed pronounced increases in frequency and severity in items of anxiety, sleep disturbances, agitation & stereotypical behavior, aggression, apathy, depressive symptoms, and eating/drinking behavior. The proportion of individuals presenting an increase was highest in DS+AD, intermediate in DS+Q, and lowest in DS. Interestingly, among DS+Q individuals, a substantial proportion already presented increased anxiety, sleep disturbances, apathy, and depressive symptoms, suggesting that these changes occur early in the course of AD. Future efforts should optimize the scale based on current results and clinical experiences, and further study applicability, reliability, and validity. Future application of the scale in daily care may aid caregivers to understand changes, and contribute to timely interventions and adaptation of caregiving.

Biallelic Loss of Function of SORL1 in an Early Onset Alzheimer's Disease Patient. - Le Guennec, Kilan; Tubeuf, Hélène; Hannequin, Didier; Wallon, David; Quenez, Olivier; Rousseau, Stéphane; Richard, Anne-Claire; Deleuze, Jean-François; Boland, Anne; Frebourg, Thierry; Gaildrat, Pascaline; Campion, Dominique; et al. (J Alzheimers Dis, 2018)
Heterozygous SORL1 protein truncating variants (PTV) are a strong risk factor for early-onset Alzheimer's disease (EOAD). In case control studies performed at the genome-wide level, PTV definition is usually straightforward. Regarding splice site variants, only those affecting canonical sites are typically included. Some other variants, not annotated as PTV, could, however, affect splicing and hence result in a loss of SORL1 function. We took advantage of the whole exome sequencing data from the 9/484 patients with a previously reported SORL1 PTV in the French EOAD series and searched for a second variant which may affect splicing and eventually result in more than 50% loss of function overall. We found that one patient, known to carry a variant predicted to disrupt the canonical 5' splice site of exon 8, also carried a second novel intronic variant predicted to affect SORL1 splicing of exon 29. Segregation analysis showed that the second variant was located in trans from the known PTV. We performed ex vivo minigene splicing assays and showed that both variants led to the generation of transcripts containing a premature stop codon. This is therefore the first evidence of a human carrying biallelic SORL1 PTV. This patient had a family history of dementia in both maternal and paternal lineages with later ages of onset than the proband himself. However, his 55 years age at onset was in the same ranges as previously published SORL1 heterozygous PTV carriers. This suggests that biallelic loss of SORL1 function is an extremely rare event that was not associated with a dramatically earlier age at onset than heterozygous SORL1 loss-of-function variant carriers, in this single patient.
Keywords: Alzheimer Disease; Case-Control Studies; Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Humans; LDL-Receptor Related Proteins; Male; Membrane Transport Proteins; Middle Aged; Risk Factors

Bi-directional Association of Cerebrospinal Fluid Immune Markers with Stage of Alzheimer's Disease Pathogenesis. - Meyer, Pierre-François; Savard, Mélissa; Poirier, Judes; Labonte, Anne; Rosa-Neto, Pedro; Weitz, Tara M; Town, Terrence; Breitner, John (J Alzheimers Dis, 2018)
Immune mechanisms may be important in the pathogenesis of Alzheimer's disease (AD). Yet, studies comparing cerebrospinal fluid (CSF) and plasma immune marker levels of healthy and demented individuals have yielded conflicting results. We analyzed CSF from 101 members of the parental history-positive PREVENT-AD cohort of healthy aging adults, and 237 participants without dementia from the initial cohort of the Alzheimer's Disease Neuroimaging Initiative (ADNI-1). Following recent practice, we used the biomarkers total-tau and amyloid-β1-42 to allocate participants from each study into four stages of AD pathogenesis: Stage 0 (no abnormality), Stage 1 (reduced amyloid-β1-42), Stage 2 (reduced amyloid-β1-42 and increased total-tau), or "Suspected Non-Alzheimer Pathology" (elevated total-tau only). Investigating the PREVENT-AD participants' CSF assay results for 19 immune/inflammatory markers, we found six that showed a distinct bi-directional relationship with pathogenetic stage. Relative to Stage 0, these were diminished at Stage 1 but strongly increased at Stage 2. Among the ADNI participants (90 healthy controls and 147 with mild cognitive impairment), we found that 23 of 83 available CSF markers also showed this distinct pattern. These results support recent observations that immune activation may become apparent only after the onset of both amyloid and tau pathologies. Unexpectedly, they also suggest that immune marker activity may diminish along with earliest appearance of amyloid-β plaque pathology. These findings may explain discordant results from past studies, and suggest the importance of characterizing the extent of AD pathology when comparing clinical groups.

Bioactive Food Abates Metabolic and Synaptic Alterations by Modulation of Gut Microbiota in a Mouse Model of Alzheimer's Disease. - Syeda, Tauqeerunnisa; Sanchez-Tapia, Mónica; Pinedo-Vargas, Laura; Granados, Omar; Cuervo-Zanatta, Daniel; Rojas-Santiago, Eleazar; Díaz-Cintra, Sof A; Torres, Nimbe; Perez-Cruz, Claudia (J Alzheimers Dis, 2018)
Recent investigations have demonstrated an important role of gut microbiota (GM) in the pathogenesis of Alzheimer's disease (AD). GM modulates a host's health and disease by production of several substances, including lipopolysaccharides (LPS) and short-chain fatty acids (SCFAs), among others. Diet can modify the composition and diversity of GM, and ingestion of a healthy diet has been suggested to lower the risk to develop AD. We have previously shown that bioactive food (BF) ingestion can abate neuroinflammation and oxidative stress and improve cognition in obese rats, effects associated with GM composition. Therefore, BF can impact the gut-brain axis and improved behavior. In this study, we aim to explore if inclusion of BF in the diet may impact central pathological markers of AD by modulation of the GM. Triple transgenic 3xTg-AD (TG) female mice were fed a combination of dried nopal, soy, chia oil, and turmeric for 7 months. We found that BF ingestion improved cognition and reduced Aβ aggregates and tau hyperphosphorylation. In addition, BF decreased MDA levels, astrocyte and microglial activation, PSD-95, synaptophysin, GluR1 and ARC protein levels in TG mice. Furthermore, TG mice fed BF showed increased levels of pGSK-3β. GM analysis revealed that pro-inflammatory bacteria were more abundant in TG mice compared to wild-type, while BF ingestion was able to restore the GM's composition, LPS, and propionate levels to control values. Therefore, the neuroprotective effects of BF may be mediated, in part, by modulation of GM and the release of neurotoxic substances that alter brain function.

Blood Inflammatory Mediators and Cognitive Decline in Alzheimer's Disease: A Two Years Longitudinal Study. - Julian, Adrien; Rioux-Bilan, Agnès; Ragot, Stéphanie; Krolak-Salmon, Pierre; Berrut, Gilles; Dantoine, Thierry; Hommet, Caroline; Hanon, Olivier; Page, Guylène; Paccalin, Marc (J Alzheimers Dis, 2018)
Peripheral inflammatory processes are involved in Alzheimer's disease (AD). We aimed to determine whether plasma inflammatory mediator levels at diagnosis are associated with cognitive decline through a 2-year follow-up in AD patients. Patients (n = 109, mean age 79.44 (6.82) years) were included at diagnosis with MMSE scores between 16 and 25, with C-reactive protein <10 mg/L, and without any acute or chronic inflammation status. Plasma IL-1β, IL-6, TNF-α, and CCL5 were measured using Luminex X-MAP technology at baseline, and after one year and two years of follow-up. The mean values of IL-1β, IL-6, TNF-α, and CCL5 at diagnosis were 0.3, 1.94, 6.57, and 69,615.81 pg/mL, respectively. Mean cognitive decline in MMSE was 3.35 points. No correlation between plasmatic value of IL-1β, IL-6, TNF-α, or CCL5 at diagnosis and cognitive decline during the two years of follow-up was found. Cognitive decline in AD does not appear to be predictable by the tested inflammatory mediators.

Can 11C-PiB-PET Relative Delivery R1 or 11C-PiB-PET Perfusion Replace 18F-FDG-PET in the Assessment of Brain Neurodegeneration? - Oliveira, Francisco P M; Moreira, Ana Paula; de Mendonça, Alexandre; Verdelho, Ana; Xavier, Carolina; Barroca, Dalila; Rio, Joana; Cardoso, Eva; Cruz, Ângela; Abrunhosa, Antero; Castelo-Branco, Miguel (J Alzheimers Dis, 2018)
BACKGROUND: Pittsburgh Compound B (PiB) positron emission tomography (PET) is used to visualize in vivo amyloid plaques in the brain. Frequently the PiB examinations are complemented with a fluorodeoxyglucose (FDG) PET scan to further assess neurodegeneration. OBJECTIVE: Our goal is to identify alternative correlates of FDG images by assessing which kinetic methods originate PiB derived relative delivery ratio (R1) images that can be correlated with the FDG images, and to compare them with PiB perfusion (pPiB) images obtained from the early-phase of PiB acquisition. METHODS: We selected 52 patients with cognitive impairment who underwent a dynamic PiB and FDG acquisitions. To compute the R1 images, two simplified reference tissue models (SRTM and SRTM2) and two multi-linear reference tissue models (MRTM and MRTM2) were used. The pPiB images were obtained in two different time intervals. RESULTS: All six types of images were of good quality and highly correlated with the FDG images (mean voxelwise within-subjects r > 0.92). The higher correlation was found for FDG-R1(MRTM). Regarding the voxelwise regional correlation, the higher mean all brain correlations was r = 0.825 for FDG-R1(MRTM) and statistically significant in the whole brain analysis. CONCLUSION: All R1 and pPiB images here tested have potential to assess the metabolic impact of neurodegeneration almost as reliably as the FDG images. However, this is not enough to validate these images for a single-subject analysis compared with the FDG image, and thus they cannot yet be used clinically to replace the FDG image before such evaluation.

Cardiorespiratory Fitness and Cognitive Function are Positively Related Among Participants with Mild and Subjective Cognitive Impairment. - Stuckenschneider, Tim; Askew, Christopher David; Rüdiger, Stefanie; Polidori, Maria Cristina; Abeln, Vera; Vogt, Tobias; Krome, Andreas; Olde Rikkert, Marcel; Lawlor, Brian; Schneider, Stefan (J Alzheimers Dis, 2018)
BACKGROUND: By 2030, about 74 million people will be diagnosed with dementia, and many more will experience subjective (SCI) or mild cognitive impairment (MCI). As physical inactivity has been identified to be a strong modifiable risk factor for dementia, exercise and physical activity (PA) may be important parameters to predict the progression from MCI to dementia, but might also represent disease trajectory modifying strategies for SCI and MCI. OBJECTIVE: A better understanding of the relationship between activity, fitness, and cognitive function across the spectrum of MCI and SCI would provide an insight into the potential utility of PA and fitness as early markers, and treatment targets to prevent cognitive decline. METHODS: 121 participants were stratified into three groups, late MCI (LMCI), early MCI (EMCI), and SCI based on the Montreal Cognitive Assessment (MoCA). Cognitive function assessments also included the Trail Making Test A+B, and a verbal fluency test. PA levels were evaluated with an interviewer-administered questionnaire (LAPAQ) and an activity monitor. An incremental exercise test was performed to estimate cardiorespiratory fitness and to determine exercise capacity relative to population normative data. RESULTS: ANCOVA revealed that LMCI subjects had the lowest PA levels (LAPAQ, p = 0.018; activity monitor, p = 0.041), and the lowest exercise capacity in relation to normative values (p = 0.041). Moreover, a modest correlation between MoCA and cardiorespiratory fitness (r = 0.25; p < 0.05) was found. CONCLUSION: These findings suggest that during the earliest stages of cognitive impairment PA and exercise capacity might present a marker for the risk of further cognitive decline. This finding warrants further investigation using longitudinal cohort studies.

Cardiorespiratory Fitness and White Matter Neuronal Fiber Integrity in Mild Cognitive Impairment. - Ding, Kan; Tarumi, Takashi; Zhu, David C; Tseng, Benjamin Y; Thomas, Binu P; Turner, Marcel; Repshas, Justin; Kerwin, Diana R; Womack, Kyle B; Lu, Hanzhang; Cullum, C Munro; Zhang, Rong (J Alzheimers Dis, 2018)
BACKGROUND: Mounting evidence showed the self-reported levels of physical activity are positively associated with white matter (WM) integrity and cognitive performance in normal adults and patients with mild cognitive impairment (MCI). However, the objective measure of cardiorespiratory fitness (CRF) was not used in these studies. OBJECTIVE: To determine the associations of CRF measured by maximal oxygen uptake (VO2max) with WM fiber integrity and neurocognitive performance in older adults with MCI. METHODS: Eighty-one participants (age = 65±7 years, 43 women), including 26 cognitively normal older adults and 55 amnestic MCI patients, underwent VO2max test to measure CRF, diffusion tensor imaging (DTI) to assess WM fiber integrity, and neurocognitive assessment focused on memory and executive function. DTI data were analyzed by the tract-based spatial statistics and region-of-interest approach. RESULTS: Cognitively normal older adults and MCI patients were not different in global WM fiber integrity and VO2max. VO2max was associated positively with DTI metrics of fractional anisotropy in ∼54% WM fiber tracts, and negatively with mean and radial diffusivities in ∼46% and ∼56% of the WM fiber tracts. The associations of VO2max with DTI metrics remained statistically significant after adjustment of age, sex, body mass index, WM lesion burden, and MCI status. The DTI metrics obtained from the area that correlated to VO2max were associated with executive function performance in MCI patients. CONCLUSIONS: Higher levels of CRF are associated with better WM fiber integrity, which in turn is correlated with better executive function performance in MCI patients.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Anisotropy; Cardiorespiratory Fitness; Case-Control Studies; Cognition; Cognitive Dysfunction; Diffusion Tensor Imaging; Executive Function; Female; Humans; Linear Models; Male; Memory; Middle Aged; Nerve Fibers, Myelinated; Neuropsychological Tests; Texas; White Matter

Caregiving and Caregiver Burden in Dementia Home Care: Results from the Prospective Dementia Registry (PRODEM) of the Austrian Alzheimer Society. - Ransmayr, Gerhard; Hermann, Philipp; Sallinger, Katharina; Benke, Thomas; Seiler, Stephan; Dal-Bianco, Peter; Marksteiner, Josef; Defrancesco, Michaela; Sanin, Günter; Struhal, Walter; Guger, Michael; Vosko, Milan; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Comprehensive studies on caregiver burden (CB) of persons caring for dementia patients differ methodologically and show variable results. OBJECTIVE: Analysis of known and hypothesized factors of CB in home care of dementia patients. METHODS: Multicenter longitudinal study comprising 585 persons caring mostly for Alzheimer's disease patients (age median 77.25 years, Mini-Mental State Examination raw score median 23) using the Zarit Caregiver Burden Interview (CBI). Known patient-related determinants of CB were studied, such as dementia severity (Clinical Dementia Rating, CDR), neuropsychological deficits (CERAD-Plus), neuropsychiatric symptoms (Neuropsychiatric Inventory, NPI), disability (Disability Assessment for Dementia, DAD), dependency (Dependency Scale, DS), and moreover, unclarified potential factors (age, sex, education of patients; age, sex, occupational status of the caregivers; family relationship). Psychological and somatic effects of CB were analyzed (factor analysis). RESULTS: Caregiver age was median 61. Female caregivers prevailed (67.8%). Median CBI sum score (CBIss) was 16 at baseline. After two years, CBIss was 22 and 37% of the caregivers reported mild to moderate (CBIss 21-40), 16.8% moderate to severe or severe (≥41), and 46.2% absent to little CB (CBIss ≤ 20). CB correlated positively with NPI, CDR, DS scores, disability (DAD), years of education of the patients, and proximity of patient and caregiver sex (female), and negatively with caregiver age. Caregivers reported restrictions of time, health problems, and negative emotions. CONCLUSION: The findings are applicable to identify persons at risk for substantial CB and its consequences. There is demand for personal, psychological, and medical support of caregivers and increasing male participation.

Cerebral Amyloid Angiopathy and Cerebral Amyloid Angiopathy-Related Inflammation: Comparison of Hemorrhagic and DWI MRI Features. - Renard, Dimitri; Tatu, Lavinia; Collombier, Laurent; Wacongne, Anne; Ayrignac, Xavier; Charif, Mahmoud; Boukriche, Yassine; Chiper, Laura; Fourcade, Genevieve; Azakri, Souhayla; Gaillard, Nicolas; Mercier, Erick; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Cerebral amyloid angiopathy (CAA) can be associated with primary vasculitis of small/medium-sized leptomeningeal and cortical arteries, called CAA-related inflammation (CAA-ri). OBJECTIVE: To compare hemorrhagic and diffusion-weighted imaging (DWI) MRI features in CAA and CAA-ri. METHODS: We prospectively scored in a consecutive CAA and CAA-ri cohort: presence/number of chronic intracerebral hemorrhage (ICH), cerebral microbleeds (CMB), and cortical superficial siderosis (CSS) on initial T2*-weighted imaging, and DWI lesions on both initial and follow-up imaging. In a subgroup, ApoE, CSF, and 18F-florbetaben-positron emission tomography (FBB-PET) were also analyzed. RESULTS: In CAA-ri, CMB presence was more frequent (100% versus 40%, p < 0.001) and CMB numbers higher (mean 137 versus 8, p < 0.001). No difference was observed for chronic ICH or CSS. DWI lesions were more frequent in acute compared to chronic CAA-ri (p = 0.025), whereas no such difference was observed between acute and chronic CAA (p = 0.18). Both ApoE4 (genotyping available in 22 CAA-ri and 48 CAA patients) carriers and homozygosity were more frequent in CAA-ri (48% versus 19% [p = 0.014] and 32% versus 2% [p < 0.001] respectively). CSF biomarker analyses (performed in 20 CAA-ri and 45 CAA patients) showed lower Aβ42 levels in CAA-ri compared to CAA (median 312 versus 422 pg/mL, p = 0.0032). FBB-PET (performed in 11 CAA-ri and 20 CAA patients) showed higher standardized uptake value ratios in CAA-ri compared with CAA, only significant when the pons was used as reference (p = 0.037). CONCLUSION: Compared to CAA, CAA-ri was associated with higher CMB numbers, more frequent ApoE4 carriers and homozygotes, lower CSF Aβ42 levels, and more severe amyloid load on FBB-PET.

Cerebrospinal Fluid Levels of Angiotensin-Converting Enzyme Are Associated with Amyloid-β42 Burden in Alzheimer's Disease. - Rocha, Natalia P; Toledo, Andre; Corgosinho, Laiane T S; de Souza, Leonardo C; Guimarães, Henrique C; Resende, Elisa P F; Braz, Nayara F T; Gomes, Karina B; Simoes E Silva, Ana C; Caramelli, Paulo; Teixeira, Antônio L (J Alzheimers Dis, 2018)
This study was designed to determine whether the levels of renin-angiotensin system (RAS) components are associated with Alzheimer's disease (AD) pathology. Cerebrospinal fluid levels of Angiotensin (Ang) II, Ang-(1-7), angiotensin-converting enzyme (ACE), ACE2, Amyloid-β (Aβ)40, Aβ42, total tau (hTau), and phospho-tau (pTau) were measured in 18 patients with AD and 10 controls. Patients with AD presented decreased levels of ACE when compared with controls. We found a significant positive correlation between ACE and Aβ42 levels among patients. Our results strengthen the hypothesis that ACE is associated with Aβ pathology in AD.

Cerebrospinal Fluid, MRI, and Florbetaben-PET in Cerebral Amyloid Angiopathy-Related Inflammation. - Renard, Dimitri; Collombier, Laurent; Demattei, Christophe; Wacongne, Anne; Charif, Mahmoud; Ayrignac, Xavier; Azakri, Souhayla; Gaillard, Nicolas; Boudousq, Vincent; Lehmann, Sylvain; Menjot de Champfleur, Nicolas; Thouvenot, Eric (J Alzheimers Dis, 2018)
BACKGROUND: Cerebral amyloid angiopathy-related inflammation (CAA-ri) is associated with a cerebrospinal fluid (CSF) biomarker profile similar to that observed in CAA. Few CAA-ri patients have been studied by fibrillar amyloid-β (Aβ) imaging (using 11C-Pittsburgh compound B and 18F-florbetapir, but not 18F-florbetaben). OBJECTIVE: To describe CSF biomarkers, magnetic resonance imaging (MRI), and 18F-florbetaben (FBB)-positron emission tomography (PET) changes in CAA-ri patients. METHODS: CSF levels of total tau, phosphorylated tau, Aβ1-42, and Aβ1-40, MRI (cerebral microbleeds count on susceptibility-weighted imaging and semi-quantitative analysis of fluid-attenuation inversion recovery white matter hyperintensities), and FBB-PET (using both cerebellar cortex and pons to calculate standardized uptake value ratios) were analyzed in nine consecutive CAA-ri patients. RESULTS: A median number of 769 cerebral microbleeds/patient were counted on MRI. When using the pons as reference region, amyloid load on FBB-PET was very strongly correlated to CSF Aβ1-40 levels (rho = -0.83, p = 0.008) and moderately correlated to cerebral microbleed numbers in the occipital lobes (rho = 0.59, p = 0.001), while comparisons with other CSF biomarkers were not statistically significant (total tau, rho = -0.63, p = 0.076; phosphorylated tau, rho = -0.68, p = 0.05; Aβ1-42, rho = -0.59, p = 0.09). All correlations were weaker, and not statistically significant, when using the cerebellum as reference region. A non-significant correlation (rho = -0.50, p = 0.18) was observed between CSF Aβ1-40 levels and cerebral microbleed numbers. CONCLUSION: In CAA-ri, CSF Aβ1-40 levels correlated well with amyloid load assessed by FBB-PET when the pons was used as reference, and to a lesser degree with cerebral microbleeds count on MRI. This confirms earlier data on CSF Aβ1-40 as an in vivo marker for CAA and CAA-ri.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Aniline Compounds; Biomarkers; Brain; Cerebral Amyloid Angiopathy; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Multivariate Analysis; Positron-Emission Tomography; Prospective Studies; Stilbenes; tau Proteins; Vasculitis, Central Nervous System

Cerebrovascular Disease and Neurodegeneration in Alzheimer's Disease with and without a Strong Family History: A Pilot Magnetic Resonance Imaging Study in Dominican Republic. - Piriz, Angel; Reyes, Dolly; Narkhede, Atul; Guzman, Vanessa A; Viqar, Fawad; Meier, Irene B; Budge, Mariana; Mena, Pedro; Dashnaw, Stephen; Lee, Joseph; Reitz, Christiane; Gutierrez, Jose; et al. (J Alzheimers Dis, 2018)
The incidence and prevalence of Alzheimer's disease (AD) dementia are higher among Caribbean Hispanics than among non-Hispanic Whites. The causes of this health disparity remain elusive, partially because of the relative limited capacity for biomedical research in the developing countries that comprise Caribbean Latin America. To begin to address this issue, we were awarded a Development Research Award from the US NIH and Fogarty International Center in order to establish the local capacity to integrate magnetic resonance imaging (MRI) into studies of cognitive aging and dementia in Dominican Republic, establish collaborations with Dominican investigators, and conduct a pilot study on the role of cerebrovascular markers in the clinical expression of AD. Ninety older adult participants with and without AD dementia and with and without a strong family history of AD dementia received MRI scans and clinical evaluation. We quantified markers of cerebrovascular disease (white matter hyperintensities [WMH], presence of infarct, and presence of microbleed) and neurodegeneration (entorhinal cortex volume) and compared them across groups. Patients with AD dementia had smaller entorhinal cortex and greater WMH volumes compared with controls, regardless of family history status. This study provides evidence for the capacity to conduct MRI studies of cognitive aging and dementia in Dominican Republic. The results are consistent with the hypothesis that small vessel cerebrovascular disease represents a core feature of AD dementia, as affected participants had elevated WMH volumes irrespective of family history status.

CFH and ARMS2 Polymorphisms Interact with Zinc Supplements in Cognitive Impairment in the Women's Health Initiative Hormone Trial. - Kustra, Rafal; Awh, Carl C; Rojas-Fernandez, Carlos; Zanke, Brent (J Alzheimers Dis, 2018)
BACKGROUND: An interaction between genetic variants in complement factor H (CFH) and age-related maculopathy susceptibility 2 (ARMS2) and high-dose zinc supplementation on progression to advanced age-related macular degeneration (AMD) exists. Because cognitive impairment (CI) is associated with AMD, we used data from the Women's Health Initiative (WHI) to search for a zinc/genetics interaction. OBJECTIVE: To study the interaction of chronic zinc supplementation with genetic variants in CFH and ARMS2 on the development of CI. BACKGROUND: Zinc dietary supplements, CFH and ARMS2 genotypes, and serial mental status was analyzed in participants with available genetic data (n = 7,483). Cognition was assessed using the Modified Mini-Mental State Examination. The development of CI over 5 years was analyzed by genotype and zinc intake using a repeated measures logistic regression model. RESULTS: Zinc supplementation of approximately 15 mg/day was associated with decreased development of CI in women with 1 or 2 CFH and no ARMS2 risk alleles (OR = 0.46: 1 CFH risk allele; 0.20: 2 CFH risk alleles; p = 0.002). CONCLUSION: Low-dose zinc (approximately 15 mg) is associated with reduced CI in women with 2 CFH and 0 ARMS2 AMD risk alleles. This interaction is opposite in direction to that observed in AMD, where patients with 2 CFH and 0 ARMS2 risk alleles had increased progression to neovascular AMD if treated with 80 mg/day of zinc. This may be due to a zinc dose-response or to a fundamental difference in the role of zinc in the progression of early CI versus advanced AMD.

Childhood Lead Exposure and Adult Neurodegenerative Disease. - Reuben, Aaron (J Alzheimers Dis, 2018)
Millions of Americans now entering midlife and old age were exposed to high levels of lead, a neurotoxin, as children. Evidence from animal-model and human observational studies suggest that childhood lead exposure may raise the risk of adult neurodegenerative disease, particularly dementia, through a variety of possible mechanisms including epigenetic modification, delayed cardiovascular and kidney disease, direct degenerative CNS injury from lead remobilized from bone, and lowered neural and cognitive reserve. Within the next ten years, the generation of children with the highest historical lead exposures, those born in the 1960s, 1970s, and 1980s, will begin to enter the age at which dementia symptoms tend to emerge. Many will also enter the age in which lead stored in the skeleton may be remobilized at greater rates, particularly for women entering menopause and men and women experiencing osteoporosis. Should childhood lead exposure prove pro-degenerative, the next twenty years will provide the last opportunities for possible early intervention to forestall greater degenerative disease burden across the aging lead-exposed population. More evidence is needed now to characterize the nature and magnitude of the degenerative risks facing adults exposed to lead as children and to identify interventions to limit long-term harm.

Circulating, Cell-Free Micro-RNA Profiles Reflect Discordant Development of Dementia in Monozygotic Twins. - Mengel-From, Jonas; Rønne, Mette E; Carlsen, Anting L; Skogstrand, Kristin; Larsen, Lisbeth A; Tan, Qihua; Christiansen, Lene; Christensen, Kaare; Heegaard, Niels H H (J Alzheimers Dis, 2018)
We aim to examine if circulating micro-RNA and cytokine levels associate with dementia diagnosis and cognitive scores. To test our hypothesis, we use plasma donated from 48 monozygotic twin pairs in 1997 and 46 micro-RNAs and 10 cytokines were quantified using microfluidic RT-qPCR and multiplex solid-phase immunoassays, respectively. Micro-RNA and cytokine profiling were examined for associations with dementia diagnoses in a longitudinal registry study or with cognitive scores at baseline. Thirty-six micro-RNAs and all cytokines were detected consistently. Micro-RNA profiles associate with diagnoses and cognitive scores at statistically significant levels while cytokine only showed trends pointing at chronic inflammation in twins having or developing dementia. The most notable findings were decreased miR-106a and miR-210, and increased miR-106b expression in twins with a dementia diagnosis. This pioneering evaluation of micro-RNA and cytokine and dementia diagnosis suggests micro-RNA targets in vasculogenesis, lipoprotein transport, and amyloid precursor protein genes.

Circulating Plasma microRNAs are Altered with Amyloidosis in a Mouse Model of Alzheimer's Disease. - Ryan, Margaret M; Guévremont, Diane; Mockett, Bruce G; Abraham, Wickliffe C; Williams, Joanna M (J Alzheimers Dis, 2018)
Pathological changes underlying Alzheimer's disease (AD) begin decades before the classical symptoms of memory loss become evident. As microRNAs are released from neurons and enter the bloodstream, circulating microRNAs may be reflective of AD progression and are ideal candidates as biomarkers for early-stage disease detection. Here, we provide a novel, in-depth analysis of how plasma microRNAs alter with aging, the most prominent risk factor for AD, and with development of amyloid-β (Aβ) plaque deposition. We assessed the circulating microRNAs in APPswe/PSEN1dE9 transgenic mice and wild-type controls at 4, 8 and 15 m (n = 8-10) using custom designed Taqman arrays representing 185 neuropathology-related microRNAs. We performed a linear mixed-effects model to investigate the effects of age and genotype on plasma microRNAs expression. Following this analysis, we found 8 microRNAs were significantly affected by age alone in wild-type animals and 12 microRNAs altered in APPswe/PSEN1dE9 mice, either prior to Aβ plaque deposition (4 m) or during the development of AD-like pathogenesis (8 m or 15 m). Importantly, we found that differing sets of microRNAs were identified at each time point. Functional analysis of these data revealed that while common biological pathways, such as Inflammatory Response, were enriched throughout the disease process, Free Radical Scavenging, Immunological Disease, and Apoptosis Signaling were specifically enriched later in the disease process. Overall, this study reinforces that distinct biological processes underpin the early versus late stages of AD-like pathogenesis and highlights potential pre-symptomatic microRNAs biomarkers of neurodegeneration.

Circulating Progenitor Cells Correlate with Memory, Posterior Cortical Thickness, and Hippocampal Perfusion. - Nation, Daniel A; Tan, Alick; Dutt, Shubir; McIntosh, Elissa C; Yew, Belinda; Ho, Jean K; Blanken, Anna E; Jang, Jung Yun; Rodgers, Kathleen E; Gaubert, Aimée (J Alzheimers Dis, 2018)
BACKGROUND: Bone marrow-derived progenitor cells survey the vasculature and home to sites of tissue injury where they can promote repair and regeneration. It has been hypothesized that these cells may play a protective role neurodegenerative and vascular cognitive impairment. OBJECTIVE: To evaluate progenitor cell levels in older adults with and without mild cognitive impairment (MCI), and to relate circulating levels to memory, brain volume, white matter lesion volume, and cerebral perfusion. METHOD: Thirty-two older adults, free of stroke and cardiovascular disease, were recruited from the community and evaluated for diagnosis of MCI versus cognitively normal (CN). Participants underwent brain MRI and blood samples were taken to quantify progenitor reserve using flow cytometry (CD34+, CD34+CD133+, and CD34+CD133+CD309+ cells). RESULTS: Participants with MCI (n = 10) exhibited depletion of all CPC markers relative to those who were CN (n = 22), after controlling for age, sex, and education. Post-hoc age, sex, and education matched comparisons (n = 10 MCI, n = 10 CN) also revealed the same pattern of results. Depletion of CD34+ cells correlated with memory performance, left posterior cortical thickness, and bilateral hippocampal perfusion. Participants exhibited low levels of vascular risk and white matter lesion burden that did not correlate with progenitor levels. CONCLUSIONS: Circulating progenitor cells are associated with cognitive impairment, memory, cortical atrophy, and hippocampal perfusion. We hypothesize that progenitor depletion contributes to, or is triggered by, cognitive decline and cortical atrophy. Further study of progenitor cell depletion in older adults may benefit efforts to prevent or delay dementia.
Keywords: Aged; Aged, 80 and over; Antigens, CD; Apolipoproteins E; Cerebral Cortex; Cognitive Dysfunction; Female; Flow Cytometry; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Perfusion; Stem Cells; White Matter

Clinical Subtypes of Dementia with Lewy Bodies Based on the Initial Clinical Presentation. - Morenas-Rodriguez, Estrella; Sala, Isabel; Subirana, Andrea; Pascual-Goñi, Elba; Sánchez-Saudinós, Ma Belén; Alcolea, Daniel; Illán-Gala, Ignacio; Carmona-Iragui, María; Ribosa-Nogué, Roser; Camacho, Valle; Blesa, Rafael; Fortea, Juan; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Dementia with Lewy bodies (DLB) is a heterogeneous disease in which clinical presentation, symptoms, and evolution widely varies between patients. OBJECTIVE: To investigate the existence of clinical subtypes in DLB based on the initial clinical presentation. METHODS: 81 patients with a clinical diagnosis of probable DLB were consecutively included. All patients underwent a neurological evaluation including a structured questionnaire about neuropsychiatric symptoms and sleep, an assessment of motor impairment (Unified Parkinson Disease Rating Scale subscale III), and a formal neuropsychological evaluation. Onset of core symptoms (hallucinations, parkinsonism, and fluctuations) and dementia were systematically reviewed from medical records. We applied a K-means clustering method based on the initial clinical presentation. RESULTS: Cluster analysis yielded three different groups. Patients in cluster I (cognitive-predominant, n = 46) presented more frequently with cognitive symptoms (95.7%, n = 44, p < 0.001), and showed a longer duration from onset to DLB diagnosis (p < 0.001) than the other clusters. Patients in cluster II (neuropsychiatric-predominant, n = 22) were older at disease onset (78.1±5 versus 73.6±6.1 and 73.6±4.2 in clusters I and III, respectively, both p < 0.01), presented more frequently with psychotic symptoms (77.3%, n = 17), and had a shorter duration until the onset of hallucinations (p < 0.001). Patients in cluster III (parkinsonism-predominant, n = 13) showed a shorter time from onset to presence of parkinsonism (p < 0.001) and dementia (0.008). CONCLUSIONS: Three clinical subtypes of DLB can be defined when considering the differential initial presentations. The proposed subtypes have distinct clinical profiles and progression patterns.

Clinical Trials for Disease-Modifying Therapies in Alzheimer's Disease: A Primer, Lessons Learned, and a Blueprint for the Future. - Cummings, Jeffrey; Ritter, Aaron; Zhong, Kate (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) has no currently approved disease-modifying therapies (DMTs), and treatments to prevent, delay the onset, or slow the progression are urgently needed. A delay of 5 years if available by 2025 would decrease the total number of patients with AD by 50% in 2050. To meet the definition of DMT, an agent must produce an enduring change in the course of AD; clinical trials of DMTs have the goal of demonstrating this effect. AD drug discovery entails target identification followed by high throughput screening and lead optimization of drug-like compounds. Once an optimized agent is available and has been assessed for efficacy and toxicity in animals, it progresses through Phase I testing with healthy volunteers, Phase II learning trials to establish proof-of-mechanism and dose, and Phase III confirmatory trials to demonstrate efficacy and safety in larger populations. Phase III is followed by Food and Drug Administration review and, if appropriate, market access. Trial populations include cognitively normal at-risk participants in prevention trials, mildly impaired participants with biomarker evidence of AD in prodromal AD trials, and subjects with cognitive and functional impairment in AD dementia trials. Biomarkers are critical in trials of DMTs, assisting in participant characterization and diagnosis, target engagement and proof-of-pharmacology, demonstration of disease-modification, and monitoring side effects. Clinical trial designs include randomized, parallel group; delayed start; staggered withdrawal; and adaptive. Lessons learned from completed trials inform future trials and increase the likelihood of success.
Keywords: Alzheimer Disease; Animals; Clinical Trials as Topic; Humans

Clinical-Neuropathological Correlations of Alzheimer's Disease and Related Dementias in Latino Volunteers. - Soria, Jose A; Huisa, Branko N; Edland, Steven D; Litvan, Irene; Peavy, Guerry M; Salmon, David P; Hansen, Lawrence A; Galasko, Douglas R; Brewer, James B; González, Hector M; Rissman, Robert A (J Alzheimers Dis, 2018)
Clinical, neuropsychological, and neurological procedures used to diagnose Alzheimer's disease (AD) and related dementias were largely developed and validated in well-educated, non-Latino, English-speaking populations. Sociocultural and genetic differences in Latinos might influence the accuracy of clinical diagnosis of AD and other dementias. We aim to compare the accuracy of the clinical diagnosis of AD and related dementias in Latinos with the corresponding neuropathological diagnosis. From the UCSD Alzheimer's Disease Research Center longitudinal cohort, we selected all Latino participants who had autopsy neuropathological studies from 1991 to 2017. Participants underwent annual neurological clinical evaluations, standard neuropsychological tests, neuroimaging, and genotyping of Apolipoprotein E. We calculated the sensitivity and specificity of the clinical diagnosis of AD against the primary pathological diagnosis. Of the 34 participants with a primary neuropathological diagnosis of AD, 33 (97.1%) were correctly clinically diagnosed as having AD at the last clinical evaluation, and 1 was incorrectly diagnosed with dementia with Lewy bodies. Of the 19 participants without a primary neuropathological diagnosis of AD, 8 were incorrectly clinically diagnosed with probable AD at the last clinic evaluation. The clinical diagnosis of AD at the last clinical evaluation had 97.1% sensitivity and 57.9% specificity for autopsy-verified AD. In this Latino cohort, clinicians predicted AD pathological findings with high sensitivity but moderate specificity. Tangle-only dementia was the most common misdiagnosis. Our study suggests that current procedures and instruments to clinically determine AD in Latinos have high sensitivity compared with neuropathology, but specificity needs to be improved.

Clinic-Based Validation of Cerebrospinal Fluid Biomarkers with Florbetapir PET for Diagnosis of Dementia. - Álvarez, Ignacio; Aguilar, Miquel; González, Jose Manuel; Ysamat, Montse; Lorenzo-Bosquet, Carles; Alonso, Alvaro; Tartari, Juan Pablo; Romero, Silvia; Diez-Fairen, Monica; Carcel, Maria; Pujalte, Francisco; Pastor, Pau (J Alzheimers Dis, 2018)
BACKGROUND: Cerebrospinal fluid (CSF) biomarker studies have shown variable accuracy for diagnosis of Alzheimer's disease (AD); therefore, internal validation is recommended. OBJECTIVE: To investigate the correlation between CSF biomarkers and cerebral 18-Florbetapir positron emission tomography (Amyloid-PET) and calculate their sensitivity and specificity to obtain the optimal clinical cut-off points to diagnose the etiology of cognitive impairment. METHODS: We performed Amyloid-PET scans and CSF biomarker levels analyses in 68 subjects (50 with mild cognitive impairment, 11 with AD dementia, and 7 with non-AD dementia). Visual examination of Amyloid-PET scans was performed. CSF analyses were performed using standard sandwich ELISA. RESULTS: Amyloid-PET was positive in 36 subjects, negative in 26, and inconclusive in 6. Optimal clinical cut-off points for CSF markers were the following: amyloid-β 1-42 (Aβ42) = 629 pg/ml, total tau (t-tau) = 532 pg/ml, phosphorylated tau (p-tau) = 88 pg/ml, and t-tau/Aβ42 ratio = 0.58. T-tau/Aβ42 ratio showed the best sensitivity and specificity (92 and 84%, respectively). T-tau and p-tau CSF levels (r2 = 0.867) followed by the t-tau and t-tau/Aβ42 CSF ratio (r2 = 0.666) showed the strongest inter-marker correlation. Interestingly, subjects with inconclusive Amyloid-PET showed intermediate values for all CSF markers between negative and positive Amyloid-PET groups. CONCLUSIONS: CSF t-tau/Aβ42 ratio appears to be the most accurate AD CSF marker. The presence of intermediate values for CSF markers among the subjects with inconclusive Amyloid-PET suggests the presence of other dementias associated with AD pathology or intermediate phenotypes.
Keywords: Aged; Amyloid beta-Peptides; Analysis of Variance; Aniline Compounds; Apolipoproteins E; Biomarkers; Cognition Disorders; Dementia; Ethylene Glycols; Female; Humans; Male; Middle Aged; Peptide Fragments; Positron-Emission Tomography; tau Proteins

Co-Expression of Glia Maturation Factor and Apolipoprotein E4 in Alzheimer's Disease Brain. - Thangavel, Ramasamy; Bhagavan, Sachin M; Ramaswamy, Swathi Beladakere; Surpur, Spurthi; Govindarajan, Raghav; Kempuraj, Duraisamy; Zaheer, Smita; Raikwar, Sudhanshu; Ahmed, Mohammad E; Selvakumar, Govindhasamy Pushpavathi; Iyer, Shankar S; Zaheer, Asgar (J Alzheimers Dis, 2018)
Apolipoprotein E4 (ApoE4) is a major genetic risk factor for Alzheimer's disease (AD). The E4 allele of ApoE plays a crucial role in the inflammatory and neurodegenerative processes associated with AD. This is evident from the multiple effects of the ApoE isoforms in amyloid-β (Aβ) aggregation. Glia maturation factor (GMF) is a brain-specific neuroinflammatory protein that we have previously demonstrated to be significantly upregulated in various regions of AD brains compared to non-AD control brains and that it induces neurodegeneration. We have previously reported that GMF is predominantly expressed in the reactive astrocytes surrounding amyloid plaques (APs) in AD brain. In the present study, using immunohistochemical and dual immunofluorescence staining, we show the expression and colocalization of GMF and ApoE4 in AD brains. Our results show that ApoE4 is present within the APs of AD brain. Further, we found that GMF and ApoE4 were strongly expressed and co-associated in APs and in the reactive astrocytes surrounding APs in AD. An increased expression of GMF in APs and neurofibrillary tangles in the AD brain, and the co-localization of GMF and ApoE4 in APs suggest that GMF and ApoE4 together should be contributing to the neuropathological changes associated with AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Brain; Case-Control Studies; Fluorescent Antibody Technique; Glia Maturation Factor; Humans; Neurofibrillary Tangles; Plaque, Amyloid

Combining Cognitive, Genetic, and Structural Neuroimaging Markers to Identify Individuals with Increased Dementia Risk. - Payton, Nicola M; Kalpouzos, Grégoria; Rizzuto, Debora; Fratiglioni, Laura; Kivipelto, Miia; Bäckman, Lars; Laukka, Erika J (J Alzheimers Dis, 2018)
BACKGROUND: Cognitive and biological markers have shown varying degrees of success in identifying persons who will develop dementia. OBJECTIVE: To evaluate different combinations of cognitive and biological markers and identify prediction models with the highest accuracy for identifying persons with increased dementia risk. METHODS: Neuropsychological assessment, genetic testing (apolipoprotein E -APOE), and structural magnetic resonance imaging (MRI) were performed for 418 older individuals without dementia (60-97 years) from a population-based study (SNAC-K). Participants were followed for six years. RESULTS: Cognitive, genetic, and MRI markers were systematically combined to create prediction models for dementia at six years. The most predictive individual markers were perceptual speed or carrying at least one APOEɛ4 allele (AUC = 0.875). The most predictive model (AUC = 0.924) included variables from all three modalities (category fluency, general knowledge, any ɛ4 allele, hippocampal volume, white matter-hyperintensity volume). CONCLUSION: This study shows that combining markers within and between modalities leads to increased predictivity for future dementia. However, minor increases in predictive value should be weighed against the cost of additional tests in larger-scale screening.

Comparison between FCSRT and LASSI-L to Detect Early Stage Alzheimer's Disease. - Matías-Guiu, Jordi A; Cabrera-Martín, María Nieves; Curiel, Rosie E; Valles-Salgado, María; Rognoni, Teresa; Moreno-Ramos, Teresa; Carreras, José Luis; Loewenstein, David A; Matías-Guiu, Jorge (J Alzheimers Dis, 2018)
BACKGROUND: The Free and Cued Selective Reminding Test (FCSRT) is the most accurate test for the diagnosis of prodromal Alzheimer's disease (AD). Recently, a novel cognitive test, the Loewenstein-Acevedo Scale for Semantic Interference and Learning (LASSI-L), has been developed in order to provide an early diagnosis. OBJECTIVE: To compare the diagnostic accuracy of the FCSRT and the LASSI-L for the diagnosis of AD in its preclinical and prodromal stages using 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) as a reference. METHODS: Fifty patients consulting for subjective memory complaints without functional impairment and at risk for AD were enrolled and evaluated using FCSRT, LASSI-L, and FDG-PET. Participants were evaluated using a comprehensive neurological and neuropsychological protocol and were assessed with the FCSRT and LASSI-L. FDG-PET was acquired concomitantly and used for classification of patients as AD or non-AD according to brain metabolism using both visual and semi-quantitative methods. RESULTS: LASSI-L scores allowed a better classification of patients as AD/non-AD in comparison to FCSRT. Logistic regression analysis showed delayed recall and failure to recovery from proactive semantic interference from LASSI-L as independent statistically significant predictors, obtaining an area under the curve of 0.894. This area under the curve provided a better discrimination than the best FCSRT score (total delayed recall, area under the curve 0.708, p = 0.029). CONCLUSIONS: The LASSI-L, a cognitive stress test, was superior to FCSRT in the prediction of AD features on FDG-PET. This emphasizes the possibility to advance toward an earlier diagnosis of AD from a clinical perspective.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cues; Female; Fluorodeoxyglucose F18; Humans; Male; Memory Disorders; Mental Recall; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography; Psychiatric Status Rating Scales; ROC Curve; Semantics

Complexity and Selectivity of γ-Secretase Cleavage on Multiple Substrates: Consequences in Alzheimer's Disease and Cancer. - Medoro, Alessandro; Bartollino, Silvia; Mignogna, Donatella; Passarella, Daniela; Porcile, Carola; Pagano, Aldo; Florio, Tullio; Nizzari, Mario; Guerra, Germano; Di Marco, Roberto; Intrieri, Mariano; Raimo, Gennaro; et al. (J Alzheimers Dis, 2018)
The processing of the amyloid-β protein precursor (AβPP) by β- and γ-secretases is a pivotal event in the genesis of Alzheimer's disease (AD). Besides familial mutations on the AβPP gene, or upon its overexpression, familial forms of AD are often caused by mutations or deletions in presenilin 1 (PSEN1) and 2 (PSEN2) genes: the catalytic components of the proteolytic enzyme γ-secretase (GS). The "amyloid hypothesis", modified over time, states that the aberrant processing of AβPP by GS induces the formation of specific neurotoxic soluble amyloid-β (Aβ) peptides which, in turn, cause neurodegeneration. This theory, however, has recently evidenced significant limitations and, in particular, the following issues are debated: 1) the concept and significance of presenilin's "gain of function" versus "loss of function"; and 2) the presence of several and various GS substrates, which interact with AβPP and may influence Aβ formation. The latter consideration is suggestive: despite the increasing number of GS substrates so far identified, their reciprocal interaction with AβPP itself, even in the AD field, is significantly unexplored. On the other hand, GS is also an important pharmacological target in the cancer field; inhibitors or GS activity are investigated in clinical trials for treating different tumors. Furthermore, the function of AβPP and PSENs in brain development and in neuronal migration is well known. In this review, we focused on a specific subset of GS substrates that directly interact with AβPP and are involved in its proteolysis and signaling, by evaluating their role in neurodegeneration and in cell motility or proliferation, as a possible connection between AD and cancer.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Humans; Neoplasms; Presenilin-1

Concordance Between Cerebrospinal Fluid Biomarkers with Alzheimer's Disease Pathology Between Three Independent Assay Platforms. - Doecke, James D; Rembach, Alan; Villemagne, Victor L; Varghese, Shiji; Rainey-Smith, Stephanie; Sarros, Shannon; Evered, Lisbeth A; Fowler, Christopher J; Pertile, Kelly K; Rumble, Rebecca L; Trounson, Brett; Taddei, Kevin; et al. (J Alzheimers Dis, 2018)
BACKGROUND: To enhance the accuracy of clinical diagnosis for Alzheimer's disease (AD), pre-mortem biomarkers have become increasingly important for diagnosis and for participant recruitment in disease-specific treatment trials. Cerebrospinal fluid (CSF) biomarkers provide a low-cost alternative to positron emission tomography (PET) imaging for in vivo quantification of different AD pathological hallmarks in the brains of affected subjects; however, consensus around the best platform, most informative biomarker and correlations across different methodologies are controversial. OBJECTIVE: Assessing levels of Aβ-amyloid and tau species determined using three different versions of immunoassays, the current study explored the ability of CSF biomarkers to predict PET Aβ-amyloid (32 Aβ-amyloid-and 45 Aβ-amyloid+), as well as concordance between CSF biomarker levels and PET Aβ-amyloid imaging. METHODS: Prediction and concordance analyses were performed using a sub-cohort of 77 individuals (48 healthy controls, 15 with mild cognitive impairment, and 14 with AD) from the Australian Imaging Biomarker and Lifestyle study of aging. RESULTS: Across all three platforms, the T-tau/Aβ42 ratio biomarker had modestly higher correlation with SUVR/BeCKeT (ρ= 0.69-0.8) as compared with Aβ42 alone (ρ= 0.66-0.75). Differences in CSF biomarker levels between the PET Aβ-amyloid-and Aβ-amyloid+ groups were strongest for the Aβ42/Aβ40 and T-tau/Aβ42 ratios (p < 0.0001); however, comparison of predictive models for PET Aβ-amyloid showed no difference between Aβ42 alone and the T-tau/Aβ42 ratio. CONCLUSION: This study confirms strong concordance between CSF biomarkers and PET Aβ-amyloid status is independent of immunoassay platform, supporting their utility as biomarkers in clinical practice for the diagnosis of AD and for participant enrichment in clinical trials.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognition Disorders; Female; Humans; Male; Mental Status Schedule; Peptide Fragments; Positron-Emission Tomography; ROC Curve; tau Proteins

Deep Brain Stimulation of Frontal Lobe Networks to Treat Alzheimer's Disease. - Scharre, Douglas W; Weichart, Emily; Nielson, Dylan; Zhang, Jun; Agrawal, Punit; Sederberg, Per B; Knopp, Michael V; Rezai, Ali R (J Alzheimers Dis, 2018)
The study objective was to evaluate the safety and efficacy of deep brain stimulation (DBS) at the ventral capsule/ventral striatum (VC/VS) region to specifically modulate frontal lobe behavioral and cognitive networks as a novel treatment approach for Alzheimer's disease (AD) patients. This is a non-randomized phase I prospective open label interventional trial of three subjects with matched comparison groups. AD participants given DBS for at least 18 months at the VC/VS target were compared on the Clinical Dementia Rating-Sum of Boxes (CDR-SB), our primary outcome clinical measure, to matched groups without DBS from the AD Neuroimaging Initiative (ADNI) cohort. Serial 2-Deoxy-2-[18F]fluoro-D-glucose (FDG) positron emission tomography (PET) images of AD participants were also compared longitudinally over time. Three AD DBS participants were matched to subjects from the ADNI cohort. All participants tolerated DBS well without significant adverse events. All three AD DBS participants had less performance decline and two of them meaningfully less decline over time on our primary outcome measure, CDR-SB, relative to matched comparison groups from the ADNI using score trajectory slopes. Minimal changes or increased metabolism on FDG-PET were seen in frontal cortical regions after chronic DBS at the VC/VS target. The first use of DBS in AD at a frontal lobe behavior regulation target (VC/VS) was well-tolerated and revealed less performance decline in CDR-SB. Frontal network modulation to improve executive and behavioral deficits should be furthered studied in AD.
Keywords: Aged; Alzheimer Disease; Deep Brain Stimulation; Female; Frontal Lobe; Humans; Male; Middle Aged; Ohio; Pilot Projects; Positron-Emission Tomography; Prospective Studies

Deep Brain Stimulation Targeting the Fornix for Mild Alzheimer Dementia (the ADvance Trial): A Two Year Follow-up Including Results of Delayed Activation. - Leoutsakos, Jeannie-Marie S; Yan, Haijuan; Anderson, William S; Asaad, Wael F; Baltuch, Gordon; Burke, Anna; Chakravarty, M Mallar; Drake, Kristen E; Foote, Kelly D; Fosdick, Lisa; Giacobbe, Peter; Mari, Zoltan; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Given recent challenges in developing new treatments for Alzheimer dementia (AD), it is vital to explore alternate treatment targets, such as neuromodulation for circuit dysfunction. We previously reported an exploratory Phase IIb double-blind trial of deep brain stimulation targeting the fornix (DBS-f) in mild AD (the ADvance trial). We reported safety but no clinical benefits of DBS-f versus the delayed-on (sham) treatment in 42 participants after one year. However, secondary post hoc analyses of the one-year data suggested a possible DBS-f benefit for participants≥65 years. OBJECTIVE: To examine the long-term safety and clinical effects of sustained and delayed-on DBS-f treatment of mild AD after two years. METHODS: 42 participants underwent implantation of DBS-f electrodes, with half randomized to active DBS-f stimulation (early on) for two years and half to delayed-on (sham) stimulation after 1 year to provide 1 year of active DBS-f stimulation (delayed on). We evaluated safety and clinical outcomes over the two years of the trial. RESULTS: DBS-f had a favorable safety profile with similar rates of adverse events across both trial phases (years 1 and 2) and between treatment arms. There were no differences between treatment arms on any primary clinical outcomes. However, post-hoc age group analyses suggested a possible benefit among older (>65) participants. CONCLUSION: DBS-f was safe. Additional study of mechanisms of action and methods for titrating stimulation parameters will be needed to determine if DBS has potential as an AD treatment. Future efficacy studies should focus on patients over age 65.

Deficits in Regional Cerebral Blood Flow on Brain SPECT Predict Treatment Resistant Depression. - Amen, Daniel G; Taylor, Derek V; Meysami, Somayeh; Raji, Cyrus A (J Alzheimers Dis, 2018)
BACKGROUND: Depression remains an important risk factor for Alzheimer's disease, yet few neuroimaging biomarkers are available to identify treatment response in depression. OBJECTIVE: To analyze and compare functional perfusion neuroimaging in persons with treatment resistant depression (TRD) compared to those experiencing full remission. METHODS: A total of 951 subjects from a community psychiatry cohort were scanned with perfusion single photon emission computed tomography (SPECT) of the brain in both resting and task related settings. Of these, 78% experienced either full remission (n = 506) or partial remission (n = 237) and 11% were minimally responsive (n = 103) or non-responsive (11%. n = 106). Severity of depression symptoms were used to define these groups with changes in the Beck Depression Inventory prior to and following treatment. Voxel-based analyses of brain SPECT images from full remission compared to the worsening group was conducted with the statistical parametric mapping software, version 8 (SPM 8). Multiple comparisons were accounted for with a false discovery rate (p < 0.001). RESULTS: Persons with depression that worsened following treatment had reduced cerebral perfusion compared to full remission in the multiple regions including the bilateral frontal lobes, right hippocampus, left precuneus, and cerebellar vermis. Such differences were observed on both resting and concentration SPECT scans. CONCLUSION: Our findings identify imaging-based biomarkers in persons with depression related to treatment response. These findings have implications in understanding both depression to prognosis and its role as a risk factor for dementia.

Depression and Alzheimer's Disease Biomarkers Predict Driving Decline. - Babulal, Ganesh M; Chen, Suzie; Williams, Monique M; Trani, Jean-Francois; Bakhshi, Parul; Chao, Grace L; Stout, Sarah H; Fagan, Anne M; Benzinger, Tammie L S; Holtzman, David M; Morris, John C; Roe, Catherine M (J Alzheimers Dis, 2018)
BACKGROUND: Symptomatic Alzheimer's disease (AD) and depression independently increase crash risk. Additionally, depression is both a risk factor for and a consequence of AD. OBJECTIVE: To examine whether a depression diagnosis, antidepressant use, and preclinical AD are associated with driving decline among cognitively normal older adults. METHODS: Cognitively normal participants, age ≥65, were enrolled. Cox proportional hazards models evaluated whether a depression diagnosis, depressive symptoms (Geriatric Depression Scale), antidepressant use, cerebrospinal fluid (amyloid-β42 [Aβ42], tau, phosphorylated tau181 [ptau181]), and amyloid imaging biomarkers (Pittsburgh Compound B and Florbetapir) were associated with time to receiving a rating of marginal/fail on a road test. Age was adjusted for in all models. RESULTS: Data were available from 131 participants with age ranging from 65.4 to 88.2 years and mean follow up of 2.4 years (SD = 1.0). A depression diagnosis was associated with a faster time to receiving a marginal/fail rating on a road test and antidepressant use (p = 0.024, HR = 2.62). Depression diagnosis and CSF and amyloid PET imaging biomarkers were associated with driving performance on the road test (p≤0.05, HR = 2.51-3.15). In the CSF ptau181 model, depression diagnosis (p = 0.031, HR = 2.51) and antidepressant use (p = 0.037, HR = 2.50) were statistically significant predictors. There were no interaction effects between depression diagnosis, antidepressant use, and biomarker groups. Depressive symptomology was not a statistically significant predictor of driving performance. CONCLUSIONS: While, as previously shown, preclinical AD alone predicts a faster time to receiving a marginal/fail rating, these results suggest that also having a diagnosis of depression accelerates the onset of driving problems in cognitively normal older adults.

Depressive Symptoms Are Associated with Cognitive Function in the Elderly with Type 2 Diabetes. - Guerrero-Berroa, Elizabeth; Ravona-Springer, Ramit; Schmeidler, James; Heymann, Anthony; Soleimani, Laili; Sano, Mary; Leroith, Derek; Preiss, Rachel; Zukran, Ruth; Silverman, Jeremy M; Beeri, Michal Schnaider (J Alzheimers Dis, 2018)
BACKGROUND: Type 2 diabetes (T2D) is a metabolic condition associated with poor clinical and cognitive outcomes including vascular disease, depressive symptoms, cognitive impairment, and dementia. In the general elderly population, depression has been consistently identified as a risk factor for cognitive impairment/decline. However, the association between depression and cognitive function in T2D has been understudied. OBJECTIVE: We investigated the association between depression and cognitive function in a large sample of cognitively normal elderly with T2D. METHODS: In this cross-sectional study, we examined 738 participants, aged 65-88 years old, enrolled in the Israel Diabetes and Cognitive Decline study. For each cognitive domain (Episodic Memory, Executive Function, Attention/Working Memory, Language/Semantic Categorization) and Overall Cognition, multiple linear regressions assessed its association with depression (score greater than 5 on the 15-item version of the Geriatric Depression Scale [GDS]), adjusting for age, sex, and education. RESULTS: Depression (n = 66, 8.9%) was associated with worse performance on tasks of Executive Function (p = 0.004), Language/Semantic Categorization (p < 0.001), and Overall Cognition (p < 0.002), but not Episodic Memory (p = 0.643) or Attention/Working Memory (p = 0.488). Secondary analyses using GDS as a continuous variable did not substantially change the results. Adjusting also for a history of antidepressant medication use slightly weakened the findings. CONCLUSION: Significant associations of depression with several cognitive domains and Overall Cognition even in cognitively normal elderly with T2D, suggest that depression may have a role in impaired cognitive function in T2D, which may be attenuated by antidepressants.

Designing an Internet-Based Multidomain Intervention for the Prevention of Cardiovascular Disease and Cognitive Impairment in Older Adults: The HATICE Trial. - Barbera, Mariagnese; Mangialasche, Francesca; Jongstra, Susan; Guillemont, Juliette; Ngandu, Tiia; Beishuizen, Cathrien; Coley, Nicola; Brayne, Carol; Andrieu, Sandrine; Richard, Edo; Soininen, Hilkka; Kivipelto, Miia (J Alzheimers Dis, 2018)
BACKGROUND: Many dementia and cardiovascular disease (CVD) cases in older adults are attributable to modifiable vascular and lifestyle-related risk factors, providing opportunities for prevention. In the Healthy Aging Through Internet Counselling in the Elderly (HATICE) randomized controlled trial, an internet-based multidomain intervention is being tested to improve the cardiovascular risk (CVR) profile of older adults. OBJECTIVE: To design a multidomain intervention to improve CVR, based on the guidelines for CVR management, and administered through a coach-supported, interactive, platform to over 2500 community-dwellers aged 65+ in three European countries. METHODS: A comparative analysis of national and European guidelines for primary and secondary CVD prevention was performed. Results were used to define the content of the intervention. RESULTS: The intervention design focused on promoting awareness and self-management of hypertension, dyslipidemia, diabetes mellitus, and overweight, and supporting smoking cessation, physical activity, and healthy diet. Overall, available guidelines lacked specific recommendations for CVR management in older adults. The comparative analysis of the guidelines showed general consistency for lifestyle-related recommendations. Key differences, identified mostly in methods used to assess the overall CVR, did not hamper the intervention design. Minor country-specific adaptations were implemented to maximize the intervention feasibility in each country. CONCLUSION: Despite differences in CVR management within the countries considered, it was possible to design and implement the HATICE multidomain intervention. The study can help define preventative strategies for dementia and CVD that are applicable internationally.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cognitive Dysfunction; Counseling; Europe; Exercise; Female; Healthy Aging; Humans; Internet; Life Style; Male; Practice Guidelines as Topic; Risk Factors; Telemedicine

Detection of Dementia Cases in Two Swedish Health Registers: A Validation Study. - Rizzuto, Debora; Feldman, Adina L; Karlsson, Ida K; Dahl Aslan, Anna K; Gatz, Margaret; Pedersen, Nancy L (J Alzheimers Dis, 2018)
BACKGROUND: Population-based health registers are potential assets in epidemiological research; however, the quality of case ascertainment is crucial. OBJECTIVE: To compare the case ascertainment of dementia, from the National Patient Register (NPR) and the Cause of Death Register (CDR) with dementia diagnoses from six Swedish population based studies. METHODS: Sensitivity, specificity, and positive predictive value (PPV) of dementia identification in NPR and CDR were estimated by individual record linkage with six Swedish population based studies (n = 19,035). Time to detection in NPR was estimated using data on dementia incidence from longitudinal studies with more than two decades of follow-up. RESULTS: Barely half of the dementia cases were ever detected by NPR or CDR. Using data from longitudinal studies we estimated that a record with a dementia diagnosis appears in the NPR on average 5.5 years after first diagnosis. Although the ability of the registers to detect dementia cases was moderate, the ability to detect non-dementia cases was almost perfect (99%). When registers indicate that there is a dementia diagnosis, there are very few instances in which the clinicians determined the person was not demented. Indeed, PPVs were close to 90%. However, misclassification between dementia subtype diagnoses is quite common, especially in NPR. CONCLUSIONS: Although the overall sensitivity is low, the specificity and the positive predictive value are very high. This suggests that hospital and death registers can be used to identify dementia cases in the community, but at the cost of missing a large proportion of the cases.
Keywords: Aged; Aged, 80 and over; Cause of Death; Dementia; Female; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Registries; Sensitivity and Specificity; Sweden; Twin Studies as Topic

Diagnosis of Mild Cognitive Impairment Due to Alzheimer's Disease with Transcranial Magnetic Stimulation. - Padovani, Alessandro; Benussi, Alberto; Cantoni, Valentina; Dell'Era, Valentina; Cotelli, Maria Sofia; Caratozzolo, Salvatore; Turrone, Rosanna; Rozzini, Luca; Alberici, Antonella; Altomare, Daniele; Depari, Alessandro; Flammini, Alessandra; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Considering the increasing evidence that disease-modifying treatments for Alzheimer's disease (AD) must be administered early in the disease course, the development of diagnostic tools capable of accurately identifying AD at early disease stages has become a crucial target. In this view, transcranial magnetic stimulation (TMS) has become an effective tool to discriminate between different forms of neurodegenerative dementia. OBJECTIVE: To determine whether a TMS multi-paradigm approach can be used to correctly identify mild cognitive impairment (MCI) due to AD (AD MCI). METHODS: A sample of 69 subjects with MCI were included and classified as AD MCI or MCI unlikely due to AD (non-AD MCI) based on 1) extensive neurological and neuropsychological evaluation, 2) MRI imaging, and 3) cerebrospinal fluid analysis or/and amyloid PET imaging. A paired-pulse TMS multi-paradigm approach assessing short interval intracortical inhibition-facilitation (SICI-ICF), dependent on GABAergic and glutamatergic intracortical circuits, respectively, and short latency afferent inhibition (SAI), dependent on cholinergic circuits, was performed. RESULTS: We observed a significant impairment of SAI and unimpaired SICI and ICF in AD MCI as compared to non-AD MCI. According to ROC curve analysis, the SICI-ICF / SAI index differentiated AD MCI from non-AD MCI with a specificity of 87.9% and a sensitivity of 94.4%. CONCLUSIONS: The assessment of intracortical connectivity with TMS could aid in the characterization of MCI subtypes, correctly identifying AD pathophysiology. TMS can be proposed as an adjunctive, non-invasive, inexpensive, and time-saving screening tool in MCI differential diagnosis.

Diaphanous 1 (DIAPH1) is Highly Expressed in the Aged Human Medial Temporal Cortex and Upregulated in Myeloid Cells During Alzheimer's Disease. - Derk, Julia; Bermudez Hernandez, Keria; Rodriguez, Moises; He, Meilun; Koh, Hyunwook; Abedini, Andisheh; Li, Huilin; Fenyö, David; Schmidt, Ann Marie (J Alzheimers Dis, 2018)
BACKGROUND: The receptor for advanced glycation end products (RAGE) is linked to cellular stress and inflammation during Alzheimer's disease (AD). RAGE signals through Diaphanous-1 (DIAPH1); however, the expression of DIAPH1 in the healthy and AD human brain has yet to be methodically addressed. OBJECTIVE: To delineate the cell- and disease-state specific expression of DIAPH1 in the human medial temporal cortex during healthy aging and AD. METHODS: We used semi-quantitative immunohistochemistry in the human medial temporal cortex paired with widefield and confocal microscopy and automated analyses to determine colocalization and relative expression of DIAPH1 with key cell markers and molecules in the brains of subjects with AD versus age-matched controls. RESULTS: We report robust colocalization of DIAPH1 with myeloid cells and increased expression during AD, which strongly correlated to increased neutral lipids and morphology of inflamed myeloid cells. DIAPH1 moderately colocalized with markers of endothelial cells, astrocytes, neurons, and oligodendrocytes. DISCUSSION: Our findings localize DIAPH1 particularly to myeloid cells in the CNS, especially in AD in the locations of lipid droplet accumulation, thereby implicating RAGE-DIAPH1 signaling in dysregulated lipid metabolism and morphological changes of inflamed myeloid cells in this disorder.

Diazepam Toxicity Presenting as a Dementia Disorder. - Kurlawala, Zimple; Roberts, Jeffrey A; McMillan, Joseph D; Friedland, Robert P (J Alzheimers Dis, 2018)
The toxicity associated with long-standing benzodiazepine use in older persons is a critical issue. Several epidemiological reports have studied correlation between benzodiazepine use and risk of dementia development. In this manuscript, we used a case report to demonstrate how chronic diazepam use can cause cognitive deficits that resemble Alzheimer's disease and related conditions. Benzodiazepine use is common in the geriatric population and is often taken for long periods of time in improper doses. In combination with age-related cortical atrophy on the MRI, our patient risked being misdiagnosed with Alzheimer's disease or another dementing disorder if not for the systematic investigation to resolve his symptoms. With elimination of the offending dispensable drug (diazepam), the patient's cognition improved greatly.

Differences Between Women and Men in Incidence Rates of Dementia and Alzheimer's Disease. - Beam, Christopher R; Kaneshiro, Cody; Jang, Jung Yun; Reynolds, Chandra A; Pedersen, Nancy L; Gatz, Margaret (J Alzheimers Dis, 2018)
In the following brief report, we examined gender differences in incidence rates of any dementia, Alzheimer's disease (AD) alone, and non-Alzheimer's dementia alone in 16,926 women and men in the Swedish Twin Registry aged 65+. Dementia diagnoses were based on clinical workup and national health registry linkage. Incidence rates of any dementia and AD were greater in women than men, with any dementia rates diverging after age 85 and AD rates diverging around 80. This pattern is consistent with women's survival to older ages compared to men. These findings are similar to incidence rates reported in other Swedish samples.

Differentiating between Alzheimer's Disease and Vascular Cognitive Impairment: Is the "Memory Versus Executive Function" Contrast Still Relevant? - Andriuta, Daniela; Roussel, Martine; Barbay, Mélanie; Despretz-Wannepain, Sandrine; Godefroy, Olivier (J Alzheimers Dis, 2018)
BACKGROUND: The contrast between memory versus executive function impairments is commonly used to differentiate between neurocognitive disorders (NCDs) due to Alzheimer's disease (AD) and vascular cognitive impairment (VCI). We reconsidered this question because of the current use of AD biomarkers and the recent revision of the criteria for AD, VCI, and dysexecutive syndrome. OBJECTIVE: To establish and compare the neuropsychological profiles in AD (i.e., with positive CSF biomarkers) and in VCI. METHODS: We included 62 patients with mild or major NCDs due to pure AD (with positive CSF biomarker assays), and 174 patients (from the GRECogVASC cohort) with pure VCI. The neuropsychological profiles were compared after stratification for disease severity (mild or major NCD). We defined a memory-executive function index (the mean z score for the third free recall and the delayed free recall in the Free and Cued Selective Reminding Test minus the mean z score for category fluency and the completion time in the Trail Making Test part B) and determined its diagnostic accuracy. RESULTS: Compared with VCI patients, patients with AD had significantly greater memory impairments (p = 0.001). Executive function was impaired to a similar extent in the two groups (p = 0.11). Behavioral executive disorders were more prominent in the AD group (p = 0.001). Although the two groups differed significant with regard to the memory-executive function index (p < 0.001), the latter's diagnostic accuracy was only moderate (sensitivity: 63%, specificity: 87%). CONCLUSION: Although the contrast between memory and executive function impairments was supported at the group level it does not reliably discriminate between AD and VCI at the individual level.

Dipeptidyl-Peptidase Activity of Meprin β Links N-truncation of Aβ with Glutaminyl Cyclase-Catalyzed pGlu-Aβ Formation. - Schlenzig, Dagmar; Cynis, Holger; Hartlage-Rübsamen, Maike; Zeitschel, Ulrike; Menge, Katja; Fothe, Anja; Ramsbeck, Daniel; Spahn, Claudia; Wermann, Michael; Roßner, Steffen; Buchholz, Mirko; Schilling, Stephan; et al. (J Alzheimers Dis, 2018)
The formation of amyloid-β (Aβ) peptides is causally involved in the development of Alzheimer's disease (AD). A significant proportion of deposited Aβ is N-terminally truncated and modified at the N-terminus by a pGlu-residue (pGlu-Aβ). These forms show enhanced neurotoxicity compared to full-length Aβ. Although the truncation may occur by aminopeptidases after formation of Aβ, recently discovered processing pathways of amyloid-β protein precursor (AβPP) by proteases such as meprin β may also be involved. Here, we assessed a role of meprin β in forming Aβ3-40/42, which is the precursor of pGlu-Aβ3-40/42 generated by glutaminyl cyclase (QC). Similar to QC, meprin β mRNA is significantly upregulated in postmortem brain from AD patients. A histochemical analysis supports the presence of meprin β in neurons and astrocytes in the vicinity of pGlu-Aβ containing deposits. Cleavage of AβPP-derived peptides by meprin β in vitro results in peptides Aβ1-x, Aβ2-x, and Aβ3-x. The formation of N-truncated Aβ by meprin β was also corroborated in cell culture. A subset of the generated peptides was converted into pGlu-Aβ3-40 by an addition of glutaminyl cyclase, supporting the preceding formation of Aβ3-40. Further analysis of the meprin β cleavage revealed a yet unknown dipeptidyl-peptidase-like activity specific for the N-terminus of Aβ1-x. Thus, our data suggest that meprin β contributes to the formation of N-truncated Aβ by endopeptidase and exopeptidase activity to generate the substrate for QC-catalyzed pGlu-Aβ formation.

Distinct Neuroanatomical Correlates of Neuropsychiatric Symptoms in the Three Main Forms of Genetic Frontotemporal Dementia in the GENFI Cohort. - Sellami, Leila; Bocchetta, Martina; Masellis, Mario; Cash, David M; Dick, Katrina M; van Swieten, John; Borroni, Barbara; Galimberti, Daniela; Tartaglia, Maria Carmela; Rowe, James B; Graff, Caroline; Tagliavini, Fabrizio; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The overlap between frontotemporal dementia (FTD) and primary psychiatric disorders has been brought to light by reports of prominent neuropsychiatric symptoms (NPS) in FTD-related genetic mutations, particularly among C9orf72 and GRN carriers. It has been recently demonstrated that early neuroanatomical changes in genetic FTD may be different across the major disease-causing mutations. OBJECTIVE: We aimed to identify whether NPS could be driven by distinct structural correlates. METHODS: One hundred and sixty-seven mutation carriers (75 GRN, 60 C9orf72, and 32 MAPT) were included from the Genetic FTD Initiative (GENFI) study, a large international cohort of genetic FTD. Neuropsychiatric symptoms including delusions, hallucinations (visual, auditory, and tactile), depression, and anxiety were investigated using a structured interview. Voxel-based morphometry was performed to identify neuroanatomical correlates of NPS. RESULTS: Psychotic symptoms correlated mainly with grey matter (GM) atrophy in the anterior insula, left thalamus, cerebellum, and cortical regions including frontal, parietal, and occipital lobes in GRN mutations carriers. GM atrophy in posterior structures of the default-mode network was associated with anxiety in the GRN group. Delusions in C9orf72 expansion carriers were mainly associated with left frontal cortical atrophy. Cerebellar atrophy was found to be correlated only with anxiety in C9orf72 carriers. NPS in the MAPT group were mainly associated with volume loss in the temporal lobe. CONCLUSION: Neuroanatomical correlates of NPS appear to be distinct across the main forms of genetic FTD. Overall, our findings support overlapping brain structural changes between FTD and primary psychiatric disorders.

Dual-Task Gait and Alzheimer's Disease Genetic Risk in Cognitively Normal Adults: A Pilot Study. - Whitson, Heather E; Potter, Guy G; Feld, Jody A; Plassman, Brenda L; Reynolds, Kelly; Sloane, Richard; Welsh-Bohmer, Kathleen A (J Alzheimers Dis, 2018)
BACKGROUND: Dual-task paradigms, in which an individual performs tasks separately and then concurrently, often demonstrate that people with neurodegenerative disorders experience more dual-task interference, defined as worse performance in the dual-task condition compared to the single-task condition. OBJECTIVE: To examine how gait-cognition dual-task performance differs between cognitively normal older adults with and without an APOE ɛ4 allele. METHODS: Twenty-nine individuals ages 60 to 72 with normal cognition completed a dual-task protocol in which walking and cognitive tasks (executive function, memory) were performed separately and concurrently. Fourteen participants carried APOE ɛ4 alleles (ɛ3/ɛ4 or ɛ2/ɛ4); fifteen had APOE genotypes (ɛ2/ɛ2, ɛ2/ɛ3, or ɛ3/ɛ3) associated with lower risk of Alzheimer's disease (AD). RESULTS: The two risk groups did not differ by age, sex, race, education, or gait or cognitive measures under single-task conditions. Compared to low risk participants, APOE ɛ4 carriers tended to exhibit greater dual-task interference. Both the memory and executive function tasks resulted in dual-task interference on gait, but effect sizes for a group difference were larger when the cognitive task was executive function. In the dual-task protocol that combined walking and the executive function task, effect sizes for group difference in gait interference were larger (0.62- 0.70) than for cognitive interference (0.45- 0.47). DISCUSSION: Dual-task paradigms may reveal subtle changes in brain function in asymptomatic individuals at heightened risk of AD.

Early Detection of Alzheimer's Disease Based on the Patient's Creative Drawing Process: First Results with a Novel Neuropsychological Testing Method. - Heymann, Petra; Gienger, Regine; Hett, Andreas; Müller, Stephan; Laske, Christoph; Robens, Sibylle; Ostermann, Thomas; Elbing, Ulrich (J Alzheimers Dis, 2018)
Based on the knowledge of art therapy, we developed a new neuropsychological drawing test in order to identify individuals with mild cognitive impairment (MCI) as well as dementia patients and healthy controls (HC). By observing a variety of drawing characteristics of 92 participants with a mean age of 67.7, art therapy and dementia experts discriminate HC from MCI, early dementia of the Alzheimer-type (eDAT), and moderate dementia of the Alzheimer-type (mDAT) by the process analysis of tree drawings on a digitizing tablet. The art therapist's average categorical rating of healthy and MCI or demented individuals matched the clinical diagnosis by 88%. In a first small study, we analyzed interrater reliability, sensitivity, specificity, negative and positive predicted values of our tree drawing test (TDT) in comparison with the clock drawing test (CDT). Similar values of moderate interrater reliability were found for the TDT (0.56) as well as for the CDT (0.54). A significant high sensitivity of 0.9 within this binary impairment scale (HC versus impaired or demented) can be demonstrated. Substantial values for the specificity (0.67) could be obtained that however remain under a perfect value of the CDT (1.0). Considering 31 individuals that received the clinical diagnosis "impaired or demented" the TDT shows a higher recognition rate for the MCI group than the CDT. Furthermore in 8 of 12 borderline cases of clinical diagnosis, the outcome of the TDT diagnosis was consistent with the final clinical result.

Early Intervention with a Multi-Ingredient Dietary Supplement Improves Mood and Spatial Memory in a Triple Transgenic Mouse Model of Alzheimer's Disease. - Hutton, Craig P; Lemon, Jennifer A; Sakic, Boris; Rollo, C David; Boreham, Douglas R; Fahnestock, Margaret; Wojtowicz, J Martin; Becker, Suzanna (J Alzheimers Dis, 2018)
The increasing global burden of Alzheimer's disease (AD) and failure of conventional treatments to stop neurodegeneration necessitates an alternative approach. Evidence of inflammation, mitochondrial dysfunction, and oxidative stress prior to the accumulation of amyloid-β in the prodromal stage of AD (mild cognitive impairment; MCI) suggests that early interventions which counteract these features, such as dietary supplements, may ameliorate the onset of MCI-like behavioral symptoms. We administered a polyphenol-containing multiple ingredient dietary supplement (MDS), or vehicle, to both sexes of triple transgenic (3xTg-AD) mice and wildtype mice for 2 months from 2-4 months of age. We hypothesized that the MDS would preserve spatial learning, which is known to be impaired in untreated 3xTg-AD mice by 4 months of age. Behavioral phenotyping of animals was done at 1-2 and 3-4 months of age using a comprehensive battery of tests. As previously reported in males, both sexes of 3xTg-AD mice exhibited increased anxiety-like behavior at 1-2 months of age, prior to deficits in learning and memory, which did not appear until 3-4 months of age. The MDS did not reduce this anxiety or prevent impairments in novel object recognition (both sexes) or on the water maze probe trial (females only). Strikingly, the MDS specifically prevented 3xTg-AD mice (both sexes) from developing impairments (exhibited by untreated 3xTg-AD controls) in working memory and spatial learning. The MDS also increased sucrose preference, an indicator of hedonic tone. These data show that the MDS can prevent some, but not all, psychopathology in an AD model.

The Effects and Meanings of Receiving a Diagnosis of Mild Cognitive Impairment or Alzheimer's Disease When One Lives Alone. - Portacolone, Elena; Johnson, Julene K; Covinsky, Kenneth E; Halpern, Jodi; Rubinstein, Robert L (J Alzheimers Dis, 2018)
BACKGROUND: One third of older adults with cognitive impairment live alone and are at high risk for poor health outcomes. Little is known about how older adults who live alone experience the process of receiving a diagnosis of mild cognitive impairment (MCI) or Alzheimer's disease (AD). OBJECTIVE: The aim of this study was to understand the effects and meanings of receiving a diagnosis of MCI or AD on the lived experience of older adults living alone. METHODS: This is a qualitative study of adults age 65 and over living alone with cognitive impairment. Participants' lived experiences were elicited through ethnographic interviews and participant observation in their homes. Using a qualitative content analysis approach, interview transcripts and fieldnotes were analyzed to identify codes and themes. RESULTS: Twenty-nine older adults and 6 members of their social circles completed 114 ethnographic interviews. Core themes included: relief, distress, ambiguous recollections, and not knowing what to do. Participants sometimes felt uplifted and relieved by the diagnostic process. Some participants did not mention having received a diagnosis or had only partial recollections about it. Participants reported that, as time passed, they did not know what to do with regard to the treatment of their condition. Sometimes they also did not know how to prepare for a likely worsening of their condition, which they would experience while living alone. CONCLUSION: Findings suggest the need for more tailored care and follow-up as soon as MCI or AD is diagnosed in persons living alone.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Emotions; Female; Health Services; Humans; Interviews as Topic; Male; Residence Characteristics; Single Person

Endocannabinoid and Muscarinic Signaling Crosstalk in the 3xTg-AD Mouse Model of Alzheimer's Disease. - Llorente-Ovejero, Alberto; Manuel, Iván; Lombardero, Laura; Giralt, Maria Teresa; Ledent, Catherine; Giménez-Llort, Lydia; Rodríguez-Puertas, Rafael (J Alzheimers Dis, 2018)
The endocannabinoid system, which modulates emotional learning and memory through CB1 receptors, has been found to be deregulated in Alzheimer's disease (AD). AD is characterized by a progressive decline in memory associated with selective impairment of cholinergic neurotransmission. The functional interplay of endocannabinoid and muscarinic signaling was analyzed in seven-month-old 3xTg-AD mice following the evaluation of learning and memory of an aversive stimulus. Neurochemical correlates were simultaneously studied with both receptor and functional autoradiography for CB1 and muscarinic receptors, and regulations at the cellular level were depicted by immunofluorescence. 3xTg-AD mice exhibited increased acquisition latencies and impaired memory retention compared to age-matched non-transgenic mice. Neurochemical analyses showed changes in CB1 receptor density and functional coupling of CB1 and muscarinic receptors to Gi/o proteins in several brain areas, highlighting that observed in the basolateral amygdala. The subchronic (seven days) stimulation of the endocannabinoid system following repeated WIN55,212-2 (1 mg/kg) or JZL184 (8 mg/kg) administration induced a CB1 receptor downregulation and CB1-mediated signaling desensitization, normalizing acquisition latencies to control levels. However, the observed modulation of cholinergic neurotransmission in limbic areas did not modify learning and memory outcomes. A CB1 receptor-mediated decrease of GABAergic tone in the basolateral amygdala may be controlling the limbic component of learning and memory in 3xTg-AD mice. CB1 receptor desensitization may be a plausible strategy to improve behavior alterations associated with genetic risk factors for developing AD.

Endogenous Murine Amyloid-β Peptide Assembles into Aggregates in the Aged C57BL/6J Mouse Suggesting These Animals as a Model to Study Pathogenesis of Amyloid-β Plaque Formation. - Ahlemeyer, Barbara; Halupczok, Sascha; Rodenberg-Frank, Elke; Valerius, Klaus-Peter; Baumgart-Vogt, Eveline (J Alzheimers Dis, 2018)
Amyloid-β peptide (Aβ), paired helical filament-tau (PHF-tau), and α-synuclein are in the focus of neuroscience research because they aggregate in brains of patients with Alzheimer's and Parkinson's diseases. For this purpose, transgenic mouse models were used containing the human genes for AβPP/presenilin/tau or α-synuclein with the most frequent mutations. This is not ideal because most patients develop sporadic forms of the diseases with no causative single gene defect and furthermore the aggregation of human proteins in man is not necessarily the same in rodents. We hypothesized that for such cases the aged mouse could be an alternative model and analyzed the distribution of endogenous Aβ, PHF-tau, and α-synuclein in mouse brains at different ages. Whereas Aβ was below detectable levels at birth, it was present at high levels in the 15-month-old mouse. Aβ was found in the cytosol and lysosomes of neurons of the temporal cortex, cingulate area, pons, and cerebellum as well as extracellularly in the periventricular zone. Contrary to Aβ, mouse brain was devoid of PHF-tau-positive neurofibrillary tangles. α-Synuclein was detectable in the newborn mouse with highest levels in the marginal zone of the lateral cortex and average levels in the hippocampus, pons, and cerebellum. Brain-area specific differences in the α-synuclein level persisted up to 15 months of age, but increased 3-fold in all areas over time. α-Synuclein resided in the neuropil, but not in intracellular aggregates even in the aged mouse. We suggest the aged mouse as a model to study Aβ plaque formation.
Keywords: Age Factors; Aged; Aged, 80 and over; alpha-Synuclein; Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Disease Models, Animal; Female; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Neurofibrillary Tangles; Neurons; Plaque, Amyloid; tau Proteins

Epigenetic Drug Repositioning for Alzheimer's Disease Based on Epigenetic Targets in Human Interactome. - Chatterjee, Paulami; Roy, Debjani; Rathi, Nitin (J Alzheimers Dis, 2018)
BACKGROUND: Epigenetics has emerged as an important field in drug discovery. Alzheimer's disease (AD), the leading neurodegenerative disorder throughout the world, is shown to have an epigenetic basis. Currently, there are very few effective epigenetic drugs available for AD. OBJECTIVE: In this work, for the first time we have proposed 14 AD repositioning epigenetic drugs and identified their targets from extensive human interactome. METHODS: Interacting partners of the AD epigenetic proteins were identified from the extensive human interactome to construct Epigenetic Protein-Protein Interaction Network (EP-PPIN). Epigenetic Drug-Target Network (EP-DTN) was constructed with the drugs associated with the proteins of EP-PPIN. Regulation of non-coding RNAs associated with the target proteins of these drugs was also studied. AD related target proteins, epigenetic targets, enriched pathways, and functional categories of the proposed repositioning drugs were also studied. RESULTS: The proposed 14 AD epigenetic repositioning drugs have overlapping targets and miRs with known AD epigenetic targets and miRs. Furthermore, several shared functional categories and enriched pathways were obtained for these drugs with FDA approved epigenetic drugs and known AD drugs. CONCLUSIONS: The findings of our work might provide insight into future AD epigenetic-therapeutics.
Keywords: Alzheimer Disease; Antipsychotic Agents; Computational Biology; Drug Repositioning; Epigenesis, Genetic; Epigenomics; Humans; MicroRNAs; Protein Interaction Maps; PubMed

Episodic Memory and Learning Dysfunction Over an 18-Month Period in Preclinical and Prodromal Alzheimer's Disease. - Baker, Jenalle E; Lim, Yen Ying; Jaeger, Judith; Ames, David; Lautenschlager, Nicola T; Robertson, Joanne; Pietrzak, Robert H; Snyder, Peter J; Villemagne, Victor L; Rowe, Christopher C; Masters, Colin L; Maruff, Paul (J Alzheimers Dis, 2018)
Recent meta-analyses suggest that episodic memory impairment associated with preclinical Alzheimer's disease (AD) equates to 0.15-0.24 standard deviations below that of cognitively healthy older adults. The current study aimed to characterize impairments in verbal acquisition and recall detectable at a single assessment, and investigate how verbal learning and episodic memory deteriorates in preclinical AD. A verbal list-learning task, the International Shopping List Test (ISLT), was administered multiple times over an 18-month period, to three groups of participants: amyloid-beta negative healthy older adults (Aβ- CN; n = 50); Aβ+ positive healthy older adults (preclinical AD; n = 25); and Aβ+ positive individuals diagnosed with mild cognitive impairment (prodromal AD; n = 22). At baseline, there was no significant difference between the preclinical AD and control groups rate of acquisition, or total and delayed recall, however all indices were impaired in prodromal AD. Performance on ISLT total score improved in the control group over the 18-month period, but showed a moderate magnitude decline in the preclinical AD group (Cohen's d = - 0.63, [- 1.12, - 0.14]) and the prodromal AD group (Cohen's d = - 0.36, [- 0.94, 0.22]). No significant impairment in acquisition associated with preclinical AD was seen at baseline. Individuals with preclinical AD showed a significantly different performance on the ISLT total score over an 18-month period, compared to those without abnormal Aβ. Individuals with prodromal AD showed substantial impairment on the ISLT at baseline and declined to a greater extent over time.

Epitomic Characterization of the Specificity of the Anti-Amyloid Aβ Monoclonal Antibodies 6E10 and 4G8. - Baghallab, Ibtisam; Reyes-Ruiz, Jorge Mauricio; Abulnaja, Khalid; Huwait, Etimad; Glabe, Charles (J Alzheimers Dis, 2018)
The monoclonal antibodies 6E10 and 4G8 are among the first anti-amyloid monoclonal antibodies against Aβ and the most widely used antibodies in Alzheimer's disease research. Although the epitopes for 6E10 and 4G8 have been reported to correspond to residues 1-16 and 17-24, a more recent high-resolution mapping approach indicates that 6E10 maps to residues 4-10 while 4G8 maps to residues 18-23. To characterize the binding specificity of both antibodies in greater detail, we used immunoselection of random sequences from phage display library followed by deep sequencing and analysis of resulting patterns from thousands of immunoselected sequences. We found that the minimum sequence required for 6E10 binding is R-x-D with over half (53%) of the immunoselected sequences conforming to this pattern. The vast majority of these sequences contain an H at position x (R-H-D), corresponding to residues 5-7 of the Aβ target sequences, but Y is also permitted at this position in a minority of sequences. For 4G8 we found that the most frequent pattern is F-x-A contained in approximately 30% of the sequences, followed by F-A, L-x(3)-A, L-x-F, and F-F each accounting for approximately 18% of the sequences. The F-x-A motif also occurs in islet amyloid poly peptide which may explain why 4G8 also recognizes amyloid fibrils of this peptide. Immunoselection of random sequences and deep sequencing may also be a facile and efficient means of determining residues critical for antibody binding and validating the specificity of monoclonal antibodies and polyclonal antisera.

Erythromyeloid-Derived TREM2: A Major Determinant of Alzheimer's Disease Pathology in Down Syndrome. - Raha-Chowdhury, Ruma; Henderson, James W; Raha, Animesh Alexander; Stott, Simon R W; Vuono, Romina; Foscarin, Simona; Wilson, Liam; Annus, Tiina; Fincham, Robert; Allinson, Kieren; Devalia, Vinod; Friedland, Robert P; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Down syndrome (DS; trisomy 21) individuals have a spectrum of hematopoietic and neuronal dysfunctions and by the time they reach the age of 40 years, almost all develop Alzheimer's disease (AD) neuropathology which includes senile plaques and neurofibrillary tangles. Inflammation and innate immunity are key players in AD and DS. Triggering receptor expressed in myeloid cells-2 (TREM2) variants have been identified as risk factors for AD and other neurodegenerative diseases. OBJECTIVE: To investigate the effects of TREM2 and the AD-associated R47H mutation on brain pathology and hematopoietic state in AD and DS. METHODS: We analyzed peripheral blood, bone marrow, and brain tissue from DS, AD, and age-matched control subjects by immunohistochemistry and western blotting. TREM2-related phagocytosis was investigated using a human myeloid cell line. RESULTS: TREM2 protein levels in brain and sera declined with age and disease progression in DS. We observed soluble TREM2 in brain parenchyma that may be carried by a subset of microglia, macrophages, or exosomes. Two DS cases had the AD-associated TREM2-R47H mutation, which manifested a morphologically extreme phenotype of megakaryocytes and erythrocytes in addition to impaired trafficking of TREM2 to the erythroid membrane. TREM2 was shown to be involved in phagocytosis of red blood cells. TREM2 was seen in early and late endosomes. Silencing TREM2 using siRNA in THP1 cells resulted in significant cell death. CONCLUSION: We provide evidence that peripheral TREM2 originating from erythromyeloid cells significantly determines AD neuropathology in DS subjects. Understanding the molecular signaling pathways mediated by TREM2 may reveal novel therapeutic targets.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Cell Line; Disease Progression; Down Syndrome; Exosomes; Female; Humans; Immunity, Innate; Macrophages; Male; Membrane Glycoproteins; Microglia; Middle Aged; Phagocytosis; Polymorphism, Single Nucleotide; Receptors, Immunologic

Ethical Arguments Concerning the Use of Alzheimer's Disease Biomarkers in Individuals with No or Mild Cognitive Impairment: A Systematic Review and Framework for Discussion. - Smedinga, Marthe; Tromp, Krista; Schermer, Maartje H N; Richard, Edo (J Alzheimers Dis, 2018)
BACKGROUND: The shift to defining Alzheimer's disease (AD) as a biological continuum, which is characterized by the presence of biomarkers instead of clinical symptoms, has sparked a widespread debate. Insight into the given arguments and their underlying moral values is crucial to ensure well-considered and appropriate AD biomarker testing in the future. OBJECTIVE: To critically review the arguments in favor of or against AD biomarker testing in people with no or mild cognitive impairment and to explicate their underlying moral values. METHODS: Seven databases were systematically searched for publications mentioning arguments of interest. Arguments are identified using qualitative data-analysis and evaluated within an ethical framework. RESULTS: Our search yielded 3,657 articles of which 34 met the inclusion criteria. We discuss the clusters of arguments separate from their evaluation and the assessment of the debate as a whole. The right to know, which derives from the moral value of respect for autonomy, is a central argument in favor of biomarker testing. On the other hand, fear of the disease and lack of a disease-modifying treatment may result in a negative balance of good over inflicted harms, which argues against its use. CONCLUSION: Critical evaluation and weighing of the given arguments in a specific context, within an ethical framework, demonstrates the necessity to differentiate between what we hope or expect from research and where we currently stand. While AD biomarkers may have an indispensable value for research, the current advantage for clinical practice appears limited.

Executive and Language Subjective Cognitive Decline Complaints Discriminate Preclinical Alzheimer's Disease from Normal Aging. - Valech, Natalia; Tort-Merino, Adrià; Coll-Padrós, Nina; Olives, Jaume; León, María; Rami, Lorena; Molinuevo, José Luis (J Alzheimers Dis, 2018)
BACKGROUND: There is a need to specify the profile of subjective cognitive decline in preclinical Alzheimer's disease (preAD). OBJECTIVES: To explore specific items of the Subjective Cognitive Decline Questionnaire (SCD-Q) that discriminate preAD from normal aging. METHODS: 68 cognitively normal older adults were classified as controls (n = 52) or preAD (n = 16) according to amyloid-β (Aβ) levels. An exploratory factor analysis and item analysis of the SCD-Q were performed. Informant reports of the SCD-Q were used to corroborate the findings of self-reports. One-year neuropsychological follow-up was available. RESULTS: Four SCD-Q factors were extracted: EM-factor (episodic memory), A-factor (attention), O-factor (organization), and L-factor (language). PreAD reported a significantly higher decline in L-factor (F(1) = 6.49; p = 0.014) and A-factor (F(1) = 4.04; p = 0.049) compared to controls, and showed a higher frequency of perceived decline in SCD-Q items related with language and executive tasks (Sig-items.) Significant discriminative powers for Aβ-positivity were found for L-factor (AUC = 0.75; p = 0.003) and A-factor (AUC = 0.74; p = 0.004). Informants in the preAD group confirmed significantly higher scores in L-factor and Sig-items. A significant time×group interaction was found in the Semantic Fluency and Stroop tests, with the preAD group showing a decrease in performance at one-year. CONCLUSIONS: Our results suggest that SCD-Q items related with language and executive decline may help in prediction algorithms to detect preAD. Validation in an independent population is needed.
Keywords: Aged; Aging; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Executive Function; Factor Analysis, Statistical; Female; Humans; Language; Male; Middle Aged; Neuropsychological Tests; Self Report

Exercise Training on Locomotion in Patients with Alzheimer's Disease: A Feasibility Study. - Pedrinolla, Anna; Venturelli, Massimo; Fonte, Cristina; Munari, Daniele; Benetti, Maria Vittoria; Rudi, Doriana; Tamburin, Stefano; Muti, Ettore; Zanolla, Luisa; Smania, Nicola; Schena, Federico (J Alzheimers Dis, 2018)
BACKGROUND: Although current literature has shown that patients with Alzheimer's disease (AD) have worse locomotion compared with healthy counterparts, no studies have focused on the efficacy of exercise training in improving gait abnormalities including biomechanics and metabolic aspects, in this population. OBJECTIVE: To verify the effectiveness of exercise training (ET) on gait parameters (i.e., speed, step and stride length, single and double support, and energy cost of walking (Cw)) in patients with AD with respect to a standard cognitive treatment (CT). METHODS: In this study, we included a small portion of data belonging to a larger study (ClinicalTrials.gov number, NCT03034746). Patients with AD (Mini-Mental State Examination 22±5) were included in the study. Gait parameters and Cw were assessed at baseline and after 6 months (72 treatment sessions) of treatment. ET included 90 min of aerobic and strength training. CT included 90 min of cognitive stimuli. RESULTS: The 16 patients assigned to ET exhibited significant improvement of Cw (-0.9±0.1 J/kg·m-1), while differences in gait parameters were negligible. The effect on gait parameters were undetectable in the 18 patients assigned to CT (-0.2±0.5 J/kg·m-1). CONCLUSIONS: Data from this study showed that ET program seems effective in improving Cw in patients with AD. Interestingly, the positive effect of ET on Cw was not coupled with ameliorations of patient's gait parameters, suggesting that the gain of metabolic aspects of locomotion were the main factors responsible for this positive result.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomechanical Phenomena; Exercise Test; Exercise Therapy; Feasibility Studies; Female; Gait; Humans; Italy; Male; Single-Blind Method

Expression Profiling of Cytokine, Cholinergic Markers, and Amyloid-β Deposition in the APPSWE/PS1dE9 Mouse Model of Alzheimer's Disease Pathology. - Reale, Marcella; D'Angelo, Chiara; Costantini, Erica; Di Nicola, Marta; Yarla, Nagnedra Sastry; Kamal, Mohammad Amjad; Salvador, Nieves; Perry, George (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD), a neurodegenerative disease, is associated with dysfunction of the olfactory and the entorhinal cortex of the brain that control memory and cognitive functions and other daily activities. Pro-inflammatory cytokines, amyloid-β (Aβ), and the cholinergic system play vital roles in the pathophysiology of AD. However, the role of changes in cholinergic system components, Aβ accumulation, and cytokines in both the olfactory and entorhinal cortex is not known clearly. OBJECTIVE: The present study is aimed to evaluate the changes of cholinergic system components, Aβ accumulation, and cytokines in both the olfactory bulb (OB) and entorhinal cortex (EC) of young and aged APPSWE/PS1dE9 transgenic (Tg) mice. METHODS: We have explored the changes of cholinergic system components, Aβ accumulation, and expression profiling of cytokines in the OB and EC of aged APPswe transgenic mice and age-matched wild type mice using quantitative Real-Time PCR assays and immunohistochemistry techniques. RESULTS: In aged Tg mice, a significant increase of expression of interleukin (IL)-1β, tumor necrosis factor (TNF)-α, and chemokine MCP1 (p < 0.001, p < 0.001, and p = 0.001, respectively) and a significant reduction of nAChRα4 (p = 0.048) and AChE (p = 0.023) was observed when compared with age-matched wild type mice. Higher levels of AChE and BuChE are expressed in OB and EC of the APPSWE/PS1dE9 of Tg mice. Aβ accumulation was observed in OB and EC of the APPSWE/PS1dE9 of Tg mice. CONCLUSION: The study demonstrates the expression profiling of pro-inflammatory cytokines and cholinergic markers as well as Aβ accumulation in OB and EC of the APPSWE/PS1dE9 Tg mice. Moreover, the study also demonstrated that the APPSWE/PS1dE9 Tg mice can be useful as a mouse model to understand the role of pro-inflammatory cytokines and cholinergic markers in pathophysiology of AD.

Fragmentation of the Golgi Apparatus in Neuroblastoma Cells Is Associated with Tau-Induced Ring-Shaped Microtubule Bundles. - Rodríguez-Cruz, Fanny; Torres-Cruz, Francisco Miguel; Monroy-Ramírez, Hugo Christian; Escobar-Herrera, Jaime; Basurto-Islas, Gustavo; Avila, Jesús; Garcia-Sierra, Francisco (J Alzheimers Dis, 2018)
Abnormal fibrillary aggregation of tau protein is a pathological condition observed in Alzheimer's disease and other tauopathies; however, the presence and pathological significance of early non-fibrillary aggregates of tau remain under investigation. In cell and animal models expressing normal or modified tau, toxic effects altering the structure and function of several membranous organelles have also been reported in the absence of fibrillary structures; however, how these abnormalities are produced is an issue yet to be addressed. In order to obtain more insights into the mechanisms by which tau may disturb intracellular membranous elements, we transiently overexpressed human full-length tau and several truncated tau variants in cultured neuroblastoma cells. After 48 h of transfection, either full-length or truncated tau forms produced significant fragmentation of the Golgi apparatus (GA) with no changes in cell viability. Noteworthy is that in the majority of cells exhibiting dispersion of the GA, a ring-shaped array of cortical or perinuclear microtubule (Mt) bundles was also generated under the expression of either variant of tau. In contrast, Taxol treatment of non-transfected cells increased the amount of Mt bundles but not sufficiently to produce fragmentation of the GA. Tau-induced ring-shaped Mt bundles appeared to be well-organized and stable structures because they were resistant to Nocodazole post-treatment and displayed a high level of tubulin acetylation. These results further indicate that a mechanical force generated by tau-induced Mt-bundling may be responsible for Golgi fragmentation and that the repeated domain region of tau may be the main promoter of this effect.

A Free Radical-Generating System Regulates Amyloid Oligomers: Involvement of Cathepsin B. - Llorente, Patricia; Kristen, Henrike; Sastre, Isabel; Toledano-Zaragoza, Ana; Aldudo, Jesús; Recuero, María; Bullido, Maria J (J Alzheimers Dis, 2018)
Amyloid-β (Aβ), a major component of senile plaques, is generated via the proteolysis of amyloid-β protein precursor (AβPP). This cleavage also produces AβPP fragment-derived oligomers which can be highly neurotoxic. AβPP metabolism/processing is affected by many factors, one of which is oxidative stress (OS). Associated with aging, OS is an important risk factor for Alzheimer's disease. In addition, the protein degradation systems, especially those involving cathepsins, are impaired in aging brains. Moreover, cathepsin B (CTSB) is a cysteine protease with potentially specific roles in AβPP proteolysis (β-secretase activity) and Aβ clearance (Aβ degradative activity). The present work examines the effect of OS and the involvement of CTSB in amyloid oligomer formation. The xanthine/xanthine oxidase (X-XOD) free radical generating system induced the partial inhibition of CTSB activity, which was accompanied by an increase in large amyloid oligomers. These were located throughout the cytosol and in endo-lysosomal vesicles. Cells treated with the CTSB inhibitor CA-074Me also showed increased amyloid oligomer levels, whereas those subjected to OS in the presence of the inhibitor showed no such increase. However, CTSB inhibition clearly modulated the AβPP metabolism/processing induced by X-XOD, as revealed by the increase in intracellular AβPP and secreted α-secretase-cleaved soluble AβPP. The present results suggest that CTSB participates in the changes of amyloid oligomer induced by mild OS.

Frequency and Correlates of Subjective Memory Complaints in Parkinson's Disease with and without Mild Cognitive Impairment: Data from the Parkinson's Disease Cognitive Impairment Study. - Baschi, Roberta; Nicoletti, Alessandra; Restivo, Vincenzo; Recca, Deborah; Zappia, Mario; Monastero, Roberto (J Alzheimers Dis, 2018)
Subjective memory complaints (SMC) may represent the preclinical phase of mild cognitive impairment (MCI) due to Alzheimer's disease. Dementia/MCI have been described with a high prevalence in Parkinson's disease (PD), but whether SMC may predict the development of cognitive impairment has been barely explored. To evaluate the frequency and clinical correlates of isolated SMC (PD-SMC) or within the construct of MCI in subjects with PD, 147 PD patients from the PArkinson's disease COgnitive impairment Study (PACOS) were consecutively recruited for the study. This is a multicenter study involving two Movement Disorder Centers in south Italy. All subjects underwent comprehensive neuropsychological evaluation and PD-MCI was diagnosed according to Litvan's criteria. The Memory Assessment Clinics Questionnaire was used to assess SMC. Logistic regression analysis, adjusted for demographics and significant covariates, was used to evaluate clinical differences between groups. Forty-two (28.6%) individuals presented with PD without SMC and/or MCI (PDw), 40 (27,2%) with PD-SMC, 48 (32,6%) PD-SMC-MCI, and 17 (11,6%) PD-MCI without SMC (PD-MCI). When compared to PDw, PD-SMC was significantly associated with anxiety (OR = 3.93, 95% CI = 1.18-13.03), while PD-SMC-MCI related to motor progression (OR = 5.29, 95% CI = 1.12-24.86), and instrumental disability (OR = 6.98, 95% CI = 2.08-23.38). About 60% of patients showed SMC, in isolation or within the MCI frame. The role of SMC in PD seems to have a different etiology depending on the presence/absence of MCI. In particular, PD-SMC would represent a subjective reaction to the disease, while PD-SMC-MCI would depict motor progression and disability.

Frequency of Cardiovascular Genetic Risk Factors in a Calabrian Population and Their Effects on Dementia. - Maletta, Raffaele; Smirne, Nicoletta; Bernardi, Livia; Anfossi, Maria; Gallo, Maura; Conidi, Maria Elena; Colao, Rosanna; Puccio, Gianfranco; Curcio, Sabrina A M; Laganà, Valentina; Frangipane, Francesca; Cupidi, Chiara; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Several genetic variants playing a key role in cholesterol levels, blood pressure, and vascular dysfunction influence the risk of Alzheimer's disease (AD) and vascular dementia (VaD). The many meta-analysis studies carried out on large numbers of samples in different populations have not provided clear results to date, because a trans-ethnic shift of risk genotypes in different populations is often observed. OBJECTIVES: To determine genotypes allele frequencies of the polymorphisms most frequently identified to be correlated with cardio-cerebrovascular disease and AD in a Southern Italy population and to investigate their possible association with dementia. METHODS: The genotype and allele frequencies of 13 cardio-cerebrovascular risk polymorphisms were assessed and their possible association with dementia was investigated in a case-control study, including 221 consecutive unrelated subjects diagnosed with dementia (120 subjects affected by AD, 55 by frontotemporal dementia, and 33 by vascular dementia) and 218 matched controls of Calabrian origin. RESULTS: Carriers of at least one APOEɛ4 allele resulted to be at higher risk of AD [OR(95% CI) = 2.721(1.477-5.011)] and VaD [OR(95% CI) = 6.205(2.356-16.342)] compared to non-carriers. Individuals with the IV genotype of the CETP polymorphism were more likely to have AD [OR(95% CI) = 2.427(1.364-4.319)] and VaD [OR(95% CI) = 3.649(1.455-9.152)] compared to subjects with the II-VV genotypes. CONCLUSION: CETP I405V polymorphism is likely a risk factor for AD and VaD in our cohort, independent of APOEɛ4 status. Unmodifiable genetic risk factors should be taken into account to promote a healthy lifestyle to prevent dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Case-Control Studies; Cholesterol Ester Transfer Proteins; Cohort Studies; Dementia, Vascular; Female; Frontotemporal Dementia; Gene Frequency; Humans; Italy; Male; Middle Aged; Polymorphism, Genetic; Risk Factors

Frontotemporal Dementia and Chorea Associated with a Compound Heterozygous TREM2 Mutation. - Redaelli, Veronica; Salsano, Ettore; Colleoni, Lara; Corbetta, Paola; Tringali, Giovanni; Del Sole, Angelo; Giaccone, Giorgio; Rossi, Giacomina (J Alzheimers Dis, 2018)
Frontotemporal dementia (FTD) is clinically characterized by behavioral changes, language impairment, and executive dysfunction. FTD usually belongs to the frontotemporal lobar degeneration (FTLD) disease group, and its familial forms are dominantly inherited and linked to a group of genes relevant to frontal and temporal brain pathology, such as MAPT, GRN, C9ORF72, TARDBP, CHMP2B, VCP, and FUS. However, FTD can also be associated with different clinical or pathological phenotypes caused by mutations in other genes, whose heredity can be dominant or recessive. In this work we report on a familial case of FTD characterized by behavioral changes and aphasia, very early onset and very long duration, choreic movements, and white matter lesions at magnetic resonance imaging. We performed a wide-range genetic analysis, using a next generation sequencing approach, to evaluate a number of genes involved in neurodegeneration. We found a previously unreported compound heterozygous mutation in TREM2, that is commonly associated with the recessively inherited Nasu-Hakola disease. We discuss the differential diagnosis to be taken into account in cases of FTD presenting with atypical features.

Gait in Mild Alzheimer's Disease: Feasibility of Multi-Center Measurement in the Clinic and Home with Body-Worn Sensors: A Pilot Study. - Mc Ardle, Ríona; Morris, Rosie; Hickey, Aodhán; Del Din, Silvia; Koychev, Ivan; Gunn, Roger N; Lawson, Jennifer; Zamboni, Giovanna; Ridha, Basil; Sahakian, Barbara J; Rowe, James B; Thomas, Alan; et al. (J Alzheimers Dis, 2018)
Gait is emerging as a potential diagnostic tool for cognitive decline. The 'Deep and Frequent Phenotyping for Experimental Medicine in Dementia Study' (D&FP) is a multicenter feasibility study embedded in the United Kingdom Dementia Platform designed to determine participant acceptability and feasibility of extensive and repeated phenotyping to determine the optimal combination of biomarkers to detect disease progression and identify early risk of Alzheimer's disease (AD). Gait is included as a clinical biomarker. The tools to quantify gait in the clinic and home, and suitability for multi-center application have not been examined. Six centers from the National Institute for Health Research Translational Research Collaboration in Dementia initiative recruited 20 individuals with early onset AD. Participants wore a single wearable (tri-axial accelerometer) and completed both clinic-based and free-living gait assessment. A series of macro (behavioral) and micro (spatiotemporal) characteristics were derived from the resultant data using previously validated algorithms. Results indicate good participant acceptability, and potential for use of body-worn sensors in both the clinic and the home. Recommendations for future studies have been provided. Gait has been demonstrated to be a feasible and suitable measure, and future research should examine its suitability as a biomarker in AD.

Glia Maturation Factor and Mast Cell-Dependent Expression of Inflammatory Mediators and Proteinase Activated Receptor-2 in Neuroinflammation. - Kempuraj, Duraisamy; Selvakumar, Govindhasamy Pushpavathi; Thangavel, Ramasamy; Ahmed, Mohammad Ejaz; Zaheer, Smita; Kumar, Keerthana Kuppamma; Yelam, Anudeep; Kaur, Harleen; Dubova, Iuliia; Raikwar, Sudhanshu P; Iyer, Shankar S; Zaheer, Asgar (J Alzheimers Dis, 2018)
Parkinson's disease (PD) is characterized by the presence of inflammation-mediated dopaminergic neurodegeneration in the substantia nigra. Inflammatory mediators from activated microglia, astrocytes, neurons, T-cells and mast cells mediate neuroinflammation and neurodegeneration. Administration of neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induces PD like motor deficits in rodents. 1-methyl-4-phenylpyridinium (MPP+), a toxic metabolite of MPTP activates glial cells, neurons and mast cells to release neuroinflammatory mediators. Glia maturation factor (GMF), mast cells and proteinase activated receptor-2 (PAR-2) are implicated in neuroinflammation. Alpha-synuclein which induces neurodegeneration increases PAR-2 expression in the brain. However, the exact mechanisms are not yet understood. In this study, we quantified inflammatory mediators in the brains of MPTP-administered wild type (Wt), GMF-knockout (GMF-KO), and mast cell knockout (MC-KO) mice. Additionally, we analyzed the effect of MPP+, GMF, and mast cell proteases on PAR-2 expression in astrocytes and neurons in vitro. Results show that the levels of interleukin-1beta (IL-1β), tumor necrosis factor-alpha (TNF-α), and the chemokine (C-C motif) ligand 2 (CCL2) were lesser in the brains of GMF-KO mice and MC-KO mice when compared to Wt mice brain after MPTP administration. Incubation of astrocytes and neurons with MPP+, GMF, and mouse mast cell protease-6 (MMCP-6) and MMCP-7 increased the expression of PAR-2. Our studies show that the absence of mast cells and GMF reduce the expression of neuroinflammatory mediators in the brain. We conclude that GMF along with mast cell interactions with glial cells and neurons during neuroinflammation can be explored as a new therapeutic target for PD and other neuroinflammatory disorders.

Growth Hormone-Releasing Hormone Modulation of Neuronal Exosome Biomarkers in Mild Cognitive Impairment. - Winston, Charisse N; Goetzl, Edward J; Baker, Laura D; Vitiello, Michael V; Rissman, Robert A (J Alzheimers Dis, 2018)
Age-related changes in cognition are linked to decreased expression of somatotropins, GHRH and IGF-1. Mild cognitive impairment (MCI) and Alzheimer's disease (AD) are heterogeneous conditions. The loss of GHRH signaling in the brain may be mechanistically involved in AD pathogenesis. The consequent need to identify AD at an early and perhaps more treatable stage has fueled research into blood-based, exosome biomarkers. Plasma exosomes from participants enrolled in a randomized, double-blind, placebo-controlled 20-week trial of GHRH administration, were isolated, precipitated, and enriched by immuno-absorption with anti-L1CAM antibody (neural adhesion protein) from adults with MCI and age-matched, cognitively normal controls (CNC). Extracted protein cargo from neuronally-derived exosomes (NDEs) were assessed by ELISAs for protein levels implicated in AD neuropathology and for synaptic proteins altered by AD. Plasma NDE concentrations of Aβ1-42 were significantly increased while plasma NDE concentrations of NRGN, synaptophysin, synaptotagmin, and synaptopodin were significantly decreased in patients with MCI, independent of GHRH treatment. Plasma NDE concentrations of ptau-S396 and GAP43 were not affected by cognitive status (CNC versus MCI) or by GHRH treatment. Aβ1-42, neurogranin (NRGN), synaptophysin, synaptotagmin, and synaptopodin demonstrated the highest diagnostic accuracy for distinguishing between CNC and MCI patients, while synaptophysin and synaptotagmin demonstrated moderate accuracy in distinguishing between placebo-treated and GHRH-treated, MCI patients.

Heparin Modulates the Kinetics of Zinc-Induced Aggregation of Amyloid-β Peptides. - Radko, Sergey P; Khmeleva, Svetlana A; Mantsyzov, Alexey B; Kiseleva, Yana Y; Mitkevich, Vladimir A; Kozin, Sergey A; Makarov, Alexander A (J Alzheimers Dis, 2018)
Zinc-induced aggregation of amyloid-β peptides (Aβ) is considered to contribute to the pathogenesis of Alzheimer's disease. While glycosaminoglycans (GAGs) that are commonly present in interneuronal space are known to enhance Aβ self-aggregation in vitro, the impact of GAGs on the formation of zinc-induced amorphous Aβ aggregates has not yet been thoroughly studied. Here, employing dynamic light scattering, bis-ANS fluorimetry, and sedimentation assays, we demonstrate that heparin serving as a representative GAG modulates the kinetics of zinc-induced Aβ42 aggregation in vitro by slowing the rate of aggregate formation and aggregate size growth. By using synthetic Aβ16 peptides to model the Aβ metal-binding domain (MBD), heparin was found to effectively interact with MBDs in complex with zinc ions. We suggest that heparin adsorbs to the surface of growing zinc-induced Aβ42 aggregates via electrostatic interactions, thus creating a steric hindrance that inhibits further inclusion of monomeric and/or oligomeric zinc-Aβ42 complexes. Furthermore, the adsorbed heparin can interfere with the zinc-bridging mechanism of Aβ42 aggregation, requiring the formation of two zinc-mediated interaction interfaces in the MBD. As revealed by computer simulations of the zinc-Aβ16 homodimer complexed with a heparin chain, heparin can interact with the MBD via polar contacts with residues Arg-5 and Tyr-10, resulting in a conformational rearrangement that hampers the formation of the second zinc-mediated interaction in the MBD interface. The findings of this study suggest that GAGs, which are common in the in vivo macromolecular environment, may have a substantial impact on the time course of zinc-induced Aβ aggregation.

Hippocampal Sclerosis in the Oldest Old: A Finnish Population-Based Study. - Kero, Mia; Raunio, Anna; Polvikoski, Tuomo; Tienari, Pentti J; Paetau, Anders; Myllykangas, Liisa (J Alzheimers Dis, 2018)
BACKGROUND: There are only few population-based studies that have systemically investigated the prevalence of hippocampal sclerosis (HS) in the very old. The frequency of unilateral versus bilateral HS has been rarely studied. OBJECTIVE: We investigated the prevalence and laterality of HS and its association with other neurodegenerative and vascular pathologies in a population-based sample of very elderly. Furthermore, the concomitant presence of immunoreactivity for TDP-43, p62, and HPtau was studied. METHODS: The population-based Vantaa 85+ study includes all inhabitants of the city of Vantaa, who were >85 years in 1991 (n = 601). Neuropathological assessment was possible in 302 subjects. Severity of neuronal loss of CA sectors and subiculum was determined bilaterally by HE- staining. Immunohistochemistry performed using antibodies for TDP-43, p62, and HPtau. RESULTS: Neuronal loss and pathological changes in the hippocampus sector CA1 and subiculum were observed in 47 of the 302 individuals (16%), and 51% of these changes were bilateral. HS without comorbid neurodegenerative pathology was found in 1/47 subjects with HS (2%). Dementia (p < 0.001) and TDP-43 immunopositivity of the granular cell layer of the dentate fascia (p < 0.001) were strongly associated with HS. The CERAD score, immunopositivity for HPtau and p62 in the granular cell layer of the fascia dentate were also associated. CONCLUSION: HS is prevalent (16%) in the oldest old population, but HS without any comorbid neurodegenerative pathology is rare. The high frequency of unilateral HS (49%) implied that bilateral sampling of hippocampi should be routine practice in neuropathological examination.

Hippocampal Stratum Radiatum, Lacunosum, and Moleculare Sparing in Mild Cognitive Impairment. - Su, Li; Hayes, Lawrence; Soteriades, Soteris; Williams, Guy; Brain, Susannah A E; Firbank, Michael J; Longoni, Giulia; Arnold, Robert J; Rowe, James B; O'Brien, John T (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is associated with atrophy in entorhinal cortex (ERC), the hippocampus, and its subfields Cornu Ammonis 1 (CA1) and subiculum, which predict conversion from mild cognitive impairment (MCI) to clinical AD. The stratum radiatum, lacunosum, and moleculare (SRLM) are also important gateways involving ERC and CA1, which are affected by early AD pathology. OBJECTIVE: To assess whether the SRLM is affected in MCI and AD. METHODS: In this proof-of-concept study, 27 controls, 13 subjects with AD, and 22 with MCI underwent 3T MRI. T1 maps were used for whole-hippocampal volumetry, T2 maps were segmented for hippocampal subfield areas, entorhinal cortex and subiculum thickness, and evaluated for SRLM integrity. RESULTS: Significant CA1 atrophy and subiculum thinning were found in both AD and MCI compared to similarly aged controls. However, SRLM integrity was only significantly reduced in AD but not in MCI compared to controls. There were no significant differences in other hippocampal subfields (CA2, CA3/dentate gyrus) or ERC thickness between the groups. Finally, CA1 and CA3/DG areas and SRLM clarity were correlated with clinical and cognitive measurements of disease severity. CONCLUSION: Although this study was cross sectional, it suggests a progression of specific subfield changes from MCI to established AD that is associated with the reduced integrity of SRLM, which may reflect more widespread hippocampal involvement as the disease progresses and the relative preservation of SRLM in MCI. These results provide new MRI biomarkers for disease staging and understanding of the neurobiology in AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Atrophy; Cognitive Dysfunction; Disease Progression; Entorhinal Cortex; Female; Hippocampus; Humans; Imaging, Three-Dimensional; Magnetic Resonance Imaging; Male; Middle Aged; Reproducibility of Results

Hippocampal Subfield Volumetry: Differential Pattern of Atrophy in Different Forms of Genetic Frontotemporal Dementia. - Bocchetta, Martina; Iglesias, Juan Eugenio; Scelsi, Marzia A; Cash, David M; Cardoso, M Jorge; Modat, Marc; Altmann, Andre; Ourselin, Sebastien; Warren, Jason D; Rohrer, Jonathan D (J Alzheimers Dis, 2018)
BACKGROUND: Frontotemporal dementia (FTD) is a heterogeneous neurodegenerative disorder, with a strong genetic component. Previous research has shown that medial temporal lobe atrophy is a common feature of FTD. However, no study has so far investigated the differential vulnerability of the hippocampal subfields in FTD. OBJECTIVES: We aimed to investigate hippocampal subfield volumes in genetic FTD. METHODS: We in6/2/2018vestigated hippocampal subfield volumes in a cohort of 75 patients with genetic FTD (age: mean (standard deviation) 59.3 (7.7) years; disease duration: 5.1 (3.4) years; 29 with MAPT, 28 with C9orf72, and 18 with GRN mutations) compared with 97 age-matched controls (age: 62.1 (11.1) years). We performed a segmentation of their volumetric T1-weighted MRI scans to extract hippocampal subfields volumes. Left and right volumes were summed and corrected for total intracranial volumes. RESULTS: All three groups had smaller hippocampi than controls. The MAPT group had the most atrophic hippocampi, with the subfields showing the largest difference from controls being CA1-4 (24-27%, p < 0.0005). For C9orf72, the CA4, CA1, and dentate gyrus regions (8-11%, p < 0.0005), and for GRN the presubiculum and subiculum (10-14%, p < 0.0005) showed the largest differences from controls. CONCLUSIONS: The hippocampus was affected in all mutation types but a different pattern of subfield involvement was found in the three genetic groups, consistent with differential cortical-subcortical network vulnerability.

Histological and Behavioral Phenotypes of a Novel Mutated APP Knock-In Mouse. - Plucińska, Kaja; Crouch, Barry; Yeap, Jie M; Stoppelkamp, Sandra; Riedel, Gernot; Platt, Bettina (J Alzheimers Dis, 2018)
Gene mutations within amyloid precursor protein (APP or AβPP) and/or presenilin 1 (PS1) genes are determinants of familial Alzheimer's disease (fAD) and remain fundamental for experimental models. Here, we generated a neuronal knock-in mouse (PLB2APP) with mutated human APPSwe/Lon and investigated histopathology and behavioral phenotypes. Additionally, PLB2APP mice were cross-bred with a presenilin (PS1A246E) line to assess the impact of this gene combination. Immunohistochemistry determined amyloid-β (Aβ) pathology, astrogliosis (via GFAP labelling), and neuronal densities in hippocampal and cortical brain regions. One-year old PLB2APP mice showed higher levels of intracellular Aβ in CA1, dentate gyrus, and cortical regions compared to PLBWT controls. Co-expression of PS1 reduced hippocampal but elevated cortical Aβ build-up. Amyloid plaques were sparse in aged PLB2APP mice, and co-expression of PS1 promoted plaque formation. Heightened GFAP expression followed the region-specific pattern of Aβ in PLB2APP and PLB2APP/PS1 mice. Behaviorally, habituation to a novel environment was delayed in 6-month-old PLB2APP mice, and overall home-cage activity was reduced in both lines at 6 and 12 months, particularly during the dark phase. Spatial learning in the water maze was impaired in PLB2APP mice independent of PS1 expression and associated with reduced spatial navigation strategies. Memory retrieval was compromised in PLB2APP mice only. Our data demonstrate that low expression of APP is sufficient to drive histopathological and cognitive changes in mice without overexpression or excessive plaque deposition. AD-like phenotypes were altered by co-expression of PS1, including a shift from hippocampal to cortical Aβ pathology, alongside reduced deficits in spatial learning.

Homocysteine and Dementia: An International Consensus Statement. - Smith, A David; Refsum, Helga; Bottiglieri, Teodoro; Fenech, Michael; Hooshmand, Babak; McCaddon, Andrew; Miller, Joshua W; Rosenberg, Irwin H; Obeid, Rima (J Alzheimers Dis, 2018)
Identification of modifiable risk factors provides a crucial approach to the prevention of dementia. Nutritional or nutrient-dependent risk factors are especially important because dietary modifications or use of dietary supplements may lower the risk factor level. One such risk factor is a raised concentration of the biomarker plasma total homocysteine, which reflects the functional status of three B vitamins (folate, vitamins B12, B6). A group of experts reviewed literature evidence from the last 20 years. We here present a Consensus Statement, based on the Bradford Hill criteria, and conclude that elevated plasma total homocysteine is a modifiable risk factor for development of cognitive decline, dementia, and Alzheimer's disease in older persons. In a variety of clinical studies, the relative risk of dementia in elderly people for moderately raised homocysteine (within the normal range) ranges from 1.15 to 2.5, and the Population Attributable risk ranges from 4.3 to 31%. Intervention trials in elderly with cognitive impairment show that homocysteine-lowering treatment with B vitamins markedly slows the rate of whole and regional brain atrophy and also slows cognitive decline. The findings are consistent with moderately raised plasma total homocysteine (>11 μmol/L), which is common in the elderly, being one of the causes of age-related cognitive decline and dementia. Thus, the public health significance of raised tHcy in the elderly should not be underestimated, since it is easy, inexpensive, and safe to treat with B vitamins. Further trials are needed to see whether B vitamin treatment will slow, or prevent, conversion to dementia in people at risk of cognitive decline or dementia.
Keywords: Cognition; Cognitive Dysfunction; Consensus; Dementia; Dietary Supplements; Homocysteine; Humans; Meta-Analysis as Topic; Review Literature as Topic; Risk Factors; Vitamin B Complex

Immunotherapy of Mild Cognitive Impairment by ω-3 Supplementation: Why Are Amyloid-β Antibodies and ω-3 Not Working in Clinical Trials? - Fiala, Milan; Restrepo, Lucas; Pellegrini, Matteo (J Alzheimers Dis, 2018)
This article reviews the basic tenets of a clinical approach to effective immunotherapy of Alzheimer's disease (AD) in patients with mild cognitive impairment (MCI). Although one randomized controlled study in early MCI patients by fish-derived omega-3 fatty acids (ω-3) showed slowing of disease progression, large clinical trials with different products have failed to show cognitive effects. Macrophages of healthy subjects phagocytize and degrade amyloid-β1 - 42 (Aβ) in the brain tissues, whereas macrophages of patients with AD and MCI are functionally defective. ω-3 and ω-3-derived specialized proresolving mediators (SPMs), such as resolvin D1, have powerful biochemical and immunological effects, which may repair the functions of MCI patients' macrophages in the brain's clearance of Aβ. Unfortunately, ω-3 products on the market have a variable quality. Nutritional supplementation with a combination drink called Smartfish with an emulsion of ω-3 and other fatty acids, antioxidants, 1,25-dihydroxy vitamin D3, and resveratrol improved the innate immune system of MCI patients by modulation of macrophage type to the pro-phagocytic M1-M2 type with an effective unfolded protein response against endoplasmic reticulum stress. Some MCI patients maintained their initial cognitive status for three years on Smartfish supplementation. Future randomized clinical trials should investigate the immune effects of ω-3, 1,25-dihydroxy vitamin D3, and SPMs on macrophage type, function, and biochemistry in parallel with cognitive effects.

Impact of Mild Cognitive Impairment on Mortality and Cause of Death in the Elderly. - Bae, Jong Bin; Han, Ji Won; Kwak, Kyung Phil; Kim, Bong Jo; Kim, Shin Gyeom; Kim, Jeong Lan; Kim, Tae Hui; Ryu, Seung-Ho; Moon, Seok Woo; Park, Joon Hyuk; Youn, Jong Chul; Lee, Dong Young; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Mild cognitive impairment (MCI) is a cognitive state that lies on the continuum between normal aging and dementia, and the prevalence of MCI is higher than dementia. However, the risk for mortality of people with MCI has been far less studied than that of people with dementia, and the population attributable risk percent (PAR%) of death attributable to MCI has not been estimated yet. OBJECTIVE: To investigate the impact of MCI on mortality and the cause of death in the elderly, and to estimate the PAR% of deaths attributable to MCI. METHODS: Data came from 7,315 elderly subjects aged ≥60 years without dementia from two cohort studies with diagnostic assessments of MCI at baseline. Deaths among participants were confirmed through the nationwide mortality database of Statistics Korea. RESULTS: MCI increased the risk of mortality in a multivariate Cox proportional model adjusting for age, sex, education, smoking, alcohol drinking, chronic illness, depression, vascular components, and cohort (hazard ratio = 1.59, 95% confidence interval 1.30, 1.94). PAR% of death attributable to MCI was 10.7% for age 65-74 years, 16.0% for age 75-84 years, and 24.2% for age ≥85 years. In the elderly with MCI, mortality risks from cerebrovascular disease, respiratory disease, and external causes were higher than in the cognitively normal elderly. CONCLUSIONS: Our results suggest that the mortality risk of MCI in Asian countries may be comparable to that in Western countries, and MCI can contribute to the death of the elderly as much as dementia.

Impact of Olfactory Priming on Food Intake in an Alzheimer's Disease Unit. - Sulmont-Rossé, Claire; Gaillet, Marie; Raclot, Carine; Duclos, Michel; Servelle, Maud; Chambaron, Stéphanie (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is often associated with feeding difficulties and changes in eating behavior with may lead to malnutrition. In French nursing homes, AD patients may live in special care units that better meet dementia residents' needs. However, meals are often delivered to AD patients by using meal trays coming from central kitchens. This led to the disappearance of cues that could help residents to foresee mealtime, such as the smell of food odors. The aim of the present study was to assess the impact of odorizing the dining room of AD Units with a meat odor before lunch on subsequent food intake and eating behavior. Thirty-two residents (>75 years old) from three AD Units were included in the study. They participated in two control lunches and two primed lunches, for which a meat odor was diffused in the dining room 15 minutes before the arrival of the meal tray (olfactory priming). Results of the first replication showed a significant effect of olfactory priming, with a 25% increase in meat and vegetable consumption compared to the control condition. Behavioral measurements also showed a significant increase of resident's interest toward the meal in the primed lunch. However, this effect was no longer observed when the priming session was replicated two weeks later with the same priming odor and the same menu. Although further research is needed to understand why this priming effect cannot be replicated, our experiment is one of the very first to investigate the effect of food odor priming on subsequent food intake in AD patients in a real-life setting.

Impact of Total Knee Arthroplasty with General Anesthesia on Brain Networks: Cognitive Efficiency and Ventricular Volume Predict Functional Connectivity Decline in Older Adults. - Huang, Haiqing; Tanner, Jared; Parvataneni, Hari; Rice, Mark; Horgas, Ann; Ding, Mingzhou; Price, Catherine (J Alzheimers Dis, 2018)
Using resting state functional magnetic resonance imaging (RS-fMRI), we explored: 1) pre- to post-operative changes in functional connectivity in default mode, salience, and central executive networks after total knee arthroplasty (TKA) with general anesthesia, and 2) the contribution of cognitive/brain reserve metrics these resting state functional declines. Individuals age 60 and older electing unilateral total knee arthroplasty (TKA; n = 48) and non-surgery peers with osteoarthritis (n = 45) completed baseline cognitive testing and baseline and post-surgery (post-baseline, 48-h post-surgery) brain MRI. We acquired cognitive and brain estimates for premorbid (vocabulary, reading, education, intracranial volume) and current (working memory, processing speed, declarative memory, ventricular volume) reserve. Functional network analyses corrected for pain severity and pain medication. The surgery group declined in every functional network of interest (p < 0.001). Relative to non-surgery peers, 23% of surgery participants declined in at least one network and 15% of the total TKA sample declined across all networks. Larger preoperative ventricular volume and lower scores on preoperative metrics of processing speed and working memory predicted default mode network connectivity decline. Premorbid cognitive and premorbid brain reserve did not predict decline. Within 48 hours after surgery, at least one fourth of the older adult sample showed significant functional network decline. Metrics of current brain status (ventricular volume), working memory, and processing speed predicted the severity of default mode network connectivity decline. These findings demonstrate the relevance of preoperative cognition and brain integrity on acute postoperative functional network change.

Impact of Untimely Access to Formal Care on Costs and Quality of Life in Community Dwelling People with Dementia. - Janssen, Niels; Handels, Ron L; Sköldunger, Anders; Woods, Bob; Jelley, Hannah; Edwards, Rhiannon Tudor; Orrell, Martin; Selbæk, Geir; Røsvik, Janne; Gonçalves-Pereira, Manuel; Marques, Maria J; Zanetti, Orazio; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Access to formal care is not always timely and a better understanding on the impact of untimely access is needed. OBJECTIVE: To examine, from a societal perspective, the impact of untimely access to formal care in terms of total costs and quality of life over one year in community dwelling people with dementia. METHODS: Within the Actifcare study, needs, resource use, and quality of life were observed for one year in a cohort of 451 community dwelling people with dementia in 8 European countries. Untimely access to care was operationalized as having at least one unmet need for care identified by the Camberwell Assessment of Need for the Elderly (CANE) instrument. Two regression models were built for both total costs and quality of life measured by the EQ-5D-5L, one using sum of unmet needs and one using a predefined selection of need items. RESULTS: Unmet needs were not associated with higher total costs but they were associated with a lower quality of life of people with dementia. Of all CANE items, only an unmet need for "company" was significantly related to lower total costs. CONCLUSION: Total costs did not seem to differ between participants with unmet and met needs. Only few associations between specific unmet needs and costs and quality of life were found. Furthermore, quality of life of people with dementia decreases when multiple unmet needs are experienced, indicating that assessing and meeting needs is important to improve quality of life.

Improvement of Main Cognitive Functions in Patients with Alzheimer's Disease after Treatment with Coconut Oil Enriched Mediterranean Diet: A Pilot Study. - de la Rubia Ortí, Jose Enrique; García-Pardo, María Pilar; Drehmer, Eraci; Sancho Cantus, David; Julián Rochina, Mariano; Aguilar, Maria Asunción; Hu Yang, Iván (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is the most prevalent neurodegenerative disorder (mainly in women), and new therapies are needed. In this way, ketone bodies are a direct source of cellular energy and can be obtained from coconut oil, postulating that coconut oil could be a new non-pharmacological alternative in AD patients. OBJECTIVE: The aim of this study is to detect changes in the main cognitive functions of patients with AD after following a coconut oil enriched Mediterranean diet, and to determine whether there are differences in function of stage or sex. METHODS: A prospective, longitudinal, qualitative, analytic, experimental study was carried out in 44 patients with AD, who were randomly divided into two homogenous groups of 22 patients each: an experimental group of patients who followed a coconut oil enriched Mediterranean diet for 21 days and a control group. In order to determine the cognitive changes after the intervention, we carried out the 7 Minute Screen, which analyses temporal orientation, visuospatial and visuoconstructive abilities, and semantic and episodic memory. RESULTS: After intervention with coconut oil, improvements in episodic, temporal orientation, and semantic memory were observed, and it seems that the positive effect is more evident in women with mild-moderate state, although other improvements in males and severe state were also shown. CONCLUSIONS: The isocaloric coconut oil enriched Mediterranean diet seems to improve cognitive functions in patients with AD, with differences according to patient sex and degree of severity of the disease, although more studies in this line are needed.

In Vivo MRI of Amyloid Plaques in a Cholesterol-Fed Rabbit Model of Alzheimer's Disease. - Chen, Yuanxin; Lim, Patrick; Rogers, Kem A; Rutt, Brian K; Ronald, John A (J Alzheimers Dis, 2018)
Hypercholesterolemia has been identified as a risk factor for Alzheimer's disease. In this study, rabbits were fed either a cholesterol diet or normal chow diet for 24 months. At endpoint, in vivo MRI was performed at the field strength of 3 Tesla using fast imaging employing steady state acquisition without (FIESTA) or with susceptibility-weighted post-processing (SWI-FIESTA) and susceptibility-weighted imaging with multi-echo acquisition (SWAN). This imaging revealed signal voids/hypointensities throughout the cortex, sub-cortex, and hippocampus of cholesterol-fed animals compared to control animals. Quantitative image analysis corroborated these qualitative findings and highlighted that SWI processing of FIESTA images significantly improved the detectability of plaques (p < 0.05). Aβ immunostaining and Prussian blue staining for iron demonstrated that the voids in MR images corresponded to iron-laden Aβ-positive plaques. This study demonstrates non-invasive in vivo visualization of Aβ plaques in a diet-induced large animal model of Alzheimer's disease. This work lays the foundation for future work focusing on longitudinal monitoring of plaque formation in this model and the effects of diet or drug interventions.

Increased Albumin Oxidation in Cerebrospinal Fluid and Plasma from Alzheimer's Disease Patients. - Costa, Montserrat; Horrillo, Raquel; Ortiz, Ana María; Pérez, Alba; Mestre, Anna; Ruiz, Agustin; Boada, Merce; Grancha, Salvador (J Alzheimers Dis, 2018)
BACKGROUND: Oxidative stress in the brain and peripheral systems is considered a major player in Alzheimer's disease (AD). Albumin is the main transporter and the main extracellular antioxidant in the human body. OBJECTIVE: Here we explore for the first time the oxidation status of cerebrospinal fluid (CSF) and plasma albumin in AD in comparison to healthy subjects. METHODS: Plasma and CSF samples were obtained from mild-moderate AD patients and control healthy age-matched donors. Albumin redox state forms (reduced: HMA; reversibly oxidized: HNA1; irreversibly oxidized: HNA2) were determined by HPLC. Albumin post-translational modifications (PTM) analysis was performed by mass spectrometry. RESULTS: HPLC showed less HMA in AD plasma than in controls (54.1% versus 65.2% ; p < 0.0001), mainly at expense of HNA1 (42.8% versus 32.5% ; p < 0.0001). In AD CSF, HMA was drastically decreased compared to controls (9.6% versus 77.4% ; p < 0.0001), while HNA2 was increased (52.8% versus 7.4% ; p < 0.0001). In AD patients but not in healthy controls, CSF albumin was much more irreversibly oxidized than in plasma (close to 20-fold increase in HNA2). PTM analysis showed that AD CSF albumin samples behave as a differentiated cluster, thus confirming the albumin oxidative pattern observed by HPLC. CONCLUSION: CSF albumin oxidation in AD patients was dramatically increased comparing to healthy controls, while in plasma this increase was smaller. CSF albumin in AD patients was much more oxidized than in plasma, but this effect was not observed in healthy controls. These results suggest that albumin oxidation, especially in CSF, and its role in AD deserves further investigation.

Increased Vulnerability of the Hippocampus in Transgenic Mice Overexpressing APP and Triple Repeat Tau. - Arner, Andrew; Rockenstein, Edward; Mante, Michael; Florio, Jazmin; Masliah, Deborah; Salehi, Bahar; Adame, Anthony; Overk, Cassia; Masliah, Eliezer; Rissman, Robert A (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is the most common tauopathy, characterized by progressive accumulation of amyloid-β (Aβ) and hyperphosphorylated tau. While pathology associated with the 4-repeat (4R) tau isoform is more abundant in corticobasal degeneration and progressive supranuclear palsy, both 3R and 4R tau isoforms accumulate in AD. Many studies have investigated interactions between Aβ and 4R tau in double transgenic mice, but few, if any, have examined the effects of Aβ with 3R tau. To examine this relationship, we crossed our APP751 mutant line with our recently characterized 3R tau mutant model to create a bigenic line (hAPP-3RTau) to model AD neuropathology. Mice were analyzed at 3 and 6 months of age for pathological and behavioral endpoints. While both the 3RTau and the hAPP-3RTau mice showed neuronal loss, increased tau aggregation, Aβ plaques and exhibited more behavioral deficits compared to the non-tg control, the bigenic mice often displaying relatively worsening levels. We found that even in young animals we found that the presence of APP/Aβ increased the accumulation of 3R tau in the neocortex and hippocampus. This observation was accompanied by activation of GSK3 and neurodegeneration in the neocortex and CA1 region. These results suggest that in addition to 4R tau, APP/Aβ may also enhance accumulation of 3R tau, a process which may be directly relevant to pathogenic pathways in AD. Our results demonstrate that this bigenic model closely parallels the pathological course of AD and may serve as a valuable model for testing new pharmacological interventions.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Disease Models, Animal; Female; Glycogen Synthase Kinase 3; Hippocampus; Humans; Male; Mice; Mice, Transgenic; Neocortex; tau Proteins; Tauopathies

An Inducible Alpha-Synuclein Expressing Neuronal Cell Line Model for Parkinson's Disease1. - Vasquez, Velmarini; Mitra, Joy; Perry, George; Rao, K S; Hegde, Muralidhar L (J Alzheimers Dis, 2018)
Altered expression of α-synuclein is linked to Parkinson's disease (PD). A major challenge to explore how the increased α-synuclein affect neurotoxicity is the lack of a suitable human neuronal cell model that mimics this scenario. Its expression in neural precursors affects their differentiation process, in addition to the neuronal adaptability and variability in maintaining a constant level of expression across passages. Here, we describe an SH-SY5Y line harboring Tet-ON SNCA cDNA cassette that allows for induction of controlled α-synuclein expression after neuronal differentiation, which can be an important tool for PD research.

Inflammatory Cytokine, IL-1β, Regulates Glial Glutamate Transporter via microRNA-181a in vitro. - Zumkehr, Joannee; Rodriguez-Ortiz, Carlos J; Medeiros, Rodrigo; Kitazawa, Masashi (J Alzheimers Dis, 2018)
Glutamate overload triggers synaptic and neuronal loss that potentially contributes to neurodegenerative diseases including Alzheimer's disease (AD). Glutamate clearance and regulation at synaptic clefts is primarily mediated by glial glutamate transporter 1 (GLT-1). We determined that inflammatory cytokines significantly upregulated GLT-1 through microRNA-181a-mediated post-transcriptional modifications. Unveiling the key underlying mechanisms modulating GLT-1 helps better understand its physiological and pathological interactions with cytokines. Primary murine astrocyte and neuron co-culture received 20 ng/mL IL-1β, TNF-α, or IL-6 for 48 h. Soluble proteins or total RNA were extracted after treatment for further analyses. Treatment with inflammatory cytokines, IL-1β and TNF-α, but not IL-6, significantly increased GLT-1 steady-state levels (p≤0.05) without affecting mRNA levels, suggesting the cytokine-induced GLT-1 was regulated through post-transcriptional modifications. Among the candidate microRNAs predicted to modulate GLT-1, only microRNA-181a was significantly decreased following the IL-1β treatment (p≤0.05). Co-treatment of microRNA-181a mimic in IL-1β-treated primary astrocytes and neurons effectively blocked the IL-1β-induced upregulation of GLT-1. Lastly, we attempted to determine the link between GLT-1 and microRNA-181a in human AD brains. A significant reduction of GLT-1 was found in AD hippocampus tissues, and the ratio of mature microRNA-181a over primary microRNA-181a had an increasing tendency in AD. MicroRNA-181a controls rapid modifications of GLT-1 levels in astrocytes. Cytokine-induced inhibition of microRNA-181a and subsequent upregulation of GLT-1 may have physiological implications in synaptic plasticity while aberrant maturation of microRNA-181a may be involved in pathological consequences in AD.

Influence of Butyrylcholinesterase in Progression of Mild Cognitive Impairment to Alzheimer's Disease. - Gabriel, António José; Almeida, Maria Rosário; Ribeiro, Maria Helena; Carneiro, Diogo; Valério, Daniela; Pinheiro, Ana Cristina; Pascoal, Rui; Santana, Isabel; Baldeiras, Ines (J Alzheimers Dis, 2018)
BACKGROUND: Several demographic and genetic prognostic factors of conversion from mild cognitive impairment (MCI) to Alzheimer's disease (AD) have been recognized so far. The most frequent polymorphism of butyrylcholinesterase (BuChE), the K-variant, has been proposed as a risk factor for AD, but data regarding its influence on early disease progression is still limited. OBJECTIVE: To investigate the influence of the BuChE-K variant in MCI progression to AD. METHODS: 96 MCI patients were included in the study and were genotyped for BuChE-K variant and Apolipoprotein E (ApoE). Cerebrospinal fluid (CSF) BuChE activity, as well as the levels of AD biomarkers amyloid-β 42 (Aβ42), total and hyperphosphorylated tau (t-tau and p-tau) were also determined. RESULTS: No significant differences were found in either BuChE-K variant or BuChE activity between MCI patients that progressed to AD (MCI-AD) and patients that remained stable during clinical follow-up (MCI-St). As expected, baseline CSF levels of Aβ42 were significantly lower and t-Tau, p-Tau, and ApoE ɛ4 allele frequency were significantly higher in MCI-AD patients. An association between the ApoE ɛ4 allele and the BuChE-K variant in MCI-AD, but not in MCI-St patients, was found with patients carrying both alleles presenting the highest incidence of progression and the lowest estimated time of progression to AD. CONCLUSION: Although BuChE-K alone does not seem to play a major role in progression to AD in MCI patients, a synergistic effect with the ApoE ɛ4 allele was found, highlighting the importance of assessing these combined genotypes for evaluating risk progression in MCI patients.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Biomarkers; Butyrylcholinesterase; Cognitive Dysfunction; Disease Progression; Female; Genetic Predisposition to Disease; Humans; Kaplan-Meier Estimate; Male; Middle Aged; Risk Factors; tau Proteins

Influence of Lewy Pathology on Alzheimer's Disease Phenotype: A Retrospective Clinico-Pathological Study. - Roudil, Jennifer; Deramecourt, Vincent; Dufournet, Boris; Dubois, Bruno; Ceccaldi, Mathieu; Duyckaerts, Charles; Pasquier, Florence; Lebouvier, Thibaud (J Alzheimers Dis, 2018)
BACKGROUND: Studies have shown the frequent coexistence of Lewy pathology (LP) in Alzheimer's Disease (AD). OBJECTIVE: The aim of this study was to determine the influence of LP on the clinical and cognitive phenotype in a cohort of patients with a neuropathological diagnosis of AD. METHODS: We reviewed neuropathologically proven AD cases, reaching Braak stages V and VI in the brain banks of Lille and Paris between 1993 and 2016, and classified them according to LP extension (amygdala, brainstem, limbic, or neocortical). We then searched patient files for all available clinical and neuropsychiatric features and neuropsychological data. RESULTS: Thirty-three subjects were selected for this study, among which 16 were devoid of LP and 17 presented AD with concomitant LP. The latter were stratified into two subgroups according to LP distribution: 7 were AD with amygdala LP and 10 were AD with 'classical' (brainstem, limbic or neocortical) LP. When analyzing the incidence of each clinical feature at any point during the disease course, we found no significant difference in symptom frequency between the three groups. However, fluctuations appeared significantly earlier in patients with classical LP (2±3.5 years) than in patients without LP (7±1.7 years) or with amygdala LP (8±2.8 years; p < 0.01). There was no significant difference in cognitive profiles. CONCLUSION: Our findings suggest that the influence of LP on the clinical phenotype of AD is subtle. Core features of dementia with Lewy bodies do not allow clinical diagnosis of a concomitant LP on a patient-to-patient basis.

Interrelationship between the Levels of C9orf72 and Amyloid-β Protein Precursor and Amyloid-β in Human Cells and Brain Samples. - Leskelä, Stina; Takalo, Mari; Marttinen, Mikael; Huber, Nadine; Paananen, Jussi; Mitra, Vikram; Rauramaa, Tuomas; Mäkinen, Petra; Leinonen, Ville; Soininen, Hilkka; Pike, Ian; Remes, Anne M; et al. (J Alzheimers Dis, 2018)
A subset of C9orf72 repeat expansion-carrying frontotemporal dementia patients display an Alzheimer-like decrease in cerebrospinal fluid amyloid-β (Aβ) biomarker levels. We report that downregulation of C9orf72 in non-neuronal human cells overexpressing amyloid-β protein precursor (AβPP) resulted in increased levels of secreted AβPP fragments and Aβ, while levels of AβPP or its C-terminal fragments (CTFs) remained unchanged. In neuronal cells, AβPP and C83 CTF levels were decreased upon C9orf72 knockdown, but those of secreted AβPP fragments or Aβ remained unchanged. C9orf72 protein levels significantly increased in human brain with advancing neurofibrillary pathology and positively correlated with brain Aβ42 levels. Our data suggest that altered C9orf72 levels may lead to cell-type specific alterations in AβPP processing, but warrant further studies to clarify the underlying mechanisms.

Kainic Acid Impairs the Memory Behavior of APP23 Mice by Increasing Brain Amyloid Load through a Tumor Necrosis Factor-α-Dependent Mechanism. - Ruan, Yang; Guo, Shi-Jie; Wang, Xu; Dong, Dong; Shen, Dong-Hui; Zhu, Jie; Zheng, Xiang-Yu (J Alzheimers Dis, 2018)
Kainic acid (KA) was recently identified as an epileptogenic and neuroexcitotoxic agent that is responsible for inducing learning and memory deficits in various neurodegenerative diseases, such as Alzheimer's disease (AD). However, the mechanism by which KA acts upon AD remains unclear. To this end, we presently investigated the roles of KA in processing amyloid-β protein precursor (AβPP) and amyloid-β protein (Aβ) loads during the course of AD development and progression. Specifically, KA treatment clearly caused the upregulation of tumor necrosis factor α (TNF-α) via activation of the PI3-K/AKT, ERK1/2, and p65 pathways in glial cells. TNF-α secreted from glial cells was then found to be responsible for stimulating the expression of BACE-1 and PS1/2, which resulted in the production and deposition of Aβ in neurons. Finally, the accumulation and aggregation of Aβ lead to the cognitive decline of APP23 mice. These results indicate that KA accelerates the progression of AD by inducing the crosstalk between glial cells and neurons.

Ketogenic Medium Chain Triglycerides Increase Brain Energy Metabolism in Alzheimer's Disease. - Croteau, Etienne; Castellano, Christian-Alexandre; Richard, Marie Anne; Fortier, Mélanie; Nugent, Scott; Lepage, Martin; Duchesne, Simon; Whittingstall, Kevin; Turcotte, Éric E; Bocti, Christian; Fülöp, Tamás; Cunnane, Stephen C (J Alzheimers Dis, 2018)
BACKGROUND: In Alzheimer's disease (AD), it is unknown whether the brain can utilize additional ketones as fuel when they are derived from a medium chain triglyceride (MCT) supplement. OBJECTIVE: To assess whether brain ketone uptake in AD increases in response to MCT as it would in young healthy adults. METHODS: Mild-moderate AD patients sequentially consumed 30 g/d of two different MCT supplements, both for one month: a mixture of caprylic (55%) and capric acids (35%) (n = 11), followed by a wash-out and then tricaprylin (95%; n = 6). Brain ketone (11C-acetoacetate) and glucose (FDG) uptake were quantified by PET before and after each MCT intervention. RESULTS: Brain ketone consumption doubled on both types of MCT supplement. The slope of the relationship between plasma ketones and brain ketone uptake was the same as in healthy young adults. Both types of MCT increased total brain energy metabolism by increasing ketone supply without affecting brain glucose utilization. CONCLUSION: Ketones from MCT compensate for the brain glucose deficit in AD in direct proportion to the level of plasma ketones achieved.

Learning Processes and Brain Connectivity in A Cognitive-Motor Task in Neurodegeneration: Evidence from EEG Network Analysis. - Vecchio, Fabrizio; Miraglia, Francesca; Quaranta, Davide; Lacidogna, Giordano; Marra, Camillo; Rossini, Paolo Maria (J Alzheimers Dis, 2018)
Electroencephalographic (EEG) rhythms are linked to any kind of learning and cognitive performance including motor tasks. The brain is a complex network consisting of spatially distributed networks dedicated to different functions including cognitive domains where dynamic interactions of several brain areas play a pivotal role. Brain connectome could be a useful approach not only to mechanisms underlying brain cognitive functions, but also to those supporting different mental states. This goal was approached via a learning task providing the possibility to predict performance and learning along physiological and pathological brain aging. Eighty-six subjects (22 healthy, 47 amnesic mild cognitive impairment, 17 Alzheimer's disease) were recruited reflecting the whole spectrum of normal and abnormal brain connectivity scenarios. EEG recordings were performed at rest, with closed eyes, both before and after the task (Sensory Motor Learning task consisting of a visual rotation paradigm). Brain network properties were described by Small World index (SW), representing a combination of segregation and integration properties. Correlation analyses showed that alpha 2 SW in pre-task significantly predict learning (r  =  -0.2592, p < 0.0342): lower alpha 2 SW (higher possibility to increase during task and better the learning of this task), higher the learning as measured by the number of reached targets. These results suggest that, by means of an innovative analysis applied to a low-cost and widely available techniques (SW applied to EEG), the functional connectome approach as well as conventional biomarkers would be effective methods for monitoring learning progress during training both in normal and abnormal conditions.

Leisure-Time Physical Activity and the Risk of Incident Dementia: The Mayo Clinic Study of Aging. - Krell-Roesch, Janina; Feder, Nathanael T; Roberts, Rosebud O; Mielke, Michelle M; Christianson, Teresa J; Knopman, David S; Petersen, Ronald C; Geda, Yonas E (J Alzheimers Dis, 2018)
We conducted a prospective cohort study derived from the population-based Mayo Clinic Study of Aging. We investigated if leisure-time physical activity among individuals with mild cognitive impairment (MCI) was associated with a decreased risk of developing dementia. 280 persons aged≥70 years (median 81 years, 165 males) with MCI and available data from neurologic evaluation, neuropsychological testing, and questionnaire-based physical activity assessment, were followed for a median of 3 years to the outcomes of incident dementia or censoring variables. We conducted Cox proportional hazards regression analyses with age as a time scale and adjusted for sex, education, medical comorbidity, depression, and APOE ɛ4 status. Moderate intensity midlife physical activity among MCI participants was significantly associated with a decreased risk of incident dementia (HR = 0.64; 95% CI, 0.41-0.98). There was a non-significant trend for a decreased risk of dementia for light and vigorous intensity midlife physical activity, as well as light and moderate intensity late-life physical activity. In conclusion, we observed that physical activity may be associated with a reduced risk of dementia among individuals with MCI. Furthermore, intensity and timing of physical activity may be important factors when investigating this association.

Lentivirus-Mediated HDAC3 Inhibition Attenuates Oxidative Stress in APPswe/PS1dE9 Mice. - Yu, Linjie; Liu, Yi; Jin, Yuexinzi; Cao, Xiang; Chen, Jian; Jin, Jiali; Gu, Yue; Bao, Xinyu; Ren, Zhuoying; Xu, Yun; Zhu, Xiaolei (J Alzheimers Dis, 2018)
Amyloid-β (Aβ) induces a burst of oxidative stress and plays a critical role in the pathogenesis of Alzheimer's disease (AD). Our previous results have shown that histone deacetylase 3 (HDAC3) inhibition ameliorates spatial memory deficits and decreases the Aβ burden in the brains of 9-month-old APPswe/PS1dE9 (APP/PS1) mice. In this study, we investigated the role of HDAC3 inhibition in oxidative stress in vivo and in vitro models of AD. HDAC3 was detected mainly in the neurons, and HDAC3 inhibition significantly decreased reactive oxygen species generation and improved primary cortical neuron viability. In addition, HDAC3 inhibition attenuated spatial memory dysfunction in 6-month-old APP/PS1 mice, and decreased the apoptotic rate in the hippocampi as demonstrated by TUNEL staining. HDAC3 inhibition also reduced markers of lipid peroxidation, protein oxidation, and DNA/RNA oxidation in the hippocampi of APP/PS1 mice. Moreover, HDAC3 inhibition inactivated the c-Abl/MST1/YAP signaling pathway in the hippocampi of APP/PS1 mice. In conclusion, our data show that HDAC3 inhibition can attenuate spatial memory deficits and inhibit oxidative stress in APP/PS1 mice; these results indicate a potential strategy for AD treatment.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Disease Models, Animal; Hippocampus; Histone Deacetylases; Lentivirus; Male; Maze Learning; Mice; Mice, Inbred C57BL; Mice, Transgenic; Neurons; Oxidative Stress; Plaque, Amyloid; Primary Cell Culture; Reactive Oxygen Species; Spatial Memory; tau Proteins

Lipid Metabolism and Survival Across the Frontotemporal Dementia-Amyotrophic Lateral Sclerosis Spectrum: Relationships to Eating Behavior and Cognition. - Ahmed, Rebekah M; Highton-Williamson, Elizabeth; Caga, Jashelle; Thornton, Nicolette; Ramsey, Eleanor; Zoing, Margaret; Kim, Woojin Scott; Halliday, Glenda M; Piguet, Olivier; Hodges, John R; Farooqi, I Sadaf; Kiernan, Matthew C (J Alzheimers Dis, 2018)
BACKGROUND: Patients with frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) exhibit changes in eating behavior that could potentially affect lipid levels. OBJECTIVE: This study aimed to document changes in lipid metabolism across the ALS-FTD spectrum to identify potential relationships to eating behavior (including fat intake), cognitive change, body mass index (BMI), and effect on survival. METHODS: One hundred and twenty-eight participants were recruited: 37 ALS patients, 15 ALS patients with cognitive and behavioral change (ALS-Plus), 13 ALS-FTD, 31 behavioral variant FTD, and 32 healthy controls. Fasting total cholesterol, low density lipoprotein cholesterol (LDL), high density lipoprotein cholesterol (HDL) and triglyceride levels were measured and correlated to eating behavior (caloric, fat intake), cognitive change, and BMI; effect on survival was examined using cox regression analyses. RESULTS: There was a spectrum of lipid changes from ALS to FTD with increased triglyceride (p < 0.001), total cholesterol/HDL ratio (p < 0.001), and lower HDL levels (p = 0.001) in all patient groups compared to controls. While there was no increase in total cholesterol levels, a higher cholesterol level was found to correlate with 3.25 times improved survival (p = 0.008). Triglyceride and HDL cholesterol levels correlated to fat intake, BMI, and measures of cognition and disease duration. CONCLUSION: A spectrum of changes in lipid metabolism has been identified in ALS-FTD, with total cholesterol levels found to potentially impact on survival. These changes were mediated by changes in fat intake, and BMI, and may also be mediated by the neurodegenerative process, offering the potential to modify these factors to slow disease progression and improve survival.
Keywords: Adult; Aged; Amyotrophic Lateral Sclerosis; Australia; Body Mass Index; Case-Control Studies; Cholesterol; Cholesterol, HDL; Cognition; Energy Intake; Feeding Behavior; Female; Frontotemporal Dementia; Humans; Lipid Metabolism; Male; Middle Aged; Neuropsychological Tests; Survival Analysis

A Long Journey into Aging, Brain Aging, and Alzheimer's Disease Following the Oxidative Stress Tracks. - Mecocci, Patrizia; Boccardi, Virginia; Cecchetti, Roberta; Bastiani, Patrizia; Scamosci, Michela; Ruggiero, Carmelinda; Baroni, Marta (J Alzheimers Dis, 2018)
The Editors of the Journal of Alzheimer's Disease invited Professor Patrizia Mecocci to contribute a review article focused on the importance and implications of her research on aging, brain aging, and senile dementias over the last years. This invitation was based on an assessment that she was one of the journal's top authors and a strong supporter of the concept that oxidative stress is a major contributor to several alterations observed in age-related conditions (sarcopenia, osteoporosis) and, more significantly, in brain aging suggesting a pivotal role in the pathogenesis and progression of one of the most dramatic age-related diseases, Alzheimer's disease (AD). Her first pioneering research was on the discovery of high level of 8-hydroxy-2'-deoxyguanosine (OH8dG), a marker of oxidation in nucleic acids, in mitochondrial DNA isolated from cerebral cortex. This molecule increases progressively with aging and more in AD brain, supporting the hypothesis that oxidative stress, a condition of unbalance between the production of reactive oxygen species and antioxidants, gives a strong contribution to the high incidence of AD in old age subjects. OH8dG also increases in peripheral lymphocyte from AD subjects, suggesting that AD is not only a cerebral but also a systemic disease. The role of antioxidants, particularly vitamin E and zinc, were also studied in longevity and in cognitive decline and dementia. This review shows the main findings from Mecocci's laboratory related to oxidative stress in aging, brain aging, and AD and discusses the importance and implications of some of the major achievements in this field of research.
Keywords: Aging; Alzheimer Disease; Animals; Brain; Humans; Oxidative Stress

Longitudinal Changes in Serum Glucose Levels are Associated with Metabolic Changes in Alzheimer's Disease Related Brain Regions. - Burns, Christine M; Kaszniak, Alfred W; Chen, Kewei; Lee, Wendy; Bandy, Daniel J; Caselli, Richard J; Reiman, Eric M (J Alzheimers Dis, 2018)
BACKGROUND: The association between longitudinal changes in serum glucose level and longitudinal changes in [18F] Fluorodeoxyglucose-PET (FDG PET) measurements of Alzheimer's disease (AD) risk are unknown. OBJECTIVE: To investigate whether variation in serum glucose levels across time are associated with changes in FDG PET measurements of cerebral metabolic rate for glucose (rCMRgl) in brain regions preferentially affected by Alzheimer's disease (AD). METHODS: Participants are a subset of a prospective cohort study investigating FDG PET, apolipoprotein E (APOE) ɛ4, and risk for AD which includes data from baseline, interim, and follow up visits over 4.4±1.0-years. An automated brain-mapping algorithm was utilized to characterize and compare associations between longitudinal changes in serum glucose levels and longitudinal changes in rCMRgl. RESULTS: This study included 80 adults aged 61.5±5 years, including 38 carriers and 42 non-carriers of the APOE ɛ4 allele. Longitudinal increases in serum glucose levels were associated with longitudinal CMRgl decline in the vicinity of parietotemporal, precuneus/posterior cingulate, and prefrontal brain regions preferentially affected by AD (p < 0.05, corrected for multiple comparisons). Findings remained significant when controlled for APOE ɛ4 status and baseline and advancing age. CONCLUSIONS: Additional studies are needed to clarify and confirm the relationship between longitudinal changes in peripheral glucose and FDG PET measurements of AD risk. Future findings will set the stage on the use of FDG PET in the evaluation of possible interventions that target risk factors for the development of AD.
Keywords: Aged; Alzheimer Disease; Apolipoprotein E4; Blood Glucose; Brain; Brain Mapping; Female; Fluorodeoxyglucose F18; Heterozygote; Humans; Longitudinal Studies; Male; Middle Aged; Positron-Emission Tomography; Prospective Studies; Radiopharmaceuticals

Longitudinal Neuroimaging Analysis in Mild-Moderate Alzheimer's Disease Patients Treated with Plasma Exchange with 5% Human Albumin. - Cuberas-Borrós, Gemma; Roca, Isabel; Boada, Merce; Tárraga, Lluís; Hernandez, Isabel; Buendia, Mar; Rubio, Lourdes; Torres, Gustavo; Bittini, Ángel; Guzmán-de-Villoria, Juan A; Pujadas, Francesc; Torres, Mireia; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Recently, modifications of Aβ1-42 levels in CSF and plasma associated with improvement in memory and language functions have been observed in patients with mild-moderate Alzheimer's disease (AD) treated with plasma exchange (PE) with albumin replacement. OBJECTIVE: To detect structural and functional brain changes in PE-treated AD patients as part of a Phase II clinical trial. METHODS: Patients received between 3 and 18 PE with albumin (Albutein® 5%, Grifols) or sham-PE (controls) for 21 weeks (divided in one intensive and two maintenance periods) followed by 6-month follow-up. Brain perfusion assessed by SPECT scans using an automated software (NeuroGam®) and brain structural changes assessed by MRI were performed at weeks 0 (baseline), 21, and 44 (with additional SPECT at weeks 9 and 33). Statistical parametric mapping (voxel-based analysis, SPM) and Z-scores calculations were applied to investigate changes to baseline. RESULTS: 42 patients were recruited (39 evaluable; 37 analyzed: 18 PE-treated; 19 controls). There was a trend toward decreasing hippocampi and total intracranial volume for both patient groups during the study (p < 0.05). After six months, PE-treated patients had less cerebral perfusion loss than controls in frontal, temporal, and parietal areas, and perfusion stabilization in Brodmann area BA38-R during the PE-treatment period (p < 0.05). SPM analysis showed stabilization or absence of progression of perfusion loss in PE-treated patients until week 21, not observed in controls. CONCLUSIONS: Mild-moderate AD patients showed decreased brain volume and impairment of brain perfusion as expected for the progression of the disease. PE-treatment with albumin replacement favored the stabilization of perfusion.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuroimaging; Plasma Exchange; Serum Albumin, Human; Time Factors; Tomography, Emission-Computed, Single-Photon; Treatment Outcome

Long-Term Follow Up of Patients with Mild-to-Moderate Alzheimer's Disease Treated with Bapineuzumab in a Phase III, Open-Label, Extension Study. - Salloway, Stephen P; Sperling, Reisa; Fox, Nick C; Sabbagh, Marwan N; Honig, Lawrence S; Porsteinsson, Anton P; Rofael, Hany; Ketter, Nzeera; Wang, Daniel; Liu, Enchi; Carr, Stephen; Black, Ronald S; et al. (J Alzheimers Dis, 2018)
BACKGROUND: A 3-year extension of two Phase III parent studies of intravenous (IV) bapineuzumab in patients with mild-to-moderate Alzheimer's disease dementia (apolipoprotein (APOE) ɛ4 carriers and noncarriers) is summarized. OBJECTIVES: The primary and secondary objectives were to evaluate the long-term safety, tolerability, and maintenance of efficacy of bapineuzumab. METHODS: A multicenter study in patients who had participated in double-blind placebo-controlled parent studies. Patients enrolled in the extension study were assigned to receive IV infusions of bapineuzumab (0.5 or 1.0 mg/kg) every 13 weeks until termination but were blinded to whether they had received bapineuzumab or placebo in the parent studies. RESULTS: A total of 1,462 (688 were APOEɛ4 carriers and 774 were noncarriers) patients were enrolled. Extension-onset adverse events occurred in >81% of the patients in each dose group. Fall, urinary tract infection, agitation, and ARIA-E occurred in ≥10% of participants. The incidence proportion of ARIA-E was higher among carriers and noncarriers who received bapineuzumab for the first time in the extension study (11.8% and 5.4%, respectively) versus those who were previously exposed in the parent studies (5.1% and 1.3%, respectively). After 6 to 12 months exposure to bapineuzumab IV in the extension study, similar deterioration of cognition and function occurred with no significant differences between the dose groups. CONCLUSIONS: Infusion of bapineuzumab 0.5 or 1.0 mg/kg every 13 weeks for up to 3 years was generally well tolerated, with a safety and tolerability profile similar to that in previous studies.

Low Prevalence of Cancer in Patients with Frontotemporal Lobar Degeneration. - Katisko, Kasper; Haapasalo, Annakaisa; Koivisto, Anne; Krüger, Johanna; Hartikainen, Päivi; Korhonen, Ville; Helisalmi, Seppo; Herukka, Sanna-Kaisa; Remes, Anne M; Solje, Eino (J Alzheimers Dis, 2018)
Several studies have reported reduced risk of cancer in patients with Alzheimer's disease (AD) or Parkinson's disease. The relationship between cancer and frontotemporal lobar degeneration (FTLD) has not been previously reported. Here, our aim was to evaluate the occurrence of cancer in Finnish FTLD patients with a high proportion of C9ORF72 repeat expansion carriers in comparison to age- and sex-matched group of AD patients and control subjects classified as not cognitively impaired (NCI). The prevalence of cancer was 9.7% in FTLD, 18.7% in AD, and 17.4% in NCI (FTLD versus AD p = 0.012, FTLD versus NCI p = 0.029) groups. No differences were observed between C9ORF72 repeat expansion carriers and non-carriers inside the FTLD group. To our knowledge, this is the first study showing significantly lower prevalence of cancer in FTLD patients compared to patients with AD or NCI subjects. Our data suggest an inverse association between neurodegeneration and cancer and that FTLD-specific mechanisms may underlie the especially strong inverse association observed in this study.
Keywords: Aged; Alzheimer Disease; C9orf72 Protein; DNA Repeat Expansion; Female; Finland; Frontotemporal Lobar Degeneration; Heterozygote; Humans; Male; Middle Aged; Neoplasms; Prevalence

Mediterranean Diet, Its Components, and Amyloid Imaging Biomarkers. - Vassilaki, Maria; Aakre, Jeremiah A; Syrjanen, Jeremy A; Mielke, Michelle M; Geda, Yonas E; Kremers, Walter K; Machulda, Mary M; Alhurani, Rabe E; Staubo, Sara C; Knopman, David S; Petersen, Ronald C; Lowe, Val J; et al. (J Alzheimers Dis, 2018)
BACKGROUND: There is accumulating evidence suggesting that diet may play a role in preventing or delaying cognitive decline and dementia, but the underlying biological mechanisms are not well understood. OBJECTIVES: To examine the cross-sectional associations of the Mediterranean diet (MeDi) and its components with 11C-PiB-PET scan measures of amyloid-β (Aβ) deposition. METHODS: The study consisted of 278 Mayo Clinic Study of Aging participants 70+ years old, who were cognitively unimpaired (CU) at the time of completion of the Food Frequency Questionnaire (FFQ) and when they underwent PET imaging. Adherence to the MeDi was assessed by computing the MeDi score for each participant. All scans were performed after the FFQ completion; median [IQR] time between FFQ and Aβ PET was 3.5 (1.4) years. Z-scores were created for component, macro- and micronutrients measured. Linear and logistic regression models were adjusted for age, sex, education, apolipoprotein E (APOE) ɛ4 allele carrier status, time interval between the FFQ completion and PET scan, and total energy intake. RESULTS: Participants' median age at FFQ was 77.7 years (55.8% men; 26.6% with an APOE ɛ4 allele). Higher MeDi score (linear regression slope (beta):-0.035, p = 0.012; per standard deviation increase), vegetable intake (beta:-0.043, p = 0.002), intake of vitamin A (beta:-0.041, p = 0.003) or β-carotene (beta: -0.039, p = 0.005) from food sources and moderate alcohol consumption (beta: -0.074, p = 0.03) were associated with lower 11C-PiB standardized uptake value ratio. CONCLUSION: Findings are consistent with previous studies suggesting that higher adherence to a MeDi pattern and higher vegetable consumption are associated with better neuroimaging biomarker profile. Prospective studies are needed to validate current findings.

Memory Binding Test Predicts Incident Dementia: Results from the Einstein Aging Study. - Mowrey, Wenzhu B; Lipton, Richard B; Katz, Mindy J; Ramratan, Wendy S; Loewenstein, David A; Zimmerman, Molly E; Buschke, Herman (J Alzheimers Dis, 2018)
BACKGROUND: The Memory Binding Test (MBT) demonstrated good cross-sectional discriminative validity and predicted incident aMCI. OBJECTIVE: To assess whether the MBT predicts incident dementia better than a conventional list learning test in a longitudinal community-based study. METHODS: As a sub-study in the Einstein Aging Study, 309 participants age≥70 initially free of dementia were administered the MBT and followed annually for incident dementia for up to 13 years. Based on previous work, poor memory binding was defined using an optimal empirical cut-score of≤17 on the binding measure of the MBT, Total Items in the Paired condition (TIP). Cox proportional hazards models were used to assess predictive validity adjusting for covariates. We compared the predictive validity of MBT TIP to that of the free and cued selective reminding test free recall score (FCSRT-FR; cut-score:≤24) and the single list recall measure of the MBT, Cued Recalled from List 1 (CR-L1; cut-score:≤12). RESULTS: Thirty-five of 309 participants developed incident dementia. When assessing each test alone, the hazard ratio (HR) for dementia was significant for MBT TIP (HR = 8.58, 95% CI: (3.58, 20.58), p < 0.0001), FCSRT-FR (HR = 4.19, 95% CI: (1.94, 9.04), p = 0.0003) and MBT CR-L1 (HR = 2.91, 95% CI: (1.37, 6.18), p = 0.006). MBT TIP remained a significant predictor of dementia (p = 0.0002) when adjusting for FCSRT-FR or CR-L1. CONCLUSIONS: Older adults with poor memory binding as measured by the MBT TIP were at increased risk for incident dementia. This measure outperforms conventional episodic memory measures of free and cued recall, supporting the memory binding hypothesis.

Meta-Analysis of Personality Traits in Alzheimer's Disease: A Comparison with Healthy Subjects. - D'Iorio, Alfonsina; Garramone, Federica; Piscopo, Fausta; Baiano, Chiara; Raimo, Simona; Santangelo, Gabriella (J Alzheimers Dis, 2018)
BACKGROUND: The role of specific personality traits as factor risks of Alzheimer's disease (AD) has been consistently found, whereas personality traits specifically related to AD (after the diagnosis) have not been outlined yet. OBJECTIVE: A meta-analysis of published studies was performed to determine whether AD patients have a distinctive personality trait profile compared to healthy subjects (HC), similar to or different from a premorbid personality profile consistently reported in previous studies. METHODS: A systematic literature search was performed using PsycInfo (PROQUEST), PubMed, and Scopus. The meta-analysis pooled results from primary studies using Hedges' g unbiased approach. RESULTS: The meta-analysis included 10 primary studies and revealed that, when the personality was evaluated by informant-rated measures, AD patients had significantly higher levels of Neuroticism, lower levels of Openness, Agreeableness, Conscientiousness, and Extraversion than HCs. When the personality was evaluated by self-rated measures, the results obtained from informants were confirmed for Neuroticism, Openness, and Extraversion but not for Agreeableness and Conscientiousness where AD patients and HCs achieved similar scores. CONCLUSIONS: The meta-analysis revealed that high Neuroticism and low Openness and Extraversion are distinctive personality traits significantly associated with a diagnosis of AD when evaluated both self-rated and informant-rated measures. This personality trait profile is similar to premorbid one, which contributes to development of AD over time. Therefore, our findings indirectly support the idea of specific premorbid personality traits as harbingers of AD.
Keywords: Alzheimer Disease; Case-Control Studies; Humans; Personality; Personality Inventory

Metabolic Dysfunction in Alzheimer's Disease: From Basic Neurobiology to Clinical Approaches. - Clarke, Julia R; Ribeiro, Felipe C; Frozza, Rudimar L; De Felice, Fernanda G; Lourenco, Mychael V (J Alzheimers Dis, 2018)
Clinical trials have extensively failed to find effective treatments for Alzheimer's disease (AD) so far. Even after decades of AD research, there are still limited options for treating dementia. Mounting evidence has indicated that AD patients develop central and peripheral metabolic dysfunction, and the underpinnings of such events have recently begun to emerge. Basic and preclinical studies have unveiled key pathophysiological mechanisms that include aberrant brain stress signaling, inflammation, and impaired insulin sensitivity. These findings are in accordance with clinical and neuropathological data suggesting that AD patients undergo central and peripheral metabolic deregulation. Here, we review recent basic and clinical findings indicating that metabolic defects are central to AD pathophysiology. We further propose a view for future therapeutics that incorporates metabolic defects as a core feature of AD pathogenesis. This approach could improve disease understanding and therapy development through drug repurposing and/or identification of novel metabolic targets.

Metabolic Syndrome and Amyloid Accumulation in the Aging Brain. - Gomez, Gabriela; Beason-Held, Lori L; Bilgel, Murat; An, Yang; Wong, Dean; Studenski, Stephanie; Ferrucci, Luigi; Resnick, Susan M (J Alzheimers Dis, 2018)
BACKGROUND: Recent studies show links between metabolic syndrome and Alzheimer's disease (AD) neuropathology. Understanding the link between vascular-related health conditions and dementia will help target at risk populations and inform clinical strategies for early detection and prevention of AD. OBJECTIVE: To determine whether metabolic syndrome is associated with global cerebral amyloid-β (Aβ) positivity and longitudinal Aβ accumulation. METHODS: Prospective study of 165 participants who underwent (11)C-Pittsburgh compound B (PiB) PET neuroimaging to measure Aβ, from June 2005 to May 2016. Metabolic syndrome was defined using the revised Third Adults Treatment Panel of the National Cholesterol Education Program criteria. Participants were classified as PiB+/- . Linear mixed effects models assessed the relationships between baseline metabolic syndrome and PiB status and regional Aβ change over time. RESULTS: A total of 165 cognitively normal participants of the Baltimore Longitudinal Study of Aging (BLSA) Neuroimaging substudy, aged 55-92 years (mean baseline age = 76.4 years, 85 participants were male), received an average of 2.5 PET-PiB scans over an average interval of 2.6 (3.08 SD) years between first and last visits. Metabolic syndrome was not associated with baseline PiB positivity or concurrent regional Aβ. Metabolic syndrome was associated with increased rates of Aβ accumulation in superior parietal and precuneus regions over time in the PiB+ group. Elevated fasting glucose and blood pressure showed individual associations with accelerated Aβ accumulation. CONCLUSION: Metabolic syndrome was associated with accelerated Aβ accumulation in PiB+ individuals and may be an important factor in the progression of AD pathology.

Minor Hallucinations in Alzheimer's Disease. - Ruiz, Maria; Arias, Alfonso; Sánchez-Llanos, Ernesto; Gil, Maria Pilar; López-Ortega, Ricard; Dakterzada, Faridé; Purroy, Francisco; Piñol-Ripoll, Gerard (J Alzheimers Dis, 2018)
BACKGROUND: Hallucinations may have a broad spectrum and include so-called minor hallucinations (MHs). MHs include passage hallucinations (PHs), visual illusions, and presence hallucinations (PrHs). OBJECTIVE: To determine the prevalence and characteristics of MHs in Alzheimer's disease (AD) and amnestic mild cognitive impairment (aMCI) patients, and to describe their potential relationship with cognition, behavioral symptoms, and use of psychoactive drugs. METHODS: We have recruited prospectively and consecutively 268 subjects (90 AD mild-moderate drug-naïve patients, 78 aMCI, and 100 controls). All patients responded to a semi-structured questionnaire in order to rate psychotic phenomena. Clinical, neuropsychological, and demographic data of patients with and without MH were compared with those of age, sex, and education-matched controls. RESULTS: The prevalence of MHs was 21.1% (19) in AD, 12.8% (10) in aMCI, and 3% (3) in controls (p < 0.01). The most frequent MH was PrH (9.3%), followed by PH (4.9%) and illusion (0.7%). Eight (27.8%) patients had more than one MH. After adjusting for age and gender, there was a negative correlation between the presence of MHs and MMSE score (r = -0.261; p < 0.01) and a positive correlation between MHs and Neuropsychiatric Inventory score (r = 0.237; p < 0.01). We did not observe a significant relationship between presence of MHs and the consumption of psychoactive drugs (p > 0.05). CONCLUSION: We have shown that the presence of MHs in patients with newly diagnosed, untreated AD and aMCI is more than controls. MHs were correlated with other behavioral symptoms and a worse cognitive performance. We suggest the specific interrogation for MHs as a clinical feature for this population.

Mitochondrial Dysfunction as a Predictor and Driver of Alzheimer's Disease-Like Pathology in OXYS Rats. - Tyumentsev, Mikhail A; Stefanova, Natalia A; Muraleva, Natalia A; Rumyantseva, Yulia V; Kiseleva, Elena; Vavilin, Valentin A; Kolosova, Nataliya G (J Alzheimers Dis, 2018)
Growing evidence suggests that mitochondrial dysfunction is an early event in sporadic Alzheimer's disease (AD), but the impact of mitochondrial dysfunction on the transition from healthy aging to AD remains elusive. Here we estimated the influence of mitochondrial dysfunction on the initiation of AD signs in OXYS rats, which simulate key characteristics of sporadic AD. We assessed the mitochondrial ultrastructure of pyramidal neurons of the hippocampus at the age preceding the development (age 20 days), during manifestation (4-5 months), and at the well-pronounced stages (18-24 months) of the AD-like pathology in OXYS rats. Ultrastructural alterations were collated with the amounts of proteins mediating mitochondrial dynamics [mitofusins (MFN1 and MFN2) and dynamin-1-like protein (DRP1)]; with activity of respiratory chain complexes I, IV, and V in the hippocampal mitochondria; with reactive oxygen species (ROS) production; and with expression of uncoupling protein 2 (UCP2) regulating ROS production. Already at the preclinical stage, OXYS rats showed some characteristic changes in hippocampal mitochondria, which increased in size with the manifestation and progression of AD-like pathology, including decreased activity of respiratory complexes against the background of greater fusion and formation of larger mitochondria. Signs of AD developed simultaneously with increasing dysfunction of mitochondria, with a dramatic decrease in their number, and with increased fission but without upregulation of ROS production (observed only in 20-day-old OXYS rats). Summarizing the data from our present and previous studies, we conclude that mitochondrial dysfunction appears to mediate or possibly even initiate pathological molecular cascades of AD-like pathology in OXYS rats and can be considered a predictor of the early development of the late-onset form of AD in humans.

A Multi-Center Study on Human Brain Glutathione Conformation using Magnetic Resonance Spectroscopy. - Shukla, Deepika; Mandal, Pravat K; Ersland, Lars; Grüner, Eli Renate; Tripathi, Manjari; Raghunathan, Partha; Sharma, Ankita; Chaithya, G R; Punjabi, Khushboo; Splaine, Christopher (J Alzheimers Dis, 2018)
Molecular dynamics simulation and in vitro nuclear magnetic resonance (NMR) studies on glutathione (GSH) indicated existence of closed and extended conformations. The present work in a multi-center research setting reports in-depth analysis of GSH conformers in vivo using a common magnetic resonance spectroscopy (MRS) protocol and signal processing scheme. MEGA-PRESS pulse sequence was applied on healthy subjects using 3T Philips MRI scanner (India) and 3T GE MRI scanner (Norway) using the same experimental parameters (echo time, repetition time, and selective 180° refocusing ON-pulse at 4.40 ppm and 4.56 ppm). All MRS data were processed at one site National Brain Research Center (NBRC) using in-house MRS processing toolbox (KALPANA) for consistency. We have found that both the closed and extended GSH conformations are present in human brain and the relative proportion of individual conformer peak depends on the specific selection of refocusing ON-pulse position in MEGA-PRESS pulse sequence. It is important to emphasize that in vivo experiments with different refocusing and inversion pulse positions, echo time, and voxel size, clearly evidence the presence of both the GSH conformations. The GSH conformer peak positions for the closed GSH (Cys-Hβ) peak at ∼2.80 ppm and extended GSH (Cys-Hβ) peak at ∼2.95 ppm remain consistent irrespective of the selective refocusing OFF-pulse positions. This is the first in vivo study where both extended and closed GSH conformers are detected using the MEGA-PRESS sequence employing the parameters derived from the high resolution in vitro NMR studies on GSH.

Mutation Screening of the CHCHD2 Gene for Alzheimer's Disease and Frontotemporal Dementia in Chinese Mainland Population. - Che, Xiang-Qian; Zhao, Qian-Hua; Huang, Yue; Li, Xia; Ren, Ru-Jing; Chen, Sheng-Di; Guo, Qi-Hao; Wang, Gang (J Alzheimers Dis, 2018)
As an important multifunctional protein involved in regulation of mitochondrial metabolism, CHCHD2 was identified as a causative gene for Parkinson's disease (PD), yet the relationship between CHCHD2 and neurodegenerative dementia is not well understood. We directly sequenced the entire coding region of CHCHD2 gene in 150 AD patients, 84 FTD patients, and 417 controls. Four rare putative pathogenic variants of CHCHD2, including rs142444896 (c.5C>T, p.P2L), rs752705344 (c.15C>G, p.S5R), rs145190179 (c.94G>A, p.A32T), and rs182992574 (c.255T>A, p.S85R) were identified from a cohort composed of 150 AD and 84 FTD patients. These results suggest that CH CHD2 gene play an important role in other neurodegenerative disorders from our dementia study in China.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Asian Continental Ancestry Group; Case-Control Studies; China; Female; Frontotemporal Dementia; Genetic Association Studies; Humans; Male; Middle Aged; Mitochondrial Proteins; Mutation; Transcription Factors

Negative 11C-PIB PET Predicts Lack of Alzheimer's Disease Pathology in Postmortem Examination. - Scheinin, Noora M; Gardberg, Maria; Röyttä, Matias; Rinne, Juha O (J Alzheimers Dis, 2018)
Our aim was to assess whether in vivo11C-PIB negative memory-impaired subjects may nonetheless exhibit brain Alzheimer's disease (AD) pathology. We re-evaluated the PET images and systematically characterized the postmortem neuropathology of six individuals who had undergone clinically indicated amyloid PET. The single case with negligible amyloid-β (Aβ) pathology had Lewy body disease, where concomitant AD changes are often seen. Further, the subject's plaques were predominantly diffuse. The predictive value of a negative 11C-PIB scan appears to be good, even in memory-impaired populations. Our results suggest that considerable neuritic Aβ plaque pathology in the absence of specific/cortical 11C-PIB binding upon PET is unlikely.

NeuroEPO Preserves Neurons from Glutamate-Induced Excitotoxicity. - Garzón, Fernando; Coimbra, Débora; Parcerisas, Antoni; Rodriguez, Yamila; García, Julio Cesar; Soriano, Eduardo; Rama, Ramón (J Alzheimers Dis, 2018)
Many experimental studies show that erythropoietin (EPO) has a neuroprotective action in the brain. EPO in acute and chronic neurological disorders, particularly in stroke, traumatic brain injury, Alzheimer's disease, Parkinson's disease, and amyotrophic lateral sclerosis, has neuroprotective effects. We previously reported the neuroprotective effect of NeuroEPO, a low sialic form of EPO, against oxidative stress induced by glutamate excitotoxicity. In this paper, we analyze the effect of NeuroEPO against apoptosis induced by glutamate excitotoxicity in primary neuronal cultures obtained from the forebrains of Wistar rat embryos after 17 days of gestation. Excitotoxicity was induced after nine days of in vitro culture by treatment with a culture medium containing 100μM glutamate for 15 min. To withdraw glutamate, a new medium containing 100 ng NeuroEPO/mL was added. Apoptosis was analyzed after 24 h. Images obtained by phase contrast microscopy show that neurons treated with glutamate exhibit cell body shrinkage, loss of dendrites that do not make contact with neighboring cells, and that NeuroEPO was able to preserve the morphological characteristics of the control. Immunocytochemistry images show that the culture is essentially pure in neurons; that glutamate causes cell mortality, and that this is partially avoided when the culture medium is supplemented with NeuroEPO. Activation of intrinsic apoptotic pathways was analyzed. The decreases in Bcl-2/Bax ratio, increase in the release of cytochrome c, and in the expression and activity of caspase-3 observed in cells treated with glutamate, were restored by NeuroEPO. The results from this study show that NeuroEPO protects cortical neurons from glutamate-induced apoptosis via upregulation of Bcl-2 and inhibit glutamate-induced activation of caspase-3.

Neuro-Immuno-Gene- and Genome-Editing-Therapy for Alzheimer's Disease: Are We There Yet? - Raikwar, Sudhanshu P; Thangavel, Ramasamy; Dubova, Iuliia; Ahmed, Mohammad Ejaz; Selvakumar, Pushpavathi Govindhasamy; Kempuraj, Duraisamy; Zaheer, Smita; Iyer, Shankar; Zaheer, Asgar (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a highly complex neurodegenerative disorder and the current treatment strategies are largely ineffective thereby leading to irreversible and progressive cognitive decline in AD patients. AD continues to defy successful treatment despite significant advancements in the field of molecular medicine. Repeatedly, early promising preclinical and clinical results have catapulted into devastating setbacks leading to multi-billion dollar losses not only to the top pharmaceutical companies but also to the AD patients and their families. Thus, it is very timely to review the progress in the emerging fields of gene therapy and stem cell-based precision medicine. Here, we have made sincere efforts to feature the ongoing progress especially in the field of AD gene therapy and stem cell-based regenerative medicine. Further, we also provide highlights in elucidating the molecular mechanisms underlying AD pathogenesis and describe novel AD therapeutic targets and strategies for the new drug discovery. We hope that the quantum leap in the scientific advancements and improved funding will bolster novel concepts that will propel the momentum toward a trajectory leading to a robust AD patient-specific next generation precision medicine with improved cognitive function and excellent life quality.

Neuropathologic Correlates of Psychiatric Symptoms in Alzheimer's Disease. - Ehrenberg, Alexander J; Suemoto, Claudia K; França Resende, Elisa de Paula; Petersen, Cathrine; Leite, Renata Elaine Paraizo; Rodriguez, Roberta Diehl; Ferretti-Rebustini, Renata Eloah de Lucena; You, Michelle; Oh, Jun; Nitrini, Ricardo; Pasqualucci, Carlos Augusto; Jacob-Filho, Wilson; et al. (J Alzheimers Dis, 2018)
Clarifying the relationships between neuropsychiatric symptoms and Alzheimer's disease (AD)-related pathology may open avenues for effective treatments. Here, we investigate the odds of developing neuropsychiatric symptoms across increasing burdens of neurofibrillary tangle and amyloid-β pathology. Participants who passed away between 2004 and 2014 underwent comprehensive neuropathologic evaluation at the Biobank for Aging Studies from the Faculty of Medicine at the University of São Paulo. Postmortem interviews with reliable informants were used to collect information regarding neuropsychiatric and cognitive status. Of 1,092 cases collected, those with any non-Alzheimer pathology were excluded, bringing the cohort to 455 cases. Braak staging was used to evaluate neurofibrillary tangle burden, and the CERAD neuropathology score was used to evaluate amyloid-β burden. The 12-item neuropsychiatric inventory was used to evaluate neuropsychiatric symptoms and CDR-SOB score was used to evaluate dementia status. In Braak I/II, significantly increased odds were detected for agitation, anxiety, appetite changes, depression, and sleep disturbances, compared to controls. Increased odds of agitation continue into Braak III/IV. Braak V/VI is associated with higher odds for delusions. No increased odds for neuropsychiatric symptoms were found to correlate with amyloid-β pathology. Increased odds of neuropsychiatric symptoms are associated with early neurofibrillary tangle pathology, suggesting that subcortical neurofibrillary tangle accumulation with minimal cortical pathology is sufficient to impact quality of life and that neuropsychiatric symptoms are a manifestation of AD biological processes.

Neurotoxic Effects of Aβ6-42 Peptides Mimicking Putative Products Formed by the Angiotensin Converting Enzyme. - Medvedev, Alexei E; Radko, Sergey P; Yurinskaya, Marina M; Vinokurov, Maxim G; Buneeva, Olga A; Kopylov, Arthur T; Kozin, Sergey A; Mitkevich, Vladimir A; Makarov, Alexander A (J Alzheimers Dis, 2018)
Angiotensin converting enzyme (ACE) is involved in proteolytic processing of the amyloid-β(Aβ) peptide implicated in the development of Alzheimer's disease (AD) and known products of ACE-based processing of Aβ42 are characterized by reduced aggregability and cytotoxicity. Recently it has been demonstrated that ACE can act as an arginine specific endopeptidase cleaving the N-terminal pentapeptide (Aβ1-5) from synthetic Aβ peptide analogues. In the context of proteolytic processing of full length Aβ42, this suggests possible formation of Aβ6-42 species. The aim of this study was to test a hypothesis that some N-terminally truncated Aβ peptide(s) could retain aggregability and neurotoxic properties typical for Aβ42. We have investigated aggregability of two amyloid-β peptides, Aβ6-42 and isoD7-Aβ6-42, mimicking potential proteolytic products of Aβ42 and isoD7-Aβ42, and evaluated their effects on the repertoire of brain Aβ binding proteins, and cytotoxicity towards neuroblastoma SH-SY5Y cells. Aggregability of isoD7-Aβ6-42 and Aβ6-42 was higher than that of full-length peptides Aβ42 and isoD7-Aβ42, while the repertoire of mouse brain Aβ binding proteins dramatically decreased. Aβ6-42 and isoD7-Aβ6-42 exhibited higher neurotoxicity towards SH-SY5Y cells than Aβ42 and isoD7-Aβ42, respectively. They effectively stimulated production of ROS and NO, and also TNFα secretion by cells. Thus, our results suggest that ACE-dependent processing of full-length Aβs could result in formation of more pathogenic peptides.

New Insights into the Spontaneous Human Alzheimer's Disease-Like Model Octodon degus: Unraveling Amyloid-β Peptide Aggregation and Age-Related Amyloid Pathology. - Cisternas, Pedro; Zolezzi, Juan M; Lindsay, Carolina; Rivera, Daniela S; Martinez, Alexis; Bozinovic, Francisco; Inestrosa, Nibaldo C (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is the most common cause of dementia worldwide. Despite advances in our understanding of the molecular milieu driving AD pathophysiology, no effective therapy is currently available. Moreover, various clinical trials have continued to fail, suggesting that our approach to AD must be revised. Accordingly, the development and validation of new models are highly desirable. Over the last decade, we have been working with Octodon degus (degu), a Chilean rodent, which spontaneously develops AD-like neuropathology, including increased amyloid-β (Aβ) aggregates, tau hyperphosphorylation, and postsynaptic dysfunction. However, for proper validation of degu as an AD model, the aggregation properties of its Aβ peptide must be analyzed. Thus, in this study, we examined the capacity of the degu Aβ peptide to aggregate in vitro. Then, we analyzed the age-dependent variation in soluble Aβ levels in the hippocampus and cortex of third- to fifth-generation captive-born degu. We also assessed the appearance and spatial distribution of amyloid plaques in O. degus and compared them with the plaques in two AD transgenic mouse models. In agreement with our previous studies, degu Aβ was able to aggregate, forming fibrillar species in vitro. Furthermore, amyloid plaques appeared in the anterior brain structures of O. degus at approximately 32 months of age and in the whole brain at 56 months, along with concomitant increases in Aβ levels and the Aβ42/Aβ40 ratio, indicating that O. degus spontaneously develops AD-like pathology earlier than other spontaneous models. Based on these results, we can confirm that O. degus constitutes a valuable model to improve AD research.

NO-Dependent Akt Inactivation by S-Nitrosylation as a Possible Mechanism of STZ-Induced Neuronal Insulin Resistance. - Crunfli, Fernanda; Mazucanti, Caio Henrique; de Moraes, Ruan Carlos Macêdo; Costa, Andressa Pereira; Rodrigues, Alice Cristina; Scavone, Cristoforo; Torrão, Andréa da Silva (J Alzheimers Dis, 2018)
Sporadic Alzheimer's disease (sAD) is associated with energy metabolism deficiency and impairment of insulin receptor (IR) signaling in the brain. In this context, low doses of intracerebroventricular (icv) injection of streptozotocin (STZ) in rodents has been used as an experimental model of sAD which leads to an insulin-resistant brain state and neurodegeneration. However, the STZ effects on brain insulin signaling-related proteins it is not appropriately elucidated. The aim of this study was to evaluate the beginning and progression of alterations in the brain IR pathway of rats after 1, 3, 5, and 7 days of STZ injection and investigate intracellular signaling involved on STZ induced insulin resistance. We observed that STZ injection causes cognitive impairment in the animals, a temporal variation of the insulin signaling-related proteins and apoptosis cell death in the hippocampus. We also have shown that STZ causes insulin resistance and impairment on phosphoinositide 3-kinase (PI3K) activity in the Neuro-2a cells through protein kinase B (Akt) inactivation by S-nitrosylation, which could upregulate GSK3-β activity. STZ ability to cause an insulin-resistant neuron state involves NO production and ROS production which may play an important role in the mechanism linked to STZ-induced neurotoxicity. The icv injection of STZ model and STZ exposed Neuro-2a cells may be potential experimental models for assessing molecules related to the pathogenesis of sAD.

Non-Genetic Risk Factors for Degenerative and Vascular Young Onset Dementia: Results from the INSPIRED and KGOW Studies. - Cations, Monica; Draper, Brian; Low, Lee-Fay; Radford, Kylie; Trollor, Julian; Brodaty, Henry; Sachdev, Perminder; Gonski, Peter; Broe, Gerald Anthony; Withall, Adrienne (J Alzheimers Dis, 2018)
BACKGROUND: Several brain reserve, vascular risk, and other modifiable factors have been associated with late-onset dementia, but their association with young onset dementia (YOD) has not been adequately explored. OBJECTIVE: To examine the association of cognitive reserve enhancing factors, cardiovascular risk factors (including smoking), depression, alcohol use, and traumatic brain injury (TBI) with non-autosomal dominant degenerative and/or vascular YOD. METHODS: Data for this matched case-control study were taken from two larger studies conducted in NSW, Australia. One comprised all people with YOD within a geographical region, while the other exclusively included Aboriginal and Torres Strait Islander participants. Dementia diagnosis was confirmed by clinical consensus, and risk exposure was retrospectively self- and/or informant-reported. RESULTS: Participants were 96 people with YOD (58.4% with probable Alzheimer's disease) and 175 age-group, sex, and sample matched control participants. Poor educational attainment, low participation in cognitive leisure activity, stroke, transient ischemic attack, and self-reported very heavy alcohol use were related to the risk of primary degenerative and/or vascular YOD. The effect of hypertension and depression varied depending on when they occurred relative to dementia onset. Current smoking was significantly associated with risk in univariate analyses but did not retain significance in multivariate modelling. There was no association with hypercholesterolemia, diabetes, or TBI of any kind. Some compensation for low educational attainment was possible via a complex occupation later in life. CONCLUSION: Non-genetic factors have a role in YOD, though the relative importance of each factor may be different to late onset dementia. The timing and severity of exposure, as well as the potential for compensation with later protective exposures, are important considerations for potential prevention strategies.

Non-Phosphorylated Tau in Cerebrospinal Fluid is a Marker of Alzheimer's Disease Continuum in Young Urbanites Exposed to Air Pollution. - Calderón-Garcidueñas, Lilian; Mukherjee, Partha S; Waniek, Katharina; Holzer, Max; Chao, Chih-Kai; Thompson, Charles; Ruiz-Ramos, Rubén; Calderón-Garcidueñas, Ana; Franco-Lira, Maricela; Reynoso-Robles, Rafael; González-Maciel, Angelica; Lachmann, Ingolf (J Alzheimers Dis, 2018)
Long-term exposure to fine particulate matter (PM2.5) and ozone (O3) above USEPA standards is associated with Alzheimer's disease (AD) risk. Metropolitan Mexico City (MMC) children exhibit subcortical pretangles in infancy and cortical tau pre-tangles, NFTs, and amyloid phases 1-2 by the 2nd decade. Given their AD continuum, we measured in 507 normal cerebrospinal fluid (CSF) samples (MMC 354, controls 153, 12.82±6.73 y), a high affinity monoclonal non-phosphorylated tau antibody (non-P-Tau), as a potential biomarker of AD and axonal damage. In 81 samples, we also measured total tau (T-Tau), tau phosphorylated at threonine 181 (P-Tau), amyloid-β1-42, BDNF, and vitamin D. We documented by electron microscopy myelinated axonal size and the pathology associated with combustion-derived nanoparticles (CDNPs) in anterior cingulate cortex white matter in 6 young residents (16.25±3.34 y). Non-P-Tau showed a strong increase with age significantly faster among MMC versus controls (p = 0.0055). Aβ1 - 42 and BDNF concentrations were lower in MMC children (p = 0.002 and 0.03, respectively). Anterior cingulate cortex showed a significant decrease (p = <0.0001) in the average axonal size and CDNPs were associated with organelle pathology. Significant age increases in non-P-Tau support tau changes early in a population with axonal pathology and evolving AD hallmarks in the first two decades of life. Non-P-Tau is an early biomarker of axonal damage and potentially valuable to monitor progressive longitudinal changes along with AD multianalyte classical CSF markers. Neuroprotection of young urbanites with PM2.5 and CDNPs exposures ought to be a public health priority to halt the development of AD in the first two decades of life.

Overactive BRCA1 Affects Presenilin 1 in Induced Pluripotent Stem Cell-Derived Neurons in Alzheimer's Disease. - Wezyk, Michalina; Szybinska, Aleksandra; Wojsiat, Joanna; Szczerba, Marcelina; Day, Kelly; Ronnholm, Harriet; Kele, Malin; Berdynski, Mariusz; Peplonska, Beata; Fichna, Jakub Piotr; Ilkowski, Jan; Styczyńska, Maria; et al. (J Alzheimers Dis, 2018)
The BRCA1 protein, one of the major players responsible for DNA damage response has recently been linked to Alzheimer's disease (AD). Using primary fibroblasts and neurons reprogrammed from induced pluripotent stem cells (iPSC) derived from familial AD (FAD) patients, we studied the role of the BRCA1 protein underlying molecular neurodegeneration. By whole-transcriptome approach, we have found wide range of disturbances in cell cycle and DNA damage response in FAD fibroblasts. This was manifested by significantly increased content of BRCA1 phosphorylated on Ser1524 and abnormal ubiquitination and subcellular distribution of presenilin 1 (PS1). Accordingly, the iPSC-derived FAD neurons showed increased content of BRCA1(Ser1524) colocalized with degraded PS1, accompanied by an enhanced immunostaining pattern of amyloid-β. Finally, overactivation of BRCA1 was followed by an increased content of Cdc25C phosphorylated on Ser216, likely triggering cell cycle re-entry in FAD neurons. This study suggests that overactivated BRCA1 could both influence PS1 turnover leading to amyloid-β pathology and promote cell cycle re-entry-driven cell death of postmitotic neurons in AD.

Pathological Correlates of Cognitive Impairment in The University of Manchester Longitudinal Study of Cognition in Normal Healthy Old Age. - Robinson, Andrew C; Davidson, Yvonne S; Horan, Michael A; Pendleton, Neil; Mann, David M A (J Alzheimers Dis, 2018)
The neuropathological changes responsible for cognitive impairment and dementia remain incompletely understood. Longitudinal studies with a brain donation end point allow the opportunity to examine relationships between cognitive status and neuropathology. We report on the first 97 participants coming to autopsy with sufficient clinical information from The University of Manchester Longitudinal Study of Cognition in Normal Healthy Old Age. This study began in 1983 and recruited 6,542 healthy individuals between 1983 and 1994, 312 of whom consented to brain donation. Alzheimer-type pathology was common throughout the cohort and generally correlated well with cognitive status. However, there was some overlap between cognitive status and measures of Alzheimer pathology with 26% of cognitively intact participants reaching either CERAD B or C, 11% reaching Thal phase 4 or 5, and 29% reaching Braak stage III- VI. Cerebral amyloid angiopathy(CAA), α-synuclein, and TDP-43 pathology was less common, but when present correlated well with cognitive status. Possession of APOEɛ4 allele(s) was associated with more severe Alzheimer-type and CAA pathology and earlier death, whereas possession of APOEɛ2 allele(s) had no effect on pathology but was more common in cognitively intact individuals. The University of Manchester Longitudinal Study of Cognition in Normal Healthy Old Age cohort is pathologically representative when compared with similar studies. Cognitive impairment in life correlates strongly with all pathologies examined and the APOE status of an individual can affect pathology severity and longevity.

Patient Engagement: The Fundació ACE Framework for Improving Recruitment and Retention in Alzheimer's Disease Research. - Boada, Merce; Santos-Santos, Miguel A; Rodríguez-Gómez, Octavio; Alegret, Montserrat; Cañabate, Pilar; Lafuente, Asunción; Abdelnour, Carla; Buendia, Mar; de Dios, Maria José; Morera, Amèrica; Sanabria, Ángela; Campo, Laura; et al. (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) research is at a critical time. The global society is increasingly aware of the frightening rate of growth of the human and financial burden caused by this condition and of the urgent need to halt its progression. Consequently, the scientific community holds great responsibility to quickly put in place and optimize the machinery necessary for testing new treatments or interventions. In this context demand for participants for AD research is at an all-time high. In this review, we will focus on a methodological factor that is increasingly recognized as a key factor that shapes trial populations and affects validity of results in clinical trials: patient engagement, recruitment, and retention. We outline specific problems relevant to patient engagement in AD including recruiting enough participants, difficulties in participant retention, ensuring the recruited sample is representative of the general AD population, the burden of screening failures, and new challenges related to recruiting in preclinical disease. To address the urgent need for more research studying the applicability and cost-effectiveness of different recruitment strategies across different settings and nationalities, we describe the Models of Patient Engagement for Alzheimer's Disease (MOPEAD) project, a public-private partnership promoted by the Innovative Medicine Initiative (IMI), which will provide a large multinational quantitative analysis comparing different innovative recruitment models. We also discuss strategies that address each problem and draw on the experience of Fundació ACE to argue that focusing resources on comprehensive AD centers that offer coordinated clinical and social care and participate in basic and clinical research, is an effective and efficient way of implementing many of the discussed strategies.

Patterns of Regional Cerebral Blood Flow as a Function of Age Throughout the Lifespan. - Amen, Daniel G; Egan, Sachit; Meysami, Somayeh; Raji, Cyrus A; George, Noble (J Alzheimers Dis, 2018)
BACKGROUND: Understanding the influence of aging on the brain remains a challenge in determining its role as a risk factor for Alzheimer's disease. OBJECTIVE: To identify patterns of aging in a large neuroimaging cohort. METHODS: A large psychiatric cohort of 31,227 individuals received brain SPECT at rest and during a concentration task for a total of 62,454 scans. ANOVA was done to identify the mean age trends over the course of the age range in this group, 0- 105 years. A regression model in which brain SPECT regions of interest was used to predict chronological age (CA) was then utilized to derive brain estimated age (BEA). The difference between CA and BEA was calculated to determine increased brain aging in common disorders in our sample such as depression, dementia, substance use, and anxiety. RESULTS: Throughout the lifespan, variations in perfusion were observed in childhood, adolescence, and late life. Increased brain aging was seen in alcohol use, cannabis use, anxiety, bipolar, schizophrenia, attention-deficit/hyperactivity disorder, and in men. CONCLUSION: Brain SPECT can predict chronological age and this feature varies as a function of common psychiatric disorders.

Personality Modulates the Efficacy of Art Intervention on Chronic Pain in a Population of Patients with Alzheimer's Disease. - Rouch, Isabelle; Pongan, Elodie; Leveque, Yohana; Tillmann, Barbara; Trombert, Béatrice; Getenet, Jean Claude; Auguste, Nicolas; Krolak-Salmon, Pierre; Laurent, Bernard; Dorey, Jean-Michel (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) mainly occurs in elderly individuals. Comorbidities and chronic pain are frequent in this population. Previous studies revealed that personality modulates both chronic pain (CP) andADoccurrence and evolution. Moreover, as pain treatments can induce side-effects, non-drugs treatments, such as art interventions, are interesting alternative therapies for decreasing CP in these patients. OBJECTIVE: Our aim was to assess the potential role of personality traits on art intervention efficacy for reducing CP in a population of patients with mild AD. METHODS: Design: multicenter randomized controlled trial. Fifty mild AD patients underwent a 12-week art intervention including singing and painting groups. Personality was assessed with the Big Five Inventory before the sessions. CP was measured with Numeric Rating Scale (NRS) [Usual pain (NRS-U) and most Intense pain (NRS-I)], Simple Visual Scale [Usual pain (SVS-U) and most Intense pain (SVS-I)] and Brief Pain Inventory (BPI) before and after the sessions. The influence of personality traits on CP evolution before and after art intervention was assessed with multiple linear regression models. RESULTS: A positive association was observed between neuroticism and the evolution of three CP measures including NRS-U (B = 0.34, p = 0.01), SVS-U (B = 0.20, p = 0.04), and BPI-U (B = 0.46, p = 0.02) evolution. No significant relationship was observed between neuroticism and NRS-I, SVS-I and BPI-R evolution. CONCLUSIONS: Our findings suggest that neuroticism can decrease the efficacy of group art intervention on pain in patients with mild AD. Individual therapies could be more appropriate for these patients. These results emphasize the interest of taking into account patients' personality before proposing them to participate to a group therapy.

Perspectives on Communicating Biomarker-Based Assessments of Alzheimer's Disease to Cognitively Healthy Individuals. - Milne, Richard; Bunnik, Eline; Diaz, Ana; Richard, Edo; Badger, Shirlene; Gove, Dianne; Georges, Jean; Fauria, Karine; Molinuevo, Jose-Luis; Wells, Katie; Ritchie, Craig; Brayne, Carol (J Alzheimers Dis, 2018)
In clinical trials which target pathophysiological mechanisms associated with Alzheimer's disease, research participants who are recruited based on biomarker test results should be informed about their increased risk of developing Alzheimer's dementia. This paper presents the results of a qualitative focus group study of attitudes and concerns toward learning information about biomarker-based risk status among healthy research participants in the United Kingdom and Spain and people with dementia and their supporters/caregivers from countries represented in the European Working Group of People with Dementia of Alzheimer Europe. The study identified expectations related to learning risk status and preferences related to the content, quality, and follow-up of the disclosure process. The latter emphasize distinctions between risk and diagnoses, the importance of clear information about risk, and suggestions for risk reduction, as well as expectations for follow up and support. The implications of these preferences for practice are discussed. Providing details of research participants' experience and views may serve as a guide for the development of processes for the responsible disclosure of Alzheimer's disease biomarkers.
Keywords: Adult; Aged; Alzheimer Disease; Biomarkers; Caregivers; Disclosure; Female; Focus Groups; Humans; Male; Middle Aged; Qualitative Research; Risk Factors; Spain; United Kingdom

Physical Activity and Hippocampal Sub-Region Structure in Older Adults with Memory Complaints. - Siddarth, Prabha; Rahi, Berna; Emerson, Natacha D; Burggren, Alison C; Miller, Karen J; Bookheimer, Susan; Lavretsky, Helen; Dobkin, Bruce; Small, Gary; Merrill, David A (J Alzheimers Dis, 2018)
BACKGROUND: Physical activity (PA) plays a major role in maintaining cognition in older adults. PA has been shown to be correlated with total hippocampal volume, a memory-critical region within the medial temporal lobe (MTL). However, research on associations between PA and MTL sub-region integrity is limited. OBJECTIVE: To examine the relationship between PA, MTL thickness, and its sub-regions, and cognitive function in non-demented older adults with memory complaints. METHODS: Twenty-nine subjects aged ≥60 years, with memory complaints were recruited for this cross-sectional study. PA was tracked for 7 days using accelerometers, and average number of steps/day determined. Subjects were categorized into two groups: those who walked ≤4000 steps/day (lower PA) and those with >4000 steps/day (higher PA). Subjects received neuropsychological testing and 3T MRI scans. Nonparametric ANCOVAs controlling for age examined differences between the two groups. RESULTS: Twenty-six subjects aged 72.7(8.1) years completed the study. The higher PA group (n = 13) had thicker fusiform gyrus (median difference = 0.11 mm, effect size (ES) = 1.43, p = 0.001) and parahippocampal cortex (median difference = 0.12 mm, ES = 0.93, p = 0.04) compared to the lower PA group. The higher PA group also exhibited superior performance in attention and information-processing speed (median difference = 0.90, ES = 1.61, p = 0.003) and executive functioning (median difference = 0.97, ES = 1.24, p = 0.05). Memory recall was not significantly different between the two groups. CONCLUSION: Older non-demented individuals complaining of memory loss who walked >4000 steps each day had thicker MTL sub-regions and better cognitive functioning than those who walked ≤4000 steps. Future studies should include longitudinal analyses and explore mechanisms mediating hippocampal related atrophy.
Keywords: Aged; Aged, 80 and over; Cognition; Cross-Sectional Studies; Executive Function; Exercise; Female; Geriatric Assessment; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Memory; Memory Disorders; Middle Aged; Neuropsychological Tests

Pink1 Regulates Tyrosine Hydroxylase Expression and Dopamine Synthesis. - Lu, Lingling; Jia, Huanzhen; Gao, Ge; Duan, Chunli; Ren, Jing; Li, Yi; Yang, Hui (J Alzheimers Dis, 2018)
PTEN induced putative kinase 1 (PINK1), also known as PARK6, is causally linked to familial Parkinsonism, and heterozygous loss of PINK1 is a risk factor for sporadic Parkinson's disease. However, little is known about its physiological function. Its deficiency was shown to decrease dopamine without significant loss of dopaminergic neurons. We investigated the mechanistic basis for this observation in the present study using dopaminergic MN9D cells. We found that PINK1 knockdown resulted in dopamine content to decrease with suppressed tyrosine hydroxylase expression in cells. Conversely, PINK1 overexpression increased tyrosine hydroxylase protein level. We also found that PINK1 deficiency blocked the nuclear translocation and activity of nuclear receptor-related 1, a transcription factor regulating tyrosine hydroxylase gene expression. These data suggest that PINK1 regulates tyrosine hydroxylase gene expression and dopamine content by modulating the transcriptional activity of nuclear receptor-related 1. Taken together, our results reveal a novel function of PINK1 in dopamine homeostasis.

Potential of Low Dose Leuco-Methylthioninium Bis(Hydromethanesulphonate) (LMTM) Monotherapy for Treatment of Mild Alzheimer's Disease: Cohort Analysis as Modified Primary Outcome in a Phase III Clinical Trial. - Wilcock, Gordon K; Gauthier, Serge; Frisoni, Giovanni B; Jia, Jianping; Hardlund, Jiri H; Moebius, Hans J; Bentham, Peter; Kook, Karin A; Schelter, Bjoern O; Wischik, Damon J; Davis, Charles S; Staff, Roger T; et al. (J Alzheimers Dis, 2018)
BACKGROUND: LMTM is being developed as a treatment for AD based on inhibition of tau aggregation. OBJECTIVES: To examine the efficacy of LMTM as monotherapy in non-randomized cohort analyses as modified primary outcomes in an 18-month Phase III trial in mild AD. METHODS: Mild AD patients (n = 800) were randomly assigned to 100 mg twice a day or 4 mg twice a day. Prior to unblinding, the Statistical Analysis Plan was revised to compare the 100 mg twice a day as monotherapy subgroup (n = 79) versus 4 mg twice a day as randomized (n = 396), and 4 mg twice a day as monotherapy (n = 76) versus 4 mg twice a day as add-on therapy (n = 297), with strong control of family-wise type I error. RESULTS: The revised analyses were statistically significant at the required threshold of p < 0.025 in both comparisons for change in ADAS-cog, ADCS-ADL, MRI atrophy, and glucose uptake. The brain atrophy rate was initially typical of mild AD in both add-on and monotherapy groups, but after 9 months of treatment, the rate in monotherapy patients declined significantly to that reported for normal elderly controls. Differences in severity or diagnosis at baseline between monotherapy and add-on patients did not account for significant differences in favor of monotherapy. CONCLUSIONS: The results are consistent with earlier studies in supporting the hypothesis that LMTM might be effective as monotherapy and that 4 mg twice a day may serve as well as higher doses. A further suitably randomized trial is required to test this hypothesis.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Antipsychotic Agents; Cohort Studies; Double-Blind Method; Female; Humans; International Cooperation; Male; Mental Status and Dementia Tests; Methylene Blue; Middle Aged; Treatment Outcome

A Precision Medicine Model for Targeted NSAID Therapy in Alzheimer's Disease. - O'Bryant, Sid E; Zhang, Fan; Johnson, Leigh A; Hall, James; Edwards, Melissa; Grammas, Paula; Oh, Esther; Lyketsos, Constantine G; Rissman, Robert A (J Alzheimers Dis, 2018)
BACKGROUND: To date, the therapeutic paradigm for Alzheimer's disease (AD) has focused on a single intervention for all patients. However, a large literature in oncology supports the therapeutic benefits of a precision medicine approach to therapy. Here we test a precision-medicine approach to AD therapy. OBJECTIVE: To determine if a baseline, blood-based proteomic companion diagnostic predicts response to NSAID therapy. METHODS: Proteomic assays of plasma from a multicenter, randomized, double-blind, placebo-controlled, parallel group trial, with 1-year exposure to rofecoxib (25 mg once daily), naproxen (220 mg twice-daily) or placebo. RESULTS: 474 participants with mild-to-moderate AD were screened with 351 enrolled into the trial. Using support vector machine (SVM) analyses, 89% of the subjects randomized to either NSAID treatment arms were correctly classified using a general NSAID companion diagnostic. Drug-specific companion diagnostics yielded 98% theragnostic accuracy in the rofecoxib arm and 97% accuracy in the naproxen arm. CONCLUSION: Inflammatory-based companion diagnostics have significant potential to identify select patients with AD who have a high likelihood of responding to NSAID therapy. This work provides empirical support for a precision medicine model approach to treating AD.

Predicting and Tracking Short Term Disease Progression in Amnestic Mild Cognitive Impairment Patients with Prodromal Alzheimer's Disease: Structural Brain Biomarkers. - Marizzoni, Moira; Ferrari, Clarissa; Jovicich, Jorge; Albani, Diego; Babiloni, Claudio; Cavaliere, Libera; Didic, Mira; Forloni, Gianluigi; Galluzzi, Samantha; Hoffmann, Karl-Titus; Molinuevo, José Luis; Nobili, Flavio; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Early Alzheimer's disease (AD) detection using cerebrospinal fluid (CSF) biomarkers has been recommended as enrichment strategy for trials involving mild cognitive impairment (MCI) patients. OBJECTIVE: To model a prodromal AD trial for identifying MRI structural biomarkers to improve subject selection and to be used as surrogate outcomes of disease progression. METHODS: APOE ɛ4 specific CSF Aβ42/P-tau cut-offs were used to identify MCI with prodromal AD (Aβ42/P-tau positive) in the WP5-PharmaCog (E-ADNI) cohort. Linear mixed models were performed 1) with baseline structural biomarker, time, and biomarker×time interaction as factors to predict longitudinal changes in ADAS-cog13, 2) with Aβ42/P-tau status, time, and Aβ42/P-tau status×time interaction as factors to explain the longitudinal changes in MRI measures, and 3) to compute sample size estimation for a trial implemented with the selected biomarkers. RESULTS: Only baseline lateral ventricle volume was able to identify a subgroup of prodromal AD patients who declined faster (interaction, p = 0.003). Lateral ventricle volume and medial temporal lobe measures were the biomarkers most sensitive to disease progression (interaction, p≤0.042). Enrichment through ventricular volume reduced the sample size that a clinical trial would require from 13 to 76%, depending on structural outcome variable. The biomarker needing the lowest sample size was the hippocampal subfield GC-ML-DG (granule cells of molecular layer of the dentate gyrus) (n = 82 per arm to demonstrate a 20% atrophy reduction). CONCLUSION: MRI structural biomarkers can enrich prodromal AD with fast progressors and significantly decrease group size in clinical trials of disease modifying drugs.

Predicting Imminent Progression to Clinically Significant Memory Decline Using Volumetric MRI and FDG PET. - Stonnington, Cynthia M; Chen, Yinghua; Savage, Cary R; Lee, Wendy; Bauer Iii, Robert J; Sharieff, Sameen; Thiyyagura, Pradeep; Alexander, Gene E; Caselli, Richard J; Locke, Dona E C; Reiman, Eric M; Chen, Kewei (J Alzheimers Dis, 2018)
BACKGROUND: Brain imaging measurements can provide evidence of possible preclinical Alzheimer's disease (AD). Their ability to predict individual imminent clinical conversion remains unclear. OBJECTIVE: To investigate the ability of pre-specified volumetric magnetic resonance imaging (MRI) and fluorodeoxyglucose positron emission tomography (FDG-PET) measurements to predict which cognitively unimpaired older participants would subsequently progress to amnestic mild cognitive impairment (aMCI) within 2 years. METHODS: From an apolipoprotein E4 (APOE4) enriched prospective cohort study, 18 participants subsequently progressed to the clinical diagnosis of aMCI or probable AD dementia within 1.8±0.8 years (progressors); 20 participants matched for sex, age, education, and APOE allele dose remained cognitively unimpaired for at least 4 years (nonprogressors). A complementary control group not matched for APOE allele dose included 35 nonprogressors. Groups were compared on baseline FDG-PET and MRI measures known to be preferentially affected in the preclinical and clinical stages of AD and by voxel-wise differences in regional gray matter volume and glucose metabolism. Receiver Operating Characteristic, binary logistic regression, and leave-one-out procedures were used to predict clinical outcome for the a priori measures. RESULTS: Compared to non-progressors and regardless of APOE-matching, progressors had significantly reduced baseline MRI and PET measurements in brain regions preferentially affected by AD and reduced hippocampal volume was the strongest predictor of an individual's imminent progression to clinically significant memory decline (79% sensitivity/78% specificity among APOE-matched cohorts). CONCLUSION: Regional MRI and FDG-PET measurements may be useful in predicting imminent progression to clinically significant memory decline.

Predictors of Age of Diagnosis and Survival of Alzheimer's Disease in Down Syndrome. - Sinai, Amanda; Mokrysz, Claire; Bernal, Jane; Bohnen, Ingrid; Bonell, Simon; Courtenay, Ken; Dodd, Karen; Gazizova, Dina; Hassiotis, Angela; Hillier, Richard; McBrien, Judith; McCarthy, Jane; et al. (J Alzheimers Dis, 2018)
BACKGROUND: People with Down syndrome (DS) are an ultra-high risk population for Alzheimer's disease (AD). Understanding the factors associated with age of onset and survival in this population could highlight factors associated with modulation of the amyloid cascade. OBJECTIVE: This study aimed to establish the typical age at diagnosis and survival associated with AD in DS and the risk factors associated with these. METHODS: Data was obtained from the Aging with Down Syndrome and Intellectual Disabilities (ADSID) research database, consisting of data extracted from clinical records of patients seen by Community Intellectual Disability Services (CIDS) in England. Survival times when considering different risk factors were calculated. RESULTS: The mean age of diagnosis was 55.80 years, SD 6.29. Median survival time after diagnosis was 3.78 years, and median age at death was approximately 60 years. Survival time was associated with age of diagnosis, severity of intellectual disability, living status, anti-dementia medication status, and history of epilepsy. Age at diagnosis and treatment status remained predictive of survival time following adjustment. CONCLUSION: This study provides the best estimate of survival in dementia within the DS population to date, and is in keeping with previous estimates from smaller studies in the DS population. This study provides important estimates and insights into possible predictors of survival and age of diagnosis of AD in adults with DS, which will inform selection of participants for treatment trials in the future.
Keywords: Age of Onset; Alzheimer Disease; Down Syndrome; England; Female; Humans; Male; Middle Aged; Risk Factors; Survival Analysis

Preserved Structural Network Organization Mediates Pathology Spread in Alzheimer's Disease Spectrum Despite Loss of White Matter Tract Integrity. - Powell, Fon; Tosun, Duygu; Sadeghi, Roksana; Weiner, Michael; Raj, Ashish (J Alzheimers Dis, 2018)
Models of Alzheimer's disease (AD) hypothesize stereotyped progression via white matter (WM) fiber connections, most likely via trans-synaptic transmission of toxic proteins along neuronal pathways. An important question in the field is whether and how organization of fiber pathways is affected by disease. It remains unknown whether fibers act as conduits of degenerative pathologies, or if they also degenerate with the gray matter network. This work uses graph theoretic modeling in a longitudinal design to investigate the impact of WM network organization on AD pathology spread. We hypothesize if altered WM network organization mediates disease progression, then a previously published network diffusion model will yield higher prediction accuracy using subject-specific connectomes in place of a healthy template connectome. Neuroimaging data in 124 subjects from ADNI were assessed. Graph topology metrics show preserved network organization in patients compared to controls. Using a published diffusion model, we further probe the effect of network alterations on degeneration spread in AD. We show that choice of connectome does not significantly impact the model's predictive ability. These results suggest that, despite measurable changes in integrity of specific fiber tracts, WM network organization in AD is preserved. Further, there is no difference in the mediation of putative pathology spread between healthy and AD-impaired networks. This conclusion is somewhat at variance with previous results, which report global topological disturbances in AD. Our data indicates the combined effect of edge thresholding, binarization, and inclusion of subcortical regions to network graphs may be responsible for previously reported effects.

Prevalence of Dementia and Associated Risk Factors: A Population-Based Study in the Philippines. - Dominguez, Jacqueline; Fe de Guzman, Ma; Reandelar, Macario; Thi Phung, Thien Kieu (J Alzheimers Dis, 2018)
BACKGROUND: The Philippines is experiencing rapid demographic aging and with it, the dementia epidemic. Prevalence of dementia and associated risk factors have not been studied in the Philippines. OBJECTIVES: The study aimed to provide a reliable estimate of dementia prevalence and identify associated risk factors in the Filipino population. METHODS: 1460 participants 60 years and older were randomly selected from the Marikina City's senior registry. A multidisciplinary team (nurse, psychologist, and neurologist) administered a comprehensive assessment to the study population: health history, neurological examination, Geriatric Depression Scale, Neuropsychiatric Inventory, Disability Assessment for Dementia, Alzheimer's Disease 8, and Clinical Dementia Rating Scale. The neurologist analyzed all clinical data to diagnose dementia based on the DSM-IV criteria, Alzheimer's Disease (AD) on the NINCDS-ADRDA criteria, vascular dementia (VaD) on the Hachinski Ischemic Scale, cognitive impairment no dementia (CIND) on a CDR score of 0.5 and not fulfilling DSM-IV criteria for dementia. Risk factors were correlated with dementia prevalence using multivariate binary logistic regression. RESULTS: 1460 persons were randomly selected. 1367 agreed to participate and underwent all assessments. The response rate was 93.6%. Dementia prevalence was found to be 10.6% (95% CI 9.0 to 12.4) with the breakdown 85.5% AD, 11.7% VaD, and 2.7% other dementias. In this population, 82.0% of men and 70.4% of women had at least one cardiovascular risk factor (hypertension, diabetes, dyslipidemia, smoking), which was associated with VaD prevalence but not AD. CONCLUSION: The prevalence of dementia, CIND, and cardiovascular risk factors are high in the Philippines.

Prevalence of Potentially Inappropriate Medication Use in Older Inpatients with and without Cognitive Impairment: A Systematic Review. - Redston, Mitchell R; Hilmer, Sarah N; McLachlan, Andrew J; Clough, Alexander J; Gnjidic, Danijela (J Alzheimers Dis, 2018)
BACKGROUND: Older people with cognitive impairment, including dementia and delirium, are high users of acute care services internationally. Potentially inappropriate medication (PIM) use may be associated with adverse outcomes, including hospital re-admission, functional disability, and mortality. OBJECTIVE: This systematic review aimed to quantify and compare the prevalence of PIMs in older inpatients with and without cognitive impairment. METHODS: A systematic search of observational studies was performed independently assessed by two reviewers in Embase, Medline, PsycINFO, International Pharmaceutical Abstracts, Scopus, and Informit. Articles published in English during the period January 2007-June 2017 that reported PIM prevalence in hospital inpatients ≥ 65 years were included. PIMs were defined as the presence of polypharmacy (multiple medication use) and using implicit or explicit tools, such as the Beers criteria, and 'Screening Tool of Older Person's Prescriptions' (STOPP). RESULTS: 47 articles were included. In studies measuring polypharmacy (n = 15), the prevalence of PIMs ranged from 53.2% to 89.8% and 30.4% to 97.1% for inpatients with and without cognitive impairment, respectively, and 24.0% to 80.0% when cognitive status was unreported. In studies employing explicit and implicit tools (n = 35), the prevalence of PIMs when cognitive impairment was reported ranged from 20.6% to 80.5% using the Beers criteria, and 39.3% to 88.5% using STOPP. When cognitive status was unreported, the prevalence of PIMs ranged from 7.0% to 79.2% using the Beers criteria, and 20.0% to 63.4% using STOPP. CONCLUSION: Our findings suggest a high prevalence of PIMs in older inpatients with and without cognitive impairment. Future studies should investigate the impact of PIM use on patient-centered outcomes, such as functional status and quality of life, to inform enhanced acute care services.
Keywords: Aged; Cognitive Dysfunction; Dementia; Humans; Inpatients; Polypharmacy; Potentially Inappropriate Medication List; Prevalence; Quality of Life

Prevalence, Safety, and Effectiveness of Oral Anticoagulant Use in People with and without Dementia or Cognitive Impairment: A Systematic Review and Meta-Analysis. - Fanning, Laura; Ryan-Atwood, Taliesin E; Bell, J Simon; Meretoja, Atte; McNamara, Kevin P; Dārziņš, Pēteris; Wong, Ian C K; Ilomäki, Jenni (J Alzheimers Dis, 2018)
BACKGROUND: Differences in management and outcomes of oral anticoagulant (OAC) use may exist for people with and without dementia or cognitive impairment (CI). OBJECTIVE: To systematically review the prevalence and safety and effectiveness outcomes of OAC use in people with and without dementia or CI. METHODS: MEDLINE, EMBASE, and CINAHL were searched for studies reporting prevalence or safety and effectiveness outcomes of OAC use for people with and without dementia, published between 2000 to September 2017. Study selection, data extraction, and quality assessment were performed by two reviewers. RESULTS: studies met pre-specified inclusion criteria (21 prevalence studies, 6 outcomes studies). People with dementia had 52% lower odds of receiving OAC compared to people without dementia. Mean OAC prevalence was 32% for people with dementia, compared to 48% without dementia. There was no difference in the composite outcome of embolic events, myocardial infarction, and all-cause death between dementia and non-dementia groups (adjusted hazard ratio (HR) 0.72, 95% CI, 0.45-1.14, p = 0.155). Bleeding rate was lower for people without dementia (HR 0.56, 95% CI, 0.37-0.85). Adverse warfarin events were more common for residents of long-term care with dementia (adjusted incidence rate ratio 1.48, 95% CI, 1.20-1.82). Community-dwelling people with dementia treated with warfarin had poorer anticoagulation control than those without dementia (mean time in therapeutic range (TTR) % ±SD, 38±26 (dementia), 61±27 (no dementia), p < 0.0001). CONCLUSION: A lower proportion of people with dementia received oral anticoagulation compared with people without dementia. People with dementia had higher bleeding risk and poorer anticoagulation control when treated with warfarin.

Prominent Non-Memory Deficits in Alzheimer's Disease Are Associated with Faster Disease Progression. - Scheltens, Nienke M E; Tijms, Betty M; Heymans, Martijn W; Rabinovici, Gil D; Cohn-Sheehy, Brendan I; Miller, Bruce L; Kramer, Joel H; Wolfsgruber, Steffen; Wagner, Michael; Kornhuber, Johannes; Peters, Oliver; Scheltens, Philip; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is a heterogeneous disorder. OBJECTIVE: To investigate whether cognitive AD subtypes are associated with different rates of disease progression. METHODS: We included 1,066 probable AD patients from the Amsterdam Dementia Cohort (n = 290), Alzheimer's Disease Neuroimaging Initiative (n = 268), Dementia Competence Network (n = 226), and University of California, San Francisco (n = 282) with available follow-up data. Patients were previously clustered into two subtypes based on their neuropsychological test results: one with most prominent memory impairment (n = 663) and one with most prominent non-memory impairment (n = 403). We examined associations between cognitive subtype and disease progression, as measured with repeated Mini-Mental State Examination (MMSE) and Clinical Dementia Rating scale sum of boxes (CDR sob), using linear mixed models. Furthermore, we investigated mortality risk associated with subtypes using Cox proportional hazard analyses. RESULTS: Patients were 71±9 years old; 541 (51%) were female. At baseline, pooled non-memory patients had worse MMSE scores (23.1±0.1) and slightly worse CDR sob (4.4±0.1) than memory patients (MMSE 24.0±0.1; p < 0.001; CDR sob 4.1±0.1; p < 0.001). During follow-up, pooled non-memory patients showed steeper annual decline in MMSE (-2.8±0.1) and steeper annual increase in CDR sob (1.8±0.1) than memory patients (MMSE - 1.9±0.1; pinteraction<0.001; CDR sob 1.3±0.1; pinteraction<0.001). Furthermore, the non-memory subtype was associated with an increased risk of mortality compared with the memory subtype at trend level (HR = 1.36, CI = 1.00-1.85, p = 0.05). CONCLUSIONS: AD patients with most prominently non-memory impairment show faster disease progression and higher risk of mortality than patients with most prominently memory impairment.

Protective Effects of Indian Spice Curcumin Against Amyloid-β in Alzheimer's Disease. - Reddy, P Hemachandra; Manczak, Maria; Yin, XiangLing; Grady, Mary Catherine; Mitchell, Andrew; Tonk, Sahil; Kuruva, Chandra Sekhar; Bhatti, Jasvinder Singh; Kandimalla, Ramesh; Vijayan, Murali; Kumar, Subodh; Wang, Rui; et al. (J Alzheimers Dis, 2018)
The purpose of our article is to assess the current understanding of Indian spice, curcumin, against amyloid-β (Aβ)-induced toxicity in Alzheimer's disease (AD) pathogenesis. Natural products, such as ginger, curcumin, and gingko biloba have been used as diets and dietary supplements to treat human diseases, including cancer, cardiovascular, respiratory, infectious, diabetes, obesity, metabolic syndromes, and neurological disorders. Products derived from plants are known to have protective effects, including anti-inflammatory, antioxidant, anti-arthritis, pro-healing, and boosting memory cognitive functions. In the last decade, several groups have designed and synthesized curcumin and its derivatives and extensively tested using cell and mouse models of AD. Recent research on Aβ and curcumin has revealed that curcumin prevents Aβ aggregation and crosses the blood-brain barrier, reach brain cells, and protect neurons from various toxic insults of aging and Aβ in humans. Recent research has also reported that curcumin ameliorates cognitive decline and improves synaptic functions in mouse models of AD. Further, recent groups have initiated studies on elderly individuals and patients with AD and the outcome of these studies is currently being assessed. This article highlights the beneficial effects of curcumin on AD. This article also critically assesses the current limitations of curcumin's bioavailability and urgent need for new formulations to increase its brain levels to treat patients with AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Blood-Brain Barrier; Curcumin; Disease Models, Animal; Humans; Mice; Neuroprotective Agents; Randomized Controlled Trials as Topic; Spices

Protofibrillar and Fibrillar Amyloid-β Binding Proteins in Cerebrospinal Fluid. - Rahman, M Mahafuzur; Westermark, Gunilla T; Zetterberg, Henrik; Härd, Torleif; Sandgren, Mats (J Alzheimers Dis, 2018)
Aggregation and deposition of misfolded amyloid-β (Aβ) peptide in the brain is central to Alzheimer's disease (AD). Oligomeric, protofibrillar, and fibrillar forms of Aβ are believed to be neurotoxic and cause neurodegeneration in AD, but the toxicity mechanisms are not well understood and may involve Aβ-interacting molecular partners. In a previous study, we identified potential Aβ42 protofibrillar-binding proteins in serum and cerebrospinal fluid (CSF) using an engineered version of Aβ42 (Aβ42CC) that forms protofibrils, but not fibrils. Here we studied binding of proteins to Aβ42 fibrils in AD and non-AD CSF and compared these with protofibrillar Aβ42CC-binding partners. Aβ42 fibrils sequestered 2.4-fold more proteins than Aβ42CC protofibrils. Proteins with selective binding to fibrillar aggregates with low nanomolar affinity were identified. We also found that protofibrillar and fibrillar Aβ-binding proteins represent distinct functional categories. Aβ42CC protofibrils triggered interactions with proteins involved in catalytic activities, like transferases and oxidoreductases, while Aβ42 fibrils were more likely involved in binding to proteoglycans, growth factors and neuron-associated proteins, e.g., neurexin-1, -2, and -3. Interestingly, 10 brain-enriched proteins were identified among the fibril-binding proteins, while protofibril-extracted proteins had more general expression patterns. Both types of Aβ aggregates bound several extracellular proteins. Additionally, we list a set of CSF proteins that might have potential to discriminate between AD and non-AD CSF samples. The results may be of relevance both for biomarker studies and for studies of Aβ-related toxicity mechanisms.

Psychometric Properties of Apathy Scales in Dementia: A Systematic Review. - Mohammad, Dana; Ellis, Courtney; Rau, Allison; Rosenberg, Paul B; Mintzer, Jacobo; Ruthirakuhan, Myuri; Herrmann, Nathan; Lanctôt, Krista L (J Alzheimers Dis, 2018)
Apathy is a prevalent and problematic neuropsychiatric symptom in those with dementia that is emerging as a treatment target, necessitating accurate assessment. While many apathy scales are available, not all have been developed for use exclusively in dementia, and psychometric properties may vary across different populations. This systematic review aimed to provide an overview of the psychometric properties of apathy scales used in Alzheimer's disease (AD) and related dementias, as well as rate the methodological quality of supporting studies. In addition, for those scales identified, performance in clinical trials was reviewed. A search was conducted through Medline, Psychinfo, Embase, Cochrane Central Register of Controlled Trials, and Cochrane Database of Systematic Reviews. Articles that reported psychometric properties of an apathy scale in an AD or mixed dementia population were included. Of 15 articles, the methodological quality ratings of the studies ranged from adequate to excellent. Three clinical trials and two pooled analyses of clinical trials were included that used apathy scales evaluated in this review. Three scales emerged. The Neuropsychiatric Inventory apathy subscale (NPI-apathy) and the Apathy Evaluation Scale (AES) had the greatest number of studies evaluating psychometric properties and were also used in the clinical trials and have shown sensitivity to change. The Dementia Apathy Interview and Rating demonstrated excellent values of internal consistency, validity, and reliability for use in an AD population. Future research should address comparative scale performance and assess ability to distinguish subtypes of apathy. Validation may include evaluation of performance against specific imaging defined deficits.

Putative Dementia Cases Fluctuate as a Function of Mini-Mental State Examination Cut-Off Points. - Rosa, Ilka M; Henriques, Ana G; Wiltfang, Jens; da Cruz E Silva, Odete A B (J Alzheimers Dis, 2018)
As the population ages, there is a growing need to quickly and accurately identify putative dementia cases. Many cognitive tests are available; among those commonly used are the Cognitive Dementia Rating (CDR) and the Mini-Mental Status Examination (MMSE). The aim of this work was to compare the validity and reliability of these cognitive tests in a primary care based cohort (pcb-Cohort). The MMSE and the CDR were applied to 568 volunteers in the pcb-Cohort. Distinct cut-off points for the MMSE were considered, namely MMSE 27, MMSE 24, and MMSE PT (adapted for the Portuguese population). The MMSE 27 identified the greatest number of putative dementia cases, and, as determined by the ROC curve, it was the most sensitive and specific of the MMSE cut-offs considered. Putative predictive or risk factors identified included age, literacy, depression, and diabetes mellitus (DM). DM has previously been indicated as a risk factor for dementia and Alzheimer's disease. Comparatively, the MMSE 27 cut-off has the greatest sensibility (94.9%) and specificity (66.3%) when compared to MMSE PT and MMSE 24. Upon comparing MMSE and CDR scores, the latter identified a further 146 putative dementia cases, thus permitting one to propose that in an ideal situation, both tests should be employed. This increases the likelihood of identifying putative dementia cases for subsequent follow up work, thus these cognitive tests represent important tools in patient care. Further, this is a significant study for Portuguese populations, where few of these studies have been carried out.
Keywords: Age Factors; Aged; Aged, 80 and over; Cohort Studies; Community Health Planning; Cross-Sectional Studies; Dementia; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Neuropsychological Tests; ROC Curve

Putative Gonadotropin-Releasing Hormone Agonist Therapy and Dementia: An Application of Medicare Hospitalization Claims Data. - Smith, Mark A; Bowen, Richard L; Nguyen, Richard Q; Perry, George; Atwood, Craig S; Rimm, Alfred A (J Alzheimers Dis, 2018)
BACKGROUND: Estrogen and hormone replacement therapies to reduce Alzheimer's disease (AD) have yielded conflicting results. However, this study proposes that the well-characterized increase in serum gonadotropins following menopause or andropause are accountable for the increased risk of developing AD among the elderly population. OBJECTIVE: To determine the role of gonadotropins in the development of AD and investigate gonadotropin-releasing hormone (GnRH) agonist therapy as a potential preventative and/or disease-modifying approach to AD management. METHODS: Male Medicare beneficiaries aged 67 to 75 and hospitalized with prostate cancer (n = 115,789) were compared to three control groups: men of the same demographics undergoing a cholecystectomy (n = 97,267), herniorrhaphy (n = 68,778), or transurethral prostatectomy (n = 267,691). A proportion of the patients hospitalized with prostate cancer were assumed to have low concentrations of serum gonadotropins and sex steroids as a result of GnRH agonist therapy, while those in the control groups were assumed to have elevated gonadotropin but lowered sex steroid levels that are associated with andropause in this age group. RESULTS: The rates of development of select diagnoses of dementia, including AD, over a twelve-year follow-up period following surgery. When compared to control patients, men hospitalized with prostate cancer have a protection against dementia after twelve years of follow-up, with relative risks ranging from 0.48 to 0.83. CONCLUSION: Patients with prostate cancer are treated with the GnRH analogue leuprolide acetate, our data suggest that leuprolide acetate may be therapeutic for AD via its downregulation of serum gonadotropins.

Quality of Life, Care Resource Use, and Costs of Dementia in 8 European Countries in a Cross-Sectional Cohort of the Actifcare Study. - Handels, Ron L H; Sköldunger, Anders; Bieber, Anja; Edwards, Rhiannon Tudor; Gonçalves-Pereira, Manuel; Hopper, Louise; Irving, Kate; Jelley, Hannah; Kerpershoek, Liselot; Marques, Maria J; Meyer, Gabriele; Michelet, Mona; et al. (J Alzheimers Dis, 2018)
BACKGROUND: With 10.5 million people with dementia in Europe and $301 billion associated costs, governments face challenges organizing access to care. OBJECTIVE: To examine the costs related to formal and informal care use and quality of life for people with dementia in eight European countries, and explore the association with unmet needs. METHODS: Cross-sectional data from 451 persons with dementia and their informal caregivers of the Actifcare cohort study were obtained. Formal and informal care use was multiplied by country specific unit prices of services. Needs were measured using the CANE and health-related quality of life (HRQOL) of the person with dementia (both self- and proxy-rated) and informal caregiver's quality of life using EQ-5D-5L, ICECAP-O, DEMQOL-U, and CarerQol utility scores. The association between costs and country, European region, and unmet needs was assessed using multi-level linear regression. RESULTS: Self-rated EQ-5D-5L utility score was higher than proxy-rated (0.84 and 0.71, respectively). Informal caregivers' utility score was 0.84. Across eight countries annual mean costs of formal and informal care were approximately € 17,000. Unmet needs were not associated with annual costs of care, nor with proxy-rated HRQOL, but were associated with self-rated HRQOL. CONCLUSION: We found varying relationships between unmet needs and quality of life, and no association between unmet needs and care costs, although the results were sensitive to various factors. Future research should further investigate the relation between unmet needs, quality of life and costs to generate a better understanding of the effects of (un)timely access to care.

Quantifying the Diagnostic Pathway for Patients with Cognitive Impairment: Real-World Data from Seven European and North American Countries. - Ritchie, Craig W; Black, Christopher M; Khandker, Rezaul K; Wood, Robert; Jones, Eddie; Hu, Xiaohan; Ambegaonkar, Baishali M (J Alzheimers Dis, 2018)
To ensure that patients with dementia and their caregivers receive appropriate treatment and support, early diagnosis is essential but remains challenging. Real-world data from a multi-national, cross-sectional survey of physicians and their patients were analyzed to quantify the diagnostic pathway for dementia, including a focus on severity of patients' cognitive impairment (CI) at the time of symptom onset, referral and subsequent diagnosis. Data were collected for 7,620 patients with CI. Most patients saw a healthcare professional within 1 year of first symptoms and received a diagnosis within 3-7 months of initial consultation. However, only 20% of patients received a diagnosis before their disease progressed beyond the prodromal stage and 23.5% already had moderate CI at diagnosis. These findings show that the goal of identifying and diagnosing CI at the earliest stages of disease is, for many patients, not achieved. Efforts toward public awareness and proactive, earlier detection and intervention, must be maintained-indeed where possible invigorated.

Quantitative PET and Histology of Brain Biopsy Reveal Lack of Selective Pittsburgh Compound-B Binding to Intracerebral Amyloidoma. - Groot, Colin; Tolboom, Nelleke; Ikonomovic, Milos D; Lammertsma, Adriaan A; Boon, Baayla D C; Barkhof, Frederik; Scheltens, Philip; Klunk, William E; Rozemuller, Annemieke J M; Ossenkoppele, Rik; van Berckel, Bart N M (J Alzheimers Dis, 2018)
This single case study examines selective Pittsburgh compound-B (PiB) binding to an intracerebral light-chain amyloidoma using a 90-minute dynamic [11C]PiB-PET scan and brain biopsy tissue. Parametric non-displaceable binding potential (BPND) images showed low specific binding in the amyloidoma (BPND = 0.23), while relative tracer delivery was adequate (R1 = 0.44). Histology of the tissue revealed strong coloring with Congo-red, thioflavin-S, and X-34, indicating presence of amyloid. However, immunological staining with 6F/3D revealed absence of amyloid-β and histofluorescence of 6-CN-PiB, a highly fluorescent derivative of PiB, was at background levels. Our results suggest that PiB does not detect the atypical amyloid pathology associated with an intracerebral light-chain amyloidoma. These findings are of interest to clinicians and researchers applying [11C]PiB-PET to detect atypical forms of amyloid pathology.

Quantitative Susceptibility Mapping of Amyloid-β Aggregates in Alzheimer's Disease with 7T MR. - Tiepolt, Solveig; Schäfer, Andreas; Rullmann, Michael; Roggenhofer, Elisabeth; Gertz, Hermann-Josef; Schroeter, Matthias L; Patt, Marianne; Bazin, Pierre-Louis; Jochimsen, Thies H; Turner, Robert; Sabri, Osama; Barthel, Henryk (J Alzheimers Dis, 2018)
BACKGROUND: PET imaging is an established technique to detect cerebral amyloid-β (Aβ) plaques in vivo. Some preclinical and postmortem data report an accumulation of redox-active iron near Aβ plaques. Quantitative susceptibility mapping (QSM) at high-field MRI enables iron deposits to be depicted with high spatial resolution. OBJECTIVE: Aim of this study was to examine whether iron and Aβ plaque accumulation is related and thus, whether 7T MRI might be an additive diagnostic tool to Aβ PET imaging. METHODS: Postmortem human Alzheimer's disease (AD) and healthy control (HC) frontal gray matter (GM) was imaged with 7T MRI which resulted in T1 maps and QSM. Aβ plaque load was determined by histopathology. In vivo, 10 Aβ PET-positive AD patients (74.1±6.0a) and 10 Aβ PET-negative HCs (67.1±4.4a) underwent 7T MR examination and QSM maps were analyzed. Severity of cognitive deficits was determined by MMSE. RESULTS: Postmortem, the susceptibility of Aβ plaque-containing GM were higher than those of Aβ plaque-free GM (0.011±0.002 versus - 0.008±0.003 ppm, p < 0.001). In vivo, only the bilateral globus pallidus showed significantly higher susceptibility in AD patients compared to HCs (right: 0.277±0.018 versus - 0.009±0.009 ppm; left: 0.293±0.014 versus - 0.007±0.012 ppm, p < 0.0001). The pallidal QSM values were negatively correlated with those of the MMSE (r = - 0.69, p = 0.001). CONCLUSION: The postmortem study revealed significant susceptibility differences between the Aβ plaque-containing and Aβ plaque-free GM, whereas in vivo only the QSM values of the globus pallidus differed significantly between AD and HC group. The pallidal QSM values correlated with the severity of cognitive deficits. These findings encourage efforts to optimize the 7T-QSM methodology.

The Rationale Behind the New Alzheimer's Disease Conceptualization: Lessons Learned During the Last Decades. - Molinuevo, José Luis; Minguillon, Carolina; Rami, Lorena; Gispert, Juan Domingo (J Alzheimers Dis, 2018)
In the last decades, progress in neuroimaging techniques and cerebrospinal fluid assays has enabled the characterization of several Alzheimer's disease (AD) biomarkers. This knowledge has shifted the conceptualization of AD from a clinical-pathological construct, where its diagnosis required the presence of dementia with distinct pathologic features, toward a clinical-biological one that recognizes AD as a pathological continuum with a clinical picture that ranges from normal cognition to a dementia stage. Specifically, AD is now divided into three stages: preclinical (abnormal biomarkers and no or only subtle cognitive impairment), mild cognitive impairment or prodromal AD (abnormal pathophysiological biomarkers and episodic memory impairment), and dementia (abnormal biomarkers and clear cognitive and functional impairment). The possibility of assessing AD pathophysiology in vivo before the onset of clinical symptoms in the preclinical stage provides the unprecedented opportunity to intervene at earlier stages of the continuum in secondary prevention trials. Currently, large cohort studies of cognitively healthy participants are undergoing with the main aim of disentangling the natural history of AD to identify individuals with an increased risk of developing AD in the near future to be recruited in these clinical trials. In this paper, we review how the concept of AD has changed over the years as well as discuss the implications of this conceptual change.

Real World Recruiting of Older Subjects with Mild Cognitive Impairment for Exercise Trials: Community Readiness is Pivotal. - Sanders, Marit L; Stuckenschneider, Tim; Devenney, Kate E; Lawlor, Brian; Schneider, Stefan; Olde Rikkert, Marcel G M (J Alzheimers Dis, 2018)
Prevention trials in subjects with mild cognitive impairment (MCI), especially lifestyle interventions, can be difficult to carry out, particularly the recruitment and retention of subjects. We experienced these challenges in our multi-site one-year exercise trial in MCI, NeuroExercise. Trial recruitment rates differed significantly across sites; the non-medical sport university site, providing free access to a range of group exercise in a sports environment, proved far more successful than memory clinics linked to hospitals. This suggests that non-medical settings and a non-medical research community facilitating physical activities may be important factors in recruitment of subjects with MCI for large prevention trials.
Keywords: Aged; Cognitive Dysfunction; Europe; Exercise; Female; Humans; Life Style; Male; Middle Aged; Patient Selection

Real-World, Multinational, Retrospective Observational Survey of the ADAS-Cog and Associations with Healthcare Resource Utilization in Patients with Alzheimer's Disease. - Ritchie, Craig W; Khandker, Rezaul K; Pike, James; Black, Christopher M; Jones, Eddie; Ambegaonkar, Baishali M (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is one of the most costly conditions, both economically and regarding patient disability and dependency. The huge costs coupled with the predicted increase in prevalence worldwide are likely to challenge healthcare systems in the future. The classic version of the Alzheimer's Disease Assessment Scale-Cognition subscale (ADAS-Cog) is generally seen as the current gold standard primary outcome measure of cognitive symptom progression in dementia clinical trials. OBJECTIVE: This study evaluated the relationship between ADAS-Cog scores as a measure of clinical progression and the healthcare resource utilization (HCRU)-measured burden of cognitive impairment in patients with mild cognitive impairment, AD, or suspected AD in the real world. METHODS: A retrospective observational survey of physicians and their consulting patients with multiple ADAS-Cog scores. Regression models were constructed for HCRU variables (e.g., consultations, hospitalizations, caregiving requirements) with ADAS-Cog rate of change, baseline ADAS-Cog, and their interaction included as exposure variables. RESULTS: 651 patient records were completed by 154 physicians. Approximately 70% of patients had mild to moderate dementia. In 56.7% of patients, clinical progression was maintained/stable from baseline. Mean change in ADAS-Cog (adjusted to 12 months) was 2.8 points and change scores increased with increasing dementia severity. Most HCRU variables increased significantly (p < 0.05; joint test) with increasing ADAS-Cog scores (indexing clinical deterioration). CONCLUSION: The results suggest that further understanding the relationship between HCRU and ADAS-Cog changes in real-world clinical practice could potentially provide a baseline upon which the success of disease-modifying, as well as newer symptomatic, dementia therapies can be judged.

Relationship Between Amyloid-β Positivity and Progression to Mild Cognitive Impairment or Dementia over 8 Years in Cognitively Normal Older Adults. - Dang, Christa; Harrington, Karra D; Lim, Yen Ying; Ames, David; Hassenstab, Jason; Laws, Simon M; Yassi, Nawaf; Hickey, Martha; Rainey-Smith, Stephanie; Robertson, Joanne; Sohrabi, Hamid R; Salvado, Olivier; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Preclinical Alzheimer's disease (AD) is defined by cerebral amyloid-β positivity (Aβ+) in cognitively normal (CN) older adults. OBJECTIVE: To estimate the risk of progression to the symptomatic stages of AD due to PET Aβ+ and the extent that progression was influenced by other demographic, genetic, and clinical characteristics in a large prospective study. METHODS: Fine-Gray subdistribution modeling was used to examine the risk of progression from CN to MCI/dementia due to Aβ+, APOEɛ4 carriage, and their interaction in the Australian Imaging, Biomarkers and Lifestyle (AIBL) flagship study of aging CN cohort (n = 599) over 8 years. RESULTS: 17.7% Aβ+ and 8.1% Aβ-progressed over 8 years (OR: 2.43). Risk of progression for Aβ+ was 65-104% greater than Aβ-. Aβ+ APOEɛ4 carriers were at 348% greater risk than all other participants. Significant risk factors of progression in Aβ+ were age (HR: 1.05), PET SUVR (HR: 2.49) and APOE ɛ4 carriage (HR: 2.63); only age was a significant risk factor in Aβ-(HR: 1.09). Aβ-progressors were not near the threshold for Aβ+. These relationships were not moderated by hypertension, diabetes, obesity, or stroke/TIA. CONCLUSION: Aβ+ is an important prognostic marker for progression from CN to MCI/dementia in older adults and APOEɛ4 carriage provides further predictive value in the presence of Aβ+. These data suggest that Aβ-associated clinical progression is consistent with clinical-pathological models of AD, whereas progression in the absence of elevated Aβ deposition may be the result of neuropathological processes other than AD that accumulate with age.

Relationship Between Body Mass Index, ApoE4 Status, and PET-Based Amyloid and Neurodegeneration Markers in Amyloid-Positive Subjects with Normal Cognition or Mild Cognitive Impairment. - Blautzik, Janusch; Kotz, Sebastian; Brendel, Matthias; Sauerbeck, Julia; Vettermann, Franziska; Winter, Yaroslav; Bartenstein, Peter; Ishii, Kazunari; Rominger, Axel (J Alzheimers Dis, 2018)
Body weight loss in late-life is known to occur at a very early stage of Alzheimer's disease (AD). Apolipoprotein E4 (ApoE4) represents a major genetic risk factor for AD and is linked to an increased cortical amyloid-β (Aβ) accumulation. Since the relationship between body weight, ApoE4, and AD pathology is poorly investigated, we aimed to evaluate whether ApoE4 allelic status modifies the association of body mass index (BMI) with markers of AD pathology. A total of 368 Aβ-positive cognitively healthy or mild cognitive impaired subjects had undergone [18F]-AV45-PET, [18F]-FDG-PET, and T1w-MRI examinations. Composite cortical [18F]-AV45 uptake and [18F]-FDG uptake in posterior cingulate cortex were calculated as surrogates of cortical Aβ load and glucose metabolism, respectively. Multiple linear regressions were performed to assess the relationships between these PET biomarkers with BMI, present cognitive performance, and cognitive changes over time. Multivariate analysis of covariance was conducted to test for statistical differences between ApoE4/BMI categories on the PET markers and cognitive scores. In carriers of the ApoE4 allele only, BMI was inversely associated with cortical amlyoid load (β= -0.193, p < 0.005) and recent cognitive decline (β= -0.209, p < 0.05), and positively associated with cortical glucose metabolism in an AD-vulnerable region (β= 0.145, p < 0.05). ApoE4/BMI category analyses demonstrated lower Aβ load, higher posterior cingulate glucose metabolism, improved cognitive performance, and lower progression of cognitive decline in obese ApoE4 carriers. The effect of ApoE4 in promoting the accumulation of cortical amyoid, which may itself be a driver for weight loss, may be moderated by altering leptin signaling in the hypothalamus.

Relationships between Cognition and Activities of Daily Living in Alzheimer's Disease During a 5-Year Follow-Up: ALSOVA Study. - Saari, Toni; Hallikainen, Ilona; Hänninen, Tuomo; Räty, Hannu; Koivisto, Anne (J Alzheimers Dis, 2018)
BACKGROUND: Impaired cognition and activities of daily living (ADL) are core symptoms of Alzheimer's disease (AD), but their relationship is unclear. OBJECTIVES: To explore relationships between cognitive domains and functional ability during 5-year follow-up in persons with AD. METHODS: We analyzed ALSOVA study data from 236 individuals with very mild or mild AD at baseline. The CERAD Neuropsychological Battery (CERAD-NB) was used as a cognitive measure and Alzheimer's Disease Cooperative Study ADL (ADCS-ADL) as a functional measure, analyzing the IADL and BADL sub-scores separately. Annual regression models and linear mixed-effect models (LMMs) covering a 5-year follow-up period were used. RESULTS: Annually, the CERAD-NB total and especially Verbal Fluency, Clock Drawing, and Constructional Praxis were associated with the total ADCS-ADL and IADL scores increasingly yet modestly, and to a lesser extent the BADL score. In the LMMs, the same measures and MMSE were associated with ADL. CONCLUSION: Measures of executive function and visuoconstructive skills appear to be associated with caregiver-interview based ADL measure during the progression of AD.

Relationships Between Lower Olfaction and Brain White Matter Lesions in Elderly Subjects with Mild Cognitive Impairment. - Heinrich, Juliette; Vidal, Jean-Sébastien; Simon, Axelle; Rigaud, Anne-Sophie; Hanon, Olivier; Epelbaum, Jacques; Viollet, Cécile; Duron, Emmanuelle (J Alzheimers Dis, 2018)
BACKGROUND: Olfactory impairment is reported in mild cognitive impairment (MCI) and Alzheimer's disease (AD) and is associated with hippocampal atrophy. In elderly people, dementia with AD neuropathology and white matter lesions (WML) is common. In this context, olfactory impairment could also depend on the presence of WML. OBJECTIVE: To assess the cross-sectional relationship between olfaction and WML in elderly subjects with MCI. METHODS: Consecutive subjects, >65 years old, diagnosed as MCI after a comprehensive neuropsychological assessment in an expert memory center, with a brain MRI performed within a year and without major depressive state, were included. Olfaction was assessed by the Brief Smell Identification Test (BSIT). Two trained neuroradiologists, blind to cognitive and olfaction status, visually assessed hippocampal atrophy according to Scheltens' scale and WML according to Fazekas criteria. RESULTS: Seventy-five MCI subjects (mean age (SD) = 77.1 (6.2) years, 74.7% of women) were included. After adjustment for age and sex, factors associated with low BSIT scores were older age (p = 0.007), lower BMI (p = 0.08), lower MMSE score (p = 0.05), lower FCRST (p = 0.008), hippocampal atrophy (p = 0.04), periventricular WML (p = 0.007), and deep WML burden (p = 0.005). In multivariate analysis, severe deep WML (OR (95% CI) = 6.29 (1.4-35.13), p = 0.02) remained associated with low BSIT score independently from hippocampal atrophy. CONCLUSION: In elderly MCI subjects, low olfactory performances are associated with WML, whose progression may be slowed by vascular treatments. A longitudinal study to evaluate whether the progression of WML, hippocampal atrophy and low olfactory function, can predict accurately conversion from MCI to dementia is ongoing.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Atrophy; Cognitive Dysfunction; Cross-Sectional Studies; Disease Progression; Female; Humans; Logistic Models; Longitudinal Studies; Magnetic Resonance Imaging; Male; Multivariate Analysis; Neuropsychological Tests; Olfaction Disorders; Severity of Illness Index; White Matter

Retinoic Acid Enhances Apolipoprotein E Synthesis in Human Macrophages. - Clemens, Vera; Regen, Francesca; Le Bret, Nathalie; Heuser, Isabella; Hellmann-Regen, Julian (J Alzheimers Dis, 2018)
Apolipoprotein E (ApoE) represents a pivotal target in Alzheimer's disease (AD) and is modulated through retinoic acid (RA), an endogenous neuroprotective and anti-inflammatory compound. A major source of ApoE are microglia, which are pathologically activated in AD. Activated microglia are known to block RA signaling. This suggests a vicious cycle between inflammation, RA signaling, and ApoE homeostasis in AD pathogenesis. To test this hypothesis, we investigated effects of RA and proinflammatory activation on ApoE synthesis in primary human macrophage-derived microglial-like cells. Our results indicate that proinflammatory activation attenuates ApoE synthesis, an effect blocked by RA.
Keywords: Alzheimer Disease; Apolipoproteins E; Cells, Cultured; Humans; Macrophages; Signal Transduction; Tretinoin

A Retrospective Belgian Multi-Center MRI Biomarker Study in Alzheimer's Disease (REMEMBER). - Niemantsverdriet, Ellis; Ribbens, Annemie; Bastin, Christine; Benoit, Florence; Bergmans, Bruno; Bier, Jean-Christophe; Bladt, Roxanne; Claes, Lene; De Deyn, Peter Paul; Deryck, Olivier; Hanseeuw, Bernard; Ivanoiu, Adrian; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Magnetic resonance imaging (MRI) acquisition/processing techniques assess brain volumes to explore neurodegeneration in Alzheimer's disease (AD). OBJECTIVE: We examined the clinical utility of MSmetrix and investigated if automated MRI volumes could discriminate between groups covering the AD continuum and could be used as a predictor for clinical progression. METHODS: The Belgian Dementia Council initiated a retrospective, multi-center study and analyzed whole brain (WB), grey matter (GM), white matter (WM), cerebrospinal fluid (CSF), cortical GM (CGM) volumes, and WM hyperintensities (WMH) using MSmetrix in the AD continuum. Baseline (n = 887) and follow-up (FU, n = 95) T1-weighted brain MRIs and time-linked neuropsychological data were available. RESULTS: The cohort consisted of cognitively healthy controls (HC, n = 93), subjective cognitive decline (n = 102), mild cognitive impairment (MCI, n = 379), and AD dementia (n = 313). Baseline WB and GM volumes could accurately discriminate between clinical diagnostic groups and were significantly decreased with increasing cognitive impairment. MCI patients had a significantly larger change in WB, GM, and CGM volumes based on two MRIs (n = 95) compared to HC (FU>24months, p = 0.020). Linear regression models showed that baseline atrophy of WB, GM, CGM, and increased CSF volumes predicted cognitive impairment. CONCLUSION: WB and GM volumes extracted by MSmetrix could be used to define the clinical spectrum of AD accurately and along with CGM, they are able to predict cognitive impairment based on (decline in) MMSE scores. Therefore, MSmetrix can support clinicians in their diagnostic decisions, is able to detect clinical disease progression, and is of help to stratify populations for clinical trials.

Revolution of Alzheimer Precision Neurology. Passageway of Systems Biology and Neurophysiology. - Hampel, Harald; Toschi, Nicola; Babiloni, Claudio; Baldacci, Filippo; Black, Keith L; Bokde, Arun L W; Bun, René S; Cacciola, Francesco; Cavedo, Enrica; Chiesa, Patrizia A; Colliot, Olivier; Coman, Cristina-Maria; et al. (J Alzheimers Dis, 2018)
The Precision Neurology development process implements systems theory with system biology and neurophysiology in a parallel, bidirectional research path: a combined hypothesis-driven investigation of systems dysfunction within distinct molecular, cellular, and large-scale neural network systems in both animal models as well as through tests for the usefulness of these candidate dynamic systems biomarkers in different diseases and subgroups at different stages of pathophysiological progression. This translational research path is paralleled by an "omics"-based, hypothesis-free, exploratory research pathway, which will collect multimodal data from progressing asymptomatic, preclinical, and clinical neurodegenerative disease (ND) populations, within the wide continuous biological and clinical spectrum of ND, applying high-throughput and high-content technologies combined with powerful computational and statistical modeling tools, aimed at identifying novel dysfunctional systems and predictive marker signatures associated with ND. The goals are to identify common biological denominators or differentiating classifiers across the continuum of ND during detectable stages of pathophysiological progression, characterize systems-based intermediate endophenotypes, validate multi-modal novel diagnostic systems biomarkers, and advance clinical intervention trial designs by utilizing systems-based intermediate endophenotypes and candidate surrogate markers. Achieving these goals is key to the ultimate development of early and effective individualized treatment of ND, such as Alzheimer's disease. The Alzheimer Precision Medicine Initiative (APMI) and cohort program (APMI-CP), as well as the Paris based core of the Sorbonne University Clinical Research Group "Alzheimer Precision Medicine" (GRC-APM) were recently launched to facilitate the passageway from conventional clinical diagnostic and drug development toward breakthrough innovation based on the investigation of the comprehensive biological nature of aging individuals. The APMI movement is gaining momentum to systematically apply both systems neurophysiology and systems biology in exploratory translational neuroscience research on ND.
Keywords: Alzheimer Disease; Animals; Brain; Humans; Neurology; Neurophysiology; Precision Medicine; Systems Biology; Translational Medical Research

Risk of Alzheimer's Disease in Obstructive Sleep Apnea Syndrome: Amyloid-β and Tau Imaging. - Elias, Alby; Cummins, Tia; Tyrrell, Regan; Lamb, Fiona; Doré, Vincent; Williams, Robert; Rosenfeld, J V; Hopwood, Malcolm; Villemagne, Victor L; Rowe, Christopher C (J Alzheimers Dis, 2018)
BACKGROUND: An association between obstructive sleep apnea (OSA) and Alzheimer's disease has been suggested but little is known about amyloid-β and tau deposition in this syndrome. OBJECTIVE: To determine amyloid and tau burden and cognitive function in OSA in comparison with those without a diagnosis of OSA. METHODS: The status of OSA was determined by asking participants about history of polysomnographic diagnosis of OSA and the use of Continuous Positive Airway Pressure (CPAP). A comprehensive neuropsychological battery measured cognitive function. Positron emission tomography (PET) was used to measure standardized uptake value ratio (SUVR) of 18F-florbetaben and 18F-AV1451, to quantify amyloid and tau burden. RESULTS: 119 male Vietnam veterans completed assessment. Impairment in visual attention and processing speed and increased body mass index (BMI) were seen in subjects with OSA compared with those without a diagnosis OSA. The cortical uptake of 18F-florbetaben was higher in the OSA group than in the control group (SUVR: 1.35±0.21 versus 1.27±0.16, p = 0.04). There were more apolipoprotein E ɛ4 allele (APOE ɛ4) carriers in the OSA group than in the control group. In multilinear regression analysis, the significance of OSA in predicting 18F-florbetaben uptake remained independent of age and vascular risk factors but not when BMI or APOE ɛ4 was adjusted. The reported use of CPAP (n = 14) had no effect on cognitive or amyloid PET findings. There was no significant difference in 18F-AV1451 uptake between the two groups. CONCLUSIONS: Obstructive sleep apnea is associated with Alzheimer's disease pathology, but this relationship is moderated by APOE ɛ4 and BMI.

Risk of Conversion to Dementia in a Mild Behavioral Impairment Group Compared to a Psychiatric Group and to a Mild Cognitive Impairment Group. - Taragano, Fernando E; Allegri, Ricardo F; Heisecke, Silvina L; Martelli, María I; Feldman, Mónica L; Sánchez, Viviana; García, Virginia A; Tufro, Graciela; Castro, Diego M; Leguizamón, Patricio Perez; Guelar, Verónica; Ruotolo, Eva; et al. (J Alzheimers Dis, 2018)
BACKGROUND: There is insufficient available information on behavioral changes in the absence of cognitive impairment as factors increasing the risk of conversion to dementia. OBJECTIVE: To observe and analyze patients with mild behavioral impairment (MBI), mild cognitive impairment (MCI), and a psychiatry group (PG) to compare the risk of progression to dementia. METHODS: From 677 initially assessed ≥60-year-old patients, a series of 348 patients was studied for a five-year period until censoring or conversion to dementia: 96 with MBI, 87 with MCI, and 165 with general psychiatry disorders, including 4 subgroups: Anxiety, Depression, Psychosis and Others. All patients were assessed with clinical, psychiatric, neurological, neuropsychological, and neuroimaging studies. RESULTS: From 348 patients, 126 evolved to dementia (36.2%). Conversion was significantly higher in MBI (71.5%), followed by the MCI-MBI overlap (59.6%) and MCI (37.8%) groups, compared to PG (13.9%) (Log-rank p < 0.001). MCI patients mostly converted to Alzheimer's dementia, while MBI converted to frontotemporal dementia and Lewy body dementia. Patients in PG converted to Lewy body dementia and frontotemporal dementia. CONCLUSION: Conversion to dementia is significantly higher in patients with neuropsychiatric symptoms. The MBI concept generates a new milestone in the refining of diagnosis of neurodegenerative diseases and the possibility of creating neuropsychiatric profiles. Its earlier identification will allow new possibilities for therapeutic intervention.

The Role of Verb Fluency in the Detection of Early Cognitive Impairment in Alzheimer's Disease. - Alegret, Montserrat; Peretó, Mar; Pérez, Alba; Valero, Sergi; Espinosa, Ana; Ortega, Gemma; Hernandez, Isabel; Mauleón, Ana; Rosende-Roca, Maitee; Vargas, Liliana; Rodríguez-Gómez, Octavio; Abdelnour, Carla; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Verb fluency (VF) is the less commonly used fluency test, despite several studies suggesting its potential as a neuropsychological assessment tool. OBJECTIVE: To investigate the presence of VF deficits in mild cognitive impairment (MCI) and mild Alzheimer's disease (AD) dementia; to assess the usefulness of VF in the detection of cognitively healthy (CH) people who will convert to MCI, and from MCI to dementia; and to establish the VF cut-offs useful in the cognitive assessment of Spanish population. METHODS: 568 CH, 885 MCI, and 367 mild AD dementia individuals were administered the VF test and a complete neuropsychological battery. Longitudinal analyses were performed in 231 CH and 667 MCI subjects to search for VF predictors of diagnosis conversion. RESULTS: A worsening on VF performance from CH, MCI to AD dementia groups was found. Lower performances on VF were significantly related to conversion from CH to MCI/MCI to dementia. When the effect of time to conversion was analyzed, a significant effect of VF was found on the faster conversion from CH to MCI, but not from MCI to dementia. Moreover, VF cut-off scores and sensitivity/specificity values were calculated for 6 conditions (3 age ranges by 2 educational levels). CONCLUSION: The VF test may be a useful tool for the differential diagnosis of cognitive failure in the elderly. Since VF deficits seem to take place in early stages of the disease, it is a suitable neuropsychological tool for the detection not only of CH people who will convert to MCI, but also from MCI to dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cognitive Dysfunction; Cross-Sectional Studies; Early Diagnosis; Executive Function; Female; Humans; Language Tests; Logistic Models; Longitudinal Studies; Male; Middle Aged; Proportional Hazards Models; Sensitivity and Specificity; Spain

S-[18F]THK-5117-PET and [11C]PIB-PET Imaging in Idiopathic Normal Pressure Hydrocephalus in Relation to Confirmed Amyloid-β Plaques and Tau in Brain Biopsies. - Leinonen, Ville; Rauramaa, Tuomas; Johansson, Jarkko; Bottelbergs, Astrid; Tesseur, Ina; van der Ark, Peter; Pemberton, Darrel; Koivisto, Anne M; Jääskeläinen, Juha E; Hiltunen, Mikko; Herukka, Sanna-Kaisa; Blennow, Kaj; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Detection of pathological tau aggregates could facilitate clinical diagnosis of Alzheimer's disease (AD) and monitor drug effects in clinical trials. S-[18F]THK-5117 could be a potential tracer to detect pathological tau deposits in brain. However, no previous study have correlated S-[18F]THK-5117 uptake in PET with brain biopsy verified tau pathology in vivo. OBJECTIVE: Here we aim to evaluate the association between cerebrospinal fluid (CSF) AD biomarkers, S-[18F]THK-5117, and [11C]PIB PET against tau and amyloid lesions in brain biopsy. METHODS: Fourteen patients with idiopathic normal pressure hydrocephalus (iNPH) with previous shunt surgery including right frontal cortical brain biopsy and CSF Aβ1 - 42, total tau, and P-tau181 measures, underwent brain MRI, [11C]PIB PET, and S-[18F]THK-5117 PET imaging. RESULTS: Seven patients had amyloid-β (Aβ, 4G8) plaques, two both Aβ and phosphorylated tau (Pτ, AT8) and one only Pτ in biopsy. As expected, increased brain biopsy Aβ was well associated with higher [11C]PIB uptake in PET. However, S-[18F]THK-5117 uptake did not show any statistically significant correlation with either brain biopsy Pτ or CSF P-tau181 or total tau. CONCLUSIONS: S-[18F]THK-5117 lacked clear association with neuropathologically verified tau pathology in brain biopsy probably, at least partially, due to off-target binding. Further studies with larger samples of patients with different tau tracers are urgently needed. The detection of simultaneous Aβ and tau pathology in iNPH is important since that may indicate poorer and especially shorter response for CSF shunt surgery compared with no pathology.

Secular Trends in Dementia Prevalence and Incidence Worldwide: A Systematic Review. - Stephan, Blossom C M; Birdi, Ratika; Tang, Eugene Yee Hing; Cosco, Theodore D; Donini, Lorenzo M; Licher, Silvan; Ikram, M Arfan; Siervo, Mario; Robinson, Louise (J Alzheimers Dis, 2018)
BACKGROUND: Time trends for dementia prevalence and incidence rates have been reported over the past seven decades in different countries and some have reported a decline. OBJECTIVE: To undertake a systematic review to critically appraise and provide an evidence-based summary of the magnitude and direction of the global changes in dementia prevalence and incidence across time. METHODS: Medline, EMBASE, and PsychINFO were searched for studies focused on secular trends in dementia prevalence and/or incidence until 18 December 2017. In total, 10,992 articles were identified and 43 retained. RESULTS: Overall, prevalence rates are largely increasing (evidence primarily from record-based surveys and cohort studies in Japan, Canada, and France) or have remained stable (evidence primarily from cohort studies in Sweden, Spain and China). A significant decline in prevalence has however been reported in more recent studies (i.e., from 2010 onwards) from Europe (e.g., UK and Sweden) and the USA. Incidence rates have generally remained stable or decreased in China, Canada, France, Germany, Denmark, Sweden, the Netherlands, UK, and USA. An increase has only been reported in five countries: Italy, Japan, Wales, Germany, and the Netherlands. Only one study reported findings (stability in incidence) from a low and middle-income country using data from Nigeria. CONCLUSIONS: The evidence on secular trends in the prevalence and incidence of dementia is mixed including contradictory findings using different (and in some cases the same) datasets in some countries (e.g., the USA, UK, and Sweden). This making it difficult to draw concrete conclusions. However, declining trends recently observed in some high-income Western countries in the most recent two decades including the UK, USA, and Sweden are encouraging. Updated dementia prevalence and incidence estimates will inform public health and financial planning as well as development of prevention strategies.

Self- and Informant-Reported Memory Complaints: Frequency and Severity in Cognitively Intact Individuals and those with Mild Cognitive Impairment and Neurodegenerative Dementias. - Rahman-Filipiak, Annalise M; Giordani, Bruno; Heidebrink, Judith; Bhaumik, Arijit; Hampstead, Benjamin M (J Alzheimers Dis, 2018)
BACKGROUND: Subjective memory complaints (SMCs) are incorporated into the diagnosis of mild cognitive impairment (MCI) and neurodegenerative dementias; however, the relative frequency of SMCs in cognitively intact older adults and those with different types of dementia is poorly understood. Similarly, the concordance between self- versus informant-reported SMCs has not been compared across different diagnostic groups. OBJECTIVE: This study aimed to evaluate the frequency of self-reported (Objective 1) and informant-reported (Objective 2) SMCs in cognitively intact adults or those diagnosed with MCI or a neurodegenerative dementia. Agreement between participant and informant complaints was also evaluated (Objective 3). METHODS: Baseline evaluation data were drawn from 488 participants (Mage = 70.49 years; Medu = 15.62 years) diagnosed as cognitively intact, non-amnestic MCI, amnestic single domain MCI, amnestic multi-domain MCI, possible/probable Alzheimer's disease, dementia with Lewy bodies, or frontotemporal dementia. Participants and their informants completed the Memory Assessment Clinic Questionnaire. RESULTS: One-way ANCOVAs controlling for age, education, and depression revealed no group differences in severity of self-reported SMCs. In contrast, informant memory ratings followed the expected clinical pattern, with comparable and most impaired ratings given to participants with any dementia diagnosis, followed by those with any MCI diagnosis, followed by cognitively intact participants. There was inconsistent agreement between self- and informant-reported SMC ratings in any of the impaired groups. CONCLUSIONS: Given greater diagnostic specificity and internal consistency of informant report, clinicians should weigh this information more heavily than self-report in the diagnostic process.

Self-Reported Physical Activity is Associated with Tau Burden Measured by Positron Emission Tomography. - Brown, Belinda M; Rainey-Smith, Stephanie R; Doré, Vincent; Peiffer, Jeremiah J; Burnham, Samantha C; Laws, Simon M; Taddei, Kevin; Ames, David; Masters, Colin L; Rowe, Christopher C; Martins, Ralph N; Villemagne, Victor L (J Alzheimers Dis, 2018)
Numerous animal studies have reported exercise reduces the accumulation of Alzheimer's disease pathology, including amyloid-β (Aβ) and tau. Furthermore, we previously reported a relationship between higher levels of physical activity (PA) and lower brain Aβ burden in a human population. The recent advent of tau positron emission tomography (PET) tracers enables us to extend our investigations into the evaluation of the relationship between PA and brain tau burden. Utilizing data from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study, we have examined the cross-sectional relationship between habitual PA and PET-quantified tau burden. Forty-three cognitively healthy older adults were categorized into low-moderate PA (LMPA; n = 16) or high PA (HPA; n = 27), based on self-reported PA levels. Tau PET imaging with the AV1451 tracer was conducted on all participants. The LMPA group had significantly higher neocortical tau burden (presented as a z-score; 1.22±1.98), compared to the HPA group (z-score: - 0.28±1.18). The difference between the LMPA and HPA groups was also evident when examining regional tau burden in the temporoparietal cortex and the prefrontal cortex. Our results suggest an association between self-reported PA level and brain tau burden. Future longitudinal and interventional studies utilizing larger samples sizes are vital to further investigate the nature of the relationship between tau and PA.

Serotonin Selective Reuptake Inhibitor Treatment Improves Cognition and Grey Matter Atrophy but not Amyloid Burden During Two-Year Follow-Up in Mild Cognitive Impairment and Alzheimer's Disease Patients with Depressive Symptoms. - Brendel, Matthias; Sauerbeck, Julia; Greven, Sonja; Kotz, Sebastian; Scheiwein, Franziska; Blautzik, Janusch; Delker, Andreas; Pogarell, Oliver; Ishii, Kazunari; Bartenstein, Peter; Rominger, Axel (J Alzheimers Dis, 2018)
Late-life depression, even when of subsyndromal severity, has shown strong associations with mild cognitive impairment (MCI) and Alzheimer's disease (AD). Preclinical studies have suggested that serotonin selective reuptake inhibitors (SSRIs) can attenuate amyloidogenesis. Therefore, we aimed to investigate the effect of SSRI medication on amyloidosis and grey matter volume in subsyndromal depressed subjects with MCI and AD during an interval of two years. 256 cognitively affected subjects (225 MCI/ 31 AD) undergoing [18F]-AV45-PET and MRI at baseline and 2-year follow-up were selected from the ADNI database. Subjects with a positive depression item (DEP(+); n = 73) in the Neuropsychiatric Inventory Questionnaire were subdivided to those receiving SSRI medication (SSRI(+); n = 24) and those without SSRI treatment (SSRI(-); n = 49). Longitudinal cognition (Δ-ADAS), amyloid deposition rate (standardized uptake value, using white matter as reference region (SUVRWM), and changes in grey matter volume were compared using common covariates. Analyses were performed separately in all subjects and in the subgroup of amyloid-positive subjects. Cognitive performance in DEP(+)/SSRI(+) subjects (Δ-ADAS: -5.0%) showed less deterioration with 2-year follow-up when compared to DEP(+)/SSRI(-) subjects (Δ-ADAS: +18.6%, p < 0.05), independent of amyloid SUVRWM at baseline. With SSRI treatment, the progression of grey matter atrophy was reduced (-0.9% versus -2.7%, p < 0.05), notably in fronto-temporal cortex. A slight trend towards lower amyloid deposition rate was observed in DEP(+)/SSRI(+) subjects versus DEP(+)/SSRI(-). Despite the lack of effect to amyloid PET, SSRI medication distinctly rescued the declining cognitive performance in cognitively affected patients with depressive symptoms, and likewise attenuated grey matter atrophy.

Serum Copper is not Altered in Frontotemporal Lobar Degeneration. - Squitti, Rosanna; Fostinelli, Silvia; Siotto, Mariacristina; Ferrari, Clarissa; Binetti, Giuliano; Benussi, Luisa; Rongioletti, Mauro; Ghidoni, Roberta (J Alzheimers Dis, 2018)
Meta-analyses show copper dyshomeostasis in Alzheimer's disease. However, a study evaluating copper changes in other neurodegenerative forms of dementia has not yet been performed. In this study, we assessed copper, ceruloplasmin, copper not bound to ceruloplasmin, and copper to ceruloplasmin ratio in 85 patients affected by frontotemporal lobar degeneration (FTLD) and 55 healthy controls. Data were analyzed through multivariate ANOVA models taking into account age and sex as covariates and the stratification for FTLD variants, after calculating power analysis to ensure the reliability of the conclusions drawn. The study revealed no difference between the groups.

Serum Non-Ceruloplasmin Non-Albumin Copper Elevation in Mild Cognitive Impairment and Dementia due to Alzheimer's Disease: A Case Control Study. - Rozzini, Luca; Lanfranchi, Francesco; Pilotto, Andrea; Catalani, Simona; Gilberti, Maria Enrica; Paganelli, Matteo; Apostoli, Pietro; Padovani, Alessandro (J Alzheimers Dis, 2018)
Several studies showed high serum copper levels in Alzheimer's disease (AD). The present study applied a newly developed method to detect serum copper free from proteins (free-Cu). Forty-four patients affected by dementia due to AD, thirty-six patients affected by mild cognitive impairment (MCI) due to AD, and twenty-eight healthy controls underwent clinical, cognitive, and MRI assessment. The new method showed higher free-Cu concentrations in MCI and dementia due to AD compared to controls (p < 0.0001). No correlation between copper levels, cognitive or MRI measures were found.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cognitive Dysfunction; Copper; Female; Humans; Magnetic Resonance Imaging; Male; Psychiatric Status Rating Scales

Sex Influences the Accuracy of Subjective Memory Complaint Reporting in Older Adults. - Sundermann, Erin E; Edmonds, Emily C; Delano-Wood, Lisa; Galasko, Douglas R; Salmon, David P; Rubin, Leah H; Bondi, Mark W (J Alzheimers Dis, 2018)
Subjective memory complaints (SMC) are required when diagnosing amnestic mild cognitive impairment (aMCI), although their relationship with objective memory performance and Alzheimer's disease (AD) pathology remains unclear. We investigated whether the sex of the patient/participant moderates these associations. Participants were 940 normal control (NC) and aMCI participants from the Alzheimer's Disease Neuroimaging Initiative. SMC were assessed via the memory scale of the Everyday Cognition questionnaire. Discrepancy scores were calculated between self- and informant-reports and categorized into "overestimates," "comparable estimates", and "underestimates" of SMC. We conducted linear and logistic regressions to examine the interaction of sex with self- and informant-reported SMC and discrepancy group on the Rey Auditory Verbal Learning Test (RAVLT) Immediate and Delayed Recall and on PET measures of amyloid-β (Aβ) positivity. Diagnosis-stratified analyses were also conducted. Overall, there were sex by self- and informant-reported SMC interactions for Immediate and Delayed Recall. Despite a higher proportion of "overestimates" in women, greater self- and informant-reported SMC showed a stronger relationship to poorer RAVLT scores in women versus men. Diagnosis-stratified analyses revealed that results were driven by aMCI participants. Conversely, overall, greater self- and informant-reported SMC related to greater odds of Aβ positivity regardless of sex. In diagnosis-stratified analyses, only informant-reported SMC related to Aβ positivity in aMCI. Relative to "comparable estimates," "underestimates" of SMC were associated with poorer RAVLT scores across sexes in the overall sample and in aMCI. The predictive utility of self-report SMC may be limited to women in aMCI. Sex differences should be considered when evaluating SMC.
Keywords: Aged; Cognitive Dysfunction; Female; Humans; Logistic Models; Male; Memory Disorders; Mental Recall; Neuropsychological Tests; Self Report; Sex Factors

Sex-Dependent Differences in Spontaneous Autoimmunity in Adult 3xTg-AD Mice. - Kapadia, Minesh; Mian, M Firoz; Michalski, Bernadeta; Azam, Amber B; Ma, Donglai; Salwierz, Patrick; Christopher, Adam; Rosa, Elyse; Zovkic, Iva B; Forsythe, Paul; Fahnestock, Margaret; Sakic, Boris (J Alzheimers Dis, 2018)
The triple-transgenic (3xTg-AD) mouse strain is a valuable model of Alzheimer's disease (AD) because it develops both amyloid-β (Aβ) and tau brain pathology. However, 1-year-old 3xTg-AD males no longer show plaques and tangles, yet early in life they exhibit diverse signs of systemic autoimmunity. The current study aimed to address whether females, which exhibit more severe plaque/tangle pathology at 1 year of age, show similar autoimmune phenomena and if so, whether these immunological changes coincide with prodromal markers of AD pathology, markers of learning and memory formation, and epigenetic markers of neurodegenerative disease. Six-month-old 3xTg-AD and wild-type mice of both sexes were examined for T-cell phenotype (CD3+, CD8+, and CD4+ populations), serological measures (autoantibodies, hematocrit), soluble tau/phospho-tau and Aβ levels, brain-derived neurotrophic factor (BDNF) expression, and expression of histone H2A variants. Although no significant group differences were seen in tau/phospho-tau levels, 3xTg-AD mice had lower brain mass and showed increased levels of soluble Aβ and downregulation of BDNF expression in the cortex. Splenomegaly, depleted CD+ T-splenocytes, increased autoantibody levels and low hematocrit were more pronounced in 3xTg-AD males than in females. Diseased mice also failed to exhibit sex-specific changes in histone H2A variant expression shown by wild-type mice, implicating altered nucleosome composition in these immune differences. Our study reveals that the current 3xTg-AD model is characterized by systemic autoimmunity that is worse in males, as well as transcriptional changes in epigenetic factors of unknown origin. Given the previously observed lack of plaque/tangle pathology in 1-year-old males, an early, sex-dependent autoimmune mechanism that interferes with the formation and/or deposition of aggregated protein species is hypothesized. These results suggest that more attention should be given to studying sex-dependent differences in the immunological profiles of human patients.

Single Subject Classification of Alzheimer's Disease and Behavioral Variant Frontotemporal Dementia Using Anatomical, Diffusion Tensor, and Resting-State Functional Magnetic Resonance Imaging. - Bouts, Mark J R J; Möller, Christiane; Hafkemeijer, Anne; van Swieten, John C; Dopper, Elise; van der Flier, Wiesje M; Vrenken, Hugo; Wink, Alle Meije; Pijnenburg, Yolande A L; Scheltens, Philip; Barkhof, Frederik; Schouten, Tijn M; et al. (J Alzheimers Dis, 2018)
BACKGROUND/OBJECTIVE: Overlapping clinical symptoms often complicate differential diagnosis between patients with Alzheimer's disease (AD) and behavioral variant frontotemporal dementia (bvFTD). Magnetic resonance imaging (MRI) reveals disease specific structural and functional differences that aid in differentiating AD from bvFTD patients. However, the benefit of combining structural and functional connectivity measures to-on a subject-basis-differentiate these dementia-types is not yet known. METHODS: Anatomical, diffusion tensor (DTI), and resting-state functional MRI (rs-fMRI) of 30 patients with early stage AD, 23 with bvFTD, and 35 control subjects were collected and used to calculate measures of structural and functional tissue status. All measures were used separately or selectively combined as predictors for training an elastic net regression classifier. Each classifier's ability to accurately distinguish dementia-types was quantified by calculating the area under the receiver operating characteristic curves (AUC). RESULTS: Highest AUC values for AD and bvFTD discrimination were obtained when mean diffusivity, full correlations between rs-fMRI-derived independent components, and fractional anisotropy (FA) were combined (0.811). Similarly, combining gray matter density (GMD), FA, and rs-fMRI correlations resulted in highest AUC of 0.922 for control and bvFTD classifications. This, however, was not observed for control and AD differentiations. Classifications with GMD (0.940) and a GMD and DTI combination (0.941) resulted in similar AUC values (p = 0.41). CONCLUSION: Combining functional and structural connectivity measures improve dementia-type differentiations and may contribute to more accurate and substantiated differential diagnosis of AD and bvFTD patients. Imaging protocols for differential diagnosis may benefit from also including DTI and rs-fMRI.

Small Vessel Cerebrovascular Pathology Identified by Magnetic Resonance Imaging Is Prevalent in Alzheimer's Disease and Mild Cognitive Impairment: A Potential Target for Intervention. - Scott, Tammy M; Bhadelia, Rafeeque A; Qiu, Wei Qiao; Folstein, Marshal F; Rosenberg, Irwin H (J Alzheimers Dis, 2018)
BACKGROUND: There is evidence that Alzheimer's disease (AD) has significant cerebrovascular etiopathogenesis. Understanding potentially modifiable risk factors for vascular disease can help design long-term intervention strategies for controlling or preventing cognitive dysfunction attributable to cerebrovascular disease. OBJECTIVE: To evaluate the presence and severity of markers of cerebrovascular pathology, its relationship to diagnostic categories of dementia, including AD, and association with the metabolic biomarker homocysteine. METHODS: In a cross-sectional observational study, 340 community-dwelling elders received a clinical evaluation including brain MRI and neuropsychological tests. Dementia and mild cognitive impairment (MCI) were diagnosed by consensus committee. Fasting total plasma homocysteine was measured. Statistical analyses were adjusted for demographics and cerebrovascular risk factors. RESULTS: Nearly 25% of those diagnosed with AD had small vessel infarcts (SVI). Periventricular white matter hyperintensity (pvWMHI) was prevalent in participants with AD (61%) or MCI (amnesic 61% and non-amnesic 54%, respectively). Participants with SVI and/or pvWMHI also had greater brain atrophy. Homocysteine concentrations were higher in individuals with cerebrovascular findings than in those without. In individuals with cerebrovascular disease, homocysteine was inversely related to executive function (p = 0.022) and directly related to degree of brain atrophy (p = 0.009). CONCLUSIONS: We demonstrated a significant prevalence of small vessel markers of cerebrovascular pathology in individuals diagnosed with AD, with a significant concurrence between cerebrovascular disease and brain and ventricular atrophy. While current research on AD has focused on amyloid-βpeptide deposition, tau-pathology, and microglial activation and inflammation, greater attention to the cerebrovascular contribution to this neurodegenerative disease presents an additional target for therapeutic prevention and intervention.

SORL1 Variants in Familial Alzheimer's Disease. - Gómez-Tortosa, Estrella; Ruggiero, María; Sainz, Ma José; Villarejo-Galende, Alberto; Prieto-Jurczynska, Cristina; Venegas Pérez, Begoña; Ordás, Carlos; Agüero, Pablo; Guerrero-López, Rosa; Pérez-Pérez, Julián (J Alzheimers Dis, 2018)
The SORL1 gene encodes a protein involved in the amyloidogenic process, and its variants have been associated with Alzheimer's disease (AD) physiopathology. We screened for SORL1 variants in 124 familial (44 early- and 80 late-onset) dementia of Alzheimer type (DAT) cases. Nine potentially pathogenic changes (three not previously reported and six rare variants) were found in nine probands (7%). After screening the control population and siblings (presence in at least 1/200 controls and/or absence of segregation pattern), a causal relationship with the disease was considered unlikely in six variants and uncertain in one. The change Trp848Ter and a splice-site variant remained likely correlated with the disease. SORL1 mutations are present in 7% of our familial DAT cohort, though in most cases cannot be considered the direct cause of the disease.
Keywords: Aged; Alzheimer Disease; Case-Control Studies; Female; Gene Frequency; Genetic Predisposition to Disease; Humans; LDL-Receptor Related Proteins; Male; Membrane Transport Proteins; Middle Aged; Mutation; Polymorphism, Single Nucleotide; Siblings; Spain

Statins and Brain Health: Alzheimer's Disease and Cerebrovascular Disease Biomarkers in Older Adults. - Ramanan, Vijay K; Przybelski, Scott A; Graff-Radford, Jonathan; Castillo, Anna M; Lowe, Val J; Mielke, Michelle M; Roberts, Rosebud O; Reid, Robert I; Knopman, David S; Jack, Clifford R; Petersen, Ronald C; Vemuri, Prashanthi (J Alzheimers Dis, 2018)
BACKGROUND: Statins have been proposed to reduce the risk of Alzheimer's disease (AD). OBJECTIVE: Assess whether long-term statin use was associated with neuroimaging biomarkers of aging and dementia. METHODS: Methods: We analyzed neuroimaging biomarkers in 1,160 individuals aged 65+ from the Mayo Clinic Study of Aging, a population-based prospective longitudinal study of cognitive aging. RESULTS: Statin-treated (5+ years of therapy) individuals had greater burden of mid-and late-life cardiovascular disease (p < 0.001) than statin-untreated (≤3 months) individuals. Lower fractional anisotropy in the genu of the corpus callosum, an early marker of cerebrovascular disease, was associated with long-term statin exposure (p < 0.035). No significant associations were identified between long-term statin exposure and cerebral amyloid or tau burden, AD pattern neurodegeneration, or white matter hyperintensity burden. CONCLUSIONS: Long-term statin therapy was not associated with differences in AD biomarkers. Individuals with long-term statin exposure had worse white matter integrity in the genu of the corpus callosum, consistent with the coexistence of higher cerebrovascular risk factor burden in this group.

Structural Anatomical Investigation of Long-Term Memory Deficit in Behavioral Frontotemporal Dementia. - Bertoux, Maxime; Flanagan, Emma C; Hobbs, Matthew; Ruiz-Tagle, Amparo; Delgado, Carolina; Miranda, Marcelo; Ibáñez, Agustín; Slachevsky, Andrea; Hornberger, Michael (J Alzheimers Dis, 2018)
Although a growing body of work has shown that behavioral variant frontotemporal dementia (bvFTD) could present with severe amnesia in approximately half of cases, memory assessment is currently the clinical standard to distinguish bvFTD from Alzheimer's disease (AD). Thus, the concept of "relatively preserved episodic memory" in bvFTD remains the basis of its clinical distinction from AD and a criterion for bvFTD's diagnosis. This view is supported by the idea that bvFTD is not characterized by genuine amnesia and hippocampal degeneration, by contrast to AD. In this multicenter study, we aimed to investigate the neural correlates of memory performance in bvFTD as assessed by the Free and Cued Selective Reminding Test (FCSRT). Imaging explorations followed a two-step procedure, first relying on a visual rating of atrophy of 35 bvFTD and 34 AD patients' MRI, contrasted with 29 controls; and then using voxel-based morphometry (VBM) in a subset of bvFTD patients. Results showed that 43% of bvFTD patients presented with a genuine amnesia. Data-driven analysis on visual rating data showed that, in bvFTD, memory recall & storage performances were significantly predicted by atrophy in rostral prefrontal and hippocampal/perihippocampal regions, similar to mild AD. VBM results in bvFTD (pFWE<0.05) showed similar prefrontal and hippocampal regions in addition to striatal and lateral temporal involvement. Our findings showed the involvement of prefrontal as well as medial/lateral temporal atrophy in memory deficits of bvFTD patients. This contradicts the common view that only frontal deficits explain memory impairment in this disease and plead for an updated view on memory dysfunctions in bvFTD.

Structural Connectivity Alterations Along the Alzheimer's Disease Continuum: Reproducibility Across Two Independent Samples and Correlation with Cerebrospinal Fluid Amyloid-β and Tau. - Tucholka, Alan; Grau-Rivera, Oriol; Falcon, Carles; Rami, Lorena; Sánchez-Valle, Raquel; Lladó, Albert; Gispert, Juan Domingo; Molinuevo, José Luis (J Alzheimers Dis, 2018)
BACKGROUND: Gray matter changes associated with the progression of Alzheimer's disease (AD) have been thoroughly studied. However, alterations in white matter tracts have received less attention, particularly during early or preclinical stages of the disease. OBJECTIVE: To identify the structural connectivity changes across the AD continuum. METHODS: We performed probabilistic tractography in a total of 183 subjects on two independent samples that include control (n = 68) and preclinical AD individuals (n = 28), patients diagnosed with mild cognitive impairment (MCI) due to AD (n = 44), and AD patients (n = 43). We compared the connectivity between groups, and with CSF Aβ42 and tau biomarkers. RESULTS: We observed disconnections in preclinical individuals, mainly located in the temporal lobe. This pattern of disconnection spread to the parietal and frontal lobes at the MCI stage and involved almost all the brain in AD. These findings were not driven by gray matter atrophy. DISCUSSION: Using tractography, we were able to identify white matter changes between subsequent disease stages and, notably, also in preclinical AD. Therefore, this method may be useful for detecting early and specific brain structural changes during preclinical AD stage.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Atrophy; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Cohort Studies; Disease Progression; Female; Gray Matter; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Reproducibility of Results; Spain; tau Proteins; White Matter

Subjective Cognitive Decline Is Associated with Greater White Matter Hyperintensity Volume. - van Rooden, Sanneke; van den Berg-Huysmans, Annette A; Croll, Pauline H; Labadie, Gerda; Hayes, Jessica M; Viviano, Raymond; van der Grond, Jeroen; Rombouts, Serge A R B; Damoiseaux, Jessica S (J Alzheimers Dis, 2018)
BACKGROUND: Research in older adults with subjective cognitive decline (SCD) has mainly focused on Alzheimer's disease (AD)-related MRI markers, such as hippocampal volume. However, small vessel disease (SVD) is currently established as serious comorbidity in dementia and its preliminary stages. It is therefore important to examine SVD markers in addition to AD markers in older adults presenting with SCD. OBJECTIVE: The aim of our study was to elucidate the role of SVD markers in late middle-aged to older adults with and without SCD in addition to the commonly found role of AD markers (hippocampal volume). METHODS: 67 healthy late middle-aged to older adults participated in this study (mean age 68 years); 25 participants with SCD and 42 participants without SCD. We evaluated quantitative as well as qualitative AD markers (i.e., hippocampal volume and medial temporal lobe atrophy (MTA) scale) and SVD markers (i.e., white matter hyperintensities (WMH) volume, Fazekas scale, microbleeds, and lacunar infarcts), and neuropsychological function and amount of memory complaints. RESULTS: We found a significant effect of SCD on hippocampal atrophy, as assessed using the MTA scale, but not on hippocampal volume. In addition, we found a significant effect of SCD, and amount of memory complaints, on WMH volume and Fazekas score, suggesting larger WMH volumes in participants with SCD. CONCLUSION: SVD MRI markers are related to amount of memory complaints, in addition to the commonly observed AD MRI markers, as demonstrated by the greater WMHs in healthy late middle-aged to older adults with SCD.

Subjective Cognitive Decline Prediction of Mortality: Results from the Einstein Aging Study. - Katz, Mindy J; Wang, Cuiling; Derby, Carol A; Lipton, Richard B; Zimmerman, Molly E; Sliwinski, Martin J; Rabin, Laura A (J Alzheimers Dis, 2018)
BACKGROUND: The relation of pre-dementia stages to mortality has not been fully explored. Previous work examining subjective cognitive decline (SCD) and mortality is limited and mixed regarding methods used and consistency of findings. OBJECTIVE: To examine SCD and mortality in a longitudinal, community-based cohort, using item response theory (IRT) methodology to form a composite SCD measure. Also, to assess whether this relationship was independent of clinical cognitive status. METHODS: The Einstein Aging Study is a diverse longitudinal cohort of adults aged ≥70. SCD items were extracted from baseline CERAD questionnaires and a composite score was formed using IRT methodology. A total of 1,741 participants with complete data were clinically diagnosed as cognitively normal, or as having amnestic mild cognitive impairment (aMCI), nonamnestic mild cognitive impairment (naMCI), or dementia. 645 deaths occurred over a period of 8,912 person-years of follow-up. Cox proportional hazard models predicted time to death adjusting for covariates. RESULTS: A one standard deviation unit increase in level of SCD was associated with >20% higher risk of mortality. However, when models were adjusted for clinical cognitive status, the association was no longer significant. Both dementia and aMCI predicted mortality. Furthermore, when analyses focused only on those without cognitive impairment, SCD level did not predict mortality. CONCLUSIONS: The association of SCD with mortality may be due to the association of SCD with clinical cognitive status. Thus, SCD may be used as a community-based screen to initially identify those with cognitive impairment who may be at greatest risk for death.

Subtle Cognitive Impairment and Alzheimer's Disease-Type Pathological Changes in Cerebrospinal Fluid are Common Among Neurologically Healthy Subjects. - Haapalinna, Fanni; Kokki, Merja; Jääskeläinen, Olli; Hallikainen, Merja; Helisalmi, Seppo; Koivisto, Anne; Kokki, Hannu; Paajanen, Teemu; Penttinen, Janne; Pikkarainen, Maria; Rautiainen, Minna; Soininen, Hilkka; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The neuropathology of Alzheimer's disease (AD) has previously been shown to be rather common among the elderly. OBJECTIVE: The aim of this study was to inspect the associations between cerebrospinal fluid (CSF) AD biomarker concentrations, age, the APOEɛ4 allele, cardiovascular diseases, diabetes, and cognitive performance in a cohort of a neurologically healthy population. METHODS: This study included 93 subjects (42 men, mean age 67 years) without previous neurological symptoms or subjective cognitive complaints. Their cognition was assessed, and CSF biomarkers and APOEɛ4 status were analyzed. RESULTS: Of the studied subjects, 8.6% (n = 8) had a pathological CSF AD biomarker profile. An increase in age correlated positively with CSF tau pathology and negatively with global cognitive performance. CONCLUSION: AD-type pathological changes in CSF and subtle cognitive impairment are common within a population with no previous memory complaints. Age was the main risk factor for the changes.

Synergistic Protective Effects of Mitochondrial Division Inhibitor 1 and Mitochondria-Targeted Small Peptide SS31 in Alzheimer's Disease. - Reddy, P Hemachandra; Manczak, Maria; Yin, XiangLing; Reddy, Arubala P (J Alzheimers Dis, 2018)
The purpose of our study was to determine the synergistic protective effects of mitochondria-targeted antioxidant SS31 and mitochondria division inhibitor 1 (Mdivi1) in Alzheimer's disease (AD). Using biochemical methods, we assessed mitochondrial function by measuring the levels of hydrogen peroxide, lipid peroxidation, cytochrome c oxidase activity, mitochondrial ATP, and GTPase Drp1 enzymatic activity in mutant AβPP cells. Using biochemical methods, we also measured cell survival and apoptotic cell death. Amyloid-β (Aβ) levels were measured using sandwich ELISA, and using real-time quantitative RT-PCR, we assessed mtDNA (mtDNA) copy number in relation to nuclear DNA (nDNA) in all groups of cells. We found significantly reduced levels of Aβ40 and Aβ42 in mutant AβPP cells treated with SS31, Mdivi1, and SS31+Mdivi1, and the reduction of Aβ42 levels were much higher in SS31+Mdivi1 treated cells than individual treatments of SS31 and Mdivi1. The levels of mtDNA copy number and cell survival were significantly increased in SS31, Mdivi1, and SS31+Mdivi1 treated mutant AβPP cells; however, the increased levels of mtDNA copy number and cell survival were much higher in SS31+Mdivi1 treated cells than individual treatments of SS31 and Mdivi1. Mitochondrial dysfunction is significantly reduced in SS31, Mdivi1, and SS31+Mdivi1 treated mutant AβPP cells; however, the reduction is much higher in cells treated with both SS31+Mdvi1. Similarly, GTPase Drp1 activity is reduced in all treatments, but reduced much higher in SS31+Mdivi1 treated cells. These observations strongly suggest that combined treatment of SS31+Mdivi1 is effective than individual treatments of SS31 and Mdivi1. Therefore, we propose that combined treatment of SS31+Mdivi1 is a better therapeutic strategy for AD. Ours is the first study to investigate combined treatment of mitochondria-targeted antioxidant SS31 and mitochondrial division inhibitor 1 in AD neurons.

Targeting Alzheimer's Disease at the Right Time and the Right Place: Validation of a Personalized Approach to Diagnosis and Treatment. - Gauthier, Serge; Ng, Kok Pin; Pascoal, Tharick A; Zhang, Hua; Rosa-Neto, Pedro (J Alzheimers Dis, 2018)
Cautious optimism is appropriate for a near future (five years) time frame for a number of drugs acting on the different pathophysiological components of Alzheimer's disease (amyloid deposition, tau hyperphosphorylation, neuroinflammation, vascular changes, to name the most important known so far). Since the relative weight of these components will be different between individuals and will even change over time for each individual, a 'one drug fit for all' approach is no longer defensible. Precision medicine using biomarkers in the diagnosis and treatment of Alzheimer's disease is the new strategy.

Tau and Amyloid Positron Emission Tomography Imaging Predict Driving Performance Among Older Adults with and without Preclinical Alzheimer's Disease. - Roe, Catherine M; Babulal, Ganesh M; Mishra, Shruti; Gordon, Brian A; Stout, Sarah H; Ott, Brian R; Carr, David B; Ances, Beau M; Morris, John C; Benzinger, Tammie L S (J Alzheimers Dis, 2018)
Abnormal levels of Alzheimer's disease (AD) biomarkers, measured by positron emission tomography imaging using amyloid-based radiotracers and cerebrospinal fluid, are associated with impaired driving performance in older adults. We examined whether preclinical AD staging, defined using amyloid imaging and tau imaging using the radiotracer T807 (AKA flortaucipir or AV-1451), was associated with receiving a marginal/fail rating on a standardized road test (n = 42). Participants at Stage 2 (positive amyloid and tau scans) of preclinical AD were more likely to receive a marginal/fail rating compared to participants at Stage 0 or 1. Stage 2 preclinical AD may manifest in worse driving performance.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid; Automobile Driving; Biomarkers; Carbolines; Female; Humans; Logistic Models; Male; Neuroimaging; Positron-Emission Tomography; tau Proteins

Testing Hippocampal Memory in Prodromal Dementia with Lewy Bodies. - Bussè, Cinzia; Caffarra, Paolo; Rossi, Alice; Zorzi, Giovanni; Fragiacomo, Federica; Camporese, Giulia; Pompanin, Sara; Di Bernardo, Gian Antonio; Cagnin, Annachiara (J Alzheimers Dis, 2018)
The Free and Cued Selective Reminding test (FCSRT) was used to assess memory in 19 patients with prodromal dementia with Lewy bodies (DLB) and 25 Alzheimer's disease (AD) patients. DLB scored better than AD in selective measures of the FCSRT: immediate total recall (p = 0.01) and index of sensitivity of cueing (p = 0.001), while free delayed and total memory scores were similarly impaired. The index of sensitivity of cueing held a sensitivity of 76% and specificity of 79% in distinguishing DLB. FCSRT could help in disentangling hippocampal memory deficits from memory impairment due to ineffective recall strategies.

Is There a Characteristic Clinical Profile for Patients with Dementia and Sundown Syndrome? - Angulo Sevilla, David; Carreras Rodríguez, María Teresa; Heredia Rodríguez, Patricia; Fernández Sánchez, Marisa; Vivancos Mora, José Aurelio; Gago-Veiga, Ana Beatriz (J Alzheimers Dis, 2018)
BACKGROUND: Sundown syndrome (SS) is the onset or worsening of behavioral symptoms in the evening in patients with dementia. OBJECTIVE: To identify the differential clinical profile of patients with dementia who present SS. METHODS: A cross-sectional, case-control observational study was conducted by retrospectively reviewing the medical records of patients with dementia in a specialized Memory Unit. We compared the characteristics of patients with and without SS, including sociodemographic variables, etiology, and severity of the dementia, behavioral symptoms, sleep disorders (considering insomnia and hypersomnia), other diseases and treatments employed. We identified the factors related to SS and conducted a logistic regression analysis to establish a predictive nomogram. RESULTS: Of the 216 study patients with dementia, 41 (19%) had SS. There was a predominance of women (2.4:1), advanced age (p = 0.0001), dependence (p < 0.0001), institutionalization (p < 0.0001), caregiver burden (p < 0.0001), anxiety (p < 0.0001), delirium (p < 0.0001), hallucinations (p < 0.0001), wandering (p < 0.0001), Lewy body dementia (p = 0.05), higher Global Deterioration Scale score (GDS; p < 0.0001), and sleep disorders (p < 0.0001). The multivariate analysis revealed that age (p = 0.048), GDS score (p = 0.01), and the presence of insomnia or hypersomnia (p < 0.0001) independently defined the presence of SS. We established a predictive nomogram for developing SS in patients with dementia, with a predictive capacity of 80.1%. CONCLUSION: In our study, age, a higher score on the GDS, and the presence of insomnia or hypersomnia are differential clinical characteristics of patients with SS. We defined a nomogram that helps predicting the occurrence of SS in patients with dementia.

Three VCP Mutations in Patients with Frontotemporal Dementia. - Wong, Tsz Hang; Pottier, Cyril; Hondius, David C; Meeter, Lieke H H; van Rooij, Jeroen G J; Melhem, Shami; van Minkelen, Rick; van Duijn, Cornelia M; Rozemuller, Annemieke J M; Seelaar, Harro; Rademakers, Rosa; van Swieten, John C (J Alzheimers Dis, 2018)
Valosin-containing protein (VCP) is involved in multiple cellular activities. Mutations in VCP lead to heterogeneous clinical presentations including inclusion body myopathy with Paget's disease of the bone, frontotemporal dementia and amyotrophic lateral sclerosis, even in patients carrying the same mutation. We screened a cohort of 48 patients with familial frontotemporal dementia (FTD) negative for MAPT, GRN, and C9orf72 mutations for other known FTD genes by using whole exome sequencing. In addition, we carried out targeted sequencing of a cohort of 37 patients with frontotemporal lobar degeneration with Transactive response DNA-binding protein 43 (TDP-43) subtype from the Netherlands Brain bank. Two novel (p.Thr262Ser and p.Arg159Ser) and one reported (p.Met158Val) VCP mutations in three patients with a clinical diagnosis of FTD were identified, and were absence in population-match controls. All three patients presented with behavioral changes, with additional semantic deficits in one. No signs of Paget or muscle disease were observed. Pathological examination of the patient with VCP p.Arg159Ser mutation showed numerous TDP-43 immunoreactive (IR) neuronal intranuclear inclusions (NII) and dystrophic neurites (DN), while a lower number of NII and DN were observed in the patient with the VCP p.Thr262Ser mutation. Pathological findings of both patients were consistent with FTLD-TDP subtype D. Furthermore, only rare VCP-IR NII was observed in both cases. Our study expands the clinical heterogeneity of VCP mutations carriers, and indicates that other additional factors, such as genetic modifiers, may determine the clinical phenotype.

A Three-Factor Structure of Cognitive Functioning Among Unimpaired Carriers and Non-Carriers of Autosomal-Dominant Alzheimer's Disease. - Guzmán-Vélez, Edmarie; Jaimes, Sehily; Aguirre-Acevedo, Daniel C; Norton, Daniel J; Papp, Kathryn V; Amariglio, Rebecca; Rentz, Dorene; Baena, Ana; Henao, Eliana; Tirado, Victoria; Munoz, Claudia; Giraldo, Margarita; et al. (J Alzheimers Dis, 2018)
BACKGROUND: There is a need to find cognitive markers that can help identify individuals at risk for Alzheimer's disease (AD), and that can be used to reliably measure cognitive decline. OBJECTIVE: We tested whether a theoretically driven three-factor structure would characterize cognitive functioning in individuals who are genetically-determined to develop AD due to a mutation in Presenilin-1 (PSEN1) gene. We also examined whether these factors could distinguish cognitively unimpaired PSEN1 mutation carriers from age-matched non-carrier family members. METHODS: 1,395 cognitively unimpaired members of a Colombian kindred with the PSEN1 E280A mutation were included in the study. A confirmatory factor analysis examined the fit of the three-factor model comprising episodic memory (MMSE memory recall, CERAD-COL Word list recall, and Constructional praxis recall), executive function (Phonemic fluency and WCST perseverative errors), and psychomotor processing speed (TMT-A and WAIS-III Digit Symbol). RESULTS: The three-factor model provided an excellent fit for all participants (p = 0.24; RMSEA = 0.01). Further, the episodic memory (p = 0.0004, d = 0.25) and executive functioning (p = 0.001, d = 0.18) factors distinguished cognitively unimpaired carriers from non-carriers. The episodic memory factor provided the earliest indication of preclinical cognitive decline at 35 years of age, nine years before individuals' estimated age of clinical onset. CONCLUSIONS: The three theoretically derived cognitive factors provide a reliable measure of cognition and may be useful for the early detection of AD, as well as for measuring disease progression. However, longitudinal studies are needed to confirm that these factors can be used to track the progression of cognitive decline in preclinical AD.

Treatment of Atrial Fibrillation in Patients with Dementia: A Cohort Study from the Swedish Dementia Registry. - Subic, Ana; Cermakova, Pavla; Religa, Dorota; Han, Shuang; von Euler, Mia; Kåreholt, Ingemar; Johnell, Kristina; Fastbom, Johan; Bognandi, Liselia; Winblad, Bengt; Kramberger, Milica G; Eriksdotter, Maria; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Patients with dementia might have higher risk for hemorrhagic complications with anticoagulant therapy prescribed for atrial fibrillation (AF). OBJECTIVE: This study assesses the risks and benefits of warfarin, antiplatelets, and no treatment in patients with dementia and AF. METHODS: Of 49,792 patients registered in the Swedish Dementia Registry 2007-2014, 8,096 (16%) had a previous diagnosis of AF. Cox proportional hazards models were used to calculate the risk for ischemic stroke (IS), nontraumatic intracranial hemorrhage, any-cause hemorrhage, and death. RESULTS: Out of the 8,096 dementia patients with AF, 2,143 (26%) received warfarin treatment, 2,975 (37%) antiplatelet treatment, and 2,978 (37%) had no antithrombotic treatment at the time of dementia diagnosis. Patients on warfarin had fewer IS than those without treatment (5.2% versus 8.7%; p < 0.001) with no differences compared to antiplatelets. In adjusted analyses, warfarin was associated with a lower risk for IS (HR 0.76, CI 0.59-0.98), while antiplatelets were associated with increased risk (HR 1.25, CI 1.01-1.54) compared to no treatment. For any-cause hemorrhage, there was a higher risk with warfarin (HR 1.28, CI 1.03-1.59) compared to antiplatelets. Warfarin and antiplatelets were associated with a lower risk for death compared to no treatment. CONCLUSIONS: Warfarin treatment in Swedish patients with dementia is associated with lower risk of IS and mortality, and a small increase in any-cause hemorrhage. This study supports the use of warfarin in appropriate cases in patients with dementia. The low percentage of patients on warfarin treatment indicates that further gains in stroke prevention are possible.
Keywords: Aged; Aged, 80 and over; Anticoagulants; Atrial Fibrillation; Dementia; Female; Hemorrhage; Humans; Longitudinal Studies; Male; Registries; Risk Factors; Stroke; Survival Analysis; Sweden; Warfarin

Update on Vascular Cognitive Impairment Associated with Subcortical Small-Vessel Disease. - Wallin, Anders; Román, Gustavo C; Esiri, Margaret; Kettunen, Petronella; Svensson, Johan; Paraskevas, George P; Kapaki, Elisabeth (J Alzheimers Dis, 2018)
Subcortical small-vessel disease (SSVD) is a disorder well characterized from the clinical, imaging, and neuropathological viewpoints. SSVD is considered the most prevalent ischemic brain disorder, increasing in frequency with age. Vascular risk factors include hypertension, diabetes, hyperlipidemia, elevated homocysteine, and obstructive sleep apnea. Ischemic white matter lesions are the hallmark of SSVD; other pathological lesions include arteriolosclerosis, dilatation of perivascular spaces, venous collagenosis, cerebral amyloid angiopathy, microbleeds, microinfarcts, lacunes, and large infarcts. The pathogenesis of SSVD is incompletely understood but includes endothelial changes and blood-brain barrier alterations involving metalloproteinases, vascular endothelial growth factors, angiotensin II, mindin/spondin, and the mammalian target of rapamycin pathway. Metabolic and genetic conditions may also play a role but hitherto there are few conclusive studies. Clinical diagnosis of SSVD includes early executive dysfunction manifested by impaired capacity to use complex information, to formulate strategies, and to exercise self-control. In comparison with Alzheimer's disease (AD), patients with SSVD show less pronounced episodic memory deficits. Brain imaging has advanced substantially the diagnostic tools for SSVD. With the exception of cortical microinfarcts, all other lesions are well visualized with MRI. Diagnostic biomarkers that separate AD from SSVD include reduction of cerebrospinal fluid amyloid-β (Aβ)42 and of the ratio Aβ42/Aβ40 often with increased total tau levels. However, better markers of small-vessel function of intracerebral blood vessels are needed. The treatment of SSVD remains unsatisfactory other than control of vascular risk factors. There is an urgent need of finding targets to slow down and potentially halt the progression of this prevalent, but often unrecognized, disorder.
Keywords: Animals; Cerebrovascular Disorders; Dementia; Humans

Usefulness of Dual-Point Amyloid PET Scans in Appropriate Use Criteria: A Multicenter Study. - Segovia, Fermín; Gómez-Río, Manuel; Sánchez-Vañó, Raquel; Górriz, Juan Manuel; Ramírez, Javier; Triviño-Ibáñez, Eva; Carnero-Pardo, Cristóbal; Martínez-Lozano, María Dolores; Sopena-Novales, Pablo (J Alzheimers Dis, 2018)
BACKGROUND: Biomarkers of neurodegeneration play a major role in the diagnosis of Alzheimer's disease (AD). Information on both amyloid-β accumulation, e.g., from amyloid positron emission tomography (PET), and downstream neuronal injury, e.g., from 18F-fluorodeoxyglucose (FDG) PET, would ideally be obtained in a single procedure. OBJECTIVE: On the basis that the parallelism between brain perfusion and glucose metabolism is well documented, the objective of this work is to evaluate whether brain perfusion estimated in a dual-point protocol of 18F-florbetaben (FBB) PET can be a surrogate of FDG PET in appropriate use criteria (AUC) for amyloid PET. METHODS: This study included 47 patients fulfilling international AUC for amyloid PET. FDG PET, early FBB (pFBB) PET (0-10 min post injection), and standard FBB (sFBB) PET (90-110 min post injection) scans were acquired. Results of clinical subjective reports and of quantitative region of interest (ROI)-based analyses were compared between procedures using statistical techniques such as Pearson's correlation coefficients and t-tests. RESULTS: pFBB and FDG visual reports on the 47 patients showed good agreement (k  >  0.74); ROI quantitative analysis indicated that both data modalities are highly correlated; and the t-test analysis does not reject the null hypothesis that data from pFBB and FDG examinations comes from independent random samples from normal distributions with equal means and variances. CONCLUSIONS: A good agreement was found between pFBB and FDG data as obtained by subjective visual and quantitative analyses. Dual-point FBB PET scans could offer complementary information (similar to that from FDG PET and FBB PET) in a single procedure, considering pFBB as a surrogate of FDG.

Utility of Amyloid and FDG-PET in Clinical Practice: Differences Between Secondary and Tertiary Care Memory Units. - Lage, Carmen; Suarez, Andrea Gonzalez; Pozueta, Ana; Riancho, Javier; Kazimierczak, Martha; Bravo, María; Jimenez Bonilla, Julio; de Arcocha Torres, Marıa; Quirce, Remedios; Banzo, Ignacio; Vázquez-Higuera, José Luis; Rabinovici, Gil D; et al. (J Alzheimers Dis, 2018)
The clinical utility of amyloid positron emission tomography (PET) has not been fully established. Our aim was to evaluate the effect of amyloid imaging on clinical decision making in a secondary care unit and compare our results with a previous study in a tertiary center following the same methods. We reviewed retrospectively 151 cognitively impaired patients who underwent amyloid (Pittsburgh compound B [PiB]) PET and were evaluated clinically before and after the scan in a secondary care unit. One hundred and fifty concurrently underwent fluorodeoxyglucose (FDG)-PET. We assessed changes between the pre- and post-PET clinical diagnosis and Alzheimer's disease treatment plan. The association between PiB/FDG results and changes in management was evaluated using χ2 and multivariate logistic regression. Concordance between classification based on scan readings and baseline diagnosis was 66% for PiB and 47% for FDG. The primary diagnosis changed after PET in 17.2% of cases. When examined independently, discordant PiB and discordant FDG were both associated with diagnostic change (p < 0.0001). However, when examined together in a multivariate logistic regression, only discordant PiB remained significant (p = 0.0002). Changes in treatment were associated with concordant PiB (p = 0.009) while FDG had no effect on treatment decisions. Based on our regression model, patients with diagnostic dilemmas, a suspected non-amyloid syndrome, and Clinical Dementia Rating <1 were more likely to benefit from amyloid PET due to a higher likelihood of diagnostic change. We found that changes in diagnosis after PET in our secondary center almost doubled those of our previous analysis of a tertiary unit (9% versus 17.2%). Our results offer some clues about the rational use of amyloid PET in a secondary care memory unit stressing its utility in mild cognitive impairment patients.

Utility of an Alzheimer's Disease Risk-Weighted Polygenic Risk Score for Predicting Rates of Cognitive Decline in Preclinical Alzheimer's Disease: A Prospective Longitudinal Study. - Porter, Tenielle; Burnham, Samantha C; Milicic, Lidija; Savage, Greg; Maruff, Paul; Lim, Yen Ying; Li, Qiao-Xin; Ames, David; Masters, Colin L; Rainey-Smith, Stephanie; Rowe, Christopher C; Salvado, Olivier; et al. (J Alzheimers Dis, 2018)
BACKGROUND: With the exception of APOE, genetic variants associated with increased Alzheimer's disease (AD) risk are characterized by small effect sizes. Polygenic risk scores (PRS) have shown utility in predicting AD risk; however, their utility for predicting decline in cognition at preclinical stages of AD is poorly understood. OBJECTIVE: To validate associations of a 22-variant AD-risk-weighted PRS with AD risk and related biomarkers and to assess its utility to predict cognitive decline. METHODS: The PRS was evaluated with respect to brain amyloid-β (Aβ) burden, cerebrospinal fluid (CSF) Aβ42, total-tau, and phospho-tau, and decline in cognition in 643 (570 cognitively normal (CN), 73 AD) PET-imaged participants from the longitudinal Australian Imaging, Biomarkers and Lifestyle (AIBL) Study of Ageing. Cognition was assessed using three composite measures; global cognition, verbal episodic memory, and a Pre-Alzheimer's Cognitive Composite (PACC). RESULTS: PRS, both with and without APOE, were positively correlated with brain Aβ burden, CSF total-tau, and phospho-tau in CN older adults. Further, in CN biomarker positive (Aβhigh) participants, significant associations were observed with baseline and longitudinal cognition. However, this association was not observed after the removal of APOE. Partitioning the PRS into quartiles revealed that the PRS associations with cognitive decline in Aβhigh CN older adults is due to a saturating effect of APOE genotype. CONCLUSIONS: An AD-risk-weighted PRS is associated with cognitive decline in CN older adults. However, this association is absent when APOE genotype is excluded from the PRS, suggesting that associations with cognitive decline in this model of polygenic risk are driven by APOE genotype alone. Further research is needed to define appropriate PRSs with greater utility for predicting preclinical AD cognitive decline.

Visit-To-Visit Blood Pressure Variability and the Risk of Dementia in Older People. - van Middelaar, Tessa; van Dalen, Jan W; van Gool, Willem A; van den Born, Bert-Jan H; van Vught, Lonneke A; Moll van Charante, Eric P; Richard, Edo (J Alzheimers Dis, 2018)
BACKGROUND: High visit-to-visit variability (VVV) in blood pressure (BP) is associated with cerebrovascular lesions on neuroimaging. OBJECTIVE: Our primary objective was to investigate whether VVV is associated with incident all-cause dementia. As a secondary objective, we studied the association of VVV with cognitive decline and cardiovascular disease (CVD). METHODS: We included community-dwelling people (age 70-78 year) from the 'Prevention of Dementia by Intensive Vascular Care' (preDIVA) trial with three to five 2-yearly BP measurements during 6-8 years follow-up. VVV was defined using coefficient of variation (CV; SD/mean×100). Cognitive decline was assessed using the Mini-Mental State Examination (MMSE). Incident CVD was defined as myocardial infarction or stroke. We used a Cox proportional hazard regression and mixed-effects model adjusted for sociodemographic factors and cardiovascular risk factors. RESULTS: In 2,305 participants (aged 74.2±2.5), mean systolic BP over all available visits was 150.1 mmHg (SD 13.6), yielding a CV of 9.0. After 6.4 years (SD 0.8) follow-up, 110 (4.8%) participants developed dementia and 140 (6.1%) CVD. Higher VVV was not associated with increased risk of dementia (hazard ratio [HR] 1.00 per point CV increase; 95% confidence interval [CI] 0.96-1.05), although the highest quartile of VVV was associated with stronger decline in MMSE (β -0.09, 95% CI -0.17 to -0.01). Higher VVV was associated with incident CVD (HR 1.07; 95% CI 1.04-1.11). CONCLUSION: In our study among older people, high VVV is not associated with incident all-cause dementia. It is associated with decline in MMSE and incident CVD.
Keywords: Aged; Antihypertensive Agents; Blood Pressure; Cardiovascular Diseases; Dementia; Female; Humans; Hypertension; Incidence; Male; Netherlands; Proportional Hazards Models; Risk Factors

Visualization of Focal Thinning of the Ganglion Cell-Inner Plexiform Layer in Patients with Mild Cognitive Impairment and Alzheimer's Disease. - Shao, Yi; Jiang, Hong; Wei, Yantao; Shi, Yingying; Shi, Ce; Wright, Clinton B; Sun, Xiaoyan; Vanner, Elizabeth A; Rodriguez, Anny D; Lam, Byron L; Rundek, Tatjana; Baumel, Barry S; et al. (J Alzheimers Dis, 2018)
BACKGROUND: A detailed analysis of the tomographic thickness of intraretinal layers may provide more information on neurodegeneration in patients with mild cognitive impairment (MCI) and Alzheimer's disease (AD). OBJECTIVE: The goal was to analyze tomographic thickness patterns of intraretinal layers in patients with AD andMCI. METHOD: Forty-nine patients (25 AD and 24 MCI) and 21 cognitively normal (CN) controls were imaged using ultra-high-resolution optical coherence tomography to obtain volumetric data centered on the fovea. The segmented intraretinal layers were retinal nerve fiber layer (RNFL), ganglion cell- inner plexiform layer (GCIPL), inner nuclear layer (INL), outer nuclear layer (ONL), outer plexiform layer (OPL), and retinal photoreceptor (PR), in addition to the total retinal thickness(TRT). RESULTS: The thickness differences were negative (thinning) mainly in TRT, RNFL, and GCIPL in both AD and MCI groups in comparison to CN, while the thickness differences were positive (thickening) mainly in ONL and PR in AD. GCIPL of AD and MCI was thinner in superior, nasal superior, and temporal superior quadrants, compared to CN (p < 0.05). GCIPL of the inner superior, inner nasal superior, inner temporal superior, and outer nasal superior sectors was significantly thinner in AD than CN (p < 0.05). GCIPL of the outer superior, inner temporal superior, outer nasal, and temporal superior sectors was significantly thinner in MCI than CN (p < 0.05). CONCLUSION: Focal thinning of the GCIPL was visualized and quantified by detailed partitions in AD and MCI, which provides specific information about neurodegeneration in MCI and AD.

18F-AV-1451 PET Imaging in Three Patients with Probable Cerebral Amyloid Angiopathy. - Kim, Hee Jin; Cho, Hanna; Werring, David J; Jang, Young Kyoung; Kim, Yeo Jin; Lee, Jin San; Lee, Juyoun; Jun, Soomin; Park, Seongbeom; Ryu, Young Hoon; Choi, Jae Yong; Cho, Young Seok; et al. (J Alzheimers Dis, 2017)
Cerebrovascular deposition of amyloid-β, known as cerebral amyloid angiopathy (CAA), is associated with MRI findings of lobar hemorrhage, cerebral microbleeds, and cortical superficial siderosis. Although pathological studies suggest that tau may co-localize with vascular amyloid, this has not yet been investigated in CAA in vivo. Three patients with probable CAA underwent 11C-Pittsburgh Compound B (PiB) PET or 18F-florbetaben PET to evaluate amyloid burden, and 18F-AV-1451 PET to evaluate paired helical filament tau burden. Regions that had cerebral microbleeds or cortical superficial siderosis largely overlapped with those showing increased 18F-AV-1451. Our preliminary study raised the possibility that lobar cerebral microbleeds, and cortical superficial siderosis, which are characteristic markers of vascular amyloid, may be associated with local production of paired helical filament tau.
Keywords: Aged; Aged, 80 and over; Aniline Compounds; Brain; Carbolines; Cerebral Amyloid Angiopathy; Female; Humans; Image Processing, Computer-Assisted; Male; Positron-Emission Tomography; Thiazoles

Abnormalities of Cortical Neural Synchronization Mechanisms in Subjects with Mild Cognitive Impairment due to Alzheimer's and Parkinson's Diseases: An EEG Study. - Babiloni, Claudio; Del Percio, Claudio; Lizio, Roberta; Noce, Giuseppe; Cordone, Susanna; Lopez, Susanna; Soricelli, Andrea; Ferri, Raffaele; Pascarelli, Maria Teresa; Nobili, Flavio; Arnaldi, Dario; Famá, Francesco; et al. (J Alzheimers Dis, 2017)
The aim of this retrospective and exploratory study was that the cortical sources of resting state eyes-closed electroencephalographic (rsEEG) rhythms might reveal different abnormalities in cortical neural synchronization in groups of patients with mild cognitive impairment due to Alzheimer's disease (ADMCI) and Parkinson's disease (PDMCI) as compared to healthy subjects. Clinical and rsEEG data of 75 ADMCI, 75 PDMCI, and 75 cognitively normal elderly (Nold) subjects were available in an international archive. Age, gender, and education were carefully matched in the three groups. The Mini-Mental State Evaluation (MMSE) was matched between the ADMCI and PDMCI groups. Individual alpha frequency peak (IAF) was used to determine the delta, theta, alpha1, alpha2, and alpha3 frequency band ranges. Fixed beta1, beta2, and gamma bands were also considered. eLORETA estimated the rsEEG cortical sources. Receiver operating characteristic curve (ROC) classified these sources across individuals. Results showed that compared to the Nold group, the posterior alpha2 and alpha3 source activities were more abnormal in the ADMCI than the PDMCI group, while the parietal delta source activities were more abnormal in the PDMCI than the ADMCI group. The parietal delta and alpha sources correlated with MMSE score and correctly classified the Nold and diseased individuals (area under the ROC = 0.77-0.79). In conclusion, the PDMCI and ADMCI patients showed different features of cortical neural synchronization at delta and alpha frequencies underpinning brain arousal and vigilance in the quiet wakefulness. Future prospective cross-validation studies will have to test these rsEEG markers for clinical applications and drug discovery.

Acceleration of Amyloidosis by Inflammation in the Amyloid-Beta Marmoset Monkey Model of Alzheimer's Disease. - Philippens, Ingrid H; Ormel, Paul R; Baarends, Guus; Johansson, Maja; Remarque, Ed J; Doverskog, Magnus (J Alzheimers Dis, 2017)
BACKGROUND: The immune system is increasingly mentioned as a potential target for Alzheimer's disease (AD) treatment. OBJECTIVE: In the present pilot study, the effect of (neuro)inflammation on amyloidopathy was investigated in the marmoset monkey, which has potential as an AD animal model due to its natural cerebral amyloidosis similar to humans. METHODS: Six adult/aged marmosets (Callithrix jacchus) were intracranial injected with amyloid-beta (Aβ) fibrils at three cortical locations in the right hemisphere. Additionally, in half of the monkeys, lipopolysaccharide (LPS) was co-injected with the Aβ fibrils and injected in the other hemisphere without Aβ fibrils. The other three monkeys received phosphate buffered saline instead of LPS, as a control for the inflammatory state. The effect of inflammation on amyloidopathy was also investigated in an additional monkey that suffered from chronic inflammatory wasting syndrome. Mirror histology sections were analyzed to assess amyloidopathy and immune reaction, and peripheral blood for AD biomarker expression. RESULTS: All LPS-injected monkeys showed an early AD immune blood cell expression profile on CD95 and CD45RA. Two out of three monkeys injected with Aβ and LPS and the additional monkey, suffering from chronic inflammation, developed plaques. None of the controls, injected with Aβ only, developed any plaques. CONCLUSION: This study shows the importance of immune modulation on the susceptibility for amyloidosis, a hallmark of AD, which offers new perspectives for disease modifying approaches in AD.

Accuracy of Clinical Diagnosis of Dementia with Lewy Bodies versus Neuropathology. - Skogseth, Ragnhild; Hortobágyi, Tibor; Soennesyn, Hogne; Chwiszczuk, Luiza; Ffytche, Dominic; Rongve, Arvid; Ballard, Clive; Aarsland, Dag (J Alzheimers Dis, 2017)
BACKGROUND: The first consensus criteria for dementia with Lewy bodies (DLB) published in 1996 were revised in 2005, partly because the original clinical criteria had suboptimal sensitivity. Few studies have assessed the accuracy of the 2005 criteria applied prospectively in newly diagnosed patients who have been followed longitudinally. OBJECTIVE: To explore the correlation between clinical and pathological diagnoses in patients with DLB and Parkinson's disease with dementia (PDD). METHODS: From a prospective referral cohort study with enriched recruitment of patients with DLB and PDD, we included the first 56 patients coming to autopsy. Patients had mild dementia at inclusion and were followed annually until death with standardized clinical assessments. Pathological assessment was performed blind to clinical information according to standardized protocols and consensus criteria for DLB. RESULTS: 20 patients received a pathological diagnosis of Lewy body disease; the corresponding clinical diagnoses were probable DLB (n = 11), PDD (n = 5), probable (n = 2) or possible (n = 2) Alzheimer's disease (AD). Of 14 patients with a clinical diagnosis of probable DLB, 11 had DLB/PDD and 3 had AD at pathology. One patient with clinically possible DLB fulfilled criteria for pathological AD. Sensitivity, specificity, positive predictive value, and negative predictive values for probable DLB were 73%, 93%, 79%, and 90%. CONCLUSION: Our findings suggest that the international clinical consensus criteria for DLB perform reasonably well. However, false positive and false negative diagnoses still occur, indicating that the criteria need to be improved, that biomarkers may be needed, and that neuropathological feedback is vital to improve accuracy.

Adherence to Clinical Practice Guidelines during Dementia Work-Up in a Real-World Setting: A Study from the Registry of Dementias of Girona. - Turró-Garriga, Oriol; Calvó-Perxas, Laia; Vilalta-Franch, Joan; Hernández-Ferrándiz, Marta; Flaqué, Margarita; Linares, Marta; Cullell, Marta; Gich, Jordi; Casas, Isabel; Perkal, Héctor; Garre-Olmo, Josep (J Alzheimers Dis, 2017)
BACKGROUND: There are several position statements and clinical practice guidelines (CPG) for diagnosing dementia. OBJECTIVE: Our aims were to evaluate the adherence to CPG among specialists in the 7 memory clinics included in the Registry of Dementias of Girona (ReDeGi), and to compare the results between 2007-2011 and 2012-2015. We also determined the time and number of visits required to achieve a diagnosis, the supplementary tests ordered, and the drugs prescribed according to dementia subtypes. METHODS: Medical charts of a stratified random sample of 475 ReDeGi cases were reviewed. Basic dementia work-up was evaluated using as a reference evidence-based CPG. An Index of Adherence (AI) was calculated using the following items in the medical chart: cognitive symptomatology; functional disability evaluation; physical examination; neurological examination; psychiatric examination; brief cognitive examination; activities of daily living performance examination; blood test; structural neuroimaging (CT-scan or MRI). RESULTS: The mean AI to CPG among specialists was of 8.2 points, and it improved from 7.9 points in 2007-2011 to 8.5 points in 2012-2015 (Cohen's d = 0.46). A lower adherence was detected in the most severe cases. A dementia diagnosis required 3.5 visits, regardless of the subtype of dementia, although milder cases required more time, more visits, and more supplementary tests than severe cases. CONCLUSION: The adherence to CPG in the catchment area of the ReDeGi is high, and an epidemiological surveillance system such as the ReDeGi may help in improving it. Dementia guidelines should establish procedures adapted to clinical practice, with simplified recommendations for most severe cases.

Alcohol Intake and Cognitively Healthy Longevity in Community-Dwelling Adults: The Rancho Bernardo Study. - Richard, Erin L; Kritz-Silverstein, Donna; Laughlin, Gail A; Fung, Teresa T; Barrett-Connor, Elizabeth; McEvoy, Linda K (J Alzheimers Dis, 2017)
To better understand the association of alcohol intake with cognitively healthy longevity (CHL), we explored the association between amount and frequency of alcohol intake and CHL among 1,344 older community-dwelling adults. Alcohol intake was assessed by questionnaire in 1984-1987. Cognitive function was assessed in approximate four-year intervals between 1988 and 2009. Multinomial logistic regression, adjusting for multiple lifestyle and health factors, was used to examine the association between alcohol consumption and CHL (living to age 85 without cognitive impairment), survival to age 85 with cognitive impairment (MMSE score >1.5 standard deviations below expectation for age, sex, and education), or death before age 85. Most participants (88%) reported some current alcohol intake; 49% reported a moderate amount of alcohol intake, and 48% reported drinking near-daily. Relative to nondrinkers, moderate and heavy drinkers (up to 3 drinks/day for women and for men 65 years and older, up to 4 drinks/day for men under 65 years) had significantly higher adjusted odds of survival to age 85 without cognitive impairment (p's < 0.05). Near-daily drinkers had 2-3 fold higher adjusted odds of CHL versus living to at least age 85 with cognitive impairment (odds ratio (OR) = 2.06; 95% confidence interval (CI): 1.21, 3.49) or death before 85 (OR = 3.24; 95% CI: 1.92, 5.46). Although excessive drinking has negative health consequences, these results suggest that regular, moderate drinking may play a role in cognitively healthy longevity.

Algoplus® Scale in Older Patients with Dementia: A Reliable Real-World Pain Assessment Tool. - Monacelli, Fiammetta; Signori, Alessio; Roffredo, Laura; Pace, Katiuscia; Nencioni, Alessio; Pickering, Gisele; Nicolas, Macian; Odetti, Patrizio (J Alzheimers Dis, 2017)
Pain is still a neglected clinical issue in elderly people with dementia and/or communicative disorders, with an unacceptable higher rate of under diagnosis and under treatment. Cognitive deficit and emotional and psychological disturbances entangle pain symptoms, affecting patient self-report. So far, observational pain tools do not have fully adequate clinimetric properties and quality requirements for easy-to-use daily rating. Older patients with dementia represent a clinical challenge. The assessment of pain is important for improving clinical outcomes, such as functional status, frailty trajectories, comorbidity, and quality of life. The PAINAID scale appears to be the most accurate pain tool in people with dementia along with the Algoplus® scale, a recently developed tool to rapidly assess acute pain in hospitals settings. The present study aimed to assess the clinimetric properties of the Algoplus®, as compared to PAINAID, for detecting acute pain in a real-world cohort of hospitalized older patients with dementia.

Alterations of Clock Gene RNA Expression in Brain Regions of a Triple Transgenic Model of Alzheimer's Disease. - Bellanti, Francesco; Iannelli, Giuseppina; Blonda, Maria; Tamborra, Rosanna; Villani, Rosanna; Romano, Adele; Calcagnini, Silvio; Mazzoccoli, Gianluigi; Vinciguerra, Manlio; Gaetani, Silvana; Giudetti, Anna Maria; Vendemiale, Gianluigi; et al. (J Alzheimers Dis, 2017)
A disruption to circadian rhythmicity and the sleep/wake cycle constitutes a major feature of Alzheimer's disease (AD). The maintenance of circadian rhythmicity is regulated by endogenous clock genes and a number of external Zeitgebers, including light. This study investigated the light induced changes in the expression of clock genes in a triple transgenic model of AD (3×Tg-AD) and their wild type littermates (Non-Tg). Changes in gene expression were evaluated in four brain areas¾suprachiasmatic nucleus (SCN), hippocampus, frontal cortex and brainstem¾of 6- and 18-month-old Non-Tg and 3×Tg-AD mice after 12 h exposure to light or darkness. Light exposure exerted significant effects on clock gene expression in the SCN, the site of the major circadian pacemaker. These patterns of expression were disrupted in 3×Tg-AD and in 18-month-old compared with 6-month-old Non-Tg mice. In other brain areas, age rather than genotype affected gene expression; the effect of genotype was observed on hippocampal Sirt1 expression, while it modified the expression of genes regulating the negative feedback loop as well as Rorα, Csnk1ɛ and Sirt1 in the brainstem. In conclusion, during the early development of AD, there is a disruption to the normal expression of genes regulating circadian function after exposure to light, particularly in the SCN but also in extra-hypothalamic brain areas supporting circadian regulation, suggesting a severe impairment of functioning of the clock gene pathway. Even though this study did not demonstrate a direct association between these alterations in clock gene expression among brain areas with the cognitive impairments and chrono-disruption that characterize the early onset of AD, our novel results encourage further investigation aimed at testing this hypothesis.

Altered Gut Microbiome Composition and Tryptic Activity of the 5xFAD Alzheimer's Mouse Model. - Brandscheid, Carolin; Schuck, Florian; Reinhardt, Sven; Schäfer, Karl-Herbert; Pietrzik, Claus U; Grimm, Marcus; Hartmann, Tobias; Schwiertz, Andreas; Endres, Kristina (J Alzheimers Dis, 2017)
The regulation of physiological gut functions such as peristalsis or secretion of digestive enzymes by the central nervous system via the Nervus vagus is well known. Recent investigations highlight that pathological conditions of neurological or psychiatric disorders might directly interfere with the autonomous neuronal network of the gut - the enteric nervous system, or even derive from there. By using a murine Alzheimer's disease model, we investigated a potential influence of disease-associated changes on gastrointestinal properties. 5xFAD mice at three different ages were compared to wild type littermates in regard to metabolic parameters and enzymes of the gut by fluorimetric enzyme assay and western blotting. Overexpression of human amyloid-β protein precursor (AβPP) within the gut was assessed by qPCR and IHC; fecal microbiome analysis was conducted by 16SrRNA quantitation of selected phyla and species. While general composition of fecal samples, locomotion, and food consumption of male 5xFAD animals were not changed, we observed a reduced body weight occurring at early pathological stages. Human AβPP was not only expressed within the brain of these mice but also in gut tissue. Analysis of fecal proteins revealed a reduced trypsin amount in the 5xFAD model mice as compared to the wild type. In addition, we observed changes in fecal microbiota composition along with age. We therefore suggest that the presence of the mutated transgenes (AβPP and PS1), which are per se the basis for the genetic form of Alzheimer's disease in humans, directly interferes with gut function as shown here for the disease model mice.

Altered Sphingolipid Balance in Capillary Cerebral Amyloid Angiopathy. - de Wit, Nienke M; Snkhchyan, Hripsime; den Hoedt, Sandra; Wattimena, Darcos; de Vos, Rob; Mulder, Monique T; Walter, Jochen; Martinez-Martinez, Pilar; Hoozemans, Jeroen J; Rozemuller, Annemieke J; De Vries, Helga E (J Alzheimers Dis, 2017)
BACKGROUND: The majority of patients with Alzheimer's disease (AD) exhibit amyloid-β (Aβ) deposits at the brain vasculature, a process referred to as cerebral amyloid angiopathy (CAA). In over 51% of AD cases, Aβ also accumulates in cortical capillaries, which is termed capillary CAA (capCAA). It has been postulated that the presence of capCAA in AD is a specific subtype of AD, although underlying mechanisms are not yet fully understood. Sphingolipids (SLs) are implicated in neurodegenerative disorders, including AD. However, to date it remains unknown whether alterations in the SL pathway are involved in capCAA pathogenesis and if these differ from AD. OBJECTIVE: To determine whether AD cases with capCAA have an altered SL profile compared to AD cases without capCAA. METHODS: Immunohistochemistry was performed to assess the expression and localization of ceramide, acid sphingomyelinase (ASM), and sphingosine-1-phosphate receptors (S1P1, S1P3). In addition, we determined the concentrations of S1P as well as different chain-lengths of ceramides using HPLC-MS/MS. RESULTS: Immunohistochemical analysis revealed an altered expression of ceramide, ASM, and S1P receptors by reactive astrocytes and microglial cells specifically associated with capCAA. Moreover, a shift in the balance of ceramides with different chain-lengths and S1P content is observed in capCAA. CONCLUSION: Here we provide evidence of a deregulated SL balance in capCAA. The increased levels of ASM and ceramide in activated glia cells suggest that the SL pathway is involved in the neuroinflammatory response in capCAA pathogenesis. Future research is needed to elucidate the role of S1P in capCAA.

Alzheimer's Disease: Characterization of the Brain Sites of the Initial Tau Cytoskeletal Pathology Will Improve the Success of Novel Immunological Anti-Tau Treatment Approaches. - Rüb, Udo; Stratmann, Katharina; Heinsen, Helmut; Seidel, Kay; Bouzrou, Mohamed; Korf, Horst-Werner (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) represents the most frequent neurodegenerative disease of the human brain worldwide. Currently practiced treatment strategies for AD only include some less effective symptomatic therapeutic interventions, which unable to counteract the disease course of AD. New therapeutic attempts aimed to prevent, reduce, or remove the extracellular depositions of the amyloid-β protein did not elicit beneficial effects on cognitive deficits or functional decline of AD. In view of the failure of these amyloid-β-based therapeutic trials and the close correlation between the brain pathology of the cytoskeletal tau protein and clinical AD symptoms, therapeutic attention has since shifted to the tau cytoskeletal protein as a novel drug target. The abnormal hyperphosphorylation and intraneuronal aggregation of this protein are early events in the evolution of the AD-related neurofibrillary pathology, and the brain spread of the AD-related tau aggregation pathology may possibly follow a corruptive protein templating and seeding-like mechanism according to the prion hypothesis. Accordingly, immunotherapeutic targeting of the tau aggregation pathology during the very early pre-tangle phase is currently considered to represent an effective and promising therapeutic approach for AD. Recent studies have shown that the initial immunoreactive tau aggregation pathology already prevails in several subcortical regions in the absence of any cytoskeletal changes in the cerebral cortex. Thus, it may be hypothesized that the subcortical brain regions represent the "port of entry" for the pathogenetic agent from which the disease ascends anterogradely as an "interconnectivity pathology".
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Humans; Immunotherapy; tau Proteins

Alzheimer's Disease Severity is Not Significantly Associated with Short Sleep: Survey by Actigraphy on 208 Mild and Moderate Alzheimer's Disease Patients. - Leger, Damien; Elbaz, Maxime; Dubois, Alexandre; Rio, Stéphane; Mezghiche, Hocine; Carita, Paulo; Stemmelin, Jeanne; Strauss, Melanie (J Alzheimers Dis, 2017)
BACKGROUND: In epidemiological surveys, cognitive decline has been found to be associated with both short and long sleep duration. OBJECTIVE: Our goal was to objectively determine how total sleep time (TST) at night was associated or not with apathy or severity scores in patients with Alzheimer 's disease (AD). METHODS: During an observational first step of a clinical trial, sleep was assessed in institutionalized patients with mild or moderate AD using actigraphy (MW8, Camtech, Cambridge, UK) for 14 consecutive 24-hour periods. Sleep parameters analyzed were: TST, time in bed (TIB), wake after sleep onset (WASO), sleep efficiency (SE) defined by the ratio TST/TIB, in percentage), the number and length of awakenings, the night fragmentation index, the interdaily stability, and intradaily variability indexes. Statistical association analyses were tested between these values and AD apathy and severity scores. RESULTS: 208 individuals coming from 82 centers worldwide (France, Germany, Spain, Italy, Portugal, Poland, United States, Canada, and Australia) and≥50 years old participated. Their average TST was 7 hours and 35 minutes and the average WASO 58 minutes. TST and SE were significantly higher in patients with apathy and the number of awakenings was significantly lower. TST was also positively associated with functional disability (ADCS-ADL scores), but it was not found significantly greater in patients with a moderate AD severity compared to the mild. CONCLUSION: Despite several and long awakenings, TST was not shorter in patients with AD. TST was even significantly increased with disability and apathy.

Alzheimer's Disease-Related Polymorphisms in Shunt-Responsive Idiopathic Normal Pressure Hydrocephalus. - Huovinen, Joel; Helisalmi, Seppo; Paananen, Jussi; Laiterä, Tiina; Kojoukhova, Maria; Sutela, Anna; Vanninen, Ritva; Laitinen, Marjo; Rauramaa, Tuomas; Koivisto, Anne M; Remes, Anne M; Soininen, Hilkka; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Idiopathic normal pressure hydrocephalus (iNPH) is a late onset, surgically treated progressive brain disease caused by impaired cerebrospinal fluid dynamics and subsequent ventriculomegaly. Comorbid Alzheimer's disease (AD) seems to be frequent in iNPH. OBJECTIVE: We aim to evaluate the role of AD-related polymorphisms in iNPH. METHODS: Overall 188 shunt-operated iNPH patients and 688 controls without diagnosed neurodegenerative disease were included into analysis. Twenty-three single-nucleotide polymorphisms (SNPs FRMD4A [rs7081208_A, rs2446581_A, rs17314229_T], CR1, BIN, CD2AP, CLU, MS4A6A, MS4A4E, PICALM, ABCA7, CD33, INPP5D, HLA_DRB5, EPHA1, PTK2B, CELF1, SORL1, FERMT2, SLC24A, DSG2, CASS4, and NME8) adjusted to APOE were analyzed between groups by using binary logistic regression analysis. Neuroradiological characteristics and AD-related changes in the right frontal cortical brain biopsies were available for further analysis. RESULTS: Logistic regression analysis adjusted to age, gender, and other SNPs indicated allelic variation of NME8 between iNPH patients and non-demented controls (p = 0.014). The allelic variation of NME8 was not related to the neuropathological changes in the brain biopsies of iNPH patients. However, periventricular white matter changes (p = 0.017) were more frequent in the iNPH patients with the AA-genotype, an identified risk factor of AD. CONCLUSIONS: Our findings increase the evidence that iNPH is characterized by genetic and pathophysiological mechanisms independent from AD. Considering that NME8 plays a role in the ciliary function and displays SNP-related diversity in white matter changes, the mechanisms of NME8 in iNPH and other neurodegenerative processes are worth further study.

Amygdala α-Synuclein Pathology in the Population-Based Vantaa 85+ Study. - Raunio, Anna; Myllykangas, Liisa; Kero, Mia; Polvikoski, Tuomo; Paetau, Anders; Oinas, Minna (J Alzheimers Dis, 2017)
We investigated the frequency of Lewy-related pathology (LRP) in the amygdala among the population-based Vantaa 85+ study. Data of amygdala samples (N = 304) immunostained with two α-synuclein antibodies (clone 42 and clone 5G4) was compared with the previously analyzed LRP and AD pathologies from other brain regions. The amygdala LRP was present in one third (33%) of subjects. Only 5% of pure AD subjects, but 85% of pure DLB subjects had LRP in the amygdala. The amygdala LRP was associated with dementia; however, the association was dependent on LRP on other brain regions, and thus was not an independent risk factor. The amygdala-predominant category was a rare (4%) and heterogeneous group.

Amyloid-Beta and Phosphorylated Tau Accumulations Cause Abnormalities at Synapses of Alzheimer's disease Neurons. - Rajmohan, Ravi; Reddy, P Hemachandra (J Alzheimers Dis, 2017)
Amyloid-beta (Aβ) and hyperphosphorylated tau are hallmark lesions of Alzheimer's disease (AD). However, the loss of synapses and dysfunctions of neurotransmission are more directly tied to disease severity. The role of these lesions in the pathoetiological progression of the disease remains contested. Biochemical, cellular, molecular, and pathological studies provided several lines of evidence and improved our understanding of how Aβ and hyperphosphorylated tau accumulation may directly harm synapses and alter neurotransmission. In vitro evidence suggests that Aβ and hyperphosphorylated tau have both direct and indirect cytotoxic effects that affect neurotransmission, axonal transport, signaling cascades, organelle function, and immune response in ways that lead to synaptic loss and dysfunctions in neurotransmitter release. Observations in preclinical models and autopsy studies support these findings, suggesting that while the pathoetiology of positive lesions remains elusive, their removal may reduce disease severity and progression. The purpose of this article is to highlight the need for further investigation of the role of tau in disease progression and its interactions with Aβ and neurotransmitters alike.

Analytical Strategy to Prioritize Alzheimer's Disease Candidate Genes in Gene Regulatory Networks Using Public Expression Data. - Kawalia, Shweta Bagewadi; Raschka, Tamara; Naz, Mufassra; de Matos Simoes, Ricardo; Senger, Philipp; Hofmann-Apitius, Martin (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) progressively destroys cognitive abilities in the aging population with tremendous effects on memory. Despite recent progress in understanding the underlying mechanisms, high drug attrition rates have put a question mark behind our knowledge about its etiology. Re-evaluation of past studies could help us to elucidate molecular-level details of this disease. Several methods to infer such networks exist, but most of them do not elaborate on context specificity and completeness of the generated networks, missing out on lesser-known candidates. In this study, we present a novel strategy that corroborates common mechanistic patterns across large scale AD gene expression studies and further prioritizes potential biomarker candidates. To infer gene regulatory networks (GRNs), we applied an optimized version of the BC3Net algorithm, named BC3Net10, capable of deriving robust and coherent patterns. In principle, this approach initially leverages the power of literature knowledge to extract AD specific genes for generating viable networks. Our findings suggest that AD GRNs show significant enrichment for key signaling mechanisms involved in neurotransmission. Among the prioritized genes, well-known AD genes were prominent in synaptic transmission, implicated in cognitive deficits. Moreover, less intensive studied AD candidates (STX2, HLA-F, HLA-C, RAB11FIP4, ARAP3, AP2A2, ATP2B4, ITPR2, and ATP2A3) are also involved in neurotransmission, providing new insights into the underlying mechanism. To our knowledge, this is the first study to generate knowledge-instructed GRNs that demonstrates an effective way of combining literature-based knowledge and data-driven analysis to identify lesser known candidates embedded in stable and robust functional patterns across disparate datasets.

Anomalous White Matter Structure and the Effect of Age in Down Syndrome Patients. - Fenoll, Raquel; Pujol, Jesus; Esteba-Castillo, Susanna; de Sola, Susana; Ribas-Vidal, Núria; García-Alba, Javier; Sánchez-Benavides, Gonzalo; Martínez-Vilavella, Gerard; Deus, Joan; Dierssen, Mara; Novell-Alsina, Ramón; de la Torre, Rafael (J Alzheimers Dis, 2017)
BACKGROUND: Neural tissue alterations in Down syndrome are fully expressed at relatively late developmental stages. In addition, there is an early presence of neurodegenerative changes in the late life stages. OBJECTIVE: The aims of this study were both to characterize white matter abnormalities in the brain of adult Down syndrome patients using diffusion tensor imaging (DTI) and to investigate whether degenerative alterations in white matter structure are detectable before dementia is clinically evident. METHODS: Forty-five adult non-demented Down syndrome patients showing a wide age range (18-52 years) and a matched 45-subject control group were assessed. DTI fractional anisotropy (FA) brain maps were generated and selected cognitive tests were administered. RESULTS: Compared with healthy controls, non-demented Down syndrome patients showed lower DTI FA in white matter involving the major pathways, but with more severe alterations in the frontal-subcortical circuits. White matter FA decreased with age at a similar rate in both DS and control groups. CONCLUSIONS: Our results contribute to characterizing the expression of white matter structural alterations in adult Down syndrome. However, an accelerated aging effect was not demonstrated, which may suggest that the FA measurements used are not sufficiently sensitive or, alternatively, age-related white matter neurodegeneration is not obvious prior to overt clinical dementia.

Antibodies to Signaling Molecules and Receptors in Alzheimer's Disease are Associated with Psychomotor Slowing, Depression, and Poor Visuospatial Function. - Giil, Lasse M; Vedeler, Christian A; Kristoffersen, Einar K; Nordrehaug, Jan Erik; Heidecke, Harald; Dechend, Ralf; Schulze-Forster, Kai; Muller, Dominik N; von Goetze, Victoria S; Cabral-Marques, Otavio; Riemekasten, Gabriela; Vogelsang, Petra; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) is associated with several antibodies as well as signaling molecules and receptors. These may be detrimental in the presence of a disrupted blood-brain barrier (BBB). OBJECTIVE: To investigate whether the levels of antibodies toward 33 signaling molecules involved in neurotransmitter, vascular, and immune functions were associated with AD and, within the AD group; cognitive function and mood. METHODS: Antibodies in sera from patients with mild AD [(n = 91) defined as a Mini-Mental State Examination ≥ 20 or a Clinical Dementia Rating Scale≤1] and healthy controls (n = 102) were measured with enzyme-linked immunosorbent assays. Levels in AD and controls were compared by Mann-Whitney test. In the AD group, associations between antibodies and psychometric test scores were analyzed by robust regression. The false discovery threshold was set to 0.05. RESULTS: Antibodies to serotonin receptors [5-HT2AR (effect size (r) = 0.21, p = 0.004), 5-HT2CR (r = 0.25, p = 0.0005) and 5-HT7R (r = 0.21, p = 0.003)], vascular endothelial growth factor receptor 1 [VEGFR1 (r = 0.29, p < 0.001)] and immune-receptors (Stabilin-1 (r = 0.23, p = 0.001) and C5aR1 (r = 0.21, p = 0.004) were higher in AD. Psychomotor speed was associated with D1R-abs (β 0.49, p < 0.001), depression with ETAR-abs (β 0.31, p < 0.001), and visuospatial function with 5-HT1AR-abs (β 0.27, p = 0.004) despite similar antibody levels compared to controls. CONCLUSIONS: Antibody levels to VEGFR1, serotonergic receptors, and receptors in the immune system were increased in AD. Antibodies at similar levels as in controls were associated cognitive dysfunction and depression in AD.

Antihypertensive Treatment is associated with MRI-Derived Markers of Neurodegeneration and Impaired Cognition: A Propensity-Weighted Cohort Study. - Edwards, Jodi D; Ramirez, Joel; Callahan, Brandy L; Tobe, Sheldon W; Oh, Paul; Berezuk, Courtney; Lanctôt, Krista; Swardfager, Walter; Nestor, Sean; Kiss, Alexander; Strother, Stephen; Black, Sandra E (J Alzheimers Dis, 2017)
BACKGROUND: Hypertension is an important risk factor for Alzheimer's disease (AD) and cerebral small vessel disease. Angiotensin converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) are common anti-hypertensive treatments, but have differential effects on cortical amyloid. OBJECTIVE: The objective of this study was to evaluate associations between anti-hypertensive treatment, brain volume, and cognition, using a propensity-weighted analysis to account for confounding by indication. METHODS: We identified a cohort of normal elderly adults and individuals with mild cognitive impairment (MCI) or AD (N = 886; mean age = 75.0) from the Alzheimer's Disease Neuroimaging Initiative. Primary outcomes were brain parenchymal fraction, total hippocampal volume, and white matter hyperintensity (WMH) volume. Secondary outcomes were standardized scores on neuropsychological tests. Propensity-weighted adjusted multivariate linear regression was used to estimate associations between anti-hypertensive treatment class and MRI volumes and cognition. RESULTS: Individuals treated with ARBs showed larger hippocampal volumes (R2 = 0.83, p = 0.05) and brain parenchymal fraction (R2 = 0.83, p = 0.01) than those treated with ACEIs. When stratified by diagnosis, this effect remained only in normal elderly adults and MCI patients, and a significant association between ARBs and lower WMH volume (R2 = 0.83, p = 0.03) emerged for AD patients only. ARBs were also associated with significantly better performance on tests of episodic and verbal memory, language, and executive function (all p < 0.05). CONCLUSIONS: Findings are consistent with evidence for a neuroprotective effect of treatment with ARBs for brain structure and cognition. This study has potential implications for the treatment of hypertension, particularly in elderly adults at risk of cognitive decline and AD.

APOE ε4 Modulation of Training Outcomes in Several Cognitive Domains in a Sample of Cognitively Intact Older Adults. - López-Higes, Ramón; Rodríguez-Rojo, Inmaculada C; Prados, José M; Montejo, Pedro; Del-Río, David; Delgado-Losada, María Luisa; Montenegro, Mercedes; López-Sanz, David; Barabash, Ana (J Alzheimers Dis, 2017)
BACKGROUND: Most research points to the ɛ4 allele of the apolipoprotein E (APOE) gene as the most recognizable genetic risk factor associated with Alzheimer's disease pathogenesis. It has been also suggested that the APOEɛ4 allele has a negative influence on cognitive functioning, which begins long before cognitive impairment becomes manifest. However, still, little is known about the APOEɛ4 interaction with cognitive intervention programs. OBJECTIVE: The main goal of this study was to explore whether there was a differential APOE genotype modulation effect after cognitive training in different domains, such as language comprehension, executive functions, and memory. Contrary to other studies, hippocampal volume was controlled for. METHODS: Fifty older adults (65+ years; 30 women and 20 men) participated in a multi-domain cognitive training that involved 30 sessions taking place over 12 weeks. Half of the participants were APOEɛ4 carriers. The control group was matched in age, gender, normalized hippocampal volume, cognitive reserve, Mini-Mental State Examination score, and Geriatric Depression Scale-Short Version. RESULTS: The study revealed that there were consistent treatment benefits in complex sentence comprehension (noncanonical sentences and sentences with two propositions), a domain that was not directly trained, but only in the A POEɛ4 noncarrier group. CONCLUSION: Genetic profile modulates training outcomes in sentence comprehension.

APOEɛ4 Genotype, Amyloid, and Clinical Disease Progression in Cognitively Normal Older Adults. - Hollands, Simone; Lim, Yen Ying; Laws, Simon M; Villemagne, Victor L; Pietrzak, Robert H; Harrington, Karra; Porter, Tenielle; Snyder, Peter; Ames, David; Fowler, Christopher; Rainey-Smith, Stephanie R; Martins, Ralph N; et al. (J Alzheimers Dis, 2017)
BACKGROUND: In cognitively normal (CN) older adults, carriage of the apolipoprotein E (APOE) ɛ4 allele is associated with increased risk for dementia of the Alzheimer type (AD-dementia). It is unclear whether this occurs solely through APOEɛ4 increasing amyloid-β (Aβ) accumulation or through processes independent of Aβ. OBJECTIVE: To determine the extent and nature to which APOEɛ4 increases risk for clinical disease progression in CN older adults. METHODS: Data from the total (n = 765) and Aβ-imaged (n = 423) CN cohort in the Australian Imaging, Biomarker and Lifestyle (AIBL) Study of Ageing was analyzed using Cox proportional hazard models to estimate ɛ4 risk for clinical disease progression over a 72-month follow-up. RESULTS: With Aβ status unknown and risk from demographic characteristics controlled, ɛ4 carriage increased risk for clinical disease progression over 72 months by 2.66 times compared to risk of non-ɛ4 carriage. Re-analysis with Aβ status included showed that abnormally high Aβ increased risk for clinical disease progression over 72 months by 2.11 times compared to risk of low Aβ. However, with Aβ level known, ɛ4 carriage was no longer predictive of clinical disease progression. CONCLUSION: In CN older adults, the risk of ɛ4 for clinical disease progression occurs through the effect of ɛ4 increasing Aβ levels.

Apolipoprotein E4 Elicits Lysosomal Cathepsin D Release, Decreased Thioredoxin-1 Levels, and Apoptosis. - Persson, Torbjörn; Lattanzio, Francesca; Calvo-Garrido, Javier; Rimondini, Roberto; Rubio-Rodrigo, Marta; Sundström, Erik; Maioli, Silvia; Sandebring-Matton, Anna; Cedazo-Minguez, Angel (J Alzheimers Dis, 2017)
The major genetic risk factor for Alzheimer's disease (AD), apolipoprotein E4 (ApoE4), has been suggested to have detrimental effects on neurons, including direct toxicity via apoptosis. Thioredoxin-1 (Trx1) is an endogenous antioxidant protein important for redox regulation and participates in the regulation of apoptosis through the inhibition of apoptosis signal-regulating kinase-1 (Ask-1). In this study, we have investigated the effects of ApoE on Trx1 in the brain. Our results showed that the protein levels of Trx1 were reduced in the hippocampus of ApoE4 targeted replacement (TR) mice compared to ApoE3 TR mice. The reduction was also seen in vitro after treatment of both human primary cortical neurons and neuroblastoma cells with human recombinant ApoE4 (rApoE4). Furthermore, ApoE4 caused a disruption of lysosomal integrity and a shift in the localization of Cathepsin D, an enzyme known to degrade Trx1. ApoE4 treatment induced in addition apoptosis through translocation of Death-domain associated protein-6 (Daxx) from the nucleus to the cytosol, suggesting an activation of the Ask-1 pathway. This toxicity was prevented by overexpression of Trx1 and other endogenous Ask-1 inhibitors. Our data suggests that down-regulation of Trx1 is involved in the toxicity caused by ApoE4. An activated ASK-1 pathway might indeed make cells more vulnerable to other insults such as amyloid-β, which could partially explain the mechanism behind the strongest genetic risk factor for AD.

APP Mutations in Cerebral Amyloid Angiopathy with or without Cortical Calcifications: Report of Three Families and a Literature Review. - Sellal, François; Wallon, David; Martinez-Almoyna, Laurent; Marelli, Cecilia; Dhar, Abhinav; Oesterlé, Héléne; Rovelet-Lecrux, Anne; Rousseau, Stéphane; Kourkoulis, Christina E; Rosand, Jon; DiPucchio, Zora Y; Frosch, Matthew; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Specific APP mutations cause cerebral amyloid angiopathy (CAA) with or without Alzheimer's disease (AD). OBJECTIVE: We aimed at reporting APP mutations associated with CAA, describe the clinical, cerebrospinal fluid AD biomarkers, and neuroimaging features, and compare them with the data from the literature. METHODS: We performed a retrospective study in two French genetics laboratories by gathering all clinical and neuroimaging data from patients referred for a genetic diagnosis of CAA with an age of onset before 66 years and fulfilling the other Boston revised criteria. We studied the segregation of mutations in families and performed a comprehensive literature review of all cases reported with the same APP mutation. RESULTS: We screened APP in 61 unrelated French patients. Three mutations, located in the Aβ coding region, were detected in five patients from three families: p.Ala692Gly (Flemish), p.Glu693Lys (Italian), and p.Asp694Asn (Iowa). Patients exhibited CAA and progressive cognitive impairment associated with cortical calcifications in the Iowa and Italian mutation carriers, but not the patient carrying the Flemish mutation. CONCLUSIONS: This is the first evidence of cortical calcification in patients with an APP mutation other than the Iowa mutation. We discuss the radiological, cerebrospinal fluid, and clinical phenotype of patients carrying these mutations in the literature.

An Arabic Version of the Cognitive Subscale of the Alzheimer's Disease Assessment Scale (ADAS-Cog): Reliability, Validity, and Normative Data. - Ben Jemaa, Sonia; Attia Romdhane, Neila; Bahri-Mrabet, Amel; Jendli, Adel; Le Gall, Didier; Bellaj, Tarek (J Alzheimers Dis, 2017)
The Alzheimer's Disease Assessment Scale's cognitive subscale (ADAS-Cog) is the most widely used instrument for screening cognitive dysfunction in Alzheimer's disease. The aim of the present study was to develop an Arabic version of this scale (A-ADAS-Cog), examine its psychometric properties (reliability and validity), and provide normative data. The A-ADAS-Cog), an Arabic version of the Mini-Mental State Examination (A-MMSE), and a Standardized Clinical Dementia Rating Scale (CDR) were administered to three Tunisian groups: 124 normal controls (NC), 33 patients with non-Alzheimer dementia (N-AD), and 25 patients with Alzheimer's disease (AD). The A-ADAS-Cog scores were significantly affected by age and education. A correction table was constructed to control these effects. The results showed that the A-ADAS-Cog has good internal consistency and reliability (α= 0.82 for AD). The test-retest reliability of the A-ADAS-Cog was stable over time (r = 0.97). An evaluation of the construct validity of the A-ADAS-Cog using principal component analysis led to a solution with three factors (memory, language and praxis), which explained 72% of the variance. The concurrent validity of the A-ADAS-Cog was established using the A-MMSE score (r = -0.86), CDR Sum of Boxes score (CDR-SB; r = 0.87), and global CDR score (CDR-Global; r = 0.74). Finally, the A-ADAS-Cog has an excellent discriminating power in the diagnosis of AD (ROC area = 0.92). A cut-off score of 10 (sensitivity = 84% and specificity = 91%) is indicated for the screening of the AD. Overall, the results indicated that the A-ADAS-Cog is psychometrically reliable and valid and provides promising results for screening of dementia in Arabic speaking patients.

Association between Cholesterol Exposure and Neuropathological Findings: The ACT Study. - Bettcher, Brianne M; Ard, M Colin; Reed, Bruce R; Benitez, Andreana; Simmons, Amanda; Larson, Eric B; Sonnen, Josh A; Montine, Thomas J; Li, Ge; Keene, C Dirk; Crane, Paul K; Mungas, Dan (J Alzheimers Dis, 2017)
We characterized the relationship between late life cholesterol exposure and neuropathological outcomes in a community-based, older adult cohort. Adult Changes in Thought (ACT) is a cohort study that enrolls consenting, randomly selected, non-demented people aged ≥65 from a healthcare delivery system. We used late life HDL and total cholesterol lab values from Group Health computerized records, and calculated HDL and non-HDL levels. We evaluated neuropathological outcomes of Alzheimer's disease, cerebral amyloid angiopathy, vascular brain injury, and Lewy body disease. Using linear mixed models with age and antilipemic medication as predictors, we obtained predicted cholesterol values at age 70 and 10 years prior to death for individuals with available cholesterol data in 10-year exposure windows. We used logistic regression to determine whether predicted late life cholesterol levels were associated with neuropathological outcomes controlling for age at death, APOE genotype, sex, and their interactions with cholesterol levels. 525 decedents came to autopsy by 08/2014. Of these, plasma cholesterol concentration was available for 318 (age 70, model 1) and 396 (10 years prior to death, model 2) participants. We did not find associations between late life cholesterol and Alzheimer's disease neuropathological changes, and there were no associations between cholesterol levels and amyloid angiopathy or vascular brain injury. We observed an association between predicted non-HDL cholesterol at age 70 and Lewy body disease. Our study suggests an association between late life non-HDL cholesterol exposure and Lewy body disease. We did not observe associations between late life cholesterol levels and Braak stage or CERAD score.

Association between Cognitive Status before Surgery and Outcomes in Elderly Patients with Hip Fracture in a Dedicated Orthogeriatric Care Pathway. - Zerah, Lorene; Cohen-Bittan, Judith; Raux, Mathieu; Meziere, Anthony; Tourette, Cendrine; Neri, Christian; Verny, Marc; Riou, Bruno; Khiami, Frederic; Boddaert, Jacques (J Alzheimers Dis, 2017)
BACKGROUND: Dementia is associated with a worse prognosis of hip fracture, but the impact of a dedicated geriatric care pathway on the prognosis of these patients has not been evaluated. OBJECTIVE: According to the cognitive status before surgery, our main objective was to compare mortality rate at 6 months; secondary outcomes were to compare in-hospital complications, the risk of new institutionalization, and the ability to walk at 6 months. METHODS: Between 2009 and 2015, all patients (>70 years) admitted after hip fracture surgery into a dedicated unit of peri-operative geriatric care were included: patients with dementia (DP), without dementia (NDP), and with cognitive status not determined (CSND). Data are expressed as hazard ratio (HR) for multivariate cox analysis or odds ratio (OR) for multivariate logistic regression analysis and their 95% confidence interval (CI). RESULTS: We included 650 patients (86±6 years): 168 DP, 400 NDP, and 82 CSND. After adjustment for age, sex, comorbidities, polypharmacy, pre-fracture autonomy, time-to-surgery, and delirium, there were no significant differences for 6-month mortality (DP versus NDP: HR = 0.7[0.4-1.2], DP versus CSND: HR = 0.6[0.3-1.4], CSND versus NDP: HR = 0.8[0.4-1.7]); but DP and CSND were more likely to be newly institutionalized after 6 months compared to NDP (OR DP = 2.6[1.4-4.9], p = 0.003, OR CSND = 2.9[1.4-6.1], p = 0.004). 92% of population was walking after 6 months (63% with assistance): no difference was found between the three groups. CONCLUSION: In a dedicated geriatric care pathway, DP and CSND undergoing hip surgery have the same 6-month mortality and walking ability as NDP.

Association Between Later Life Lifestyle Factors and Alzheimer's Disease Biomarkers in Non-Demented Individuals: A Longitudinal Descriptive Cohort Study. - Reijs, Babette L R; Vos, Stephanie J B; Soininen, Hilkka; Lötjönen, Jyrki; Koikkalainen, Juha; Pikkarainen, Maria; Hall, Anette; Vanninen, Ritva; Liu, Yawu; Herukka, Sanna-Kaisa; Freund-Levi, Yvonne; Frisoni, Giovanni B; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Lifestyle factors have been associated with the risk of dementia, but the association with Alzheimer's disease (AD) remains unclear. OBJECTIVE: To examine the association between later life lifestyle factors and AD biomarkers (i.e., amyloid-β 1-42 (Aβ42) and tau in cerebrospinal fluid (CSF), and hippocampal volume) in individuals with subjective cognitive decline (SCD) and mild cognitive impairment (MCI). In addition, to examine the effect of later life lifestyle factors on developing AD-type dementia in individuals with MCI. METHODS: We selected individuals with SCD (n = 111) and MCI (n = 353) from the DESCRIPA and Kuopio Longitudinal MCI studies. CSF Aβ42 and tau concentrations were assessed with ELISA assay and hippocampal volume with multi-atlas segmentation. Lifestyle was assessed by clinical interview at baseline for: social activity, physical activity, cognitive activity, smoking, alcohol consumption, and sleep. We performed logistic and Cox regression analyses adjusted for study site, age, gender, education, and diagnosis. Prediction for AD-type dementia was performed in individuals with MCI only. RESULTS: Later life lifestyle factors were not associated with AD biomarkers or with conversion to AD-type dementia. AD biomarkers were strongly associated with conversion to AD-type dementia, but these relations were not modulated by lifestyle factors. Apolipoprotein E (APOE) genotype did not influence the results. CONCLUSIONS: Later life lifestyle factors had no impact on key AD biomarkers in individuals with SCD and MCI or on conversion to AD-type dementia in MCI.

The Association between Montreal Cognitive Assessment Memory Scores and Hippocampal Volume in a Neurodegenerative Disease Sample. - Ritter, Aaron; Hawley, Nanako; Banks, Sarah J; Miller, Justin B (J Alzheimers Dis, 2017)
Despite widespread use, there have been few investigations into the neuroanatomical correlates of the Montreal Cognitive Assessment (MoCA). In a sample of 138 consecutive patients presenting with cognitive complaints, we report significant correlations between lower MoCA memory scores and smaller hippocampal volumes (r = 0.36-0.41, p < 0.001). We also report that the newly devised memory index score, designed to better capture encoding deficits than the standard delayed recall score, was not significantly better for predicting hippocampal volume. These initial results suggest that poor performance on the MoCA's memory section should prompt further evaluation for hippocampal atrophy.

Association of Kidney Function Biomarkers with Brain MRI Findings: The BRINK Study. - Vemuri, Prashanthi; Knopman, David S; Jack, Clifford R; Lundt, Emily S; Weigand, Stephen D; Zuk, Samantha M; Thostenson, Kaely B; Reid, Robert I; Kantarci, Kejal; Slinin, Yelena; Lakshminarayan, Kamakshi; Davey, Cynthia S; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Chronic kidney disease (CKD) studies have reported variable prevalence of brain pathologies, in part due to low inclusion of participants with moderate to severe CKD. OBJECTIVE: To measure the association between kidney function biomarkers and brain MRI findings in CKD. METHODS: In the BRINK (BRain IN Kidney Disease) study, MRI was used to measure gray matter volumes, cerebrovascular pathologies (white matter hyperintensity (WMH), infarctions, microhemorrhages), and microstructural changes using diffusion tensor imaging (DTI). We performed regression analyses with estimated glomerular filtration rate (eGFR) and urine albumin to creatinine ratio (UACR) as primary predictors, and joint models that included both predictors, adjusted for vascular risk factors. RESULTS: We obtained 240 baseline MRI scans (150 CKD with eGFR <45 in ml/min/1.73 m2; 16 mild CKD: eGFR 45-59; 74 controls: eGFR≥60). Lower eGFR was associated with greater WMH burden, increased odds of cortical infarctions, and worsening diffusion changes throughout the brain. In eGFR models adjusted for UACR, only cortical infarction associations persisted. However, after adjusting for eGFR, higher UACR provided additional information related to temporal lobe atrophy, increased WMH, and whole brain microstructural changes as measured by increased DTI mean diffusivity. CONCLUSIONS: Biomarkers of kidney disease (eGFR and UACR) were associated with MRI brain changes, even after accounting for vascular risk factors. UACR adds unique additional information to eGFR regarding brain structural and diffusion biomarkers. There was a greater impact of kidney function biomarkers on cerebrovascular pathologies and microstructural brain changes, suggesting that cerebrovascular etiology may be the primary driver of cognitive impairment in CKD.

Association of Radon Background and Total Background Ionizing Radiation with Alzheimer's Disease Deaths in U.S. States. - Lehrer, Steven; Rheinstein, Peter H; Rosenzweig, Kenneth E (J Alzheimers Dis, 2017)
BACKGROUND: Exposure of the brain to ionizing radiation might promote the development of Alzheimer's disease (AD). OBJECTIVE: Analysis of AD death rates versus radon background radiation and total background radiation in U.S. states. METHODS: Total background, radon background, cosmic and terrestrial background radiation measurements are from Assessment of Variations in Radiation Exposure in the United States and Report No. 160 - Ionizing Radiation Exposure of the Population of the United States. 2013 AD death rates by U.S. state are from the Alzheimer's Association. RESULTS: Radon background ionizing radiation was significantly correlated with AD death rate in 50 states and the District of Columbia (r = 0.467, p = 0.001). Total background ionizing radiation was also significantly correlated with AD death rate in 50 states and the District of Columbia (r = 0.452, p = 0.001). Multivariate linear regression weighted by state population demonstrated that AD death rate was significantly correlated with radon background (β= 0.169, p < 0.001), age (β= 0.231, p < 0.001), hypertension (β= 0.155, p < 0.001), and diabetes (β= 0.353, p < 0.001). CONCLUSION: Our findings, like other studies, suggest that ionizing radiation is a risk factor for AD. Intranasal inhalation of radon gas could subject the rhinencephalon and hippocampus to damaging radiation that initiates AD. The damage would accumulate over time, causing age to be a powerful risk factor.

Associations of CAIDE Dementia Risk Score with MRI, PIB-PET measures, and cognition. - Stephen, Ruth; Liu, Yawu; Ngandu, Tiia; Rinne, Juha O; Kemppainen, Nina; Parkkola, Riitta; Laatikainen, Tiina; Paajanen, Teemu; Hänninen, Tuomo; Strandberg, Timo; Antikainen, Riitta; Tuomilehto, Jaakko; et al. (J Alzheimers Dis, 2017)
BACKGROUND: CAIDE Dementia Risk Score is the first validated tool for estimating dementia risk based on a midlife risk profile. OBJECTIVES: This observational study investigated longitudinal associations of CAIDE Dementia Risk Score with brain MRI, amyloid burden evaluated with PIB-PET, and detailed cognition measures. METHODS: FINGER participants were at-risk elderly without dementia. CAIDE Risk Score was calculated using data from previous national surveys (mean age 52.4 years). In connection to baseline FINGER visit (on average 17.6 years later, mean age 70.1 years), 132 participants underwent MRI scans, and 48 underwent PIB-PET scans. All 1,260 participants were cognitively assessed (Neuropsychological Test Battery, NTB). Neuroimaging assessments included brain cortical thickness and volumes (Freesurfer 5.0.3), visually rated medial temporal atrophy (MTA), white matter lesions (WML), and amyloid accumulation. RESULTS: Higher CAIDE Dementia Risk Score was related to more pronounced deep WML (OR 1.22, 95% CI 1.05-1.43), lower total gray matter (β-coefficient -0.29, p = 0.001) and hippocampal volume (β-coefficient -0.28, p = 0.003), lower cortical thickness (β-coefficient -0.19, p = 0.042), and poorer cognition (β-coefficients -0.31 for total NTB score, -0.25 for executive functioning, -0.33 for processing speed, and -0.20 for memory, all p < 0.001). Higher CAIDE Dementia Risk Score including APOE genotype was additionally related to more pronounced MTA (OR 1.15, 95% CI 1.00-1.30). No associations were found with periventricular WML or amyloid accumulation. CONCLUSIONS: The CAIDE Dementia Risk Score was related to indicators of cerebrovascular changes and neurodegeneration on MRI, and cognition. The lack of association with brain amyloid accumulation needs to be verified in studies with larger sample sizes.

AZD3293: Pharmacokinetic and Pharmacodynamic Effects in Healthy Subjects and Patients with Alzheimer's Disease. - Cebers, Gvido; Alexander, Robert C; Haeberlein, Samantha Budd; Han, David; Goldwater, Ronald; Ereshefsky, Larry; Olsson, Tina; Ye, Naidong; Rosen, Laura; Russell, Muir; Maltby, Justine; Eketjäll, Susanna; et al. (J Alzheimers Dis, 2017)
AZD3293 (LY3314814) is a promising new potentially disease-modifying BACE1 (β-secretase) inhibitor in Phase III clinical development for the treatment of Alzheimer's disease. Reported here are the first two Phase I studies: (1) a single ascending dose study evaluating doses of 1-750 mg with a food-effect component (n = 72), and (2) a 2-week multiple ascending dose study evaluating doses of 15 or 50 mg once daily (QD) or 70 mg once weekly (QW) in elderly subjects (Part 1, n = 31), and 15, 50, or 150 mg QD in patients with mild to moderate Alzheimer's disease (Part 2, n = 16). AZD3293 was generally well tolerated up to the highest doses given. No notable food effects were observed. PK following multiple doses (Part 2) were tmax of 1 to 3 h and mean t1/2 of 16 to 21 h across the 15 to 150 mg dose range. For single doses of ≥5 mg, a ≥70% reduction was observed in mean plasma Aβ40 and Aβ42 concentrations, with prolonged suppression for up to 3 weeks at the highest dose level studied. Following multiple doses, robust reductions in plasma (≥64% at 15 mg and ≥78% at ≥50 mg) and cerebrospinal fluid (≥51% at 15 mg and ≥76% at ≥50 mg) Aβ peptides were seen, including prolonged suppression even with a QW dosing regimen. AZD3293 is the only BACE1 inhibitor for which prolonged suppression of plasma Aβ with a QW dosing schedule has been reported. Two Phase III studies of AZD3293 (AMARANTH, NCT02245737; and DAYBREAK-ALZ, NCT02783573) are now ongoing.

Biomarkers and Functional Decline in Prodromal Alzheimer's Disease. - Robb, Catherine; Udeh-Momoh, Chinedu; Wagenpfeil, Stefan; Schöpe, Jakob; Alexopoulos, Panagiotis; Perneczky, Robert (J Alzheimers Dis, 2017)
BACKGROUND: Little is known of possible associations between Alzheimer's disease (AD) biomarkers and instrumental activities of daily living (IADL) change over time. OBJECTIVE: The present study seeks to identify relationships between baseline imaging and fluid biomarker profiles, and decline in IADL utilizing data collated from the Alzheimer's Disease Neuroimaging Initiative (ADNI) cohort. METHODS: Generalized estimating equations analysis, adjusted for cognitive deterioration, was applied to a cohort of 509 individuals from all stages of ADNI, including 156 healthy controls, 189 early mild cognitive impairment (MCI) patients and 164 MCI patients. RESULTS: A significant correlation was found between baseline biomarkers, specifically CSF Aβ and FDG PET, and IADL change over a 3-year period in individuals with MCI. Importantly, comparable correlations between presence of pathological biomarker levels and temporal decline in both functional and cognitive performance were also noted. DISCUSSION: We show that distinct baseline biomarkers may predict latent changes in IADL. Our results necessitate a revision of the commonly held view upholding cognitive changes as the predominant endpoint measure associated with presence of abnormal baseline biomarkers.

Blood Pressure and Hispanic/Latino Cognitive Function: Hispanic Community Health Study/Study of Latinos Results. - Tarraf, Wassim; Rodríguez, Carlos J; Daviglus, Martha L; Lamar, Melissa; Schneiderman, Neil; Gallo, Linda; Talavera, Gregory A; Kaplan, Robert C; Fornage, Myriam; Conceicao, Alan; González, Hector M (J Alzheimers Dis, 2017)
BACKGROUND: Hispanics/Latinos are at increased risk for cardiovascular disease and cognitive decline and dementias. High blood pressure (BP) has been implicated in both stroke and dementias. Associations between BP and cognition among diverse Latinos are still unpublished. OBJECTIVE: We examined associations between cognition and four BP based measures among diverse Hispanics/Latinos. We hypothesized that higher BP, particularly systolic pressure, and increased arterial stiffness (i.e., pulse pressure), would be associated with lower cognitive function. METHODS: We used baseline (2008-2011) Hispanic Community Health Study/Study of Latinos (HCHS/SOL; n = 9,019; ages 45-74 years) data to examine cognition in relation to BP measures. RESULTS: In age, sex, and education adjusted models, systolic, pulse, and mean arterial pressure were consistently negatively associated with executive function, psychomotor speed and sustained attention, verbal episodic learning and memory, speech fluency, and mental status measures. These associations were attenuated but remained statistically significant in fully adjusted models. CONCLUSION: Among middle-aged and older diverse Hispanics/Latinos, we found modest but consistent associations between indicators of arterial stiffness, and compromised blood flow and lower cognitive function. Clinical management and public health interventions to raise awareness and enhance BP management beginning in midlife could reduce disparities and improve population health by reducing cognitive decline burdens.

Blood-Based Oligomeric and Other Protein Variant Biomarkers to Facilitate Pre-Symptomatic Diagnosis and Staging of Alzheimer's Disease. - Williams, Stephanie M; Schulz, Philip; Rosenberry, Terrone L; Caselli, Richard J; Sierks, Michael R (J Alzheimers Dis, 2017)
Oligomeric forms of amyloid-β (Aβ), tau, and TDP-43 play important roles in Alzheimer's disease (AD), and therefore are promising biomarkers. We previously generated single chain antibody fragments (scFvs) that selectively bind disease-related variants of these proteins including A4, C6T, and E1, which bind different oligomeric Aβ variants; D11C, which binds oligomeric tau; and AD-TDP1 and AD-TDP2, which bind disease related TDP-43 variants. To determine the utility of these disease-related variants as early biomarkers, we first analyzed 11 human sera samples obtained ∼2 years prior to an initial mild cognitive impairment (MCI) diagnosis. While the subsequent diagnoses for the cases covered several different conditions, all samples had elevated protein variant levels relative to the plasma controls although with different individual biomarker profiles. We then analyzed a set of longitudinal human plasma samples from four AD (encompassing time points prior to MCI diagnosis and continuing until after conversion to AD) and two control cases. Pre-MCI samples were characterized by high TDP-43 variant levels, MCI samples by high Aβ variant levels, and AD samples by high Aβ and tau variant levels. Sample time points ranged from ∼7 years pre-MCI to ∼9 years after AD conversion. Bivariate correlations showed a negative correlation with TDP-43 levels and positive correlations with cumulative Aβ and oligomeric tau levels indicating an increase in neurodegenerative processes with time in AD. Detection of disease related protein variants not only readily selects AD cases from controls, but also stages progression of AD and holds promise for a pre-symptomatic blood-based biomarker profile for AD.

The Brain's Structural Connectome Mediates the Relationship between Regional Neuroimaging Biomarkers in Alzheimer's Disease. - Pandya, Sneha; Kuceyeski, Amy; Raj, Ashish (J Alzheimers Dis, 2017)
Alzheimer's disease (AD), one of the most common causes of dementia in adults, is a progressive neurodegenerative disorder exhibiting well-defined neuropathological hallmarks. It is known that disease pathology involves misfolded amyloid-β (Aβ) and tau proteins, and exhibits a relatively stereotyped progression over decades. The relationship between AD neuropathological hallmarks (Aβ, hypometabolism, and tau proteins) and imaging biomarkers (MRI, AV-45/FDG-PET) is not fully understood. In addition, biomarker pathologies are oftentimes discordant, wherein it may show varying levels of abnormality across brain regions. Evidence based on recent elucidation of trans-neuronal "prion-like" transmission and other available data already suggests that disease spread follows the brain's fiber connectivity network. Thereby, the brain's connectome information can be used to predict the process of disease spread in AD. A recently established mathematical model of AD pathology spread using a connectome-based network diffusion model was successful in encapsulating neurodegenerative progression. Motivated by these network-based findings, the current study explores whether and how network connectivity mediates the interactions between various AD biomarkers. We hypothesized that the structural connectivity matrix will mediate the cross-sectional association between regional AD-associated hypometabolism and Aβ deposition. Given recent reports of inherent or lifetime activity of brain regions as strong predictors of Aβ deposition in patients, we also tested whether healthy metabolism exerts a network-mediated effect on Aβ deposition and hypometabolism in AD patients. We found that regional Aβ deposition is best predicted by a linear combination of both regional healthy local metabolism and connectome-mediated regional healthy metabolism.

Can Better Management of Periodontal Disease Delay the Onset and Progression of Alzheimer's Disease? - Harding, Alice; Robinson, Sarita; Crean, StJohn; Singhrao, Sim K (J Alzheimers Dis, 2017)
A risk factor relationship exists between periodontal disease and Alzheimer's disease (AD) via tooth loss, and improved memory following dental intervention. This links the microbial contribution from indigenous oral periodontal pathogens to the manifestation of chronic conditions, such as AD. Here, we use Porphyromonas gingivalis infection to illustrate its effect on mental health. P. gingivalis infection, in its primary sub-gingival niche, can cause polymicrobial synergy and dysbiosis. Dysbiosis describes the residency of select commensals from the oral cavity following co-aggregation around the dominant keystone pathogen, such as P. gingivalis, to gain greater virulence. The initial process involves P. gingivalis disturbing neutrophil mediated innate immune responses in the healthy gingivae and then downregulating adaptive immune cell differentiation and development to invade, and subsequently, establish new dysbiotic bacterial communities. Immune responses affect the host in general and functionally via dietary adjustments caused by tooth loss. Studies from animals orally infected with P. gingivalis confirm this bacterium can transmigrate to distant organ sites (the brain) and contribute toward peripheral and intracerebral inflammation, and compromise vascular and microvascular integrity. In another study, P. gingivalis infection caused sleep pattern disturbances by altering glial cell light/dark molecular clock activity, and this, in turn, can affect the clearance of danger associated molecular patterns, such as amyloid-β, via the glymphatic system. Since P. gingivalis can transmigrate to the brain and modulate organ-specific inflammatory innate and adaptive immune responses, this paper explores whether better management of indigenous periodontal bacteria could delay/prevent the onset and/or progression of dementia.

Can Musical or Painting Interventions Improve Chronic Pain, Mood, Quality of Life, and Cognition in Patients with Mild Alzheimer's Disease? Evidence from a Randomized Controlled Trial. - Pongan, Elodie; Tillmann, Barbara; Leveque, Yohana; Trombert, Béatrice; Getenet, Jean Claude; Auguste, Nicolas; Dauphinot, Virginie; El Haouari, Hanane; Navez, Malou; Dorey, Jean-Michel; Krolak-Salmon, Pierre; Laurent, Bernard; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Among non-pharmacological therapies, musical intervention is often used for patients with Alzheimer's disease (AD) and patients presenting chronic pain. However, their efficacy is still under debate. OBJECTIVE: Our aim was to determine the efficacy of choral singing versus painting sessions on chronic pain, mood, quality of life, and cognition in AD patients. METHODS: In this multicenter randomized controlled trial, 59 mild AD patients were randomized to a 12-week singing (SG; n = 31) or painting group (PG; n = 28). Chronic pain, anxiety, depression, and quality of life were assessed before, after, and 1 month after the sessions. Cognitive abilities were assessed before and after interventions. The evolution of these different measures was assessed with mixed linear models. The primary data analysis was by intention-to-treat, and completed by a 'per protocol' approach. RESULTS: Both singing and painting interventions led to significant pain reduction (Time effect: F = 4.71; p = 0.01), reduced anxiety (Time effect: F = 10.74; p < 0.0001), improved Quality of Life (Time effect: F = 6.79; p = 0.002), improved digit span (F = 12.93; p = 0.001), and inhibitory processes (Time effect: F = 4.93; p = 0.03). Depression was reduced over time in PG only (Time x Group effect: F = 4.53; p = 0.01). Verbal Memory performance remained stable over time in SG, but decreased in PG (Time x group effect: F = 9.29; p = 0.004). CONCLUSION: Findings suggest that singing and painting interventions may reduce pain and improve mood, quality of life, and cognition in patients with mild AD, with differential effects of painting for depression and singing for memory performance.

Cerebral Hemodynamics in Mild Cognitive Impairment: A Systematic Review. - Beishon, Lucy; Haunton, Victoria J; Panerai, Ronney B; Robinson, Thompson G (J Alzheimers Dis, 2017)
BACKGROUND: The incidence of dementia is projected to rise over the coming decades, but with no sensitive diagnostic tests available. Vascular pathology precedes the deposition of amyloid and is an attractive early target. OBJECTIVE: The aim of this review was to investigate the use of cerebral hemodynamics and oxygenation as a novel biomarker for mild cognitive impairment (MCI), focusing on transcranial Doppler ultrasonography (TCD) and near-infrared spectroscopy (NIRS). METHODS: 2,698 articles were identified from Medline, Embase, PsychINFO, and Web of Science databases. 306 articles were screened and quality assessed independently by two reviewers; 26 met the inclusion criteria. Meta-analyses were performed for each marker with two or more studies and limited heterogeneity. RESULTS: Eleven studies were TCD, 8 NIRS, 5 magnetic resonance imaging, and 2 positron/single photon emission tomography. Meta-analyses showed reduced tissue oxygenation index, cerebral blood flow and velocity, with higher pulsatility index, phase and cerebrovascular resistance in MCI compared to controls. The majority of studies found reduced CO2 reactivity in MCI, with mixed findings in neuroactivation studies. CONCLUSION: Despite small sample sizes and heterogeneity, meta-analyses demonstrate clear abnormalities in cerebral hemodynamic and oxygenation parameters, even at an early stage of cognitive decline. Further work is required to investigate the use of cerebral hemodynamic and oxygenation parameters as a sensitive biomarker for dementia.

Cerebral Oxidative Stress and Microvasculature Defects in TNF-α Expressing Transgenic and Porphyromonas gingivalis-Infected ApoE-/- Mice. - Rokad, Farheen; Moseley, Ryan; Hardy, Rowan S; Chukkapalli, Sasanka; Crean, StJohn; Kesavalu, Lakshmyya; Singhrao, Sim K (J Alzheimers Dis, 2017)
The polymicrobial dysbiotic subgingival biofilm microbes associated with periodontal disease appear to contribute to developing pathologies in distal body sites, including the brain. This study examined oxidative stress, in the form of increased protein carbonylation and oxidative protein damage, in the tumor necrosis factor-α (TNF-α) transgenic mouse that models inflammatory TNF-α excess during bacterial infection; and in the apolipoprotein knockout (ApoE-/-) mouse brains, following Porphyromonas gingivalis gingival monoinfection. Following 2,4-dinitrophenylhydrazine derivatization, carbonyl groups were detected in frontal lobe brain tissue lysates by immunoblotting and immunohistochemical analysis of fixed tissue sections from the frontotemporal lobe and the hippocampus. Immunoblot analysis confirmed the presence of variable carbonyl content and oxidative protein damage in all lysates, with TNF-α transgenic blots exhibiting increased protein carbonyl content, with consistently prominent bands at 25 kDa (p = 0.0001), 43 kDa, and 68 kDa, over wild-type mice. Compared to sham-infected ApoE-/- mouse blots, P. gingivalis-infected brain tissue blots demonstrated the greatest detectable protein carbonyl content overall, with numerous prominent bands at 25 kDa (p = 0.001) and 43 kDa (p = 0.0001) and an exclusive band to this group between 30-43 kDa* (p = 0.0001). In addition, marked immunostaining was detected exclusively in the microvasculature in P. gingivalis-infected hippocampal tissue sections, compared to sham-infected, wild-type, and TNF-α transgenic mice. This study revealed that the hippocampal microvascular structure of P. gingivalis-infected ApoE-/- mice possesses elevated oxidative stress levels, resulting in the associated tight junction proteins being susceptible to increased oxidative/proteolytic degradation, leading to a loss of functional integrity.

Cerebrospinal Fluid Biomarkers and Clinical Progression in Patients with Subjective Cognitive Decline and Mild Cognitive Impairment. - Wolfsgruber, Steffen; Polcher, Alexandra; Koppara, Alexander; Kleineidam, Luca; Frölich, Lutz; Peters, Oliver; Hüll, Michael; Rüther, Eckart; Wiltfang, Jens; Maier, Wolfgang; Kornhuber, Johannes; Lewczuk, Piotr; et al. (J Alzheimers Dis, 2017)
BACKGROUND: There is very limited data on the prevalence of abnormal cerebrospinal fluid (CSF) biomarkers of Alzheimer's disease (AD) and their predictive value for clinical progression in memory clinic patients with subjective cognitive decline (SCD). OBJECTIVE: To assess the frequency of abnormal CSF biomarkers of AD and their predictive value for clinical progression in memory clinic patients with SCD in comparison to patients with mild cognitive impairment (MCI) from the same cohort. METHODS: We analyzed prospective data from memory clinic patients of the German Competence Network Dementia cohort with a baseline diagnosis of SCD (n = 82) or MCI (n = 134), distinguished by actuarial neuropsychological MCI criteria ("Jak-Bondi criteria"). Risk of clinical progression during 3-year follow-up was evaluated with Cox-Proportional-Hazard models. RESULTS: Prevalence of abnormal values in CSF markers of tau-mediated neurodegeneration (67.8% versus 46.3%) but not of amyloid deposition (40.3% versus 35.4%) was significantly higher in MCI compared to SCD. The rate of incident AD dementia (26.1% versus 12.2%) was also significantly higher in MCI. In SCD, additional 22% progressed to MCI during follow-up. Combined amyloid/tau abnormality was the strongest predictor of clinical progression in both groups. CONCLUSION: High prevalence of biomarker abnormality and clinical progression, together with the predictive value of CSF biomarkers, in memory clinic patients with SCD support the validity and usefulness of this condition as a "pre-MCI" at risk stage of AD.

Cerebrospinal Fluid Biomarkers for Alzheimer's Disease: A View of the Regulatory Science Qualification Landscape from the Coalition Against Major Diseases CSF Biomarker Team. - Arnerić, Stephen P; Batrla-Utermann, Richard; Beckett, Laurel; Bittner, Tobias; Blennow, Kaj; Carter, Leslie; Dean, Robert; Engelborghs, Sebastiaan; Genius, Just; Gordon, Mark Forrest; Hitchcock, Janice; Kaplow, June; et al. (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) drug development is burdened with the current requirement to conduct large, lengthy, and costly trials to overcome uncertainty in patient progression and effect size on treatment outcome measures. There is an urgent need for the discovery, development, and implementation of novel, objectively measured biomarkers for AD that would aid selection of the appropriate subpopulation of patients in clinical trials, and presumably, improve the likelihood of successfully evaluating innovative treatment options. Amyloid deposition and tau in the brain, which are most commonly assessed either in cerebrospinal fluid (CSF) or by molecular imaging, are consistently and widely accepted. Nonetheless, a clear gap still exists in the accurate identification of subjects that truly have the hallmarks of AD. The Coalition Against Major Diseases (CAMD), one of 12 consortia of the Critical Path Institute (C-Path), aims to streamline drug development for AD and related dementias by advancing regulatory approved drug development tools for clinical trials through precompetitive data sharing and adoption of consensus clinical data standards. This report focuses on the regulatory process for biomarker qualification, briefly comments on how it contrasts with approval or clearance of companion diagnostics, details the qualifications currently available to the field of AD, and highlights the current challenges facing the landscape of CSF biomarkers qualified as hallmarks of AD. Finally, it recommends actions to accelerate regulatory qualification of CSF biomarkers that would, in turn, improve the efficiency of AD therapeutic development.

Cerebrospinal Fluid Biomarkers for the Differential Diagnosis between Alzheimer's Disease and Frontotemporal Lobar Degeneration: Systematic Review, HSROC Analysis, and Confounding Factors. - Rivero-Santana, Amado; Ferreira, Daniel; Perestelo-Pérez, Lilisbeth; Westman, Eric; Wahlund, Lars-Olof; Sarría, Antonio; Serrano-Aguilar, Pedro (J Alzheimers Dis, 2017)
BACKGROUND: Differential diagnosis in dementia is at present one of the main challenges both in clinical practice and research. Cerebrospinal fluid (CSF) biomarkers are included in the current diagnostic criteria of Alzheimer's disease (AD) but their clinical utility is still unclear. OBJECTIVE: We performed a systematic review of studies analyzing the diagnostic performance of CSF Aβ42, total tau (t-tau), and phosphorylated tau (p-tau) in the discrimination between AD and frontotemporal lobar degeneration (FTLD) dementias. METHODS: The following electronic databases were consulted until May 2016: Medline and PreMedline, EMBASE, PsycInfo, CINAHL, Cochrane Library, and CRD. For the first-time in the field, a Hierarchical Summary Receiver Operating Characteristic (HRSOC) model was applied, which avoids methodological problems of meta-analyses based on summary points of sensitivity and specificity values. We also investigated relevant confounders of CSF biomarkers' diagnostic performance such as age, disease duration, and global cognitive impairment. RESULTS: The p-tau/Aβ42 ratio showed the best diagnostic performance. No statistically significant effects of the confounders were observed. Nonetheless, the p-tau/Aβ42 ratio may be especially indicated for younger patients. P-tau may be preferable for less cognitively impaired patients (high MMSE scores) and the t-tau/Aβ42 ratio for more cognitively impaired patients (low MMSE scores). CONCLUSION: The p-tau/Aβ42 ratio has potential for being implemented in the clinical routine for the differential diagnosis between AD and FTLD. It is of utmost importance that future studies report information on confounders such as age, disease duration, and cognitive impairment, which should also stimulate understanding of the role of these factors in disease mechanisms and pathophysiology.

Challenges in Screening and Recruitment for a Neuroimaging Study in Cognitively Impaired Geriatric Inpatients. - Apostolova, Ivayla; Lange, Catharina; Roberts, Anna; Igel, Hans Joachim; Mäurer, Anja; Liese, Stephanie; Estrella, Melanie; Prasad, Vikas; Stechl, Elisabeth; Lämmler, Gernot; Steinhagen-Thiessen, Elisabeth; Buchert, Ralph (J Alzheimers Dis, 2017)
BACKGROUND: Neuroimaging-based biomarkers have the potential to improve etiological diagnosis of cognitive impairment in elderly inpatients. However, there is a relative lack of studies on neuroimaging-based biomarkers in hospitalized geriatric patients, as the vast majority of neuroimaging studies in dementia have focused on memory clinic outpatients. An important aspect of study planning is a priori estimation of the rate of screen failures. OBJECTIVE: To report on the rate and causes of screen failures in a prospective study on the utility of neuroimaging (PET, MRI) for the etiological diagnosis of newly manifested cognitive impairment in acutely hospitalized geriatric patients. METHODS: Ten acute care geriatrics clinics with 802 beds participated in the study. The potential recruitment rate had been estimated to 5 patients/100 beds/week. RESULTS: Seventeen months of pre-screening resulted in 322 potential participants. 109 of these patients were enrolled, i.e., the screen failure rate was 66%. 58% of the screen failures were due to refusal of participation by the patient, most often due to lack of interest in clarifying the cause of the cognitive impairment or due to reluctance to engage in additional diagnostic procedures associated with physical stress. 42% of pre-screened patients were excluded because of violation of the eligibility criteria. CONCLUSION: Enrollment for neuroimaging studies presents considerable additional challenges in acutely hospitalized geriatric patients compared to outpatient settings. Low rate of approaching potential candidates by attending geriatricians and a high rate of screen failures have to be anticipated in the study design.

Changes in Plasma β-NGF and Its Receptors Expression on Peripheral Blood Monocytes During Alzheimer's Disease Progression. - Crispoltoni, Lucia; Stabile, Anna Maria; Pistilli, Alessandra; Venturelli, Massimo; Cerulli, Giuliano; Fonte, Cristina; Smania, Nicola; Schena, Federico; Rende, Mario (J Alzheimers Dis, 2017)
Alzheimer's disease (AD), the most common cause of dementia, is characterized by the deposition of extracellular amyloid-β (Aβ) plaques and intracellular neurofibrillary tangles, and by neuroinflammation. During the pathogenesis of AD, monocyte-macrophage lineage cells become increasingly ineffective in clearing Aβ deposits, less able to differentiate, and shift toward pro-inflammatory processes. Beta-nerve growth factor (β-NGF) and its receptors, TrKA and p75NTR, produce several biological responses, including cell apoptosis and survival, and inflammation. In the central nervous system, the involvement of these receptors in several critical hallmarks of AD is well known, but their role in circulating monocytes during the progression of dementia is unclear. We investigated the relationship between plasma β-NGF concentration and TrkA/p75NTR receptor expression in monocytes of patients with mild cognitive impairment (MCI), mild AD, and severe AD. We observed that plasma β-NGF concentration was increased with a higher expression of TrKA, but not of p75NTR, in monocytes from patients with MCI and mild AD, whereas β-NGF concentration and TrKA expression were decreased and p75NTR expression was increased, associated with caspase 3-mediated apoptosis, in patients with severe AD. In our study, we show evidence of variation in plasmatic β-NGF and monocytic TrkA/p75NTR receptor expression during the progression of dementia. These novel findings add evidence to support the hypothesis for the involvement of β-NGF and its receptors on monocytes during AD progression.

Chromatin-Bound Oxidized α-Synuclein Causes Strand Breaks in Neuronal Genomes in in vitro Models of Parkinson's Disease. - Vasquez, Velmarini; Mitra, Joy; Hegde, Pavana M; Pandey, Arvind; Sengupta, Shiladitya; Mitra, Sankar; Rao, K S; Hegde, Muralidhar L (J Alzheimers Dis, 2017)
Alpha-synuclein (α-Syn) overexpression and misfolding/aggregation in degenerating dopaminergic neurons have long been implicated in Parkinson's disease (PD). The neurotoxicity of α-Syn is enhanced by iron (Fe) and other pro-oxidant metals, leading to generation of reactive oxygen species in PD brain. Although α-Syn is predominantly localized in presynaptic nerve terminals, a small fraction exists in neuronal nuclei. However, the functional and/or pathological role of nuclear α-Syn is unclear. Following up on our earlier report that α-Syn directly binds DNA in vitro, here we confirm the nuclear localization and chromatin association of α-Syn in neurons using proximity ligation and chromatin immunoprecipitation analysis. Moderate (∼2-fold) increase in α-Syn expression in neural lineage progenitor cells (NPC) derived from induced pluripotent human stem cells (iPSCs) or differentiated SHSY-5Y cells caused DNA strand breaks in the nuclear genome, which was further enhanced synergistically by Fe salts. Furthermore, α-Syn required nuclear localization for inducing genome damage as revealed by the effect of nucleus versus cytosol-specific mutants. Enhanced DNA damage by oxidized and misfolded/oligomeric α-Syn suggests that DNA nicking activity is mediated by the chemical nuclease activity of an oxidized peptide segment in the misfolded α-Syn. Consistent with this finding, a marked increase in Fe-dependent DNA breaks was observed in NPCs from a PD patient-derived iPSC line harboring triplication of the SNCA gene. Finally, α-Syn combined with Fe significantly promoted neuronal cell death. Together, these findings provide a novel molecular insight into the direct role of α-Syn in inducing neuronal genome damage, which could possibly contribute to neurodegeneration in PD.

Classification of Depression, Cognitive Disorders, and Co-Morbid Depression and Cognitive Disorders with Perfusion SPECT Neuroimaging. - Amen, Daniel G; Krishnamani, Pavitra; Meysami, Somayeh; Newberg, Andrew; Raji, Cyrus A (J Alzheimers Dis, 2017)
BACKGROUND: Depression and cognitive disorders (CDs) are two common co-morbid afflictions that commonly present with overlapping symptoms. OBJECTIVE: To evaluate if perfusion neuroimaging with brain SPECT can distinguish persons with depression from those with CDs or both conditions. METHODS: Inclusion criteria were DSM-IV defined depression or CDs (Alzheimer's disease, vascular dementia, dementia not otherwise specified, and amnestic disorders not otherwise specified) including persons with both (total n = 4,541; 847 CDs, 3,269 depression, 425 with both). Perfusion differences between the groups were calculated using two-sampled t-tests corrected for multiple comparisons. Diagnostic separation was determined with discriminant analysis. Feature selection revealed predictive regions in delineating depression from CDs and comorbid cases. RESULTS: Persons with CDs had lower cerebral perfusion compared to depression. In co-morbid persons, cerebral hypoperfusion was additive, with regions showing lower regional cerebral blood flow compared to either diagnosis alone. Both baseline and concentration SPECT regions yielded correct classification of 86% and leave one out cross-validation of 83%. AUC analysis for SPECT regions showed 86% accuracy, 80% sensitivity and 75% specificity. Discriminant analysis separated depression and CDs from comorbid cases with correct classification of 90.8% and cross validated accuracy of 88.6%. Area under the curve was 83% with sensitivity of 80% and specificity of 70%. Feature selection identified the most predictive regions in left hippocampus, right insula, cerebellar, and frontal lobe regions. CONCLUSION: Quantitative perfusion SPECT neuroimaging distinguishes depression from dementia and those with both co-morbidities. Perfusion brain SPECT can be utilized clinically to delineate between these two disorders.

Clinical Effectiveness and Tolerability of Electroconvulsive Therapy in Patients with Neuropsychiatric Symptoms of Dementia. - Isserles, Moshe; Daskalakis, Zafiris J; Kumar, Sanjeev; Rajji, Tarek K; Blumberger, Daniel M (J Alzheimers Dis, 2017)
BACKGROUND: Dementia frequently presents with aggression, agitation, and disorganized behavior for which current treatment is partially effective and is associated with significant adverse effects. OBJECTIVE: The aim of this study was to retrospectively assess the clinical effectiveness and tolerability of electroconvulsive therapy (ECT) in a sample of patients with neuropsychiatric symptoms of dementia (NPS) and to explore factors associated with response and with cognitive adverse effects. METHODS: We examined the clinical records of 25 patients with dementia and a pre-existing psychiatric disorder treated with ECT at an academic mental health hospital between April 1, 2010 and January 28, 2016. Twenty-nine acute ECT courses and fifteen maintenance courses were reviewed. We assessed treatment effectiveness and cognitive adverse effects as well as factors associated with response to treatment, including pre-existing psychiatric disorders, concomitant pharmacological treatment and types of dementia. RESULTS: ECT resulted in a clinically meaningful response in 72% of acute treatment courses. Cognitive adverse effects affecting functioning were reported in 7% of the acute treatment courses. Maintenance treatment was effective in sustaining the response in 87% of treatment courses with two reports of significant cognitive adverse effects. One patient fell and experienced a hip fracture a day after treatment. Use of antipsychotic or antidepressant medications, pre-existing psychiatric disorder, or gender were not associated with response. CONCLUSION: This study shows meaningful clinical effectiveness and good tolerability of ECT in patients with severe NPS of dementia. Furthermore, maintenance ECT was effective in sustaining treatment response.

Clinical Response to Donepezil in Mild and Moderate Dementia: Relationship to Drug Plasma Concentration and CYP2D6 and APOE Genetic Polymorphisms. - Miranda, Luís F J R; Gomes, Karina B; Tito, Pedro A L; Silveira, Josianne N; Pianetti, Gerson A; Byrro, Ricardo M D; Peles, Patrícia R H; Pereira, Fernando H; Santos, Thiago R; Assini, Arthur G; Ribeiro, Valéria V; Moraes, Edgar N; et al. (J Alzheimers Dis, 2017)
The clinical response to donepezil in patients with mild and moderate dementia was investigated in relation to the drug plasma concentration and APOE and CYP2D6 polymorphisms. In a prospective naturalistic observational study, 42 patients with Alzheimer's disease (AD) and AD with cerebrovascular disease who took donepezil (10 mg) for 12 months were evaluated. Their DNA was genotyped, and the donepezil plasma concentrations were measured after 3, 6, and 12 months. Good responders scored ≥-1 on the Mini-Mental State Examination at 12 months in comparison to the baseline score. The study results indicated the good response pattern was influenced by the concentration of donepezil, but not by APOE and CYP2D6 polymorphisms.

Cognitive Composites Domain Scores Related to Neuroimaging Biomarkers within Probable-Amnestic Mild Cognitive Impairment-Storage Subtype. - Espinosa, Ana; Alegret, Montserrat; Pesini, Pedro; Valero, Sergi; Lafuente, Asunción; Buendia, Mar; San José, Itziar; Ibarria, Marta; Tejero, Miguel A; Giménez, Joan; Ruiz, Susana; Hernandez, Isabel; et al. (J Alzheimers Dis, 2017)
The probable-amnestic (Pr-a) mild cognitive impairment (MCI)-storage subtype is a phenotype with 8.5 times more risk of conversion to dementia, mainly Alzheimer's disease (AD), than the possible non-amnestic (Pss-na) MCI. The aim of this study was to find the optimized cognitive composites (CCs) domain scores most related to neuroimaging biomarkers within Pr-aMCI-storage subtype patients. The Fundació ACE (ACE) study with 20 Pr-aMCI-storage subtype subjects (MCI) were analyzed. All subjects underwent a neuropsychological assessment, a structural MRI, FDG-PET, and PIB-PET. The adjusted hippocampal volume (aHV) on MRI, the standard uptake value ratio (SUVR) on FDG-PET and PIB-PET SUVR measures were analyzed. The construction of the CCs domain scores, and the aHV on MRI and FDG-PET SUVR measures, were replicated in the parental AB255 study database (n = 133 MCI). Partial correlations adjusted by age, gender, and education were calculated with the associated p-value among every CC domain score and the neuroimaging biomarkers. The results were replicated in the "MCI due to AD" with memory storage impairments from ADNI. Delayed Recall CC domain score was significantly correlated with PIB-PET SUVR (β= -0.61, p = 0.003) in the ACE study and also with aHV on MRI (β= 0.27, p = 0.01) and FDG-PET SUVR (β= 0.27, p = 0.01) in the AB255 study. After a median survival time of 20.6 months, 85% from the ACE MCI converted to AD. The replication of our results in the ADNI dataset also confirmed our findings. Delayed Recall is the CC domain score best correlated with neuroimaging biomarkers associated with prodromal AD diagnosis.

Cognitive Status, Gray Matter Atrophy, and Lower Orthostatic Blood Pressure in Older Adults. - O'Hare, Celia; Kenny, Rose-Anne; Aizenstein, Howard; Boudreau, Robert; Newman, Anne; Launer, Lenore; Satterfield, Suzanne; Yaffe, Kristine; Rosano, Caterina (J Alzheimers Dis, 2017)
BACKGROUND: Associations between orthostatic blood pressure and cognitive status (CS) have been described with conflicting results. OBJECTIVE: We hypothesize that long-term exposure to lower orthostatic blood pressure is related to having worse CS later in life and that atrophy of regions involved in central regulation of autonomic function mediate these associations. METHODS: Three-to-four measures of orthostatic blood pressure were obtained from 1997-2003 in a longitudinal cohort of aging, and average systolic orthostatic blood pressure response (ASOBPR) was computed as % change in systolic blood pressure from sit-to-stand measured at one minute post stand. CS was determined in 2010-2012 by clinician-adjudication (n = 240; age = 87.1±2.6; 59% women; 37% black) with a subsample also undergoing concurrent structural neuroimaging (n = 129). Gray matter volume of regions related to autonomic function was measured. Multinomial regression was used to compare ASOBPR in those who were cognitively intact versus those with a diagnosis of mild cognitive impairment or dementia, controlling for demographics, trajectories of seated blood pressure, incident cardiovascular risk/events and medications measured from 1997 to 2012. Models were repeated in the subsample with neuroimaging, before and after adjustment for regional gray matter volume. RESULTS: There was an inverse association between ASOBPR and probability of dementia diagnosis (9% lower probability for each % point higher ASOBPR: OR 0.91, CI95%  = 0.85-0.98; p = 0.01). Associations were similar in the subgroup with neuroimaging before and after adjustment for regional gray matter volume. CONCLUSION: ASOBPR may be an early marker of risk of dementia in older adults living in the community.

Co-Localization of Glia Maturation Factor with NLRP3 Inflammasome and Autophagosome Markers in Human Alzheimer's Disease Brain. - Ahmed, Mohammad Ejaz; Iyer, Shankar; Thangavel, Ramasamy; Kempuraj, Duraisamy; Selvakumar, Govindhasamy Pushpavathi; Raikwar, Sudhanshu P; Zaheer, Smita; Zaheer, Asgar (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a progressive neurodegenerative disease characterized by the presence of intracellular neurofibrillary tangles (NFTs) containing hyperphosphorylated tau, and the extracellular deposition of amyloid plaques (APs) with misfolded amyloid-β (Aβ) peptide. Glia maturation factor (GMF), a highly conserved pro-inflammatory protein, isolated and cloned in our laboratory, has been shown to activate glial cells leading to neuroinflammation and neurodegeneration in AD. We hypothesized that inflammatory reactions promoted by NLRP3-Caspase-1inflammasome pathway trigger dysfunction in autophagy and accumulation of Aβ which is amplified and regulated by GMF in AD. In this study, using immunohistochemical techniques we analyzed components of the NLRP3 inflammasome and autophagy- lysosomal markers in relation to Aβ, p-tau and GMF in human postmortem AD and age-matched non-AD brains. Tissue sections were prepared from the temporal cortex of human postmortem brains. Here, we demonstrate an increased expression of the inflammasome components NLRP3 and Caspase-1 and the products of inflammasome activation IL-1β and IL-18 along with GMF in the temporal cortex of AD brains. These inflammasome components and the pro-inflammatory cytokines co-localized with GMF in the vicinity and periphery of the APs and NFTs. Moreover, using double immunofluorescence staining, AD brain displayed an increase in the autophagy SQSTM1/p62 and LC3 positive vesicles and the lysosomal marker LAMP1 that also co-localized with GMF, Aβ and hyperphosphorylated p-tau. Our results indicate that in AD, the neuroinflammation promoted by the NLRP3 inflammasome may be amplified and regulated by GMF, which further impairs clearance of protein aggregates mediated by the auto-phagosomal pathway.

Combustion-Derived Nanoparticles in Key Brain Target Cells and Organelles in Young Urbanites: Culprit Hidden in Plain Sight in Alzheimer's Disease Development. - González-Maciel, Angelica; Reynoso-Robles, Rafael; Torres-Jardón, Ricardo; Mukherjee, Partha S; Calderón-Garcidueñas, Lilian (J Alzheimers Dis, 2017)
Millions of children and young adults are exposed to fine particulate matter (PM2.5) and ozone, associated with Alzheimer's disease (AD) risk. Mexico City (MC) children exhibit systemic and brain inflammation, low cerebrospinal fluid (CSF) Aβ1-42, breakdown of nasal, olfactory, alveolar-capillary, duodenal, and blood-brain barriers, volumetric and metabolic brain changes, attention and short-term memory deficits, and hallmarks of AD and Parkinson's disease. Airborne iron-rich strongly magnetic combustion-derived nanoparticles (CDNPs) are present in young urbanites' brains. Using transmission electron microscopy, we documented CDNPs in neurons, glia, choroid plexus, and neurovascular units of young MC residents versus matched clean air controls. CDNPs are associated with pathology in mitochondria, endoplasmic reticulum (ER), mitochondria-ER contacts (MERCs), axons,and dendrites. There is a significant difference in size and numbers between spherical CDNPs (>85%) and the angular, euhedral endogenous NPs (<15%). Spherical CDNPs (dogs 21.2±7.1 nm in diameter versus humans 29.1±11.2 nm, p = 0.002) are present in neurons, glia, choroid plexus, endothelium, nasal and olfactory epithelium, and in CSF at significantly higher in numbers in MC residents (p < 0.0001). Degenerated MERCs, abnormal mitochondria, and dilated ER are widespread, and CDNPs in close contact with neurofilaments, glial fibers, and chromatin are a potential source for altered microtubule dynamics, mitochondrial dysfunction, accumulation and aggregation of unfolded proteins, abnormal endosomal systems, altered insulin signaling, calcium homeostasis, apoptotic signaling, autophagy, and epigenetic changes. Highly oxidative, ubiquitous CDNPs constitute a novel path into AD pathogenesis. Exposed children and young adults need early neuroprotection and multidisciplinary prevention efforts to modify the course of AD at early stages.

A Common Variant of IL-6R is Associated with Elevated IL-6 Pathway Activity in Alzheimer's Disease Brains. - Haddick, Patrick C G; Larson, Jessica L; Rathore, Nisha; Bhangale, Tushar R; Phung, Qui T; Srinivasan, Karpagam; Hansen, David V; Lill, Jennie R; Pericak-Vance, Margaret A; Haines, Jonathan; Farrer, Lindsay A; Kauwe, John S; et al. (J Alzheimers Dis, 2017)
The common p.D358A variant (rs2228145) in IL-6R is associated with risk for multiple diseases and with increased levels of soluble IL-6R in the periphery and central nervous system (CNS). Here, we show that the p.D358A allele leads to increased proteolysis of membrane bound IL-6R and demonstrate that IL-6R peptides with A358 are more susceptible to cleavage by ADAM10 and ADAM17. IL-6 responsive genes were identified in primary astrocytes and microglia and an IL-6 gene signature was increased in the CNS of late onset Alzheimer's disease subjects in an IL6R allele dependent manner. We conducted a screen to identify variants associated with the age of onset of Alzheimer's disease in APOE ɛ4 carriers. Across five datasets, p.D358A had a meta P = 3 ×10-4 and an odds ratio = 1.3, 95% confidence interval 1.12 -1.48. Our study suggests that a common coding region variant of the IL-6 receptor results in neuroinflammatory changes that may influence the age of onset of Alzheimer's disease in APOE ɛ4 carriers.

Comparison of Gait Parameters for Predicting Cognitive Decline: The Mayo Clinic Study of Aging. - Savica, Rodolfo; Wennberg, Alexandra M V; Hagen, Clinton; Edwards, Kelly; Roberts, Rosebud O; Hollman, John H; Knopman, David S; Boeve, Bradley F; Machulda, Mary M; Petersen, Ronald C; Mielke, Michelle M (J Alzheimers Dis, 2017)
BACKGROUND: Previous studies reported that slower gait speed might predict cognitive impairment and dementing illnesses, supporting the role of gait speed as a possible subclinical marker of cognitive impairment. However, the predictive value of other gait parameters for cognitive decline is unclear. OBJECTIVE: To investigate and compare the association with, and prediction of, specific gait parameters for cognition in a population-based sample. METHODS: The analysis included 3,426 cognitively normal participants enrolled in the Mayo Clinic Study of Aging. At baseline and every 15 months (mean follow-up = 1.93 years), participants had a study coordinator evaluation, neurological examination, and a neuropsychological assessment using nine tests that covered four domains. Gait parameters were assessed with the GAITRite® instrument. General linear mixed effects models were used to compute the annualized rate of change in cognitive domain z-scores, controlling for age, sex, education, depression, comorbidities, body mass index, APOE ɛ4 allele, and visit number, and excluding individuals with a history of stroke, alcoholism, Parkinson's disease, subdural hematoma, and normal pressure hydrocephalus. RESULTS: Spatial (stride length), temporal (ambulatory time, gait speed, step count, cadence, double support time), and spatiotemporal (cadence) gait parameters, and greater intraindividual variability in stride length, swing time, and stance time were associated with a significant decline in global cognition and in specific domains including memory, executive function, visuospatial, and language. CONCLUSIONS: Spatial, temporal, and spatiotemporal measures of gait and greater variability of gait parameters were associated with and predictive of both global- and domain-specific cognitive decline.

Comprehensive Quantitative Profiling of Tau and Phosphorylated Tau Peptides in Cerebrospinal Fluid by Mass Spectrometry Provides New Biomarker Candidates. - Russell, Claire L; Mitra, Vikram; Hansson, Karl; Blennow, Kaj; Gobom, Johan; Zetterberg, Henrik; Hiltunen, Mikko; Ward, Malcolm; Pike, Ian (J Alzheimers Dis, 2017)
Aberrant tau phosphorylation is a hallmark in Alzheimer's disease (AD), believed to promote formation of paired helical filaments, the main constituent of neurofibrillary tangles in the brain. While cerebrospinal fluid (CSF) levels of total tau and tau phosphorylated at threonine residue 181 (pThr181) are established core biomarkers for AD, the value of alternative phosphorylation sites, which may have more direct relevance to pathology, for early diagnosis is not yet known, largely due to their low levels in CSF and lack of standardized detection methods. To overcome sensitivity limitations for analysis of phosphorylated tau in CSF, we have applied an innovative mass spectrometry (MS) workflow, TMTcalibratortrademark, to enrich and enhance the detection of phosphoproteome components of AD brain tissue in CSF, and enable the quantitation of these analytes. We aimed to identify which tau species present in the AD brain are also detectable in CSF and which, if any, are differentially regulated with disease. Over 75% coverage of full-length (2N4R) tau was detected in the CSF with 47 phosphopeptides covering 31 different phosphorylation sites. Of these, 11 phosphopeptides were upregulated by at least 40%, along with an overall increase in tau levels in the CSF of AD patients relative to controls. Use of the TMTcalibratortrademark workflow dramatically improved our ability to detect tau-derived peptides that are directly related to human AD pathology. Further validation of regulated tau peptides as early biomarkers of AD is warranted and is currently being undertaken.

Conscientiousness is Negatively Associated with Grey Matter Volume in Young APOE ɛ4-Carriers. - Kunz, Lukas; Reuter, Martin; Axmacher, Nikolai; Montag, Christian (J Alzheimers Dis, 2017)
The etiology of late onset Alzheimer's disease (LOAD) depends on multiple factors, among which the APOE ɛ4 allele is the most adverse genetic determinant and conscientiousness represents an influential personality trait. A potential association of both factors with brain structure in young adulthood may constitute a constellation that sets the course toward or against the subtle disease progression of LOAD that starts decades before clinical manifestation. Hence, in the present study, we examined the modulating effects of APOE ɛ4 on the relation between personality dimensions, including conscientiousness, and total grey matter volume (GMV) in young healthy adults using an a priori genotyping design. 105 participants completed an inventory assessing the Five Factor Model of Personality (NEO-FFI) and a structural MRI scan. Total GMV was estimated using both Freesurfer as well as VBM8. Across all participants, total GMV was positively associated with extraversion and negatively related to age. In APOE ɛ4-carriers- but not in APOE ɛ4-non-carriers- conscientiousness was negatively associated with total GMV. In line with the hypothesis of antagonistic pleiotropy of the APOE ɛ4 allele, this result suggests that young APOE ɛ4-carriers with increased total GMV may particularly benefit from cognitive advantages and thus have a lower need to engage in conscientious behavior. In this subset of young APOE ɛ4-carriers, the reduction in conscientiousness could then bring along adverse health behavior in the long run, potentiating the risk for LOAD. Hence, young APOE ɛ4-carriers with increased total GMV may be at a particularly high risk for LOAD.

Cortical Thickness and Depressive Symptoms in Cognitively Normal Individuals: The Mayo Clinic Study of Aging. - Pink, Anna; Przybelski, Scott A; Krell-Roesch, Janina; Stokin, Gorazd B; Roberts, Rosebud O; Mielke, Michelle M; Knopman, David S; Jack, Clifford R; Petersen, Ronald C; Geda, Yonas E (J Alzheimers Dis, 2017)
Altered cortical thickness has been observed in aging and various neurodegenerative disorders. Furthermore, reduced hippocampal volume has been reported in late-life depression. Even mild depressive symptoms are common in the elderly. However, little is known about the structural MRI measures of depressive symptoms in normal cognitive aging. Thus we sought to examine the association between depressive symptoms with cortical thickness and hippocampal volume as measured by brain MRI among community-dwelling participants. We conducted a cross-sectional study derived from the ongoing population-based Mayo Clinic Study of Aging, involving cognitively normal participants (N = 1,507) aged≥70 years. We observed that depressive symptoms were associated with lower global cortical thickness and lower thickness in specific prefrontal and temporal cortical regions, labeled by FreeSurfer software, version 5.3. As expected, the strength of correlation was very small, given that participants were community-dwelling with only mild depressive symptoms. We did not observe associations between hippocampal volume and depressive symptoms. These findings may provide insight into the structural correlates of mild depressive symptoms in elderly participants.

A Critical Assessment of Research on Neurotransmitters in Alzheimer's Disease. - Reddy, P Hemachandra (J Alzheimers Dis, 2017)
The purpose of this mini-forum, "Neurotransmitters and Alzheimer's Disease", is to critically assess the current status of neurotransmitters in Alzheimer's disease. Neurotransmitters are essential neurochemicals that maintain synaptic and cognitive functions in mammals, including humans, by sending signals across pre- to post-synaptic neurons. Authorities in the fields of synapses and neurotransmitters of Alzheimer's disease summarize the current status of basic biology of synapses and neurotransmitters, and also update the current status of clinical trials of neurotransmitters in Alzheimer's disease. This article discusses the prevalence, economic impact, and stages of Alzheimer's dementia in humans.

Cross-Sectional and Longitudinal Cognitive Correlates of FDDNP PET and CSF Amyloid-β and Tau in Parkinson's Disease1. - Buongiorno, Mariateresa; Antonelli, Francesca; Compta, Yaroslau; Fernandez, Yolanda; Pavía, Javier; Lomeña, Francisco; Ríos, José; Ramírez, Isabel; García, José Ramón; Soler, Marina; Cámara, Ana; Fernández, Manel; et al. (J Alzheimers Dis, 2017)
Tau and amyloid-β (Aβ) aggregates have been suggested to play a role in the development of dementia in Parkinson's disease (PD). Positron emission tomography (PET) with [18F]FDDNP and the determination of cerebrospinal fluid (CSF) levels of these proteins constitute a means to visualize in vivo Aβ and tau brain accumulation. Information about longitudinal changes of these CSF and PET biomarkers in PD with regard to progression to dementia is lacking. We assessed the cross-sectional and longitudinal associations of CSF and PET biomarkers of tau and Aβ with PD-related cognitive dysfunction in 6 healthy-controls (HC), 16 patients with PD without dementia (PDND), and 8 PD with dementia (PDD). All subjects underwent comprehensive neuropsychological testing, [18F]FDDNP PET, and CSF Aβ-tau determination. After 18 months, the PDND group was re-assessed clinically and by neuropsychological, PET, and CSF determinations. Cross-sectionally, PDD had higher [18F]FDDNP binding in lateral temporal regions and lower levels of CSF Aβ levels compared to PDND, with a congruent correlation between the [18F]FDDNP binding and CSF Aβ levels. Longitudinally, higher baseline lateral temporal [18F]FDDNP binding was associated to longitudinal worsening in cognitive performances and progression to dementia among subjects classified as PDND at baseline, who additionally disclosed at follow-up an increase in lateral-temporal FDDNP binding, as well as a reduction in CSF Aβ and an increase in CSF tau levels. These results confirm the relevance of these CSF and PET biomarkers to PDD, being specifically the first to show [18F]FDDNP PET as a dementia risk biomarker in PD, along with longitudinal CSF and PET changes over time.

Curcumin Inhibits Tau Aggregation and Disintegrates Preformed Tau Filaments in vitro. - Rane, Jitendra Subhash; Bhaumik, Prasenjit; Panda, Dulal (J Alzheimers Dis, 2017)
The pathological aggregation of tau is a common feature of most of the neuronal disorders including frontotemporal dementia, Parkinson's disease, and Alzheimer's disease. The inhibition of tau aggregation is considered to be one of the important strategies for treating these neurodegenerative diseases. Curcumin, a natural polyphenolic molecule, has been reported to have neuroprotective ability. In this work, curcumin was found to bind to adult tau and fetal tau with a dissociation constant of 3.3±0.4 and 8±1 μM, respectively. Molecular docking studies indicated a putative binding site of curcumin in the microtubule-binding region of tau. Using several complementary techniques, including dynamic light scattering, thioflavin S fluorescence, 90° light scattering, electron microscopy, and atomic force microscopy, curcumin was found to inhibit the aggregation of tau. The dynamic light scattering analysis and atomic force microscopic images revealed that curcumin inhibits the oligomerization of tau. Curcumin also disintegrated preformed tau oligomers. Using Far-UV circular dichroism, curcumin was found to inhibit the β-sheets formation in tau indicating that curcumin inhibits an initial step of tau aggregation. In addition, curcumin inhibited tau fibril formation. Furthermore, the effect of curcumin on the preformed tau filaments was analyzed by atomic force microscopy, transmission electron microscopy, and 90° light scattering. Curcumin treatment disintegrated preformed tau filaments. The results indicated that curcumin inhibited the oligomerization of tau and could disaggregate tau filaments.

Current Approaches and Clinician Attitudes to the Use of Cerebrospinal Fluid Biomarkers in Diagnostic Evaluation of Dementia in Europe. - Miller, Anne-Marie; Balasa, Mircea; Blennow, Kaj; Gardiner, Mary; Rutkowska, Aleksandra; Scheltens, Philip; Teunissen, Charlotte E; Visser, Pieter Jelle; Winblad, Bengt; Waldemar, Gunhild; Lawlor, Brian (J Alzheimers Dis, 2017)
BACKGROUND: BIOMARKAPD seeks to diminish the barriers associated with the clinical use of cerebrospinal fluid (CSF) biomarker analysis by reducing variation in CSF laboratory methodologies and generating consensus recommendations on their clinical interpretation and application for dementia diagnosis. OBJECTIVE: To examine the disparity in practitioner attitudes and clinical practice relating to the use of CSF biomarkers for dementia diagnosis across Europe. METHODS: Clinical dementia experts were surveyed on the prevalence of national consensus guidelines and analytical reimbursement across Europe, their biomarker platform preferences, lumbar puncture methodologies and application of reference values and cut-offs for CSF analysis. RESULTS: 74% of respondents (total n = 51) use CSF biomarkers in clinical practice and 69% perform lumbar punctures on an outpatient basis. Most use CSF biomarkers to diagnose atypical (84%) and early-onset cases of cognitive impairment (71%) and for the differential diagnosis of other dementias (69%). 82% state they are sufficiently informed about CSF biomarkers yet 61% report a lack of national consensus guidelines on their use for dementia diagnosis. 48% of countries represented do not reimburse clinical CSF analysis costs. 43% report using normal reference ranges derived from publications. CONCLUSION: Variations in attitude and practice relating to CSF biomarkers, widely recognised as barriers to their clinical acceptance, remain evident within and between countries across Europe, even in expert centres. These shortcomings must be addressed by developing consensus guidelines on CSF-related methodologies and their clinical application, to further their use for the diagnostic evaluation of dementia.

Cyclic cis-Locked Phospho-Dipeptides Reduce Entry of AβPP into Amyloidogenic Processing Pathway. - Fisher, Carolyn L; Resnick, Ross J; De, Soumya; Acevedo, Lucila A; Lu, Kun Ping; Schroeder, Frank C; Nicholson, Linda K (J Alzheimers Dis, 2017)
The cis/trans isomerization of X-Pro peptide bonds in proteins in some instances acts as a molecular switch in biological pathways. Our prior work suggests that the cis isomer of the phospho-Thr668-Pro669 motif, located in the cytoplasmic domain of the amyloid-β protein precursor (AβPP), is correlated with an increase in amyloidogenic processing of AβPP and production of amyloid-beta (Aβ), the neurotoxic peptide fragment in Alzheimer's disease (AD). We designed a 100% cis-locked cyclic dipeptide composed of cyclized phospho-Thr-Pro (pCDP) as a mimic for this putative pathological conformation, and three phosphate-blocked derivatives (pCDP-diBzl, pCDP-Bzl, and pCDP-diPOM). Two H4 neuroglioma cell lines were established as AD cell models for use in testing these compounds: H4-AβPP695 for stable overexpression of wild-type AβPP695, and H4-BACE1 for stable overexpression of β-site AβPP cleaving enzyme-1 (BACE1). The level of the secreted AβPP fragment resulting from BACE1 activity, sAβPPβ, served as a key proxy for amyloidogenic processing, since cleavage of AβPP by BACE1 is a requisite first step in Aβ production. Of the compounds tested, pCDP-diBzl decreased sAβPPβ levels in both cell lines, while pCDP-diPOM decreased sAβPPβ levels in only H4-BACE1 cells, all with similar dose-dependences and patterns of proteolytic AβPP fragments. Enzymatic assays showed that none of the pCDP derivatives directly inhibit BACE1 catalytic activity. These results suggest a model in which pCDP-diBzl and pCDP-diPOM act at a common point to inhibit entry of AβPP into the amyloidogenic AβPP processing pathway but through different targets, and provide important insights for the development of novel AD therapeutics.

Deficit in Central Auditory Processing as a Biomarker of Pre-Clinical Alzheimer's Disease. - Tuwaig, Miranda; Savard, Mélissa; Jutras, Benoît; Poirier, Judes; Collins, D Louis; Rosa-Neto, Pedro; Fontaine, David; Breitner, John C S (J Alzheimers Dis, 2017)
Prevention of dementia due to Alzheimer's disease (d/AD) requires interventions that slow the disease process prior to symptom onset. To develop such interventions, one needs metrics that assess pre-symptomatic disease progression. Familiar measures of progression include cerebrospinal fluid (CSF) biochemical and imaging analyses, as well as cognitive testing. Changes in the latter can sometimes be difficult to distinguish from effects of "normal" aging. A different approach involves testing of "central auditory processing" (CAP), which enables comprehension of auditory stimuli amidst a distracting background (e.g., conversation in a noisy bar or restaurant). Such comprehension is often impaired in d/AD. Similarly, effortful or diminished auditory comprehension is sometimes reported by cognitively healthy elders, raising the possibility that CAP deficit may be a marker of pre-symptomatic AD. In 187 cognitively and physically healthy members of the aging, AD family history-positive PREVENT-AD cohort, we therefore evaluated whether CAP deficits were associated with known markers of AD neurodegeneration. Such markers included CSF tau concentrations and magnetic resonance imaging volumetric and cortical thickness measures in key AD-related regions. Adjusting for age, sex, education, pure-tone hearing, and APOEɛ4 status, we observed a persistent relationship between CAP scores and CSF tau levels, entorhinal and hippocampal cortex volumes, cortical thickness, and deficits in cognition (Repeatable Battery for Assessment of Neuropsychological Status total score, and several of its index scales). These cross-sectional observations suggest that CAP may serve as a novel metric for pre-symptomatic AD pathogenesis. They are therefore being followed up longitudinally with larger samples.

Deleterious Effect of Butyrylcholinesterase K-Variant in Donepezil Treatment of Mild Cognitive Impairment. - Sokolow, Sophie; Li, Xiaohui; Chen, Lucia; Taylor, Kent D; Rotter, Jerome I; Rissman, Robert A; Aisen, Paul S; Apostolova, Liana G (J Alzheimers Dis, 2017)
BACKGROUND: Donepezil is an acetylcholinesterase inhibitor frequently prescribed for the treatment of mild cognitive impairment (MCI) though not approved by the Food and Drug Administration for this indication. In Alzheimer's disease, butyrylcholinesterase (BChE) activity increases with disease progression and may replace acetylcholinesterase function. The most frequent polymorphism of BChE is the K-variant, which is associated with lower acetylcholine-hydrolyzing activity. BChE-K polymorphism has been studied in Alzheimer's disease progression and donepezil therapy, and has led to contradictory results. OBJECTIVES: To determine whether BChE-K genotype predicts response to donepezil in MCI. METHODS: We examined the association between BChE-K genotype and changes in cognitive function using the data collected during the ADCS vitamin E/donepezil clinical trial in MCI. RESULTS: We found significant interactions between BChE-K genotype and the duration of donepezil treatment, with increased changes in MMSE and CDR-SB scores compared to the common allele in MCI subjects treated during the 3-year trial. We found faster MMSE decline and CDR-SB rise in BChE-K homozygous individuals treated with donepezil compared to the untreated. We observed similar interactions between BChE-K genotype and steeper changes in MMSE and CDR-SB scores in APOE4 carriers treated with donepezil compared to controls. CONCLUSION: BChE-K polymorphisms are associated with deleterious changes in cognitive decline in MCI patients treated with donepezil for 3 years. This indicates that BChE-K genotyping should be performed to help identify subsets of subjects at risk for donepezil therapy, like those carrying APOE4. BChE-K and APOE4 carriers should not be prescribed off-label donepezil therapy for MCI management.

Depressive Symptoms and Tau Accumulation in the Inferior Temporal Lobe and Entorhinal Cortex in Cognitively Normal Older Adults: A Pilot Study. - Gatchel, Jennifer R; Donovan, Nancy J; Locascio, Joseph J; Schultz, Aaron P; Becker, J Alex; Chhatwal, Jasmeer; Papp, Kathryn V; Amariglio, Rebecca E; Rentz, Dorene M; Blacker, Deborah; Sperling, Reisa A; Johnson, Keith A; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Depressive symptoms are common in older adults and associated with increased morbidity and cognitive decline. These symptoms occur during preclinical and prodromal stages of Alzheimer's disease (AD), but their relationship to tau, one of the main AD proteinopathies, is poorly understood. OBJECTIVE: The objective of this study was to investigate the cross-sectional association between depressive symptoms and cerebral tau [18F T807 (also known as 18F-AV-1451) tau positron emission tomography (PET) imaging] in cognitively normal (CN) older adults. METHODS: We measured depressive symptoms using the Geriatric Depression Scale (GDS), and in vivo cerebral tau using T807 PET in 111 CN older adults. We employed general linear regression models to evaluate the relationship of GDS score regressed on entorhinal cortex (EC) or inferior temporal (IT) tau in separate backward elimination models. Other predictors included age, sex, and in secondary analyses, amyloid (Pittsburgh Compound B PET). RESULTS: Higher GDS was significantly associated with greater IT tau (partial r = 0.188, p = 0.050) and marginally associated with greater EC tau (partial r = 0.183, p = 0.055). In additional analyses including both linear and quadratic age terms, we found a significant U-shaped relation of GDS to age (p = 0.001). CONCLUSIONS: Results suggest that IT and EC tau are modestly associated with depressive symptoms in CN older adults. Findings suggest a link between depressive symptoms and tau-mediated neurodegeneration in a region vulnerable in AD. Future longitudinal studies examining the association of more severe depressive symptoms and cerebral tau accumulation are needed to substantiate this finding and to guide prevention and treatment in AD.

Detecting At-Risk Alzheimer's Disease Cases. - Fladby, Tormod; Pålhaugen, Lene; Selnes, Per; Waterloo, Knut; Bråthen, Geir; Hessen, Erik; Almdahl, Ina Selseth; Arntzen, Kjell-Arne; Auning, Eirik; Eliassen, Carl Fredrik; Espenes, Ragna; Grambaite, Ramune; et al. (J Alzheimers Dis, 2017)
While APOEɛ4 is the major genetic risk factor for Alzheimer's disease (AD), amyloid dysmetabolism is an initial or early event predicting clinical disease and is an important focus for secondary intervention trials. To improve identification of cases with increased AD risk, we evaluated recruitment procedures using pathological CSF concentrations of Aβ42 (pAβ) and APOEɛ4 as risk markers in a multi-center study in Norway. In total, 490 subjects aged 40-80 y were included after response to advertisements and media coverage or memory clinics referrals. Controls (n = 164) were classified as normal controls without first-degree relatives with dementia (NC), normal controls with first-degree relatives with dementia (NCFD), or controls scoring below norms on cognitive screening. Patients (n = 301) were classified as subjective cognitive decline or mild cognitive impairment. Subjects underwent a clinical and cognitive examination and MRI according to standardized protocols. Core biomarkers in CSF from 411 and APOE genotype from 445 subjects were obtained. Cases (both self-referrals (n = 180) and memory clinics referrals (n = 87)) had increased fractions of pAβ and APOEɛ4 frequency compared to NC. Also, NCFD had higher APOEɛ4 frequencies without increased fraction of pAβ compared to NC, and cases recruited from memory clinics had higher fractions of pAβ and APOEɛ4 frequency than self-referred. This study shows that memory clinic referrals are pAβ enriched, whereas self-referred and NCFD cases more frequently are pAβ negative but at risk (APOEɛ4 positive), suitable for primary intervention.

Development of Nasal Lipid Nanocarriers Containing Curcumin for Brain Targeting. - Vaz, Gustavo Richter; Hädrich, Gabriela; Bidone, Juliana; Rodrigues, Jamile Lima; Falkembach, Mariana Corrêa; Putaux, Jean-Luc; Hort, Mariana Appel; Monserrat, José Maria; Varela Junior, Antônio Sergio; Teixeira, Helder Ferreira; Muccillo-Baisch, Ana Luiza; Horn, Ana Paula; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Curcumin (CUR) has properties that can be useful for the treatment of Alzheimer's disease. Such properties are the inhibition of amyloid-β-protein (Aβ) aggregation, Aβ-induced inflammation, and activities of β-secretase and acetylcholinesterase. However, previous studies have revealed that CUR exhibited low bioavailability and difficulties in reaching the brain. OBJECTIVE: To overcome such drawbacks, this study aims at developing nasal lipid nanocarriers loaded with CUR to effectively target the brain. METHODS: The lipid nanocarriers (NE) were prepared using the hot solvent diffusion associated with the phase inversion temperature methods. Physico-chemical and morphological characterizations and in vitro drug release of the nanocarriers were carried out. The CUR permeation/retention was analyzed in Franz-type diffusion cell using porcine nasal mucosa. Confocal laser scan and histopathological studies were also performed. RESULTS: The results showed that the NE sizes ranged between 18 nm and 44 nm with negative zeta potential. The CUR content ranged from 0.24 to 1.50 mg/mL with an encapsulation efficiency of 99%. The profiles of CUR release indicated a biphasic kinetics. CUR-NE permeation across the porcine nasal mucosa was higher when compared to free CUR. These results have also been validated through an analysis on a confocal microscopy. In addition, no toxicity on the nasal mucosa has been observed in a histopathological analysis. CONCLUSION: These results suggest that it is possible to develop NEs with a high content of CUR and small particle size. Such an encapsulation increases the potential of CUR permeation across the porcine nasal mucosa.

Diabetes and Alzheimer's Disease: Can Elevated Free Copper Predict the Risk of the Disease? - Squitti, Rosanna; Mendez, Armando J; Simonelli, Ilaria; Ricordi, Camillo (J Alzheimers Dis, 2017)
BACKGROUND: Defective copper regulation, primarily referred to as chelatable redox active Cu(II), has been involved in the etiology of diabetes, and Alzheimer's disease (AD). OBJECTIVES: However, no study has determined levels of labile copper non-bound to ceruloplasmin (non-Cp Cu, also known as 'free' copper) in the blood of subjects with diabetes compared with that of AD patients. METHODS: To this aim, values of non-Cp Cu were measured in 25 Type 1 (T1D) and 31 Type 2 (T2D) subjects and in28 healthy controls, along with measurements of C-reactive protein, glycated hemoglobin A1c, cholesterol, and triglycerides. Non-Cp Cu levels were compared with those of an AD group previously studied. RESULTS: T2D subjects had significantly higher non-Cp Cu levels than Controls and T1D subjects (both p < 0.001 after adjusting for age, sex, and body mass index). A multinomial logistic model revealed that a one unit standard deviation increase of non-Cp Cu increased the relative risk of having T2D by 9.64 with respect to Controls (95% CI: 2.86-32.47). The comparison of non-Cp Cu levels in T2D with those of an AD population previously studied shows rising blood non-Cp Cu copper levels from Controls to T2D and AD. CONCLUSION: These results suggest the involvement of catalytically-active Cu(II) and glucose dysregulation in oxidative stress reactions leading to tissue damage in both diseases.

Diabetes is Not Associated with Alzheimer's Disease Neuropathology. - Dos Santos Matioli, Maria Niures Pimentel; Suemoto, Claudia Kimie; Rodriguez, Roberta Diehl; Farias, Daniela Souza; da Silva, Magnólia Moreira; Leite, Renata Elaine Paraizo; Ferretti-Rebustini, Renata Eloah Lucena; Farfel, José Marcelo; Pasqualucci, Carlos Augusto; Jacob Filho, Wilson; Arvanitakis, Zoe; Naslavsky, Michel Satya; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Previous evidence linking diabetes to Alzheimer's disease (AD) neuropathology is mixed and scant data are available from low- and middle-income countries. OBJECTIVE: To investigate the association between diabetes and AD neuropathology in a large autopsy study of older Brazilian adults. METHODS: In this cross-sectional study, diabetes was defined by diagnosis during life or use of antidiabetic medication. A standardized neuropathological examination was performed using immunohistochemistry. The associations of diabetes with Consortium to Establish and Registry for Alzheimer Disease (CERAD) scores for neuritic plaques and Braak-Braak (BB) scores for neurofibrillary tangles were investigated using multivariable ordinal logistic regression. We investigated effect modification of education, race, and APOE on these associations. RESULTS: Among 1,037 subjects (mean age = 74.4±11.5 y; mean education = 4.0±3.7 y; 48% male, 61% White), diabetes was present in 279 subjects. Diabetes was not associated with BB (OR = 1.12, 95% CI = 0.81-1.54, p = 0.48) or with CERAD (OR = 0.97, 95% CI = 0.68-1.38, p = 0.86) scores on analyses adjusted for sociodemographic and clinical variables. We observed effect modification by the APOE allele ɛ4 on the association between diabetes mellitus and BB scores. CONCLUSION: No evidence of an association between diabetes and AD neuropathology was found in a large sample of Brazilians; however, certain subgroups, such as APOE allele ɛ4 carriers, had higher odds of accumulation of neurofibrillary tangles.

Diagnostic Accuracy of a Combined Analysis of Cerebrospinal Fluid t-PrP, t-tau, p-tau, and Aβ42 in the Differential Diagnosis of Creutzfeldt-Jakob Disease from Alzheimer's Disease with Emphasis on Atypical Disease Variants. - Abu Rumeileh, Samir; Lattanzio, Francesca; Stanzani Maserati, Michelangelo; Rizzi, Romana; Capellari, Sabina; Parchi, Piero (J Alzheimers Dis, 2017)
According to recent studies, the determination of cerebrospinal fluid (CSF) total tau (t-tau)/phosphorylated tau (p-tau) ratio and total prion protein (t-PrP) levels significantly improves the accuracy of the diagnosis of Alzheimer's disease (AD) in atypical cases with clinical or laboratory features mimicking Creutzfeldt-Jakob disease (CJD). However, this has neither been validated nor tested in series including atypical CJD variants. Furthermore, the added diagnostic value of amyloid-β (Aβ)42 remains unclear. To address these issues, we measured t-PrP, 14-3-3, t-tau, p-tau, and Aβ 42 CSF levels in 45 typical and 44 atypical/rapidly progressive AD patients, 54 typical and 54 atypical CJD patients, and 33 controls. CJD patients showed significantly lower CSF t-PrP levels than controls and AD patients. Furthermore, atypical CJD was associated with lower t-PrP levels in comparison to typical CJD. T-tau, 14-3-3, or t-PrP alone yielded, respectively, 80.6, 63.0, and 73.0% sensitivity and 75.3, 92.1, and 75% specificity in distinguishing AD from CJD. On receiver operating characteristic (ROC) curve analyses of biomarker combinations, the (t-tau×Aβ 42)/(p-tau×t-PrP) ratio achieved the best accuracy, with 98.1% sensitivity and 97.7% specificity overall, and 96.2% sensitivity and 95.5% specificity for the "atypical" disease groups. Our results show that the combined analysis of CSF t-PrP, t-tau, p-tau, and Aβ 42 is clinically useful in the differential diagnosis between CJD and AD. Furthermore, the finding of reduced CSF t-PrP levels in CJD patients suggest that, likewise Aβ 42 in AD, CSF t-PrP levels reflect the extent of PrPc conversion into abnormal PrP (PrPSc) and the burden of PrPSc deposition in CJD.

The Diagnostic and Prognostic Value of Neuropsychological Assessment in Memory Clinic Patients. - Jansen, Willemijn J; Handels, Ron L H; Visser, Pieter Jelle; Aalten, Pauline; Bouwman, Femke; Claassen, Jurgen; van Domburg, Peter; Hoff, Erik; Hoogmoed, Jan; Leentjens, Albert F G; Rikkert, Marcel Olde; Oleksik, Ania M; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Neuropsychological testing has long been embedded in daily clinical practice at memory clinics but the added value of a complete neuropsychological assessment (NPA) to standard clinical evaluation is unknown. OBJECTIVE: To evaluate the added diagnostic and prognostic value of NPA to clinical evaluation only in memory clinic patients. METHODS: In 221 memory clinic patients of a prospective cohort study, clinical experts diagnosed clinical syndrome (subjective cognitive impairment (SCI), mild cognitive impairment (MCI), or dementia) and etiology (Alzheimer's disease (AD) or no AD), and provided a prognosis of disease course (decline or no decline) before and after results of NPA were made available. The reference standard was a panel consensus based on all clinical information at baseline and up to 2 follow-up assessments. RESULTS: With NPA data available, clinicians changed their initial syndromal diagnosis in 22% of patients, and the etiological diagnosis as well as the prognosis in 15%. This led to an increase in correctly classified cases of 18% for syndromal diagnosis, 5% for etiological diagnosis, and 1% for prognosis. NPA data resulted in the largest improvement in patients initially classified as SCI (syndrome: 93.3% (n = 14) correctly reclassified, etiology: net reclassification improvement [NRI] = 0.61, prognosis: NRI = 0.13) or MCI (syndrome: 89.3% (n = 23) correctly reclassified, etiology: NRI = 0.17, prognosis: NRI = 0.14), while there was no improvement in patients with dementia (syndrome: 100% (n = 1) correctly reclassified, etiology: NRI = -0.05, prognosis: NRI = -0.06). Overall, inclusion of NPA in the diagnostic process increased confidence in all diagnoses with 6-7%. CONCLUSION: Administration of a complete NPA after standard clinical evaluation has added value for diagnosing cognitive syndrome and its underlying etiology in patients regarded as non-demented based on the first clinical impression.

Diagnostic and Prognostic Value of the Combination of Two Measures of Verbal Memory in Mild Cognitive Impairment due to Alzheimer's Disease. - Sala, Isabel; Illán-Gala, Ignacio; Alcolea, Daniel; Sánchez-Saudinós, Ma Belén; Salgado, Sergio Andrés; Morenas-Rodriguez, Estrella; Subirana, Andrea; Videla, Laura; Clarimón, Jordi; Carmona-Iragui, María; Ribosa-Nogué, Roser; Blesa, Rafael; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Episodic memory impairment is the core feature of typical Alzheimer's disease. OBJECTIVE: To evaluate the performance of two commonly used verbal memory tests to detect mild cognitive impairment due to Alzheimer's disease (MCI-AD) and to predict progression to Alzheimer's disease dementia (AD-d). METHODS: Prospective study of MCI patients in a tertiary memory disorder unit. Patients underwent an extensive neuropsychological battery including two tests of declarative verbal memory: The Free and Cued Selective Reminding Test (FCSRT) and the word list learning task from the Consortium to Establish a Registry for Alzheimer's disease (CERAD-WL). Cerebrospinal fluid (CSF) was obtained from all patients and MCI-AD was defined by means of the t-Tau/Aβ1-42 ratio. Logistic regression analyses tested whether the combination of FCSRT and CERAD-WL measures significantly improved the prediction of MCI-AD. Progression to AD-d was analyzed in a Cox regression model. RESULTS: A total of 202 MCI patients with a mean follow-up of 34.2±24.2 months were included and 98 (48.5%) met the criteria for MCI-AD. The combination of FCSRT and CERAD-WL measures improved MCI-AD classification accuracy based on CSF biomarkers. Both tests yielded similar global predictive values (59.9-65.3% and 59.4-62.8% for FCSRT and CERAD-WL, respectively). MCI-AD patients with deficits in both FCSRT and CERAD-WL had a faster progression to AD-d than patients with deficits in only one test. CONCLUSIONS: The combination of FCSRT and CERAD-WL improves the classification of MCI-AD and defines different prognostic profiles. These findings have important implications for clinical practice and the design of clinical trials.

Discriminative Properties of Hippocampal Hypoperfusion in Marijuana Users Compared to Healthy Controls: Implications for Marijuana Administration in Alzheimer's Dementia. - Amen, Daniel G; Darmal, Borhan; Raji, Cyrus A; Bao, Weining; Jorandby, Lantie; Meysami, Somayeh; Raghavendra, Cauligi S (J Alzheimers Dis, 2017)
BACKGROUND: Few studies have evaluated the impact of marijuana use on regional cerebral blood flow. OBJECTIVE: To determine whether perfusion in specific brain regions on functional neuroimaging, including those affected by Alzheimer's disease pathology, are abnormal in marijuana users compared to controls. METHOD: Persons with a diagnosis of cannabis use disorder by DSM-IV and DSM-V criteria (n = 982) were compared to controls (n = 92) with perfusion neuroimaging with SPECT at rest and at a concentration task. Perfusion estimates were quantified using a standard atlas. Cerebral perfusion differences were calculated using one-way ANOVA. Diagnostic separation was determined with discriminant analysis of all subjects. Feature selection with a minimum redundancy maximum relevancy (mRMR) identified predictive regions in a subset of marijuana users (n = 436) with reduced psychiatric co-morbidities. RESULTS: Marijuana users showed lower cerebral perfusion on average (p < 0.05). Discriminant analysis distinguished marijuana users from controls with correct classification of 96% and leave one out cross-validation of 92%. With concentration SPECT regions, there was correct classification of 95% with a leave-one-out cross validation of 90%. AUC analysis for concentration SPECT regions showed 95% accuracy, 90% sensitivity, and 83% specificity. The mRMR analysis showed right hippocampal hypoperfusion on concentration SPECT imaging was the most predictive in separating marijuana subjects from controls. CONCLUSION: Multiple brain regions show low perfusion on SPECT in marijuana users. The most predictive region distinguishing marijuana users from healthy controls, the hippocampus, is a key target of Alzheimer's disease pathology. This study raises the possibility of deleterious brain effects of marijuana use.

Do Hearing Aids Influence Behavioral and Psychological Symptoms of Dementia and Quality of Life in Hearing Impaired Alzheimer's Disease Patients and Their Caregivers? - Adrait, Arnaud; Perrot, Xavier; Nguyen, Marie-France; Gueugnon, Marine; Petitot, Charles; Collet, Lionel; Roux, Adeline; Bonnefoy, Marc (J Alzheimers Dis, 2017)
BACKGROUND: It has been suggested that age-related hearing loss (ARHL) and Alzheimer's disease (AD) are commonly associated. OBJECTIVE: The Alzheimer Disease, Presbycusis and Hearing Aids (ADPHA) clinical trial assessed the influence of hearing aids (HAs) on patients affected by ARHL and AD, as judged by behavioral symptoms and functional abilities, as well as patient and caregiver quality of life (QoL). METHODS: A multicenter double-blind randomized placebo-controlled trial, with a semi-crossover procedure over 12 months, was conducted from 2006 to 2012. For the first 6 months, the active group was treated with active HAs and the placebo group with inactive HAs. For the last 6 months, HAs in the placebo group were activated. Assessment was conducted at baseline, 6 months, and 12 months. We performed intergroup and intragroup comparisons. Behavioral symptoms were assessed by neuropsychiatric inventory (NPI), functional abilities by instrumental activities of daily living, and QoL by Zarit, Alzheimer's disease related quality of life, and simplified Duke scales. RESULTS: Fifty-one patients were included and randomized: 22 in active group (mean NPI 17.6; mean age 83±6.2) and 26 in placebo group (mean NPI 25.8; mean age 82.3±7.2) were fitted with HAs. At 6-month follow-up, all scores worsened without significant difference between the two groups. In placebo group, activation of HAs had no effect on the change of these scores. CONCLUSION: These findings do not provide evidence of improvement in behavioral symptoms, functional status, or QoL of hearing impaired AD patients and their caregivers after 6 months of HA use. However, we cannot exclude that HAs may have a positive effect in patients aged less than 75 years.

Does the Female Advantage in Verbal Memory Contribute to Underestimating Alzheimer's Disease Pathology in Women versus Men? - Sundermann, Erin E; Biegon, Anat; Rubin, Leah H; Lipton, Richard B; Landau, Susan; Maki, Pauline M (J Alzheimers Dis, 2017)
There is a growing recognition of sex differences in Alzheimer's disease (AD). Females show an advantage over males on tests of verbal memory, which are used to diagnose AD and its precursor, amnestic mild cognitive impairment (aMCI). Women retain this advantage in aMCI despite reduced hippocampal volume and temporal lobe glucose metabolism. Here we examined whether this female advantage endures despite evidence of AD-specific pathology, cortical amyloid-β (Aβ) deposition measured with [18F]AV45 (florbetapir) positron emission tomography. Participants with normal cognition (N = 304), aMCI (N = 515), and AD dementia (N = 175) were drawn from the Alzheimer's Disease Neuroimaging Initiative (ADNI). Across and within diagnostic groups, we conducted linear regressions to examine the interaction of sex with cortical Aβ burden on immediate and delayed recall on the Rey Auditory Verbal Learning Test (RAVLT) adjusting for age, education, and APOE4. In the overall group, sex by cortical Aβ interaction was significant for delayed recall only. Overall, delayed recall performance was significantly better in women versus men among those with low to moderate Aβ burden, but women and men performed similarly among those with high Aβ burden. In diagnosis-stratified analyses, a significant sex by cortical Aβ interaction was observed for delayed recall in the aMCI group, but not in the normal or AD dementia groups. Thus, women maintain a verbal memory advantage over men in aMCI despite similar levels of AD pathology. Although this advantage may benefit women by delaying verbal memory impairment until more advanced pathology, it may also delay diagnosis of aMCI and treatment intervention.

Dynamics of Frailty and Cognition After Age 50: Why It Matters that Cognitive Decline is Mostly Seen in Old Age. - Godin, Judith; Armstrong, Joshua J; Rockwood, Kenneth; Andrew, Melissa K (J Alzheimers Dis, 2017)
BACKGROUND: Frailty has been considered an antecedent and, to a lesser extent, an outcome of cognitive impairment. Both frailty and cognitive impairment are multiply determined and each is strongly related to age, making it likely that the two interact, especially as people age. In consequence, understanding their interaction and co-occurrence can offer insight into pathophysiology, prevention, and management. OBJECTIVE: To examine the nature of the relationship between frailty and cognitive impairment using longitudinal data from the Survey of Health Aging and Retirement in Europe (SHARE), assessing for bidirectionality. METHODS: We conducted secondary analyses using data from the first two waves of SHARE. The sample (N = 11,941) was randomly split into two halves: one half for model development and one half for model confirmation. We used a 65 deficit Frailty Index and combined 5 cognitive deficits into a global cognitive impairment index. Cross-lagged path analysis within a structural equation modelling framework was used to examine the bi-directional relationship between the two measures. RESULTS: After controlling for age, sex, social vulnerability, education, and initial cognitive impairment, each 0.10 increase in baseline frailty was associated with a 0.01 increase in cognitive impairment at follow-up (p < 0.001). Likewise, each 0.1 increase in baseline cognitive impairment was associated with a 0.003 increase frailty at follow-up (p < 0.01). CONCLUSION: Our findings underscore the importance of considering cognitive impairment in the context of overall health. Many people with dementia are likely to have other health problems, which need to be considered in concert to achieve optimal health outcomes.

Early Detection of Learning Difficulties when Confronted with Novel Information in Preclinical Alzheimer's Disease Stage 1. - Tort-Merino, Adrià; Valech, Natalia; Peñaloza, Claudia; Grönholm-Nyman, Petra; León, María; Olives, Jaume; Estanga, Ainara; Ecay-Torres, Mirian; Fortea, Juan; Martínez-Lage, Pablo; Molinuevo, José L; Laine, Matti; et al. (J Alzheimers Dis, 2017)
We employed a highly demanding experimental associative learning test (the AFE-T) to explore memory functioning in Preclinical Alzheimer's Disease stage 1 (PreAD-1) and stage 2 (PreAD-2). The task consisted in the learning of unknown object/name pairs and our comprehensive setup allowed the analysis of learning curves, immediate recall, long-term forgetting rates at one week, three months, and six months, and relearning curves. Forty-nine cognitively healthy subjects were included and classified according to the presence or absence of abnormal CSF biomarkers (Control, n = 31; PreAD-1, n = 14; PreAD-2, n = 4). Control and PreAD-1 performances on the experimental test were compared by controlling for age and education. These analyses showed clear learning difficulties in PreAD-1 subjects (F = 6.98; p = 0.01). Between-group differences in long-term forgetting rates were less notable, reaching statistical significance only for the three-month cued forgetting rate (F = 4.83; p = 0.03). Similarly, relearning sessions showed only statistical trends between the groups (F = 3.22; p = 0.08). In the whole sample, significant correlations between CSF Aβ42/tau ratio and the AFE-T were found, both in the total learning score (r = 0.52; p < 0.001) and in the three-month cued forgetting rate (r = -0.38; p < 0.01). Descriptive subanalyses involving PreAD-2 suggested greater learning and recall difficulties in these subjects when compared with the PreAD-1 group. The present results suggest that explicit learning difficulties when binding information could be one of the earliest signs of the future emergence of episodic memory difficulties on the Alzheimer's disease continuum. Our findings indicate that the AFE-T is a sensitive test, capable of detecting subtle memory difficulties in PreAD-1.

Effect of APOE Genotype on Amyloid Deposition, Brain Volume, and Memory in Cognitively Normal Older Individuals. - Lim, Yen Ying; Williamson, Robert; Laws, Simon M; Villemagne, Victor L; Bourgeat, Pierrick; Fowler, Christopher; Rainey-Smith, Stephanie; Salvado, Olivier; Martins, Ralph N; Rowe, Christopher C; Masters, Colin L; Maruff, Paul (J Alzheimers Dis, 2017)
BACKGROUND: The association between the apolipoprotein E (APOE) ɛ4 allele and high risk of developing Alzheimer's disease (AD) dementia before the age of 80 has been recognized for over 30 years. However, the timing and mode of action of APOE is not understood, nor has there been a detailed analysis of the effect of APOE genotype on memory, hippocampal volume, and amyloid-β (Aβ) levels in cognitively normal adults. OBJECTIVE: Examine the effect of APOE allelic genotype on the relationship between Aβ levels, hippocampal volume, and memory in cognitively normal adults. METHODS: This is a cross-sectional study of 989 cognitively normal older adults enrolled in the Australian Imaging, Biomarkers and Lifestyle (AIBL) study, all of whom underwent APOE genotyping and memory assessment. A subset of this group underwent PET neuroimaging for Aβ (n = 585) and MRI for hippocampal volume (n = 303). RESULTS: APOEɛ4 homozygotes (ɛ4/ɛ4) showed significantly worse episodic memory and higher Aβ levels than ɛ4 heterozygotes. The relationship between increasing Aβ levels and worse episodic memory was significant for ɛ3 homozygotes (ɛ3/ɛ3), ɛ4 heterozygotes, and strongest for ɛ4 homozygotes. There were no differences in hippocampal volume between APOE groups; the relationship between smaller hippocampal volume and worse episodic memory was significant only for ɛ4 homozygotes. CONCLUSION: APOE acts in a co-dominant fashion on Aβ levels, episodic memory, and hippocampal volume in cognitively normal older adults. APOEɛ4 is central to the events that lead to AD in cognitively normal older adults, likely through a quantitative role in the disruption of Aβ clearance.

Effect of Attention Training in Mild Cognitive Impairment Patients with Subcortical Vascular Changes: The RehAtt Study. - Pantoni, Leonardo; Poggesi, Anna; Diciotti, Stefano; Valenti, Raffaella; Orsolini, Stefano; Della Rocca, Eleonora; Inzitari, Domenico; Mascalchi, Mario; Salvadori, Emilia (J Alzheimers Dis, 2017)
BACKGROUND AND OBJECTIVE: Mild cognitive impairment (MCI) patients with small vessel disease (SVD) are at high dementia risk. We tested the effects of cognitive rehabilitation in these patients using the Attention Process Training-II (APT-II) program in a single-blinded, randomized clinical trial. METHODS: Patients were randomized to APT-II or standard care and evaluated at baseline, 6, and 12 months with functional, quality of life, cognitive tests, and resting state functional MRI (rsfMRI). RESULTS: Forty-six patients were enrolled and 43 (mean±SD age 75.1±6.8) completed the study. No change was seen in functionality and quality of life between treated and non-treated patients. However, the Rey Auditory-Verbal Learning Test immediate recall showed a significant improvement in treated compared to non-treated group (change score 6 versus 12 months: 1.8±4.9 and -1.4±3.8, p = 0.021; baseline versus 12 months: 3.8±6.1 and 0.2±4.4, p = 0.032). A higher proportion of treated patients had stable/better evaluation compared to non-treated group on Visual search test (6 versus 12 months: 95% versus 71%, p = 0.038) and Rey-Osterrieth Complex Figure copy (6 versus 12 months: 95% versus 67%, p = 0.027). RsfMRI, performed in a subsample, showed that the difference between follow-up and baseline in synchronization of activity in cerebellar areas was significantly greater in treated than in non-treated patients. CONCLUSION: We were unable to show a significant effect in quality of life or functional status in treated patients with MCI and SVD. However, APT-II produces some beneficial effects in focused attention and working memory and seems to increase activity in brain circuits involved in cognitive processes.

The Effect of the Association between Donepezil and Choline Alphoscerate on Behavioral Disturbances in Alzheimer's Disease: Interim Results of the ASCOMALVA Trial. - Carotenuto, Anna; Rea, Raffaele; Traini, Enea; Fasanaro, Angiola Maria; Ricci, Giovanna; Manzo, Valentino; Amenta, Francesco (J Alzheimers Dis, 2017)
BACKGROUND: Behavioral and psychological symptoms of dementia (BPSD) are a group of psychological reactions, psychiatric symptoms, and behaviors commonly found in Alzheimer's disease (AD). Four clusters of BPSD have been described: mood disorders (depression, anxiety, and apathy), psychotic symptoms (delusions and hallucinations), aberrant motor behaviors (pacing, wandering, and other purposeless behaviors), and inappropriate behaviors (agitation, disinhibition, and euphoria). Most of them are attributed to acetylcholine deficiency. OBJECTIVE: To evaluate if a higher amount of acetylcholine obtained by associating donepezil and choline alphoscerate might have a favorable effect on BPSD. METHODS: BPSD were measured at baseline and after 24 months in 113 mild/moderate AD patients, included in the double-blind randomized trial ASCOMALVA, by the Neuropsychiatric Inventory (NPI). Two matched groups were compared: group A treated with donepezil (10 mg/day) plus choline alphoscerate (1200 mg/day), and group B treated with donepezil (10 mg/day) plus placebo. RESULTS: Data of NPI revealed a significant decrease of BPSD severity and distress of the caregiver in patients of group A compared with group B. Mood disorders (depression, anxiety and apathy) were significantly decreased in subjects treated with donepezil and choline alphoscerate, while their severity and frequency was increased in the other group. CONCLUSIONS: Patients treated with donepezil plus choline alphoscerate showed a lower level of behavioral disturbances than subjects treated with donepezil only, suggesting that the association can have beneficial effects.

Effect Size Analyses of Souvenaid in Patients with Alzheimer's Disease. - Cummings, Jeffrey; Scheltens, Philip; McKeith, Ian; Blesa, Rafael; Harrison, John E; Bertolucci, Paulo H F; Rockwood, Kenneth; Wilkinson, David; Wijker, Wouter; Bennett, David A; Shah, Raj C (J Alzheimers Dis, 2017)
BACKGROUND: Souvenaid® (uridine monophosphate, docosahexaenoic acid, eicosapentaenoic acid, choline, phospholipids, folic acid, vitamins B12, B6, C, and E, and selenium), was developed to support the formation and function of neuronal membranes. OBJECTIVE: To determine effect sizes observed in clinical trials of Souvenaid and to calculate the number needed to treat to show benefit or harm. METHODS: Data from all three reported randomized controlled trials of Souvenaid in Alzheimer's disease (AD) dementia (Souvenir I, Souvenir II, and S-Connect) and an open-label extension study were included in analyses of effect size for cognitive, functional, and behavioral outcomes. Effect size was determined by calculating Cohen's d statistic (or Cramér's V method for nominal data), number needed to treat and number needed to harm. Statistical calculations were performed for the intent-to-treat populations. RESULTS: In patients with mild AD, effect sizes were 0.21 (95% confidence intervals: -0.06, 0.49) for the primary outcome in Souvenir II (neuropsychological test battery memory z-score) and 0.20 (0.10, 0.34) for the co-primary outcome of Souvenir I (Wechsler memory scale delayed recall). No effect was shown on cognition in patients with mild-to-moderate AD (S-Connect). The number needed to treat (6 and 21 for Souvenir I and II, respectively) and high number needed to harm values indicate a favorable harm:benefit ratio for Souvenaid versus control in patients with mild AD. CONCLUSIONS: The favorable safety profile and impact on outcome measures converge to corroborate the putative mode of action and demonstrate that Souvenaid can achieve clinically detectable effects in patients with early AD.

Effects of Alzheimer's Disease-Associated Risk Loci on Amyloid-β Accumulation in the Brain of Idiopathic Normal Pressure Hydrocephalus Patients. - Laiterä, Tiina; Paananen, Jussi; Helisalmi, Seppo; Sarajärvi, Timo; Huovinen, Joel; Laitinen, Marjo; Rauramaa, Tuomas; Alafuzoff, Irina; Remes, Anne M; Soininen, Hilkka; Haapasalo, Annakaisa; Jääskeläinen, Juha E; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Idiopathic normal pressure hydrocephalus (iNPH) is a dementing condition featuring characteristic symptoms, ventriculomegaly, and normal or slightly elevated cerebrospinal fluid pressure. In Alzheimer's disease (AD) patients, diffuse aggregates of amyloid-β (Aβ) and neurofibrillary hyperphosphorylated tau are detected in the neocortex of the brain, while similar accumulation of Aβ is also detected in iNPH. Recent genome-wide association studies have identified several novel risk loci for AD, potentially affecting Aβ-related cellular processes. Apart from the apolipoprotein E ɛ4 allele (APOE4), the risk effect of single loci is low, emphasizing the importance of the polygenic risk score approach when assessing the combined effects. OBJECTIVE: To study the effects of AD-associated individual and polygenic risk score of single nucleotide polymorphisms (SNPs) on the accumulation of Aβ in the brain samples of iNPH patients. METHODS: A sample set of frontal cortex biopsies from 188 iNPH patients were divided into two groups according to the Aβ pathology. After the genotyping of the AD-associated risk loci, polygenic risk score was calculated for each iNPH patient and subsequently analyzed in relation to Aβ deposition. RESULTS: Apart from the APOE4, none of the SNPs revealed a statistically significant effect on the accumulation of Aβ in iNPH. Also, the non-APOE4 polygenic risk score did not associate with Aβ deposition. CONCLUSION: Novel AD-associated risk genes have no significant effect on Aβ accumulation in the brain of iNPH patients. However, APOE4 affects the Aβ deposition in the brain of iNPH and AD patients in a similar manner.

Effects of Exercise on Cognitive Function in Older People with Dementia: A Randomized Controlled Trial. - Toots, Annika; Littbrand, Håkan; Boström, Gustaf; Hörnsten, Carl; Holmberg, Henrik; Lundin-Olsson, Lillemor; Lindelöf, Nina; Nordström, Peter; Gustafson, Yngve; Rosendahl, Erik (J Alzheimers Dis, 2017)
BACKGROUND: Although physical exercise has been suggested to influence cognitive function, previous exercise studies show inconsistent results in people with dementia. OBJECTIVES: To investigate effects of exercise on cognitive function in people with dementia. METHOD: The Umeå Dementia and Exercise (UMDEX) study, a cluster-randomized controlled trial, was set in 16 nursing homes in Umeå, Sweden. One hundred-and-forty-one women and 45 men with dementia; mean age of 85 y and mean Mini-Mental State Examination (MMSE) score of 15, were randomized to a High-Intensity Functional Exercise program or a seated attention control activity. Blinded assessors measured global cognitive function using the MMSE and the Alzheimer's disease Assessment Scale - Cognitive subscale (ADAS-Cog), and executive function using Verbal fluency (VF) at baseline and 4 months (directly after intervention completion), and MMSE and VF at 7 months. RESULTS: Linear mixed models showed no between-group effects in mean difference from baseline (95% confidence intervals, CI) at 4 months in MMSE (-0.27; 95% CI -1.4 to 0.87, p = 0.644), ADAS-Cog (-1.04, 95% CI -4 to 1.92, p = 0.491), or VF (-0.53, 95% CI -1.42 to 0.35, p = 0.241) or at 7 months in MMSE (-1.15, 95% CI -2.32 to 0.03, p = 0.056) or VF (-0.18, 95% CI -1.09 to 0.74, p = 0.707). CONCLUSION: A 4-month, high-intensity functional exercise program had no superior effects on global cognition or executive function in people with dementia living in nursing homes when compared with an attention control activity.

Effects of Multiple Genetic Loci on Age at Onset in Frontotemporal Dementia. - Ferrari, Raffaele; Grassi, Mario; Graziano, Francesca; Palluzzi, Fernando; Archetti, Silvana; Bonomi, Elisa; Bruni, Amalia C; Maletta, Raffaele G; Bernardi, Livia; Cupidi, Chiara; Colao, Rosanna; Rainero, Innocenzo; et al. (J Alzheimers Dis, 2017)
In frontotemporal dementia (FTD), age at disease onset (AAO) is unpredictable in both early and late-onset cases; AAO variability is found even in autosomal dominant FTD. The present study was aimed at identifying genetic modifiers modulating AAO in a large cohort of Italian FTD patients. We conducted an association analysis on 411 FTD patients, belonging to 7 Italian Centers, and for whom AAO was available. Population structure was evaluated by principal component analysis to infer continuous axes of genetic variation, and single linear regression models were applied. A genetic score (GS) was calculated on the basis of suggestive single nucleotide polymorphisms (SNPs) found by association analyses. GS showed genome-wide significant slope decrease by -3.86 (95% CI: -4.64 to -3.07, p < 2×10-16) per standard deviation of the GS for 6 SNPs mapping to genes involved in neuronal development and signaling, axonal myelinization, and glutamatergic/GABA neurotransmission. An increase of the GS was associated with a decrease of the AAO. Our data indicate that there is indeed a genetic component that underpins and modulates up to 14.5% of variability of AAO in Italian FTD. Future studies on genetic modifiers in FTD are warranted.

Efficacy of Hearing Aids on the Cognitive Status of Patients with Alzheimer's Disease and Hearing Loss: A Multicenter Controlled Randomized Trial. - Nguyen, Marie-France; Bonnefoy, Marc; Adrait, Arnaud; Gueugnon, Marine; Petitot, Charles; Collet, Lionel; Roux, Adeline; Perrot, Xavier (J Alzheimers Dis, 2017)
BACKGROUND/OBJECTIVE: This study evaluated the cognitive benefit of hearing aids (HA) in older patients with Alzheimer's disease (AD) and hearing loss (HL) after a 6- and 12-month period of utilization. METHODS: A multicenter double-blind randomized placebo-controlled trial was conducted in patients aged more than 65 years. A group was equipped with active HA for 6 months (active group) and a second group had placebo HA for 6 months (placebo group) followed by a secondary activation phase for a further 6 months (semi crossover procedure). Both groups were retested after a 12-month period. The primary endpoint was the change from baseline of the Alzheimer's Disease Assessment Scale-Cognitive subscale (ADAS Cog) after a 6-month period in both groups and after 6 months of secondary HA activation in the placebo group. A smaller cognitive decline should be obtained with HA use; an increase in ADAS Cog score of less than 6 points was defined a success. RESULTS: Fifty-one patients aged 68 to 99 years were included; 38 attended the 6-month visit: 18 in the active group and 20 in the placebo group. At 6 months, 14 (82.4%) successes were noticed in the active group, and 15 (88.2%) in the placebo group (p = 1.0); delta ADAS Cog in the active group was 1.8±5.3 and 1.3±5.3 in the placebo group (p = 0.8). In the placebo group, after the secondary HA activation, no significant improvement was observed. CONCLUSION: No significant effect of HA use was observed after 6 months of follow-up in patients with AD and HL.

Evaluation of a DNA Aβ42 Vaccine in Aged NZW Rabbits: Antibody Kinetics and Immune Profile after Intradermal Immunization with Full-Length DNA Aβ42 Trimer. - Lambracht-Washington, Doris; Fu, Min; Wight-Carter, Mary; Riegel, Matthew; Rosenberg, Roger N (J Alzheimers Dis, 2017)
A pathological hallmark of Alzheimer's disease (AD) are amyloid plaques in the brain consisting of aggregated amyloid-β 42 peptide (Aβ42) derived from cellular amyloid-β protein precursor (AβPP). Based on successful experiments in mouse AD models, active immunization with Aβ42 peptide and passive immunizations with anti-Aβ42 antibodies were started in clinical trials. Active Aβ42 peptide immunization in humans had led to an inflammatory autoimmune response, and the trial was stopped. Passive immunizations had shown some effects in slowing AD pathology. Active DNA Aβ42 immunizations administered with the gene gun into the skin elicits a different immune response and is non-inflammatory. While in rodents, good responses had been found for this type of immunization, positive results in larger mammals are missing. We present here results from sixteen New Zealand White Rabbits, which underwent intradermal DNA Aβ42 immunization via gene gun. The humoral immune response was analyzed from blood throughout the study, and cellular immune responses were determined from spleens at the end of the study. A good anti-Aβ antibody response was found in the rabbit model. The T cell response after re-stimulation in cell culture showed no IFNγ producing cells when ELISPOT assays were analyzed from PBMC, but low numbers of IFNγ and IL-17 producing cells were found in ELISPOTS from spleens (both 5 immunizations). Brains from immunized rabbits showed no signs of encephalitis. Based on these results, DNA Aβ42 immunization is highly likely to be safe and effective to test in a possible clinical AD prevention trial in patients.

Everyday Memory in Patients with Alzheimer's Disease: Fragmentary and Distorted. - Sejunaite, Karolina; Lanza, Claudia; Riepe, Matthias W (J Alzheimers Dis, 2017)
BACKGROUND: Errors of omission are an established hallmark of memory impairment in Alzheimer's disease (AD). Much less is known about other memory errors in AD such as false memories. OBJECTIVE: We investigated false memories in healthy elderly controls (HC; n = 23) and patients with AD (n = 20) using real-life tasks of watching news and commercials. METHODS: Participants received a comprehensive neuropsychological assessment and were shown original news and commercials with a subsequent recognition task to assess veridical and false memories. RESULTS: Subjective estimate of the number of errors were alike in HC and patients with AD. However, memory performance in both the news and the commercials task was significantly worse in patients with AD. Trail-Making Test and Symbol-Span Test were significant predictors of false memories on viewing news and commercials. In patients with AD, levels of Aβ1 - 42, but not levels of tau-protein were correlated with false memories in both tasks. CONCLUSIONS: Everyday life in patients with AD is impeded not due to the incompleteness of memory but also due to its distortions. Furthermore, it is hindered by the lack of awareness towards these deficits. False memory content in patients with AD is associated with Aβ42 levels in the CSF as a surrogate of the overall extent to which the brain has been affected by AD pathology. Future studies will need to address the impact of this duality of memory failure on everyday life of patients with AD and their proxies in greater detail.

Exercise Training and Functional Connectivity Changes in Mild Cognitive Impairment and Healthy Elders. - Chirles, Theresa J; Reiter, Katherine; Weiss, Lauren R; Alfini, Alfonso J; Nielson, Kristy A; Smith, J Carson (J Alzheimers Dis, 2017)
BACKGROUND: Effective interventions are needed to improve brain function in mild cognitive impairment (MCI), an early stage of Alzheimer's disease (AD). The posterior cingulate cortex (PCC)/precuneus is a hub of the default mode network (DMN) and is preferentially vulnerable to disruption of functional connectivity in MCI and AD. OBJECTIVE: We investigated whether 12 weeks of aerobic exercise could enhance functional connectivity of the PCC/precuneus in MCI and healthy elders. METHODS: Sixteen MCI and 16 healthy elders (age range = 60-88) engaged in a supervised 12-week walking exercise intervention. Functional MRI was acquired at rest; the PCC/precuneus was used as a seed for correlated brain activity maps. RESULTS: A linear mixed effects model revealed a significant interaction in the right parietal lobe: the MCI group showed increased connectivity while the healthy elders showed decreased connectivity. In addition, both groups showed increased connectivity with the left postcentral gyrus. Comparing pre to post intervention changes within each group, the MCI group showed increased connectivity in 10 regions spanning frontal, parietal, temporal and insular lobes, and the cerebellum. Healthy elders did not demonstrate any significant connectivity changes. CONCLUSION: The observed results show increased functional connectivity of the PCC/precuneus in individuals with MCI after 12 weeks of moderate intensity walking exercise training. The protective effects of exercise training on cognition may be realized through the enhancement of neural recruitment mechanisms, which may possibly increase cognitive reserve. Whether these effects of exercise training may delay further cognitive decline in patients diagnosed with MCI remains to be demonstrated.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Exercise; Exercise Test; Female; Gyrus Cinguli; Humans; Image Processing, Computer-Assisted; Linear Models; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Oxygen; Psychiatric Status Rating Scales

The Experiences of People with Dementia and Their Caregivers in Dementia Diagnosis. - Lian, Yan; Xiao, Lily Dongxia; Zeng, Fan; Wu, Xianmu; Wang, Zhen; Ren, Hui (J Alzheimers Dis, 2017)
BACKGROUND: People can live well with dementia if they are diagnosed early and receive early interventions and appropriate dementia management and care. However, dementia is currently under-detected and under-diagnosed. The diagnosis rate is around 50% only in higher-income countries and 5-10% only in low- and middle-income countries. Studies on consumers' experiences in engaging in dementia diagnosis in a socio-cultural context are much needed in order to generate research evidence to inform person-centered dementia care and services. OBJECTIVE: The aim of the study was to understand the experiences of people with dementia and their caregivers in engaging in dementia diagnosis. METHODS: An interpretative study design informed by Gadamer's hermeneutic principles was applied to the present study to achieve the aim of the study. The study was strengthened by applying a social ecological framework to the study design. In total, 23 participants contributed to the interviews or focus group. Thematic analysis was applied to data analysis. RESULTS: Four themes were determined from data and described as: capabilities to detect the memory loss in an early stage, perceptions and beliefs of dementia in the community, different journeys toward the diagnosis and expectations of a smooth journey for others. These findings illuminate a social ecological perspective of improving early detection and timely diagnosis of dementia in the community settings. CONCLUSION: The findings of this study have implications for policy, resource, and practice development. Consumers expect that government subsidized dementia care services in primary care and specialist care settings are needed in order to enable consumer-driven timely diagnosis and dementia management in home care settings.

Five-Year Longitudinal Brain Volume Change in Healthy Elders at Genetic Risk for Alzheimer's Disease. - Reiter, Katherine; Nielson, Kristy A; Durgerian, Sally; Woodard, John L; Smith, J Carson; Seidenberg, Michael; Kelly, Dana A; Rao, Stephen M (J Alzheimers Dis, 2017)
Neuropathological changes associated with Alzheimer's disease (AD) precede symptom onset by more than a decade. Possession of an apolipoprotein E (APOE) ɛ4 allele is the strongest genetic risk factor for late onset AD. Cross-sectional studies of cognitively intact elders have noted smaller hippocampal/medial temporal volumes in ɛ4 carriers (ɛ4+) compared to ɛ4 non-carriers (ɛ4-). Few studies, however, have examined long-term, longitudinal, anatomical brain changes comparing healthy ɛ4+ and ɛ4- individuals. The current five-year study examined global and regional volumes of cortical and subcortical grey and white matter and ventricular size in 42 ɛ4+ and 30 ɛ4- individuals. Cognitively intact participants, ages 65-85 at study entry, underwent repeat anatomical MRI scans on three occasions: baseline, 1.5, and 4.75 years. Results indicated no between-group volumetric differences at baseline. Over the follow-up interval, the ɛ4+ group experienced a greater rate of volume loss in total grey matter, bilateral hippocampi, right hippocampal subfields, bilateral lingual gyri, bilateral parahippocampal gyri, and right lateral orbitofrontal cortex compared to the ɛ4- group. Greater loss in grey matter volumes in ɛ4+ participants were accompanied by greater increases in lateral, third, and fourth ventricular volumes. Rate of change in white matter volumes did not differentiate the groups. The current results indicate that longitudinal measurements of brain atrophy can serve as a sensitive biomarker for identifying neuropathological changes in persons at genetic risk for AD and potentially, for assessing the efficacy of treatments designed to slow or prevent disease progression during the preclinical stage of AD.

Functional Disintegration of the Default Mode Network in Prodromal Alzheimer's Disease. - Dillen, Kim N H; Jacobs, Heidi I L; Kukolja, Juraj; Richter, Nils; von Reutern, Boris; Onur, Özgür A; Langen, Karl-Josef; Fink, Gereon R (J Alzheimers Dis, 2017)
Neurodegenerative brain changes can affect the functional connectivity strength between nodes of the default-mode network (DMN), which may underlie changes in cognitive performance. It remains unclear how the functional connectivity strength of DMN nodes differs from healthy to pathological aging and whether these changes are cognitively relevant. We used resting-state functional magnetic resonance imaging to investigate the functional connectivity strength across five DMN nodes in 25 healthy controls (HC), 28 subjective cognitive decline (SCD) participants, and 25 prodromal Alzheimer's disease (AD) patients. After identifying the ventral medial prefrontal cortex (vmPFC), posterior cingulate cortex (PCC), retrosplenial cortex (RSC), inferior parietal lobule, and the hippocampus we investigated the functional strength between DMN nodes using temporal network modeling. Functional coupling of the vmPFC and PCC in prodromal AD patients was disrupted. This vmPFC-PCC coupling correlated positively with memory performance in prodromal AD. Furthermore, the hippocampus de-coupled from posterior DMN nodes in SCD and prodromal AD patients. There was no coupling between the hippocampus and the anterior DMN. Additional mediation analyses indicated that the RSC enables communication between the hippocampus and DMN regions in HC but none of the other two groups. These results suggest an anterior-posterior disconnection and a hippocampal de-coupling from posterior DMN nodes with disease progression. Hippocampal de-coupling already occurring in SCD may provide valuable information for the development of a functional biomarker.

Functional Reserve: Experience Participating in Instrumental Activities of Daily Living is Associated with Gender and Functional Independence in Mild Cognitive Impairment. - Berezuk, Courtney; Zakzanis, Konstantine K; Ramirez, Joel; Ruocco, Anthony C; Edwards, Jodi D; Callahan, Brandy L; Black, Sandra E (J Alzheimers Dis, 2017)
BACKGROUND: Gender differences in instrumental activities of daily living (IADLs) in mild cognitive impairment (MCI) and Alzheimer's disease may be explained by gender differences in IADL involvement. OBJECTIVE: We introduce a novel theoretical construct, termed functional reserve, and empirically examine gender differences in IADL experience as a proxy of this reserve. METHODS: We cross-sectionally examined men (n = 502) and women (n = 340) with MCI from the Alzheimer's Disease Neuroimaging Initiative (ADNI). Demographic factors, depressive symptoms, neuropsychological scores, and IADL experience were included as independent variables and total Functional Activities Questionnaire (FAQ) scores as the dependent variable. Regression analyses were performed on the full cohort and stratified by gender to identify differential predictive relationships for men and women. RESULTS: Gender was associated with total FAQ (p < 0.05) until adjusting for IADL experience. Furthermore, the combination of cognitive measures accounted for the most variance in functional dependence (12% explained, p < 0.001), although IADL experience was the most important single variable (4.8% explained, p < 0.001). Stratification by gender revealed that IADL experience accounted for 6.6% of the variance in FAQ score in men (p < 0.001) but only 2.4% in women (p = 0.001); however, the interaction between gender and experience was not statistically significant. DISCUSSION: A small effect of men showing greater functional dependence in MCI may be explained by lower IADL experience. Additionally, IADL experience was associated with superior functioning in all analyses, potentially through increased functional reserve. This concept of functional reserve may have implications for identifying individuals at risk for IADL dependence, preventing or delaying decline, and potentially treating functional impairment.

Gender-Based Cerebral Perfusion Differences in 46,034 Functional Neuroimaging Scans. - Amen, Daniel G; Trujillo, Manuel; Keator, David; Taylor, Derek V; Willeumier, Kristen; Meysami, Somayeh; Raji, Cyrus A (J Alzheimers Dis, 2017)
BACKGROUND: Studies have reported that females have widespread increases in regional cerebral blood flow, but the studies were relatively small and inconsistent. OBJECTIVE: Here we analyzed a healthy and a very large clinical psychiatric population to determine the effect of gender, using single photon emission computed tomography (SPECT). METHODS: Whole brain and region of interest (ROI) gender differences were analyzed in a total of 46,034 SPECT scans at baseline and concentration. The sample included 119 healthy subjects and 26,683 patients (60.4% male, 39.6% female); a subset of 11,587 patients had complete diagnostic information. A total of 128 regions were analyzed according to the AAL Atlas, using ROI Extract and SPSS statistical software programs, controlling for age, diagnoses, and correcting for multiple comparisons. RESULTS: Compared to males, healthy females showed significant whole brain (p < 0.01) and ROI increases in 65 baseline and 48 concentration regions (p < 0.01 corrected). Healthy males showed non-significant increases in 9 and 22 regions, respectively. In the clinical group, there were widespread significant increases in females, especially in the prefrontal and limbic regions, and specific increases in males in the inferior occipital lobes, inferior temporal lobes, and lobule 7 and Crus 2 of the cerebellum. These findings were replicated in the subset of 11,587 patients with the effect of diagnoses removed. CONCLUSIONS: Our results demonstrated significant gender differences in a healthy and clinical population. Understanding these differences is crucial in evaluating functional neuroimaging and may be useful in understanding the epidemiological gender differences among psychiatric disorders.

Genetic Prion Disease Caused by PRNP Q160X Mutation Presenting with an Orbitofrontal Syndrome, Cyclic Diarrhea, and Peripheral Neuropathy. - Fong, Jamie C; Rojas, Julio C; Bang, Jee; Legati, Andrea; Rankin, Katherine P; Forner, Sven; Miller, Zachary A; Karydas, Anna M; Coppola, Giovanni; Grouse, Carrie K; Ralph, Jeffrey; Miller, Bruce L; et al. (J Alzheimers Dis, 2017)
Patients with pathogenic truncating mutations in the prion gene (PRNP) usually present with prolonged disease courses with severe neurofibrillary tangle and cerebral amyloidosis pathology, but more atypical phenotypes also occur, including those with dysautonomia and peripheral neuropathy. We describe the neurological, cognitive, neuroimaging, and electrophysiological features of a 31-year-old man presenting with an orbitofrontal syndrome, gastrointestinal symptoms, and peripheral neuropathy associated with PRNP Q160X nonsense mutation, with symptom onset at age 27. The mutation was also detected in his asymptomatic father and a symptomatic paternal cousin; several members of prior generations died from early onset dementia. This is the first report of a family affected with the nonsense PRNP mutation Q160X displaying clear autosomal dominant disease in multiple family members and reduced penetrance. This case strengthens the evidence suggesting an association between PRNP truncating mutations and prion systemic amyloidosis. PRNP gene testing should be considered in any patient with atypical dementia, especially with early onset and neuropathy, even in the absence of a family history.

Health Advice in a Digital World: Quality and Content of Online Information about the Prevention of Alzheimer's Disease. - Robillard, Julie M; Feng, Tanya L (J Alzheimers Dis, 2017)
BACKGROUND: As the number of older adults turning to the Internet for health information increases, so does the potential for online information to have a substantial impact on the patient-physician relationship and on their health. Inaccurate information may weaken patient-physician relationships or result in increased physician visits and health anxiety, while high quality information may allow Internet users to make better decisions about their health. OBJECTIVE: To assess the quality and content of available online resources about the prevention of Alzheimer's disease (AD). METHODS: A sample of 308 articles related to the prevention of AD was collected from the first three pages of location-independent keyword searches on Google.com between September 17-30, 2014. Content analysis was applied to articles that met criteria (n = 298) and a quality evaluation tool was developed to generate a quality score for each of the articles (n = 290). RESULTS: We found that articles on the high end of the quality spectrum focused on modifiable risk factors and tended to present balanced information, while articles of low quality emphasized nutrition as a method of prevention and were more likely to be in conflict of interest. CONCLUSION: This study provides the first insight into the content and quality of prevention information for AD currently available online and highlights the importance of future research to better understand the impact of this information on the patient-physician relationship and health decision-making of older adults.

Histopathology and Florbetaben PET in Patients Incorrectly Diagnosed with Alzheimer's Disease. - Sabbagh, Marwan N; Schäuble, Barbara; Anand, Keshav; Richards, Danielle; Murayama, Shigeo; Akatsu, Hiroyasu; Takao, Masaki; Rowe, Christopher C; Masters, Colin L; Barthel, Henryk; Gertz, Hermann-Josef; Peters, Oliver; et al. (J Alzheimers Dis, 2017)
Of 57 individuals diagnosed with Alzheimer's disease (AD) in a phase III study, 13 (23%) had amyloid-β (Aβ) levels on postmortem histopathology that did not explain the dementia. Based on postmortem histopathology, a wide range of different non-AD conditions was identified, including frontotemporal dementia, hippocampal sclerosis, and dementia with Lewy bodies. Of the histopathologically Aβ negative scored cases ante-mortem Florbetaben PET scans were classified as negative for Aβ in 11 patients based on visual analysis and in all 12 quantifiable cases based on composite standardized uptake value ratios. Thus, florbetaben PET can assist physicians in the differential diagnosis of neurodegenerative disorders by reliably excluding Aβ pathology.

Home-Based Exercise Program Improves Balance and Fear of Falling in Community-Dwelling Older Adults with Mild Alzheimer's Disease: A Pilot Study. - Padala, Kalpana P; Padala, Prasad R; Lensing, Shelly Y; Dennis, Richard A; Bopp, Melinda M; Roberson, Paula K; Sullivan, Dennis H (J Alzheimers Dis, 2017)
BACKGROUND/OBJECTIVE: Balance problems are common in older adults with Alzheimer's disease (AD). The objective was to study the effects of a Wii-Fit interactive video-game-led physical exercise program to a walking program on measures of balance in older adults with mild AD. METHODS: A prospective randomized controlled parallel-group trial (Wii-Fit versus walking) was conducted in thirty community-dwelling older adults (73±6.2 years) with mild AD. Home-based exercises were performed under caregiver supervision for 8 weeks. Primary (Berg Balance Scale, BBS) and secondary outcomes (fear of falls and quality of life) were measured at baseline, 8 weeks (end of intervention), and 16 weeks (8-weeks post-intervention). RESULTS: At 8 weeks, there was a significantly greater improvement (average inter-group difference [95% CI]) in the Wii-Fit group compared to the walking group in BBS (4.8 [3.3-6.2], p < 0.001), after adjusting for baseline. This improvement was sustained at 16 weeks (3.5 [2.0-5.0], p < 0.001). Analyses of the secondary outcome measures indicated that there was a significantly greater improvement in the Wii-Fit group compared to walking group in Activity-specific Balance Confidence scale (6.5 [3.6-9.4], p < 0.001) and Falls Efficacy Scale (-4.8 [-7.6 to -2.0], p = 0.002) at 8 weeks. However, this effect was not sustained at 16 weeks. Quality of life improved in both groups at 8 weeks; however, there were no inter-group differences (p = 0.445). CONCLUSION: Home-based, caregiver-supervised Wii-Fit exercises improve balance and may reduce fear of falling in community-dwelling older adults with mild AD.

How Different are Quality of Life Ratings for People with Dementia Reported by Their Family Caregivers from Those Reported by the Patients Themselves? - Jacob, Louis; Han, Ji Won; Kim, Tae Hui; Park, Joon Hyuk; Lee, Seok Bum; Lee, Jung Jae; Ryu, Seung-Ho; Kim, Shin-Kyeom; Yoon, Jong Chul; Jhoo, Jin Hyeong; Kim, Jeong Lan; Kwak, Kyung Phil; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Measurements of patient quality of life (QoL) play a major role in the management of dementia. OBJECTIVE: We investigated the self-proxy discrepancy of QoL ratings in the elderly and the impact of dementia severity on the discrepancy. METHODS: QoL of 718 patients with dementia and 651 non-demented elderly were rated by themselves and their caregivers (CG) using the Quality of Life-Alzheimer's Disease (QoL-AD). The impact of the rater on the total and item scores of QoL-AD was analyzed using repeated measures ANOVA and differential response patterns between self and proxy were analyzed using differential item functioning (DIF) analysis. RESULTS: Self-rated scores were higher than CG-rated scores in all diagnostic groups. The interaction between rater and diagnostic group was significant in total QoL-AD score and 5 item scores ('memory', 'marriage', 'chores around the house', 'do things for fun', and 'life as a whole'). The strength of the DIF increased with advancing dementia in these items. CONCLUSION: Self-proxy rating discrepancy of QoL was influenced by the presence and severity of dementia only in five items.

How Studies of the Serotonin System in Macaque Models of Menopause Relate to Alzheimer's Disease1. - Bethea, Cynthia L; Reddy, Arubala P; Christian, Fernanda Lima (J Alzheimers Dis, 2017)
Serotonin plays a key role in mood or affect, and dysfunction of the serotonin system has been linked to depression in humans and animal models. Depression appears prior to or coincident with overt symptoms of Alzheimer's disease (AD) in about 50% of patients, and some experts consider it a risk factor for the development of AD. In addition, AD is more prevalent in women, who also show increased incidence of depression. Indeed, it has been proposed that mechanisms underlying depression overlap the mechanisms thought to hasten AD. Women undergo ovarian failure and cessation of ovarian steroid production in middle age and the postmenopausal period correlates with an increase in the onset of depression and AD. This laboratory has examined the many actions of ovarian steroids in the serotonin system of non-human primates using a rhesus macaque model of surgical menopause with short or long-term estradiol (E) or estradiol plus progesterone (E+P) replacement therapy. In this mini-review, we present a brief synopsis of the relevant literature concerning AD, depression, and serotonin. We also present some of our data on serotonin neuron viability, the involvement of the caspase-independent pathway, and apoptosis-inducing factor in serotonin-neuron viability, as well as gene expression related to neurodegeneration and neuron viability in serotonin neurons from adult and aged surgical menopausal macaques. We show that ovarian steroids, particularly E, are crucial for serotonin neuron function and health. In the absence of E, serotonin neurons are endangered and deteriorating toward apoptosis. The possibility that this scenario may proceed or accompany AD in postmenopausal women seems likely.

Humanin Specifically Interacts with Amyloid-β Oligomers and Counteracts Their in vivo Toxicity. - Romeo, Margherita; Stravalaci, Matteo; Beeg, Marten; Rossi, Alessandro; Fiordaliso, Fabio; Corbelli, Alessandro; Salmona, Mario; Gobbi, Marco; Cagnotto, Alfredo; Diomede, Luisa (J Alzheimers Dis, 2017)
The 24-residue peptide humanin (HN) has been proposed as a peptide-based inhibitor able to interact directly with amyloid-β (Aβ) oligomers and interfere with the formation and/or biological properties of toxic Aβ species. When administered exogenously, HN, or its synthetic S14G-derivative (HNG), exerted multiple cytoprotective effects, counteracting the Aβ-induced toxicity. Whether these peptides interact directly with Aβ, particularly with the soluble oligomeric assemblies, remains largely unknown. We here investigated the ability of HN and HNG to interact directly with highly aggregating Aβ42, and interfere with the formation and toxicity of its oligomers. Experiments were run in cell-free conditions and in vivo in a transgenic C. elegans strain in which the Aβ toxicity was specifically due to oligomeric species. Thioflavin-T assay indicated that both HN and HNG delay the formation and reduce the final amount of Aβ42 fibrils. In vitro surface plasmon resonance studies indicated that they interact with Aβ42 oligomers favoring the formation of amorphous larger assemblies, observed with turbidity and electron microscopy. In vivo studies indicated that both HN and HNG decrease the relative abundance of A11-positive prefibrillar oligomers as well as OC-positive fibrillar oligomers and had similar protective effects. However, while HN possibly decreased the oligomers by promoting their assembly into larger aggregates, the reduction of oligomers caused by HNG can be ascribed to a marked decrease of the total Aβ levels, likely the consequence of the HNG-induced overexpression of the Aβ-degrading enzyme neprilysin. These findings provide information on the mechanisms underlying the anti-oligomeric effects of HN and HNG and illustrate the role of S14G substitution in regulating the in vivo mechanism of action.
Keywords: Amyloid beta-Peptides; Animals; Animals, Genetically Modified; Caenorhabditis elegans; Caenorhabditis elegans Proteins; Circular Dichroism; Disease Models, Animal; Dose-Response Relationship, Drug; Gene Expression Regulation; Humans; Intracellular Signaling Peptides and Proteins; Microscopy, Atomic Force; Microscopy, Electron, Transmission; Neprilysin; Paralysis; Peptide Fragments; Surface Plasmon Resonance

Identification of Successful Cognitive Aging in the Alzheimer's Disease Neuroimaging Initiative Study. - Lin, Feng V; Wang, Xixi; Wu, Rachel; Rebok, George W; Chapman, Benjamin P (J Alzheimers Dis, 2017)
The present prospective observational study aimed to identify the existence of successful cognitive agers among a group of well-defined cognitively healthy older adults (n = 354, mean age = 75 years), and to examine baseline individual-level predictors and associated health outcomes over time. Episodic memory (EM) and executive function (EF) composite scores and multiple health outcomes were obtained annually over 5 years. Potential individual-level predictors that were related to Alzheimer's disease pathology or genetic risk, neurodegeneration, and vascular risks were collected at baseline. Three latent classes with matched age and education were identified using growth mixture modeling: a group of participants who exhibited high, stable EM and EF (40.7% of the sample, "successful agers"); a group who had initial high cognitive performance that declined over time (21.2%, "declining agers"); and a group who had normal (EM) or poor (EF) but stable cognitive performance over time (38.1%, "low stable agers"). The group classification predicted significant differences in the incidence of global cognitive impairment, the development of at least one depressive symptom, and everyday functional impairment. Sex, apolipoprotein E allele 4, amyloid-β1-42, and t-tau significantly contributed to the difference in cognitive trajectories between the successful agers and the other two groups. Characterizing successful cognitive agers who are relatively resistant to both tau and amyloid pathology provides potential pathways for promoting successful cognitive aging and preventing cognitive decline.

The Impact of Alzheimer's Disease on the Resting State Functional Connectivity of Brain Regions Modulating Pain: A Cross Sectional Study. - Monroe, Todd B; Beach, Paul A; Bruehl, Stephen P; Dietrich, Mary S; Rogers, Baxter P; Gore, John C; Atalla, Sebastian W; Cowan, Ronald L (J Alzheimers Dis, 2017)
BACKGROUND: It is currently unknown why people with Alzheimer's disease (AD) receive less pain medication and report pain less frequently. OBJECTIVE: The purpose of this study was to determine the impact of AD on thermal psychophysics and resting-state functional connectivity (RSFC) among sensory, affective, descending modulatory, and default mode structures. METHODS: Controls (n = 23, 13 = female) and age-matched people with AD (n = 23, 13 = females) underwent psychophysical testing to rate perceptions of warmth, mild, and moderate pain and then completed resting-state fMRI. Between groups analysis in psychophysics and RSFC were conducted among pre-defined regions of interest implicated in sensory and affective dimensions of pain, descending pain modulation, and the default mode network. RESULTS: People with AD displayed higher thermal thresholds for warmth and mild pain but similar moderate pain thresholds to controls. No between-group differences were found for unpleasantness at any percept. Relative to controls, people with AD demonstrated reduced RSFC between the right posterior insula and left anterior cingulate and also between right amygdala and right secondary somatosensory cortex. Moderate pain unpleasantness reports were associated with increased RSFC between right dorsolateral prefrontal cortex and left ACC in controls only. CONCLUSIONS: While AD had little effect on unpleasantness, people with AD had increased thermal thresholds, altered RSFC, and no association of psychophysics with RSFC in pain regions. Findings begin to elucidate that in people with AD, altered integration of pain sensation, affect, and descending modulation may, in part, contribute to decreased verbal pain reports and thus decreased analgesic administration.

Impact of Recruitment Methods in Subjective Cognitive Decline. - Abdelnour, Carla; Rodríguez-Gómez, Octavio; Alegret, Montserrat; Valero, Sergi; Moreno-Grau, Sonia; Sanabria, Ángela; Hernandez, Isabel; Rosende-Roca, Maitee; Vargas, Liliana; Mauleón, Ana; Sánchez, Domingo; Espinosa, Ana; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Recruitment methods can determine sample characteristics in mild cognitive impairment and Alzheimer's disease dementia, but little is known about its influence in subjective cognitive decline (SCD). OBJECTIVE: To determine the influence of two types of recruitment methods in the characteristics of individuals with SCD. METHODS: We select and compare clinical and neuropsychological features, and frequency of APOE ɛ4 allele of 326 subjects with SCD from two cohorts: Open House Initiative (OHI) versus Memory Unit (MU). A logistic regression analysis (LRA), using gender and years of education as covariates, was used to examine the neuropsychological variables. RESULTS: The OHI sample were mostly women (75.9% versus 64.5%, p < 0.05), with higher educational level (12.15 [3.71] versus 10.70 [3.80] years, p = 0.001), and more family history of dementia (138 [62.7%] versus 44 [41.5%], p < 0.001) than the MU sample. Also, the OHI sample showed better overall neuropsychological performance than the MU sample, and after a LRA, this trend continued in automatic response inhibition capacity, abstract reasoning, and recognition memory. We did not find differences in age, depression history, and/or APOE ɛ4 allele frequency. CONCLUSION: SCD subjects showed different demographic and neuropsychological characteristics depending on the recruitment method, which should be taken into account in the design of research studies with this target population.

Impact of the Relationship of Stress and the Immune System in the Appearance of Alzheimer's Disease. - de la Rubia Ortí, Jose Enrique; Sancho Castillo, Sandra; Benlloch, Maria; Julián Rochina, Mariano; Corchón Arreche, Silvia; García-Pardo, María Pilar (J Alzheimers Dis, 2017)
The understanding of how the immune system works, as well as its relationship with the stress level, seems to be important at the start of the Alzheimer's disease (AD). To analyze this, immunoglobulin A (IgA) and cortisol in saliva were measured using ELISA in patients with mild AD and healthy volunteers, and the production of both biomarkers was compared and correlated. In participants without AD, IgA was higher when cortisol was lower, and the opposite happened in participants with AD, with the quantification in saliva being a suitable method to determine it.

Increased Carbohydrate Intake is Associated with Poorer Performance in Verbal Memory and Attention in an APOE Genotype-Dependent Manner. - Gardener, Samantha L; Rainey-Smith, Stephanie R; Sohrabi, Hamid R; Weinborn, Michael; Verdile, Giuseppe; Fernando, W M A D Binosha; Lim, Yen Ying; Harrington, Karra; Burnham, Samantha; Taddei, Kevin; Masters, Colin L; Macaulay, Stuart L; et al. (J Alzheimers Dis, 2017)
Evidence suggests that a diet low in carbohydrates can impact on cognitive performance among those with Alzheimer's disease (AD). However, there is a lack of data assessing this relationship among cognitively normal (CN) older adults at increased future risk of developing AD due to carriage of the apolipoprotein E (APOE) ɛ4 allele. We assessed the cross-sectional association between carbohydrate intake, cognitive performance, and cerebral amyloid-β (Aβ) load in CN older adults, genotyped for APOEɛ4 allele carrier status. Greater carbohydrate intake was associated with poorer performance in verbal memory in APOEɛ4 allele non-carriers, and poorer performance in attention in APOEɛ4 allele carriers. There were no associations between carbohydrate intake and cerebral Aβ load. These results provide support to the idea that decreasing carbohydrate intake may offer neurocognitive benefits, with specific cognitive domains affected in an APOE genotype-dependent manner. These findings warrant further investigation utilizing a longitudinal study design.

Increased PCSK9 Cerebrospinal Fluid Concentrations in Alzheimer's Disease. - Zimetti, Francesca; Caffarra, Paolo; Ronda, Nicoletta; Favari, Elda; Adorni, Maria Pia; Zanotti, Ilaria; Bernini, Franco; Barocco, Federica; Spallazzi, Marco; Galimberti, Daniela; Ricci, Chiara; Ruscica, Massimiliano; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) has been associated with dysregulation of brain cholesterol trafficking and abnormal production of apolipoprotein E isoform 4 (apoE4). Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a protein present in serum and cerebrospinal fluid (CSF) degrading the low-density lipoprotein receptor (LDLr) and other apoE-binding receptors involved in neuron cholesterol uptake. The role of PCSK9 in AD is controversial. OBJECTIVE: We compared PCSK9 levels in CSF of AD patients and non-AD controls and looked at correlations with CSF total apoE and apoE4. METHODS: CSF from AD (n = 30) and from age and sex-matched non-AD patients (n = 30) was collected by lumbar puncture for routine diagnosis. CSF PCSK9, total apoE, and apoE4 levels were measured by ELISA. AD patients showed the typical CSF neurobiomarker pattern (decreased Aβ42 and increased tau and phospho-tau) and impaired cognitive performances, as indicated by the scores of the Mini-Mental State Examination test. RESULTS: PCSK9 levels in CSF were higher in AD than in non-AD subjects (+1.45 fold; p = 0.0049). CSF total apoE concentrations did not differ between the two groups, while apoE4 levels were higher in AD subjects (+3.34 fold; p = 0.0068). Considering all samples, a significant positive correlation was found between PCSK9 and apoE4 (r = 0.4409; p = 0.0006). PCSK9 levels were higher in APOE ɛ4 carriers, reaching statistical significance in the AD group (+1.45 fold; p = 0.0454). CONCLUSION: These results report for the first time an alteration of CSF PCSK9 levels in AD and suggest a pathophysiological link between PCSK9, apoE4, and AD.

Information and Communication Technologies for the Activities of Daily Living in Older Patients with Dementia: A Systematic Review. - D'Onofrio, Grazia; Sancarlo, Daniele; Ricciardi, Francesco; Panza, Francesco; Seripa, Davide; Cavallo, Filippo; Giuliani, Francesco; Greco, Antonio (J Alzheimers Dis, 2017)
BACKGROUND: Significant innovations have been introduced in recent years in the application of information and communication technologies (ICTs) to support healthcare for patients with dementia. OBJECTIVE: In the present systematic review, our goal is to keep track of ICT concepts and approaches to support the range of activities of daily living for people with dementia and to provide a snapshot of the effect that technology is having on patients' self-reliance. METHODS: We reviewed the literature and identified systematic reviews of cohort studies and other authoritative reports. Our selection criteria included: (1) activities of daily living, (2) ICT, and (3) dementia. RESULTS: We identified 56 studies published between 2000 and 2015, of which 26 met inclusion criteria. The present systematic review revealed many ICT systems that could purportedly support the range of activities of daily living for patients with dementia. The results showed five research bodies: 1) technologies used by patients with dementia, 2) technologies used by caregivers, 3) monitoring systems, 4) ambient assistive living with ICTs, and 5) tracking and wayfinding. CONCLUSIONS: There is a potential for ICTs to support dementia care at home and to improve quality of life for caregivers, reducing healthcare costs and premature institutional care for these patients.
Keywords: Activities of Daily Living; Aging; Databases, Bibliographic; Dementia; Humans; Medical Informatics; Self-Help Devices

Insula and Inferior Frontal Gyrus' Activities Protect Memory Performance Against Alzheimer's Disease Pathology in Old Age. - Lin, Feng; Ren, Ping; Lo, Raymond Y; Chapman, Benjamin P; Jacobs, Alanna; Baran, Timothy M; Porsteinsson, Anton P; Foxe, John J (J Alzheimers Dis, 2017)
Apolipoprotein E (APOE) ɛ4 carriers and patients with amnestic mild cognitive impairment (MCI) have high risk of developing Alzheimer's disease (AD). The Scaffolding Theory of Aging and Cognition proposes that recruitment of additional frontal brain regions can protect cognition against aging. This thesis has yet to be fully tested in older adults at high risk for AD. In the present study, 75 older participants (mean age: 74 years) were included. Applying a voxel-wise approach, fractional amplitude of low-frequency fluctuations (fALFF) in resting-state functional neuroimaging data were analyzed as a function of APOEɛ4 status (carrier versus noncarrier) and clinical status (healthy control [HC] versus MCI) using a 2×2 analysis of covariance (ANCOVA). Measures of cognition and cerebrospinal fluid levels of amyloid- β were also obtained. Three frontal regions were identified with significant interaction effects using ANCOVA (corrected p < 0.01): left-insula, left-inferior frontal gyrus (IFG), and right-precentral gyrus. The HC/APOEɛ4 carrier group had significantly higher fALFF in all three regions than other groups. In the entire sample, for two regions (left insula and left IFG), a significant positive relationship between amyloid-β and memory was only observed among individuals with low fALFF. Our results suggest higher activity in frontal regions may explain being cognitively normal among a subgroup of APOEɛ4 carriers and protect against the negative impact of AD-associated pathology on memory. This is an observation with potential implications for AD therapeutics.

Intensive 'Brain Training' Intervention Fails to Reduce Amyloid Pathologies or Cognitive Deficits in Transgenic Mouse Models of Alzheimer's Disease. - Anderson, Maria; Xu, Feng; Ou-Yang, Ming-Hsuan; Davis, Judianne; Van Nostrand, William E; Robinson, John K (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder that is the leading cause of dementia in the elderly. Amyloid-β protein (Aβ) depositions in both the brain parenchyma and the cerebral vasculature are recognized as important pathological components that contribute to the cognitive impairments found in individuals with AD. Because pharmacological options have been minimally effective in treating cognitive impairment to date, interest in the development of preventative lifestyle intervention strategies has increased in the field. One controversial strategy, cognitive-specific stimulation, has been studied previously in human participants and has been widely commercialized in the form of 'brain-training games.' In the present study, we developed a highly controlled, isolated cognitive training intervention program for mice. Two transgenic mouse lines, one that develops Aβ deposition largely in brain parenchyma, and another in the cerebral microvasculature, progressed through a series of domain-specific tasks for an average of 4 months. Despite the high intensity and duration of the intervention, we found little evidence of positive benefits for AD amyloid pathologies and post-training cognitive testing in these two models. Taken together, these results support the current evidence in human studies that cognitive-specific stimulation does not lead to a measurable reduction in AD pathology or an improvement in general brain health.

An Intracellular Amyloid-β/AβPP Epitope Correlates with Neurodegeneration in those Neuronal Populations Early Involved in Alzheimer's Disease. - Esquerda-Canals, Gisela; Martí-Clúa, Joaquim; Roda, Alejandro R; Villegas, Sandra (J Alzheimers Dis, 2017)
The main histopathological hallmarks of Alzheimer's disease (AD) are the extracellular deposition of neuritic amyloid plaques, composed of amyloid-β (Aβ) peptide, and the intracellular accumulation of neurofibrillary tangles, composed of hyperphosphorylated tau. Both traits are emulated in the 3xTg-AD mouse model. Because the relevance of this model in the bibliography and the main role of Aβ in neuronal impairment, here we have detailed the brain Aβ/AβPP distribution to subsequently quantify cellular density and intracellular burden for specific neuronal populations in the early stages of the disease. 6E10 immunoreactivity was evident in the deep layers of the cerebral cortex, in the pyramidal cell layer of the hippocampus, in the basolateral amygdala nucleus, and in the deep cerebellar nuclei macroneurons; whereas the specific neuronal populations with decreased cellular density were the large pyramidal neurons from the layers V-VI in the cerebral cortex, the pyramidal neurons from the CA2-3 region in the hippocampus, and the large neurons from the basolateral nucleus in the amygdala, apart from the already reported deep cerebellar nuclei. Interestingly, we found a strong correlation between intracellular Aβ/AβPP burden and cellular density in all these populations. In addition, behavioral testing showed the functional consequences of such a neuronal depletion. Concretely, anxious-like behavior is manifested in the corner and open-field tests, as well as cognitive functions shown to be impaired in the novel object recognition test and Morris water maze paradigm. To our knowledge, this is the first deep characterization of the specific neuronal populations affected in the 3xTg-AD mouse model.

Intracranial Arterial 4D Flow in Individuals with Mild Cognitive Impairment is Associated with Cognitive Performance and Amyloid Positivity. - Berman, Sara E; Clark, Lindsay R; Rivera-Rivera, Leonardo A; Norton, Derek; Racine, Annie M; Rowley, Howard A; Bendlin, Barbara B; Blennow, Kaj; Zetterberg, Henrik; Carlsson, Cynthia M; Asthana, Sanjay; Turski, Patrick; et al. (J Alzheimers Dis, 2017)
It is becoming increasingly recognized that cerebrovascular disease is a contributing factor in the pathogenesis of Alzheimer's disease (AD). A unique 4D-Flow magnetic resonance imaging (MRI) technique, phase contrast vastly undersampled isotropic projection imaging (PC VIPR), enables examination of angiographic and quantitative metrics of blood flow in the arteries of the Circle of Willis within a single MRI acquisition. Thirty-eight participants with mild cognitive impairment (MCI) underwent a comprehensive neuroimaging protocol (including 4D-Flow imaging) and a standard neuropsychological battery. A subset of participants (n = 22) also underwent lumbar puncture and had cerebrospinal fluid (CSF) assayed for AD biomarkers. Cut-offs for biomarker positivity in CSF resulting from a receiver operating characteristic curve analysis of AD cases and controls from the larger Wisconsin Alzheimer's Disease Research Center cohort were used to classify MCI participants as biomarker positive or negative on amyloid-β (Aβ42), total-tau and total-tau/Aβ42 ratio. Internal carotid artery (ICA) and middle cerebral artery (MCA) mean flow were associated with executive functioning performance, with lower mean flow corresponding to worse performance. MCI participants who were biomarker positive for Aβ42 had lower ICA mean flow than did those who were Aβ42 negative. In sum, mean ICA and MCA arterial flow was associated with cognitive performance in participants with MCI and lower flow in the ICA was associated with amyloid positivity. This provides further evidence for vascular health as a contributing factor in the etiopathogenesis of AD, and could represent a point to intervene in the disease process.

An Intranasal Formulation of Erythropoietin (Neuro-EPO) Prevents Memory Deficits and Amyloid Toxicity in the APPSwe Transgenic Mouse Model of Alzheimer's Disease. - Rodríguez Cruz, Yamila; Strehaiano, Manon; Rodríguez Obaya, Teresita; García Rodríguez, Julío César; Maurice, Tangui (J Alzheimers Dis, 2017)
Erythropoietin (EPO) is a cytokine known to have effective cytoprotective action in the brain, particularly in ischemic, traumatic, inflammatory, and neurodegenerative conditions. We previously reported the neuroprotective effect of a low sialic form of EPO, Neuro-EPO, applied intranasally in rodent models of stroke or cerebellar ataxia and in a non-transgenic mouse model of Alzheimer's disease (AD). Here we analyzed the protective effect of Neuro-EPO in APPSwe mice, a reference transgenic mouse model of AD. Mice were administered 3 times a day, 3 days in the week with Neuro-EPO (125, 250 μg/kg) intranasally, between 12 and 14 months of age. Motor responses, general activity, and memory responses were analyzed during and after treatment. The deficits in spontaneous alternation, place learning in the water-maze, and novel object recognition observed in APPSwe mice were alleviated by the low dose of Neuro-EPO. Oxidative stress, neuroinflammation, trophic factor levels, and a synaptic marker were analyzed in the hippocampus or cortex of the animals. The increases in lipid peroxidation or in GFAP and Iba-1 contents in APPSwe mice were significantly reduced after Neuro-EPO. Activation of intrinsic and extrinsic apoptotic pathways was analyzed. The increases in Bax/Bcl-2 ratio, TNFα, or Fas ligand levels observed in APPSwe mice were reduced by Neuro-EPO. Finally, immunohistochemical and ELISA analyses of Aβ1-42 levels in the APPSwe mouse cortex and hippocampus showed a marked reduction in Aβ deposits and in soluble and insoluble Aβ1-42 forms. This study therefore confirmed the neuroprotective activity of EPO, particularly for an intranasally deliverable formulation, devoid of erythropoietic side effects, in a transgenic mouse model of AD. Neuro-EPO alleviated memory alterations, oxidative stress, neuroinflammation, apoptosis induction, and amyloid load in 14-month-old APPSwe mice.

Intranasal Insulin Transport is Preserved in Aged SAMP8 Mice and is Altered by Albumin and Insulin Receptor Inhibition. - Rhea, Elizabeth M; Humann, Samantha R; Nirkhe, Surabhi; Farr, Susan A; Morley, John E; Banks, William A (J Alzheimers Dis, 2017)
Insulin delivered to the level of the cribriform plate (intranasal insulin) is being investigated for its ability to enhance memory in people with Alzheimer's disease (AD). Recent work has shown intranasal insulin can be detected in young CD-1 mice within 5 min and is still present 60 min after injection. The current study determined whether intranasal insulin transport and the subsequent brain distribution of insulin varies in young, healthy mice (CD-1) compared to those with an AD-like phenotype (aged SAMP8) or those pre-disposed to develop such a phenotype (young SAMP8). We showed transport does not vary among these three mouse cohorts, suggesting that intranasal uptake and brain pharmacokinetics do not differ with AD-like signs or the genetic predisposition to developing them. We found that co-administration with bovine serum albumin increased levels of insulin in most brain regions. In addition, the insulin receptor inhibitor, S961, decreases the amount of insulin transported throughout the brain after intranasal injection. These results show insulin delivery to the brain by intranasal administration can be modified with agents such as albumin, may be dependent on the insulin receptor, and is not affected by an AD-like phenotype as presented by the SAMP8 mouse.

Kynurenine Pathway Metabolites in Alzheimer's Disease. - Giil, Lasse Melvaer; Midttun, Øivind; Refsum, Helga; Ulvik, Arve; Advani, Rajiv; Smith, A David; Ueland, Per Magne (J Alzheimers Dis, 2017)
BACKGROUND: Metabolites of tryptophan, produced via the kynurenine pathway (kynurenines), have been linked to Alzheimer's disease (AD) in small cohorts with conflicting results. OBJECTIVE: To compare differences in plasma kynurenine levels between AD and controls and identify potential associations with cognition. METHODS: The study included 65 histopathologically-confirmed AD patients and 65 cognitively-screened controls from the Oxford Project to Investigate Memory and Ageing (OPTIMA) cohort. Cognition was assessed using the Cambridge Cognitive Examination (CamCog). Tryptophan, kynurenines, neopterin, and vitamin B6 forms were measured in plasma by liquid chromatography-tandem mass spectrometry. Non-parametric statistics, logistic regression and standardized robust regressions were applied with a false discovery rate of 0.05. RESULTS: Tryptophan, xanthurenic acid, 3-hydroxyanthranilic acid, and quinolinic acid were lower in AD (Odds ratios (ORs) 0.24 -0.47; p-values <0.001 -0.01). Pyridoxal 5'phosphate did not differ between AD and controls. Kynurenine, anthranilic acid, quinolinic acid, and markers of immune activation (neopterin, kynurenine/tryptophan ratio, and the PAr index (Pyridoxic acid/(Pyridoxal 5'phosphate + Pyridoxal)) increased with age (β 0.31 -0.51; p-values <0.001 -0.006). Xanthurenic acid decreased with age (β: -0.42, p < 0.001). Elderly AD patients with high quinolinic acid performed worse on the CamCog test, indicated by a significant age*quinolinic acid interaction (β 0.21, p < 0.001). CONCLUSION: Plasma concentrations of several kynurenines were lower in patients with AD compared to controls. Low xanthurenic acid occurred in both AD and with aging. Inflammation-related markers were associated with age, but not AD. However, elevated QA was associated with poor cognition in older AD patients.

Living Alone with Alzheimer's Disease: Data from SveDem, the Swedish Dementia Registry. - Cermakova, Pavla; Nelson, Maja; Secnik, Juraj; Garcia-Ptacek, Sara; Johnell, Kristina; Fastbom, Johan; Kilander, Lena; Winblad, Bengt; Eriksdotter, Maria; Religa, Dorota (J Alzheimers Dis, 2017)
BACKGROUND: Many people with Alzheimer's disease (AD) live alone in their own homes. There is a lack of knowledge about whether these individuals receive the same quality of diagnostics and treatment for AD as patients who are cohabiting. OBJECTIVES: To investigate the diagnostic work-up and treatment of community-dwelling AD patients who live alone. METHODS: We performed a cross-sectional cohort study based on data from the Swedish Dementia Registry (SveDem). We studied patients diagnosed with AD between 2007 and 2015 (n = 26,163). Information about drugs and comorbidities was acquired from the Swedish Prescribed Drug Register and the Swedish Patient Register. RESULTS: 11,878 (46%) patients lived alone, primarily older women. After adjusting for confounders, living alone was inversely associated with receiving computed tomography (OR 0.90; 95% CI 0.82-0.99), magnetic resonance imaging (OR 0.91; 95% CI 0.83-0.99), and lumbar puncture (OR 0.86; 95% CI 0.80-0.92). Living alone was also negatively associated with the use of cholinesterase inhibitors (OR 0.81; 95% CI 0.76; 0.87), memantine (OR 0.77; 95% CI 0.72; 0.83), and cardiovascular medication (OR 0.92; 0.86; 0.99). On the other hand, living alone was positively associated with the use of antidepressants (OR 1.15; 95% CI 1.08; 1.22), antipsychotics (OR 1.41; 95% CI 1.25; 1.58), and hypnotics and sedatives (OR 1.09; 95% CI 1.02; 1.17). CONCLUSIONS: Solitary living AD patients do not receive the same extent of care as those who are cohabiting.

Logopenic Aphasia due to a Strategic Stroke: New Evidence from a Single Case. - Riancho, Javier; Pozueta, Ana; Santos, Miguel; Lage, Carmen; Carril, José M; Banzo, Ignacio; Martínez-Rodriguez, Isabel; Gorno-Tempini, Marilu; Sánchez-Juan, Pascual (J Alzheimers Dis, 2017)
Among primary progressive aphasias (PPAs), logopenic variant PPA (lv-PPA) is usually related to Alzheimer's disease. Although it has been widely clinically and pathologically evaluated, the topography in LPA is still controversial. We report a patient presenting with a logopenic syndrome due to a strategic lesion located in the superior and middle temporal gyrus and compare our findings with those of a PiB-PET positive lv-PPA patient matched by age, gender, and education. We consider that our study provides new anatomical clues to better understand the cognitive mechanisms underlying the logopenic syndrome.
Keywords: Aphasia; Atrophy; Brain; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Stroke

Longitudinal Characterization of [18F]-FDG and [18F]-AV45 Uptake in the Double Transgenic TASTPM Mouse Model. - Waldron, Ann-Marie; Wyffels, Leonie; Verhaeghe, Jeroen; Richardson, Jill C; Schmidt, Mark; Stroobants, Sigrid; Langlois, Xavier; Staelens, Steven (J Alzheimers Dis, 2017)
We aimed to monitor the timing of amyloid-β deposition in relation to changes in brain function using in vivo imaging with [18F]-AV45 and [18F]-FDG in a mouse model of Alzheimer's disease. TASTPM transgenic mice and wild-type controls were scanned longitudinally with [18F]-AV45 and [18F]-FDG before (3 months of age) and at multiple time points after the onset of amyloid deposition (6, 9, 12, and 15 months of age). As expected with increasing amyloidosis, TASTPM mice demonstrated progressive age-dependent increases in [18F]-AV45 uptake that were significantly higher than for WT from 9 months onwards and correlated to ex vivo measures of amyloid burden. The metabolism of [18F]-AV45 produces several brain penetrant radiometabolites and normalization to a reference region helps to negate this non-specific binding and improve the sensitivity of [18F]-AV45. The observed trajectory of [18F]-FDG alterations deviated from our proposed hypothesis of gradual decreases with worsening amyloidosis. While [18F]-FDG uptake in TASTPM mice was significantly lower than that of WT at 9 months, reduced [18F]-FDG was not associated with aging in TASTPM mice. Moreover, [18F]-FDG uptake did not correlate to measures of ex vivo amyloid burden. Our findings suggest that while amyloid-β is sufficient to induce hypometabolism, these pathologies are not linked in a dose-dependent manner in TASTPM mice.

A Longitudinal Study on Resting State Functional Connectivity in Behavioral Variant Frontotemporal Dementia and Alzheimer's Disease. - Hafkemeijer, Anne; Möller, Christiane; Dopper, Elise G P; Jiskoot, Lize C; van den Berg-Huysmans, Annette A; van Swieten, John C; van der Flier, Wiesje M; Vrenken, Hugo; Pijnenburg, Yolande A L; Barkhof, Frederik; Scheltens, Philip; van der Grond, Jeroen; et al. (J Alzheimers Dis, 2017)
BACKGROUND/OBJECTIVE: Alzheimer's disease (AD) and behavioral variant frontotemporal dementia (bvFTD) are the most common types of early-onset dementia. We applied longitudinal resting state functional magnetic resonance imaging (fMRI) to delineate functional brain connections relevant for disease progression and diagnostic accuracy. METHODS: We used two-center resting state fMRI data of 20 AD patients (65.1±8.0 years), 12 bvFTD patients (64.7±5.4 years), and 22 control subjects (63.8±5.0 years) at baseline and 1.8-year follow-up. We used whole-network and voxel-based network-to-region analyses to study group differences in functional connectivity at baseline and follow-up, and longitudinal changes in connectivity within and between groups. RESULTS: At baseline, connectivity between paracingulate gyrus and executive control network, between cuneal cortex and medial visual network, and between paracingulate gyrus and salience network was higher in AD compared with controls. These differences were also present after 1.8 years. At follow-up, connectivity between angular gyrus and right frontoparietal network, and between paracingulate gyrus and default mode network was lower in bvFTD compared with controls, and lower compared with AD between anterior cingulate gyrus and executive control network, and between lateral occipital cortex and medial visual network. Over time, connectivity decreased in AD between precuneus and right frontoparietal network and in bvFTD between inferior frontal gyrus and left frontoparietal network. Longitudinal changes in connectivity between supramarginal gyrus and right frontoparietal network differ between both patient groups and controls. CONCLUSION: We found disease-specific brain regions with longitudinal connectivity changes. This suggests the potential of longitudinal resting state fMRI to delineate regions relevant for disease progression and for diagnostic accuracy, although no group differences in longitudinal changes in the direct comparison of AD and bvFTD were found.

Long-Term Cognitive Decline in Dementia with Lewy Bodies in a Large Multicenter, International Cohort. - Kramberger, Milica G; Auestad, Bjørn; Garcia-Ptacek, Sara; Abdelnour, Carla; Olmo, Josep Garre; Walker, Zuzana; Lemstra, Afina W; Londos, Elisabet; Blanc, Frédéric; Bonanni, Laura; McKeith, Ian; Winblad, Bengt; et al. (J Alzheimers Dis, 2017)
BACKGROUND/OBJECTIVE: The aim of this study was to describe the rate and clinical predictors of cognitive decline in dementia with Lewy bodies (DLB), and compare the findings with Alzheimer's disease (AD) and Parkinson's disease dementia (PDD) patients. METHODS: Longitudinal scores for the Mini-Mental State Examination (MMSE) in 1,290 patients (835 DLB, 198 PDD, and 257 AD) were available from 18 centers with up to three years longitudinal data. Linear mixed effects analyses with appropriate covariates were used to model MMSE decline over time. Several subgroup analyses were performed, defined by anti-dementia medication use, baseline MMSE score, and DLB core features. RESULTS: The mean annual decline in MMSE score was 2.1 points in DLB, compared to 1.6 in AD (p = 0.07 compared to DLB) and 1.8 in PDD (p = 0.19). Rates of decline were significantly higher in DLB compared to AD and PDD when baseline MMSE score was included as a covariate, and when only those DLB patients with an abnormal dopamine transporter SPECT scan were included. Decline was not predicted by sex, baseline MMSE score, or presence of specific DLB core features. CONCLUSIONS: The average annual decline in MMSE score in DLB is approximately two points. Although in the overall analyses there were no differences in the rate of decline between the three neurodegenerative disorders, there were indications of a more rapid decline in DLB than in AD and PDD. Further studies are needed to understand the predictors and mechanisms of cognitive decline in DLB.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Cognition Disorders; Cohort Studies; Female; Humans; International Cooperation; Lewy Body Disease; Male; Mental Status Schedule; Middle Aged

Low Cognitive Awareness, but Not Complaint, is a Good Marker of Preclinical Alzheimer's Disease. - Cacciamani, Federica; Tandetnik, Caroline; Gagliardi, Geoffroy; Bertin, Hugo; Habert, Marie-Odile; Hampel, Harald; Boukadida, Laurie; Révillon, Marie; Epelbaum, Stéphane; Dubois, Bruno (J Alzheimers Dis, 2017)
BACKGROUND: Subjective cognitive decline (SCD) may result from many conditions, including Alzheimer's disease (AD). OBJECTIVE: In this study, we searched for a specific pattern of SCD in asymptomatic individuals at risk for AD. METHODS: Cognitively normal older adults (N = 318) reporting SCD and their informants were enrolled in the INSIGHT-PreAD cohort. We examined the relationship between six SCD measures and both cognitive scores and AD neuroimaging markers (amyloid burden, hippocampal atrophy and brain hypometabolism). An awareness of cognitive decline index (ACDI) has been introduced based on the subject-informant discrepancy in a questionnaire of SCD and participants with low versus high awareness were compared. RESULTS: Scores in the INSIGHT-PreAD SCD questionnaires did not correlate with AD neuroimaging markers. As well, no correlation has been found between SCD measures and cognitive scores. Comparing subjects with a low (n = 19) and high (n = 86) level of awareness, no significant difference in terms of demography, neuropsychiatric symptoms, autonomy, quality of life, cognition, and hippocampal volume was found. However, the "low awareness" group showed greater amyloid burden and lower cortical metabolism, compared to the "high awareness" group. CONCLUSION: This study provided additional evidence that reporting SCD by itself is not a specific symptom of preclinical AD. Conversely, a low cognitive awareness (namely, when subjects report fewer difficulties than their relatives do) may represent a very early form of anosognosia and serve as a specific indicator of preclinical AD. This finding is of key importance as an enrichment factor to consider in both clinical practice and research trials.

Low Erythrocyte Levels of Proteasome and Acyl-Peptide Hydrolase (APEH) Activities in Alzheimer's Disease: A Sign of Defective Proteostasis? - Palmieri, Gianna; Cocca, Ennio; Gogliettino, Marta; Valentino, Roberta; Ruvo, Menotti; Cristofano, Gloria; Angiolillo, Antonella; Balestrieri, Marco; Rossi, Mosè; Di Costanzo, Alfonso (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a progressive, multifactorial neurodegenerative disorder that is the main cause of dementia. To date, there are no definitive diagnostic tests that can predict or assess onset and progression of the disease. Blood biomarkers for AD are being sought for many years but their identification remains a challenging task. In this study, we investigated the potential relationship between AD and levels of acyl-peptide hydrolase (APEH) and proteasome in erythrocyte samples of 52 participants (26 AD and 26 cognitively healthy controls). A statistically significant decrease in proteasome and exopeptidase/endopeptidase APEH activities was found in AD samples compared to those of healthy controls. Moreover, in contrast to what was observed for proteasome transcripts, APEH activities reduction in AD patients was unrelated to its gene expression levels, suggesting the occurrence of posttranslational modifications or the expression of endogenous inhibitors that might impair enzyme activity. These preliminary data further support a relationship between the APEH-proteasome system and AD molecular players, providing the first evidence of its potential use as a novel blood-based indicator for the routine detection of AD.

Memory Correlates of Alzheimer's Disease Cerebrospinal Fluid Markers: A Longitudinal Cohort Study. - Reijs, Babette L R; Ramakers, Inez H G B; Köhler, Sebastian; Teunissen, Charlotte E; Koel-Simmelink, Marleen; Nathan, Pradeep J; Tsolaki, Magda; Wahlund, Lars-Olof; Waldemar, Gunhild; Hausner, Lucrezia; Vandenberghe, Rik; Johannsen, Peter; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Performance on episodic, semantic, and working memory tests is impaired in Alzheimer's disease (AD)-type dementia, but it is unclear which type of memory test is most strongly associated with early AD biomarkers in cerebrospinal fluid (CSF), and most useful for monitoring disease progression. OBJECTIVE: To examine the association between amyloid-β 1-42 (Aβ42) and tau in CSF with performance on different memory domains at baseline, and how these CSF markers are related with memory decline. METHODS: We included 263 individuals with normal cognition, mild cognitive impairment, AD-type dementia, and non-AD dementia from the European EDAR study. Assessment included CSF Aβ42 and t-tau analyses with INNO-BIA AlzBio3 Luminex assay, the CERAD wordlist learning and delayed recall, animal fluency test, and the CANTAB Paired Associates Learning (PAL) and Spatial Working Memory tasks. Follow-up assessments were performed within 3 years after baseline. RESULTS: At baseline, decreased CSF Aβ42 correlated most strongly with the PAL total errors adjusted and the wordlist delayed recall and increased CSF t-tau with the wordlist delayed recall. Over time, decreased CSF Aβ42 was associated with decline on the wordlist learning, whereas increased CSF t-tau were associated with decline in scores on the wordlist learning, wordlist delayed recall, and animal fluency. Associations were independent of baseline diagnosis. CONCLUSION: Tests assessing episodic verbal and visuospatial memory are most useful for detection of AD pathology. Tests for episodic verbal memory and semantic memory are most useful for tracking memory decline.

Methylene Blue (Tetramethylthionine Chloride) Influences the Mobility of Adult Neural Stem Cells: A Potentially Novel Therapeutic Mechanism of a Therapeutic Approach in the Treatment of Alzheimer's Disease. - van der Ven, Amelie T; Pape, Julius C; Hermann, Dirk; Schloesser, Robert; Genius, Just; Fischer, Nadine; Mößner, Rainald; Scherbaum, Norbert; Wiltfang, Jens; Rujescu, Dan; Benninghoff, Jens (J Alzheimers Dis, 2017)
An interest in neurogenesis in the adult human brain as a relevant and targetable process has emerged as a potential treatment option for Alzheimer's disease and other neurodegenerative conditions. The aim of this study was to investigate the effects of tetramethylthionine chloride (methylene blue, MB) on properties of adult murine neural stem cells. Based on recent clinical studies, MB has increasingly been discussed as a potential treatment for Alzheimer's disease. While no differences in the proliferative capacity were identified, a general potential of MB in modulating the migratory capacity of adult neural stem cells was indicated in a cell mobility assay. To our knowledge, this is the first time that MB could be associated with neural mobility. The results of this study add insight to the spectrum of features of MB within the central nervous system and may be helpful for understanding the molecular mechanisms underlying a potential therapeutic effect of MB.

The Methylenetetrahydrofolate Reductase C677T Polymorphism and Risk for Late-Onset Alzheimer's disease: Further Evidence in an Italian Multicenter Study. - Stoccoro, Andrea; Tannorella, Pierpaola; Salluzzo, Maria Grazia; Ferri, Raffaele; Romano, Corrado; Nacmias, Benedetta; Siciliano, Gabriele; Migliore, Lucia; Coppedè, Fabio (J Alzheimers Dis, 2017)
BACKGROUND: A functional polymorphism in the methylenetetrahydrofolate reductase (MTHFR) gene, namely C677T (rs1801133), results in increased Hcy levels and has been associated with risk of late-onset Alzheimer's disease (LOAD). Many investigators reported association between rs1801133 and LOAD risk in Asian populations and in carriers of the apolipoprotein E (APOE) ɛ4 allele, but recent meta-analyses suggest a contribution also in other populations, including Caucasians and/or northern Africans. OBJECTIVE: To further address this issue, we performed a relatively large case-control study, including 581 LOAD patients and 468 matched controls of Italian origin. APOE data were available for a subgroup of almost 600 subjects. METHODS: Genotyping for rs1801133 was performed with PCR-RFLP techniques. RESULTS: In the total population, the MTHFR 677T allele (OR = 1.20; 95% CI = 1.01-1.43) and carriers of the MTHFR 677T allele (CT+TT versus CC: OR = 1.34; 95% CI = 1.03-1.73) resulted in increased LOAD risk. Similarly, in APOEɛ4 carriers, we observed an increased frequency of MTHFR 677CT carriers (CT versus CC: OR = 2.82; 95% CI = 1.25-6.32). Very interestingly, also in non-APOEɛ4 carriers, both MTHFR 677T allele (OR = 1.38; 95% CI = 1.03-1.85) and MTHFR 677TT genotype (OR = 2.08; 95% CI = 1.11-3.90) were associated with LOAD. All these associations survived after corrections for age, gender, and multiple testing. CONCLUSIONS: The present results suggest that the MTHFR C677T polymorphism is likely a LOAD risk factor in our cohort, either in APOEɛ4 or in non-APOEɛ4 carriers.

MicroRNA Profile in Patients with Alzheimer's Disease: Analysis of miR-9-5p and miR-598 in Raw and Exosome Enriched Cerebrospinal Fluid Samples. - Riancho, Javier; Vázquez-Higuera, José Luis; Pozueta, Ana; Lage, Carmen; Kazimierczak, Martha; Bravo, María; Calero, Miguel; Gonalezález, Andrea; Rodríguez, Eloy; Lleo, Alberto; Sánchez-Juan, Pascual (J Alzheimers Dis, 2017)
BACKGROUND: MicroRNAs have been postulated as potential biomarkers for Alzheimer's disease (AD). Exosomes are nanovesicles which transport microRNAs, proteins, and other cargos. It has been hypothesized that the exosome traffic might be increased in neurodegenerative disorders. OBJECTIVE: i) To assess the cerebrospinal fluid (CSF) microRNA profile in a group of AD patients and control subjects and to validate a group of microRNAs previously reported by other authors. ii) To compare microRNA levels in whole CSF and in the exosome-enriched fraction in AD patients. METHODS: A panel of 760 microRNAs was analyzed in the CSF of 10 AD patients and 10 healthy subjects. Among microRNAs differently expressed, we selected those that had been previously reported by other authors. Candidates were validated in a larger group by individual qPCR assays. MicroRNA expression was also evaluated in exosome-enriched CSF samples of patients with AD and controls. RESULTS: Fifteen microRNAs were differently expressed in AD. MiR-9-5p, miR-134, and miR-598 were selected as candidates for further analysis. MiR-9-5p and miR-598 were detected in 50 and 75% of control CSF samples, respectively, while they were not detected in any AD CSF samples. We observed an opposite pattern when we evaluated the microRNA expression in the exosome-enriched CSF AD samples. No pattern variations were noted among healthy subjects. CONCLUSION: These data propose miR-9-5p and miR-598 as potential biomarkers for AD. Further studies in plasma and other body fluids will confirm their potential role as easily accessible biomarkers. In addition, our data suggest that exosome trafficking is different between AD and control subjects raising the need to take this phenomenon into consideration in future studies of AD biomarkers.

The Mild Behavioral Impairment Checklist (MBI-C): A Rating Scale for Neuropsychiatric Symptoms in Pre-Dementia Populations. - Ismail, Zahinoor; Agüera-Ortiz, Luis; Brodaty, Henry; Cieslak, Alicja; Cummings, Jeffrey; Fischer, Corinne E; Gauthier, Serge; Geda, Yonas E; Herrmann, Nathan; Kanji, Jamila; Lanctôt, Krista L; Miller, David S; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Mild behavioral impairment (MBI) is a construct that describes the emergence at ≥50 years of age of sustained and impactful neuropsychiatric symptoms (NPS), as a precursor to cognitive decline and dementia. MBI describes NPS of any severity, which are not captured by traditional psychiatric nosology, persist for at least 6 months, and occur in advance of or in concert with mild cognitive impairment. While the detection and description of MBI has been operationalized in the International Society to Advance Alzheimer's Research and Treatment - Alzheimer's Association (ISTAART-AA) research diagnostic criteria, there is no instrument that accurately reflects MBI as described. OBJECTIVE: To develop an instrument based on ISTAART-AA MBI criteria. METHODS: Eighteen subject matter experts participated in development using a modified Delphi process. An iterative process ensured items reflected the five MBI domains of 1) decreased motivation; 2) emotional dysregulation; 3) impulse dyscontrol; 4) social inappropriateness; and 5) abnormal perception or thought content. Instrument language was developed a priori to pertain to non-demented functionally independent older adults. RESULTS: We present the Mild Behavioral Impairment Checklist (MBI-C), a 34-item instrument, which can easily be completed by a patient, close informant, or clinician. CONCLUSION: The MBI-C provides the first measure specifically developed to assess the MBI construct as explicitly described in the criteria. Its utility lies in MBI case detection, and monitoring the emergence of MBI symptoms and domains over time. Studies are required to determine the prognostic value of MBI for dementia development, and for predicting different dementia subtypes.

Mitochondria in Excitatory and Inhibitory Synapses have Similar Susceptibility to Amyloid-β Peptides Modeling Alzheimer's Disease. - Amorim, João A; Canas, Paula M; Tomé, Angelo R; Rolo, Anabela P; Agostinho, Paula; Palmeira, Carlos M; Cunha, Rodrigo A (J Alzheimers Dis, 2017)
Mitochondrial dysfunction is proposed to trigger memory deficits and synaptic damage at the onset of Alzheimer's disease (AD). However, it is unknown how mitochondria dysfunction might trigger synaptotoxicity and if a differential susceptibility of mitochondria located in synapses underlies the greater glutamatergic than GABAergic synaptotoxicity in early AD. Hippocampal synaptosomes (purified synapses) of a rat model of early AD, typified by selective memory deficits two weeks after intracerebroventricular injection of amyloid-β peptides (Aβ1-42, 2 nmol), simultaneously displayed three mitochondria-associated deleterious alterations: 1) hampered metabolism (decreased MTT reduction); 2) increased oxygen radical production (increased hydrogen peroxide production); 3) increased caspase-3 activity. The direct exposure of hippocampal synaptosomes to Aβ1-42 (500 nM) similarly decreased mitochondrial membrane potential (TMRM+ fluorescence) and increased mitochondria-derived oxygen radicals (MitoTraker®red-CM-H2Xros fluorescence) in individual glutamatergic (vesicular glutamate transporter-immunopositive) and GABAergic (vesicular GABA transporter-immunopositive) synaptosomes. However, significantly more glutamatergic than GABAergic synaptosomes were endowed with mitochondria (Tom20-immunopositive). These results indicate that dysfunctional mitochondria located in synapses can trigger synaptotoxicity through multifaceted mechanisms and that it is not the susceptibility of mitochondria to Aβ but more likely a different impact of dysfunctional mitochondria that underlies the greater sensitivity to synaptotoxicity of glutamatergic than GABA synapses in early AD.

Mitochondria-Division Inhibitor 1 Protects Against Amyloid-β induced Mitochondrial Fragmentation and Synaptic Damage in Alzheimer's Disease. - Reddy, P Hemachandra; Manczak, Maria; Yin, XiangLing (J Alzheimers Dis, 2017)
The purpose our study was to determine the protective effects of mitochondria division inhibitor 1 (Mdivi1) in Alzheimer's disease (AD). Mdivi1 is hypothesized to reduce excessive fragmentation of mitochondria and mitochondrial dysfunction in AD neurons. Very little is known about whether Mdivi1 can confer protective effects in AD. In the present study, we sought to determine the protective effects of Mdivi1 against amyloid-β (Aβ)- and mitochondrial fission protein, dynamin-related protein 1 (Drp1)-induced excessive fragmentation of mitochondria in AD progression. We also studied preventive (Mdivi1+Aβ42) and intervention (Aβ42+Mdivi1) effects against Aβ42 in N2a cells. Using real-time RT-PCR and immunoblotting analysis, we measured mRNA and protein levels of mitochondrial dynamics, mitochondrial biogenesis, and synaptic genes. We also assessed mitochondrial function by measuring H2O2, lipid peroxidation, cytochrome oxidase activity, and mitochondrial ATP. MTT assays were used to assess the cell viability. Aβ42 was found to impair mitochondrial dynamics, lower mitochondrial biogenesis, lower synaptic activity, and lower mitochondrial function. On the contrary, Mdivi1 enhanced mitochondrial fusion activity, lowered fission machinery, and increased biogenesis and synaptic proteins. Mitochondrial function and cell viability were elevated in Mdivi1-treated cells. Interestingly, Mdivi1 pre- and post-treated cells treated with Aβ showed reduced mitochondrial dysfunction, and maintained cell viability, mitochondrial dynamics, mitochondrial biogenesis, and synaptic activity. The protective effects of Mdivi1 were stronger in N2a+Aβ42 pre-treated with Mdivi1, than in N2a+Aβ42 cells than Mdivi1 post-treated cells, indicating that Mdivi1 works better in prevention than treatment in AD like neurons.

Mitochondrial Abnormalities and Synaptic Loss Underlie Memory Deficits Seen in Mouse Models of Obesity and Alzheimer's Disease. - Martins, Isaura V A; Rivers-Auty, Jack; Allan, Stuart M; Lawrence, Catherine B (J Alzheimers Dis, 2017)
Obesity is associated with impaired memory in humans, and obesity induced by high-fat diets leads to cognitive deficits in rodents and in mouse models of Alzheimer's disease (AD). However, it remains unclear how high-fat diets contribute to memory impairment. Therefore, we tested the effect of a high-fat diet on memory in male and female control non-transgenic (Non-Tg) and triple-transgenic AD (3xTgAD) mice and determined if a high-fat diet caused similar ultrastructural abnormalities to those observed in AD. Behavior was assessed in mice on control or high-fat diet at 4, 8, or 14 months of age and ultrastructural analysis at 8 months of age. A high-fat diet increased body weight, fat weight, and insulin levels with some differences in these metabolic responses observed between Non-Tg and 3xTgAD mice. In both sexes, high-fat feeding caused memory impairments in Non-Tg mice and accelerated memory deficits in 3xTgAD mice. In 3xTgAD mice, changes in hippocampal mitochondrial morphology were observed in capillaries and brain neuropil that were accompanied by a reduction in synapse number. A high-fat diet also caused mitochondria abnormalities and a reduction in synapse number in Non-Tg mice, but did not exacerbate the changes seen in 3xTgAD mice. Our data demonstrate that a high-fat diet affected memory in Non-Tg mice and produced similar impairments in mitochondrial morphology and synapse number comparable to those seen in AD mice, suggesting that the detrimental effects of a high-fat diet on memory might be due to changes in mitochondrial morphology leading to a reduction in synaptic number.

Modifiable Risk Factors for Prevention of Dementia in Midlife, Late Life and the Oldest-Old: Validation of the LIBRA Index. - Vos, Stephanie J B; van Boxtel, Martin P J; Schiepers, Olga J G; Deckers, Kay; de Vugt, Marjolein; Carrière, Isabelle; Dartigues, Jean-François; Pérès, Karine; Artero, Sylvaine; Ritchie, Karen; Galluzzo, Lucia; Scafato, Emanuele; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Recently, the LIfestyle for BRAin health (LIBRA) index was developed to assess an individual's prevention potential for dementia. OBJECTIVE: We investigated the predictive validity of the LIBRA index for incident dementia in midlife, late life, and the oldest-old. METHODS: 9,387 non-demented individuals were recruited from the European population-based DESCRIPA study. An individual's LIBRA index was calculated solely based on modifiable risk factors: depression, diabetes, physical activity, hypertension, obesity, smoking, hypercholesterolemia, coronary heart disease, and mild/moderate alcohol use. Cox regression was used to test the predictive validity of LIBRA for dementia at follow-up (mean 7.2 y, range 1-16). RESULTS: In midlife (55-69 y, n = 3,256) and late life (70-79 y, n = 4,320), the risk for dementia increased with higher LIBRA scores. Individuals in the intermediate- and high-risk groups had a higher risk of dementia than those in the low-risk group. In the oldest-old (80-97 y, n = 1,811), higher LIBRA scores did not increase the risk for dementia. CONCLUSION: LIBRA might be a useful tool to identify individuals for primary prevention interventions of dementia in midlife, and maybe in late life, but not in the oldest-old.

The Modified Frontal Behavioral Inventory (FBI-mod) for Patients with Frontotemporal Lobar Degeneration, Alzheimer's Disease, and Mild Cognitive Impairment. - Suhonen, Noora-Maria; Hallikainen, Ilona; Hänninen, Tuomo; Jokelainen, Jari; Krüger, Johanna; Hall, Anette; Pikkarainen, Maria; Soininen, Hilkka; Remes, Anne M (J Alzheimers Dis, 2017)
While behavioral symptoms are both early and prevalent features of behavioral variant frontotemporal dementia (bvFTD), they can be present in other types of dementia as well, including Alzheimer's disease (AD) and even mild cognitive impairment (MCI). The Frontal Behavioral Inventory (FBI) was specifically developed to capture the behavioral and personality changes in bvFTD; it has also been modified into a self-administered caregiver questionnaire (FBI-mod). We examined the utility of the FBI-mod in differentiating bvFTD (n = 26), primary progressive aphasia (PPA) (n = 7), AD (n = 53), and MCI (n = 50) patients, and investigated how the FBI-mod may be associated with neuropsychological measures. The bvFTD patients scored significantly higher as compared to all other patient groups on the FBI-mod Total (p < 0.005), Negative (p < 0.005), and Positive (p < 0.01) scores. The cut-off point for the FBI-mod Total score that best discriminated the bvFTD and AD patients in our sample was 16, thus substantially lower than reported for the original FBI. For the bvFTD group, only mild correlations emerged between the FBI-mod and the cognitive measures. However, significant correlations between the FBI-mod and depressive symptoms as measured by the BDI-II were found for bvFTD. This suggests that while behavioral symptoms appear independent from cognitive deficits in bvFTD, they may nevertheless be interrelated with depressive symptoms. We conclude that the FBI-mod is an easily administered behavioral scale that can aid in differential diagnosis of bvFTD and should be used in clinical practice. The FBI-mod may further be considered as an outcome measure in clinical trials.

Modulation of Immune Responses to Herpes Simplex Virus Type 1 by IFNL3 and IRF7 Polymorphisms: A Study in Alzheimer's Disease. - Costa, Andrea Saul; Agostini, Simone; Guerini, Franca Rosa; Mancuso, Roberta; Zanzottera, Milena; Ripamonti, Enrico; Racca, Vittorio; Nemni, Raffaello; Clerici, Mario (J Alzheimers Dis, 2017)
Herpes simplex virus type 1 (HSV-1) has long been suspected to play a role in Alzheimer's disease (AD), the most common form of dementia. IFN-lambda (IFN-λ) is one of the key cytokine in innate antiviral defenses and, in particular, has an appreciable antiviral activity against HSV-1 infection. IFN-λ expression is regulated by the interaction between two different proteins: Mediator Complex 23 (MED23) and Interferon-Responsive Transcription Factor 7 (IRF7); single nucleotide polymorphisms (SNPs) in these genes as well as in IFNL3 were shown to be differently distributed in AD patients. In this study, allelic discrimination analysis for IFNL3 rs12979860, MED23 rs3756784, and IRF7 rs6598008, as well as IFN-λ serum concentration and anti-HSV-1 antibody (Ab) titers were performed in 79 AD patients, 57 mild cognitive impairment (MCI) individuals, and 81 healthy controls (HC) who were HSV-1-seropositive. Results showed that INF-λ serum concentration was increased in AD and MCI carrying the IFNL3 T allele compared to HC (AD versus HC: p = 0.014; MCI versus HC: p = 0.029), with the highest anti-HSV-1 Ab titers seen in AD patients carrying the IFNL3 CC genotype (p = 0.012 versus HC). Notably, anti-HSV-1 Ab titers were higher in AD and MCI individuals carrying the IRF7 AA genotype compared to HC (p = 0.018 for both). MED23 polymorphisms did not show any statistical association either with serum IFN-λ or with anti-HSV-1 Ab. Data herein suggest that the IFNL3 rs12979860 and IRF7 rs6598008 polymorphisms modulate immune responses against HSV-1 via their effect on the IFN-λ pathway. These results help to clarify the possible role of HSV-1 infection in AD pathogenesis.

A Multi-Cohort Study of ApoE ɛ4 and Amyloid-β Effects on the Hippocampus in Alzheimer's Disease. - Khan, Wasim; Giampietro, Vincent; Banaschewski, Tobias; Barker, Gareth J; Bokde, Arun L W; Büchel, Christian; Conrod, Patricia; Flor, Herta; Frouin, Vincent; Garavan, Hugh; Gowland, Penny; Heinz, Anreas; et al. (J Alzheimers Dis, 2017)
The apolipoprotein E (APOE) gene has been consistently shown to modulate the risk of Alzheimer's disease (AD). Here, using an AD and normal aging dataset primarily consisting of three AD multi-center studies (n = 1,781), we compared the effect of APOE and amyloid-β (Aβ) on baseline hippocampal volumes in AD patients, mild cognitive impairment (MCI) subjects, and healthy controls. A large sample of healthy adolescents (n = 1,387) was also used to compared hippocampal volumes between APOE groups. Subjects had undergone a magnetic resonance imaging (MRI) scan and APOE genotyping. Hippocampal volumes were processed using FreeSurfer. In the AD and normal aging dataset, hippocampal comparisons were performed in each APOE group and in ɛ4 carriers with positron emission tomography Aβ who were dichotomized (Aβ+/Aβ-) using previous cut-offs. We found a linear reduction in hippocampal volumes with ɛ4 carriers possessing the smallest volumes, ɛ3 carriers possessing intermediate volumes, and ɛ2 carriers possessing the largest volumes. Moreover, AD and MCI ɛ4 carriers possessed the smallest hippocampal volumes and control ɛ2 carriers possessed the largest hippocampal volumes. Subjects with both APOE ɛ4 and Aβ+ had the lowest hippocampal volumes when compared to Aβ- ɛ4 carriers, suggesting a synergistic relationship between APOE ɛ4 and Aβ. However, we found no hippocampal volume differences between APOE groups in healthy 14-year-old adolescents. Our findings suggest that the strongest neuroanatomic effect of APOE ɛ4 on the hippocampus is observed in AD and groups most at risk of developing the disease, whereas hippocampi of old and young healthy individuals remain unaffected.

The Multimerization State of the Amyloid-β42 Amyloid Peptide Governs its Interaction Network with the Extracellular Matrix. - Salza, Romain; Lethias, Claire; Ricard-Blum, Sylvie (J Alzheimers Dis, 2017)
The goals of this work were i) to identify the interactions of amyloid-β (Aβ)42 under monomeric, oligomeric, and fibrillar forms with the extracellular matrix (ECM) and receptors, ii) to determine the influence of Aβ42 supramolecular organization on these interactions, and iii) to identify the molecular functions, biological processes, and pathways targeted by Aβ42 in the ECM. The ECM and cell surface partners of Aβ42 and its supramolecular forms were identified with protein and glycosaminoglycan (GAG) arrays (81 molecules in triplicate) probed by surface plasmon resonance imaging. The number of partners of Aβ42 increased upon its multimerization, ranging from 4 for the peptide up to 53 for the fibrillar aggregates. The peptide interacted only with ECM proteins but their percentage among Aβ42 partners decreased upon multimerization. Aβ42 and its supramolecular forms recognized different molecular features on their partners, and the partners of Aβ42 fibrillar forms were enriched in laminin IV-A, N-terminal, and EGF-like domains. Aβ42 oligomerization triggered interactions with receptors, whereas Aβ42 fibrillogenesis promoted binding to GAGs, proteoglycans, enzymes, and growth factors and the ability to interact with perineuronal nets. Fibril aggregation bind to further membrane proteins including tumor endothelial marker-8, syndecan-4, and discoidin-domain receptor-2. The partners of the Aβ42 supramolecular forms are enriched in proteins contributing to cell growth and/or maintenance, involved in integrin cell surface interactions and expressed in kidney cancer, preadipocytes, and dentin. In conclusion, the supramolecular assembly of Aβ42 governs its ability to interact in vitro with ECM proteins, remodeling and crosslinking ECM enzymes, proteoglycans, and receptors.

Multimodal Cognitive Enhancement Therapy for Patients with Mild Cognitive Impairment and Mild Dementia: A Multi- Center, Randomized, Controlled, Double-Blind, Crossover Trial. - Han, Ji Won; Lee, Hyeonggon; Hong, Jong Woo; Kim, Kayoung; Kim, Taehyun; Byun, Hye Jin; Ko, Ji Won; Youn, Jong Chul; Ryu, Seung-Ho; Lee, Nam-Jin; Pae, Chi-Un; Kim, Ki Woong (J Alzheimers Dis, 2017)
We developed and evaluated the effect of Multimodal Cognitive Enhancement Therapy (MCET) consisting of cognitive training, cognitive stimulations, reality orientation, physical therapy, reminiscence therapy, and music therapy in combination in older people with mild cognitive impairment (MCI) or mild dementia. This study was a multi-center, double-blind, randomized, placebo-controlled, two-period cross-over study (two 8-week treatment phases separated by a 4-week wash-out period). Sixty-four participants with MCI or dementia whose Clinical Dementia Rating was 0.5 or 1 were randomized to the MCET group or the mock-therapy (placebo) group. Outcomes were measured at baseline, week 9, and week 21. Fifty-five patients completed the study. Mini-Mental State Examination (effect size = 0.47, p = 0.013) and Alzheimer's Disease Assessment Scale-Cognitive Subscale (effect size = 0.35, p = 0.045) scores were significantly improved in the MCET compared with mock-therapy group. Revised Memory and Behavior Problems Checklist frequency (effect size = 0.38, p = 0.046) and self-rated Quality of Life - Alzheimer's Disease (effect size = 0.39, p = 0.047) scores were significantly improved in the MCET compared with mock-therapy. MCET improved cognition, behavior, and quality of life in people with MCI or mild dementia more effectively than conventional cognitive enhancing activities did.

Neural Correlates of Self-Reference Effect in Early Alzheimer's Disease. - Gaubert, Malo; Villain, Nicolas; Landeau, Brigitte; Mézenge, Florence; Egret, Stéphanie; Perrotin, Audrey; Belliard, Serge; de la Sayette, Vincent; Eustache, Francis; Desgranges, Béatrice; Chételat, Gaël; Rauchs, Géraldine (J Alzheimers Dis, 2017)
Information that is processed with reference to the self (i.e., self-referential processing, SRP) is generally associated with better remembering than information processed in a semantic condition. This benefit of self on memory performance is called self-reference effect (SRE). In the present study, we assessed changes in the SRE and SRP-related brain activity in patients diagnosed with mild cognitive impairment or early Alzheimer's disease (MCI/AD). Fifteen patients with confirmed amyloid-β deposits (positive florbetapir-PET scan) and 28 healthy controls (negative florbetapir-PET scan) were included. Participants either had to judge personality trait adjectives with reference to themselves (self condition) or to a celebrity (other condition), or determine whether these adjectives were positive or not (semantic condition). These adjectives were then presented with distractors in a surprise recognition task. Functional MRI data were acquired during both the judgment and recognition tasks. The SRE was observed in controls, but reduced in patients. Both controls and patients activated cortical midline structures when judging items with reference to themselves, but patients exhibited reduced activity in the angular gyrus. In patients, activity at encoding in the angular gyrus positively correlated with subsequent recognition accuracy in the self condition (self accuracy). This region also exhibited significant hypometabolism and Aβ burden, both related to self accuracy. By contrast, there were no differences in brain activity during recognition, either between the self and semantic conditions, or between groups. These results highlight SRE impairment in patients with MCI/AD, despite intact activity in cortical midline structures, and suggest that dysfunction of the angular gyrus is related to this impairment.

Neuroimaging and its Relevance to Understanding Pathways Linking Diabetes and Cognitive Dysfunction. - Moran, Chris; Beare, Richard; Phan, Thanh; Starkstein, Sergio; Bruce, David; Romina, Mizrahi; Srikanth, Velandai (J Alzheimers Dis, 2017)
Diabetes mellitus is associated with an elevated risk of cognitive impairment and dementia. Cerebrovascular disease and neurodegeneration are two major pathways that may explain the effect of diabetes on the brain and therefore deserve investigation. Neuroimaging provides an effective way to investigate the contribution of these pathways in vivo, guiding further mechanistic research and providing biomarkers for clinical correlation or interventional studies. In this paper, we present a narrative review of the state of play with neuroimaging evidence in studies of people with diabetes mellitus, how these data are useful in understanding mechanistic links between diabetes and brain impairment, and possible ways that the field may develop in the future.

Neuroimaging Feature Terminology: A Controlled Terminology for the Annotation of Brain Imaging Features. - Iyappan, Anandhi; Younesi, Erfan; Redolfi, Alberto; Vrooman, Henri; Khanna, Shashank; Frisoni, Giovanni B; Hofmann-Apitius, Martin (J Alzheimers Dis, 2017)
Ontologies and terminologies are used for interoperability of knowledge and data in a standard manner among interdisciplinary research groups. Existing imaging ontologies capture general aspects of the imaging domain as a whole such as methodological concepts or calibrations of imaging instruments. However, none of the existing ontologies covers the diagnostic features measured by imaging technologies in the context of neurodegenerative diseases. Therefore, the Neuro-Imaging Feature Terminology (NIFT) was developed to organize the knowledge domain of measured brain features in association with neurodegenerative diseases by imaging technologies. The purpose is to identify quantitative imaging biomarkers that can be extracted from multi-modal brain imaging data. This terminology attempts to cover measured features and parameters in brain scans relevant to disease progression. In this paper, we demonstrate the systematic retrieval of measured indices from literature and how the extracted knowledge can be further used for disease modeling that integrates neuroimaging features with molecular processes.

Neuroprotective Effect of TREM-2 in Aging and Alzheimer's Disease Model. - Raha, Animesh Alexander; Henderson, James W; Stott, Simon R W; Vuono, Romina; Foscarin, Simona; Friedland, Robert P; Zaman, Shahid H; Raha-Chowdhury, Ruma (J Alzheimers Dis, 2017)
Neuroinflammation and activation of innate immunity are early events in neurodegenerative diseases including Alzheimer's disease (AD). Recently, a rare mutation in the gene Triggering receptor expressed on myeloid cells 2 (TREM2) has been associated with a substantial increase in the risk of developing late onset AD. To uncover the molecular mechanisms underlying this association, we investigated the RNA and protein expression of TREM2 in APP/PS1 transgenic mice. Our findings suggest that TREM2 not only plays a critical role in inflammation, but is also involved in neuronal cell survival and in neurogenesis. We have shown that TREM2 is a soluble protein transported by macrophages through ventricle walls and choroid plexus, and then enters the brain parenchyma via radial glial cells. TREM2 protein is essential for neuroplasticity and myelination. During the late stages of life, a lack of TREM2 protein may accelerate aging processes and neuronal cell loss and reduce microglial activity, ultimately leading to neuroinflammation. As inflammation plays a major role in neurodegenerative diseases, a lack of TREM2 could be a missing link between immunomodulation and neuroprotection.

Neuropsychiatric Symptoms and Alzheimer's Disease Biomarkers Predict Driving Decline: Brief Report. - Babulal, Ganesh M; Stout, Sarah H; Head, Denise; Holtzman, David M; Fagan, Anne M; Morris, John C; Roe, Catherine M (J Alzheimers Dis, 2017)
We examined whether neuropsychiatric symptoms (NPS) interact with cerebrospinal fluid (CSF) biomarkers (amyloid-β42 [Aβ42], tau, phosphorylated tau181 [ptau181], tau/Aβ42, and ptau181/Aβ42) of Alzheimer's disease pathology to predict driving decline among cognitively-normal older adults (N = 116) aged ≥65. Cox proportional hazards models examined time to receiving a rating of marginal or fail on the driving test. Age, education, and gender were adjusted in the models. Participants with more abnormal CSF (Aβ42, tau/Aβ42, ptau181/Aβ42) and NPS were faster to receive a marginal/fail on the road test compared to those without NPS. NPS interact with abnormal CSF biomarkers to impact driving performance among cognitively-normal older adults.

Neuropsychological Profile in the C9ORF72 Associated Behavioral Variant Frontotemporal Dementia. - Suhonen, Noora-Maria; Haanpää, Ramona M; Korhonen, Ville; Jokelainen, Jari; Pitkäniemi, Anni; Heikkinen, Anna-Leena; Krüger, Johanna; Hartikainen, Päivi; Helisalmi, Seppo; Hiltunen, Mikko; Hänninen, Tuomo; Remes, Anne M (J Alzheimers Dis, 2017)
While the C9ORF72 expansion is a major cause of behavioral variant frontotemporal dementia (bvFTD), little is known of the resultant cognitive profile. Our aim was to characterize the neuropsychological profile of the C9ORF72 associated bvFTD. We contrasted structured neuropsychological assessments of the C9ORF72 expansion carrier bvFTD patients (n = 26) with non-carrier bvFTD patients (n = 47) and those with Alzheimer's disease (AD) (n = 47). As compared to the non-carrier bvFTD patients, the C9ORF72 expansion carriers performed at a higher level in an immediate verbal memory test while showing poorer phonemic verbal fluency. Additionally, the expansion carriers committed more errors in the Stroop test and the Alternating S task relative to the non-carriers. Finally, while the AD patients outperformed both bvFTD patient groups in working memory, their performance was more impaired in episodic memory tasks relative to the bvFTD groups. We conclude that bvFTD patients carrying the C9ORF72 expansion may display more pronounced executive deficits together with less severe verbal memory impairment as compared to their non-carrier bvFTD counterparts. Knowledge of the specific neuropsychological features associated with the C9ORF72 related bvFTD may aid in the early diagnosis of the disease as well as in targeting genetic testing.

Neuropsychological Symptoms in Sporadic Creutzfeldt-Jakob Disease Patients in Germany. - Krasnianski, Anna; Bohling, Geeske T; Heinemann, Uta; Varges, Daniela; Meissner, Bettina; Schulz-Schaeffer, Walter J; Reif, Andreas; Zerr, Inga (J Alzheimers Dis, 2017)
BACKGROUND: The polymorphism at codon 129 of the prion protein gene (PRNP) and the PrPSc types 1 and 2 belong to a molecular classification of sporadic Creutzfeldt-Jakob disease (sCJD) that correlates well with the clinical and neuropathological phenotype of sCJD. OBJECTIVE: The aim of the study was to perform the first detailed evaluation of neuropsychological deficits in a large group of definite sCJD patients with known molecular subtype. METHODS: We analyzed neuropsychological symptoms in a cohort of 248 sCJD patients with known M129 V polymorphism of PRNP and prion protein type. RESULTS: Neuropsychological symptoms were very frequent in our patients (96%) and occurred as early as in the first third of the disease course. Besides amnesia and impaired attention (89% each), frontal lobe syndrome (75%), aphasia (63%), and apraxia (57%) were the most common neuropsychological deficits. There was no statistically significant difference with regard to frequency of neuropsychological symptoms between the subtypes. In MV2 and VV2 patients, the onset of neuropsychological symptoms was significantly later than in all other subtypes. CONCLUSION: We provide the first detailed analysis of neuropsychological symptoms in a large group of sCJD patients with known M129 V genotype and prion protein type. We suggest that the rate of progression of neuropsychological symptoms is subtype-specific. These data may improve the diagnosis in atypical sCJD subtypes.

A Novel Assessment and Profiling of Multidimensional Apathy in Alzheimer's Disease. - Radakovic, Ratko; Starr, John M; Abrahams, Sharon (J Alzheimers Dis, 2017)
BACKGROUND: Apathy is a complex multidimensional syndrome frequently reported in Alzheimer's disease (AD) and is associated with impaired awareness. Here we present a psychometrically robust method to profile apathy in AD. OBJECTIVES: To determine the validity and reliability of a multidimensional apathy measure, the Dimensional Apathy Scale (DAS), and explore the apathy subtype profile and its associations in AD. METHODS: 102 people with AD and 55 healthy controls were recruited. Participants completed the DAS, the Apathy Evaluation Scale (AES), Geriatric Depression Short form (GDS-15), and Lawton Instrumental Activities of Daily Living (LIADL). Psychometric properties of the DAS were determined. AD-Control comparison was performed to explore group differences on the DAS. Latent Class Analysis (LCA) was used to explore the profile of apathy in AD. RESULTS: The DAS had a good to excellent Cronbach's standardized alpha (self-rated = 0.85, informant/carer-rated = 0.93) and good convergent and divergent validity against standard apathy (AES) and depression (GDS-15) measures. Group comparison showed people with AD were significantly higher for all apathy subtypes than controls (p < 0.001), and lacking in awareness over all apathy subtype deficits. LCA showed three distinct AD subgroups, with 42.2% in the Executive-Initiation apathy, 28.4% in the Global apathy, and 29.4% in the Minimal apathy group. CONCLUSIONS: The DAS is a psychometrically robust method of assessing multidimensional apathy in AD. The apathy profiles in AD are heterogeneous, with additional specific impairments relating to awareness dependent on apathy subtype.

A Novel Loss-of-Function GRN Mutation p.(Tyr229*): Clinical and Neuropathological Features. - Kuuluvainen, Liina; Pöyhönen, Minna; Pasanen, Petra; Siitonen, Maija; Rummukainen, Jaana; Tienari, Pentti J; Paetau, Anders; Myllykangas, Liisa (J Alzheimers Dis, 2017)
Mutations in the progranulin (GRN) gene represent about 5-10% of frontotemporal lobar degeneration (FTLD). We describe a proband with a novel GRN mutation c.687T>A, p.(Tyr229*), presenting with dyspraxia, dysgraphia, and dysphasia at the age of 60 and a very severe FTLD neuropathological phenotype with TDP43 inclusions. The nephew of the proband had signs of dementia and personality changes at the age of 60 and showed similar but milder FTLD pathology. Three other family members had had early-onset dementia. Gene expression studies showed decreased GRN gene expression in mutation carriers' blood samples. In conclusion, we describe a novel GRN, p.(Tyr229*) mutation, resulting in haploinsufficiency of GRN and a severe neuropathologic FTLD phenotype.

Odor Identification Screening Improves Diagnostic Classification in Incipient Alzheimer's Disease. - Quarmley, Megan; Moberg, Paul J; Mechanic-Hamilton, Dawn; Kabadi, Sushila; Arnold, Steven E; Wolk, David A; Roalf, David R (J Alzheimers Dis, 2017)
BACKGROUND: Measurements of olfaction may serve as useful biomarkers of incipient dementia. Here we examine the improvement in diagnostic accuracy of Alzheimer's disease (AD) and mild cognitive impairment (MCI) when assessing both cognitive functioning and odor identification. OBJECTIVE: To determine the utility of odor identification as a supplementary screening test in incipient AD. METHODS: Sniffin' Sticks Odor Identification Test (SS-OIT) and the Montreal Cognitive Assessment (MoCA) were administered in 262 AD, 174 MCI [150 amnestic (aMCI), and 24 non-amnestic (naMCI)], and 292 healthy older adults (HOA). RESULTS: Odor identification scores were higher in HOA relative to MCI or AD groups, and MCI outperformed AD. Odor identification scores were higher in aMCI single domain than aMCI multiple domain. Complementing MoCA scores with the SS-OIT significantly improved diagnostic accuracy of individuals with AD and MCI, including within MCI subgroups. DISCUSSION: Odor identification is a useful supplementary screening tool that provides additional information relevant for clinical categorization of AD and MCI, including those who are at highest risk to convert to AD.

One-Year Evolution of Behavioral and Psychological Symptoms of Dementia in Patients Initially Hospitalized in Cognitive Behavioral Units: The EVITAL Prospective Cohort. - Rouch, Isabelle; Pongan, Elodie; Trombert, Béatrice; Fabre, Florence; Auguste, Nicolas; Sellier, Claire; Freulon, Magalie; Jacqueline, Sophie; Federico, Denis; Mouchoux, Christelle; Martin-Gaujard, Géraldine; Krolak-Salmon, Pierre; et al. (J Alzheimers Dis, 2017)
BACKGROUND: The 2008-2012 French Alzheimer's Plan has provided hospital Cognitive and Behavioral Units (CBU) to improve the management of patients with productive behavioral and psychological symptoms of dementia (BPSD). Little is known concerning the behavioral outcome of these patients after discharge. OBJECTIVE: The present study investigated the long-term evolution of BPSD over one year after CBU discharge. METHODS: The EVITAL cohort included 221 participants admitted to the CBUs of 3 French hospitals. BPSD were collected using the Neuropsychiatric Inventory (NPI) at admission and 3, 6, and 12 months after hospitalization. The global NPI score evolution was assessed using a linear mixed-effect model. A four-factor model of the NPI including behavioral dyscontrol, psychosis, mood, and agitation subscores was also analyzed. RESULTS: Our analysis focused on 148 patients followed up during 12 months and evaluated at each visit. The global NPI score was 48.5 (SD 21.7) at baseline, 28.8 (SD 18.7) at 3-month, 23.2 (SD 16.4) at 6-month and 20.9 (SD 15.9) at 12-month follow-up. The score significantly decreased from baseline to follow-up (F = 109.3 p < 0.0001). Moreover, the decrease was observed for each NPI subscores. The Clinical Dementia Rating (CDR) scale score was significantly linked to the baseline NPI score (t = 2.76, p = 0.009). Conversely, the NPI decline was observed whatever the CDR level. CONCLUSION: The present study showed a decrease in the global NPI score and all its subscores during the year following the CBU hospitalization, regardless of the initial CDR score.

Overexpression of Kinesin Superfamily Motor Proteins in Alzheimer's Disease. - Hares, Kelly; Miners, James Scott; Cook, Amelia Jane; Rice, Claire; Scolding, Neil; Love, Seth; Wilkins, Alastair (J Alzheimers Dis, 2017)
Defects in motor protein-mediated neuronal transport mechanisms have been implicated in a number of neurodegenerative disorders but remain relatively little studied in Alzheimer's disease (AD). Our aim in the present study was to assess the expression of the anterograde kinesin superfamily motor proteins KIF5A, KIF1B, and KIF21B, and to examine their relationship to levels of hyperphosphorylated tau, amyloid-β protein precursor (AβPP), and amyloid-β (Aβ) in human brain tissue. We used a combination of qPCR, immunoblotting, and ELISA to perform these analyses in midfrontal cortex from 49 AD and 46 control brains. Expression of KIF5A, KIF1B, and KIF21B at gene and protein level was significantly increased in AD. KIF5A protein expression correlated inversely with the levels of AβPP and soluble Aβ in AD brains. Upregulation of KIFs may be an adaptive response to impaired axonal transport in AD.

Palmitate Increases β-site AβPP-Cleavage Enzyme 1 Activity and Amyloid-β Genesis by Evoking Endoplasmic Reticulum Stress and Subsequent C/EBP Homologous Protein Activation. - Marwarha, Gurdeep; Rostad, Stephen; Lilek, Jaclyn; Kleinjan, Mason; Schommer, Jared; Ghribi, Othman (J Alzheimers Dis, 2017)
Epidemiological studies implicate diets rich in saturated free fatty acids (sFFA) as a potential risk factor for developing Alzheimer's disease (AD). In particular, high plasma levels of the sFFA palmitic acid (palmitate) were shown to inversely correlate with cognitive function. However, the cellular mechanisms by which sFFA may increase the risk for AD are not well known. Endoplasmic reticulum (ER) stress has emerged as one of the signaling pathways initiating and fostering the neurodegenerative changes in AD by increasing the aspartyl protease β-site AβPP cleaving enzyme 1 (BACE1) and amyloid-β (Aβ) genesis. In this study, we determined the extent to which palmitate increases BACE1 and Aβ levels in vitro and in vivo as well as the potential role of ER stress as cellular mechanism underlying palmitate effects. We demonstrate, in palmitate-treated SH-SY5Y neuroblastoma cells and in the hippocampi of palmitate-enriched diet-fed mice, that palmitate evokes the activation of the C/EBP Homologous Protein (CHOP), a transcription factor that is specifically responsive to ER stress. Induction of CHOP expression is associated with increased BACE1 mRNA, protein and activity levels, and subsequent enhanced amyloidogenic processing of amyloid-β protein precursor (AβPP) that culminates in a substantial increase in Aβ genesis. We further show that CHOP is an indispensable molecular mediator of palmitate-induced upregulation in BACE1 activity and Aβ genesis. Indeed, we show that Chop-/- mice and CHOP knocked-down SH-SY5Y neuroblastoma cells do not exhibit the same commensurate degree of palmitate-induced increase in BACE1 expression levels and Aβ genesis.
Keywords: Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Aspartic Acid Endopeptidases; Cell Line, Tumor; Dose-Response Relationship, Drug; Endoplasmic Reticulum Stress; Gene Expression Regulation; Hippocampus; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Neuroblastoma; Palmitates; RNA, Messenger; Signal Transduction; Transcription Factor CHOP; Transcription Factors; Transfection

Pathway-Specific Polygenic Risk Scores as Predictors of Amyloid-β Deposition and Cognitive Function in a Sample at Increased Risk for Alzheimer's Disease. - Darst, Burcu F; Koscik, Rebecca L; Racine, Annie M; Oh, Jennifer M; Krause, Rachel A; Carlsson, Cynthia M; Zetterberg, Henrik; Blennow, Kaj; Christian, Bradley T; Bendlin, Barbara B; Okonkwo, Ozioma C; Hogan, Kirk J; et al. (J Alzheimers Dis, 2017)
Polygenic risk scores (PRSs) have been used to combine the effects of variants with small effects identified by genome-wide association studies. We explore the potential for using pathway-specific PRSs as predictors of early changes in Alzheimer's disease (AD)-related biomarkers and cognitive function. Participants were from the Wisconsin Registry for Alzheimer's Prevention, a longitudinal study of adults who were cognitively asymptomatic at enrollment and enriched for a parental history of AD. Using genes associated with AD in the International Genomics of Alzheimer's Project's meta-analysis, we identified clusters of genes that grouped into pathways involved in amyloid-β (Aβ) deposition and neurodegeneration: Aβ clearance, cholesterol metabolism, and immune response. Weighted pathway-specific and overall PRSs were developed and compared to APOE alone. Mixed models were used to assess whether each PRS was associated with cognition in 1,200 individuals, cerebral Aβ deposition measured using amyloid ligand (Pittsburgh compound B) positron emission imaging in 168 individuals, and cerebrospinal fluid Aβ deposition, neurodegeneration, and tau pathology in 111 individuals, with replication performed in an independent sample. We found that PRSs including APOE appeared to be driven by the inclusion of APOE, suggesting that the pathway-specific PRSs used here were not more predictive than an overall PRS or APOE alone. However, pathway-specific PRSs could prove to be useful as more knowledge is gained on the genetic variants involved in specific biological pathways of AD.

PCSK9 Promotes oxLDL-Induced PC12 Cell Apoptosis Through the Bcl-2/Bax-Caspase 9/3 Signaling Pathway. - Liu, Lu-Shan; Bai, Xue-Qin; Gao, Ya; Wu, Qi; Ren, Zhong; Li, Qing; Pan, Li-Hong; He, Ni-Ya; Peng, Juan; Tang, Zhi-Han (J Alzheimers Dis, 2017)
BACKGROUND: Hyperlipidemia is a risk factor for neurodegenerative diseases. Proprotein convertase subtilisin / Kexin type 9 (PCSK9) degrades hepatic low-density lipoprotein receptor (LDLR) to regulate lipid metabolism. It is unclear if PCSK9 plays a role in neurodegenerative diseases. OBJECTIVE: This study was designed to determine whether PCSK9 is crucial between hyperlipidemia and Alzheimer's disease. The interrelationship between PCSK9 and neuronal apoptosis was explored in PC12 cells in response to treatment with oxidized low-density lipoprotein (oxLDL). METHODS: Cultured PC12 cells were serum-starved and incubated with different concentrations of oxLDL for 24 h. Intracytoplasmic lipid droplets were observed by oil red O staining. Morphological assessment of apoptotic cells was performed using Hoechst 33258 staining and flow cytometry analysis. The expression of mRNA and protein was detected by reverse-transcription polymerase chain reaction (RT-PCR) and western blot analyses, respectively. Transfection of small interfering RNA (siRNA) into PC12 cells was conducted using HiperFect Transfection Reagent. Concentrations of Aβ40 and Aβ42 were detected by enzyme-linked immunosorbent assay (ELISA) kit. RESULTS: Intracellular lipid content, the number of apoptotic cells, and PCSK9 expression were increased in PC12 cells after oxLDL treatment. Transfection with PCSK9 siRNA reduced the oxLDL-induced apoptosis of PC12 cells. We further confirmed the involvement of Bcl-2/Bax-Caspase (9, 3) signaling pathway in the regulation of PC12 cells apoptosis.β-Secretase 1, another target gene of PCSK9, was downregulated in PC12 cells in response to oxLDL treatment. Aβ40 and Aβ42 contents were also decreased. CONCLUSION: PCSK9 promotes oxLDL-induced PC12 cell apoptosis through the Bcl-2/Bax-Caspase 9/3 signaling pathway.
Keywords: Amyloid beta-Peptides; Analysis of Variance; Animals; Apoptosis; bcl-2-Associated X Protein; Caspases; Culture Media, Serum-Free; Dose-Response Relationship, Drug; Flow Cytometry; Lipid Metabolism; Lipoproteins, LDL; PC12 Cells; Peptide Fragments; Proprotein Convertase 9; Proto-Oncogene Proteins c-bcl-2; Rats; RNA, Messenger; RNA, Small Interfering; Signal Transduction; Transfection

PET Imaging of Tau Pathology and Relationship to Amyloid, Longitudinal MRI, and Cognitive Change in Down Syndrome: Results from the Down Syndrome Biomarker Initiative (DSBI). - Rafii, Michael S; Lukic, Ana S; Andrews, Randolph D; Brewer, James; Rissman, Robert A; Strother, Stephen C; Wernick, Miles N; Pennington, Craig; Mobley, William C; Ness, Seth; Matthews, Dawn C (J Alzheimers Dis, 2017)
BACKGROUND: Adults with Down syndrome (DS) represent an enriched population for the development of Alzheimer's disease (AD), which could aid the study of therapeutic interventions, and in turn, could benefit from discoveries made in other AD populations. OBJECTIVES: 1) Understand the relationship between tau pathology and age, amyloid deposition, neurodegeneration (MRI and FDG PET), and cognitive and functional performance; 2) detect and differentiate AD-specific changes from DS-specific brain changes in longitudinal MRI. METHODS: Twelve non-demented adults, ages 30 to 60, with DS were enrolled in the Down Syndrome Biomarker Initiative (DSBI), a 3-year, observational, cohort study to demonstrate the feasibility of conducting AD intervention/prevention trials in adults with DS. We collected imaging data with 18F-AV-1451 tau PET, AV-45 amyloid PET, FDG PET, and volumetric MRI, as well as cognitive and functional measures and additional laboratory measures. RESULTS: All amyloid negative subjects imaged were tau-negative. Among the amyloid positive subjects, three had tau in regions associated with Braak stage VI, two at stage V, and one at stage II. Amyloid and tau burden correlated with age. The MRI analysis produced two distinct volumetric patterns. The first differentiated DS from normal (NL) and AD, did not correlate with age or amyloid, and was longitudinally stable. The second pattern reflected AD-like atrophy and differentiated NL from AD. Tau PET and MRI atrophy correlated with several cognitive and functional measures. CONCLUSIONS: Tau accumulation is associated with amyloid positivity and age, as well as with progressive neurodegeneration measurable using FDG and MRI. Tau correlates with cognitive decline, as do AD-specific hypometabolism and atrophy.

PET Tau and Amyloid-β Burden in Mild Alzheimer's Disease: Divergent Relationship with Age, Cognition, and Cerebrospinal Fluid Biomarkers. - Koychev, Ivan; Gunn, Roger N; Firouzian, Azadeh; Lawson, Jennifer; Zamboni, Giovanna; Ridha, Basil; Sahakian, Barbara J; Rowe, James B; Thomas, Alan; Rochester, Lynn; Ffytche, Dominic; Howard, Robert; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Combining PET amyloid-β (Aβ) and tau imaging may be critical for tracking disease progression in Alzheimer's disease (AD). OBJECTIVE: We sought to characterize the relationship between Aβ and tau ligands as well as with other measures of pathology. METHODS: We conducted a multi-center observational study in early AD (MMSE >20) participants aged 50 to 85 y. The schedule included cognitive assessments (ADAS-Cog) and CSF measurement of Aβ and tau at baseline and 6 months; PET-CT imaging with Aβ ([18F]AV45) and tau ([18F]AV1451) ligands at baseline. RESULTS: 22 participants took part in the study with 20 completing its 6-month duration and 12 having both tau and amyloid PET. The PET biomarker analysis revealed a strong negative correlation between age and tau in multiple regions. Entorhinal cortex tau and age interacted significantly in terms of cognitive change over 6 months which may have been to older participants deteriorating faster despite lower levels of cortical tau. Cortical Aβ associated with entorhinal cortex tau while CSF tau/Aβ ratio correlated strongly with cortical tau but not Aβ. CONCLUSION: The negative relationship between age and cortical tau whereby younger patients with mild AD had relatively greater tau burden is potentially important. It suggests that younger-age onset AD may be primarily driven by tau pathology while AD developing later may depend on a multitude of pathological mechanisms. These data also suggest that PET-tau performs better than PET-amyloid in predicting the best validated AD diagnostic marker- the CSF total tau/Aβ ratio.

Phenotype-Dependent Interactions between N-acetyl-L-Aspartate and Acetyl-CoA in Septal SN56 Cholinergic Cells Exposed to an Excess of Zinc. - Zyśk, Marlena; Bielarczyk, Hanna; Gul-Hinc, Sylwia; Dyś, Aleksandra; Gapys, Beata; Ronowska, Anna; Sakowicz-Burkiewicz, Monika; Szutowicz, Andrzej (J Alzheimers Dis, 2017)
Pyruvate dehydrogenase reaction utilizing glucose-derived pyruvate is an almost exclusive source of acetyl-CoA in different cell mitochondrial compartments of the brain. In neuronal mitochondria, the largest fraction of acetyl-CoA is utilized for energy production and the much smaller one for N-acetyl-L-aspartate (NAA) synthesis. Cholinergic neurons, unlike others, require additional amounts of acetyl-CoA for acetylcholine synthesis. Therefore, several neurotoxic signals, which inhibit pyruvate dehydrogenase, generate deeper shortages of acetyl-CoA and greater mortality of cholinergic neurons than noncholinergic ones. NAA is considered to be a marker of neuronal energy status in neuropathic brains. However, there is no data on putative differential fractional distribution of the acetyl-CoA pool between energy producing and NAA or acetylcholine synthesizing pathways in noncholinergic and cholinergic neurons, respectively. Therefore, the aim of this study was to investigate whether zinc-excess, a common excitotoxic signal, may evoke differential effects on the NAA metabolism in neuronal cells with low and high expression of the cholinergic phenotype. Differentiated SN56 neuronal cells, displaying a high activity of choline acetyltransferase and rates of acetylcholine synthesis, contained lower levels of acetyl-CoA and NAA, being more susceptible to ZnCl2 exposition that the nondifferentiated SN56 or differentiated dopaminergic SHSY5Y neuronal and astroglial C6 cells. Differentiated SN56 accumulated greater amounts of Zn2 + from extracellular space than the other ones, and displayed a stronger suppression of pyruvate dehydrogenase complex activity and acetyl-CoA, NAA, ATP, acetylcholine levels, and loss of viability. These data indicate that the acetyl-CoA synthesizing system in neurons constitutes functional unity with energy generating and NAA or acetylcholine pathways of its utilization, which are uniformly affected by neurotoxic conditions.

Physical Exercise Moderates the Relationship of Apolipoprotein E (APOE) Genotype and Dementia Risk: A Population-Based Study. - Fenesi, Barbara; Fang, Hanna; Kovacevic, Ana; Oremus, Mark; Raina, Parminder; Heisz, Jennifer J (J Alzheimers Dis, 2017)
Genetics and lifestyle independently determine dementia risk, but the interaction is unclear. We assessed the interactive relationship of apolipoprotein E (APOE) genotype and physical exercise on dementia risk over a 5-year period in 1,646 older adults from the Canadian Study of Health and Aging who were dementia-free at baseline. Physical exercise moderated the relationship between genotype and dementia (p < 0.01). Specifically, for APOE ɛ4 non-carriers, the odds of developing dementia were higher in non-exercisers than exercisers (OR = 1.98, 95% CI = 1.44, 2.71, p < 0.001), whereas, for APOE ɛ4 carriers, the odds of developing dementia were not significantly different between non-exercisers and exercisers (OR = 0.71, 95% CI = 0.46, 1.31, p = 0.34). Given that most individuals are not at genetic risk, physical exercise may be an effective strategy for preventing dementia.

The Pitfall of Behavioral Variant Frontotemporal Dementia Mimics Despite Multidisciplinary Application of the FTDC Criteria. - Krudop, Welmoed A; Dols, Annemieke; Kerssens, Cora J; Eikelenboom, Piet; Prins, Niels D; Möller, Christiane; Schouws, Sigfried; Rhebergen, Didi; van Exel, Eric; van der Flier, Wiesje M; Sikkes, Sietske; Scheltens, Philip; et al. (J Alzheimers Dis, 2017)
BACKGROUND: The behavioral variant of frontotemporal dementia (bvFTD) has a broad differential diagnosis including other neurological and psychiatric disorders. Psychiatric misdiagnoses occur in up to 50% of bvFTD patients. Numbers on misdiagnosis of bvFTD in psychiatric disorders are lacking. OBJECTIVE: The aim of our study was to investigate the frequency and characteristics of bvFTD misdiagnoses in psychiatric disorders and other neurologic disorders. METHODS: Thirty-five patients with a (possible or probable) bvFTD diagnosis made by specialized memory clinic neurologists were included. Change in diagnosis after consulting a psychiatrist at baseline was recorded as well as change in diagnosis after two years of multidisciplinary neuropsychiatric follow-up. Differences in cognitive and behavioral profiles were investigated per diagnostic group after follow-up (bvFTD, psychiatry, other neurologic disorders). Clinical profiles are described in detail. RESULTS: In 17 patients (48.5%), the bvFTD baseline diagnosis changed: Two at baseline after psychiatric consultation, and 15 after two years of multidisciplinary follow-up. Eleven (64.5%) of these 17 patients (31.5% of total) were reclassified with a psychiatric diagnosis. We found no differences for cognitive baseline profiles between patients with bvFTD versus psychiatric diagnoses. CONCLUSION: In almost half of cases, the initial bvFTD diagnosis was changed after follow-up, most often into a psychiatric disorder. A multidisciplinary neuropsychiatric approach in the diagnostic process of bvFTD results in the identification of treatable disorders. Our findings illustrate a limited specificity of the [18F]FDG-PET-scan and the bvFTD criteria in a neuropsychiatric cohort, especially combined with certain clinical symptoms, like disinhibition, apathy, or loss of empathy.

Plasma Tau Association with Brain Atrophy in Mild Cognitive Impairment and Alzheimer's Disease. - Deters, Kacie D; Risacher, Shannon L; Kim, Sungeun; Nho, Kwangsik; West, John D; Blennow, Kaj; Zetterberg, Henrik; Shaw, Leslie M; Trojanowski, John Q; Weiner, Michael W; Saykin, Andrew J (J Alzheimers Dis, 2017)
BACKGROUND: Peripheral (plasma) and central (cerebrospinal fluid, CSF) measures of tau are higher in Alzheimer's disease (AD) relative to prodromal stages and controls. While elevated CSF tau concentrations have been shown to be associated with lower grey matter density (GMD) in AD-specific regions, this correlation has yet to be examined for plasma in a large study. OBJECTIVE: Determine the neuroanatomical correlates of plasma tau using voxel-based analysis. METHODS: Cross-sectional data for 508 ADNI participants were collected for clinical, plasma total-tau (t-tau), CSF amyloid (Aβ42) and tau, and MRI variables. The relationship between plasma tau and GMD and between CSF t-tau and GMD were assessed on a voxel-by-voxel basis using regression models. Age, sex, APOEɛ4 status, diagnosis, and total intracranial volume were used as covariates where appropriate. Participants were defined as amyloid positive (Aβ+) if CSF Aβ42 was <192 pg/mL. RESULTS: Plasma tau was negatively correlated with GMD in the medial temporal lobe (MTL), precuneus, thalamus, and striatum. The associations with thalamus and striatum were independent of diagnosis. A negative correlation also existed between plasma tau and GMD in Aβ+ participants in the MTL, precuneus, and frontal lobe. When compared to CSF t-tau, plasma tau showed a notably different associated brain atrophy pattern, with only small overlapping regions in the fusiform gyrus. CONCLUSION: Plasma tau may serve as a non-specific marker for neurodegeneration but is still relevant to AD considering low GMD was associated with plasma tau in Aβ+ participants and not Aβ-participants.

Positive and Negative Experiences of Social Support and Risk of Dementia in Later Life: An Investigation Using the English Longitudinal Study of Ageing. - Khondoker, Mizanur; Rafnsson, Snorri Bjorn; Morris, Stephen; Orrell, Martin; Steptoe, Andrew (J Alzheimers Dis, 2017)
BACKGROUND: Having a network of close relationships may reduce the risk of developing dementia. However, social exchange theory suggests that social interaction entails both rewards and costs. The effects of quality of close social relationships in later life on the risk of developing dementia are not well understood. OBJECTIVE: To investigate the effects of positive and negative experiences of social support within key relationships (spouse or partner, children, other immediate family, and friends) on the risk of developing dementia in later life. METHODS: We analyzed 10-year follow up data (2003/4 to 2012/13) in a cohort of 10,055 dementia free (at baseline) core participants aged 50 years and over from the English Longitudinal Study of Ageing (ELSA). Incidence of dementia was identified from participant or informant reported physician diagnosed dementia or overall score of informant-completed IQCODE questionnaire. Effects of positive and negative experiences of social support measured at baseline on risk of developing dementia were investigated using proportional hazards regression accommodating interval censoring of time-to-dementia. RESULTS: There were 340 (3.4%) incident dementia cases during the follow-up. Positive social support from children significantly reduced the risk of dementia (hazard ratio, HR = 0.83, p = 0.042, 95% CI: 0.69 to 0.99). Negative support from other immediate family (HR = 1.26, p = 0.011, CI: 1.05 to 1.50); combined negative scores from spouse and children (HR = 1.23, p = 0.046, CI: 1.004 to 1.51); spouse, children, and other family (HR = 1.27, p = 0.021, CI = 1.04 to 1.56); other family & friends (HR = 1.25, p = 0.033, CI: 1.02 to 1.55); and the overall negative scores (HR = 1.31, p = 0.019, CI: 1.05 to 1.64) all were significantly associated with increased risk of dementia. CONCLUSION: Positive social support from children is associated with reduced risk of developing dementia whereas experiences of negative social support from children and other immediate family increase the risk. Further research is needed to better understand the causal mechanisms that drive these associations.

Potentially Inappropriate Medication in Community-Dwelling Primary Care Patients who were Screened Positive for Dementia. - Wucherer, Diana; Eichler, Tilly; Hertel, Johannes; Kilimann, Ingo; Richter, Steffen; Michalowsky, Bernhard; Thyrian, Jochen René; Teipel, Stefan; Hoffmann, Wolfgang (J Alzheimers Dis, 2017)
BACKGROUND: Potentially inappropriate medication (PIM) in older people is a risk factor for adverse drug effects. This risk is even higher in older people with dementia (PWD). OBJECTIVE: Our study aimed to determine (1) the prevalence of PIM among primary care patients who were screened positive for dementia and (2) the sociodemographic and clinical variables associated with the use of PIM. METHODS: DelpHi-MV (Dementia: life- and person-centered help in Mecklenburg-Western Pomerania) is a general practitioner-based, cluster-randomized, controlled intervention study to implement and evaluate an innovative concept of collaborative dementia care management in Germany. The comprehensive baseline assessment includes a home medication review. The present analyses are based on the data from 448 study participants (age 70+, DemTect <9). PIMs were identified using the list of Potentially Inappropriate Medications in the Elderly (Priscus). RESULTS: (1) A total of 99 study participants (22%) received at least one PIM. The highest prevalence was found for antidepressants, benzodiazepines, and analgetics. The most frequently prescribed PIMs were amitriptyline, etoricoxib, and doxazosin. (2) Use of a PIM was significantly associated with a diagnosis of a mental or behavioral disorder. CONCLUSIONS: The prescription rate of PIMs for community-dwelling PWD was comparable with the rates found for the general population of older people in Germany (20-29%). Antidepressants with anticholinergic properties and long-acting benzodiazepines were the most prescribed PIMs, despite having an unfavorable benefit-risk ratio. This high prevalence of PIM prescriptions in a vulnerable population of PWD indicates that standard care for dementia should include careful medication review and management.

Preclinical Amyloid-β and Axonal Degeneration Pathology in Delirium. - Idland, Ane-Victoria; Wyller, Torgeir Bruun; Støen, Randi; Eri, Lars Magne; Frihagen, Frede; Ræder, Johan; Chaudhry, Farrukh Abbas; Hansson, Oskar; Zetterberg, Henrik; Blennow, Kaj; Bogdanovic, Nenad; Brækhus, Anne; et al. (J Alzheimers Dis, 2017)
BACKGROUND: The clinical relevance of brain β-amyloidosis in older adults without dementia is not established. As delirium and dementia are strongly related, studies on patients with delirium may give pathophysiological clues. OBJECTIVE: To determine whether the Alzheimer's disease (AD) cerebrospinal fluid (CSF) biomarkers amyloid-β 1-42 (Aβ42), total tau (T-tau), and phosphorylated tau (P-tau) are associated with delirium in hip fracture patients with and without dementia. METHODS: CSF was collected in conjunction to spinal anesthesia in 129 patients. Delirium was assessed using the Confusion Assessment Method once daily in all patients, both pre- and postoperatively. The diagnosis of dementia at admission was based upon clinical consensus. CSF levels of Aβ42, T-tau, and P-tau were analyzed. RESULTS: In patients without dementia, we found lower CSF Aβ42 levels (median, 310 ng/L versus 489 ng/L, p = 0.006), higher T-tau levels (median, 505 ng/L versus 351 ng/L, p = 0.02), but no change in P-tau in patients who developed delirium (n = 16) compared to those who remained lucid (n = 49). Delirious patients also had lower ratios of Aβ42 to T-tau (p < 0.001) and P-tau (p = 0.001) relative to those without delirium. CSF Aβ42 and T-tau remained significantly associated with delirium status in adjusted analyses. In patients with dementia, CSF biomarker levels did not differ between those with (n = 54) and without delirium (n = 10). CONCLUSION: The reduction in CSF Aβ42, indicating β-amyloidosis, and increase in T-tau, indicating neurodegeneration, in hip fracture patients without dementia developing delirium indicates that preclinical AD brain pathology is clinically relevant and possibly plays a role in delirium pathophysiology.

Predictors of Discharge Destinations and Three-Month Evolution of Patients Initially Hospitalized in a Cognitive Behavioral Unit. - Pongan, Elodie; Dorey, Jean-Michel; Krolak-Salmon, Pierre; Federico, Denis; Sellier, Claire; Auguste, Nicolas; Fabre, Florence; Laurent, Bernard; Trombert-Paviot, Béatrice; Rouch, Isabelle (J Alzheimers Dis, 2017)
BACKGROUND: Previous studies showed that a third of patients living at home entered an institution after hospitalization in Cognitive and Behavioral Units (CBUs). OBJECTIVE: The main objective of this study was to identify predictors of discharge destination for these patients. The secondary objective was to estimate whether institutionalization can have an impact on a patient's long-term prognosis. METHODS: The study population was selected from the EVITAL study and included 140 participants living at home before hospitalization in CBUs. Factors favoring nursing-home admission were investigated and the impact of discharge destinations (i.e., home or nursing home) on patients' prognosis was examined. RESULTS: Institutionalized patients were more likely to be women (F = 4.7; p = 0.03), with a higher dementia severity (F = 9.82; p = 0.007), often living alone (F = 19.69; p = 0.001), with a caregiver other than spouse (F = 8.93; p = 0.003), and with a higher patient quality of life (QoL) according to the caregiver (F = 11.73; p = 0.001). When using multivariate logistic linear regressions, we showed a relationship between marital status (OR = 0.19, 95% CI: 0.08-0.43, p < 0.001), dementia severity (OR = 0.15, 95% CI: 0.03-0.79, p = 0.03), QoL (OR = 0.88, 95% CI: 0.79-0.98, p = 0.017), and institutionalization. At three months, a higher overall rate of rehospitalization (F = 12.21; p < 0.001) and rehospitalization for behavioral and psychological symptoms of dementia (F = 6.76; p = 0.006) were observed for patients staying at home after CBU discharge. CONCLUSION: Our study allows for a better understanding of the institutionalization risk factors of the patients hospitalized in CBUs. Identification of these factors could help clinicians to better support patients and to help the transition to be smoother. Moreover, our results suggest that prognosis of institutionalized patients is not unfavorable when compared with patients staying at home.

Prevalence and Correlates of Behavioral Disorders in Old Age Subjects with Cognitive Impairment: Results from the ReGAl Project. - Boccardi, Virginia; Conestabile Della Staffa, Manuela; Baroni, Marta; Ercolani, Sara; Croce, Michele Francesco; Ruggiero, Carmelinda; Mecocci, Patrizia (J Alzheimers Dis, 2017)
BACKGROUND: Presence of behavioral and psychological symptoms of dementia (BPSD) is very common in subjects with cognitive impairment, representing an important determinant of disease progression, institutionalization, and worse prognosis. Knowledge of the prevalence and correlates of BPSD in community-living old subjects with cognitive impairment is limited so far, but it is essential for establishing specifically tailored care and cure in such a vulnerable population. OBJECTIVE: With this study, we aimed at investigating, in a large sample of old age subjects with cognitive impairment, BPSD prevalence and correlates including the main demographic, clinical, and socio-environmental characteristics. METHODS: Data were gathered from the ReGAl project (Rete Geriatrica Alzheimer; Geriatric Network on Alzheimer's disease), a large longitudinal Italian multicentric clinical-based study, promoted by the Italian Society of Gerontology and Geriatrics (SIGG). RESULTS: We evaluated data from 4,157 old-age subjects affected by mild cognitive impairment (MCI) (541; 13%) or dementia (3616; 87%). 85.2% of all the population presented with at least one BPSD. Using a factor analysis, we identified four factors of BPSD: psychotic, affective, maniac, and impulse control behaviors. Logistic regression analyses revealed that among the main demographic, clinical, and socio-environmental aspects considered, only comorbidity was associated with all factors, independently of multiple covariates. CONCLUSION: Identification of BPSD is crucial in everyday clinical practice and necessary to develop specific interventions and to define appropriate outcomes in their management. BPSD occur in a complex psychopathological context, influenced by several demographic and environmental factors that must be taken into account for a correct diagnosis and treatment.

The Proactive Self in Space: How Egocentric and Allocentric Spatial Impairments Contribute to Anosognosia in Alzheimer's Disease. - Serino, Silvia; Riva, Giuseppe (J Alzheimers Dis, 2017)
In addition to impairments in episodic and spatial memory, anosognosia (i.e., loss of awareness of the deficient aspect of own cognitive functioning) may be considered an important cognitive marker of Alzheimer's disease (AD). However, although a growing body of interesting models have been proposed to explain this early symptom, what is still missing is a unifying framework of all the characteristic signs occurring in patients with AD that may guide the search for its causal neuropathological process and, ultimately, the etiological process. This contribution will first show how anosognosia may be related to the above-mentioned episodic and spatial memory impairment through a unifying framework of all these characteristic signs, i.e., the continuous interaction between different spatial representations. Second, we hypothesize that a break in the interaction between different spatial representations, as we suggest occurs in AD, may contribute significantly both to the early impairments in spatial and episodic memory, and to a deficient self-awareness since it may interfere with the capacity of the brain to detect predictive errors.

Psychosocial Risk and Protective Factors and Incident Mild Cognitive Impairment and Dementia in Community Dwelling Elderly: Findings from the Singapore Longitudinal Ageing Study. - Rawtaer, Iris; Gao, Qi; Nyunt, Ma Shwe Zin; Feng, Lei; Chong, Mei Sian; Lim, Wee Shiong; Lee, Tih-Shih; Yap, Philip; Yap, Keng Bee; Ng, Tze Pin (J Alzheimers Dis, 2017)
BACKGROUND: Indicators of social isolation or support such as living alone, loneliness, being married, and life satisfaction are possible psychosocial risk and protective factors for dementia. OBJECTIVE: We investigate the associations of these overlapping psychosocial factors with incident MCI-dementia (neurocognitive disorder) in a population cohort. METHODS: Using data from 1601 participants of the Singapore Longitudinal Ageing Study (SLAS) who were free of MCI or dementia at baseline and followed up to 8 years, we estimated hazards ratio (HR) of association of living alone, loneliness, being married, and high life satisfaction with incident MCI-dementia. RESULTS: In univariate analyses, individual HRs of association with incident MCI-dementia for living alone was 1.86 [1.18 - 2.95], (p = 0.008), loneliness was 1.26 [0.86 - 1.84], (p = 0.23), being married was 0.54 [0.39 - 0.75] (p < 0.0001), and being very satisfied with life was 0.59 [0.38-0.91]), (p = 0.017). Adjusted mutually for other psychosocial variables, and for age, sex, education, ethnicity, smoking, alcohol, dyslipidemia, hypertension, diabetes, central obesity, history of stroke or heart disease, APOE-ɛ4, depression, physical, social, and productive activities, only being married (0.68 [0.47-0.99], p = 0.044), and being very satisfied with life (0.61 [0.39 - 0.96], p = 0.034) remained significant variables associated with lower risks of developing MCI-dementia. CONCLUSION: Individuals who were married and those who were very satisfied with life are protected against the risk of developing MCI and dementia. Controlling for the adverse effects of being without spousal support and low life satisfaction, living alone or a feeling of loneliness were not associated with increased risk of MCI-dementia.

Quantification of Butyrylcholinesterase Activity as a Sensitive and Specific Biomarker of Alzheimer's Disease. - Macdonald, Ian R; Maxwell, Selena P; Reid, George A; Cash, Meghan K; DeBay, Drew R; Darvesh, Sultan (J Alzheimers Dis, 2017)
Amyloid-β (Aβ) plaques are a neuropathological hallmark of Alzheimer's disease (AD); however, a significant number of cognitively normal older adults can also have Aβ plaques. Thus, distinguishing AD from cognitively normal individuals with Aβ plaques (NwAβ) based on Aβ plaque detection is challenging. It has been observed that butyrylcholinesterase (BChE) accumulates in plaques preferentially in AD. Thus, detecting BChE-associated plaques has the potential as an improved AD biomarker. We present Aβ, thioflavin-S, and BChE quantification of 26 postmortem brain tissues; AD (n = 8), NwAβ (n = 6), cognitively normal without plaques (n = 8), and other common dementias including corticobasal degeneration, frontotemporal dementia with tau, dementia with Lewy bodies, and vascular dementia. Pathology burden in the orbitofrontal cortex, entorhinal cortex, amygdala, and hippocampal formation was determined and compared. The predictive value of Aβ and BChE quantification was determined, via receiver-operating characteristic plots, to evaluate their AD diagnostic performance using sensitivity, specificity, and area under curve (AUC) metrics. In general, Aβ and BChE-associated pathology were greater in AD, particularly in the orbitofrontal cortex. In this region, the largest increase (9.3-fold) was in BChE-associated pathology, observed between NwAβ and AD, due to the virtual absence of BChE-associated plaques in NwAβ brains. Furthermore, BChE did not associate with pathology of the other dementias. In this sample, BChE-associated pathology provided better diagnostic performance (AUC = 1.0, sensitivity/specificity = 100% /100%) when compared to Aβ (AUC = 0.98, 100% /85.7%). These findings highlight the predictive value of BChE as a biomarker for AD that could facilitate timely disease diagnosis and management.

Quantitative Comparison of Dense-Core Amyloid Plaque Accumulation in Amyloid-β Protein Precursor Transgenic Mice. - Liu, Peng; Reichl, John H; Rao, Eshaan R; McNellis, Brittany M; Huang, Eric S; Hemmy, Laura S; Forster, Colleen L; Kuskowski, Michael A; Borchelt, David R; Vassar, Robert; Ashe, Karen H; Zahs, Kathleen R (J Alzheimers Dis, 2017)
There exist several dozen lines of transgenic mice that express human amyloid-β protein precursor (AβPP) with Alzheimer's disease (AD)-linked mutations. AβPP transgenic mouse lines differ in the types and amounts of Aβ that they generate and in their spatiotemporal patterns of expression of Aβ assemblies, providing a toolkit to study Aβ amyloidosis and the influence of Aβ aggregation on brain function. More complete quantitative descriptions of the types of Aβ assemblies present in transgenic mice and in humans during disease progression should add to our understanding of how Aβ toxicity in mice relates to the pathogenesis of AD. Here, we provide a direct quantitative comparison of amyloid plaque burdens and plaque sizes in four lines of AβPP transgenic mice. We measured the fraction of cortex and hippocampus occupied by dense-core plaques, visualized by staining with Thioflavin S, in mice from young adulthood through advanced age. We found that the plaque burdens among the transgenic lines varied by an order of magnitude: at 15 months of age, the oldest age studied, the median cortical plaque burden in 5XFAD mice was already ∼4.5 times that of 21-month-old Tg2576 mice and ∼15 times that of 21-24-month-old rTg9191 mice. Plaque-size distributions changed across the lifespan in a line- and region-dependent manner. We also compared the dense-core plaque burdens in the mice to those measured in a set of pathologically-confirmed AD cases from the Nun Study. Cortical plaque burdens in Tg2576, APPSwePS1ΔE9, and 5XFAD mice eventually far exceeded those measured in the human cohort.

Quantitative Erythrocyte Omega-3 EPA Plus DHA Levels are Related to Higher Regional Cerebral Blood Flow on Brain SPECT. - Amen, Daniel G; Harris, William S; Kidd, Parris M; Meysami, Somayeh; Raji, Cyrus A (J Alzheimers Dis, 2017)
BACKGROUND: The interrelationships between omega-3 fatty acids status, brain perfusion, and cognition are not well understood. OBJECTIVE: To evaluate if SPECT brain imaging of cerebral perfusion and cognition varies as a function of omega-3 fatty acid levels. METHODS: A random sample of 166 study participants was drawn from a psychiatric referral clinical for which erythrocyte quantification of omega-3 eicosapentaenoic acid (EPA) plus docosahexaenoic acid (DHA) (the Omega-3 Index) was available. Quantitative brain SPECT was done on 128 regions based on a standard anatomical Atlas Persons with erythrocyte EPA+DHA concentrations were dichotomized based on membership in top 50th percentile versus bottom 50th percentile categories. Two-sample t-tests were done to identify statistically significant differences in perfusion between the percentile groups. Partial correlations were modeled between EPA+DHA concentration and SPECT regions. Neurocognitive status was assessed using computerized testing (WebNeuro) and was separately correlated to cerebral perfusion on brain SPECT imaging and omega-3 EPA+DHA levels. RESULTS: Partial correlation analyses showed statistically significant relationships between higher omega-3 levels and cerebral perfusion were in the right parahippocampal gyrus (r = 0.20, p = 0.03), right precuneus (r = 0.20, p = 0.03), and vermis subregion 6 (p = 0.21, p = 0.03). Omega-3 Index levels separately correlated to the feeling subsection of the WebNeuro (r = 0.25, p = 0.01). CONCLUSION: Quantitative omega-3 EPA+DHA erythrocyte concentrations are independently correlated with brain perfusion on SPECT imaging and neurocognitive tests. These results have implications for the role of omega-3 fatty acids toward contributing to cognitive reserve.

A Randomized, Double-Blind, Placebo-Controlled, Phase II Study of Oral ELND005 (scyllo-Inositol) in Young Adults with Down Syndrome without Dementia. - Rafii, Michael S; Skotko, Brian G; McDonough, Mary Ellen; Pulsifer, Margaret; Evans, Casey; Doran, Eric; Muranevici, Gabriela; Kesslak, Patrick; Abushakra, Susan; Lott, Ira T (J Alzheimers Dis, 2017)
BACKGROUND: ELND005 (scyllo-Inositol; cyclohexane-1,2,3,4,5,6-hexol) has been evaluated as a potential disease-modifying treatment for Alzheimer's disease (AD). Individuals with Down syndrome (DS) have an increased risk for developing AD dementia. OBJECTIVE: To evaluate the safety and tolerability of ELND005 and to determine its pharmacokinetics (PK) and relationship between PK parameters, safety outcome measures, and exploratory efficacy outcome measures in young adults with DS without dementia. METHODS: This was a prospective, randomized, double-blind, placebo-controlled, parallel-group, three-arm, multicenter Phase II study of the safety and pharmacokinetics of ELND005 administered orally for 4 weeks (ClinicalTrials.gov NCT01791725). Participants who met study eligibility criteria were randomly assigned in a 2 : 1:1 ratio to receive ELND005 at either 250 mg twice daily (BID) or 250 mg once daily (QD) or matching placebo for 4 weeks. RESULTS: There were no apparent treatment group-related trends on cognitive or behavioral measures and there were no SAEs and no deaths in the study. Overall, mean changes from baseline in clinical laboratory parameters, vital sign measurements, electrocardiogram results, and other physical findings were unremarkable. ELND005 accumulation averaged approximately 2-fold with QD dosing, and 3- to 4-fold with BID dosing. CONCLUSION: Overall, treatment of adults with DS with ELND005 at both doses was well tolerated, achieved measurable blood levels and demonstrated no safety findings. Further studies will be needed to test efficacy.

Rare Genetic Variant in SORL1 May Increase Penetrance of Alzheimer's Disease in a Family with Several Generations of APOE-ɛ4 Homozygosity. - Louwersheimer, Eva; Cohn-Hokke, Petra E; Pijnenburg, Yolande A L; Weiss, Marjan M; Sistermans, Erik A; Rozemuller, Annemieke J; Hulsman, Marc; van Swieten, John C; van Duijn, Cock M; Barkhof, Frederik; Koene, Teddy; Scheltens, Philip; et al. (J Alzheimers Dis, 2017)
BACKGROUND: The major genetic risk factor for late onset Alzheimer's disease (AD) is the APOE-ɛ4 allele. However, APOE-ɛ4 homozygosity is not fully penetrant, suggesting co-occurrence of additional genetic variants. OBJECTIVE: To identify genetic factors that, next to APOE-ɛ4 homozygosity, contribute to the development of AD. METHODS: We identified a family with nine AD patients spanning four generations, with an inheritance pattern suggestive of autosomal dominant AD, with no variants in PSEN1, PSEN2, or APP. We collected DNA from four affected and seven unaffected family members and performed exome sequencing on DNA from three affected and one unaffected family members. RESULTS: All affected family members were homozygous for the APOE-ɛ4 allele. Statistical analysis revealed that AD onset in this family was significantly earlier than could be expected based on APOE genotype and gender. Next to APOE-ɛ4 homozygosity, we found that all four affected family members carried a rare variant in the VPS10 domain of the SORL1 gene, associated with AβPP processing and AD risk. Furthermore, three of four affected family members carried a rare variant in the TSHZ3 gene, also associated with AβPP processing. Affected family members presented between 61 and 74 years, with variable presence of microbleeds/cerebral amyloid angiopathy and electroencephalographic abnormalities. CONCLUSION: We hypothesize that next to APOE-ɛ4 homozygosity, impaired SORL1 protein function, and possibly impaired TSHZ3 function, further disturbed Aβ processing. The convergence of these genetic factors over several generations might clarify the increased AD penetrance and the autosomal dominant-like inheritance pattern of AD as observed in this family.

Recent Progress in Alzheimer's Disease Research, Part 2: Genetics and Epidemiology. - Robinson, Morgan; Lee, Brenda Y; Hane, Francis T (J Alzheimers Dis, 2017)
This is the second part of a three-part review series reviewing the most important advances in Alzheimer's disease (AD) research since 2010. This review covers the latest research on genetics and epidemiology. Epidemiological and genetic studies are revealing important insights into the etiology of, and factors that contribute to AD, as well as areas of priority for research into mechanisms and interventions. The widespread adoption of genome wide association studies has provided compelling evidence of the genetic complexity of AD with genes associated with such diverse physiological function as immunity and lipid metabolism being implicated in AD pathogenesis.

Recent Progress in Alzheimer's Disease Research, Part 3: Diagnosis and Treatment. - Hane, Francis T; Robinson, Morgan; Lee, Brenda Y; Bai, Owen; Leonenko, Zoya; Albert, Mitchell S (J Alzheimers Dis, 2017)
The field of Alzheimer's disease (AD) research has grown exponentially over the past few decades, especially since the isolation and identification of amyloid-β from postmortem examination of the brains of AD patients. Recently, the Journal of Alzheimer's Disease (JAD) put forth approximately 300 research reports which were deemed to be the most influential research reports in the field of AD since 2010. JAD readers were asked to vote on these most influential reports. In this 3-part review, we review the results of the 300 most influential AD research reports to provide JAD readers with a readily accessible, yet comprehensive review of the state of contemporary research. Notably, this multi-part review identifies the "hottest" fields of AD research providing guidance for both senior investigators as well as investigators new to the field on what is the most pressing fields within AD research. Part 1 of this review covers pathogenesis, both on a molecular and macro scale. Part 2 review genetics and epidemiology, and part 3 covers diagnosis and treatment. This part of the review, diagnosis and treatment, reviews the latest diagnostic criteria, biomarkers, imaging, and treatments in AD.
Keywords: Alzheimer Disease; Biomarkers; Biomedical Research; Humans; Neuroimaging

Recovery from Proactive Semantic Interference and MRI Volume: A Replication and Extension Study. - Loewenstein, David A; Curiel, Rosie E; DeKosky, Steven; Rosselli, Monica; Bauer, Russell; Grieg-Custo, Maria; Penate, Ailyn; Li, Chunfei; Lizagarra, Gabriel; Golde, Todd; Adjouadi, Malek; Duara, Ranjan (J Alzheimers Dis, 2017)
BACKGROUND: The rise in incidence of Alzheimer's disease (AD) has led to efforts to advance early detection of the disease during its preclinical stages. To achieve this, the field needs to develop more sensitive cognitive tests that relate to biological markers of disease pathology. Failure to recover from proactive interference (frPSI) is one such cognitive marker that is associated with volumetric reductions in the hippocampus, precuneus, and other AD-prone regions, and to amyloid load in the brain. OBJECTIVE: The current study attempted to replicate and extend our previous findings that frPSI is a sensitive marker of early AD, and related to a unique pattern of volumetric loss in AD prone areas. METHODS: Three different memory measures were examined relative to volumetric loss and cortical thickness among 45 participants with amnestic mild cognitive impairment. RESULTS: frPSI was uniquely associated with reduced volumes in the hippocampus (r = 0.50) precuneus (r = 0.41), and other AD prone regions, replicating previous findings. Strong associations between frPSI and lower entorhinal cortex volumes and cortical thickness (r≥0.60) and precuneus (r = 0.50) were also observed. CONCLUSION: Unique and strong associations between volumetric reductions and frPSI as observed by Loewenstein and colleagues were replicated. Together with cortical thickness findings, these results indicate that frPSI is worthy of further study as a sensitive and early cognitive marker of AD.

Recovery from Proactive Semantic Interference in Mild Cognitive Impairment and Normal Aging: Relationship to Atrophy in Brain Regions Vulnerable to Alzheimer's Disease. - Loewenstein, David A; Curiel, Rosie E; Wright, Clinton; Sun, Xiaoyan; Alperin, Noam; Crocco, Elzabeth; Czaja, Sara J; Raffo, Arlene; Penate, Ailyn; Melo, Jose; Capp, Kimberly; Gamez, Monica; et al. (J Alzheimers Dis, 2017)
BACKGROUND: There is growing evidence that proactive semantic interference (PSI) and failure to recover from PSI may represent early features of Alzheimer's disease (AD). OBJECTIVE: This study investigated the association between PSI, recovery from PSI, and reduced MRI volumes in AD signature regions among cognitively impaired and unimpaired older adults. METHODS: Performance on the LASSI-L (a novel test of PSI and recovery from PSI) and regional brain volumetric measures were compared between 38 cognitively normal (CN) elders and 29 older participants with amnestic mild cognitive impairment (MCI). The relationship between MRI measures and performance on the LASSI-L as well as traditional memory and non-memory cognitive measures was also evaluated in both diagnostic groups. RESULTS: Relative to traditional neuropsychological measures, MCI patients' failure to recover from PSI was associated with reduced volumes in the hippocampus (rs = 0.48), precuneus (rs = 0.50); rostral middle frontal lobules (rs = 0.54); inferior temporal lobules (rs = 0.49), superior parietal lobules (rs = 0.47), temporal pole (rs = 0.44), and increased dilatation of the inferior lateral ventricle (rs = -0.49). For CN elders, only increased inferior lateral ventricular size was associated with vulnerability to PSI (rs = -0.49), the failure to recover from PSI (rs = -0.57), and delayed recall on the Hopkins Verbal Learning Test-Revised (rs = -0.48). DISCUSSION: LASSI-L indices eliciting failure to recover from PSI were more highly associated with more MRI regional biomarkers of AD than other traditional cognitive measures. These results as well as recent amyloid imaging studies with otherwise cognitively normal subjects, suggest that recovery from PSI may be a sensitive marker of preclinical AD and deserves further investigation.

Reduced Cerebral Blood Flow in Mild Cognitive Impairment Assessed Using Phase-Contrast MRI. - de Eulate, Reyes García; Goñi, Irene; Galiano, Alvaro; Vidorreta, Marta; Recio, Miriam; Riverol, Mario; Zubieta, José L; Fernández-Seara, María A (J Alzheimers Dis, 2017)
There is increasing evidence of a vascular contribution to Alzheimer's disease (AD). In some cases, prior work suggests that chronic brain hypoperfusion could play a prime pathogenic role contributing to the accumulation of amyloid-β,while other studies favor the hypothesis that vascular dysfunction and amyloid pathology are independent, although synergistic, mechanisms contributing to cognitive impairment. Vascular dysfunction can be evaluated by assessing cerebral blood flow impairment. Phase contrast velocity mapping by MRI offers a non-invasive means of quantifying the total inflow of blood to the brain. This quantitative parameter could be a sensitive indicator of vascular disease at early stages of AD. In this work, phase contrast MRI was used to evaluate cerebral hemodynamics in patients with subjective memory complaints, amnestic mild cognitive impairment, and mild to moderate AD, and compare them with control subjects. Results showed that blood flow and velocity were decreased in the patients with cognitive dysfunction and the decrease correlated with the degree of cognitive impairment as assessed by means of neuropsychological tests. Total cerebral blood flow measurements were clearly reduced in AD patients, but more importantly appeared to be sensitive enough to distinguish between healthy subjects and those with mild cognitive impairment. A quantitative measurement of total brain blood flow could potentially predict vascular dysfunction and compromised brain perfusion in early stages of AD.

Relation of Odor Identification with Alzheimer's Disease Markers in Cerebrospinal Fluid and Cognition. - Reijs, Babette L R; Ramakers, Inez H G B; Elias-Sonnenschein, Lyzel; Teunissen, Charlotte E; Koel-Simmelink, Marleen; Tsolaki, Magda; Wahlund, Lars-Olof; Waldemar, Gunhild; Hausner, Lucrezia; Johannsen, Peter; Vanderstichele, Hugo; Verhey, Frans; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Impaired olfactory function is an early characteristic of Alzheimer's disease (AD), but it remains unclear if odor identification also relates to early markers of AD in cerebrospinal fluid (CSF). OBJECTIVE: To investigate the association between odor identification and amyloid-β 1-42 (Aβ42) and total tau (t-tau) concentrations in CSF. In addition, to examine the relation between odor identification and cognitive function at baseline and at follow-up, and whether these associations are moderated by CSF Aβ42 and t-tau and apolipoprotein E (APOE) genotype. METHODS: We included 160 individuals (40 with normal cognition, 45 with mild cognitive impairment (MCI), 42 with AD-type dementia, and 26 individuals with non-AD dementia) from the EDAR study. Individuals were recruited from six memory clinics across Europe. Odor identification was tested with the brief University of Pennsylvania Smell Identification Test. CSF Aβ42 and t-tau were assessed with INNO-BIA AlzBio3 Luminex assay. Neuropsychological assessment included tests for verbal memory, verbal fluency, attention, executive function, and visuoconstruction. Follow-up was performed within 3 years after baseline. RESULTS: Lower odor identification scores correlated with increased CSF t-tau concentrations and with lower scores on all cognitive measures at baseline independent of diagnostic group. Lower odor identification scores predicted decline on the MMSE in the total group, and decline on wordlist learning and delayed recall in APOE ɛ4 carriers and in individuals with abnormal Aβ42. CONCLUSION: Odor identification impairment may be an indicator of neuronal injury rather than amyloid pathology.

Relative Incidence of Seizures and Myoclonus in Alzheimer's Disease, Dementia with Lewy Bodies, and Frontotemporal Dementia. - Beagle, Alexander J; Darwish, Sonja M; Ranasinghe, Kamalini G; La, Alice L; Karageorgiou, Elissaios; Vossel, Keith A (J Alzheimers Dis, 2017)
BACKGROUND: Patients with Alzheimer's disease (AD) are more prone to seizures and myoclonus, but relative risk of these symptoms among other dementia types is unknown. OBJECTIVE: To determine incidence of seizures and myoclonus in the three most common neurodegenerative dementias: AD, dementia with Lewy bodies (DLB), and frontotemporal dementia (FTD). METHODS: Our institution's medical records were reviewed for new-onset unprovoked seizures and myoclonus in patients meeting criteria for AD (n = 1,320), DLB (n = 178), and FTD (n = 348). Cumulative probabilities of developing seizures and myoclonus were compared between diagnostic groups, whereas age-stratified incidence rates were determined relative to control populations. RESULTS: The cumulative probability of developing seizures after disease onset was 11.5% overall, highest in AD (13.4%) and DLB (14.7%) and lowest in FTD (3.0%). The cumulative probability of developing myoclonus was 42.1% overall, highest in DLB (58.1%). The seizure incidence rates, relative to control populations, were nearly 10-fold in AD and DLB, and 6-fold in FTD. Relative seizure rates increased with earlier age-at-onset in AD (age <50, 127-fold; 50-69, 21-fold; 70+, 2-fold) and FTD (age <50, 53-fold; 50-69, 9-fold), and relative myoclonus rates increased with earlier age-at-onset in all groups. Seizures began an average of 3.9 years after the onset of cognitive or motor decline, and myoclonus began 5.4 years after onset. CONCLUSIONS: Seizures and myoclonus occur with greater incidence in patients with AD, DLB, and FTD than in the general population, but rates vary with diagnosis, suggesting varied pathomechanisms of network hyperexcitability. Patients often experience these symptoms early in disease, suggesting hyperexcitability could be an important target for interventions.

Remyelination: A Potential Therapeutic Strategy for Alzheimer's Disease? - Sun, Junjun; Zhou, Hong; Bai, Feng; Zhang, Zhijun; Ren, Qingguo (J Alzheimers Dis, 2017)
Myelin is a lipid-rich multilamellar membrane that wraps around long segments of neuronal axons and it increases the conduction of action potentials, transports the necessary trophic support to the neuronal axons, and reduces the energy consumed by the neuronal axons. Together with axons, myelin is a prerequisite for the higher functions of the central nervous system and complex forms of network integration. Myelin impairments have been suggested to lead to neuronal dysfunction and cognitive decline. Accumulating evidence, including brain imaging and postmortem and genetic association studies, has implicated myelin impairments in Alzheimer's disease (AD). Increasing data link myelin impairments with amyloid-β (Aβ) plaques and tau hyperphosphorylation, which are both present in patients with AD. Moreover, aging and apolipoprotein E (ApoE) may be involved in the myelin impairments observed in patients with AD. Decreased neuronal activity, increased Aβ levels, and inflammation further damage myelin in patients with AD. Furthermore, treatments that promote myelination contribute to the recovery of neuronal function and improve cognition. Therefore, strategies targeting myelin impairment may provide therapeutic opportunities for patients with AD.

Role of Glutamate and NMDA Receptors in Alzheimer's Disease. - Wang, Rui; Reddy, P Hemachandra (J Alzheimers Dis, 2017)
Excitatory glutamatergic neurotransmission via N-methyl-d-aspartate receptor (NMDAR) is critical for synaptic plasticity and survival of neurons. However, excessive NMDAR activity causes excitotoxicity and promotes cell death, underlying a potential mechanism of neurodegeneration occurred in Alzheimer's disease (AD). Studies indicate that the distinct outcomes of NMDAR-mediated responses are induced by regionalized receptor activities, followed by different downstream signaling pathways. The activation of synaptic NMDARs initiates plasticity and stimulates cell survival. In contrast, the activation of extrasynaptic NMDARs promotes cell death and thus contributes to the etiology of AD, which can be blocked by an AD drug, memantine, an NMDAR antagonist that selectively blocks the function of extrasynaptic NMDARs.

Role of Niemann-Pick Type C Disease Mutations in Dementia. - Cupidi, Chiara; Frangipane, Francesca; Gallo, Maura; Clodomiro, Alessandra; Colao, Rosanna; Bernardi, Livia; Anfossi, Maria; Conidi, Maria Elena; Vasso, Franca; Curcio, Sabrina Anna Maria; Mirabelli, Maria; Smirne, Nicoletta; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Several neurological and systemic diseases can cause dementia, beyond Alzheimer's disease. Rare genetic causes are often responsible for dementia with atypical features. Recently, mutations causative for Niemann-Pick type C disease (NPC) have also been implicated in neurodegenerative diseases. NPC is an autosomal recessive lipid storage disorder caused by mutations in NPC1 and NPC2 genes. In adults, clinical presentation mimicking other neurodegenerative diseases makes diagnosis difficult. Recent evidence suggests that heterozygous mutations in NPC genes may take on etiological significance. OBJECTIVE: To investigate the presence of NPC1 and NPC2 mutations in adults affected by neurodegenerative dementia plus. METHODS: We performed a genetic screening on 50 patients using a wide clinical and biochemical approach to characterize the phenotype of mutated patients. RESULTS: Sequencing analysis revealed four different and known heterozygous mutations in NPC1 and NPC2 genes. Patient 1 carried the p. F284LfsX26 in NPC1 and was affected by progressive supranuclear palsy-like syndrome. The remaining three patients showed a corticobasal syndrome and harbored the c.441+1G>A variant of NPC2 (patient 2), the missense p.N222 S mutation associated with the c.1947+8G>C variant in the splice region of intron 12 in NPC1 (patient 3), and the p.V30M mutation in NPC2 (patient 4), respectively. Filipin staining was abnormal in patients 1 and 2. mRNA analysis revealed an altered splicing of the NPC2 gene in patient 2. CONCLUSIONS: Heterozygous mutations of NPC1 and NPC2 genes could contribute to dementia plus, at least in a subset of patients. We highlight the occurrence of NPC1 and NPC2 heterozygous variants in dementia-plus as pathological event.

Selenium Levels in Serum, Red Blood Cells, and Cerebrospinal Fluid of Alzheimer's Disease Patients: A Report from the Australian Imaging, Biomarker & Lifestyle Flagship Study of Ageing (AIBL). - Cardoso, Bárbara R; Hare, Dominic J; Bush, Ashley I; Li, Qiao-Xin; Fowler, Christopher J; Masters, Colin L; Martins, Ralph N; Ganio, Katherine; Lothian, Amber; Mukherjee, Soumya; Kapp, Eugene A; Roberts, Blaine R (J Alzheimers Dis, 2017)
Selenium (Se) protects cells against oxidative stress damage through a range of bioactive selenoproteins. Increased oxidative stress is a prominent feature of Alzheimer's disease (AD), and previous studies have shown that Se deficiency is associated with age-related cognitive decline. In this study, we assessed Se status in different biofluids from a subgroup of participants in the Australian Imaging, Biomarkers and Lifestyle Flagship Study of Ageing. As Se in humans can either be an active component of selenoproteins or inactive via non-specific incorporation into other proteins, we used both size exclusion chromatography-inductively coupled plasma-mass spectrometry (SEC-ICP-MS) and tandem mass spectrometry to characterize selenoproteins in serum. We observed no differences in total Se concentration in serum or cerebrospinal fluid of AD subjects compared to mildly cognitively impairment patients and healthy controls. However, Se levels in erythrocytes were decreased in AD compared to controls. SEC-ICP-MS analysis revealed a dominant Se-containing fraction. This fraction was subjected to standard protein purification and a bottom-up proteomics approach to confirm that the abundant Se in the fraction was due, in part, to selenoprotein P. The lack of change in the Se level is at odds with our previous observations in a Brazilian population deficient in Se, and we attribute this to the Australian cohort being Se-replete.

Selenoprotein S Reduces Endoplasmic Reticulum Stress-Induced Phosphorylation of Tau: Potential Role in Selenate Mitigation of Tau Pathology. - Rueli, Rachel H L H; Torres, Daniel J; Dewing, Andrea S T; Kiyohara, Arlene C; Barayuga, Stephanie M; Bellinger, Miyoko T; Uyehara-Lock, Jane H; White, Lon R; Moreira, Paula I; Berry, Marla J; Perry, George; Bellinger, Frederick P (J Alzheimers Dis, 2017)
Previous studies demonstrated that selenium in the form of sodium selenate reduces neurofibrillary tangle formation in Alzheimer's disease models. Hyperphosphorylation of tau, which leads to formation of neurofibrillary tangles in Alzheimer's disease, is increased by endoplasmic reticulum (ER) stress. Selenoprotein S (SelS) is part of an ER membrane complex that removes misfolded proteins from the ER as a means to reduce ER stress. Selenate, as with other forms of selenium, will increase selenoprotein expression. We therefore proposed that increased SelS expression by selenate would contribute to the beneficial actions of selenate in Alzheimer's disease. SelS expression increased with ER stress and decreased under conditions of elevated glucose concentrations in the SH-SY5Y neuronal cell line. Reducing expression of SelS with siRNA promoted cell death in response to ER stress. Selenate increased SelS expression, which significantly correlated with decreased tau phosphorylation. Restricting SelS expression during ER stress conditions increased tau phosphorylation, and also promoted aggregation of phosphorylated tau in neurites and soma. In human postmortem brain, SelS expression coincided with neurofibrillary tangles, but not with amyloid-β plaques. These results indicate that selenate can alter phosphorylation of tau by increasing expression of SelS in Alzheimer's disease and potentially other neurodegenerative disorders.

Sembragiline in Moderate Alzheimer's Disease: Results of a Randomized, Double-Blind, Placebo-Controlled Phase II Trial (MAyflOwer RoAD). - Nave, Stephane; Doody, Rachelle S; Boada, Merce; Grimmer, Timo; Savola, Juha-Matti; Delmar, Paul; Pauly-Evers, Meike; Nikolcheva, Tania; Czech, Christian; Borroni, Edilio; Ricci, Benedicte; Dukart, Juergen; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Sembragiline is a potent, selective, long-acting, and reversible MAO-B inhibitor developed as a potential treatment for Alzheimer's disease (AD). OBJECTIVE: To evaluate the safety, tolerability, and efficacy of sembragiline in patients with moderate AD. METHODS: In this Phase II study (NCT01677754), 542 patients with moderate dementia (MMSE 13-20) on background acetylcholinesterase inhibitors with/without memantine were randomized (1:1:1) to sembragiline 1 mg, 5 mg, or placebo once daily orally for 52 weeks. RESULTS: No differences between treated groups and placebo in adverse events or in study completion. The primary endpoint, change from baseline in ADAS-Cog11, was not met. At Week 52, the difference between sembragiline and placebo in ADAS-Cog11 change from baseline was - 0.15 (p = 0.865) and 0.90 (p = 0.312) for 1 and 5 mg groups, respectively. Relative to placebo at Week 52 (but not at prior assessment times), the 1 mg and 5 mg sembragiline groups showed differences in ADCS-ADL of 2.64 (p = 0.051) and 1.89 (p = 0.160), respectively. A treatment effect in neuropsychiatric symptoms (as assessed by the difference between sembragiline and placebo on BEHAVE-AD-FW) was also seen at Week 52 only: - 2.80 (p = 0.014; 1 mg) and - 2.64 (p = 0.019; 5 mg), respectively. A post hoc subgroup analysis revealed greater treatment effects on behavior and functioning in patients with more severe baseline behavioral symptoms (above the median). CONCLUSIONS: This study showed that sembragiline was well-tolerated in patients with moderate AD. The study missed its primary and secondary endpoints. Post hoc analyses suggested potential effect on neuropsychiatric symptoms and functioning in more behaviorally impaired study population at baseline.

Sensing of Alzheimer's Disease and Multiple Sclerosis Using Nano-Bio Interfaces. - Hajipour, Mohammad Javad; Ghasemi, Forough; Aghaverdi, Haniyeh; Raoufi, Mohammad; Linne, Uwe; Atyabi, Fatemeh; Nabipour, Iraj; Azhdarzadeh, Morteza; Derakhshankhah, Hossein; Lotfabadi, Alireza; Bargahi, Afshar; Alekhamis, Zahra; et al. (J Alzheimers Dis, 2017)
It is well understood that patients with different diseases may have a variety of specific proteins (e.g., type, amount, and configuration) in their plasmas. When nanoparticles (NPs) are exposed to these plasmas, the resulting coronas may incorporate some of the disease-specific proteins. Using gold (Au) NPs with different surface properties and corona composition, we have developed a colorimetric sensor array for the discrimination and detection of two neurodegenerative diseases, Alzheimer's disease (AD) and multiple sclerosis (MS). Applying a variety of techniques, including UV-visible spectra, array response analyses and liquid chromatography-tandem mass spectrometry, we found the corona-NP complexes, obtained from different human serums, had distinct protein composition, including some specific proteins that are known as AD and MS biomarkers. The array responses, analyzed by chemometrics and statistical methods, demonstrate promising capabilities of the sensor to unambiguously identify and discriminate AD and MS. The developed sensor array might enable a simple, inexpensive and rapid detection/discrimination of neurodegenerative diseases.

Serum SHBG Levels are not Associated with Longitudinal Cognitive Decline in Mild Cognitive Impairment. - Lin, Katherine Amy; Rundel, Colin; Doraiswamy, P Murali (J Alzheimers Dis, 2017)
BACKGROUND: Prior studies have noted gender differences in cognition, imaging, and pathological markers in mild cognitive impairment (MCI) subjects. Sex hormone-binding globulin (SHBG), a major controlling factor in the proportion of bioavailable versus bound testosterone and estrogen, has been proposed to contribute to links between hormones and dementia, but has not yet been investigated fully in a prospective biomarker trial. OBJECTIVE: This study examined whether, among subjects with MCI, SHBG levels predict future rate of cognitive decline. METHODS: We examine the effect of gender on cognitive decline and factors modulating potential gender differences in 378 MCI subjects (134 females, 244 males) in the Alzheimer's Disease Neuroimaging Initiative-1 (ADNI-1), followed for up to 8 years (mean ± SE, 4.0 ± 0.1 years). Cognition was assessed using the ADAS-cog-11. Multivariate models examined the effect of gender covarying for age, ApoE4, baseline cognition, years of education, and SHBG levels. RESULTS: MCI women declined significantly faster than men in cognition over the follow up period. Baseline SHBG levels differed significantly between men and women (p < 0.0001), and by age in men, but not by ApoE4 status. In the multivariate models, SHBG levels were not a significant predictor of cognitive decline in men or women but ApoE4 status, baseline cognition, years of education, and female gender were. CONCLUSION: SHBG levels did not influence the rate of cognitive decline in MCI. Further studies to confirm these findings and uncover other potential mechanisms of gender differences in the risk for AD may be warranted.

Short-Term Response is not Predictive of Long-Term Response to Acetylcholinesterase Inhibitors in Old Age Subjects with Alzheimer's Disease: A "Real World" Study. - Boccardi, Virginia; Baroni, Marta; Smirne, Nicoletta; Clodomiro, Alessandra; Ercolani, Sara; Longo, Annalisa; Ruggiero, Carmelinda; Bruni, Amalia C; Mecocci, Patrizia (J Alzheimers Dis, 2017)
BACKGROUND: Most of clinical guidelines recommend discontinuing treatment with cholinesterase inhibitors (ChEIs) in patients with Alzheimer's disease (AD) who do not show an initial response to therapy as evaluated with the Mini-Mental State Examination (MMSE) scale. However, understanding the relationship between the initial response to ChEI treatment and the subsequent course of the disease is extremely important in clinical practice, but evidence is limited, particularly in the old-old population. OBJECTIVE: We aimed at investigating the relationship between short-term and long-term response to ChEI therapy in old age subjects with AD in a "real life" setting. METHODS: This is a retrospective longitudinal study of 628 old age subjects (≥65 years old) with AD and treated with ChEIs over three year follow-up. The sample was divided into "young-old" (≤75 years) and "old-old" (≥76 years) according to age, and as "responder" and "non-responder" according to the initial (i.e., after three months) response to treatment. Cognitive and functional evaluation was performed by means of MMSE and ADL/IADL, respectively. RESULTS: In the long run, subjects considered as non-responders showed a lower rate of cognitive decline as compared with responders, with a mean annual decline at MMSE of 1.0 point versus 1.6 points (p < 0.0001), respectively. Old-old non-responders had a slower rate of cognitive (p < 0.0001) and functional decline (p < 0.0001) as compared with responders after three years of observation. CONCLUSION: Discontinuing ChEI treatment solely for the absence of an initial response is not appropriate, especially in old-old subjects.

Sildenafil Improves Vascular and Metabolic Function in Patients with Alzheimer's Disease. - Sheng, Min; Lu, Hanzhang; Liu, Peiying; Li, Yang; Ravi, Harshan; Peng, Shin-Lei; Diaz-Arrastia, Ramon; Devous, Michael D; Womack, Kyle B (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) is the leading cause of degenerative dementia in the aging population. Patients with AD have alterations in cerebral hemodynamic function including reduced cerebral blood flow (CBF) and cerebral metabolic rate. Therefore, improved cerebrovascular function may be an attractive goal for pharmaceutical intervention in AD. OBJECTIVE: We wished to observe the acute effects of sildenafil on cerebrovascular function and brain metabolism in patients with AD. METHODS: We used several novel non-invasive MRI techniques to investigate the alterations of CBF, cerebral metabolic rate of oxygen (CMRO2), and cerebrovascular reactivity (CVR) after a single dose of sildenafil administration in order to assess its physiological effects in patients with AD. CBF, CMRO2, and CVR measurements using MRI were performed before and one hour after the oral administration of 50 mg sildenafil. Baseline Montreal Cognitive Assessment score was also obtained. RESULTS: Complete CBF and CMRO2 data were obtained in twelve patients. Complete CVR data were obtained in eight patients. Global CBF and CMRO2 significantly increased (p = 0.03, p = 0.05, respectively) following sildenafil administration. Voxel-wise analyses of CBF maps showed that increased CBF was most pronounced in the bilateral medial temporal lobes. CVR significantly decreased after administration of sildenafil. CONCLUSION: Our data suggest that a single dose of sildenafil improves cerebral hemodynamic function and increases cerebral oxygen metabolism in patients with AD.

Social Representation of Dementia: An Analysis of 5,792 Consecutive Cases Evaluated in a Memory Clinic. - Cañabate, Pilar; Martínez, Gabriel; Rosende-Roca, Maitee; Moreno, Mariola; Preckler, Silvia; Valero, Sergi; Sotolongo, Oscar; Hernandez, Isabel; Alegret, Montserrat; Ortega, Gemma; Espinosa, Ana; Mauleón, Ana; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Different interpretations of cognitive impairment and dementia due to differences in health structures, such as cultural differences could affect the diagnosis and treatment of the condition. it is reasonable to expect that the social and family impact of the disease and coping strategies will differ among societies. OBJECTIVE: The general aim of this study is to understand the social representations of dementia, its associated practices, and the effects they imply. METHODS: People diagnosed with clinical dementia and their families were assessed from 2005 to 2015 in the memory clinic of the Fundació ACE, Institut Català de Neurociències Aplicades in Barcelona, Spain. RESULTS: 9,898 people were examined and 5,792 were diagnosed with dementia. For those with a caregiver (71%), the decision-making fell on the person with dementia in 16.2% of the cases; and for those without a caregiver, in 26.4% of the cases the family did not perceive the deficits as a disease, which led to multiple risk situations (74.6%). CONCLUSIONS: The recognition of dementia as part of aging is common among families. Consequently, risk situations may arise and diagnosis and access to treatment may be delayed. The incorporation of a social appraisal to the diagnostic process is a necessity to evaluate these situations.

Subclinical Doses of ATP-Sensitive Potassium Channel Modulators Prevent Alterations in Memory and Synaptic Plasticity Induced by Amyloid-β. - Salgado-Puga, Karla; Rodríguez-Colorado, Javier; Prado-Alcalá, Roberto A; Peña-Ortega, Fernando (J Alzheimers Dis, 2017)
In addition to coupling cell metabolism and excitability, ATP-sensitive potassium channels (KATP) are involved in neural function and plasticity. Moreover, alterations in KATP activity and expression have been observed in Alzheimer's disease (AD) and during amyloid-β (Aβ)-induced pathology. Thus, we tested whether KATP modulators can influence Aβ-induced deleterious effects on memory, hippocampal network function, and plasticity. We found that treating animals with subclinical doses (those that did not change glycemia) of a KATP blocker (Tolbutamide) or a KATP opener (Diazoxide) differentially restrained Aβ-induced memory deficit, hippocampal network activity inhibition, and long-term synaptic plasticity unbalance (i.e., inhibition of LTP and promotion of LTD). We found that the protective effect of Tolbutamide against Aβ-induced memory deficit was strong and correlated with the reestablishment of synaptic plasticity balance, whereas Diazoxide treatment produced a mild protection against Aβ-induced memory deficit, which was not related to a complete reestablishment of synaptic plasticity balance. Interestingly, treatment with both KATP modulators renders the hippocampus resistant to Aβ-induced inhibition of hippocampal network activity. These findings indicate that KATP are involved in Aβ-induced pathology and they heighten the potential role of KATP modulation as a plausible therapeutic strategy against AD.

Tailored and Adaptive Computerized Cognitive Training in Older Adults at Risk for Dementia: A Randomized Controlled Trial. - Bahar-Fuchs, Alex; Webb, Shannon; Bartsch, Lauren; Clare, Linda; Rebok, George; Cherbuin, Nicolas; Anstey, Kaarin J (J Alzheimers Dis, 2017)
BACKGROUND: Computerized Cognitive Training (CCT) has been shown to improve cognitive function in older adults with mild cognitive impairment (MCI) or mood-related neuropsychiatric symptoms (MrNPS), but many questions remain unresolved. OBJECTIVE: To evaluate the extent to which CCT benefits older adults with both MCI and MrNPS, and its effects on meta-cognitive and non-cognitive outcomes, as well as establish whether adapting difficulty levels and tailoring to individuals' profile is superior to generic training. METHODS: Older adults with MCI (n = 9), MrNPS (n = 11), or both (MCI+, n = 25) were randomized into a home-based individually-tailored and adaptive CCT (n = 21) or an active control condition (AC; n = 23) in a double-blind design. Interventions lasted 8-12 weeks and outcomes were assessed after the intervention, and at a 3-month follow-up. RESULTS: Participants in both conditions reported greater satisfaction with their everyday memory following intervention and at follow-up. However, participants in the CCT condition showed greater improvement on composite measures of memory, learning, and global cognition at follow-up. Participants with MrNPS in the CCT condition were also found to have improved mood at 3-month follow-up and reported using fewer memory strategies at the post-intervention and follow-up assessments. There was no evidence that participants with MCI+ were disadvantaged relative to the other diagnostic conditions. Finally, informant-rated caregiver burden declined at follow-up assessment in the CCT condition relative to the AC condition. CONCLUSIONS: Home-based CCT with adaptive difficulty and personal tailoring appears superior to more generic CCT in relation to both cognitive and non-cognitive outcomes. Mechanisms of treatment effect and future directions are discussed.

Tau Oligomers in Sera of Patients with Alzheimer's Disease and Aged Controls. - Kolarova, Michala; Sengupta, Urmi; Bartos, Ales; Ricny, Jan; Kayed, Rakez (J Alzheimers Dis, 2017)
Although tau protein was long regarded as an intracellular protein with several functions inside the cell, new evidence has shown tau secretion into the extracellular space. The active secretion of tau could be a physiological response of neurons to increased intracellular amounts of tau during the progression of tau pathology. We looked for potential differences in the serum levels of toxic tau oligomers in regards to cognitive impairment of subjects. We detected tau oligomers in the serum of Alzheimer's disease (AD) patients, but they were also present to some extent in the serum of healthy older subjects where the levels positively correlated with aging (Spearman r = 0.26, p = 0.016). On the contrary, we found lower levels of tau oligomers in the serum of mild cognitive impairment (MCI) (p = 0.033) and MCI-AD (p = 0.006) patients. These results could suggest that clearance of extracellular tau proteins takes place, in part, in the periphery. In the case of MCI patients, the lower levels of tau oligomers could be the result of impaired clearance of tau protein from interstitium to blood and consequent accumulation of tau aggregates in the brain.

Tau Platelets Correlate with Regional Brain Atrophy in Patients with Alzheimer's Disease. - Slachevsky, Andrea; Guzmán-Martínez, Leonardo; Delgado, Carolina; Reyes, Pablo; Farías, Gonzalo A; Muñoz-Neira, Carlos; Bravo, Eduardo; Farías, Mauricio; Flores, Patricia; Garrido, Cristian; Becker, James T; Lopez, Oscar L; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Intracellular neurofibrillary tangles are part of the core pathology of Alzheimer's disease (AD), which are mainly composed of hyperphosphorylated tau protein. OBJECTIVES: The purpose of this study is to determine whether high molecular weight (HMW) or low molecular weight (LMW) tau protein levels, as well as the ratio HMW/LMW, present in platelets correlates with brain magnetic resonance imaging (MRI) structural changes in normal and cognitively impaired subjects. METHODS: We examined 53 AD patients and 37 cognitively normal subjects recruited from two Memory Clinics at the Universidad de Chile. Tau levels in platelets were determined by immunoreactivity and the MRI scans were analyzed using voxel-based morphometry in 41 AD patients. RESULTS: The HMW/LMW tau ratio was statistically different between controls and AD patients, and no associations were noted between HMW or LMW tau and MRI structures. In a multivariate analysis controlled for age and education level, the HMW/LMW tau ratio was associated with reduced volume in the left medial and right anterior cingulate gyri, right cerebellum, right thalamus (pulvinar), left frontal cortex, and right parahippocampal region. CONCLUSIONS: This exploratory study showed that HMW/LMW tau ratio is significantly higher in AD patients than control subjects, and that it is associated with specific brain regions atrophy. Determination of peripheral markers of AD pathology can help understanding the pathophysiology of neurodegeneration in AD.

Tau Rather than TDP-43 Proteins are Potential Cerebrospinal Fluid Biomarkers for Frontotemporal Lobar Degeneration Subtypes: A Pilot Study. - Kuiperij, H Bea; Versleijen, Alexandra A M; Beenes, Marijke; Verwey, Nicolaas A; Benussi, Luisa; Paterlini, Anna; Binetti, Giuliano; Teunissen, Charlotte E; Raaphorst, Joost; Schelhaas, Helenius J; Küsters, Benno; Pijnenburg, Yolande A L; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Frontotemporal dementia (FTD) is a heterogeneous disease both at the clinical, genetic, and pathobiological level. The underlying pathological spectrum (termed FTLD, frontotemporal lobar degeneration) is in most cases defined by accumulation of either tau (FTLD-tau) or TDP-43 proteins (FTLD-TDP). Biomarkers to differentiate these subtypes are not yet available, whereas these are essential requirements to study the natural course of disease and for homogeneous inclusion of patients in clinical studies. OBJECTIVE: To study if a combination of total (t-) and phosphorylated (p-)tau, and t-TDP-43 and p-TDP-43 proteins in cerebrospinal fluid (CSF) is suitable to discriminate FTLD-tau and FTLD-TDP subtypes. METHODS: We developed immunoassays for the quantification of t-TDP-43 and p-TDP-43 proteins and used commercially available assays for the quantification of t-tau and p-tau proteins. We quantified these proteins in ventricular CSF samples from neuropathologically defined FTLD-tau and FTLD-TDP cases to study the reflection of underlying brain pathology in CSF composition, and in lumbar CSF samples from FTLD-tau and FTLD-TDP patients to study the diagnostic potential of CSF biomarkers. RESULTS: In ventricular CSF, t-TDP-43 and t-tau levels, when combined into one model, were significantly different between neuropathologically-defined FTLD-tau and FTLD-TDP cases. In a pilot study using lumbar CSF, the p-tau/t-tau ratio, but not t-TDP-43 levels, were significantly different between FTLD-TDP and FTLD-tau patients. CONCLUSION: We conclude that with current available methods, CSF tau, rather than TDP-43 proteins, may have diagnostic value in the differentiation of FTLD patients with either tau or TDP-43 pathology.

Temporal Order of Alzheimer's Disease-Related Cognitive Marker Changes in BLSA and WRAP Longitudinal Studies. - Bilgel, Murat; Koscik, Rebecca L; An, Yang; Prince, Jerry L; Resnick, Susan M; Johnson, Sterling C; Jedynak, Bruno M (J Alzheimers Dis, 2017)
Investigation of the temporal trajectories of currently used neuropsychological tests is critical to identifying earliest changing measures on the path to dementia due to Alzheimer's disease (AD). We used the Progression Score (PS) method to characterize the temporal trajectories of measures of verbal memory, executive function, attention, processing speed, language, and mental status using data spanning normal cognition, mild cognitive impairment, and AD from 1,661 participants with a total of 7,839 visits (age at last visit 77.6 SD 9.2) in the Baltimore Longitudinal Study of Aging (BLSA) and 1510 participants with a total of 3,473 visits (age at last visit 59.5 SD 7.4) in the Wisconsin Registry for Alzheimer's Prevention (WRAP). This method aligns individuals in time based on the similarity of their longitudinal measurements to reveal temporal trajectories. As a validation of our methodology, we explored the associations between the individualized cognitive progression scores (Cog-PS) computed by our method and clinical diagnosis. Digit span tests were the first to show declines in both data sets, and were detected mainly among cognitively normal individuals. These were followed by tests of verbal memory, which were in turn followed by Trail Making Tests, Boston Naming Test, and Mini-Mental State Examination. Differences in Cog-PS across the clinical diagnosis and APOEɛ4 groups were statistically significant, highlighting the potential use of Cog-PS as individualized indicators of disease progression. Identifying cognitive measures that are changing in preclinical AD can lead to the development of novel cognitive tests that are finely tuned to detecting earliest changes.

TFP5, a Peptide Inhibitor of Aberrant and Hyperactive Cdk5/p25, Attenuates Pathological Phenotypes and Restores Synaptic Function in CK-p25Tg Mice. - Shukla, Varsha; Seo, Jinsoo; Binukumar, B K; Amin, Niranjana D; Reddy, Preethi; Grant, Philip; Kuntz, Susan; Kesavapany, Sashi; Steiner, Joseph; Mishra, Santosh K; Tsai, Li-Huei; Pant, Harish C (J Alzheimers Dis, 2017)
It has been reported that cyclin-dependent kinase 5 (cdk5), a critical neuronal kinase, is hyperactivated in Alzheimer's disease (AD) and may be, in part, responsible for the hallmark pathology of amyloid plaques and neurofibrillary tangles (NFTs). It has been proposed by several laboratories that hyperactive cdk5 results from the overexpression of p25 (a truncated fragment of p35, the normal cdk5 regulator), which, when complexed to cdk5, induces hyperactivity, hyperphosphorylated tau/NFTs, amyloid-β plaques, and neuronal death. It has previously been shown that intraperitoneal (i.p.) injections of a modified truncated 24-aa peptide (TFP5), derived from the cdk5 activator p35, penetrated the blood-brain barrier and significantly rescued AD-like pathology in 5XFAD model mice. The principal pathology in the 5XFAD mutant, however, is extensive amyloid plaques; hence, as a proof of concept, we believe it is essential to demonstrate the peptide's efficacy in a mouse model expressing high levels of p25, such as the inducible CK-p25Tg model mouse that overexpresses p25 in CamKII positive neurons. Using a modified TFP5 treatment, here we show that peptide i.p. injections in these mice decrease cdk5 hyperactivity, tau, neurofilament-M/H hyperphosphorylation, and restore synaptic function and behavior (i.e., spatial working memory, motor deficit using Rota-rod). It is noteworthy that TFP5 does not inhibit endogenous cdk5/p35 activity, nor other cdks in vivo suggesting it might have no toxic side effects, and may serve as an excellent therapeutic candidate for neurodegenerative disorders expressing abnormally high brain levels of p25 and hyperactive cdk5.

Theobromine-Induced Changes in A1 Purinergic Receptor Gene Expression and Distribution in a Rat Brain Alzheimer's Disease Model. - Mendiola-Precoma, Jesus; Padilla, Karla; Rodríguez-Cruz, Alfredo; Berumen, Laura C; Miledi, Ricardo; García-Alcocer, Guadalupe (J Alzheimers Dis, 2017)
Dementia caused by Alzheimer's disease (AD) is mainly characterized by accumulation in the brain of extra- and intraneuronal amyloid-β (Aβ) and tau proteins, respectively, which selectively affect specific regions, particularly the neocortex and the hippocampus. Sporadic AD is mainly caused by an increase in apolipoprotein E, a component of chylomicrons, which are cholesterol transporters in the brain. Recent studies have shown that high lipid levels, especially cholesterol, are linked to AD. Adenosine is an atypical neurotransmitter that regulates a wide range of physiological functions by activating four P1 receptors (A1, A2A, A2B, and A3) and P2 purinergic receptors that are G protein-coupled. A1 receptors are involved in the inhibition of neurotransmitter release, which could be related to AD. The aim of the present work was to study the effects of a lard-enriched diet (LED) on cognitive and memory processes in adult rats (6 months of age) as well as the effect of theobromine on these processes. The results indicated that the fat-enriched diet resulted in a long-term deterioration in cognitive and memory functions. Increased levels of Aβ protein and IL-1β were also observed in the rats fed with a high-cholesterol diet, which were used to validate the AD animal model. In addition, the results of qPCR and immunohistochemistry indicated a decrease in gene expression and distribution of A1 purinegic receptor, respectively, in the hippocampus of LED-fed rats. Interestingly, theobromine, at both concentrations tested, restored A1 receptor levels and improved cognitive functions and Aβ levels for a dose of 30 mg/L drinking water.

Therapeutics of Neurotransmitters in Alzheimer's Disease. - Kandimalla, Ramesh; Reddy, P Hemachandra (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a progressive neurodegenerative disease, characterized by the loss of memory, multiple cognitive impairments and changes in the personality and behavior. Several decades of intense research have revealed that multiple cellular changes are involved in disease process, including synaptic damage, mitochondrial abnormalities and inflammatory responses, in addition to formation and accumulation of amyloid-β (Aβ) and phosphorylated tau. Although tremendous progress has been made in understanding the impact of neurotransmitters in the progression and pathogenesis of AD, we still do not have a drug molecule associated with neurotransmitter(s) that can delay disease process in elderly individuals and/or restore cognitive functions in AD patients. The purpose of our article is to assess the latest developments in neurotransmitters research using cell and mouse models of AD. We also updated the current status of clinical trials using neurotransmitters' agonists/antagonists in AD.

Toward the Automation of Diagnostic Conversation Analysis in Patients with Memory Complaints. - Mirheidari, Bahman; Blackburn, Daniel; Harkness, Kirsty; Walker, Traci; Venneri, Annalena; Reuber, Markus; Christensen, Heidi (J Alzheimers Dis, 2017)
BACKGROUND: The early diagnosis of dementia is of great clinical and social importance. A recent study using the qualitative methodology of conversation analysis (CA) demonstrated that language and communication problems are evident during interactions between patients and neurologists, and that interactional observations can be used to differentiate between cognitive difficulties due to neurodegenerative disorders (ND) or functional memory disorders (FMD). OBJECTIVE: This study explores whether the differential diagnostic analysis of doctor-patient interactions in a memory clinic can be automated. METHODS: Verbatim transcripts of conversations between neurologists and patients initially presenting with memory problems to a specialist clinic were produced manually (15 with FMD, and 15 with ND). A range of automatically detectable features focusing on acoustic, lexical, semantic, and visual information contained in the transcripts were defined aiming to replicate the diagnostic qualitative observations. The features were used to train a set of five machine learning classifiers to distinguish between ND and FMD. RESULTS: The mean rate of correct classification between ND and FMD was 93% ranging from 97% by the Perceptron classifier to 90% by the Random Forest classifier.Using only the ten best features, the mean correct classification score increased to 95%. CONCLUSION: This pilot study provides proof-of-principle that a machine learning approach to analyzing transcripts of interactions between neurologists and patients describing memory problems can distinguish people with neurodegenerative dementia from people with FMD.

Triceps and Subscapular Skinfold in Men Aged 40-65 and Dementia Prevalence 36 Years Later. - Ravona-Springer, Ramit; Schnaider-Beeri, Michal; Goldbourt, Uri (J Alzheimers Dis, 2017)
BACKGROUND: The relationship of obesity with risk for dementia is complex and may change with age. OBJECTIVE: To analyze the relationship between measures of obesity at age 40-65 and dementia prevalence in survivors 36 years later. METHODS: Obesity-related measures of triceps and subscapular skinfold thickness were assessed in 1963 in n = 9,760 men aged 40-65 participating in the Israel Ischemic Heart Disease study. Cognitive evaluation and assessment of dementia prevalence were performed in n = 1,643 participants of the original cohort who survived until 1999/2000 (age ≥76 years) and had anthropometric measures in 1963. RESULTS: Age-adjusted prevalence of dementia in survivors in 1999/2000 by baseline triceps skinfold quintile was 20.5%, 21.2%, 17.6%, 15.6%, and 14.5%, respectively, from lowest to highest (p = 0.006 in trend test). Using logistic regression, a 6-mm increment of triceps skinfold was associated with an age and BMI-adjusted odds ratio of 0.81 (95% CI, 0.70-0.94) for dementia prevalence among survivors. Age-adjusted risk for dementia by subscapular skinfold quintile demonstrated 20.5%, 17.1%, 15.7%, 19.4%, and 18.1%, respectively, in groups of subjects by subscapular skinfold quintile from lowest to highest (p = 0.6 in trend test). CONCLUSIONS: Lower triceps skinfold at age 40-65, reflecting diminished peripheral fat, was associated with higher dementia prevalence in late life, potentially suggesting a protective role of peripheral fat to brain health.
Keywords: Adipose Tissue; Aged; Anthropometry; Arm; Body Mass Index; Dementia; Exercise; Humans; Israel; Leisure Activities; Longitudinal Studies; Male; Middle Aged; Muscle, Skeletal; Obesity; Odds Ratio; Prevalence; Shoulder; Skinfold Thickness; Social Class

Two Novel Mutations in the First Transmembrane Domain of Presenilin1 Cause Young-Onset Alzheimer's Disease. - Liu, Collin Y; Ohki, Yu; Tomita, Taisuke; Osawa, Satoko; Reed, Bruce R; Jagust, William; Van Berlo, Victoria; Jin, Lee-Way; Chui, Helena C; Coppola, Giovanni; Ringman, John M (J Alzheimers Dis, 2017)
BACKGROUND: The presenilin-1 protein (PS1) is the catalytic unit of γ-secretase implicated in the production of abnormally long forms of amyloid-β (Aβ), including Aβ42, proteins thought critical in the pathogenesis of Alzheimer's disease (AD). In AD of autosomal dominant inheritance, the majority of pathogenic mutations have been found in the PSEN1 gene within which the location of the mutation can provide clues as to the mechanism of pathogenesis. OBJECTIVE: To describe clinical features of two novel mutations in the transmembrane portion 1 (TMD-1) of PSEN1 as well as biochemical features in one and neuropathological findings in the other. METHODS: Two index patients with young onset AD with an autosomal dominant pattern of inheritance underwent clinical and imaging assessments, as well as PSEN1 sequencing. Postmortem examination was completed in one patient. An artificial construct in which the P88L mutation was introduced was created to examine its effects on γ-secretase cleavage. RESULTS: Two novel variants in TMD-1 (P88L and V89L) were identified in affected probands. The neuropathological findings of AD were confirmed in the V89L mutation. Both patients presented around age 40 with early short-term memory deficits followed by seizures and corticospinal tract signs. The P88L mutation additionally featured early myoclonus followed by Parkinsonism. The causal role of the P88L mutation is supported by demonstration that this mutation dramatically increased Aβ42 and decreased APP and Notch intracellular domain production in vitro. CONCLUSION: Changes in a single amino acid in codons 88 and 89 of TMD-1 can result in young-onset AD. The TMD-1 of PS1 is a region important for the γ-secretase cleavage of Aβ.

Upregulated Expression of Heparanase and Heparanase 2 in the Brains of Alzheimer's Disease. - Garcia, Beatriz; Martin, Carla; Garcia-Suarez, Olivia; Muniz-Alonso, Barbara; Ordiales, Helena; Fernandez-Menendez, Santiago; Santos-Juanes, Jorge; Lorente-Gea, Laura; Castanon, Sonia; Vicente-Etxenausia, Ikerne; Pina Batista, Kelvin Manuel; Ruiz-Diaz, Irune; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Heparan sulfate proteoglycans (HSPGs) promote amyloid-β peptide and tau fibrillization in Alzheimer's disease (AD) and provide resistance against proteolytic breakdown. Heparanase (HPSE) is the only enzyme that cleaves heparan sulfate (HS). Heparanase 2 (HPSE2) lacks HS-degrading activity, although it is able to interact with HS with high affinity. OBJECTIVE: To analyze HPSE and HPSE2 expressions at different stages of AD. METHODS: RT-PCR was used to analyze transcription levels of both heparanases at different stages of AD, and immunohistochemistry was performed to localize each one in different parts of the brain. RESULTS: Both proteins appeared overexpressed at different stages of AD. Immunohistochemistry indicated that the presence of the heparanases was related to AD pathology, with intracellular deposits found in degenerated neurons. At the extracellular level, HPSE was observed only in neuritic plaques with a fragmented core, while HPSE2 appeared in those with compact cores as well. CONCLUSION: Given the involvement of HSPGs in AD pathology, there would seem to be a relationship between the regulation of heparanase expression, the features of the disease, and a possible therapeutic alternative.

Utility of Molecular and Structural Brain Imaging to Predict Progression from Mild Cognitive Impairment to Dementia. - Lan, Martin J; Ogden, R Todd; Kumar, Dileep; Stern, Yaakov; Parsey, Ramin V; Pelton, Gregory H; Rubin-Falcone, Harry; Pradhaban, Gnanavalli; Zanderigo, Francesca; Miller, Jeffrey M; Mann, J John; Devanand, D P (J Alzheimers Dis, 2017)
This project compares three neuroimaging biomarkers to predict progression to dementia in subjects with mild cognitive impairment (MCI). Eighty-eight subjects with MCI and 40 healthy controls (HCs) were recruited. Subjects had a 3T magnetic resonance imaging (MRI) scan, and two positron emission tomography (PET) scans, one with Pittsburgh compound B ([11C]PIB) and one with fluorodeoxyglucose ([18F]FDG). MCI subjects were followed for up to 4 y and progression to dementia was assessed on an annual basis. MCI subjects had higher [11C]PIB binding potential (BPND) than HCs in multiple brain regions, and lower hippocampus volumes. [11C]PIB BPND, [18F]FDG standard uptake value ratio (SUVR), and hippocampus volume were associated with time to progression to dementia using a Cox proportional hazards model. [18F]FDG SUVR demonstrated the most statistically significant association with progression, followed by [11C]PIB BPND and then hippocampus volume. [11C]PIB BPND and [18F]FDG SUVR were independently predictive, suggesting that combining these measures is useful to increase accuracy in the prediction of progression to dementia. Hippocampus volume also had independent predictive properties to [11C]PIB BPND, but did not add predictive power when combined with the [18F]FDG SUVR data. This work suggests that PET imaging with both [11C]PIB and [18F]FDG may help to determine which MCI subjects are likely to progress to AD, possibly directing future treatment options.

Validation of the Korean Version of the Lewy Body Composite Risk Score (K-LBCRS). - Ryu, Hui Jin; Kim, Minyoung; Moon, Yeonsil; Choi, Yeji; Han, Jee-Young; Galvin, James E; Han, Seol-Heui (J Alzheimers Dis, 2017)
The Lewy body composite risk score (LBCRS) is a useful clinical screening tool to help determine whether the dementia is related to Lewy body pathology. The purpose of this study is to verify reliability, validity, and diagnostic usefulness of Korean version of LBCRS (K-LBCRS). CDR-sum of boxes, Mini-Mental State Examination, and standardized scales related to cognition, mood, behavior, and motor function were administered to a total of 107 subjects, including 30 dementia with Lewy bodies (DLB), 54 Alzheimer's disease (AD), and 23 cognitively normal elderly people and their collateral informants. Internal consistency of the K-LBCRS was good with Cronbach's alpha of 0.85, and concurrent validity was also satisfactory, with K-LBCRS correlating highly with CDR-SB and other scales. The test-retest reliability was very high with a Pearson correlation coefficient of 0.97. The mean scores of K-LBCRS were significantly different among three groups, with DLB (6.2±2.4), AD (1.4±1.3), and controls (0.3±0.6). We identified a cut-off score of 3 as best to differentiate between DLB and AD, having AUC of 0.97 (95% CI 0.94-1.00), sensitivity 97%, specificity 83%, positive predictive value 76%, negative predictive value 98%, which is the same score suggested in the original study. This study shows K-LBCRS as a new useful screening tool for Korean DLB patients in clinical settings.

Validation of the Spanish Version of the LASSI-L for Diagnosing Mild Cognitive Impairment and Alzheimer's Disease. - Matías-Guiu, Jordi A; Curiel, Rosie E; Rognoni, Teresa; Valles-Salgado, María; Fernández-Matarrubia, Marta; Hariramani, Roshan; Fernández-Castro, Alejandro; Moreno-Ramos, Teresa; Loewenstein, David A; Matías-Guiu, Jorge (J Alzheimers Dis, 2017)
BACKGROUND: The Loewenstein-Acevedo Scale for Semantic Interference and Learning (LASSI-L) is a novel cognitive test that measures recovery from proactive semantic interference, which may be an early cognitive marker of Alzheimer's disease (AD). OBJECTIVE: To generate normative data for a Spaniard population and to validate the LASSI-L for the diagnosis of amnestic mild cognitive impairment (aMCI) and mild AD. METHODS: We performed a cross-sectional study in which 97 healthy participants, 34 with aMCI, and 33 with mild AD were studied with LASSI-L and a comprehensive neuropsychological protocol. The overlapping strategy analysis was used to maximize the sample size and to provide age- and education-adjusted normative data using a logistic regression analysis. RESULTS: Internal consistency was 0.932. Convergent validity with the Free and Cued Selective Reminding Test was moderate. LASSI-L raw scores were correlated with age and years of education, but not gender. The area under the curve for discriminating between healthy controls and aMCI was 0.909, and between healthy controls and mild AD was 0.986. LASSI-L sub-scores representing maximum storage capacity, recovery from proactive interference, and delayed recall yielded the highest diagnostic accuracy. CONCLUSIONS: The LASSI-L is a reliable and valid test for the diagnosis of aMCI and mild AD. The age and education influences on the performance of the test and normative data are provided. LASSI-L merits further studies to evaluate its ability to detect preclinical AD and predict progression to aMCI and early dementia.

Visuospatial Functioning in Cerebral Amyloid Angiopathy: A Pilot Study. - Valenti, Raffaella; Charidimou, Andreas; Xiong, Li; Boulouis, Gregoire; Fotiadis, Panagiotis; Ayres, Alison; Riley, Grace; Kuijf, Hugo J; Reijmer, Yael D; Pantoni, Leonardo; Gurol, M Edip; Davidsdottir, Sigurros; et al. (J Alzheimers Dis, 2017)
Cerebral amyloid angiopathy (CAA) is a contributor to cognitive impairment in the elderly. We hypothesized that the posterior cortical predilection of CAA would cause visual-processing impairment. We systematically evaluated visuospatial abilities in 22 non-demented CAA patients. Neurocognitive evaluation demonstrated visuoperceptual impairment (23% on Benton Facial Recognition Test [BFRT] and 13.6% on Benton Judgment of Line Orientation Test [BJLO]). BFRT was inversely correlated with white matter hyperintensities volume and BJLO with parietal cerebral microbleeds. This pilot study highlights the presence of visual-processing deficits in CAA. The impairment could be related to global disease severity in addition to local brain injury.

Vitamin D Insufficiency and Cognitive Function Trajectories in Older Adults: The Rancho Bernardo Study. - Laughlin, Gail A; Kritz-Silverstein, Donna; Bergstrom, Jaclyn; Reas, Emilie T; Jassal, Simerjot K; Barrett-Connor, Elizabeth; McEvoy, Linda K (J Alzheimers Dis, 2017)
BACKGROUND: Evidence of a role for vitamin D (VitD) in cognitive aging is mixed and based primarily on extreme VitD deficiency. We evaluated the association of VitD insufficiency with cognitive function in older, community-dwelling adults living in a temperate climate with year-round sunshine. METHODS: A population-based longitudinal study of 1,058 adults (median age 75; 62% women) who had cognitive function assessed and serum levels of 25-hydroxyvitaminD (25OHD) measured in 1997-99 and were followed for up to three additional cognitive function assessments over a 12-year period. RESULTS: Overall, 14% (n = 145) of participants had VitD insufficiency defined as 25OHD <30 ng/ml. Adjusting for age, sex, education, and season, VitD insufficiency was associated with poorer baseline performance on the Mini-Mental Status Exam (MMSE) (p = 0.013), Trails Making Test B (Trails B) (p = 0.015), Category Fluency (p = 0.006), and Long Term Retrieval (p = 0.019); differences were equivalent to 5 years of age. For those with VitD insufficiency, the odds of mildly impaired performance at baseline were 38% higher for MMSE (p = 0.08), 78% higher for Trails B (p = 0.017), and 2-fold higher for Category Fluency and Long Term Retrieval (both p = 0.001). VitD insufficiency was not related to the rate of cognitive decline on any test or the risk of developing impaired performance during follow-up. CONCLUSION: In this population with little VitD deficiency, even moderately low VitD was associated with poorer performance on multiple domains of cognitive function. Low VitD did not predict 12-year cognitive decline. Clinical trials are essential to establish a causal link between VitD and cognitive well-being.

What Can Quantitative Gait Analysis Tell Us about Dementia and Its Subtypes? A Structured Review. - Mc Ardle, Ríona; Morris, Rosie; Wilson, Joanna; Galna, Brook; Thomas, Alan J; Rochester, Lynn (J Alzheimers Dis, 2017)
Distinguishing dementia subtypes can be difficult due to similarities in clinical presentation. There is increasing interest in discrete gait characteristics as markers to aid diagnostic algorithms in dementia. This structured review explores the differences in quantitative gait characteristics between dementia and healthy controls, and between four dementia subtypes under single-task conditions: Alzheimer's disease (AD), dementia with Lewy bodies and Parkinson's disease dementia, and vascular dementia. Twenty-six papers out of an initial 5,211 were reviewed and interpreted using a validated model of gait. Dementia was associated with gait characteristics grouped by slower pace, impaired rhythm, and increased variability compared to normal aging. Only four studies compared two or more dementia subtypes. People with AD are less impaired in pace, rhythm, and variability domains of gait compared to non-AD dementias. Results demonstrate the potential of gait as a clinical marker to discriminate between dementia subtypes. Larger studies using a more comprehensive battery of gait characteristics and better characterized dementia sub-types are required.

What Drives Country Differences in Cost of Alzheimer's Disease? An Explanation from Resource Use in the GERAS Study. - Reed, Catherine; Happich, Michael; Argimon, Josep Maria; Haro, Josep Maria; Wimo, Anders; Bruno, Giuseppe; Dodel, Richard; Jones, Roy W; Vellas, Bruno; Belger, Mark (J Alzheimers Dis, 2017)
BACKGROUND: Country differences in resource use and costs of Alzheimer's disease (AD) may be driven by differences in health care systems and resource availability. OBJECTIVE: To compare country resource utilization drivers of societal costs for AD dementia over 18 months. METHODS: GERAS is an observational study in France (n = 419), Germany (n = 550), and the UK (n = 526). Resource use of AD patients and caregivers contributing to >1% of total societal costs (year 2010) was assessed for country differences, adjusting for participant characteristics. RESULTS: Mean 18-month societal costs per patient were France €33,339, Germany €38,197, and UK €37,899 (£32,501). Caregiver time spent on basic and instrumental activities of daily living (ADL) contributed the most to societal costs (54% France, 64% Germany, 65% UK). Caregivers in France spent less time on ADL than UK caregivers and missed fewer work days than in other countries. Compared with other countries, patients in France used more community care services overall and were more likely to use home aid. Patients in Germany were least likely to use temporary accommodation or to be institutionalized at 18 months. UK caregivers spent the most time on instrumental ADL, UK patients used fewest outpatient resources, and UK patients/caregivers were most likely to receive financial support. CONCLUSION: Caregiver time on ADL contributed the most to societal costs and differed across countries, possibly due to use of community care services and institutionalization. Other resources had different patterns of use across countries, reflecting country-specific health and social care systems.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Caregivers; Cohort Studies; Cost of Illness; Europe; Female; Health Resources; Humans; International Cooperation; Male; Surveys and Questionnaires

When Patient Engagement and Research Ethics Collide: Lessons from a Dementia Forum. - Robillard, Julie M; Feng, Tanya L (J Alzheimers Dis, 2017)
The importance of patient engagement in research has been gaining recognition since the turn of the 21st century. However, little is known about the perspectives of people with dementia on the process of discovery. To fill this gap and to inform priorities in patient engagement in the context of dementia research, the Clinic for Alzheimer Disease and Related Disorders at the University of British Columbia hosted an interactive session for members of the patient community and of the general public to share their views on various ethical aspects of the research process. Results from the session indicate that several current research ethics policies and norms in dementia research are not in line with participants' preferences. Here we discuss the importance of bridging the gap between researchers and patients and call for reforms in current standards of dementia research.

White Matter Hyperintensities Potentiate Hippocampal Volume Reduction in Non-Demented Older Individuals with Abnormal Amyloid-β. - Freeze, Whitney M; Jacobs, Heidi I L; Gronenschild, Ed H; Jansen, Jacobus F A; Burgmans, Saartje; Aalten, Pauline; Clerx, Lies; Vos, Stephanie J; van Buchem, Mark A; Barkhof, Frederik; van der Flier, Wiesje M; Verbeek, Marcel M; et al. (J Alzheimers Dis, 2017)
Cerebral small vessel disease (cSVD) and amyloid-β (Aβ) deposition often co-exist in (prodromal) dementia, and both types of pathology have been associated with neurodegeneration. We examined whether cSVD and Aβ have independent or interactive effects on hippocampal volume (HV) in a memory clinic population. We included 87 individuals with clinical diagnoses of Alzheimer's disease (AD) (n = 24), mild cognitive impairment (MCI) (n = 26), and subjective cognitive complaints (SCC) (n = 37). cSVD magnetic resonance imaging markers included white matter hyperintensity (WMH) volume, lacunar infarct presence, and microbleed presence. Aβ pathology was assessed as cerebrospinal fluid-derived Aβ1 - 42 levels and dichotomized into normal or abnormal, and HV was determined by manual volumetric measurements. A linear hierarchical regression approach was applied for the detection of additive or interaction effects between cSVD and Aβ on HV in the total participant group (n = 87) and in the non-demented group (including SCC and MCI individuals only, n = 63). The results revealed that abnormal Aβ and lacunar infarct presence were independently associated with lower HV in the non-demented individuals. Interestingly, Aβ and WMH pathology interacted in the non-demented individuals, such that WMH had a negative effect on HV in individuals with abnormal CSF Aβ42 levels, but not in individuals with normal CSF Aβ42 levels. These associations were not present when individuals with AD were included in the analyses. Our observations suggest that relatively early on in the disease process older individuals with abnormal Aβ levels are at an increased risk of accelerated disease progression when concomitant cSVD is present.

Added Prognostic Value of Cerebrospinal Fluid Biomarkers in Predicting Decline in Memory Clinic Patients in a Prospective Cohort. - Handels, Ron L H; Joore, Manuela A; Vos, Stephanie J B; Aalten, Pauline; Ramakers, Inez H G B; Rikkert, Marcel Olde; Scheltens, Philip; Jansen, Willemijn J; Visser, Pieter-Jelle; van Berckel, Bart M N; van Domburg, Peter; Smid, Machiel; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Limited information is available on short-term prognosis of Alzheimer's disease (AD) biomarkers in cerebrospinal fluid (CSF) in addition to routine diagnostic workup. OBJECTIVE: This study aims to investigate the added prognostic value of AD CSF biomarkers. METHODS: In a prospective cohort study, clinical experts predicted cognitive and functional symptoms in 114 memory clinic patients by assessing comprehensive routine diagnostic test information (patient history, and physical, neurological, psychiatric, neuropsychological, and MRI examinations), without and with CSF biomarkers. The reference standard was the 'observed clinically relevant decline' using baseline and 1- and 2-year follow-up information. RESULTS: Decline over a 2-year period was observed in 51% of all participants (3% in SMC, 48% in MCI, 90% in mild dementia). In the total sample, the accuracy of predicted decline did not differ significantly between routine assessment without (79% correctly predicted) and with (74% correctly predicted) CSF biomarkers. Subgroup analyses revealed 25 (83%) correct predictions in SMC, 30 (68%) in MCI, and 35 (88%) in dementia without the use of CSF; and 21 (70%), 27 (61%), and 36 (90%), respectively, with the use of CSF in addition to the routine assessment. CONCLUSION: AD CSF biomarkers did not increase accuracy of 2-year prognosis of cognitive and functional decline when added to routine diagnostic workup. This suggests that the standard diagnostic workup without CSF biomarkers allows fairly accurate predictions for the short-term course of symptoms. Routine AD biomarkers in CSF have limited prognostic value over 2 years in persons with a suspected cognitive disorder.

Adenosine Type A2A Receptor in Peripheral Cell from Patients with Alzheimer's Disease, Vascular Dementia, and Idiopathic Normal Pressure Hydrocephalus: A New/Old Potential Target. - Arosio, Beatrice; Casati, Martina; Gussago, Cristina; Ferri, Evelyn; Abbate, Carlo; Scortichini, Valeria; Colombo, Elena; Rossi, Paolo Dionigi; Mari, Daniela (J Alzheimers Dis, 2016)
As the European population gets older, the incidence of neurological disorders increases with significant impact on social costs. Despite differences in disease etiology, several brain disorders in the elderly (e.g., Alzheimer's disease, vascular dementia, normal pressure hydrocephalus) share dementia as a common clinical feature. The current treatment for the majority of these diseases is merely symptomatic and does not modify the course of the illness. Symptoms of normal pressure hydrocephalus are the only ones that can be modified if they are recognized in time and treated appropriately. Therefore, an important clinical strategy may be disclosed by pathogenic pathways that can be modified and to find drugs that can slow down or even arrest disease progression. Possibly a way to answer this question could be by re-examining all the molecules which have so far succeeded in improving many aspects of cognitive deterioration in some neurodegenerative conditions, that were not considered because of controversial opinions. The main purpose of this summary is to further substantiate the hypothesis that the pathway of adenosine type A2A receptor could be used as a potential target to develop new/old therapeutic strategies.

Alcohol Consumption and Incident Dementia: Evidence from the Sydney Memory and Ageing Study. - Heffernan, Megan; Mather, Karen A; Xu, Jing; Assareh, Amelia A; Kochan, Nicole A; Reppermund, Simone; Draper, Brian; Trollor, Julian N; Sachdev, Perminder; Brodaty, Henry (J Alzheimers Dis, 2016)
Alcohol consumption is a potentially modifiable risk factor for dementia, but the literature is not completely consistent. This inconsistency may be partly due to an interaction with the apolipoprotein E (APOE) genotype, an established risk factor for Alzheimer's dementia. The aim of this study was to examine whether alcohol consumption is associated with incident dementia or decline in specific cognitive domains over 4 years, and if this effect is modified by APOEɛ4 status. Non-demented community dwelling older adults (70-90 years) from an ongoing longitudinal study were assessed for cognitive impairment in attention/processing speed, language, executive function, visuospatial ability, and memory. Incident dementia was diagnosed according to DSM-IV criteria. Compared to those who did not drink in the previous 12 months, neither low consumption (HR 0.64 95% CI 0.3-1.4) or risky consumption (HR 0.58 95% CI 0.2-1.5) was associated with incident dementia. Carriers of the APOEɛ4 allele were more likely to develop dementia, but there was no significant interaction with alcohol consumption.

Altered Affective Evaluations of Smells in Alzheimer's Disease. - Joussain, Pauline; Bessy, Marion; Fournel, Arnaud; Ferdenzi, Camille; Rouby, Catherine; Delphin-Combe, Floriane; Krolak-Salmon, Pierre; Bensafi, Moustafa (J Alzheimers Dis, 2016)
BACKGROUND: Studies of olfaction in Alzheimer's disease (AD) mainly focused on deficits in odor detection and identification, with very few investigations of olfactory emotional changes and their consequences for hedonics. OBJECTIVE: The aim of the present study was to characterize affective evaluations of odors in AD patients. METHODS: To this end, 20 AD patients and 20 matched controls were tested. Participants were screened for odor detection and identification ability and then asked to rate the intensity, pleasantness, and edibility of 20 odorants. RESULTS: Results showed that, overall, AD patients had lower detection ability and perceived all odors as weaker than controls. As expected, they had lower identification ability on both cued and non-cued tasks. In addition, when smelling pleasant odors, patients had significantly lower hedonic ratings than controls (p <  0.02), whereas no group difference was found for neutral or unpleasant odors (p >  0.05 in both cases). Moreover, an analysis combining both intensity and pleasantness ratings showed that whereas intensity increased as a function of pleasantness and unpleasantness in controls, this quadratic relationship was not observed in AD patients. CONCLUSIONS: The study suggests that the simplest categorization criteria of odors (intensity and hedonic valence) are impaired in AD patients (especially for pleasant odors).
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Case-Control Studies; Emotions; Female; Humans; Male; Mood Disorders; Odorants; Olfaction Disorders; Psychiatric Status Rating Scales; Smell; Surveys and Questionnaires

Altered sense of humor in dementia. - Clark, Camilla N; Nicholas, Jennifer M; Gordon, Elizabeth; Golden, Hannah L; Cohen, Miriam H; Woodward, Felix J; Macpherson, Kirsty; Slattery, Catherine F; Mummery, Catherine J; Schott, Jonathan M; Rohrer, Jonathan D; Warren, Jason D (J Alzheimers Dis, 2016)
Sense of humor is potentially relevant to social functioning in dementias, but has been little studied in these diseases. We designed a semi-structured informant questionnaire to assess humor behavior and preferences in patients with behavioral variant frontotemporal dementia (bvFTD; n = 15), semantic dementia (SD; n = 7), progressive nonfluent aphasia (PNFA; n = 10), and Alzheimer's disease (AD; n = 16) versus healthy age-matched individuals (n = 21). Altered (including frankly inappropriate) humor responses were significantly more frequent in bvFTD and SD (all patients) than PNFA or AD (around 40% of patients). All patient groups liked satirical and absurdist comedy significantly less than did healthy controls. This pattern was reported premorbidly for satirical comedy in bvFTD, PNFA, and AD. Liking for slapstick comedy did not differ between groups. Altered sense of humor is particularly salient in bvFTD and SD, but also frequent in AD and PNFA. Humor may be a sensitive probe of social cognitive impairment in dementia, with diagnostic, biomarker and social implications.
Keywords: Aged; Alzheimer Disease; Case-Control Studies; Cognition Disorders; Emotions; Female; Frontotemporal Dementia; Humans; Male; Middle Aged; Neuropsychological Tests; Primary Progressive Nonfluent Aphasia; Psychiatric Status Rating Scales; Surveys and Questionnaires

Anthocyanins Protect SK-N-SH Cells Against Acrolein-Induced Toxicity by Preserving the Cellular Redox State. - Belkacemi, Abdenour; Ramassamy, Charles (J Alzheimers Dis, 2016)
In Alzheimer's disease (AD) and in mild cognitive impairment (MCI) patients, by-products of lipid peroxidation such as acrolein accumulated in vulnerable regions of the brain. We have previously shown that acrolein is a highly reactive and neurotoxic aldehyde and its toxicity involves the alteration of several redox-sensitive pathways. Recently, protein-conjugated acrolein in cerebrospinal fluid has been proposed as a biomarker to distinguish between MCI and AD. With growing evidence of the early involvement of oxidative stress in AD etiology, one would expect that a successful therapy should prevent brain oxidative damage. In this regard, several studies have demonstrated that polyphenol-rich extracts exert beneficial effect on cognitive impairment and oxidative stress. We have recently demonstrated the efficacy of an anthocyanin formulation (MAF14001) against amyloid-β-induced oxidative stress. The aim of this study is to investigate the neuroprotective effect of MAF14001 as a mixture of anthocyanins, a particular class of polyphenols, against acrolein-induced oxidative damage in SK-N-SH neuronal cells. Our results demonstrated that MAF14001, from 5μM, was able to efficiently protect SK-N-SH cells against acrolein-induced cell death. MAF14001 was able to lower reactive oxygen species and protein carbonyl levels induced by acrolein. Moreover, MAF1401 prevented glutathione depletion and positively modulated, in the presence of acrolein, some oxidative stress-sensitive pathways including the transcription factors NF-κB and Nrf2, the proteins γ-GCS and GSK3β, and the protein adaptator p66Shc. Along with its proven protective effect against amyloid-β toxicity, these results demonstrate that MAF14001 could target multiple mechanisms and could be a promising agent for AD prevention.
Keywords: Acrolein; Anthocyanins; Antioxidants; Cell Death; Cell Line, Tumor; Dose-Response Relationship, Drug; Glutathione; Humans; Neuroprotective Agents; NF-kappa B; Oxidation-Reduction; Oxidative Stress; Reactive Oxygen Species; Src Homology 2 Domain-Containing, Transforming Protein 1

The Anti-Prion Antibody 15B3 Detects Toxic Amyloid-β Oligomers. - Stravalaci, Matteo; Tapella, Laura; Beeg, Marten; Rossi, Alessandro; Joshi, Pooja; Pizzi, Erika; Mazzanti, Michele; Balducci, Claudia; Forloni, Gianluigi; Biasini, Emiliano; Salmona, Mario; Diomede, Luisa; et al. (J Alzheimers Dis, 2016)
15B3 is a monoclonal IgM antibody that selectively detects pathological aggregates of the prion protein (PrP). We report the unexpected finding that 15B3 also recognizes oligomeric but not monomeric forms of amyloid-β (Aβ)42, an aggregating peptide implicated in the pathogenesis of Alzheimer's disease (AD). The 15B3 antibody: i) inhibits the binding of synthetic Aβ42 oligomers to recombinant PrP and neuronal membranes; ii) prevents oligomer-induced membrane depolarization; iii) antagonizes the inhibitory effects of oligomers on the physiological pharyngeal contractions of the nematode Caenorhabditis elegans; and iv) counteracts the memory deficits induced by intracerebroventricular injection of Aβ42 oligomers in mice. Thus this antibody binds to pathologically relevant forms of Aβ, and offers a potential research, diagnostic, and therapeutic tool for AD.

Approaches to Increasing Ethical Compliance in China with Drug Trial Standards of Practice. - Rosenberg, Jacob (J Alzheimers Dis, 2016)
Zeng et al.'s Ethics Review highlights some of the challenges associated with clinical research in China. They found that only a minority of published clinical trials of anti-dementia drugs reported that they fulfilled the basic ethical principles as outlined in the Declaration of Helsinki. With recent reports of scientific misconduct from China, there is an urgent need to find approaches to compel researchers to adhere to ethical research practices. This problem does not call for a simple solution, but if forces are joined with governmental regulations, education in ethics issues for medical researchers, and strong reinforcement by Chinese journal editors not to publish studies with these flaws, then research ethics and publication standards will probably improve. Other solutions to foster ethical practice of drug trials are discussed including Chinese initiatives directed at managing conflict of interest from the pharmaceutical industry and educating clinical researchers.

Assessment and Reporting of Driving Fitness in Patients with Dementia in Clinical Practice: Data from SveDem, the Swedish Dementia Registry. - Lovas, Joel; Fereshtehnejad, Seyed-Mohammad; Cermakova, Pavla; Lundberg, Catarina; Johansson, Björn; Johansson, Kurt; Winblad, Bengt; Eriksdotter, Maria; Religa, Dorota (J Alzheimers Dis, 2016)
BACKGROUND: Driving constitutes a very important aspect of daily life and is dependent on cognitive functions such as attention, visuo-spatial skills and memory, which are often compromised in dementia. Therefore, the driving fitness of patients with dementia needs to be addressed by physicians and those that are deemed unfit should not be allowed to continue driving. OBJECTIVE: We aimed at investigating to what extent physicians assess driving fitness in dementia patients and determinant factors for revoking of their licenses. METHODS: This study includes 15113 patients with newly diagnosed dementia and driver's license registered in the Swedish Dementia Registry (SveDem). The main outcomes were reporting to the licensing authority and making an agreement about driving eligibility with the patients. RESULTS: Physicians had not taken any action in 16% of dementia patients, whereas 9% were reported to the authority to have their licenses revoked. Males (OR = 3.04), those with an MMSE score between 20-24 (OR = 1.35) and 10-19 (OR = 1.50), patients with frontotemporal (OR = 3.09) and vascular dementia (OR = 1.26) were more likely to be reported to the authority. CONCLUSION: For the majority of patients with dementia, driving fitness was assessed. Nevertheless, physicians did not address the issue in a sizeable proportion of dementia patients. Type of dementia, cognitive status, age, sex and burden of comorbidities are independent factors associated with the assessment of driving fitness in patients with dementia. Increased knowledge on how these factors relate to road safety may pave the way for more specific guidelines addressing the issue of driving in patients with dementia.

The Association Between Plasma Ceramides and Sphingomyelins and Risk of Alzheimer's Disease Differs by Sex and APOE in the Baltimore Longitudinal Study of Aging. - Mielke, Michelle M; Haughey, Norman J; Han, Dingfen; An, Yang; Bandaru, Veera Venkata Ratnam; Lyketsos, Constantine G; Ferrucci, Luigi; Resnick, Susan M (J Alzheimers Dis, 2016)
BACKGROUND: Cellular and animal studies demonstrated relationships between sphingolipid metabolism and Alzheimer's disease (AD) pathology. High blood ceramide levels have been shown to predict cognitive impairment and AD, but these studies had small sample sizes and did not assess differences in risk by sex or APOE genotype. OBJECTIVE: To determine whether plasma ceramides and sphingomyelins were associated with risk of AD, and whether the association varied by sex and APOE genotype. METHODS: Participants included 626 men and 366 women, aged 55 years and older, enrolled in the Baltimore Longitudinal Study of Aging. Plasma ceramides and sphingomyelins were determined using quantitative analyses performed on a high-performance liquid chromatography coupled electrospray ionization tandem mass spectrometer. Cox proportional hazards models, stratified by sex, were used to examine the relationship of plasma ceramides and sphingomyelins with risk of AD over a mean (SD) follow-up of 15.0 (7.0) years for men and 13.1 (5.9) years for women. RESULTS: Among men, the highest tertile of most ceramides and sphingomyelins were associated with an increased risk of AD. Among women, there were no associations between any of the ceramides and risk of AD. In contrast, women in the highest tertile of most sphingomyelins had a reduced risk of AD, which was most pronounced among APOE ɛ4 carriers. CONCLUSION: These results provide further evidence for the role of sphingolipid metabolism in AD and highlight the importance of considering sex and APOE genotype in assessing this relationship.

Association Between Serum Ceruloplasmin Specific Activity and Risk of Alzheimer's Disease. - Siotto, Mariacristina; Simonelli, Ilaria; Pasqualetti, Patrizio; Mariani, Stefania; Caprara, Deborah; Bucossi, Serena; Ventriglia, Mariacarla; Molinario, Rossana; Antenucci, Mirca; Rongioletti, Mauro; Rossini, Paolo Maria; Squitti, Rosanna (J Alzheimers Dis, 2016)
Meta-analyses demonstrate copper involvement in Alzheimer's disease (AD), and the systemic ceruloplasmin status in relation to copper is an emerging issue. To deepen this matter, we evaluated levels of ceruloplasmin concentration, ceruloplasmin activity, ceruloplasmin specific activity (eCp/iCp), copper, non-ceruloplasmin copper iron, transferrin, the ceruloplasmin/transferrin ratio, and the APOE genotype in a sample of 84 AD patients and 58 healthy volunteers. From the univariate logistic analyses we found that ceruloplasmin concentration, eCp/iCp, copper, transferrin, the ceruloplasmin/transferrin ratio, and the APOE genotype were significantly associated with the probability of AD. In the multivariable logistic regression analysis, we selected the best subset of biological predictors by the forward stepwise procedure. The analysis showed a decrease of the risk of having AD for eCp/iCp (p = 0.001) and an increase of this risk for non-ceruloplasmin copper (p = 0.008), age (p = 0.001), and APOE-ɛ4 allele (p <  0.001). The estimated model showed a good power in discriminating AD patients from healthy controls (area under curve: 88% ; sensitivity: 66% ; specificity 93%). These data strength the breakdown of copper homeostasis and propose eCp/iCp as a reliable marker of ceruloplasmin status.
Keywords: Aged; Alzheimer Disease; Apolipoprotein E4; Area Under Curve; Biomarkers; Blood Chemical Analysis; Ceruloplasmin; Copper; Female; Genotype; Genotyping Techniques; Humans; Logistic Models; Male; Multivariate Analysis; Prognosis; Risk; ROC Curve; Sensitivity and Specificity; Transferrin

Association of Butyrylcholinesterase-K Allele and Apolipoprotein E ɛ4 Allele with Cognitive Decline in Dementia with Lewy Bodies and Alzheimer's Disease. - Vijayaraghavan, Swetha; Darreh-Shori, Taher; Rongve, Arvid; Berge, Guro; Sando, Sigrid B; White, Linda R; Auestad, Bjørn H; Witoelar, Aree; Andreassen, Ole A; Ulstein, Ingun D; Aarsland, Dag (J Alzheimers Dis, 2016)
BACKGROUND: A common polymorphism of the butyrylcholinesterase gene, the K-variant (BCHE-K) is associated with reduced butyrylcholinesterase (BuChE) activity. Insufficient studies exist regarding the frequency and role of BCHE-K in dementias. OBJECTIVE: To determine the association of BCHE-K and APOEɛ4 with diagnosis and rate of cognitive decline in dementia with Lewy bodies (DLB) and Alzheimer's disease (AD) patients. METHODS: Genomic DNA from 368 subjects (108 AD, 174 DLB, and 86 controls) from two routine clinical cohort studies in Norway; DemVest and TrønderBrain, were genotyped for BCHE-K and APOEɛ4. The mild dementia DemVest subjects received annual Mini-Mental State Examination assessments for five years. RESULTS: BCHE-K frequency was lower in DLB (33.9% ; p <  0.01) than in control subjects (51.2%), and was numerically lower in AD as well (38.9% ; p = 0.11). More rapid cognitive decline was associated with the APOEɛ4 genotype, but not with the BCHE-K genotype. In an exploratory analysis of patients who completed all five follow-up visits, there was greater cognitive decline in BCHE-K carriers in the presence of the APOEɛ4 allele than in the absence of these polymorphisms. CONCLUSION: BCHE-K is associated with a reduced risk for AD and DLB whereas APOEɛ4 is associated with more rapid cognitive decline. The greater cognitive decline in individuals with both APOEɛ4 and BCHE-K alleles require prospective confirmation in well-controlled trials.
Keywords: Aged; Aged, 80 and over; Alleles; Alzheimer Disease; Apolipoprotein E4; Butyrylcholinesterase; Cognition; Disease Progression; Female; Gene Frequency; Genotype; Humans; Lewy Body Disease; Male; Neuropsychological Tests

Association of Plasma Aβ40 Peptides, But Not Aβ42, with Coronary Artery Disease and Diabetes Mellitus. - Roeben, Benjamin; Maetzler, Walter; Vanmechelen, Eugeen; Schulte, Claudia; Heinzel, Sebastian; Stellos, Konstantinos; Godau, Jana; Huber, Heiko; Brockmann, Kathrin; Wurster, Isabel; Gaenslen, Alexandra; Grüner, Eva; et al. (J Alzheimers Dis, 2016)
BACKGROUND/OBJECTIVE: Plasma levels of amyloid-beta (Aβ) 1-40 peptide have been proposed to be associated with cardiovascular mortality in patients with coronary artery disease (CAD). Therefore, we aimed to investigate the association of plasma Aβ levels with CAD, cardiovascular risk factors (CVRF), and APOE genotype in non-demented elderly individuals. METHODS: Plasma Aβ1 - 40 and Aβ1 - 42 levels of 526 individuals (mean age of 63.0±7.3 years) were quantified with the INNO-BIA plasma Aβ forms assay based on multiplextrademark technique. APOE genotype was determined with an established protocol. Presence of CAD and CVRFs were ascertained using a questionnaire and/or medical records. RESULTS: Plasma Aβ1 - 40 levels were significantly higher in individuals with CAD (p = 0.043) and, independently, in individuals with diabetes mellitus (DM) type 2 (p = 0.001) while accounting for age- and gender-effects. Plasma Aβ1 - 42 levels were higher in APOEɛ4 carriers (p = 0.004), but were neither relevantly associated with CAD nor with any CVRF. Plasma Aβ1 - 40 showed no association with APOE genotype. DISCUSSION: Our findings argue for an association of circulating plasma Aβ1 - 40 peptides with incident CAD and DM. Further investigations are needed to entangle the role of Aβ1 - 40 role in the pathophysiology of cardiovascular disease independent of its known role in Alzheimer's disease.

Association of Serum Vitamin D with the Risk of Incident Dementia and Subclinical Indices of Brain Aging: The Framingham Heart Study. - Karakis, Ioannis; Pase, Matthew P; Beiser, Alexa; Booth, Sarah L; Jacques, Paul F; Rogers, Gail; DeCarli, Charles; Vasan, Ramachandran S; Wang, Thomas J; Himali, Jayandra J; Annweiler, Cedric; Seshadri, Sudha (J Alzheimers Dis, 2016)
BACKGROUND: Identifying nutrition- and lifestyle-based risk factors for cognitive impairment and dementia may aid future primary prevention efforts. OBJECTIVE: We aimed to examine the association of serum vitamin D levels with incident all-cause dementia, clinically characterized Alzheimer's disease (AD), MRI markers of brain aging, and neuropsychological function. METHODS: Framingham Heart Study participants had baseline serum 25-hydroxyvitamin D (25(OH)D) concentrations measured between 1986 and 2001. Vitamin D status was considered both as a continuous variable and dichotomized as deficient (<10 ng/mL), or at the cohort-specific 20th and 80th percentiles. Vitamin D was related to the 9-year risk of incident dementia (n = 1663), multiple neuropsychological tests (n = 1291) and MRI markers of brain volume, white matter hyperintensities and silent cerebral infarcts (n = 1139). RESULTS: In adjusted models, participants with vitamin D deficiency (n = 104, 8% of the cognitive sample) displayed poorer performance on Trail Making B-A (β= -0.03 to -0.05±0.02) and the Hooper Visual Organization Test (β= -0.09 to -0.12±0.05), indicating poorer executive function, processing speed, and visuo-perceptual skills. These associations remained when vitamin D was examined as a continuous variable or dichotomized at the cohort specific 20th percentile. Vitamin D deficiency was also associated with lower hippocampal volumes (β= -0.01±0.01) but not total brain volume, white matter hyperintensities, or silent brain infarcts. No association was found between vitamin D deficiency and incident all-cause dementia or clinically characterized AD. CONCLUSIONS: In this large community-based sample, low 25(OH)D concentrations were associated with smaller hippocampal volume and poorer neuropsychological function.
Keywords: Adult; Aging; Brain; Cohort Studies; Dementia; Female; Humans; Incidence; Magnetic Resonance Imaging; Male; Middle Aged; Multivariate Analysis; Neuropsychological Tests; Regression Analysis; Risk; Sensitivity and Specificity; Vitamin D

Associations between Neuropsychiatric Symptoms and Cerebral Amyloid Deposition in Cognitively Impaired Elderly People. - Bensamoun, David; Guignard, Renaud; Furst, Ansgar J; Derreumaux, Alexandre; Manera, Valeria; Darcourt, Jacques; Benoit, Michel; Robert, Philippe H; David, Renaud (J Alzheimers Dis, 2016)
BACKGROUND: Neuropsychiatric symptoms, also known as behavioral and psychological symptoms of dementia (BPSD), affect the majority of patients with dementia, and result in a greater cognitive and functional impairment. OBJECTIVE: To investigate associations between BPSD and amyloid cerebral deposition as measured by 18F-Florbetapir-PET quantitative uptake in elderly subjects with and without cognitive impairment. METHODS: Participants with cognitive impairment [mild cognitive impairment (MCI) or Alzheimer's disease (AD)] and healthy controls (HC) from the ADNI cohort (Alzheimer Disease Neuroimaging Initiative) who underwent an 18F-florbetapir PET scan between May 2010 and March 2014 were included. Clinical assessments included the Clinical Dementia Rating, the Mini-Mental State Examination (MMSE), and the Neuropsychiatric Inventory. Freesurfer software was used to extract PET counts based on T1-based structural ROI (frontal, cingulate, parietal, and temporal). Spearman's partial correlation scores between BPSD severity and regional amyloid uptake were calculated. RESULTS: Data for 657 participants [age = 72.6 (7.19); MMSE = 27.4 (2.67)] were analyzed, including 230 HC [age = 73.1 (6.02); MMSE = 29 (1.21)], 308 MCI [age = 71.5 (7.44); MMSE = 28.0 (1.75)], and 119 AD subjects [age = 74.7 (8.05); MMSE = 23.1 (2.08)]. Considering all diagnostic groups together, positive significant correlations were found between anxiety and 18F-florbetapir uptake in the frontal (r = 0.102; p = 0.009), cingulate (r = 0.083; p = 0.034), and global cerebral uptake (r = 0.099; p = 0.011); between irritability and frontal (r = 0.089; p = 0.023), cingulate (r = 0.085; p = 0.030), parietal (r = 0.087; p = 0.025), and global cerebral uptake (r = 0.093; p = 0.017); in the MCI subgroup, between anxiety and frontal (r = 0.126; p = 0.03) and global uptake (r = 0.14; p = 0.013); in the AD subgroup, between irritability and parietal uptake (r = 0.201; p = 0.03). CONCLUSION: Anxiety and irritability are associated with greater amyloid deposition in the neurodegenerative process leading to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloidogenic Proteins; Cerebral Cortex; Cognition Disorders; Cohort Studies; Female; Fluorodeoxyglucose F18; Humans; Male; Mental Status Schedule; Mood Disorders; Neuropsychological Tests; Positron-Emission Tomography

Associations between Performance on an Abbreviated CogState Battery, Other Measures of Cognitive Function, and Biomarkers in People at Risk for Alzheimer's Disease. - Racine, Annie M; Clark, Lindsay R; Berman, Sara E; Koscik, Rebecca L; Mueller, Kimberly D; Norton, Derek; Nicholas, Christopher R; Blennow, Kaj; Zetterberg, Henrik; Jedynak, Bruno; Bilgel, Murat; Carlsson, Cynthia M; et al. (J Alzheimers Dis, 2016)
It is not known whether computerized cognitive assessments, like the CogState battery, are sensitive to preclinical cognitive changes or pathology in people at risk for Alzheimer's disease(AD). In 469 late middle-aged participants from the Wisconsin Registry for Alzheimer's Prevention(mean age 63.8±7 years at testing; 67% female; 39% APOE4+), we examined relationships between a CogState abbreviated battery(CAB) of seven tests and demographic characteristics, traditional paper-based neuropsychological tests as well as a composite cognitive impairment index, cognitive impairment status(determined by consensus review), and biomarkers for amyloid and tau(CSF phosphorylated-tau/Aβ42 and global PET-PiB burden) and neural injury(CSF neurofilament light protein). CSF and PET-PiB were collected in n = 71 and n = 91 participants, respectively, approximately four years prior to CAB testing. For comparison, we examined three traditional tests of delayed memory in parallel. Similar to studies in older samples, the CAB was less influenced by demographic factors than traditional tests. CAB tests were generally correlated with most paper-based cognitive tests examined and mapped onto the same cognitive domains. Greater composite cognitive impairment index was associated with worse performance on all CAB tests. Cognitively impaired participants performed significantly worse compared to normal controls on all but one CAB test. Poorer One Card Learning test performance was associated with higher levels of CSF phosphorylated-tau/Aβ42. These results support the use of the CogState battery as measures of early cognitive impairment in studies of people at risk for AD.

Astrocytic GluN2A and GluN2B Oppose the Synaptotoxic Effects of Amyloid-β1-40 in Hippocampal Cells. - Li, Yan; Chang, Lirong; Song, Yizhi; Gao, Xianghong; Roselli, Francesco; Liu, Jinping; Zhou, Wei; Fang, Yuan; Ling, Wei; Li, Hui; Almeida, Osborne F X; Wu, Yan (J Alzheimers Dis, 2016)
Early-stage Alzheimer's disease (AD) is characterized by synaptic dysfunction, a phenomenon in which soluble oligomers of amyloid-beta (Aβ) and N-methyl-D-aspartate receptor (NMDAR) are implicated. Here, we demonstrated that astrocytes express NMDARs and therefore have the potential to modulate the synaptotoxic actions of Aβ. We found that specific pharmacological antagonism of two of the major NMDAR subunits, GluN2A and GluN2B, exacerbates Aβ-induced synaptotoxicity suggesting, for the first time, that astrocytic GluN2A and GluN2B mediate synaptoprotection. From the perspective of the pathogenic mechanisms of Alzheimer's disease, in which Aβ and NMDAR play significant roles, these observations are striking since neuronal GluN2A and GluN2B are well known modulators of neurodegeneration. We did initial studies to understand the basis for the differential effects of astrocytic and neuronal GluN2A and GluN2B in the promotion of synapse survival, and identified a neurotrophin produced by astrocytes, nerve growth factor β (β-NGF), as a likely mediator of the synaptoprotective effects of astrocytic GluN2A and GluN2B activation. The results presented suggest that astrocytes may be suitable druggable targets for the prevention and/or delay of the synaptic loss that occurs during early stages of AD.

Autobiographical Memory Performance in Alzheimer's Disease Depends on Retrieval Frequency. - Müller, Stephan; Mychajliw, Christian; Reichert, Carolin; Melcher, Tobias; Leyhe, Thomas (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is characterized by memory disturbances primarily caused by pathogenic mechanisms affecting medial temporal lobe structures. As proposed by current theories of memory formation, this decrease is mediated by the age of the acquired knowledge. However, they cannot fully explain specific patterns of retrograde amnesia in AD. In the current study we examined an alternative approach and investigated whether the extent and severity of retrograde amnesia in AD is mediated by the frequency of memory retrieval or whether it depends on the mere age of knowledge. We compared recall of autobiographical incidents from three life periods in patients with amnestic mild cognitive impairment (aMCI), patients with early dementia of Alzheimer type (eDAT), and healthy control (HC) individuals using the Autobiographical Memory Interview. Retrieval frequency was operationalized by a paired comparison analysis. In contrast to HC individuals, recall of autobiographical incidents was impaired in patients with aMCI and eDAT following Ribot's gradient, with a reduced memory loss for remote compared to more recent life events. However, there was a strong effect of retrieval frequency on memory performance with frequently retrieved incidents memorized in more detail than less frequently retrieved episodes. Remote memories were recalled more often than recent ones. These findings suggest that more frequently retrieved autobiographical memories generally become more independent of the hippocampal complex and might thus be better protected against early hippocampal damage related to AD. Hence, the extent of retrograde amnesia in AD appears mainly mediated by the frequency of memory retrieval, which could plausibly explain why cognitive activity can effectively delay the onset of memory decline in AD.

Behavioral and Electrophysiological Correlates of Memory Binding Deficits in Patients at Different Risk Levels for Alzheimer's Disease. - Pietto, Marcos; Parra, Mario A; Trujillo, Natalia; Flores, Facundo; García, Adolfo M; Bustin, Julian; Richly, Pablo; Manes, Facundo; Lopera, Francisco; Ibáñez, Agustín; Baez, Sandra (J Alzheimers Dis, 2016)
Deficits in visual short-term memory (VSTM) binding have been proposed as an early and specific marker for Alzheimer's disease (AD). However, no studies have explored the neural correlates of this domain in clinical categories involving prodromal stages with different risk levels of conversion to AD. We assessed underlying electrophysiological modulations in patients with mild cognitive impairment (MCI), patients in the MCI stages of familial AD carrying the mutation E280A of the presenilin-1 gene (MCI-FAD), and healthy controls. Moreover, we compared the behavioral performance and neural correlates of both patient groups. Participants completed a change-detection VSTM task assessing recognition of changes between shapes or shape-color bindings, presented in two consecutive arrays (i.e., study and test) while event related potentials (ERPs) were recorded. Changes always occurred in the test array and consisted of new features replacing studied features (shape-only) or features swapping across items (shape-color binding). Both MCI and MCI-FAD patients performed worse than controls in the shape-color binding condition. Early electrophysiological activity (100-250 ms) was significantly reduced in both clinical groups, particularly over fronto-central and parieto-occipital regions. However, shape-color binding performance and their reduced neural correlates were similar between MCI and MCI-FAD. Our results support the validity of the VSTM binding test and their neural correlates in the early detection of AD and highlight the importance of studies comparing samples at different risk for AD conversion. The combined analysis of behavioral and ERP data gleaned with the VSTM binding task can offer a valuable memory biomarker for AD.

Beneficial Effects of an Integrated Psychostimulation Program in Patients with Alzheimer's Disease. - Ibarria, Marta; Alegret, Montserrat; Valero, Sergi; Morera, Amèrica; Guitart, Marina; Cañabate, Pilar; Moreno, Mariola; Lara, Susana; Diego, Susana; Hernández, Joan; Tantinyá, Natàlia; Vera, Maribel; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The existing pharmacological treatments for Alzheimer's disease (AD) can only slow the progression of symptoms or delay admission to long-term care facilities. The beneficial effects of non-drug treatments are poorly studied. OBJECTIVE: To describe the effects of an Integrated Psychostimulation Program (IPP) in patients with mild-moderate AD treated with acetylcholinesterase inhibitors; and to identify factors related to greater benefit of the IPP. METHODS: 206 patients (mean age = 75.9 years; MMSE = 19.6) were evaluated before starting the IPP and 3, 6, 9, and 12 months later. Measures included: Mini-Mental State Examination (MMSE), Cognitive Subscale of Alzheimer's Disease Assessment Scale (ADAS-Cog), Rapid Disability Rating Scale (RDRS-2), and Neuropsychiatric Inventory Questionnaire (NPI-Q). RESULTS: Patients remained cognitively stable (MMSE/ADAS-Cog) for more than 6 months and significantly worsened at 9-month and 12-month follow-ups, without clinically significant functional changes (RDRS-2) or psychiatric symptoms(NPI-Q). The mean annual change on MMSE and ADAS-Cog were 2.06 and 3.56 points, respectively, lower than the annual decline demonstrated previously in similar patients (2.4 and 4.5, respectively). 42.7% of patients maintained or improved global cognitive scores between baseline and 12-month follow-up. The patients who maintained cognitive functions were older than those who did not (77.5 versus 74.7 years). CONCLUSIONS: The IPP may be an effective treatment to maintain cognition, functionality, and psychiatric symptoms in AD patients pharmacologically treated, and older age seems to increase beneficial effects of IPP.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cholinesterase Inhibitors; Cognition; Combined Modality Therapy; Disease Progression; Female; Humans; Male; Neuropsychological Tests; Psychotherapy; Severity of Illness Index; Treatment Outcome

Biomarker Exposure-Response Analysis in Mild-To-Moderate Alzheimer's Disease Trials of Bapineuzumab. - Russu, Alberto; Samtani, Mahesh N; Xu, Steven; Adedokun, Omoniyi J; Lu, Ming; Ito, Kaori; Corrigan, Brian; Raje, Sangeeta; Liu, Enchi; Brashear, H Robert; Styren, Scot; Hu, Chuanpu (J Alzheimers Dis, 2016)
BACKGROUND: Bapineuzumab, an anti-amyloid monoclonal antibody, was evaluated as a candidate for immunotherapy in mild-to-moderate Alzheimer's disease (AD) patients. OBJECTIVE: To assess the treatment effect of bapineuzumab therapy on disease-relevant biomarkers in patients with mild-to-moderate AD, using exposure-response modeling. METHODS: Biomarker data from two Phase III studies were combined to model the impact of bapineuzumab exposure on week-71 change from baseline in brain amyloid burden by 11C-labeled Pittsburgh compound B (PiB) PET imaging (global cortical average of the Standardized Uptake Value ratio values), cerebrospinal fluid (CSF) phosphorylated (p)-tau concentrations, and brain volumetrics (brain boundary shift integral) by magnetic resonance imaging. Bapineuzumab or placebo was administered as a 1-hour intravenous infusion every 13 weeks for 78 weeks. Pharmacokinetic/pharmacodynamic modeling helped determine the most appropriate exposure-response model and estimate the impact of disease-relevant covariates (baseline biomarker value, APOE*E4 allele copy number, and baseline disease status as measured by Mini-Mental State Examination score) on the three biomarkers. RESULTS: Linear exposure-response relationships with negative and significant slope terms were observed for PiB PET and CSF p-tau concentration. Baseline biomarker value and APOE*E4 carrier status were significant covariates for both biomarkers. No exposure-response relationship on brain boundary shift integral was detected. CONCLUSIONS: Bapineuzumab treatment induced exposure-dependent reductions in brain amyloid burden. Effects on CSF p-tau concentrations were significant only in APOE*E4 carriers. No apparent influence of bapineuzumab exposure on brain volume could be demonstrated.

Brain Metabolism Correlates of the Free and Cued Selective Reminding Test in Mild Cognitive Impairment. - Caffarra, Paolo; Ghetti, Caterina; Ruffini, Livia; Spallazzi, Marco; Spotti, Annamaria; Barocco, Federica; Guzzo, Caterina; Marchi, Massimo; Gardini, Simona (J Alzheimers Dis, 2016)
Free and Cued Selective Reminding Test (FCSRT) measures immediate and delayed episodic memory and cueing sensitivity and is suitable to detect prodromal Alzheimer's disease (AD). The present study aimed at investigating the segregation effect of FCSRT scores on brain metabolism of memory-related structures, usually affected by AD pathology, in the Mild Cognitive Impairment (MCI) stage. A cohort of forty-eight MCI patients underwent FCSRT and 18F-FDG-PET. Multiple regression analysis showed that Immediate Free Recall correlated with brain metabolism in the bilateral anterior cingulate and delayed free recall with the left anterior cingulate and medial frontal gyrus, whereas semantic cueing sensitivity with the left posterior cingulate. FCSRT in MCI is associated with neuro-functional activity of specific regions of memory-related structures connected to hippocampal formation, such as the cingulate cortex, usually damaged in AD.
Keywords: Aged; Brain; Cognitive Dysfunction; Cues; Female; Fluorodeoxyglucose F18; Humans; Male; Memory Disorders; Memory, Episodic; Mental Recall; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography

A Brief Computerized Paired Associate Test for the Detection of Mild Cognitive Impairment in Community-Dwelling Older Adults. - Curiel, Rosie E; Crocco, Elizabeth; Rosado, Marian; Duara, Ranjan; Greig, Maria T; Raffo, Arlene; Loewenstein, David A (J Alzheimers Dis, 2016)
BACKGROUND: Semantic memory interference has been found to be a predictive cognitive marker of incipient AD. This is relevant given that developing assessment paradigms to identify subtle cognitive and functional deficits is a priority in preclinical Alzheimer's disease research. OBJECTIVE: To examine the utility of a novel computerized paired associate test in distinguishing between mild cognitive impairment (MCI) and cognitively normal (CN) groups of older adults residing in the community. METHODS: Participants that were CN (n = 64) or MCI (n = 34) were administered the Miami Test of Semantic Interference and Learning (MITSI-L). This novel instrument is a brief, computerized paired associate test that measured the strength of memory binding of semantically related word pairs and introduced a proactive semantic interference condition which required participants to make different associations between semantically similar targets. A series of ANOVAs explored differences on MITSI-L performance. Logistic regression and receiver operator curves (ROC) analyses were employed to further determine discriminative validity. RESULTS: MCI participants had lower scores on all indices relative to CN elders. A composite of two subscores correctly classified 85.3% of MCI and 84.4% of CN participants. Area under the ROC was higher relative to the MMSE, immediate memory for passages, and several subtests of a sensitive memory measure, the LASSI-L. CONCLUSIONS: The MITSI-L is a computerized test that can successfully differentiate MCI from CN participants. Area under the ROC curve exceeded that of global mental status and other memory measures. The effectiveness of the MITSI-L in detecting MCI, and its brief administration and portability render it worthy of further research.

Cerebral Glucose Metabolism is Associated with Verbal but not Visual Memory Performance in Community-Dwelling Older Adults. - Gardener, Samantha L; Sohrabi, Hamid R; Shen, Kai-Kai; Rainey-Smith, Stephanie R; Weinborn, Michael; Bates, Kristyn A; Shah, Tejal; Foster, Jonathan K; Lenzo, Nat; Salvado, Olivier; Laske, Christoph; Laws, Simon M; et al. (J Alzheimers Dis, 2016)
Increasing evidence suggests that Alzheimer's disease (AD) sufferers show region-specific reductions in cerebral glucose metabolism, as measured by [18F]-fluoro-2-deoxyglucose positron emission tomography (18F-FDG PET). We investigated preclinical disease stage by cross-sectionally examining the association between global cognition, verbal and visual memory, and 18F-FDG PET standardized uptake value ratio (SUVR) in 43 healthy control individuals, subsequently focusing on differences between subjective memory complainers and non-memory complainers. The 18F-FDG PET regions of interest investigated include the hippocampus, amygdala, posterior cingulate, superior parietal, entorhinal cortices, frontal cortex, temporal cortex, and inferior parietal region. In the cohort as a whole, verbal logical memory immediate recall was positively associated with 18F-FDG PET SUVR in both the left hippocampus and right amygdala. There were no associations observed between global cognition, delayed recall in logical memory, or visual reproduction and 18F-FDG PET SUVR. Following stratification of the cohort into subjective memory complainers and non-complainers, verbal logical memory immediate recall was positively associated with 18F-FDG PET SUVR in the right amygdala in those with subjective memory complaints. There were no significant associations observed in non-memory complainers between 18F-FDG PET SUVR in regions of interest and cognitive performance. We observed subjective memory complaint-specific associations between 18F-FDG PET SUVR and immediate verbal memory performance in our cohort, however found no associations between delayed recall of verbal memory performance or visual memory performance. It is here argued that the neural mechanisms underlying verbal and visual memory performance may in fact differ in their pathways, and the characteristic reduction of 18F-FDG PET SUVR observed in this and previous studies likely reflects the pathophysiological changes in specific brain regions that occur in preclinical AD.

Cerebrospinal Fluid Alzheimer's Disease Biomarkers in Cerebral Amyloid Angiopathy-Related Inflammation. - Renard, Dimitri; Wacongne, Anne; Ayrignac, Xavier; Charif, Mahmoud; Fourcade, Genevieve; Azakri, Souhayla; Le Floch, Anne; Bouly, Stephane; Marelli, Cecilia; Arquizan, Caroline; Hirtz, Christophe; Gabelle, Audrey; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Decreased cerebrospinal fluid (CSF) amyloid-β 1-40 (Aβ40) and amyloid-β 1-42 (Aβ42) and increased total and phosphorylated tau (t-tau, p-tau) concentrations have been described in cerebral amyloid angiopathy (CAA). OBJECTIVE: Our aim was to analyze these biomarkers in patients with CAA-related inflammation (CAA-I). METHODS: We prospectively recruited nine patients with acute phase CAA-I fulfilling Chung criteria. CSF was analyzed for t-tau, p-tau, Aβ42, and Aβ40. Data were compared to controls (n = 14), patients with Alzheimer's disease (AD, n = 42), CAA (n = 10), and primary angiitis of the central nervous system (PACNS, n = 3). RESULTS: For the CAA-I group, statistically significant differences were: lower Aβ42 (p = 0.00053) compared to the control group; lower t-tau (p = 0.018), p-tau (p <  0.001), and Aβ40 (p <  0.001) compared to AD; lower Aβ42 (p = 0.027) compared to CAA; lower Aβ42 (p = 0.012) compared to PACNS. Nearly significantly lower Aβ40 (p = 0.051) and higher t-tau (p = 0.051) were seen in CAA-I compared to controls. CONCLUSION: CSF biomarkers profile similar to that of CAA was observed in CAA-I (with even lower levels of Aβ42 compared to CAA). Based on our findings, high p-tau seems more specific for AD, whereas low Aβ42 differentiates CAA-I from CAA, PACNS, and controls, and low Aβ40 differentiates CAA-I from AD.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cerebral Amyloid Angiopathy; Female; Humans; Inflammation; Male; Middle Aged; Retrospective Studies; tau Proteins

Cerebrospinal Fluid Alzheimer's Disease Biomarkers in Isolated Supratentorial Cortical Superficial Siderosis. - Renard, Dimitri; Gabelle, Audrey; Hirtz, Christophe; Demattei, Christophe; Thouvenot, Eric; Lehmann, Sylvain (J Alzheimers Dis, 2016)
We evaluated cerebrospinal fluid amyloid-β 1-40 (Aβ40), amyloid-β 1-42 (Aβ42), total and phosphorylated-tau (t-tau and p-tau) in patients with symptomatic isolated cortical supratentorial superficial siderosis (SS), by prospectively recruiting ten patients with SS in the absence of pre-existing cognitive dysfunction, and comparing biomarkers with lobar hematoma cerebral amyloid angiopathy patients (LH-CAA, n = 13), Alzheimer's disease patients (AD, n = 42), and controls (n = 16). Compared to controls, SS patients showed statistically significant higher t-tau (p = 0.019) and lower Aβ42 (p = 0.0084). Compared to other groups, SS showed statistically significant lower t-tau, p-tau, and Aβ40 compared to AD (p = 0.0063, p = 0.0004, and p = 0022, respectively), and higher p-tau compared to LH-CAA (p = 0.012).

Cerebrospinal Fluid Biomarkers and Reserve Variables as Predictors of Future "Non-Cognitive" Outcomes of Alzheimer's Disease. - Ingber, Adam P; Hassenstab, Jason; Fagan, Anne M; Benzinger, Tammie L S; Grant, Elizabeth A; Holtzman, David M; Morris, John C; Roe, Catherine M (J Alzheimers Dis, 2016)
BACKGROUND: The influence of reserve variables and Alzheimer's disease (AD) biomarkers on cognitive test performance has been fairly well-characterized. However, less is known about the influence of these factors on "non-cognitive" outcomes, including functional abilities and mood. OBJECTIVE: We examined whether cognitive and brain reserve variables mediate how AD biomarker levels in cognitively normal persons predict future changes in function, mood, and neuropsychiatric behavior. METHODS: Non-cognitive outcomes were examined in 328 individuals 50 years and older enrolled in ongoing studies of aging and dementia at the Knight Alzheimer Disease Research Center (ADRC). All participants were cognitively normal at baseline (Clinical Dementia Rating [CDR] 0), completed cerebrospinal fluid (CSF) and structural neuroimaging studies within one year of baseline, and were followed for an average of 4.6 annual visits. Linear mixed effects models explored how cognitive reserve and brain reserve variables mediate the relationships between AD biomarker levels and changes in function, mood, and neuropsychiatric behavior in cognitively normal participants. RESULTS: Education levels did not have a significant effect on predicting non-cognitive decline. However, participants with smaller brain volumes exhibited the worst outcomes on measures of mood, functional abilities, and behavioral disturbance. This effect was most pronounced in individuals who also had abnormal CSF biomarkers. CONCLUSIONS: The findings suggest that brain reserve plays a stronger, or earlier, role than cognitive reserve in protecting against non-cognitive impairment in AD.

Cerebrospinal Fluid Biomarkers in Highly Exposed PM2.5 Urbanites: The Risk of Alzheimer's and Parkinson's Diseases in Young Mexico City Residents. - Calderón-Garcidueñas, Lilian; Avila-Ramírez, José; Calderón-Garcidueñas, Ana; González-Heredia, Tonatiuh; Acuña-Ayala, Hilda; Chao, Chih-Kai; Thompson, Charles; Ruiz-Ramos, Rubén; Cortés-González, Victor; Martínez-Martínez, Luz; García-Pérez, Mario Alberto; Reis, Jacques; et al. (J Alzheimers Dis, 2016)
Exposure to fine particulate matter (PM2.5) and ozone (O3) above US EPA standards is associated with Alzheimer's disease (AD) risk, while Mn toxicity induces parkinsonism. Mexico City Metropolitan Area (MCMA) children have pre- and postnatal sustained and high exposures to PM2.5, O3, polycyclic aromatic hydrocarbons, and metals. Young MCMA residents exhibit frontal tau hyperphosphorylation and amyloid-β (Aβ)1 - 42 diffuse plaques, and aggregated and hyperphosphorylated α-synuclein in olfactory nerves and key brainstem nuclei. We measured total prion protein (TPrP), total tau (T-tau), tau phosphorylated at threonine 181 (P-Tau), Aβ1-42, α-synuclein (t-α-syn and d-α-synuclein), BDNF, insulin, leptin, and/or inflammatory mediators, in 129 normal CSF samples from MCMA and clean air controls. Aβ1-42 and BDNF concentrations were significantly lower in MCMA children versus controls (p = 0.005 and 0.02, respectively). TPrP increased with cumulative PM2.5 up to 5 μg/m3 and then decreased, regardless of cumulative value or age (R2 = 0.56). TPrP strongly correlated with T-Tau and P-Tau, while d-α-synuclein showed a significant correlation with TNFα, IL10, and IL6 in MCMA children. Total synuclein showed an increment in childhood years related to cumulated PM2.5, followed by a decrease after age 12 years (R2 = 0.47), while d-α-synuclein exhibited a tendency to increase with cumulated PM2.5 (R2 = 0.30). CSF Aβ1-42, BDNF, α-synuclein, and TPrP changes are evolving in young MCMA urbanites historically showing underperformance in cognitive processes, odor identification deficits, downregulation of frontal cellular PrP, and neuropathological AD and PD hallmarks. Neuroprotection of young MCMA residents ought to be a public health priority.

Cerebrospinal Fluid Markers of Alzheimer's Disease Pathology and Microglial Activation are Associated with Altered White Matter Microstructure in Asymptomatic Adults at Risk for Alzheimer's Disease. - Melah, Kelsey E; Lu, Sharon Yuan-Fu; Hoscheidt, Siobhan M; Alexander, Andrew L; Adluru, Nagesh; Destiche, Daniel J; Carlsson, Cynthia M; Zetterberg, Henrik; Blennow, Kaj; Okonkwo, Ozioma C; Gleason, Carey E; Dowling, N Maritza; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The immune response in Alzheimer's disease (AD) involves activation of microglia which may remove amyloid-β (Aβ). However, overproduction of inflammatory compounds may exacerbate neural damage in AD. AD pathology accumulates years before diagnosis, yet the extent to which neuroinflammation is involved in the earliest disease stages is unknown. OBJECTIVE: To determine whether neuroinflammation exacerbates neural damage in preclinical AD. METHODS: We utilized cerebrospinal fluid (CSF) and magnetic resonance imaging collected in 192 asymptomatic late-middle-aged adults (mean age = 60.98 years). Neuroinflammatory markers chitinase-3-like protein 1 (YKL-40) and monocyte chemoattractant protein-1 (MCP-1) in CSF were utilized as markers of neuroinflammation. Neural cell damage was assessed using CSF neurofilament light chain protein (NFL), CSF total tau (T-Tau), and neural microstructure assessed with diffusion tensor imaging (DTI). With regard to AD pathology, CSF Aβ42 and tau phosphorylated at threonine 181 (P-Tau181) were used as markers of amyloid and tau pathology, respectively. We hypothesized that higher YKL-40 and MCP-1 in the presence of AD pathology would be associated with higher NFL, T-Tau, and altered microstructure on DTI. RESULTS: Neuroinflammation was associated with markers of neural damage. Higher CSF YKL-40 was associated with both higher CSF NFL and T-Tau. Inflammation interacted with AD pathology, such that greater MCP-1 and lower Aβ42 was associated with altered microstructure in bilateral frontal and right temporal lobe and that greater MCP-1 and greater P-Tau181 was associated with altered microstructure in precuneus. CONCLUSION: Inflammation may play a role in neural damage in preclinical AD.
Keywords: Adipokines; Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Chemokine CCL2; Chitinase-3-Like Protein 1; Diffusion Tensor Imaging; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Lectins; Male; Microglia; Middle Aged; Peptide Fragments; tau Proteins; White Matter

The Cerebrospinal Fluid Neurogranin/BACE1 Ratio is a Potential Correlate of Cognitive Decline in Alzheimer's Disease. - De Vos, Ann; Struyfs, Hanne; Jacobs, Dirk; Fransen, Erik; Klewansky, Tom; De Roeck, Ellen; Robberecht, Caroline; Van Broeckhoven, Christine; Duyckaerts, Charles; Engelborghs, Sebastiaan; Vanmechelen, Eugeen (J Alzheimers Dis, 2016)
BACKGROUND: In diagnosing Alzheimer's disease (AD), ratios of cerebrospinal fluid (CSF) biomarkers, such as CSF Aβ1-42/tau, have an improved diagnostic performance compared to the single analytes, yet, still a limited value to predict cognitive decline. Since synaptic dysfunction/loss is closely linked to cognitive impairment, synaptic proteins are investigated as candidate CSF AD progression markers. OBJECTIVE: We studied CSF levels of the postsynaptic protein neurogranin and protein BACE1, predominantly localized presynaptically, and their relation to CSF total-tau, Aβ1-42, Aβ1-40, and Aβ1-38. All six analytes were considered as single parameters as well as ratios. METHODS: Every ELISA involved was based on monoclonal antibodies, including the BACE1 and neurogranin immunoassay. The latter specifically targets neurogranin C-terminally truncated at P75, a more abundant species of the protein in CSF. We studied patients with MCI due to AD (n = 38) and 50 dementia due to AD patients, as well as age-matched cognitively healthy elderly (n = 20). A significant subset of the patients was followed up by clinical and neuropsychological (MMSE) examinations for at least one year. RESULTS: The single analytes showed statistically significant differences between the clinical groups, but the ratios of analytes indeed had a higher diagnostic performance. Furthermore, only the ratio of CSF neurogranin trunc P75/BACE1 was significantly correlated with the yearly decline in MMSE scores in patients with MCI and dementia due to AD, pointing toward the prognostic value of the ratio. CONCLUSION: This is the first study demonstrating that the CSF neurogranin trunc P75/BACE1 ratio, reflecting postsynaptic/presynaptic integrity, is related to cognitive decline.

Changes in Frailty Predict Changes in Cognition in Older Men: The Honolulu-Asia Aging Study. - Armstrong, Joshua J; Godin, Judith; Launer, Lenore J; White, Lon R; Mitnitski, Arnold; Rockwood, Kenneth; Andrew, Melissa K (J Alzheimers Dis, 2016)
BACKGROUND: As cognitive decline mostly occurs in late life, where typically it co-exists with many other ailments, it is important to consider frailty in understanding cognitive change. OBJECTIVE: Here, we examined the association of change in frailty status with cognitive trajectories in a well-studied cohort of older Japanese-American men. METHODS: Using the prospective Honolulu-Asia Aging Study (HAAS), 2,817 men of Japanese descent were followed (aged 71-93 at baseline). Starting in 1991 with follow-up health assessments every two to three years, cognition was measured using the Cognitive Abilities Screening Instrument (CASI). For this study, health data was used to construct an accumulation of deficits frailty index (FI). Using six waves of data, multilevel growth curve analyses were constructed to examine simultaneous changes in cognition in relation to changes in FI, controlling for baseline frailty, age, education, and APOE-ɛ4 status. RESULTS: On average, CASI scores declined by 2.0 points per year (95% confidence interval 1.9-2.1). Across six waves, each 10% within-person increase in frailty from baseline was associated with a 5.0 point reduction in CASI scores (95% confidence interval 4.7-5.2). Baseline frailty and age were associated both with lower initial CASI scores and with greater decline across the five follow-up assessments (p < 0.01). DISCUSSION: Cognition is adversely affected by impaired health status in old age. Using a multidimensional measure of frailty, both baseline status and within-person changes in frailty were predictive of cognitive trajectories.

Changes in Neuropsychiatric Inventory Associated with Semagacestat Treatment of Alzheimer's Disease. - Rosenberg, Paul B; Lanctôt, Krista L; Herrmann, Nathan; Mintzer, Jacobo E; Porsteinsson, Anton P; Sun, Xiaoying; Raman, Rema (J Alzheimers Dis, 2016)
BACKGROUND: In a recent report, 76 weeks' treatment with a gamma-secretase inhibitor (semagacestat) was associated with poorer cognitive outcomes in Alzheimer's disease (AD). OBJECTIVE: We sought to examine the effect of semagacestat treatment on neuropsychiatric symptoms (NPS). METHODS: 1,537 participants with mild to moderate AD were randomized to 76 weeks' treatment with placebo versus two doses of semagacestat. NPS were assessed with the Neuropsychiatric Inventory (NPI-Total and subdomains). Cognition was assessed with the Alzheimer's Disease Assessment Scale-Cognitive (first 11 items, ADAS11). Mixed-Model Repeated Measures was used to compare the effects of treatment assignment on change in NPI-total and subdomains over time. Survival analysis was used to assess the treatment effect on time to first worsening of NPS (NPI-Total ≥10 or NPI subdomain ≥4) for subjects with no or minor NPS at baseline. RESULTS: Participants on high dose semagecestat (140 mg) had greater increase in NPI-Total and greater risk of incident first worsening in NPI-Total and in subdomains of aberrant motor behavior, appetite, depression/dysphoria, and sleep. ADAS11 increased more in participants whose NPI-Total increased. CONCLUSION: In participants with mild to moderate AD, high dose semagacestat treatment was associated with greater severity and faster worsening of NPS in a pattern resembling an agitated depression. Increased NPS was associated with cognitive decline regardless of treatment assignment. These findings suggest that greater NPS may be the result of gamma-secretase treatment and emphasize the importance of monitoring NPS as potential adverse events in trials of novel treatments for AD.

Characteristics of Alzheimer's Disease Patients with Severe Executive Disorders. - Godefroy, Olivier; Bakchine, Serge; Verny, Marc; Delabrousse-Mayoux, Jean-Philippe; Roussel, Martine; Pere, Jean-Jacques (J Alzheimers Dis, 2016)
BACKGROUND: Executive dysfunctions in Alzheimer's disease (AD) have been assessed using variable batteries and/or in selected populations. OBJECTIVE: The primary objective of this observational study was to determine the prevalence and severity of executive dysfunction in AD patients using a previously validated battery. The secondary objective was to determine the characteristics including treatment outcomes of AD patients with severe executive dysfunction. METHODS: The study included AD patients with mild-to-moderate dementia aged 60 or over, consulting in various clinical settings including memory clinics and requiring the introduction of an antidementia drug. Executive dysfunction was examined using a validated, shortened executive battery. RESULTS: 381 patients were included. Executive dysfunctions were observed in 88.2% of the patients (95% CI: 84.9-91.4) and were severe (defined as ≥2/3 impaired scores) in 80.4% (95% CI: 76.9-84.8). Global hypoactivity with apathy was more frequent (p = 0.0001) than impairment in executive function tests. The 308 patients with severe executive dysfunction were older (p = 0.003) and had more severe dementia (p = 0.0001). Similarly, in the subset of 257 patients with mild dementia, individuals with severe executive dysfunction were older (p = 0.003) and had more severe dementia. Global hypoactivity was independently associated with difficulties in IADL and a higher caregiver burden (p = 0.0001 for both). The severity of executive dysfunction did not significantly influence the patients' outcomes at 6 months. CONCLUSIONS: Executive dysfunction is a very common disorder in a representative population of patients with mild-to-moderate AD. It was independently correlated with impaired autonomy and increased caregiver burden but did not significantly influence treatment outcomes.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Caregivers; Cost of Illness; Executive Function; Female; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Prevalence; Severity of Illness Index; Treatment Outcome

Characterizing White Matter Tract Degeneration in Syndromic Variants of Alzheimer's Disease: A Diffusion Tensor Imaging Study. - Madhavan, Ajay; Schwarz, Christopher G; Duffy, Joseph R; Strand, Edythe A; Machulda, Mary M; Drubach, Daniel A; Kantarci, Kejal; Przybelski, Scott A; Reid, Robert I; Senjem, Matthew L; Gunter, Jeffrey L; Apostolova, Liana G; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Different clinical syndromes can arise from Alzheimer's disease (AD) neuropathology, including dementia of the Alzheimer's type (DAT), logopenic primary progressive aphasia (lvPPA), and posterior cortical atrophy (PCA). OBJECTIVE: To assess similarities and differences in patterns of white matter tract degeneration across these syndromic variants of AD. METHODS: Sixty-four subjects (22 DAT, 24 lvPPA, and 18 PCA) that had diffusion tensor imaging and showed amyloid-β deposition on PET were assessed in this case-control study. A whole-brain voxel-based analysis was performed to assess differences in fractional anisotropy, mean diffusivity, axial diffusivity, and radial diffusivity across groups. RESULTS: All three groups showed overlapping diffusion abnormalities in a network of tracts, including fornix, corpus callosum, posterior thalamic radiations, superior longitudinal fasciculus, inferior longitudinal fasciculus, inferior fronto-occipital fasciculus, and uncinate fasciculus. Subtle regional differences were also observed across groups, with DAT particularly associated with degeneration of fornix and cingulum, lvPPA with left inferior fronto-occipital fasciculus and uncinate fasciculus, and PCA with posterior thalamic radiations, superior longitudinal fasciculus, posterior cingulate, and splenium of the corpus callosum. CONCLUSION: These findings show that while each AD phenotype is associated with degeneration of a specific structural network of white matter tracts, striking spatial overlap exists among the three network patterns that may be related to AD pathology.
Keywords: Aged; Alzheimer Disease; Aniline Compounds; Anisotropy; Aphasia, Primary Progressive; Case-Control Studies; Diffusion Tensor Imaging; Female; Humans; Image Processing, Computer-Assisted; Male; Middle Aged; Nerve Fibers, Myelinated; Neurodegenerative Diseases; Neuropsychological Tests; Positron-Emission Tomography; Psychiatric Status Rating Scales; Retrospective Studies; Thiazoles; White Matter

Clearing Amyloid-β through PPARγ/ApoE Activation by Genistein is a Treatment of Experimental Alzheimer's Disease. - Bonet-Costa, Vicent; Herranz-Pérez, Vicente; Blanco-Gandía, MariCarmen; Mas-Bargues, Cristina; Inglés, Marta; Garcia-Tarraga, Patricia; Rodriguez-Arias, Marta; Miñarro, Jose; Borras, Consuelo; Garcia-Verdugo, Jose Manuel; Viña, Jose (J Alzheimers Dis, 2016)
Amyloid-β (Aβ) clearance from brain, which is decreased in Alzheimer's disease, is facilitated by apolipoprotein E (ApoE). ApoE is upregulated by activation of the retinoid X receptor moiety of the RXR/PPARγ dimeric receptor. Genistein, a non-toxic, well-tested, and inexpensive drug activates the other moiety of the receptor PPARγ. Treatment of an Alzheimer's disease mouse model with genistein results in a remarkable and rapid improvement in various parameters of cognition, such as hippocampal learning, recognition memory, implicit memory, and odor discrimination. This is associated with a lowering of Aβ levels in brain, in the number and the area of amyloid plaques (confirmed in vivo by positron emission tomography) as well as in microglial reactivity. Finally, incubation of primary astrocytes with genistein results in a PPARγ-mediated increased release of ApoE. Our results strongly suggest that controlled clinical trials should be performed to test the effect of genistein as treatment of human Alzheimer's disease.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Apolipoproteins E; Astrocytes; Avoidance Learning; Brain; Cells, Cultured; Disease Models, Animal; Female; Genistein; Habituation, Psychophysiologic; Maze Learning; Mice, Inbred C57BL; Mice, Transgenic; Neuroprotective Agents; Nootropic Agents; Olfactory Perception; Plaque, Amyloid; PPAR gamma; Recognition (Psychology); Tetrahydronaphthalenes

Clinical and Demographic Factors Associated with the Cognitive and Emotional Efficacy of Regular Musical Activities in Dementia. - Särkämö, Teppo; Laitinen, Sari; Numminen, Ava; Kurki, Merja; Johnson, Julene K; Rantanen, Pekka (J Alzheimers Dis, 2016)
Recent evidence suggests that music-based interventions can be beneficial in maintaining cognitive, emotional, and social functioning in persons with dementia (PWDs). Our aim was to determine how clinical, demographic, and musical background factors influence the cognitive and emotional efficacy of caregiver-implemented musical activities in PWDs. In a randomized controlled trial, 89 PWD-caregiver dyads received a 10-week music coaching intervention involving either singing or music listening or standard care. Extensive neuropsychological testing and mood and quality of life (QoL) measures were performed before and after the intervention (n = 84) and six months later (n = 74). The potential effects of six key background variables (dementia etiology and severity, age, care situation, singing/instrument playing background) on the outcome of the intervention were assessed. Singing was beneficial especially in improving working memory in PWDs with mild dementia and in maintaining executive function and orientation in younger PWDs. Music listening was beneficial in supporting general cognition, working memory, and QoL especially in PWDs with moderate dementia not caused by Alzheimer's disease (AD) who were in institutional care. Both music interventions alleviated depression especially in PWDs with mild dementia and AD. The musical background of the PWD did not influence the efficacy of the music interventions. Our findings suggest that clinical and demographic factors can influence the cognitive and emotional efficacy of caregiver-implemented musical activities and are, therefore, recommended to take into account when applying and developing the intervention to achieve the greatest benefit.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Caregivers; Case-Control Studies; Cognition Disorders; Dementia; Executive Function; Female; Follow-Up Studies; Humans; Male; Memory, Short-Term; Middle Aged; Mood Disorders; Music Therapy; Neuropsychological Tests; Orientation; Outcome Assessment (Health Care); Psychiatric Status Rating Scales; Quality of Life

Clinical Conversion or Reversion of Mild Cognitive Impairment in Community versus Hospital Based Studies: GDEMCIS (Gwangju Dementia and Mild Cognitive Impairment Study) and CREDOS (Clinical Research Center for Dementia of South Korea). - Roh, Hyun Woong; Hong, Chang Hyung; Lee, Yunhwan; Lee, Kang Soo; Chang, Ki Jung; Kang, Dae Ryong; Lee, Jung-Dong; Choi, Seong Hye; Kim, Seong Yoon; Na, Duk L; Seo, Sang Won; Kim, Doh Kwan; et al. (J Alzheimers Dis, 2016)
BACKGROUND: In keeping with increasing interest in dementia, few recent studies suggest that clinical course of mild cognitive impairment vary across different studies with hospital-based subjects showing higher rates of conversion than community-based subjects. OBJECTIVE: The main objective of the present study was to assess whether the clinical conversion or reversion rates differ according to recruitment source. METHODS: The baseline study subjects comprised of patients who were diagnosed with mild cognitive impairment in community-based GDEMCIS or hospital-based CREDOS. The two studies had nearly the same protocol and were performed over a similar period. We used propensity score matching for baseline comparability. After that, Cox proportional hazards regression analyses were conducted to estimate the hazard ratios and 95% confidence intervals of clinical conversion or reversion. RESULTS: Based on 89 GDEMCIS subjects, 1 : 4 propensity score matching was conducted and 356 CREDOS subjects were selected. After adjusting for covariates including baseline demographics, comorbidity, depression, disability, and neuropsychological result, Cox proportional hazard regression analysis for time to clinical conversion indicated that recruitment from hospital-based CREDOS exhibited hazard ratio of 2.13 (95% CI, 1.08-4.21), as compared to recruitment from community-based GDEMCIS. Similarly, Cox proportional hazard regression analysis for time to reversion indicated that recruitment from hospital-based CREDOS exhibited hazard ratio of 0.34 (95% CI, 0.20-0.59), as compared to recruitment from community-based GDEMCIS. CONCLUSION: The present study demonstrated that even after the matching process and adjustments for baseline covariates, recruitment source greatly affected the course of mild cognitive impairment.

The Cognitive Change Index as a Measure of Self and Informant Perception of Cognitive Decline: Relation to Neuropsychological Tests. - Rattanabannakit, Chatchawan; Risacher, Shannon L; Gao, Sujuan; Lane, Kathleen A; Brown, Steven A; McDonald, Brenna C; Unverzagt, Frederick W; Apostolova, Liana G; Saykin, Andrew J; Farlow, Martin R (J Alzheimers Dis, 2016)
BACKGROUND: The perception of cognitive decline by individuals and those who know them well ("informants") has been inconsistently associated with objective cognitive performance, but strongly associated with depressive symptoms. OBJECTIVE: We investigated associations of self-report, informant-report, and discrepancy between self- and informant-report of cognitive decline obtained from the Cognitive Change Index (CCI) with cognitive test performance and self-reported depressive symptoms. METHODS: 267 participants with normal cognition, mild cognitive impairment (MCI), or mild dementia were included from a cohort study and memory clinic. Association of test performance and self-rated depression (Geriatric Depression Scale, GDS) with CCI scores obtained from subjects (CCI-S), their informants (CCI-I), and discrepancy scores between subjects and informants (CCI-D; CCI-S minus CCI-I) were analyzed using correlation and analysis of covariance (ANCOVA) models. RESULTS: CCI-S and CCI-I scores showed high internal consistency (Cronbach alpha 0.96 and 0.98, respectively). Higher scores on CCI-S and CCI-I, and lower scores on the CCI-D, were associated with lower performance on various cognitive tests in both univariate and in ANCOVA models adjusted for age, gender, and education. Adjustment for GDS slightly weakened the relationships between CCI and test performance but most remained significant. CONCLUSION: Self- and informant-report of cognitive decline, as measured by the CCI, show moderately strong relationships with objective test performance independent of age, gender, education, and depressive symptoms. The CCI appears to be a valid cross-sectional measure of self and informant perception of cognitive decline across the continuum of functioning. Studies are needed to address the relationship of CCI scores to longitudinal outcome.
Keywords: Adult; Aged; Aged, 80 and over; Analysis of Variance; Cognitive Dysfunction; Cross-Sectional Studies; Dementia; Female; Humans; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Perception; Self Report

Cognitive Profile and its Association with Neuroimaging Markers of Non-Demented Cerebral Amyloid Angiopathy Patients in a Stroke Unit. - Xiong, Li; Davidsdottir, Sigurros; Reijmer, Yael D; Shoamanesh, Ashkan; Roongpiboonsopit, Duangnapa; Thanprasertsuk, Sekh; Martinez-Ramirez, Sergi; Charidimou, Andreas; Ayres, Alison M; Fotiadis, Panagiotis; Gurol, Edip; Blacker, Deborah L; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Cerebral amyloid angiopathy (CAA) is increasingly recognized as a cause of cognitive impairment in the elderly, but the cognitive profile in patients with the disease has not been well characterized. OBJECTIVE: To characterize the neuropsychological profile of CAA patients without dementia and to determine the association between cognitive performance in different domains and neuroimaging lesions characteristic of CAA. METHODS: Fifty-eight non-demented CAA patients were compared to 138 cognitively normal subjects using a standard neuropsychological test battery. Total brain volume (TBV), white matter hyperintensities, number of lobar cerebral microbleeds, hippocampal volume, and cortical superficial siderosis in all CAA patients were assessed. The association between these neuroimaging markers and neuropsychological performance in different cognitive domains in the CAA group were analyzed. RESULTS: Patients with CAA had significantly worse performance on all individual neuropsychological domains tested, when compared to the cognitive normal group. The cognitive decline of CAA patients was most noticeable in tests for processing speed with a Z score of -1.92±1.56 (mean±SD), then followed by executive function (-0.93±1.01), episodic memory (-0.87±1.29), semantic fluency (-0.73±1.06), and attention (-0.42±0.98). TBV of the CAA patients was correlated with processing speed (β= 0.335, p = 0.03) and executive function (β= 0.394, p = 0.01). CONCLUSIONS: Non-demented patients with CAA had cognitive deficits in multiple areas. Lower TBV was related to slower processing speed and worse executive function.
Keywords: Aged; Atrophy; Brain; Cerebral Amyloid Angiopathy; Cognition; Cognition Disorders; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Stroke

Combination of Structural MRI and FDG-PET of the Brain Improves Diagnostic Accuracy in Newly Manifested Cognitive Impairment in Geriatric Inpatients. - Ritter, Kerstin; Lange, Catharina; Weygandt, Martin; Mäurer, Anja; Roberts, Anna; Estrella, Melanie; Suppa, Per; Spies, Lothar; Prasad, Vikas; Steffen, Ingo; Apostolova, Ivayla; Bittner, Daniel; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The cause of cognitive impairment in acutely hospitalized geriatric patients is often unclear. The diagnostic process is challenging but important in order to treat potentially life-threatening etiologies or identify underlying neurodegenerative disease. OBJECTIVE: To evaluate the add-on diagnostic value of structural and metabolic neuroimaging in newly manifested cognitive impairment in elderly geriatric inpatients. METHODS: Eighty-one inpatients (55 females, 81.6±5.5 y) without history of cognitive complaints prior to hospitalization were recruited in 10 acute geriatrics clinics. Primary inclusion criterion was a clinical hypothesis of Alzheimer's disease (AD), cerebrovascular disease (CVD), or mixed AD+CVD etiology (MD), which remained uncertain after standard diagnostic workup. Additional procedures performed after enrollment included detailed neuropsychological testing and structural MRI and FDG-PET of the brain. An interdisciplinary expert team established the most probable etiologic diagnosis (non-neurodegenerative, AD, CVD, or MD) integrating all available data. Automatic multimodal classification based on Random Undersampling Boosting was used for rater-independent assessment of the complementary contribution of the additional diagnostic procedures to the etiologic diagnosis. RESULTS: Automatic 4-class classification based on all diagnostic routine standard procedures combined reproduced the etiologic expert diagnosis in 31% of the patients (p = 0.100, chance level 25%). Highest accuracy by a single modality was achieved by MRI or FDG-PET (both 45%, p≤0.001). Integration of all modalities resulted in 76% accuracy (p≤0.001). CONCLUSION: These results indicate substantial improvement of diagnostic accuracy in uncertain de novo cognitive impairment in acutely hospitalized geriatric patients with the integration of structural MRI and brain FDG-PET into the diagnostic process.

Community-Dwelling People Screened Positive for Dementia in Primary Care: A Comprehensive, Multivariate Descriptive Analysis Using Data from the DelpHi-Study. - Thyrian, Jochen René; Eichler, Tilly; Michalowsky, Bernhard; Wucherer, Diana; Reimann, Melanie; Hertel, Johannes; Richter, Steffen; Dreier, Adina; Hoffmann, Wolfgang (J Alzheimers Dis, 2016)
BACKGROUND: Efficient help and care for people with dementia (PWD) is dependent on knowledge about PWD in primary care. OBJECTIVE: This analysis comprehensively describes community-dwelling PWD in primary care with respect to various dementia care specific variables. METHODS: The analyses are based on baseline data of the ongoing general practitioner-based, randomized, controlled intervention trial DelpHi-MV (Dementia: life- and person-centered help). 6,838 patients were screened for dementia in 136 GP practices; 17.1% were screened positive, 54.4% of those agreed to participate and data could be assessed in n = 516 subjects. We assessed age, sex, living situation, cognitive status, functional status, level of impairment, comorbidities, formal diagnosis of dementia, depression, neuropsychiatric symptoms, quality of life, utilization of medical support, and pharmacological therapy. RESULTS: Concerning clinical-, dementia-, and health-related variables, the sample under examination was on average mildly cognitively and functionally impaired (MMSE, m = 22.2; BADL, m = 3.7). A level of care was assigned in 38.0%. Depression was identified in 15.4% and other frequent comorbidities were high blood pressure (83.3%), coronary heart diseases (37.1%), cerebrovascular diseases (22.3%), among others. In 48.6%, neuropsychiatric symptoms were present in a clinically relevant severity. Pharmacological treatment with antidementia medication was received by 25.8% and antidepressant medication by 14.0%. Utilization of services was generally low. CONCLUSION: The comprehensive description of people screened positive for dementia in primary care reveals a complex and unique population of patients. They are considerably underdiagnosed and in their majority mildly to moderately affected. More in-depth analyses are needed to study relations, associations and interactions between different variables.

Comparison of Different Matrices as Potential Quality Control Samples for Neurochemical Dementia Diagnostics. - Lelental, Natalia; Brandner, Sebastian; Kofanova, Olga; Blennow, Kaj; Zetterberg, Henrik; Andreasson, Ulf; Engelborghs, Sebastiaan; Mroczko, Barbara; Gabryelewicz, Tomasz; Teunissen, Charlotte; Mollenhauer, Brit; Parnetti, Lucilla; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Assay-vendor independent quality control (QC) samples for neurochemical dementia diagnostics (NDD) biomarkers are so far commercially unavailable. This requires that NDD laboratories prepare their own QC samples, for example by pooling leftover cerebrospinal fluid (CSF) samples. OBJECTIVE: To prepare and test alternative matrices for QC samples that could facilitate intra- and inter-laboratory QC of the NDD biomarkers. METHODS: Three matrices were validated in this study: (A) human pooled CSF, (B) Aβ peptides spiked into human prediluted plasma, and (C) Aβ peptides spiked into solution of bovine serum albumin in phosphate-buffered saline. All matrices were tested also after supplementation with an antibacterial agent (sodium azide). We analyzed short- and long-term stability of the biomarkers with ELISA and chemiluminescence (Fujirebio Europe, MSD, IBL International), and performed an inter-laboratory variability study. RESULTS: NDD biomarkers turned out to be stable in almost all samples stored at the tested conditions for up to 14 days as well as in samples stored deep-frozen (at - 80°C) for up to one year. Sodium azide did not influence biomarker stability. Inter-center variability of the samples sent at room temperature (pooled CSF, freeze-dried CSF, and four artificial matrices) was comparable to the results obtained on deep-frozen samples in other large-scale projects. CONCLUSION: Our results suggest that it is possible to replace self-made, CSF-based QC samples with large-scale volumes of QC materials prepared with artificial peptides and matrices. This would greatly facilitate intra- and inter-laboratory QC schedules for NDD measurements.
Keywords: Amyloid beta-Peptides; Animals; Anti-Bacterial Agents; Biomarkers; Cattle; Clinical Chemistry Tests; Dementia; Humans; Peptide Fragments; Quality Control; Reference Standards; Serum Albumin, Bovine; Sodium Azide; tau Proteins; Time Factors; Tissue Preservation

Complementary and Alternative Medicine in the Context of Earlier Diagnoses of Alzheimer's Disease: Opening the Conversation to Prepare Ethical Responses. - Racine, Eric; Forlini, Cynthia; Aspler, John; Chandler, Jennifer (J Alzheimers Dis, 2016)
Preclinical Alzheimer's disease (AD), a newly proposed, actively researched, and hotly debated research-only diagnostic category, raises the prospect of an ethical dilemma: whether, and possibly how, to treat a disorder with no target symptoms. This proposed category rests on the detection of a number of biomarkers thought to provide evidence of AD pathophysiology years before any behavioral symptoms manifest. Faced with limited treatment options, patients and their relatives may come to consider complementary and alternative medicine (CAM) a viable option, albeit one with minimal supporting evidence. Accordingly, the hopes and needs of some preclinical patients and their relatives could further fuel market-oriented entrepreneurship for CAM. In this ethics review, we provide background and reflect on some ethical questions related to the roles of key stakeholders arising from the potential for CAM use in the context of a possible preclinical AD diagnosis.
Keywords: Alzheimer Disease; Complementary Therapies; Early Diagnosis; Ethical Analysis; Humans

Connected Language in Late Middle-Aged Adults at Risk for Alzheimer's Disease. - Mueller, Kimberly Diggle; Koscik, Rebecca L; Turkstra, Lyn S; Riedeman, Sarah K; LaRue, Asenath; Clark, Lindsay R; Hermann, Bruce; Sager, Mark A; Johnson, Sterling C (J Alzheimers Dis, 2016)
Connected language is often impaired among people with Alzheimer's disease (AD), yet little is known about when language difficulties first emerge on the path to a clinical diagnosis. The objective of this study was to determine whether individuals with psychometric (preclinical) evidence of amnestic mild cognitive impairment (pMCI) showed deficits in connected language measures. Participants were 39 pMCI and 39 cognitively healthy (CH) adults drawn from the Wisconsin Registry for Alzheimer's Prevention, who were matched for age, literacy, and sex. Participants completed a connected language task in which they described the Cookie Theft picture from the Boston Diagnostic Aphasia Examination. Language samples were analyzed across three language domains: content, syntactic complexity, and speech fluency. Paired t-tests were used to compare CH and pMCI groups on all variables, and Cohen's d effect sizes were calculated for each comparison. The CH and pMCI groups differed significantly on measures of content (e.g., CH group produced more semantic units, more unique words and had larger idea density, on average, than the pMCI group). The picture description findings are consistent with previous retrospective studies showing semantic language differences in adults with autopsy-confirmed AD. Given that these comparisons are between cognitively healthy and pMCI individuals (before a clinical MCI diagnosis), these findings may represent subtle language difficulty in spontaneous speech, and may be predictive of larger language changes over time.

Consequences of Anosognosia on the Cost of Caregivers' Care in Alzheimer's Disease. - Turró-Garriga, Oriol; Garre-Olmo, Josep; Reñé-Ramírez, Ramón; Calvó-Perxas, Laia; Gascón-Bayarri, Jordi; Conde-Sala, Josep-Lluís (J Alzheimers Dis, 2016)
BACKGROUND: Anosognosia is common in patients with Alzheimer's disease (AD) and it is frequently related to an increase in time of care demand. OBJECTIVE: The aim of the study was to examine the effect of anosognosia on the total costs of informal care in patients with AD. METHODS: This was a prospective longitudinal study with community-dwelling AD patients. Anosognosia, time of informal care, and the use of support services (e.g., day care centers) were recorded at baseline and after 24 months. The cost of informal caregiving was calculated as 'market price'. RESULTS: At baseline, the prevalence of anosognosia was 54.3% (n = 221), and 43.9% were classified as mild-AD. The average time of care was 5 h/day±2.4 (IADL: 1.3 h/day±1.4 and BADL: 3.6 h/day±1.5). Thirty percent of the patients used home care services, and 25.1% attended a day care center. Patients with anosognosia received more time of care and were more likely to use support services than did their no-anosognosia peers, including institutionalization. The mean cost of support services was 490.4€ /month (SD = 413.1€; range = 25-2,212.38€), while the overall cost of care (support services plus informal care) was 1,787€ /month (SD = 972.4€), ranging from 834.1€ in mild-AD without anosognosia patients, to 2,424.8€ in severe-AD with incident anosognosia patients. CONCLUSIONS: Anosognosia was associated with an increased number of hours of informal care, and a greater use of support services, regardless of the severity of the dementia, which lead to an increase of the total family-care costs.

Contribution of the Cholinergic System to Verbal Memory Performance in Mild Cognitive Impairment. - Peter, Jessica; Lahr, Jacob; Minkova, Lora; Lauer, Eliza; Grothe, Michel J; Teipel, Stefan; Köstering, Lena; Kaller, Christoph P; Heimbach, Bernhard; Hüll, Michael; Normann, Claus; Nissen, Christoph; et al. (J Alzheimers Dis, 2016)
Acetylcholine is critically involved in modulating learning and memory function, which both decline in neurodegeneration. It remains unclear to what extent structural and functional changes in the cholinergic system contribute to episodic memory dysfunction in mild cognitive impairment (MCI), in addition to hippocampal degeneration. A better understanding is critical, given that the cholinergic system is the main target of current symptomatic treatment in mild to moderate Alzheimer's disease. We simultaneously assessed the structural and functional integrity of the cholinergic system in 20 patients with MCI and 20 matched healthy controls and examined their effect on verbal episodic memory via multivariate regression analyses. Mediating effects of either cholinergic function or hippocampal volume on the relationship between cholinergic structure and episodic memory were computed. In MCI, a less intact structure and function of the cholinergic system was found. A smaller cholinergic structure was significantly correlated with a functionally more active cholinergic system in patients, but not in controls. This association was not modulated by age or disease severity, arguing against compensational processes. Further analyses indicated that neither functional nor structural changes in the cholinergic system influence verbal episodic memory at the MCI stage. In fact, those associations were fully mediated by hippocampal volume. Although the cholinergic system is structurally and functionally altered in MCI, episodic memory dysfunction results primarily from hippocampal neurodegeneration, which may explain the inefficiency of cholinergic treatment at this disease stage.

Course and Determinants of Anosognosia in Alzheimer's Disease: A 12-Month Follow-up. - Turró-Garriga, Oriol; Garre-Olmo, Josep; Calvó-Perxas, Laia; Reñé-Ramírez, Ramón; Gascón-Bayarri, Jordi; Conde-Sala, Josep Lluís (J Alzheimers Dis, 2016)
Anosognosia in Alzheimer's disease (AD) has been associated with greater cognitive impairment and more behavioural and psychological symptoms of dementia (BPSD). This study examines the incidence, persistence, and remission rates of anosognosia over a 12-month period, as well as the related risk factors. This was an observational 12-month prospective study. The longitudinal sample comprised 177 patients with mild or moderate AD, and their respective caregivers. Anosognosia was assessed using the Anosognosia Questionnaire in Dementia, and we also evaluated cognitive status (Mini-Mental State Examination), functional disability (Disability Assessment in Dementia), and the presence of BPSD (Neuropsychiatric Inventory). Multinomial logistic regression was used to determine the variables associated with the incidence, persistence and remission of anosognosia. The prevalence of anosognosia was 39.5% (95% CI = 32.1-47.1) at baseline. At 12 months, incidence was 38.3% (95% CI = 28.6-48.0), persistence was 80.0% (95% CI = 69.9-90.1) and remission was 20.0% (95% CI = 9.9-30.1). The regression model identified lower age, more education, and the presence of delusions as variables associated with incidence, and more education, lower instrumental DAD score, and disinhibition as variables associated with persistence. No variables were associated with remission (n = 14). The presence of anosognosia in AD patients is high. Education and certain neuropsychiatric symptoms may explain a greater and earlier incidence of anosognosia. However, anosognosia also increases with greater cognitive impairment and disease severity.
Keywords: Age Factors; Aged; Agnosia; Alzheimer Disease; Disability Evaluation; Disease Progression; Educational Status; Female; Follow-Up Studies; Humans; Incidence; Logistic Models; Longitudinal Studies; Male; Mental Status Schedule; Neuropsychological Tests; Prevalence; Prospective Studies; Risk Factors; Severity of Illness Index

Describing the Sequence of Cognitive Decline in Alzheimer's Disease Patients: Results from an Observational Study. - Henneges, Carsten; Reed, Catherine; Chen, Yun-Fei; Dell'Agnello, Grazia; Lebrec, Jeremie (J Alzheimers Dis, 2016)
BACKGROUND: Improved understanding of the pattern of cognitive decline in Alzheimer's disease (AD) would be useful to assist primary care physicians in explaining AD progression to patients and caregivers. OBJECTIVE: To identify the sequence in which cognitive abilities decline in community-dwelling patients with AD. METHODS: Baseline data were analyzed from 1,495 patients diagnosed with probable AD and a Mini-Mental State Examination (MMSE) score ≤ 26 enrolled in the 18-month observational GERAS study. Proportional odds logistic regression models were applied to model MMSE subscores (orientation, registration, attention and concentration, recall, language, and drawing) and the corresponding subscores of the cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog), using MMSE total score as the index of disease progression. Probabilities of impairment start and full impairment were estimated at each MMSE total score level. RESULTS: From the estimated probabilities for each MMSE subscore as a function of the MMSE total score, the first aspect of cognition to start being impaired was recall, followed by orientation in time, attention and concentration, orientation in place, language, drawing, and registration. For full impairment in subscores, the sequence was recall, drawing, attention and concentration, orientation in time, orientation in place, registration, and language. The sequence of cognitive decline for the corresponding ADAS-cog subscores was remarkably consistent with this pattern. CONCLUSION: The sequence of cognitive decline in AD can be visualized in an animation using probability estimates for key aspects of cognition. This might be useful for clinicians to set expectations on disease progression for patients and caregivers.

Development of a Standardized Approach to Disclosing Amyloid Imaging Research Results in Mild Cognitive Impairment. - Lingler, Jennifer H; Butters, Meryl A; Gentry, Amanda L; Hu, Lu; Hunsaker, Amanda E; Klunk, William E; Mattos, Meghan K; Parker, Lisa A; Roberts, J Scott; Schulz, Richard (J Alzheimers Dis, 2016)
The increased use of PET amyloid imaging in clinical research has sparked numerous concerns about whether and how to return such research test results to study participants. Chief among these is the question of how best to disclose amyloid imaging research results to individuals who have cognitive symptoms that could impede comprehension of the information conveyed. We systematically developed and evaluated informational materials for use in pre-test counseling and post-test disclosures of amyloid imaging research results in mild cognitive impairment (MCI). Using simulated sessions, persons with MCI and their family care partners (N = 10 dyads) received fictitious but realistic information regarding brain amyloid status, followed by an explanation of how results impact Alzheimer's disease risk. Satisfaction surveys, comprehension assessments, and focus group data were analyzed to evaluate the materials developed. The majority of persons with MCI and their care partners comprehended and were highly satisfied with the information presented. Focus group data reinforced findings of high satisfaction and included 6 recommendations for practice: 1) offer pre-test counseling, 2) use clear graphics, 3) review participants' own brain images during disclosures, 4) offer take-home materials, 5) call participants post-disclosure to address emerging questions, and 6) communicate seamlessly with primary care providers. Further analysis of focus group data revealed that participants understood the limitations of amyloid imaging, but nevertheless viewed the prospect of learning one's amyloid status as valuable and empowering.
Keywords: Adult; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid; Brain; Brain Chemistry; Cognitive Dysfunction; Disclosure; Family; Female; Focus Groups; Health Communication; Humans; Male; Middle Aged; Patient Satisfaction; Pilot Projects; Positron-Emission Tomography

Diagnosing Dementia in the Clinical Setting: Can Amyloid PET Provide Additional Value Over Cerebrospinal Fluid? - Weston, Philip S J; Paterson, Ross W; Dickson, John; Barnes, Anna; Bomanji, Jamshed B; Kayani, Irfan; Lunn, Michael P; Mummery, Catherine J; Warren, Jason D; Rossor, Martin N; Fox, Nick C; Zetterberg, Henrik; et al. (J Alzheimers Dis, 2016)
Cerebrospinal fluid (CSF) measures of amyloid and tau are the first-line Alzheimer's disease biomarkers in many clinical centers. We assessed if and when the addition of amyloid PET following CSF measurements provides added diagnostic value. Twenty patients from a cognitive clinic, who had undergone detailed assessment including CSF measures, went on to have amyloid PET. The treating neurologist's working diagnosis, and degree of diagnostic certainty, was assessed both before and after the PET. Amyloid PET changed the diagnosis in 7/20 cases. Amyloid PET can provide added diagnostic value, particularly in young-onset, atypical dementias, where CSF results are borderline and diagnostic uncertainty remains.

Diagnostic Assessment and Management of Dysphagia in Patients with Alzheimer's Disease. - Boccardi, Virginia; Ruggiero, Carmelinda; Patriti, Alberto; Marano, Luigi (J Alzheimers Dis, 2016)
A growing concern in patients affected by Alzheimer's disease (AD) is dysphagia, or swallowing impairment, which leads to malnutrition, dehydration, weight loss, functional decline and fear of eating and drinking, as well as a decrease in the quality of life. Thus the diagnostic assessment of dysphagia in patients with AD is imperative to ensure that they receive effective management, avoiding complications, and reducing comorbidity and mortality in such a growing population. Dysphagia management requires a multidisciplinary approach considering that no single strategy is appropriate for all patients. However, evidence for clinical diagnostic assessment, interventions, and medical management of dysphagia in these patients are still limited: few studies are reporting the evaluation and the management among this group of patients. Here we analyzed the most recent findings in diagnostic assessment and management of swallowing impairment in patients affected by AD.
Keywords: Alzheimer Disease; Deglutition Disorders; Humans

Diet and Inflammation in Alzheimer's Disease and Related Chronic Diseases: A Review. - Gardener, Samantha L; Rainey-Smith, Stephanie R; Martins, Ralph N (J Alzheimers Dis, 2016)
Inflammation is one of the pathological features of the neurodegenerative disease, Alzheimer's disease (AD). A number of additional disorders are likewise associated with a state of chronic inflammation, including obesity, cardiovascular disease, and type-2 diabetes, which are themselves risk factors for AD. Dietary components have been shown to modify the inflammatory process at several steps of the inflammatory pathway. This review aims to evaluate the published literature on the effect of consumption of pro- or anti-inflammatory dietary constituents on the severity of both AD pathology and related chronic diseases, concentrating on the dietary constituents of flavonoids, spices, and fats. Diet-based anti-inflammatory components could lead to the development of potent novel anti-inflammatory compounds for a range of diseases. However, further work is required to fully characterize the therapeutic potential of such compounds, including gaining an understanding of dose-dependent relationships and limiting factors to effectiveness. Nutritional interventions utilizing anti-inflammatory foods may prove to be a valuable asset in not only delaying or preventing the development of age-related neurodegenerative diseases such as AD, but also treating pre-existing conditions including type-2 diabetes, cardiovascular disease, and obesity.
Keywords: Alzheimer Disease; Cardiovascular Diseases; Chronic Disease; Diet; Humans; Inflammation; Neurodegenerative Diseases

Differential Risk of Incident Alzheimer's Disease Dementia in Stable Versus Unstable Patterns of Subjective Cognitive Decline. - Wolfsgruber, Steffen; Kleineidam, Luca; Wagner, Michael; Mösch, Edelgard; Bickel, Horst; Lϋhmann, Dagmar; Ernst, Annette; Wiese, Birgitt; Steinmann, Susanne; König, Hans-Helmut; Brettschneider, Christian; Luck, Tobias; et al. (J Alzheimers Dis, 2016)
BACKGROUND: It is unknown whether longitudinal stability versus instability in subjective cognitive decline (SCD) is a modifying factor of the association between SCD and risk of incident Alzheimer's disease (AD) dementia. OBJECTIVE: We tested the modifying role of temporal stability of the SCD report on AD dementia risk in cognitively normal elderly individuals. METHODS: We analyzed data of 1,990 cognitively normal participants from the longitudinal AgeCoDe Study. We assessed SCD with/without associated worries both at baseline and first follow-up 18 months later. Participants were then classified either as (a) Controls (CO, with no SCD at both baseline and follow-up 1, n = 613), (b) inconsistent SCD (with SCD reported only at baseline or at follow-up 1, n = 637), (c) consistent SCD but without/or with inconsistent worries (n = 610) or (d) consistent SCD with worries (n = 130). We estimated incident AD dementia risk over up to 6 years for each group with Cox-Proportional Hazard Regression analyses adjusted for age, gender, education, ApoE4 status, and depression. RESULTS: Compared to CO, inconsistent SCD was not associated with increased risk of incident AD dementia. In contrast, risk was doubled in the group of consistent SCD without/ with inconsistent worries, and almost 4-fold in the group of consistent SCD with worries. These results could be replicated when using follow-up 1 to follow-up 2 response patterns for group definition. CONCLUSION: These findings suggest that longitudinal stability versus instability is an important modifying factor of the association between SCD and AD dementia risk. Worrisome SCD that is also consistently reported over time is associated with greatly increased risk of AD dementia.

Direct Evidence of Internalization of Tau by Microglia In Vitro and In Vivo. - Bolós, Marta; Llorens-Martín, María; Jurado-Arjona, Jerónimo; Hernández, Félix; Rábano, Alberto; Avila, Jesús (J Alzheimers Dis, 2016)
The microtubule-associated protein (MAP) tau plays a critical role in the pathogenesis of tauopathies. Excess tau can be released into the extracellular medium in a physiological or pathological manner to be internalized by surrounding neurons-a process that contributes to the spread of this protein throughout the brain. Such spreading may correlate with the progression of the abovementioned diseases. In addition to neurons, tau can be internalized into other cells. Here we demonstrate that microglia take up tau in vitro and in vivo. In this regard, microglia from primary cultures internalized soluble (human recombinant tau42) and insoluble (homogenates derived from human AD brain) tau in vitro. Furthermore, using stereotaxic injection of tau in mice in vivo, we show that murine microglia internalize human tau. In addition, we demonstrate, for the first time, that microglia colocalize with various forms of tau in postmortem brain tissue of patients with Alzheimer's disease and non-demented control subjects. Our data reveal a potential role of microglia in the internalization of tau that might be relevant for the design of strategies to enhance the clearance of extracellular tau in neurodegenerative diseases characterized by the accumulation of this protein.
Keywords: Alzheimer Disease; Analysis of Variance; Animals; Animals, Newborn; Calcium-Binding Proteins; Cells, Cultured; Cerebral Cortex; Glial Fibrillary Acidic Protein; Hippocampus; Humans; Mice; Mice, Inbred C57BL; Microfilament Proteins; Microglia; Phosphorylation; Protein Transport; Rats; tau Proteins; Time Factors

Discovery and Subsequent Confirmation of Novel Serum Biomarkers Diagnosing Alzheimer's Disease. - Shah, Dipti Jigar; Rohlfing, Frederick; Anand, Swati; Johnson, W Evan; Alvarez, MeiHwa Tanielle Bench; Cobell, Jesse; King, Jackson; Young, Sydney A; Kauwe, John S K; Graves, Steven W (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD) remains challenging to diagnose, especially early disease. Having serum AD biomarkers would be of significant interest both in the clinical setting and in drug development efforts. OBJECTIVE: We applied a novel serum proteomic approach to interrogate the low-molecular weight proteome for serum AD biomarkers. METHODS: A discovery study used sera from 58 any-stage AD cases and 55 matched controls analyzed by capillary liquid chromatography-electrospray ionization-tandem mass spectrometry. Candidate biomarkers were statistically modeled and promising biomarkers were retested in a second, blinded confirmatory study (AD cases = 68, controls = 57). Biomarkers that replicated in the second study were modeled for the diagnosis of any-stage and very early stage AD. Further, they were chemically identified by tandem MS. RESULTS: The initial discovery study found 59 novel potential AD biomarkers. Thirteen recurred in more than one multi-marker panel. In a second, blinded, confirmatory study, these same biomarkers were retested in separate specimens. In that study, four markers validated comparing controls to patients with any-stage AD and also with very early AD. The four biomarkers with replicable ability to diagnose AD were then chemically identified. CONCLUSION: These results suggest novel serum AD diagnostic biomarkers can be found using this approach.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Case-Control Studies; Chromatography, Liquid; Female; Humans; Male; Psychiatric Status Rating Scales; Reproducibility of Results; ROC Curve; Tandem Mass Spectrometry

Diversity of Cognitive Phenotypes Associated with C9ORF72 Hexanucleotide Expansion. - Gómez-Tortosa, Estrella; Prieto-Jurczynska, Cristina; Serrano, Soledad; Franco-Macías, Emilio; Olivié, Laura; Gallego, Jesús; Guerrero-López, Rosa; Trujillo-Tiebas, María José; Ayuso, Carmen; García Ruiz, Pedro; Pérez-Pérez, Julián; Sainz, María José (J Alzheimers Dis, 2016)
For diagnostic purposes, we screened for the C9ORF72 mutation in a) 162 FTLD cases, and b) 145 cases with other diagnoses but with some frontotemporal features or manifestations previously reported in C9 carriers. Ten cases (onset 50 to 75 years) harbored the expansion: seven had FTLD syndromes (4.3% of total, 11% of familial cases), and three (2%) had a different diagnosis. All positive cases had family history of dementia, psychiatric disease, or ALS, but only 20% of families with mixed FTLD/ALS phenotypes carried the expansion. Language impairment was the most common symptom, followed by behavioral changes, memory deficits, and parkinsonism. C9ORF72 mutation has a low frequency in our dementia series and very diverse clinical manifestations.
Keywords: Adult; Age of Onset; Apolipoprotein E4; Cognition; DNA Repeat Expansion; Family; Female; Follow-Up Studies; Frontotemporal Lobar Degeneration; Genetic Association Studies; Genetic Predisposition to Disease; Genotyping Techniques; Humans; Male; Middle Aged; Prevalence; Proteins; Spain

Drivers: A Biologically Contextualized, Cross-Inferential View of the Epidemiology of Neurodegenerative Disorders. - de Pedro-Cuesta, Jesús; Martínez-Martín, Pablo; Rábano, Alberto; Alcalde-Cabero, Enrique; José García López, Fernando; Almazán-Isla, Javier; Ruiz-Tovar, María; Medrano, Maria-José; Avellanal, Fuencisla; Calero, Olga; Calero, Miguel (J Alzheimers Dis, 2016)
BACKGROUND: Sutherland et al. (2011) suggested that, instead of risk factors for single neurodegenerative disorders (NDDs), there was a need to identify specific "drivers", i.e., risk factors with impact on specific deposits, such as amyloid-β, tau, or α-synuclein, acting across entities. OBJECTIVES AND METHODS: Redefining drivers as "neither protein/gene- nor entity-specific features identifiable in the clinical and general epidemiology of conformational NDDs (CNDDs) as potential footprints of templating/spread/transfer mechanisms", we conducted an analysis of the epidemiology of ten CNDDs, searching for patterns. RESULTS: We identified seven potential drivers, each of which was shared by at least two CNDDs: 1) an age-at-exposure-related susceptibility to Creutzfeldt-Jakob disease (CJD) and several late-life CNDDs; 2) a relationship between age at onset, survival, and incidence; 3) shared genetic risk factors for CJD and late-life CNNDs; 4) partly shared personal (diagnostic, educational, behavioral, and social risk factors) predating clinical onset of late-life CNDDs; 5) two environmental risk factors, namely, surgery for sporadic CJD and amyotrophic lateral sclerosis, and Bordetella pertussis infection for Parkinson's disease; 6) reticulo-endothelial system stressors or general drivers (andropause or premenopausal estrogen deficiency, APOEɛ4, and vascular risk factors) for late-life CNDDs such as dementia/Alzheimer's disease, type-2 diabetes mellitus, and some sporadic cardiac and vascular degenerative diseases; and 7) a high, invariant incidence ratio of sporadic to genetic forms of mid- and late-life CNDDs, and type-2 diabetes mellitus. CONCLUSION: There might be a systematic epidemiologic pattern induced by specific proteins (PrP, TDP-43, SOD1, α-synuclein, amyloid-β, tau, Langerhans islet peptide, and transthyretin) or established combinations of these.
Keywords: Age Factors; Aging; Amyloid Precursor Protein Secretases; Apolipoproteins E; Aspartic Acid Endopeptidases; Creutzfeldt-Jakob Syndrome; Environment; Female; Humans; Incidence; Male; Neurodegenerative Diseases; Personality; Risk Factors; Vascular Diseases

Early in vivo Effects of the Human Mutant Amyloid-β Protein Precursor (hAβPPSwInd) on the Mouse Olfactory Bulb. - Rusznák, Zoltán; Kim, Woojin Scott; Hsiao, Jen-Hsiang T; Halliday, Glenda M; Paxinos, George; Fu, YuHong (J Alzheimers Dis, 2016)
The amyloid-β protein precursor (AβPP) has long been linked to Alzheimer's disease (AD). Using J20 mice, which express human AβPP with Swedish and Indiana mutations, we studied early pathological changes in the olfactory bulb. The presence of AβPP/amyloid-β (Aβ) was examined in mice aged 3 months (before the onset of hippocampal Aβ deposition) and over 5 months (when hippocampal Aβ deposits are present). The number of neurons, non-neurons, and proliferating cells was assessed using the isotropic fractionator method. Our results demonstrate that although AβPP is overexpressed in some of the mitral cells, widespread Aβ deposition and microglia aggregates are not prevalent in the olfactory bulb. The olfactory bulbs of the younger J20 group harbored significantly fewer neurons than those of the age-matched wild-type mice (5.57±0.13 million versus 6.59±0.36 million neurons; p = 0.011). In contrast, the number of proliferating cells was higher in the young J20 than in the wild-type group (i.e., 6617±425 versus 4455±623 cells; p = 0.011). A significant increase in neurogenic activity was also observed in the younger J20 olfactory bulb. In conclusion, our results indicate that (1) neurons participating in the mouse olfactory function overexpress AβPP; (2) the cellular composition of the young J20 olfactory bulb is different from that of wild-type littermates; (3) these differences may reflect altered neurogenic activity and/or delayed development of the J20 olfactory system; and (4) AβPP/Aβ-associated pathological changes that take place in the J20 hippocampus and olfactory bulb are not identical.
Keywords: Age Factors; Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cell Proliferation; Disease Models, Animal; Gene Expression Regulation; Humans; Ki-67 Antigen; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Nerve Tissue Proteins; Neurogenesis; Neurons; Olfactory Bulb; Piriform Cortex

Early Postmenopausal Transdermal 17β-Estradiol Therapy and Amyloid-β Deposition. - Kantarci, Kejal; Lowe, Val J; Lesnick, Timothy G; Tosakulwong, Nirubol; Bailey, Kent R; Fields, Julie A; Shuster, Lynne T; Zuk, Samantha M; Senjem, Matthew L; Mielke, Michelle M; Gleason, Carey; Jack, Clifford R; et al. (J Alzheimers Dis, 2016)
BACKGROUND: It remains controversial whether hormone therapy in recently postmenopausal women modifies the risk of Alzheimer's disease (AD). OBJECTIVE: To investigate the effects of hormone therapy on amyloid-β deposition in recently postmenopausal women. METHODS: Participants within 5-36 months past menopause in the Kronos Early Estrogen Prevention Study, a randomized, double blinded placebo-controlled clinical trial, were randomized to: 1) 0.45 mg/day oral conjugated equine estrogens (CEE); 2) 50μg/day transdermal 17β-estradiol; or 3) placebo pills and patch for four years. Oral progesterone (200 mg/day) was given to active treatment groups for 12 days each month. 11C Pittsburgh compound B (PiB) PET imaging was performed in 68 of the 118 participants at Mayo Clinic approximately seven years post randomization and three years after stopping randomized treatment. PiB Standard unit value ratio (SUVR) was calculated. RESULTS: Women (age = 52-65) randomized to transdermal 17β-estradiol (n = 21) had lower PiB SUVR compared to placebo (n = 30) after adjusting for age [odds ratio (95% CI) = 0.31(0.11-0.83)]. In the APOEɛ4 carriers, transdermal 17β-estradiol treated women (n = 10) had lower PiB SUVR compared to either placebo (n = 5) [odds ratio (95% CI) = 0.04(0.004-0.44)], or the oral CEE treated group (n = 3) [odds ratio (95% CI) = 0.01(0.0006-0.23)] after adjusting for age. Hormone therapy was not associated with PiB SUVR in the APOEɛ4 non-carriers. CONCLUSION: In this pilot study, transdermal 17β-estradiol therapy in recently postmenopausal women was associated with a reduced amyloid-β deposition, particularly in APOEɛ4 carriers. This finding may have important implications for the prevention of AD in postmenopausal women, and needs to be confirmed in a larger sample.

Early-Life Exposure to Lead (Pb) Alters the Expression of microRNA that Target Proteins Associated with Alzheimer's Disease. - Masoud, Anwar M; Bihaqi, Syed W; Machan, Jason T; Zawia, Nasser H; Renehan, William E (J Alzheimers Dis, 2016)
There is a growing recognition of the impact of environmental toxins on the epigenetic regulation of gene expression, including the genes that play a critical role in neural development, neural function, and neurodegeneration. We have shown previously that exposure to the heavy metal lead (Pb) in early life results in a latent over-expression of AD-related proteins in rodents and primates. The present study provides evidence that early postnatal exposure to Pb also alters the expression of select miRNA. Mice were exposed to 0.2% Pb acetate from Postnatal Day 1 (PND 1, first 24 h after birth) to PND 20 via their mother's milk. Brain tissue was harvested at PND 20, 180, or 700, and miRNA were isolated and quantified by qPCR. This exposure produced a transient increase (relative to control) in the expression of miR-106b (binds to AβPP mRNA), miR-29b (targets the mRNA for the transcription factor SP1) and two miRNAs (miR-29b and miR-132) that have the ability to inhibit translation of proteins involved in promoter methylation. The expression of miR-106b decreased over time in the Pb-exposed animals and was significantly less than the levels exhibited by the control animals at PND700. The level of miR-124, which binds to SP1 mRNA, was also reduced (relative to controls) at PND700. In summary, we show that exposure to the heavy metal Pb in early life has a significant impact on the short- and long-term expression of miRNA that target epigenetic mediators and neurotoxic proteins.
Keywords: Age Factors; Amyloid beta-Protein Precursor; Animals; Animals, Newborn; Disease Models, Animal; Dose-Response Relationship, Drug; Female; Gene Expression Regulation, Developmental; Lead; Male; Mice; Mice, Inbred C57BL; MicroRNAs; Pregnancy; RNA, Messenger; Sp1 Transcription Factor

Effect of Early Referral to Specialist in Dementia on Institutionalization and Functional Decline: Findings from a Population-Based Study. - Pimouguet, Clément; Le-Goff, Mélanie; Rizzuto, Debora; Berr, Claudine; Leffondré, Karen; Pérès, Karine; Dartigues, Jean François; Helmer, Catherine (J Alzheimers Dis, 2016)
BACKGROUND: Although early diagnosis has been hypothesized to benefit both patients and caregivers, until now studies evaluating the effect of early dementia diagnosis are lacking. OBJECTIVE: To investigate the influence of early specialist referral for dementia on the risk of institutionalization and functional decline in Activity of Daily Living (ADL). METHODS: Incident dementia cases were screened in a prospective population-based cohort, the Three-City Study, and initial specialist consultation for cognitive complaint was assessed at dementia diagnosis. Proportional hazard regression and illness-death models were used to test the association between specialist referral and, respectively, institutionalization and functional decline. RESULTS: Only one third of the incident individuals with dementia had consulted a specialist for cognitive problems early (36%). After adjustment on potential confounders (including cognitive and functional decline) and competing risk of death, participants who had consulted a specialist early in the disease course presented a higher rate of being institutionalized than those who did not (Hazard Ratio = 2.00, 95% Confidence Interval (CI): 1.09- 3.64). But early specialist referral was not associated with further functional decline (HR = 1.09, 95% CI: 0.71- 1.67). CONCLUSIONS: Early specialist referral in dementia is associated with increased risk of institutionalization but not with functional decline in ADL. These findings suggest that early care referral in dementia may be a marker of concern for patients and/or caregivers; subsequent medical and social care could be suboptimal or inappropriate to allow patients to stay longer at home.
Keywords: Activities of Daily Living; Cognition Disorders; Community Health Planning; Dementia; Disability Evaluation; Female; Finland; Follow-Up Studies; Humans; Institutionalization; Male; Psychiatric Status Rating Scales; Referral and Consultation; Specialization

Effect of Normal Aging and of Mild Cognitive Impairment on Event-Related Potentials to a Stroop Color-Word Task. - Ramos-Goicoa, Marta; Galdo-Álvarez, Santiago; Díaz, Fernando; Zurrón, Montserrat (J Alzheimers Dis, 2016)
Event-related potentials (ERPs) were recorded from 84 adults (51 to 87 years old) with the aim of exploring the effects of aging (middle-aged and older groups) and cognitive status (healthy or with amnestic mild cognitive impairment, aMCI) on the neural functioning associated with stimulus and response processing in a Stroop color-word task. An interference (or Stroop) effect was observed in the Reaction Time (RT), and the RT and number of errors results were consistent with the age-related decline in performance. Cognitive status did not affect the behavioral performance of the task, but age and cognitive status affected several ERP parameters. Aging was associated with a) slowing of the neural processing of the stimuli (P150, N2, and P3b latencies were longer), b) greater activation of the motor cortex for response preparation (LRP-R amplitude was larger), and c) use of more neural resources for cognitive control of stimuli (N2 amplitude was larger to the congruent and incongruent stimuli than to the colored X-strings, in the older group). Independent of age, aMCI dedicated more neural resources to processing the irrelevant dimension of the stimulus (they showed a greater difference than the control participants between the P3b amplitude to the colored X-strings and to the congruent/incongruent stimuli) and showed a deficit in the selection and preparation of the motor response (with smaller LRP-S and LRP-R amplitudes). Furthermore, the middle-aged aMCI participants evaluated and classified both congruent and incongruent stimuli more slowly (they showed longer P3b latencies) relative to middle-aged controls.

Efficacy and Safety of ABT-126 in Subjects with Mild-to-Moderate Alzheimer's Disease on Stable Doses of Acetylcholinesterase Inhibitors: A Randomized, Double-Blind, Placebo-Controlled Study. - Florian, Hana; Meier, Andreas; Gauthier, Serge; Lipschitz, Stanley; Lin, Yunzhi; Tang, Qi; Othman, Ahmed A; Robieson, Weining Z; Gault, Laura M (J Alzheimers Dis, 2016)
BACKGROUND: ABT-126 is a potent, selective α7 nicotinic acetylcholine receptor agonist with putative procognitive effects as a monotherapy in treating Alzheimer's disease (AD). OBJECTIVE: This randomized, double-blind, placebo-controlled multicenter study (NCT01549834) investigated the efficacy and safety of ABT-126 in subjects with mild-to-moderate AD who were taking stable doses of acetylcholinesterase inhibitors (AChEIs). METHODS: Subjects received 25 mg ABT-126 (n = 143), 75 mg ABT-126 (n = 145), or placebo (n = 146) once daily for 24 weeks. Subjects who completed the 24-week double-blind study were eligible to enroll in a 28-week open-label extension study (NCT01690195) and received 75 mg ABT-126 daily. The primary efficacy endpoint was the change from baseline to week 24 in the 11-item total score of the Alzheimer's Disease Assessment Scale- Cognitive Subscale (ADAS-Cog). RESULTS: Neither dose of ABT-126 demonstrated significant improvement compared with placebo in the primary efficacy endpoint. However, 25 mg ABT-126 demonstrated significant improvement compared with placebo in ADAS-Cog scores at week 4 (least squares mean difference, -1.21; standard error, 0.51; p <  0.010, one-sided); 75 mg ABT-126 did not demonstrate significant improvements in ADAS-Cog scores compared with placebo at any time point. A treatment effect was not observed for any secondary efficacy measures of cognition, function, or global improvement. ABT-126 was generally well tolerated; the most common adverse events were agitation, constipation, diarrhea, fall, and headache. CONCLUSIONS: Overall, the efficacy profile of ABT-126 did not warrant further development as add-on therapy to AChEIs to treat mild-to-moderate AD.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cholinesterase Inhibitors; Disease Progression; Dose-Response Relationship, Drug; Double-Blind Method; Female; Humans; Indans; International Cooperation; Male; Medication Adherence; Middle Aged; Piperidines; Psychiatric Status Rating Scales; Treatment Outcome

Evaluation of a Genetic Risk Score to Improve Risk Prediction for Alzheimer's Disease. - Chouraki, Vincent; Reitz, Christiane; Maury, Fleur; Bis, Joshua C; Bellenguez, Celine; Yu, Lei; Jakobsdottir, Johanna; Mukherjee, Shubhabrata; Adams, Hieab H; Choi, Seung Hoan; Larson, Eric B; Fitzpatrick, Annette; et al. (J Alzheimers Dis, 2016)
Effective prevention of Alzheimer's disease (AD) requires the development of risk prediction tools permitting preclinical intervention. We constructed a genetic risk score (GRS) comprising common genetic variants associated with AD, evaluated its association with incident AD and assessed its capacity to improve risk prediction over traditional models based on age, sex, education, and APOEɛ4. In eight prospective cohorts included in the International Genomics of Alzheimer's Project (IGAP), we derived weighted sum of risk alleles from the 19 top SNPs reported by the IGAP GWAS in participants aged 65 and older without prevalent dementia. Hazard ratios (HR) of incident AD were estimated in Cox models. Improvement in risk prediction was measured by the difference in C-index (Δ-C), the integrated discrimination improvement (IDI) and continuous net reclassification improvement (NRI>0). Overall, 19,687 participants at risk were included, of whom 2,782 developed AD. The GRS was associated with a 17% increase in AD risk (pooled HR = 1.17; 95% CI =   [1.13-1.21] per standard deviation increase in GRS; p-value =  2.86×10-16). This association was stronger among persons with at least one APOEɛ4 allele (HRGRS = 1.24; 95% CI =   [1.15-1.34]) than in others (HRGRS = 1.13; 95% CI =   [1.08-1.18]; pinteraction = 3.45×10-2). Risk prediction after seven years of follow-up showed a small improvement when adding the GRS to age, sex, APOEɛ4, and education (Δ-Cindex =  0.0043 [0.0019-0.0067]). Similar patterns were observed for IDI and NRI>0. In conclusion, a risk score incorporating common genetic variation outside the APOEɛ4 locus improved AD risk prediction and may facilitate risk stratification for prevention trials.

Evolution of the Antidepressant Prescribing in Alzheimer's Disease and Related Disorders Between 2010 and 2014: Results from the French National Database on Alzheimer's Disease (BNA). - David, Renaud; Manera, Valeria; Fabre, Roxane; Pradier, Christian; Robert, Philippe; Tifratene, Karim (J Alzheimers Dis, 2016)
BACKGROUND: Safety warnings from health authorities are currently intended to limit the use of psychotropic agents in dementia-related conditions. Evidence concerning the use of antidepressants in dementia is, however, scarce and contradictory. OBJECTIVE: To evaluate antidepressant use among individuals with Alzheimer's disease (AD) and related disorders in the French population between 2010 and 2014. METHOD: Antidepressant prescriptions in individuals with AD, mixed dementia (MD), and vascular dementia (VaD) in the French National Alzheimer Database between 2010 and 2014 were analyzed (N = 199,544). RESULTS: Multivariate analysis showed an annual significant increase (p < 0.001) in the prescription rate of antidepressants from 26% (2010) to 31% (2014), and identified female gender, younger age, higher education, living in long-term facilities, more severe cognitive decline, and presence of vascular signs (VaD and MD) as associated factors for antidepressant prescribing. CONCLUSION: The annual increase of antidepressant prescribing among individuals with AD, MD, and VaD in French specialized settings may be partially related to the lack of current valuable medications for dementia-related behavioral symptoms.

Excess Costs Associated with Possible Misdiagnosis of Alzheimer's Disease Among Patients with Vascular Dementia in a UK CPRD Population. - Happich, Michael; Kirson, Noam Y; Desai, Urvi; King, Sarah; Birnbaum, Howard G; Reed, Catherine; Belger, Mark; Lenox-Smith, Alan; Price, David (J Alzheimers Dis, 2016)
BACKGROUND: Prior diagnosis of Alzheimer's disease (AD) among patients later diagnosed with vascular dementia (VaD) has been associated with excess costs, suggesting potential benefits of earlier rule-out of AD diagnosis. OBJECTIVE: To investigate whether prior diagnosis with AD among patients with VaD is associated with excess costs in the UK. METHODS: Patients with a final VaD diagnosis, continuous data visibility for≥6 months prior to index date, and linkage to Hospital Episode Statistics data were retrospectively selected from de-identified Clinical Practice Research Datalink data. Patients with AD diagnosis before a final VaD diagnosis were matched to similar patients with no prior AD diagnosis using propensity score methods. Annual excess healthcare costs were calculated for 5 years post-index, stratified by time to final diagnosis. RESULTS: Of 9,311 patients with VaD, 508 (6%) had prior AD diagnosis with a median time to VaD diagnosis exceeding 2 years from index date. Over the entire follow-up period, patients with prior AD diagnosis had accumulated healthcare costs that were approximately GBP2,000 higher than those for matched counterparts (mostly due to higher hospitalization costs). Cost differentials peaked particularly in the period including the final VaD diagnosis, with excess costs quickly declining thereafter. CONCLUSION: Potential misdiagnosis of AD among UK patients with VaD resulted in substantial excess costs. The decline in excess costs following a final VaD diagnosis suggests potential benefits from earlier rule-out of AD.

Exercise Plus Cognitive Performance Over and Above Exercise Alone in Subjects with Mild Cognitive Impairment. - Sacco, Guillaume; Caillaud, Corinne; Ben Sadoun, Gregory; Robert, Philippe; David, Renaud; Brisswalter, Jeanick (J Alzheimers Dis, 2016)
BACKGROUND: Epidemiological studies highlight the relevance of regular exercise interventions to enhance or maintain neurocognitive function in subjects with cognitive impairments. OBJECTIVES: The aim of this study was to ascertain the effect of aerobic exercise associated with cognitive enrichment on cognitive performance in subjects with mild cognitive impairment (MCI). METHOD: Eight participants with MCI (72 ± 2 years) were enrolled in a 9-month study that consisted of two 3-months experimental interventions separated by a training cessation period of 3 months. The interventions included either aerobic exercise alone or aerobic exercise combined with cognitive enrichment. The exercise program involved two 20-min cycling exercise bouts per week at an intensity corresponding to 60% of the heart rate reserve. Cognitive performance was assessed using a task of single reaction time (SRT) and an inhibition task (Go-no-Go) before, immediately after, and 1 month after each intervention. RESULTS: The exercise intervention improved the speed of responses during the Go-no-Go task without any increase in errors. This improvement was enhanced by cognitive enrichment (6 ± 1% ; p >  0.05), when compared with exercise alone (4 ± 0.5% ,). Following exercise cessation, this positive effect disappeared. No effect was observed on SRT performance. CONCLUSION: Regular aerobic exercise improved cognitive performance in MCI subjects and the addition of cognitive tasks during exercise potentiated this effect. However, the influence of aerobic exercise on cognitive performance did not persist after cessation of training. Studies involving a larger number of subjects are necessary to confirm these results.
Keywords: Aged; Analysis of Variance; Cognitive Dysfunction; Cognitive Therapy; Exercise; Exercise Therapy; Female; Humans; Inhibition (Psychology); Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Reaction Time; Retrospective Studies; Treatment Outcome

Expression of Tau Produces Aberrant Plasma Membrane Blebbing in Glial Cells Through RhoA-ROCK-Dependent F-Actin Remodeling. - Torres-Cruz, Francisco M; Rodríguez-Cruz, Fanny; Escobar-Herrera, Jaime; Barragán-Andrade, Norma; Basurto-Islas, Gustavo; Ripova, Daniela; Avila, Jesús; Garcia-Sierra, Francisco (J Alzheimers Dis, 2016)
Abnormal aggregation of Tau in glial cells has been reported in Alzheimer's disease (AD) and other tauopathies; however, the pathological significance of these aggregates remains unsolved to date. In this study, we evaluated whether full-length Tau (Tau441) and its aspartic acid421-truncated Tau variant (Tau421) produce alterations in the normal organization of the cytoskeleton and plasma membrane (PM) when transiently expressed in cultured C6-glial cells. Forty-eight hours post-transfection, abnormal microtubule bundling was observed in the majority of the cells, which expressed either Tau441 or Tau421. Moreover, both variants of Tau produced extensive PM blebbing associated with cortical redistribution of filamentous actin (F-Actin). These effects were reverted when Tau-expressing cells were incubated with drugs that depolymerize F-Actin. In addition, when glial cells showing Tau-induced PM blebbing were incubated with inhibitors of the Rho-associated protein kinase (ROCK) signaling pathway, both formation of abnormal PM blebs and F-Actin remodeling were avoided. All of these effects were initiated upstream by abnormal Tau-induced microtubule bundling, which may release the microtubule-bound guanine nucleotide exchange factor-H1 (GEF-H1) into the cytoplasm in order to activate its major effector RhoA-GTPase. These results may represent a new mechanism of Tau toxicity in which Tau-induced microtubule bundling produces activation of the Rho-GTPase-ROCK pathway that in turn mediates the remodeling of cortical Actin and PM blebbing. In AD and other tauopathies, these Tau-induced abnormalities may occur and contribute to the impairment of glial activity.

Familial Presenilin Mutations and Sporadic Alzheimer's Disease Pathology: Is the Assumption of Biochemical Equivalence Justified? - Roher, Alex E; Maarouf, Chera L; Kokjohn, Tyler A (J Alzheimers Dis, 2016)
Studies of presenilin (PSEN) gene mutations producing early onset Alzheimer's disease (AD) have helped elucidate the pathogenic mechanisms of dementia and guided clinical trials of potential therapeutic interventions. Although familial and sporadic forms of AD share features, it is unclear if the two are precisely equivalent. In addition, PSEN mutations do not all produce a single phenotype, but exhibit substantial variability in clinical manifestations, which are related to the position and chemical nature of their amino acid substitutions as well as ratios of critical molecules such as Aβ40 and Aβ42. These differences complicate the interpretation of critical clinical trial results and their desired extrapolation to sporadic AD treatment. In this perspective, we examine differences between familial AD and sporadic AD as well as attributes shared by these uniquely arising disturbances in brain biochemical homeostasis that culminate in dementia.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Brain; Humans; Mutation; Presenilins

FDG-PET and Neuropsychiatric Symptoms among Cognitively Normal Elderly Persons: The Mayo Clinic Study of Aging. - Krell-Roesch, Janina; Ruider, Hanna; Lowe, Val J; Stokin, Gorazd B; Pink, Anna; Roberts, Rosebud O; Mielke, Michelle M; Knopman, David S; Christianson, Teresa J; Machulda, Mary M; Jack, Clifford R; Petersen, Ronald C; et al. (J Alzheimers Dis, 2016)
One of the key research agenda of the field of aging is investigation of presymptomatic Alzheimer's disease (AD). Furthermore, abnormalities in brain glucose metabolism (as measured by FDG-PET) have been reported among cognitively normal elderly persons. However, little is known about the association of FDG-PET abnormalities with neuropsychiatric symptoms (NPS) in a population-based setting. Thus, we conducted a cross-sectional study derived from the ongoing population-based Mayo Clinic Study of Aging in order to examine the association between brain glucose metabolism and NPS among cognitively normal (CN) persons aged > 70 years. Participants underwent FDG-PET and completed the Neuropsychiatric Inventory Questionnaire (NPI-Q), Beck Depression Inventory (BDI), and Beck Anxiety Inventory (BAI). Cognitive classification was made by an expert consensus panel. We conducted multivariable logistic regression analyses to compute odds ratios (OR) and 95% confidence intervals after adjusting for age, sex, and education. For continuous variables, we used linear regression and Spearman rank-order correlations. Of 668 CN participants (median 78.1 years, 55.4% males), 205 had an abnormal FDG-PET (i.e., standardized uptake value ratio < 1.32 in AD-related regions). Abnormal FDG-PET was associated with depression as measured by NPI-Q (OR = 2.12; 1.23-3.64); the point estimate was further elevated for APOE ɛ4 carriers (OR = 2.59; 1.00-6.69), though marginally significant. Additionally, we observed a significant association between abnormal FDG-PET and depressive and anxiety symptoms when treated as continuous measures. These findings indicate that NPS, even in community-based samples, can be an important additional tool to the biomarker-based investigation of presymptomatic AD.

First Symptoms and Neurocognitive Correlates of Behavioral Variant Frontotemporal Dementia. - Santamaría-García, Hernando; Reyes, Pablo; García, Adolfo; Baez, Sandra; Martinez, Angela; Santacruz, José Manuel; Slachevsky, Andrea; Sigman, Mariano; Matallana, Diana; Ibáñez, Agustín (J Alzheimers Dis, 2016)
BACKGROUND: Previous works highlight the neurocognitive differences between apathetic and disinhibited clinical presentations of the behavioral variant frontotemporal dementia (bvFTD). However, little is known regarding how the early presentation (i.e., first symptom) is associated to the neurocognitive correlates of the disease's clinical presentation at future stages of disease. OBJECTIVES: We analyzed the neurocognitive correlates of patients with bvFTD who debuted with apathy or disinhibition as first symptom of disease. METHODS: We evaluated the neuropsychological, clinical, and neuroanatomical (3T structural images) correlates in a group of healthy controls (n = 30) and two groups of bvFTD patients (presented with apathy [AbvFTD, n = 18] or disinhibition [DbvFTD, n = 16]). To differentiate groups according to first symptoms, we used multivariate analyses. RESULTS: The first symptom in patients described the evolution of the disease. AbvFTD and DbvFTD patients showed increased brain atrophy and increased levels of disinhibition and apathy, respectively. Whole brain analyzes in AbvFTD revealed atrophy in the frontal, insular, and temporal areas. DbvFTD, in turn, presented atrophy in the prefrontal regions, temporoparietal junction, insula, and temporoparietal region. Increased atrophy in DbvFTD patients (compared to AbvFTD) was observed in frontotemporal regions. Multivariate analyses confirmed that a set of brain areas including right orbitofrontal, right dorsolateral prefrontal, and left caudate were enough to distinguish the patients' subgroups.∥Conclusion: First symptom in bvFTD patients described the neurocognitive impairments after around three years of disease, playing an important role in the early detection, disease tracking, and neuroanatomical specification of bvFTD, as well as in future research on potential disease-modifying treatments.

Fluoxetine Treatment Induces Seizure Behavior and Premature Death in APPswe/PS1dE9 Mice. - Sierksma, Annerieke S R; de Nijs, Laurence; Hoogland, Govert; Vanmierlo, Tim; van Leeuwen, Fred W; Rutten, Bart P F; Steinbusch, Harry W M; Prickaerts, Jos; van den Hove, Daniel L A (J Alzheimers Dis, 2016)
Treatment of Alzheimer's disease (AD) patients with the antidepressant fluoxetine is known to improve memory and cognitive function. However, the mechanisms underlying these effects are largely unknown. To unravel these mechanisms, we aimed to treat APPswe/PS1dE9 mice with fluoxetine. Unexpectedly, with time, an increased number of animals displayed seizure behavior and died. Although spontaneous behavioral seizures have been reported previously in this mouse model, the observation of seizures and death consequential to fluoxetine treatment is new. Our results warrant further research on the underlying mechanisms as this may refine the treatment of AD patients.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Anticonvulsants; Body Weight; Disease Models, Animal; Fluoxetine; Humans; Logistic Models; Male; Mice, Inbred C57BL; Mice, Transgenic; Neuroprotective Agents; Presenilin-1; Seizures

Future Dementia Severity is Almost Entirely Explained by the Latent Variable δ's Intercept and Slope. - Palmer, Raymond F; Royall, Donald R (J Alzheimers Dis, 2016)
BACKGROUND: Structural equation models (SEM) can explicitly distinguish dementia-relevant variance in cognitive task performance. The resulting latent construct "δ" (for dementia) provides a relatively "error free" continuously varying dementia-specific phenotype. OBJECTIVE: To estimate δ's change over time (Δδ) and determine Δδ's predictive validity using future dementia status as an outcome. METHODS: Data from n = 2,191 participants of the Texas Alzheimer's Research and Care Consortium (TARCC) were used to construct a latent growth curve model of longitudinal change over four years using five cognitive measures and one measure of Instrumental Activities of Daily Living. Four final latent factors, including baseline δ and Δδ, were simultaneously entered as predictors of wave 4 dementia severity, as estimated by the Clinical Dementia Rating Scale "sum of boxes" (CDR). RESULTS: All observed measures exhibited significant change [χ2 = 1,152 (df = 229); CFI = 0.968; RMSEA = 0.043]. The final model demonstrated excellent fit to the data [χ2 = 543 (df = 245); CFI = 0.991; RMSEA = 0.023]. All latent indicator loadings were significant, yielding four distinct factors. After adjustment for demographic covariates and baseline CDR scores, d and Δd were significantly independently associated with CDR4, explaining 25% and 49% of its variance, respectively. The latent variable g' significantly explained 3% of CDR4 variance independently of d and Δd. Δg' was not significantly associated with CDR4. Baseline CDR explained 16% of CDR4 variance. CONCLUSIONS: Future dementia severity is almost entirely explained by the latent construct δ's intercept and slope.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Cognitive Dysfunction; Factor Analysis, Statistical; Female; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Psychiatric Status Rating Scales

Genetic Counseling and Testing for Alzheimer's Disease and Frontotemporal Lobar Degeneration: An Italian Consensus Protocol. - Bocchetta, Martina; Mega, Anna; Bernardi, Livia; Di Maria, Emilio; Benussi, Luisa; Binetti, Giuliano; Borroni, Barbara; Colao, Rosanna; Di Fede, Giuseppe; Fostinelli, Silvia; Galimberti, Daniela; Gennarelli, Massimo; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Genetic testing of familial Alzheimer's disease (AD) and frontotemporal lobar degeneration (FTLD) is attracting interest thanks to innovative primary prevention clinical trials and increased request for information by at-risk individuals. However, ethical, social, and psychological implications are paramount and genetic testing must be supported by structured genetic counseling. In Italy, practice parameters and guidelines for genetic counseling in dementia are not available. OBJECTIVE: To develop a nationally harmonized protocol for genetic counseling and testing of familial AD and FTLD. METHODS: Activities were carried out in the context of the Italian Dominantly Inherited Alzheimer's and Frontotemporal Network (IT-DIAfN) project, a national network of centers of excellence with expertise in managing patients with familial AD and FTLD. A survey of the literature on genetic counseling protocols and guidelines was conducted. Local protocols for genetic counseling were surveyed. Differences and commonalities among protocols were identified and discussed among project partners. Consensus was reached following implicit aggregation methods. RESULTS: Consensus was reached on a protocol for patients with clinically diagnosed familial AD or FTLD and a distinct protocol for their at-risk relatives. Genetic counseling should be provided by a multidisciplinary team including a geneticist, a neurologist/geriatrician, and a psychologist/psychiatrist, according to the following schedule: (i) initial consultation with tailored information on the genetics of the dementias; (ii) clinical, psychological, and cognitive assessment; if deemed appropriate (iii) genetic testing following a structured decision tree for gene mutation search; (iv) genetic testing result disclosure; (v) psychological support follow-up. CONCLUSION: This genetic counseling protocol provides Italian centers with a line of shared practice for dealing with the requests for genetic testing for familial AD and FTLD from patients and at-risk relatives, who may also be eligible participants for novel prevention clinical trials.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Consensus; Female; Follow-Up Studies; Frontotemporal Lobar Degeneration; Genetic Counseling; Genetic Testing; Humans; Italy; Male; Peptide Fragments; Psychiatric Status Rating Scales

Genetic Influences on Plasma Homocysteine Levels in African Americans and Yoruba Nigerians. - Kim, Sungeun; Nho, Kwangsik; Ramanan, Vijay K; Lai, Dongbing; Foroud, Tatiana M; Lane, Katie; Murrell, Jill R; Gao, Sujuan; Hall, Kathleen S; Unverzagt, Frederick W; Baiyewu, Olusegun; Ogunniyi, Adesola; et al. (J Alzheimers Dis, 2016)
Plasma homocysteine, a metabolite involved in key cellular methylation processes seems to be implicated in cognitive functions and cardiovascular health with its high levels representing a potential modifiable risk factor for Alzheimer's disease (AD) and other dementias. A better understanding of the genetic factors regulating homocysteine levels, particularly in non-white populations, may help in risk stratification analyses of existing clinical trials and may point to novel targets for homocysteine-lowering therapy. To identify genetic influences on plasma homocysteine levels in individuals with African ancestry, we performed a targeted gene and pathway-based analysis using a priori biological information and then to identify new association performed a genome-wide association study. All analyses used combined data from the African American and Yoruba cohorts from the Indianapolis-Ibadan Dementia Project. Targeted analyses demonstrated significant associations of homocysteine and variants within the CBS (Cystathionine beta-Synthase) gene. We identified a novel genome-wide significant association of the AD risk gene CD2AP (CD2-associated protein) with plasma homocysteine levels in both cohorts. Minor allele (T) carriers of identified CD2AP variant (rs6940729) exhibited decreased homocysteine level. Pathway enrichment analysis identified several interesting pathways including the GABA receptor activation pathway. This is noteworthy given the known antagonistic effect of homocysteine on GABA receptors. These findings identify several new targets warranting further investigation in relation to the role of homocysteine in neurodegeneration.
Keywords: Adaptor Proteins, Signal Transducing; African Americans; African Continental Ancestry Group; Aged; Aged, 80 and over; Cohort Studies; Cystathionine beta-Synthase; Cytoskeletal Proteins; Female; Genetic Variation; Genome-Wide Association Study; Heterozygote; Homocysteine; Humans; Indiana; Longitudinal Studies; Male; Nigeria; Prospective Studies

The Genetic Variability of UCP4 Affects the Individual Susceptibility to Late-Onset Alzheimer's Disease and Modifies the Disease's Risk in APOE-ɛ4 Carriers. - Montesanto, Alberto; Crocco, Paolina; Anfossi, Maria; Smirne, Nicoletta; Puccio, Gianfranco; Colao, Rosanna; Maletta, Raffaele; Passarino, Giuseppe; Bruni, Amalia C; Rose, Giuseppina (J Alzheimers Dis, 2016)
Uncoupling proteins (UCPs) are a group of five mitochondrial inner membrane transporters with a tissue specific expression that uncouple biofuel oxidation from ATP synthesis and function as regulators of energy homeostasis and antioxidants. Previous data suggested that neuronal UCPs (UCP2, UCP4, and UCP5) can directly influence synaptic plasticity, neurotransmission, and neurodegenerative processes, and have a crucial role in the function and protection of the central nervous system. In fact, it has been observed that the expression of neuronal UCPs significantly decreases in Alzheimer's disease (AD) patients. Here we analyzed the variability of UCP2, -3, -4, and 5 genes in sporadic and familial cases (n = 465) of late-onset AD (LOAD) with respect to healthy controls (n = 442). We showed that a genetic variant in the human UCP4, rs9472817, not only significantly affects the individual susceptibility to LOAD, but also modulates the effect of APOE-ɛ4 on AD risk. In fact, rs9472817-C allele was significantly more frequent in both groups of patients with respect to the control group (p = 6.934*10-4 for familial and p = 1.033*10-3 for sporadic cases). In addition, gene-gene interaction analysis revealed that the effect of APOE-ɛ4 allele on LOAD risk was doubled in homozygote CC subjects; conversely, the risk conferred by the APOE-ɛ4 allele was annulled in subjects with two copies of the G allele. Our findings are further evidence that the efficiency in mitochondrial energy metabolism and oxidative stress are important factors in AD pathogenesis.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Female; Genetic Association Studies; Genotype; Humans; Male; Mental Status Schedule; Mitochondrial Uncoupling Proteins; Neuroimaging; Polymorphism, Single Nucleotide

Genetic Variations in ABCA7 Can Increase Secreted Levels of Amyloid-β40 and Amyloid-β42 Peptides and ABCA7 Transcription in Cell Culture Models. - Bamji-Mirza, Michelle; Li, Yan; Najem, Dema; Liu, Qing Yan; Walker, Douglas; Lue, Lih-Fen; Stupak, Jacek; Chan, Kenneth; Li, Jianjun; Ghani, Mahdi; Yang, Ze; Rogaeva, Ekaterina; et al. (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is characterized by extracellular deposits of amyloid-β (Aβ) in the brain. ABCA7 is highly expressed in the brain and a susceptibility gene for late-onset AD (LOAD). The minor alleles at two ABCA7 single-nucleotide polymorphisms (SNPs), rs3764650 (T>G; intron13) and rs3752246 at a predicted myristoylation site (C>G; exon33; p.Gly1527Ala), are significantly associated with LOAD risk; however, the mechanism of this association is unknown. Functional consequences of both SNPs were examined in HEK293 and CHO cells stably expressing AβPPSwe. Luciferase reporter assays in HEK293 cells suggested that intron13 carrying rs3764650 major T-allele (int13-T) possessed promoter-enhancing capabilities. Co-transfection experiments with hABCA7 and int13-T resulted in significantly increased ABCA7 protein level relative to that with int13-G. Expression of hABCA7 carrying rs3752246 risk allele led to increases in secreted Aβ40 and Aβ42 and β-secretase activity in CHO- and HEK-AβPPSwe cells. Hydroxymyristic acid treatment of cells expressing hABCA7 carrying the rs3752246 major G allele resulted in increased β-secretase activity and levels of Aβ, suggesting that lack of myristoylation contributes to the observed cell-phenotypes. Molecular weight determination, by gel-electrophoresis and mass spectrometry, of hABCA7 peptides spanning position 1527 showed loss of post-translational modification in the risk-allele peptide. These results suggest that decreased expression, or impaired function, of ABCA7 may contribute to AD pathology.

The Gesture Imitation in Alzheimer's Disease Dementia and Amnestic Mild Cognitive Impairment. - Li, Xudong; Jia, Shuhong; Zhou, Zhi; Hou, Chunlei; Zheng, Wenjing; Rong, Pei; Jiao, Jinsong (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease dementia (ADD) has become an important health problem in the world. Visuospatial deficits are considered to be an early symptom besides memory disorder. OBJECTIVES: The gesture imitation test was devised to detect ADD and amnestic mild cognitive impairment (aMCI). METHODS: A total of 117 patients with ADD, 118 with aMCI, and 95 normal controls were included in this study. All participants were administered our gesture imitation test, the Mini-Mental State Examination (MMSE), the Montreal Cognitive Assessment (MoCA), the Clock Drawing Test (CDT), and the Clinical Dementia Rating Scale (CDR). RESULTS: Patients with ADD performed worse than normal controls on global scores and had a lower success rate on every item (p < 0.001). The area under the curve (AUC) for the global scores when comparing the ADD and control groups was 0.869 (p < 0.001). Item 4 was a better discriminator with a sensitivity of 84.62% and a specificity of 67.37%. The AUC for the global scores decreased to 0.621 when applied to the aMCI and control groups (p = 0.002). After controlling for age and education, the gesture imitation test scores were positively correlated with the MMSE (r = 0.637, p < 0.001), the MoCA (r = 0.572, p < 0.001), and the CDT (r = 0.514, p < 0.001) and were negatively correlated with the CDR scores (r = -0.558, p < 0.001). CONCLUSIONS: The gesture imitation test is an easy, rapid tool for detecting ADD, and is suitable for the patients suspected of mild ADD and aMCI in outpatient clinics.

Glutamine and Glutamate Complex, as Measured by Functional Magnetic Resonance Spectroscopy, Alters During Face-Name Association Task in Patients with Mild Cognitive Impairment and Alzheimer's Disease. - Jahng, Geon-Ho; Oh, Janghoon; Lee, Do-Wan; Kim, Hyug-Gi; Rhee, Hak Young; Shin, Wonchul; Paik, Jong-Woo; Lee, Kyung Mi; Park, Soonchan; Choe, Bo-Young; Ryu, Chang-Woo (J Alzheimers Dis, 2016)
BACKGROUND: The metabolite response during a memory task in Alzheimer's disease (AD) patients is unknown. OBJECTIVE: To investigate the metabolite changes in subjects with AD, amnestic mild cognitive impairment (aMCI), and cognitively normal (CN) elderly during a memory task using functional magnetic resonance spectroscopy (fMRS). METHODS: This study involved 23 young normal controls (YC), 24 CN elderly, 24 aMCI, and 24 mild and probable AD individuals. fMRS data were acquired at the precuneus and posterior cingulate brain regions during a face-name association task. Statistical analyses of quantified metabolites were performed to evaluate differences of the metabolite values between the stimulation conditions and among the four subject groups. Receiver operating curve analysis was performed to evaluate whether the metabolic changes after functional activations can differentiate the subject groups. RESULT: Glutamine and glutamate complex (Glx) was statistically significantly different between the fixation and repeat conditions in aMCI (p = 0.0492) as well as between the fixation and the novel conditions in the AD (p = 0.0412) group. The total N-acetylaspartate (tNAA) was statistically significantly different among the four subject groups in the fixation condition (DF = 3, F = 7.673, p <  0.001), the novel condition (DF = 3, F = 6.945, p <  0.001), and the repeat condition (DF = 3, F = 7.127, p <  0.001). tNAA, tCr, and mIns could be used to differentiate CN from aMCI. Furthermore, tNAA, tCr, Glx, and Glu could also differentiate CN from AD, and aMCI from AD. CONCLUSION: Glx was altered during a stimulation that may be used to evaluate neuronal dysfunction in a demented patient. tNAA and tCr were reduced in patients with AD.

Greater specificity for cerebrospinal fluid P-tau231 over P-tau181 in the differentiation of healthy controls from Alzheimer's disease. - Spiegel, Jonathan; Pirraglia, Elizabeth; Osorio, Ricardo S; Glodzik, Lidia; Li, Yi; Tsui, Wai; Saint Louis, Leslie A; Randall, Catherine; Butler, Tracy; Xu, Jinfeng; Zinkowski, Raymond P; Zetterberg, Henrik; et al. (J Alzheimers Dis, 2016)
Cerebrospinal fluid (CSF) measures of phosphorylated-tau (P-tau) 231 and P-tau181 are two biomarkers for the identification of tau pathology as related to Alzheimer's disease (AD). While both are pathologically validated, their relative diagnostic performances are not well known. This cross-sectional diagnostic study of 87 normal (NL) subjects and 28 AD subjects compared CSF P-tau231 with CSF P-tau181. Logistic regression modeling demonstrated that the P-tau231 was superior to the P-tau181 in the diagnostic classifications. At a fixed 85% sensitivity cutoff, the ROC analysis shows that P-tau231 has greater overall specificity than P-tau181. While both P-tau analytes demonstrated equivalent negative predictive accuracies, P-tau231 yielded significantly fewer false positives. Moreover, P-tau231, but not P-tau181, demonstrated sensitivity to the E4 genotype. A postmortem validation with 9 AD subjects confirmed the superiority of the CSF P-tau231 specificity. This study suggests that P-tau231 has the potential to improve the CSF tau biomarker diagnosis of AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Case-Control Studies; Cross-Sectional Studies; Female; Humans; Logistic Models; Male; Middle Aged; Phosphorylation; ROC Curve; Sensitivity and Specificity; tau Proteins

Greater than the Sum of Its Parts: δ can be Constructed from Item Level Data. - Royall, Donald R; Palmer, Raymond F; Matsuoka, Teruyuki; Kato, Yuka; Taniguchi, Shogo; Ogawa, Mayu; Fujimoto, Hiroshi; Okamura, Aiko; Shibata, Keisuke; Nakamura, Kaeko; Nakaaki, Shutaro; Koumi, Hiroyuki; et al. (J Alzheimers Dis, 2016)
"δ", a latent variable constructed from cognitive performance and functional status measures, can accurately diagnose dementia. The minimal assessment needed is unknown. We have constructed a δ homolog, "dTEXAS", from Telephone Executive Assessment Scale (TEXAS) items, and validated it in a convenience sample of Japanese persons (n = 176). dTEXAS scores correlated strongly with both Instrumental Activities of Daily Living (IADL) (r = -0.86, p <  0.001) and Clinical Dementia Rating Scale (CDR) (r = 0.71, p <  0.001). Constructed independently of their diagnoses, dTEXAS scores accurately distinguished dementia versus controls (area under the receiver operating curve [(AUC; ROC) = 0.92], dementia versus mild cognitive impairment (MCI) (AUC = 0.80) and controls versus MCI (AUC = 0.74). These AUCs are higher than those of multiple observed executive measures, as reported recently by Matsuoka et al., 2014. A dTEXAS score of -0.58 best discriminated between dementia versus controls with 90.1% sensitivity and 80.0% specificity.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Executive Function; Female; Humans; Japan; Male; Neuropsychological Tests; Psychiatric Status Rating Scales; ROC Curve; United States

Health-Related Quality of Life in Patients with Alzheimer's Disease in Different German Health Care Settings. - Heßmann, Philipp; Seeberg, Greta; Reese, Jens Peter; Dams, Judith; Baum, Erika; Müller, Matthias J; Dodel, Richard; Balzer-Geldsetzer, Monika (J Alzheimers Dis, 2016)
The purpose of this study is to evaluate the health-related quality of life (HrQoL) of patients with Alzheimer's disease (AD) in different care settings (institutionalized versus community-dwelling) across all severity stages of dementia. Patients were consecutively recruited with their primary caregivers (123 inpatients and 272 outpatients), and the impact of patient-related parameters such as behavioral and psychological symptoms of dementia (BPSD) (Geriatric Depression Scale [GDS] and Neuropsychiatric Inventory [NPI]) and functional capacity (Alzheimer's Disease Cooperative Study-Activities of Daily Living [ADCS-ADL]) on HrQoL was analyzed. Patients' HrQoL was assessed using self-reported and caregiver-rated generic (EuroQoL Instrument) and dementia-specific (Quality of Life-Alzheimer's Disease [Qol-AD]) scales. Patients reported a considerably higher HrQoL than their caregivers on the QoL-AD, EQ-5D, and EQ VAS (p <  0.001). Different dementia severity groups showed significantly worse results in HrQoL for patients with lower MMSE scores. The mean self-reported QoL-AD decreased from 32.3±5.7 in the group with the highest MMSE scores to 27.1±5.5 in patients with the lowest MMSE scores (p <  0.001). A considerably lower HrQoL was shown for institutionalized patients versus participants in outpatient settings (proxy-rated QoL-AD 19.7±4.6 versus 26.0±7.1, p <  0.001). Depressive symptoms (GDS), BPSD (NPI), and reduced functional capacity (ADCS-ADL) were evaluated for their impact on patients' HrQoL. Multivariate models explained between 22% and 54% of the variance in patients' HrQoL. To analyze the causative direction of the reported associations, further longitudinal studies should be conducted.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Caregivers; Depression; Female; Germany; Humans; Inpatients; Male; Multivariate Analysis; Neuropsychological Tests; Outpatients; Psychiatric Status Rating Scales; Quality of Life; Residential Facilities; Self Report; Severity of Illness Index

Heart Rate Spectra Confirm the Presence of Autonomic Dysfunction in Dementia Patients. - Struhal, Walter; Mahringer, Christoph; Lahrmann, Heinz; Mörtl, Christoph; Buhl, Peter; Huemer, Mario; Ransmayr, Gerhard (J Alzheimers Dis, 2016)
Recent data suggest autonomic dysfunction in patients suffering dementia. This study evaluated autonomic modulation in dementia patients with and without autonomic involvement, employing ECG spectral analysis in the time-frequency domain (wavelet transform) in supine resting and head-up tilt (HUT) position. Thirty-six patients were prospectively evaluated at the Department of Neurology and Psychiatry, General Hospital of the City of Linz, between 2009 and 2014. A standard cardiovascular autonomic test series (Ewing battery) was performed to screen for autonomic dysfunction. The Ewing battery diagnoses were used as reference standard and compared to the diagnostic results obtained by spectral analysis (time-frequency domain) of ECG recordings. Based on the Ewing battery results, 14 patients suffered autonomic dysfunction, while 22 did not. Time frequency domain was accessed by using the continuous wavelet transformation (CWT) with an analytical Morlet mother wavelet in supine resting and HUT position. Within each cohort the modification of spectral components from supine resting to HUT was analyzed reflecting the autonomic modulation. For patients without autonomic dysfunction, a significant increase of autonomic modulation was detected by wavelet transformed ECG recordings (8%, p < 0.05; low frequency content) during HUT compared to supine resting. There was no significant modulation between HUT and supine resting in patients suffering autonomic dysfunction. In dementia patients suffering autonomic dysfunction, CWT identified blunted autonomic regulation only by analysis of ECG recordings without the need to assess other biosignals or tests depending on the patient's cooperation. Further studies are needed to evaluate whether CWT is a suitable method to support the standard Ewing battery in demented patients.

Hierarchical Distribution of the Tau Cytoskeletal Pathology in the Thalamus of Alzheimer's Disease Patients. - Rüb, Udo; Stratmann, Katharina; Heinsen, Helmut; Del Turco, Domenico; Ghebremedhin, Estifanos; Seidel, Kay; den Dunnen, Wilfred; Korf, Horst-Werner (J Alzheimers Dis, 2016)
In spite of considerable progress in neuropathological research on Alzheimer's disease (AD), knowledge regarding the exact pathoanatomical distribution of the tau cytoskeletal pathology in the thalamus of AD patients in the advanced Braak and Braak AD stages V or VI of the cortical cytoskeletal pathology is still fragmentary. Investigation of serial 100 μm-thick brain tissue sections through the thalamus of clinically diagnosed AD patients with Braak and Braak AD stage V or VI cytoskeletal pathologies immunostained with the anti-tau AT8 antibody, along with the affection of the extraterritorial reticular nucleus of the thalamus, reveals a consistent and severe tau immunoreactive cytoskeletal pathology in the limbic nuclei of the thalamus (e.g., paraventricular, anterodorsal and laterodorsal nuclei, limitans-suprageniculate complex). The thalamic nuclei integrated into the associative networks of the human brain (e.g., ventral anterior and mediodorsal nuclei) are only mildly affected, while its motor precerebellar (ventral lateral nucleus) and sensory nuclei (e.g., lateral and medial geniculate bodies, ventral posterior medial and lateral nuclei, parvocellular part of the ventral posterior medial nucleus) are more or less spared. The highly stereotypical and characteristic thalamic distribution pattern of the AD-related tau cytoskeletal pathology represents an anatomical mirror of the hierarchical topographic distribution of the cytoskeletal pathology in the interconnected regions of the cerebral cortex of AD patients. These pathoanatomical parallels support the pathophysiological concept of a transneuronal spread of the disease process of AD along anatomical pathways. The AD-related tau cytoskeletal pathology in the thalamus most likely contributes substantially to the neuropsychiatric disease symptoms (e.g., dementia), attention deficits, oculomotor dysfunctions, altered non-discriminative aspects of pain experience of AD patients, and the disruption of their waking and sleeping patterns.
Keywords: Alzheimer Disease; Cytoskeleton; Humans; tau Proteins; Thalamus

High Risk of Dementia in Ventricular Enlargement with Normal Pressure Hydrocephalus Related Symptoms1. - Koivisto, Anne M; Kurki, Mitja I; Alafuzoff, Irina; Sutela, Anna; Rummukainen, Jaana; Savolainen, Sakari; Vanninen, Ritva; Jääskeläinen, Juha E; Soininen, Hilkka; Leinonen, Ville (J Alzheimers Dis, 2016)
BACKGROUND: Differential diagnosis of ventricular enlargement with normal pressure hydrocephalus (NPH) related symptoms is challenging. Patients with enlarged ventricles often manifest cognitive deterioration but their long-term outcome is not well known. OBJECTIVES: We aim to evaluate long-term cognitive outcome in patients with enlarged ventricles and clinically suspected NPH. METHODS: A neurologist and a neurosurgeon clinically evaluated 468 patients with enlarged ventricles and suspected NPH using radiological methods, intraventricular pressure monitoring, and frontal cortical brain biopsy. The neurologist confirmed final diagnoses after a median follow-up interval of 4.8 years. RESULTS: Altogether, 232 patients (50%) with enlarged ventricles did not fulfill the criteria for shunt surgery. The incidence of dementia among patients with enlarged ventricles, and at least one NPH-related symptom with adequate follow-up data (n = 446) was high, varying from 77 (iNPH, shunt responders) to 141/1000 person-years (non-shunted patients with enlarged ventricles). At the end of the follow-up, 59% of all these patients were demented. The demented population comprised 73% of non-shunted patients with enlarged ventricles, 63% of shunted iNPH patients that did not respond to treatment, and 46% of iNPH patients that were initially responsive to shunting. The most common cause of dementia was Alzheimer's disease (n = 94, 36%), followed by vascular dementia (n = 68, 26%). CONCLUSIONS: One-half of patients with enlarged ventricles and clinically suspected NPH were not shunted after intraventricular pressure monitoring. Dementia caused by various neurodegenerative diseases was frequently seen in patients with ventricular enlargement. Thus, careful diagnostic evaluation in collaboration with neurologists and neurosurgeons is emphasized.

Higher Fasting Plasma Glucose Levels, within the Normal Range, are Associated with Decreased Processing Speed in High Functioning Young Elderly. - Raizes, Meytal; Elkana, Odelia; Franko, Motty; Ravona Springer, Ramit; Segev, Shlomo; Beeri, Michal Schnaider (J Alzheimers Dis, 2016)
We explored the association of plasma glucose levels within the normal range with processing speed in high functioning young elderly, free of type 2 diabetes mellitus (T2DM). A sample of 41 participants (mean age = 64.7, SD = 10; glucose 94.5 mg/dL, SD = 9.3), were examined with a computerized cognitive battery. Hierarchical linear regression analysis showed that higher plasma glucose levels, albeit within the normal range (<110 mg/dL), were associated with longer reaction times (p <  0.01). These findings suggest that even in the subclinical range and in the absence of T2DM, monitoring plasma glucose levels may have an impact on cognitive function.
Keywords: Aged; Blood Glucose; Cognition; Diabetes Mellitus, Type 2; Fasting; Female; Humans; Linear Models; Male; Middle Aged; Neuropsychological Tests; Psychomotor Performance; Reaction Time; Reference Values

High-Throughput Screening for Identification of Blood-Brain Barrier Integrity Enhancers: A Drug Repurposing Opportunity to Rectify Vascular Amyloid Toxicity. - Qosa, Hisham; Mohamed, Loqman A; Al Rihani, Sweilem B; Batarseh, Yazan S; Duong, Quoc-Viet; Keller, Jeffrey N; Kaddoumi, Amal (J Alzheimers Dis, 2016)
The blood-brain barrier (BBB) is a dynamic interface that maintains brain homeostasis and protects it from free entry of chemicals, toxins, and drugs. The barrier function of the BBB is maintained mainly by capillary endothelial cells that physically separate brain from blood. Several neurological diseases, such as Alzheimer's disease (AD), are known to disrupt BBB integrity. In this study, a high-throughput screening (HTS) was developed to identify drugs that rectify/protect BBB integrity from vascular amyloid toxicity associated with AD progression. Assessing Lucifer Yellow permeation across in-vitro BBB model composed from mouse brain endothelial cells (bEnd3) grown on 96-well plate inserts was used to screen 1280 compounds of Sigma LOPAC®1280 library for modulators of bEnd3 monolayer integrity. HTS identified 62 compounds as disruptors, and 50 compounds as enhancers of the endothelial barrier integrity. From these 50 enhancers, 7 FDA approved drugs were identified with EC50 values ranging from 0.76-4.56 μM. Of these 7 drugs, 5 were able to protect bEnd3-based BBB model integrity against amyloid toxicity. Furthermore, to test the translational potential to humans, the 7 drugs were tested for their ability to rectify the disruptive effect of Aβ in the human endothelial cell line hCMEC/D3. Only 3 (etodolac, granisetron, and beclomethasone) out of the 5 effective drugs in the bEnd3-based BBB model demonstrated a promising effect to protect the hCMEC/D3-based BBB model integrity. These drugs are compelling candidates for repurposing as therapeutic agents that could rectify dysfunctional BBB associated with AD.

Impact of Depressive Symptoms on Memory for Emotional Words in Mild Cognitive Impairment and Late-Life Depression. - Callahan, Brandy L; Simard, Martine; Mouiha, Abderazzak; Rousseau, François; Laforce, Robert; Hudon, Carol (J Alzheimers Dis, 2016)
BACKGROUND: Amnestic mild cognitive impairment (aMCI) and late-life depression (LLD) are associated with increased risk of Alzheimer's disease (AD). This is also true for aMCI with concomitant depressive symptoms (aMCI/D+), but few studies have investigated this syndrome. OBJECTIVES: We aimed to clarify the association between cognitive and depressive symptoms in individuals at risk for AD by examining episodic memory for emotional stimuli in aMCI, aMCI/D+, and LLD. METHODS: Participants were 34 patients with aMCI, 20 patients with aMCI/D+, 19 patients with LLD, and 28 healthy elderly adults. In an implicit encoding task, participants rated the emotional valence of 12 positive, 12 negative, and 12 neutral words. Immediately and 20 minutes later, participants recalled as many words as possible. They were also asked to identify previously presented words during a yes/no recognition trial. RESULTS: At immediate recall, aMCI participants displayed better recall of emotional words, particularly positive words. aMCI/D+ and control participants displayed better recall of positive and negative words compared to neutral words. LLD participants recalled more negative than neutral words. At delayed recall, emotional words were generally better-remembered than neutral words by all groups. At recognition, all subjects responded more liberally to emotional than to neutral words. CONCLUSION: We find that the type of emotional information remembered by aMCI patients at immediate recall depends on the presence or absence of depressive symptoms. These findings contribute to identifying sources of heterogeneity in individuals at risk for AD, and suggest that the cognitive profile of aMCI/D+ is different from that of aMCI and LLD. Future studies should systematically consider the presence of depressive symptoms in elderly at-risk individuals.

Impacts of Illiteracy on the Risk of Dementia: A Global Health Perspective. - Suh, Seung Wan; Han, Ji Won; Park, Jae Young; Hong, Jong Woo; Kim, Kayoung; Kim, Taehyun; Lee, Kyoung Hwan; Han, Guehee; Jeong, Hyeon; Seo, Jiyeong; Kim, Tae Hui; Lee, Dong Young; et al. (J Alzheimers Dis, 2016)
Despite its significance as a contributing factor for late-life dementia risk, illiteracy is frequently underappreciated in the management of dementia. In this study, we estimated the proportion of dementia cases attributable to illiteracy using the population attributable fraction (PAF), and calculated to what extent the monetary cost of dementia could be saved in the future by reducing illiteracy from the South Korean, Latin American, South Asian/Middle Eastern, and African populations. We collected necessary data from the 2011 United Nations Human Development Report and prevalence studies conducted in these regions. Additional variables not included in the above sources were estimated using a logit model under a "trend scenario"-based assumption. Around 16% of the total number of dementia cases in South Korea in 2015 can be attributed to illiteracy, with this figure predicted to decline to around 2% by 2050. This translates to a saving in dementia care costs of approximately 52 billion USD, providing we are successful in theoretically eradicating illiteracy as of 2015, in the population aged 65 years or under. Likewise, reducing illiteracy to 50% in Latin America, South Asia/The Middle East, and Africa by 2050 could generate further cost savings of between 71 and 244 billion, 13 and 94 billion, and 17 and 78 billion USD, respectively. Even public policies aimed solely at reducing illiteracy in the childhood, adolescent, or middle-aged population could potentially have a role in the primary prevention of dementia. Moving forward, governments will need to address this issue in a purposeful and systematic manner.

Increased Intrinsic Activity of Medial-Temporal Lobe Subregions is Associated with Decreased Cortical Thickness of Medial-Parietal Areas in Patients with Alzheimer's Disease Dementia. - Pasquini, Lorenzo; Scherr, Martin; Tahmasian, Masoud; Myers, Nicholas E; Ortner, Marion; Kurz, Alexander; Förstl, Hans; Zimmer, Claus; Grimmer, Timo; Akhrif, Atae; Wohlschläger, Afra M; Riedl, Valentin; et al. (J Alzheimers Dis, 2016)
In Alzheimer's disease (AD), disrupted connectivity between medial-parietal cortices and medial-temporal lobes (MTL) is linked with increased MTL local functional connectivity, and parietal atrophy is associated with increased MTL memory activation. We hypothesized that intrinsic activity in MTL subregions is increased and associated with medial-parietal degeneration and impaired memory in AD. To test this hypothesis, resting-state-functional and structural-MRI was assessed in 22 healthy controls, 22 mild cognitive impairment patients, and 21 AD-dementia patients. Intrinsic activity was measured by power-spectrum density of blood-oxygenation-level-dependent signal, medial-parietal degeneration by cortical thinning. In AD-dementia patients, intrinsic activity was increased for several right MTL subregions. Raised intrinsic activity in dentate gyrus and cornu ammonis 1 was associated with cortical thinning in posterior cingulate cortices, and at-trend with impaired delayed recall. Critically, increased intrinsic activity in the right entorhinal cortex was associated with ipsilateral posterior cingulate degeneration. Our results provide evidence that in AD, intrinsic activity in MTL subregions is increased and associated with medial-parietal atrophy. Results fit a model in which medial-parietal degeneration contributes to MTL dysconnectivity from medial-parietal cortices, potentially underpinning disinhibition-like changes in MTL activity.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Memory Disorders; Middle Aged; Nerve Net; Parietal Lobe; Temporal Lobe

Inflammation, Antiinflammatory Agents, and Alzheimer's Disease: The Last 22 Years. - McGeer, Patrick L; Rogers, Joseph; McGeer, Edith G (J Alzheimers Dis, 2016)
Two basic discoveries spurred research into inflammation as a driving force in the pathogenesis of Alzheimer's disease (AD). The first was the identification of activated microglia in association with the lesions. The second was the discovery that rheumatoid arthritics, who regularly consume anti-inflammatory agents, were relatively spared from the disease. These findings led to an exploration of the inflammatory pathways that were involved in AD pathogenesis. A pivotal advance was the discovery that amyloid-β protein (Aβ) activated the complement system. This focused attention on anti-inflammatories as blockers of complement activation. More than 15 epidemiological studies have since showed a sparing effect of non-steroidal anti-inflammatory drugs (NSAIDs) in AD. A consistent finding has been that the longer the NSAIDs were used prior to clinical diagnosis, the greater the sparing effect. The reason has since emerged from studies of biomarkers such as amyloid-β (Aβ) levels in the cerebrospinal fluid and Aβ deposits in brain. They have established that the onset of AD commences at least a decade before cognitive decline permits clinical diagnosis. Such biomarker studies have revealed that a huge window of opportunity exists when application of NSAIDs, other anti-inflammatory agents, or complement activation blockers, could arrest further progress of AD, thus eliminating its manifestation. It can be anticipated that this principle will apply to many other chronic neurodegenerative diseases. Neuroinflammation, discovered in AD more than 30 years ago, has now become a major field of brain research today. Inhibiting it may be the key to successful treatment of many chronic neurological disorders.

Influence of Incipient Dementia on Hospitalization for Primary Care Sensitive Conditions: A Population-Based Cohort Study. - Pimouguet, Clément; Rizzuto, Debora; Fastbom, Johan; Lagergren, Mårten; Fratiglioni, Laura; Xu, Weili (J Alzheimers Dis, 2016)
BACKGROUND: Studies have reported that moderate/severe stages of dementia are linked to increased hospitalization rates, but little is known about the influence of incipient dementia on hospitalizations for primary care sensitive conditions (PCSCs). OBJECTIVE: To examine the associations between incipient dementia and hospitalization outcomes, including all-cause and PCSC hospitalization. METHODS: A total of 2,268 dementia-free participants in the Swedish National study on Aging and Care-Kungsholmen were interviewed and clinically examined at baseline. Participants aged ≥78 years were followed for 3 years, and those aged 60-72 years, for 6 years. Number of hospitalizations was retrieved from the National Patient Register. Dementia was diagnosed in accordance with Diagnostic and Statistical Manual of Mental Disorders-IV criteria. Hospitalization outcomes were compared in participants who did and did not develop dementia. Zero-inflated Poisson regressions and logistic regressions were used in data analysis. RESULTS: During the follow-up, 175 participants developed dementia. The unadjusted PCSC admission rate was 88.2 per 1000 person-years in those who developed dementia and 25.6 per 1000 person-years in those who did not. In the fully adjusted logistic regression model, incipient dementia was associated with an increased risk of hospitalization for PCSCs (OR = 2.3, 95% CI 1.3-3.9) but not with the number of hospitalizations or with all-cause hospitalization. Risks for hospitalization for diabetes, congestive heart failure, and pyelonephritis were higher in those who developed dementia than in those who did not. About 10% participants had a PCSC hospitalization attributable to incipient dementia. CONCLUSION: People with incipient dementia are more prone to hospitalization for PCSCs but not to all-cause hospitalization.
Keywords: Acute Disease; Age Factors; Aged; Aged, 80 and over; Chronic Disease; Dementia; Female; Follow-Up Studies; Hospitalization; Humans; Logistic Models; Longitudinal Studies; Male; Primary Health Care; Registries; Risk; Sensitivity and Specificity; Socioeconomic Factors; Sweden

Integrating Biomarkers for Underlying Alzheimer's Disease in Mild Cognitive Impairment in Daily Practice: Comparison of a Clinical Decision Support System with Individual Biomarkers. - Rhodius-Meester, Hanneke F M; Koikkalainen, Juha; Mattila, Jussi; Teunissen, Charlotte E; Barkhof, Frederik; Lemstra, Afina W; Scheltens, Philip; Lötjönen, Jyrki; van der Flier, Wiesje M (J Alzheimers Dis, 2016)
BACKGROUND: Recent criteria allow biomarkers to provide evidence of Alzheimer's disease (AD) pathophysiology. How they should be implemented in daily practice remains unclear, especially in mild cognitive impairment (MCI) patients. OBJECTIVE: We evaluated how a clinical decision support system such as the PredictAD tool can aid clinicians to integrate biomarker evidence to support AD diagnosis. METHODS: With available data on demographics, cerebrospinal fluid (CSF), and MRI, we trained the PredictAD tool on a reference population of 246 controls and 491 AD patients. We then applied the identified algorithm to 211 MCI patients. For comparison, we also classified patients based on individual biomarkers (MRI; CSF) and the NIA-AA criteria. Progression to dementia was used as outcome measure. RESULTS: After a median follow up of 3 years, 72 (34%) MCI patients remained stable and 139 (66%) progressed to AD. The PredictAD tool assigned a likelihood of underlying AD to each patient (AUC 0.82). Excluding patients with missing data resulted in an AUC of 0.87. According to the NIA-AA criteria, half of the MCI patients had uninformative biomarkers, precluding an assignment of AD likelihood. A minority (41%) was assigned to high or low AD likelihood with good predictive value. The individual biomarkers showed best value for CSF total tau (AUC 0.86). CONCLUSION: The ability of the PredictAD tool to identify AD pathophysiology was comparable to individual biomarkers. The PredictAD tool has the advantage that it assigns likelihood to all patients, regardless of missing or conflicting data, allowing clinicians to integrate biomarker data in daily practice.
Keywords: Aged; Aged, 80 and over; Algorithms; Alzheimer Disease; Area Under Curve; Biomarkers; Cognitive Dysfunction; Cohort Studies; Decision Support Systems, Clinical; Disease Progression; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Outcome Assessment (Health Care); Predictive Value of Tests

JNK: A Putative Link Between Insulin Signaling and VGLUT1 in Alzheimer's Disease. - Rodriguez-Perdigon, Manuel; Solas, Maite; Ramirez, Maria Javier (J Alzheimers Dis, 2016)
In the present work, the involvement of JNK in insulin signaling alterations and its role in glutamatergic deficits in Alzheimer's disease (AD) has been studied. In postmortem cortical tissues, pJNK levels were increased, while insulin signaling and the expression of VGLUT1 were decreased. A significant correlation was found between reduced expression of insulin receptor and VGLUT1. The administration of a JNK inhibitor reversed the decrease in VGLUT1 expression found in a mice model of insulin resistance. It is suggested that activation of JNK in AD inhibits insulin signaling which could lead to a decreased expression of VGLUT1, therefore contributing to the glutamatergic deficit in AD.
Keywords: Aged; Alzheimer Disease; Animals; Brain; Corticosterone; Disease Models, Animal; Female; Humans; Insulin; Insulin Resistance; Male; MAP Kinase Kinase 4; Mice, Inbred C57BL; Mitogen-Activated Protein Kinase 1; Neuroprotective Agents; RNA, Messenger; Vesicular Glutamate Transport Protein 1

The Language Profile of Behavioral Variant Frontotemporal Dementia. - Hardy, Chris J D; Buckley, Aisling H; Downey, Laura E; Lehmann, Manja; Zimmerer, Vitor C; Varley, Rosemary A; Crutch, Sebastian J; Rohrer, Jonathan D; Warrington, Elizabeth K; Warren, Jason D (J Alzheimers Dis, 2016)
BACKGROUND: The language profile of behavioral variant frontotemporal dementia (bvFTD) remains to be fully defined. OBJECTIVE: We aimed to quantify the extent of language deficits in this patient group. METHODS: We assessed a cohort of patients with bvFTD (n = 24) in relation to patients with semantic variant primary progressive aphasia (svPPA; n = 14), nonfluent variant primary progressive aphasia (nfvPPA; n = 18), and healthy age-matched individuals (n = 24) cross-sectionally and longitudinally using a comprehensive battery of language and general neuropsychological tests. Neuroanatomical associations of language performance were assessed using voxel-based morphometry of patients' brain magnetic resonance images. RESULTS: Relative to healthy controls, and after accounting for nonverbal executive performance, patients with bvFTD showed deficits of noun and verb naming and single word comprehension, diminished spontaneous propositional speech, and deterioration in naming performance over time. Within the bvFTD group, patients with MAPT mutations had more severe impairments of noun naming and single word comprehension than patients with C9orf72 mutations. Overall the bvFTD group had less severe language deficits than patients with PPA, but showed a language profile that was qualitatively similar to svPPA. Neuroanatomical correlates of naming and word comprehension performance in bvFTD were identified predominantly in inferior frontal and antero-inferior temporal cortices within the dominant hemispheric language network. CONCLUSIONS: bvFTD is associated with a language profile including verbal semantic impairment that warrants further evaluation as a novel biomarker.
Keywords: Aged; Aphasia, Primary Progressive; Atrophy; Brain; Cognition; Comprehension; Female; Frontotemporal Dementia; Humans; Language; Magnetic Resonance Imaging; Male; Middle Aged; Neuroimaging; Neuropsychological Tests; Primary Progressive Nonfluent Aphasia

Late-Life Depressive Symptoms and Lifetime History of Major Depression: Cognitive Deficits are Largely Due to Incipient Dementia rather than Depression. - Heser, Kathrin; Bleckwenn, Markus; Wiese, Birgitt; Mamone, Silke; Riedel-Heller, Steffi G; Stein, Janine; Lühmann, Dagmar; Posselt, Tina; Fuchs, Angela; Pentzek, Michael; Weyerer, Siegfried; Werle, Jochen; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Late-life depression is frequently accompanied by cognitive impairments. OBJECTIVE: Whether these impairments indicate a prodromal state of dementia, or are a symptomatic expression of depression per se is not well-studied. METHODS: In a cohort of very old initially non-demented primary care patients (n = 2,709, mean age = 81.1 y), cognitive performance was compared between groups of participants with or without elevated depressive symptoms and with or without subsequent dementia using ANCOVA (adjusted for age, sex, and education). Logistic regression analyses were computed to predict subsequent dementia over up to six years of follow-up. The same analytical approach was performed for lifetime major depression. RESULTS: Participants with elevated depressive symptoms without subsequent dementia showed only small to medium cognitive deficits. In contrast, participants with depressive symptoms with subsequent dementia showed medium to very large cognitive deficits. In adjusted logistic regression models, learning and memory deficits predicted the risk for subsequent dementia in participants with depressive symptoms. Participants with a lifetime history of major depression without subsequent dementia showed no cognitive deficits. However, in adjusted logistic regression models, learning and orientation deficits predicted the risk for subsequent dementia also in participants with lifetime major depression. CONCLUSION: Marked cognitive impairments in old age depression should not be dismissed as "depressive pseudodementia", but require clinical attention as a possible sign of incipient dementia. Non-depressed elderly with a lifetime history of major depression, who remained free of dementia during follow-up, had largely normal cognitive performance.

The Latent Dementia Phenotype δ is Associated with Cerebrospinal Fluid Biomarkers of Alzheimer's Disease and Predicts Conversion to Dementia in Subjects with Mild Cognitive Impairment. - Koppara, Alexander; Wolfsgruber, Steffen; Kleineidam, Luca; Schmidtke, Klaus; Frölich, Lutz; Kurz, Alexander; Schulz, Stefanie; Hampel, Harald; Heuser, Isabella; Peters, Oliver; Reischies, Friedel M; Jahn, Holger; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The recently proposed latent variable δ is a new tool for dementia case finding. It is built in a structural equation modeling framework of cognitive and functional data and constitutes a novel endophenotype for Alzheimer's disease (AD) research and clinical trials. OBJECTIVE: To investigate the association of δ with AD biomarkers and to compare the prediction of δ with established scales for conversion to dementia in patients with mild cognitive impairment (MCI). METHODS: Using data from a multicenter memory clinic study, we examined the external associations of the latent variable δ and compared δ with well-established cognitive and functional scales and cognitive-functional composite scores. For that purpose, logistic regressions with cerebrospinal fluid (CSF) biomarkers and conversion to dementia as dependent variables were performed with the investigated scores. The models were tested for significant differences. RESULTS: In patients with MCI, δ based on a broad range of cognitive scales (including the ADAS-cog, the MMSE, and the CERAD neuropsychological battery) predicted an abnormal CSF Aβ42/tau ratio indicative of AD (n = 340, AUC = 0.78, p <  0.001), and predicted incident dementia within 1-3 years of follow-up (n = 525, AUC = 0.84, p <  0.001). These associations were generally stronger than for any other scale or cognitive-functional composite examined. Homologs of δ based on reduced test batteries yielded somewhat lower effects. CONCLUSION: These findings support the interpretation of δ as a construct capturing the disease-related "essence" of cognitive and functional impairments in patients with MCI and dementia, and suggest that δ might become an analytical tool for dementia research.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Dementia; Disease Progression; Female; Humans; Logistic Models; Longitudinal Studies; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptide Fragments; Phenotype; Predictive Value of Tests; Retrospective Studies; tau Proteins

Life's Simple 7's Cardiovascular Health Metrics are Associated with Hispanic/Latino Neurocognitive Function: HCHS/SOL Results. - González, Hector M; Tarraf, Wassim; Gouskova, Natalia; Rodríguez, Carlos J; Rundek, Tatjana; Grober, Ellen; Pirzada, Amber; González, Patricia; Lutsey, Pamela L; Camacho, Alvaro; Daviglus, Martha L; Wright, Clinton; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Hispanics/Latinos are purportedly at increased risk for neurocognitive decline and dementias. Without dementia cures, low-cost, well-tolerated public health means for mitigating neurocognitive decline are needed. OBJECTIVE: We examined associations between neurocognition and cardiovascular health (CVH) metrics (Life's Simple 7; LS7) among diverse Hispanics/Latinos. We hypothesized that higher LS7 would be associated with healthier brain function (neurocognitive performance). METHODS: We used baseline (2008-2011) Hispanic Community Health Study/Study of Latinos (HCHS/SOL; N = 9,623; ages 45-74 years) to examine neurocognition in relation to CVH LS7 scores. RESULTS: In age and sex adjusted models, a one unit LS7 score increase (range = 0-14) was associated with higher neurocognitive function on the B-SEVLT sum (0.23 [p < 0.01]; range = 3-42), B-SEVLT recall (0.12 [p < 0.01]; range = 0-15), Word Fluency (phonemic; 0.46 (p < 0.01); range = 0-49), and Digit Symbol Substitution (0.49 (p < 0.01); range = 0-83) tests, respectively. Stated differently, a change from the minimum LS7 (0) to maximum LS7 (14) score corresponded to higher scores on verbal learning (4.62) and memory (2.24), verbal fluency (7.0), and psychomotor processing speed (12). In fully adjusted models the associations were attenuated, but remained statistically significant. Incremental adjustments indicated that Latino background and, to a lesser extent, education were primary contributors to the evinced attenuations. CONCLUSIONS: We found that higher neurocognitive function was associated with better LS7 CVH metrics among middle-aged and older Hispanics/Latinos. Associations between neurocognitive function and LS7 were strongest among two at-risk groups for neurocognitive decline and dementia, women and Hispanics/Latinos with lower education. Public health efforts to reduce cardiovascular disease morbidity and mortality may have additional neurocognitive benefits among at-risk Hispanics/Latinos.

Linguistic Features Identify Alzheimer's Disease in Narrative Speech. - Fraser, Kathleen C; Meltzer, Jed A; Rudzicz, Frank (J Alzheimers Dis, 2016)
BACKGROUND: Although memory impairment is the main symptom of Alzheimer's disease (AD), language impairment can be an important marker. Relatively few studies of language in AD quantify the impairments in connected speech using computational techniques. OBJECTIVE: We aim to demonstrate state-of-the-art accuracy in automatically identifying Alzheimer's disease from short narrative samples elicited with a picture description task, and to uncover the salient linguistic factors with a statistical factor analysis. METHODS: Data are derived from the DementiaBank corpus, from which 167 patients diagnosed with "possible" or "probable" AD provide 240 narrative samples, and 97 controls provide an additional 233. We compute a number of linguistic variables from the transcripts, and acoustic variables from the associated audio files, and use these variables to train a machine learning classifier to distinguish between participants with AD and healthy controls. To examine the degree of heterogeneity of linguistic impairments in AD, we follow an exploratory factor analysis on these measures of speech and language with an oblique promax rotation, and provide interpretation for the resulting factors. RESULTS: We obtain state-of-the-art classification accuracies of over 81% in distinguishing individuals with AD from those without based on short samples of their language on a picture description task. Four clear factors emerge: semantic impairment, acoustic abnormality, syntactic impairment, and information impairment. CONCLUSION: Modern machine learning and linguistic analysis will be increasingly useful in assessment and clustering of suspected AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Diagnosis, Computer-Assisted; Factor Analysis, Statistical; Female; Humans; Language Disorders; Linguistics; Logistic Models; Machine Learning; Male; Mental Status Schedule; Middle Aged; Narration; Photic Stimulation; Speech; Verbal Behavior

Living Alone with Dementia: Prevalence, Correlates and the Utilization of Health and Nursing Care Services. - Eichler, Tilly; Hoffmann, Wolfgang; Hertel, Johannes; Richter, Steffen; Wucherer, Diana; Michalowsky, Bernhard; Dreier, Adina; Thyrian, Jochen René (J Alzheimers Dis, 2016)
BACKGROUND: Little is known about the proportion and the characteristics of community-dwelling people with dementia (PWD) living alone in Germany. OBJECTIVES: To analyze the prevalence of PWD living alone (with and without the support of an informal caregiver) and socio-demographical and clinical characteristics as well as health and nursing care utilization associated with living alone. METHODS: DelpHi-MV (Dementia: Life- and person-centered help in Mecklenburg-Western Pomerania) is a general practitioner-based, randomized controlled intervention trial. The present analyses are based on baseline data of 511 patients (≥70 years, community-dwelling) who had screened positive for dementia (DemTect <9). RESULTS: N = 251 (51%) of the patients lived alone. PWD living alone were statistically significantly more often female, older, and more often widowed than those not living alone. About 9% of the patients (n = 24) were not supported by any informal caregiver. Regarding the clinical variables (cognitive and functional impairment, depression, falls, number of drug-related problems, malnutrition, quality of life), there were no statistically significant group differences. Patients living alone utilized professional services such as home care, help with medication, home-delivered meals, or housekeeping assistance significantly more often. Multivariate analyses confirmed these findings. CONCLUSION: Our results reveal the high proportion of PWD living alone in Germany. PWD living alone did not seem to be at an increased health risk. Our findings indicate that living alone with dementia is possible. In order to ensure the sufficient provision of health and nursing care services for PWD living alone, providers should consider the present results for future planning.

Longitudinal Alteration of Intrinsic Brain Activity in the Striatum in Mild Cognitive Impairment. - Ren, Ping; Lo, Raymond Y; Chapman, Benjamin P; Mapstone, Mark; Porsteinsson, Anton; Lin, Feng (J Alzheimers Dis, 2016)
The striatum is a critical functional hub in understanding neurological disorders. However, the Alzheimer's disease (AD)-associated striatal change is unclear, as is the relationship between striatal change and AD pathology. Three-year resting-state fMRI data from 15 healthy control (HC) and 20 mild cognitive impairment (MCI) participants were obtained. We analyzed the amplitude of low-frequency fluctuations (ALFF) (0.01-0.08 Hz) and two subdivided bands (slow-4:0.027-0.073 Hz; slow-5:0.01-0.027 Hz). We calculated Aβ/pTau ratio using baseline cerebrospinal fluid pTau and Aβ1-42 to represent AD pathology. Compared to HC, MCI participants showed greater decline in right putaminal ALFF, including the slow-4 band. Greater decline of ALFF in the right putamen was significantly related to the memory decline over time and lower baseline Aβ/pTau ratio regardless of age or group. The slow-4 band, relative to slow-5 band, showed a stronger correlation between Aβ/pTau ratio and decline of ALFF in the right putamen. The results suggest that the putaminal function declines early in the AD-associated neurodegeneration. The continuous decline in putaminal ALFF, especially slow-4 band, may be a sensitive marker of AD pathology such as Aβ/pTau ratio regardless of clinical diagnosis.

The Longitudinal Association Between a Discrepancy Measure of Anosognosia in Patients with Dementia, Caregiver Burden and Depression. - Perales, Jaime; Turró-Garriga, Oriol; Gascón-Bayarri, Jordi; Reñé-Ramírez, Ramón; Conde-Sala, Josep Lluís (J Alzheimers Dis, 2016)
BACKGROUND: According to cross-sectional studies, there is an association between anosognosia in people with dementia and caregiver's burden and depression. Anosognosia in patients may be a cause of caregiver burden and depression. However, variability in caregiver anosognosia ratings may exist as caregivers with burden and depression may have a more pessimistic view of the patients' health. OBJECTIVE: To assess the variability of caregiver anosognosia ratings of patients with dementia using a widely used anosognosia scale and its longitudinal relationship with caregiver burden and depression. METHODS: A convenience cohort of 221 consecutive dementia outpatient and caregiver dyads was followed up at 12 and 24 months. The main instruments used were the Anosognosia Questionnaire-Dementia (AQ-D), Caregiver Burden Interview, and Geriatric Depression Scale. Linear mixed models were used including time as a factor in every model. Multivariate analyses controlled for caregiver's socio-demographic and possible confounding factors. RESULTS: Attrition at 12 and 24 months was 24.9% and 42.5% respectively. Patients at baseline were on average 77.8 years of age, 63.3% were women, and 63.3% had < 5 years of education. In the bivariate analyses, caregiver burden, depression, and gender were associated with caregiver ratings of total, cognitive, and personality AQ-D of the patient at different time points. Multivariate analyses revealed burden as the caregiver variable most consistently associated with total, cognitive, and personality caregiver AQ-D ratings of the patient. CONCLUSION: Some caregiver characteristics, especially burden, are associated with caregiver ratings of AQ-D with regard to the patient.

Longitudinal Relationships between Caloric Expenditure and Gray Matter in the Cardiovascular Health Study. - Raji, Cyrus A; Merrill, David A; Eyre, Harris; Mallam, Sravya; Torosyan, Nare; Erickson, Kirk I; Lopez, Oscar L; Becker, James T; Carmichael, Owen T; Gach, H Michael; Thompson, Paul M; Longstreth, W T; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Physical activity (PA) can be neuroprotective and reduce the risk for Alzheimer's disease (AD). In assessing physical activity, caloric expenditure is a proxy marker reflecting the sum total of multiple physical activity types conducted by an individual. OBJECTIVE: To assess caloric expenditure, as a proxy marker of PA, as a predictive measure of gray matter (GM) volumes in the normal and cognitively impaired elderly persons. METHODS: All subjects in this study were recruited from the Institutional Review Board approved Cardiovascular Health Study (CHS), a multisite population-based longitudinal study in persons aged 65 and older. We analyzed a sub-sample of CHS participants 876 subjects (mean age 78.3, 57.5% F, 42.5% M) who had i) energy output assessed as kilocalories (kcal) per week using the standardized Minnesota Leisure-Time Activities questionnaire, ii) cognitive assessments for clinical classification of normal cognition, mild cognitive impairment (MCI), and AD, and iii) volumetric MR imaging of the brain. Voxel-based morphometry modeled the relationship between kcal/week and GM volumes while accounting for standard covariates including head size, age, sex, white matter hyperintensity lesions, MCI or AD status, and site. Multiple comparisons were controlled using a False Discovery Rate of 5 percent. RESULTS: Higher energy output, from a variety of physical activity types, was associated with larger GM volumes in frontal, temporal, and parietal lobes, as well as hippocampus, thalamus, and basal ganglia. High levels of caloric expenditure moderated neurodegeneration-associated volume loss in the precuneus, posterior cingulate, and cerebellar vermis. CONCLUSION: Increasing energy output from a variety of physical activities is related to larger gray matter volumes in the elderly, regardless of cognitive status.

Low Prevalence of Mixed Dementia in a Cohort of 2,000 Elderly Patients in a Memory Clinic Setting. - Claus, Jules J; Staekenborg, Salka S; Roorda, Jelmen J; Stevens, Martijn; Herderschee, Dirk; van Maarschalkerweerd, Willy; Schuurmans, Lilly; Tielkes, Caroline E M; Koster, Pieter; Bavinck, Chris; Scheltens, Philip (J Alzheimers Dis, 2016)
BACKGROUND: It is generally assumed that with increasing age, pathology in clinically diagnosed Alzheimer's disease (AD) becomes more mixed, i.e., co-existence of amyloid plaques and cerebrovascular pathology. OBJECTIVE: To test the hypothesis of increasing prevalence of mixed dementia in late-onset clinically diagnosed Alzheimer's disease (AD) in a single-center memory clinic population. METHODS: Patients included had diagnoses of AD (n = 832), subjective cognitive impairment (SCI, n = 333), mild cognitive impairment (MCI, n = 492), vascular dementia (VaD, n = 57), other dementia (n = 53), or other diagnosis (n = 233). Prevalence of severe white matter lesions (WML) was defined as a score of 2 or higher on the Fazekas-scale on brain computed tomography to classify AD patients as having mixed dementia. We examined the effect of age on WML using multiple linear regression analysis, and AD patients were compared to SCI to determine the effect of disease on WML. RESULTS: Prevalence of severe WML was 33.6% in AD patients (mixed dementia), 11.4% in SCI, 22.7% in MCI, 75.4% in VaD, 3.8% in other dementia, and 15.5% in other diagnosis. With increasing age there was a significant and similar increase of WML scores in SCI, MCI, AD, other dementia, and other diagnosis, indicating no effect modification by AD. The difference between AD patients and SCI averaged 0.16 on the WML score and difference in percentage severe WML between AD and SCI patients was 15% across all ages. CONCLUSION: We found a low prevalence of mixed dementia. Furthermore, severe WML in AD was largely explained by age rather than effect of disease.
Keywords: Age Factors; Aged; Aged, 80 and over; Analysis of Variance; Cognitive Dysfunction; Cohort Studies; Dementia; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Prevalence; Regression Analysis; Risk Factors; Tomography Scanners, X-Ray Computed

Low Serum Insulin-Like Growth Factor-I Predicts Cognitive Decline in Alzheimer's Disease. - Vidal, Jean-Sébastien; Hanon, Olivier; Funalot, Benoît; Brunel, Nadège; Viollet, Cécile; Rigaud, Anne-Sophie; Seux, Marie-Laure; le-Bouc, Yves; Epelbaum, Jacques; Duron, Emmanuelle (J Alzheimers Dis, 2016)
BACKGROUND: The relationship between the insulin-like growth factor-I (IGF-I) system and Alzheimer's disease (AD) is mostly based on transversal studies. It remains, however, to demonstrate whether IGF-I is associated with cognitive decline over time in AD. OBJECTIVE: The objective of the study was to analyze the course of cognitive decline of AD subjects over a 24-month period in relation to serum IGF-I and insulin-like growth factor binding protein-3 (IGFBP-3) measured at baseline. METHODS: Data are from the SIGAL follow-up study. IGF-I and IGFBP-3 were measured in AD subjects who performed a Mini-Mental State Examination (MMSE) every 6 months for 2 years. MMSE course was analyzed using a mixed model with random intercept and slope function. RESULTS: Among the 200 AD participants, 146 (mean age = 81.1 (standard deviation (SD) = 5.9) years, 62.6% of women) had at least one follow-up visit. Mean IGF-I at baseline was 147.8 (74.2) ng/mL. Hundred forty-six participants (62.6%) had at least one follow-up visit. Mean MMSE was 21.7 (4.7)/30 and dropped on average by 2.28 points per year. MMSE decline was steeper among participants with lower IGF-I. For each decrease of 1 SD of IGF-I, subjects lost an additional 0.63 points per year in MMSE, e.g., participants with IGF-I level of 74 ng/mL lost 2.91 MMSE points per year whereas participants with IGF-I of 222 ng/mL lost 1.65 MMSE points per year. There was no association between IGFBP-3 and cognitive decline. CONCLUSION: Lower baseline serum IGF-I was associated with faster cognitive decline in AD over a 2-year period.

Lower Late-Life Body-Mass Index is Associated with Higher Cortical Amyloid Burden in Clinically Normal Elderly. - Hsu, David C; Mormino, Elizabeth C; Schultz, Aaron P; Amariglio, Rebecca E; Donovan, Nancy J; Rentz, Dorene M; Johnson, Keith A; Sperling, Reisa A; Marshall, Gad A (J Alzheimers Dis, 2016)
BACKGROUND: Lower body-mass index (BMI) in late life has been associated with an increased risk of dementia, and weight loss has been associated with more rapid decline in Alzheimer's disease (AD) dementia. OBJECTIVE: To explore the association between BMI and cortical amyloid burden in clinically normal (CN) elderly at risk for AD dementia. METHODS: Cross-sectional analyses were completed using baseline data from the Harvard Aging Brain Study, consisting of 280 community-dwelling CN older adults aged 62-90. Assessments included medical histories and physical exam, Pittsburgh compound B (PiB) positron emission tomography (PET) amyloid imaging, and apolipoprotein E ɛ4 (APOE4) genotyping. For the primary analysis, a general linear regression model was used to evaluate the association of BMI with PiB retention. Covariates included age, sex, years of education, and APOE4 carrier status. Secondary analyses were performed for BMI subdivisions (normal, overweight, obese), APOE4 carriers, and BMI×APOE4 interaction. RESULTS: In the primary analysis, greater PiB retention was associated with lower BMI (β  =  -0.14, p = 0.02). In the secondary analyses, APOE4 carrier status (β= -0.27, p = 0.02) and normal BMI (β= -0.25, p = 0.01), as opposed to overweight or obese BMI, were associated with greater PiB retention. The BMI×APOE4 interaction was also significant (β= -0.14, p = 0.04). CONCLUSIONS: This finding offers new insight into the role of BMI at the preclinical stage of AD, wherein lower BMI late in life is associated with greater cortical amyloid burden. Future studies are needed to elucidate the mechanism behind this association, especially in those with lower BMI who are APOE4 carriers.

LRP/LR Antibody Mediated Rescuing of Amyloid-β-Induced Cytotoxicity is Dependent on PrPc in Alzheimer's Disease. - Pinnock, Emma C; Jovanovic, Katarina; Pinto, Maxine G; Ferreira, Eloise; Dias, Bianca Da Costa; Penny, Clement; Knackmuss, Stefan; Reusch, Uwe; Little, Melvyn; Schatzl, Hermann M; Weiss, Stefan F T (J Alzheimers Dis, 2016)
The neuronal perturbations in Alzheimer's disease are attributed to the formation of extracellular amyloid-β (Aβ) neuritic plaques, composed predominantly of the neurotoxic Aβ42 isoform. Although the plaques have demonstrated a role in synaptic dysfunction, neuronal cytotoxicity has been attributed to soluble Aβ42 oligomers. The 37kDa/67kDa laminin receptor has been implicated in Aβ42 shedding and Aβ42-induced neuronal cytotoxicity, as well as internalization of this neurotoxic peptide. As the cellular prion protein binds to both LRP/LR and Aβ42, the mechanism underlying this cytotoxicity may be indirectly due to the PrPc-Aβ42 interaction with LRP/LR. The effects of this interaction were investigated by 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide assays. PrPc overexpression significantly enhanced Aβ42 cytotoxicity in vitro, while PrP-/-  cells were more resistant to the cytotoxic effects of Aβ42 and exhibited significantly less cell death than PrPc expressing N2a cells. Although anti-LRP/LR specific antibody IgG1-iS18 significantly enhanced cell viability in both pSFV1-huPrP1-253 transfected and non-transfected cells treated with exogenous Aβ42, it failed to have any cell rescuing effect in PrP-/-  HpL3-4 cells. These results suggest that LRP/LR plays a significant role in Aβ42-PrPc mediated cytotoxicity and that anti-LRP/LR specific antibodies may serve as potential therapeutic tools for Alzheimer's disease.
Keywords: Amyloid beta-Peptides; Animals; Antibodies; Cell Line, Transformed; Cell Survival; Flow Cytometry; Gene Expression Regulation; Humans; Mice; Peptide Fragments; Prions; Receptors, Laminin; Transfection

Maintenance of Cognitive Performance and Mood for Individuals with Alzheimer's Disease Following Consumption of a Nutraceutical Formulation: A One-Year, Open-Label Study. - Remington, Ruth; Bechtel, Cynthia; Larsen, David; Samar, Annemarie; Page, Robert; Morrell, Christopher; Shea, Thomas B (J Alzheimers Dis, 2016)
Nutritional interventions have shown varied efficacy on cognitive performance during Alzheimer's disease (AD). Twenty-four individuals diagnosed with AD received a nutraceutical formulation (NF: folate, alpha-tocopherol, B12, S-adenosyl methioinine, N-acetyl cysteine, acetyl-L-carnitine) under open-label conditions (ClinicalTrials.gov NCT01320527). Primary outcome was cognitive performance. Secondary outcomes were behavioral and psychological symptoms of dementia (BPSD) and activities of daily living. Participants maintained their baseline cognitive performance and BPSD over 12 months. These findings are consistent with improvement in cognitive performance and BPSD in prior placebo-controlled studies with NF, and contrast with the routine decline for participants receiving placebo.
Keywords: Aged; Aged, 80 and over; alpha-Tocopherol; Alzheimer Disease; Cognition Disorders; Dietary Supplements; Disease Progression; Female; Folic Acid; Follow-Up Studies; Humans; Male; Mood Disorders; Neuropsychological Tests; Psychiatric Status Rating Scales; Time Factors; Vitamin B 12

MAPT H1 Haplotype is Associated with Late-Onset Alzheimer's Disease Risk in APOEɛ4 Noncarriers: Results from the Dementia Genetics Spanish Consortium. - Pastor, Pau; Moreno, Fermín; Clarimón, Jordi; Ruiz, Agustin; Combarros, Onofre; Calero, Miguel; López de Munain, Adolfo; Bullido, Maria J; de Pancorbo, Marian M; Carro, Eva; Antonell, Anna; Coto, Eliecer; et al. (J Alzheimers Dis, 2016)
The MAPT H1 haplotype has been linked to several disorders, but its relationship with Alzheimer's disease (AD) remains controversial. A rare variant in MAPT (p.A152T) has been linked with frontotemporal dementia (FTD) and AD. We genotyped H1/H2 and p.A152T MAPT in 11,572 subjects from Spain (4,327 AD, 563 FTD, 648 Parkinson's disease (PD), 84 progressive supranuclear palsy (PSP), and 5,950 healthy controls). Additionally, we included 101 individuals from 21 families with genetic FTD. MAPT p.A152T was borderline significantly associated with FTD [odds ratio (OR) = 2.03; p = 0.063], but not with AD. MAPT H1 haplotype was associated with AD risk (OR = 1.12; p = 0.0005). Stratification analysis showed that this association was mainly driven by APOE ɛ4 noncarriers (OR = 1.14; p = 0.0025). MAPT H1 was also associated with risk for PD (OR = 1.30; p = 0.0003) and PSP (OR = 3.18; p = 8.59 × 10-8) but not FTD. Our results suggest that the MAPT H1 haplotype increases the risk of PD, PSP, and non-APOE ɛ4 AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Female; Frontotemporal Dementia; Genetic Predisposition to Disease; Haplotypes; Humans; Logistic Models; Male; Middle Aged; Polymorphism, Single Nucleotide; Spain; tau Proteins

Measuring Information Processing Speed in Mild Cognitive Impairment: Clinical Versus Research Dichotomy. - Haworth, Judy; Phillips, Michelle; Newson, Margaret; Rogers, Peter J; Torrens-Burton, Anna; Tales, Andrea (J Alzheimers Dis, 2016)
A substantial body of research evidence is indicative of disproportionately slowed information processing speed in a wide range of multi-trial, computer-based, neuroimaging- and electroencephalography-based reaction time (RT) tests in Alzheimer's disease and mild cognitive impairment (MCI). However, in what is arguably a dichotomy between research evidence and clinical practice, RT associated with different brain functions is rarely assessed as part of their diagnosis. Indeed, often only the time taken to perform a single, specific task, commonly the Trail making test (TMT), is measured. In clinical practice therefore, there can be a failure to assess adequately the integrity of the rapid, serial information processing and response, necessary for efficient, appropriate, and safe interaction with the environment. We examined whether a typical research-based RT task could at least match the TMT in differentiating amnestic MCI (aMCI) from cognitively healthy aging at group level. As aMCI is a heterogeneous group, typically containing only a proportion of individuals for whom aMCI represents the early stages of dementia, we examined the ability of each test to provide intra-group performance variation. The results indicate that as well as significant slowing in performance of the operations involved in TMT part B (but not part A), individuals with aMCI also experience significant slowing in RT compared to controls. The results also suggest that research-typical RT tests may be superior to the TMT in differentiating between cognitively healthy aging and aMCI at group level and in revealing the performance variability one would expect from an etiologically heterogeneous disorder such as aMCI.
Keywords: Aged; Aged, 80 and over; Attention; Cognitive Dysfunction; Electroencephalography; Female; Humans; Male; Mental Processes; Mental Status Schedule; Middle Aged; Neuroimaging; Neuropsychological Tests; Photic Stimulation; Reaction Time; Residence Characteristics

Memory Binding Test Predicts Incident Amnestic Mild Cognitive Impairment. - Mowrey, Wenzhu B; Lipton, Richard B; Katz, Mindy J; Ramratan, Wendy S; Loewenstein, David A; Zimmerman, Molly E; Buschke, Herman (J Alzheimers Dis, 2016)
BACKGROUND: The Memory Binding Test (MBT), previously known as Memory Capacity Test, has demonstrated discriminative validity for distinguishing persons with amnestic mild cognitive impairment (aMCI) and dementia from cognitively normal elderly. OBJECTIVE: We aimed to assess the predictive validity of the MBT for incident aMCI. METHODS: In a longitudinal, community-based study of adults aged 70+, we administered the MBT to 246 cognitively normal elderly adults at baseline and followed them annually. Based on previous work, a subtle reduction in memory binding at baseline was defined by a Total Items in the Paired (TIP) condition score of ≤22 on the MBT. Cox proportional hazards models were used to assess the predictive validity of the MBT for incident aMCI accounting for the effects of covariates. The hazard ratio of incident aMCI was also assessed for different prediction time windows ranging from 4 to 7 years of follow-up, separately. RESULTS: Among 246 controls who were cognitively normal at baseline, 48 developed incident aMCI during follow-up. A baseline MBT reduction was associated with an increased risk for developing incident aMCI (hazard ratio (HR) = 2.44, 95% confidence interval: 1.30-4.56, p = 0.005). When varying the prediction window from 4-7 years, the MBT reduction remained significant for predicting incident aMCI (HR range: 2.33-3.12, p: 0.0007-0.04). CONCLUSION: Persons with poor performance on the MBT are at significantly greater risk for developing incident aMCI. High hazard ratios up to seven years of follow-up suggest that the MBT is sensitive to early disease.

Memory for Public Events in Mild Cognitive Impairment and Alzheimer's Disease: The Importance of Rehearsal. - Langlois, Roxane; Joubert, Sven; Benoit, Sophie; Dostie, Valérie; Rouleau, Isabelle (J Alzheimers Dis, 2016)
Ribot's law refers to the better preservation of remote memories compared with recent ones that presumably characterizes retrograde amnesia. Even if Ribot-type temporal gradient has been extensively studied in retrograde amnesia, particularly in Alzheimer's disease (AD), this pattern has not been consistently found. One explanation for these results may be that rehearsal frequency rather than remoteness accounts for the better preservation of these memories. Thus, the aim of present study was to address this question by studying retrograde semantic memory in subjects with amnestic mild cognitive impairment (aMCI) (n = 20), mild AD (n = 20) and in healthy older controls (HC; n = 19). In order to evaluate the impact of repetition as well as the impact of remoteness, we used a test assessing memory for enduring and transient public events that occurred in the recent and remote past. Results show no clear temporal gradient across time periods (1960-1975; 1976-1990; 1991-2005; 2006-2011), but a better performance was observed in all three groups for enduring compared with transient events. Moreover, although deficits were globally found in both patients groups compared with HC, more specific analyses revealed that aMCI patients were only impaired on transient events while AD patients were impaired on both transient and enduring events. Exploratory analyses also revealed a tendency suggesting preservation of remote transient events in aMCI. These findings are discussed with regards to memory consolidation models.
Keywords: Aged; Alzheimer Disease; Cognitive Dysfunction; Female; Humans; Learning; Male; Memory; Psychological Tests; Semantics

Midlife Physical Activity and Cognition Later in Life: A Prospective Twin Study. - Iso-Markku, Paula; Waller, Katja; Vuoksimaa, Eero; Heikkilä, Kauko; Rinne, Juha; Kaprio, Jaakko; Kujala, Urho M (J Alzheimers Dis, 2016)
BACKGROUND: Physical activity has been associated with a reduced risk of cognitive decline but the nature of this association remains obscure. OBJECTIVE: To study associations between midlife physical activity and cognition in old age for a prospective cohort of Finnish twins. METHODS: Physical activity in the Finnish Twin Cohort was assessed using questionnaire responses collected in 1975 and 1981. After a mean follow-up of 25.1 years, the subjects' (n = 3050; mean age 74.2; range 66-97) cognition was evaluated with a validated telephone interview. Both participation in vigorous physical activity, and the volume of physical activity, divided into quintiles, were used as predictors of cognitive impairment. Metrics collected by TELE were used to categorize participants as: cognitively impaired, suffering mild cognitive impairment, or cognitively healthy. RESULTS: Participation in vigorous physical activity compared to non-participation for both 1975 and 1981 was associated with a lower risk of cognitive impairment in individual-based analyses (fully adjusted OR 0.50, 95% CI 0.35-0.73). Pairwise analyses yielded similar but statistically non-significant associations. In terms of the volume of physical activity, the most active quintile of individuals (OR 0.69, 95% CI 0.46-1.04) had a reduced risk of cognitive decline compared with the most sedentary quintile in the fully adjusted model although no clear dose-response was found. CONCLUSION: Vigorous midlife physical activity was associated with less cognitive impairment but without a clear dose-response association between the volume of physical activity and cognition.

Mindfulness in the Maintenance of Cognitive Capacities in Alzheimer's Disease: A Randomized Clinical Trial. - Quintana-Hernández, Domingo J; Miró-Barrachina, María T; Ibáñez-Fernández, Ignacio J; Pino, Angelo Santana-Del; Quintana-Montesdeoca, María P; Rodríguez-de Vera, Bienvenida; Morales-Casanova, David; Pérez-Vieitez, María Del Carmen; Rodríguez-García, Javier; Bravo-Caraduje, Noelia (J Alzheimers Dis, 2016)
BACKGROUND: The Canary Islands longitudinal study on non-pharmacological treatments showed the overall effectiveness of mindfulness in Alzheimer's disease (AD). However, no specific data on the maintenance of cognitive capacities were presented. OBJECTIVE: To determine whether the practice of mindfulness modifies the course of cognitive impairment in AD. METHODS: DESIGN: Longitudinal, non-inferiority and equivalence, randomized clinical trial, repeated-measures design, with three experimental groups and one control group. PARTICIPANTS: Patients with AD who voluntarily attended the Lidia García Foundation (n = 502). Only those who were treated with donepezil and MMSE ≥18 were included (n = 120). INTERVENTION: Over a two-year period, each group carried out three weekly sessions of stimulation based on mindfulness, cognitive stimulation therapy, and progressive muscle relaxation. MEASURES: Cognitive assessment CAMDEX-R (MMSE and CAMCOG). STATISTICAL ANALYSIS: Repeated-measures ANOVA (p <  0.05) and the effect size Cohen's d were performed. RESULTS: The mindfulness group showed significant scores compared with the control and muscle relaxation groups (p <  0.05), while mindfulness and cognitive stimulation therapy were equivalent (p≥0.05). Group cognitive stimulation evolved better than the control (p <  0.05) group but not better than the muscle relaxation group (p≥0.05). The effect size compared over two years was large for the mindfulness group (p≥0.80), moderate for the relaxation group (p≥0.50), and low for the cognitive stimulation group (p≥0.20). CONCLUSION: The practice of mindfulness maintained cognitive function over a period of two years. This longitudinal study suggests that mindfulness can be used as a non-pharmacological treatment to slow cognitive impairment in AD.
Keywords: Age Factors; Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Cognition Disorders; Double-Blind Method; Female; Humans; Longitudinal Studies; Male; Mental Status Schedule; Mindfulness; Neuropsychological Tests; Treatment Outcome

Mismatch Negativity and Ear Laterality in Alzheimer's Disease and in Mild Cognitive Impairment. - Idrizbegovic, Esma; Hederstierna, Christina; Rosenhall, Ulf (J Alzheimers Dis, 2016)
BACKGROUND: Cortical auditory event-related potentials (ERPs) were studied in order to measure mismatch negativity (MMN). Three groups of subjects were studied: patients with Alzheimer's disease (AD, n = 32), mild cognitive impairment (MCI, n = 44), and subjective memory complaints without cognitive decline (SMC, n = 27). A bottom up strategy was applied, and the right and left ears were stimulated monaurally. OBJECTIVE: To investigate MMN in AD and MCI, and in a clinical reference group. METHODS: ERPs were carried out with 500 tone pulses at 80 dBnHL. Each sequence included 80% standard tones (500 Hz) (f), and 20% deviant tones (1000 Hz) (r). MMN measurements were carried out by comparing the amplitudes of (f) and (r) recordings and to calculate the amplitude difference in μV for each group. The right and the left ears were analyzed separately. RESULTS: A left ear advantage (LEA) of MMN amplitude was demonstrated in the two groups with better cognition (the MCI and the SMC groups), but not in the AD group. DISCUSSION: The absence of MMN asymmetry in the AD group is possibly caused by a dysfunction to apprehend changes of tonal stimuli.

Molecular Signaling Mechanisms of Natural and Synthetic Retinoids for Inhibition of Pathogenesis in Alzheimer's Disease. - Chakrabarti, Mrinmay; McDonald, Alexander J; Will Reed, J; Moss, Melissa A; Das, Bhaskar C; Ray, Swapan K (J Alzheimers Dis, 2016)
Retinoids, which are vitamin A derivatives, interact through retinoic acid receptors (RARs) and retinoid X receptors (RXRs) and have profound effects on several physiological and pathological processes in the brain. The presence of retinoic acid signaling is extensively detected in the adult central nervous system, including the amygdala, cortex, hypothalamus, hippocampus, and other brain areas. Retinoids are primarily involved in neural patterning, differentiation, and axon outgrowth. Retinoids also play a key role in the preservation of the differentiated state of adult neurons. Impairment in retinoic acid signaling can result in neurodegeneration and progression of Alzheimer's disease (AD). Recent studies demonstrated severe deficiencies in spatial learning and memory in mice during retinoic acid (vitamin A) deprivation indicating its significance in preserving memory function. Defective cholinergic neurotransmission plays an important role in cognitive deficits in AD. All-trans retinoic acid is known to enhance the expression and activity of choline acetyltransferase in neuronal cell lines. Activation of RAR and RXR is also known to impede the pathogenesis of AD in mice by inhibiting accumulation of amyloids. In addition, retinoids have been shown to inhibit the expression of chemokines and pro-inflammatory cytokines in microglia and astrocytes, which are activated in AD. In this review article, we have described the chemistry and molecular signaling mechanisms of natural and synthetic retinoids and current understandings of their therapeutic potentials in prevention of AD pathology.
Keywords: Alzheimer Disease; Animals; Brain; Humans; Mice; Neurons; Retinoid X Receptors; Retinoids; Signal Transduction; Tretinoin

Monitoring Blood-Brain Barrier Integrity Following Amyloid-β Immunotherapy Using Gadolinium-Enhanced MRI in a PDAPP Mouse Model. - Blockx, Ines; Einstein, Steve; Guns, Pieter-Jan; Van Audekerke, Johan; Guglielmetti, Caroline; Zago, Wagner; Roose, Dimitri; Verhoye, Marleen; Van der Linden, Annemie; Bard, Frederique (J Alzheimers Dis, 2016)
BACKGROUND: Amyloid-related imaging abnormalities (ARIA) have been reported with some anti-amyloid-β (Aβ) immunotherapy trials. They are detected with magnetic resonance imaging (MRI) and thought to represent transient accumulation of fluid/edema (ARIA-E) or microhemorrhages (ARIA-H). Although the clinical significance and pathophysiology are unknown, it has been proposed that anti-Aβimmunotherapy may affect blood-brain barrier (BBB) integrity. OBJECTIVE: To examine vascular integrity in aged (12-16 months) PDAPP and wild type mice (WT), we performed a series of longitudinal in vivo MRI studies. METHODS: Mice were treated on a weekly basis using anti-Aβimmunotherapy (3D6) and follow up was done longitudinally from 1-12 weeks after treatment. BBB-integrity was assessed using both visual assessment of T1-weighted scans and repeated T1 mapping in combination with gadolinium (Gd-DOTA). RESULTS: A subset of 3D6 treated PDAPP mice displayed numerous BBB disruptions, whereas WT and saline-treated PDAPP mice showed intact BBB integrity under the conditions tested. In addition, the contrast induced decrease in T1 value was observed in the meningeal and midline area. BBB disruption events occurred early during treatment (between 1 and 5 weeks), were transient, and resolved quickly. Finally, BBB-leakages associated with microhemorrhages were confirmed by Perls'Prussian blue histopathological analysis. CONCLUSION: Our preclinical findings support the hypothesis that 3D6 leads to transient leakage from amyloid-positive vessels. The current study has provided valuable insights on the time course of vascular alterations during immunization treatment and supports further research in relation to the nature of ARIA and the utility of in vivo repeated T1 MRI as a translational tool.

Monophosphoryl Lipid-A: A Promising Tool for Alzheimer's Disease Toll. - Rego, Ângela; Viana, Sofia D; Ribeiro, Carlos A Fontes; Rodrigues-Santos, Paulo; Pereira, Frederico C (J Alzheimers Dis, 2016)
Neuroinflammation is a two-edged sword in Alzheimer's disease (AD). A certain degree of neuroinflammation is instrumental in the clearance of amyloid-β (Aβ) peptides by activated microglia, although a sustained neuroinflammation might accelerate Aβ deposition, thus fostering the neurodegenerative process and functional decline in AD. There is an increasing body of evidence suggesting that the innate immune system via Toll-like receptor 4 (TLR4) finely orchestrates the highly regulated inflammatory cascade that takes place in AD pathology. Herein we critically review pre-clinical (in vitro and in vivo approaches) and clinical studies showing that monophosphoryl lipid A (MPL), a partial TLR4 agonist, may have beneficial effect on AD physiopathology. The in vivo data elegantly showed that MPL enhanced Aβ plaque phagocytosis thus decreasing the number and the size of Aβ deposits and soluble Aβ in brain from APPswe/PS1 mice. Furthermore, MPL also improved their cognition. The mechanism underlying this MPL effect was proposed to be microglial activation by recruiting TLR4. Additionally, it was demonstrated that MPL increased the Aβ antibody titer and showed a safe profile in mice and primates, when used as a vaccine adjuvant. Clinical studies using MPL as an adjuvant in Aβ immunotherapy are currently ongoing. Overall, we argue that the TLR4 partial agonist MPL is a potentially safe and effective new pharmacological tool in AD.

Moving from the Dish to the Clinical Practice: A Decade of Lessons and Perspectives from the Pre-Clinical and Clinical Stem Cell Studies for Alzheimer's Disease. - Salem, Haitham; Rocha, Natalia Pessoa; Colpo, Gabriela Delevati; Teixeira, Antonio Lucio (J Alzheimers Dis, 2016)
To date, there is no definitive treatment for Alzheimer's disease (AD). The realm of stem cells is very promising in regenerative medicine, particularly neurodegenerative disorders. Various types of stem cells have been used in multiple trials on AD models, trying to find an innovative management of this disease. In this systematic review, we trace the published preclinical and clinical data throughout the last decade, to show how much knowledge we gained so far in this field and the future perspectives of stem cells in AD treatment.

Multifunctional Effect of Human Serum Albumin Reduces Alzheimer's Disease Related Pathologies in the 3xTg Mouse Model. - Ezra, Assaf; Rabinovich-Nikitin, Inna; Rabinovich-Toidman, Polina; Solomon, Beka (J Alzheimers Dis, 2016)
Alzheimer's disease (AD), the prevalent dementia in the elderly, involves many related and interdependent pathologies that manifests simultaneously, eventually leading to cognitive impairment and death. No treatment is currently available; however, an agent addressing several key pathologies simultaneously has a better therapeutic potential. Human serum albumin (HSA) is a highly versatile protein, harboring multifunctional properties that are relevant to key pathologies underlying AD. This study provides insight into the mechanism for HSA's therapeutic effect. In vivo, a myriad of beneficial effects were observed by pumps infusing HSA intracerebroventricularly, for the first time in an AD 3xTg mice model. A significant effect on amyloid-β (Aβ) pathology was observed. Aβ1-42, soluble oligomers, and total plaque area were reduced. Neuroblastoma SHSY5Y cell line confirmed that the reduction in Aβ1-42 toxicity was due to direct binding rather than other properties of HSA. Total and hyperphosphorylated tau were reduced along with an increase in tubulin, suggesting increased microtubule stability. HSA treatment also reduced brain inflammation, affecting both astrocytes and microglia markers. Finally, evidence for blood-brain barrier and myelin integrity repair was observed. These multidimensional beneficial effects of intracranial administrated HSA, together or individually, contributed to an improvement in cognitive tests, suggesting a non-immune or Aβ efflux dependent means for treating AD.
Keywords: Albumins; Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Blood-Brain Barrier; Brain; Calcium; Cell Line, Tumor; Cognition Disorders; Disease Models, Animal; Drug Delivery Systems; Encephalitis; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Neuroblastoma; Neuropsychological Tests; Peptide Fragments; Presenilin-1; tau Proteins

Music and Memory in Alzheimer's Disease and The Potential Underlying Mechanisms. - Peck, Katlyn J; Girard, Todd A; Russo, Frank A; Fiocco, Alexandra J (J Alzheimers Dis, 2016)
With population aging and a projected exponential expansion of persons diagnosed with Alzheimer's disease (AD), the development of treatment and prevention programs has become a fervent area of research and discovery. A growing body of evidence suggests that music exposure can enhance memory and emotional function in persons with AD. However, there is a paucity of research that aims to identify specific underlying neural mechanisms associated with music's beneficial effects in this particular population. As such, this paper reviews existing anecdotal and empirical evidence related to the enhancing effects of music exposure on cognitive function and further provides a discussion on the potential underlying mechanisms that may explain music's beneficial effect. Specifically, this paper will outline the potential role of the dopaminergic system, the autonomic nervous system, and the default network in explaining how music may enhance memory function in persons with AD.
Keywords: Alzheimer Disease; Auditory Perception; Autonomic Nervous System; Dopamine; Humans; Memory Disorders; Music Therapy

Netrin-1 Interrupts Amyloid-β Amplification, Increases sAβPPα in vitro and in vivo, and Improves Cognition in a Mouse Model of Alzheimer's Disease. - Spilman, Patricia R; Corset, Veronique; Gorostiza, Olivia; Poksay, Karen S; Galvan, Veronica; Zhang, Junli; Rao, Rammohan; Peters-Libeu, Clare; Vincelette, Jon; McGeehan, Andrew; Dvorak-Ewell, Melita; Beyer, Janine; et al. (J Alzheimers Dis, 2016)
Recent studies have shown that inoculation of susceptible mice with amyloid-β (Aβ) peptides accelerates Aβ deposition in the brain, supporting the idea that Aβ may be self-amplifying; however, the exact mechanism is not understood. Here we provide evidence that Aβ may self-amplify, in part, by inhibiting α-secretase ADAM10 (a disintegrin and metalloprotease) cleavage of full-length Aβ precursor protein (FL AβPP) and therefore allow greater β-secretase processing, and that Aβ itself is a substrate for ADAM10. Exposure of primary neuronal cultures from PDAβPP mice to exogenous rat Aβ1- 40 resulted in increased de novo human Aβ1-42 production and exposure of cells to Aβ decreased production of ADAM10 cleavage product soluble AβPPα (sAβPPα). In a cell-free assay, Aβ decreased ADAM10 cleavage of the chimeric substrate MBP-AβPPC125 and Aβ itself was apparently cleaved by the enzyme. The axonal guidance and trophic factor netrin-1, however, reduced the Aβ1- 40-induced Aβ1-42 increase, increased sAβPPα, and reversed the Aβ-induced sAβPPα decrease in vitro. In vivo, induction of netrin-1 expression in PDAβPPSwe/Ind transgenic mice resulted in reductions in both Aβ1-42 and Aβ1- 40, and ICV delivery of netrin-1 to PDAβPPSwe/Ind mice increased sAβPPα, decreased Aβ, and improved working memory. Finally, to support further study of netrin-1's potential as a therapeutic for Alzheimer's disease, pilot gene therapy studies were performed and a netrin mimetic peptide synthesized and tested that, like netrin, can increase sAβPPα and decrease Aβ1-42in vitro. Taken together, these data provide mechanistic insights into Aβ self-amplification and the ability of netrin-1 to disrupt it.

Neurocognitive Deficits Distinguishing Mild Dementia with Lewy Bodies from Mild Alzheimer's Disease are Associated with Parkinsonism. - Brønnick, Kolbørn; Breitve, Monica H; Rongve, Arvid; Aarsland, Dag (J Alzheimers Dis, 2016)
BACKGROUND: The cognitive profile of mild dementia with Lewy bodies (DLB) versus mild Alzheimer's disease (AD) has not been extensively studied, and the relation of cognitive deficits to the core diagnostic criteria for DLB (fluctuations, visual hallucinations, and parkinsonism) remains poorly understood. OBJECTIVE: To compare the cognitive profile in patients with mild DLB to patients with mild AD and investigate the relation between cognitive deficits distinguishing DLB from AD and the core diagnostic features in DLB. METHODS: Patients with mild dementia were recruited from the southwestern part of Norway and patients diagnosed with probable AD (n = 113) or probable DLB (n = 77) were included. The DLB core diagnostic symptoms were assessed using standardized clinical measures, and standardized neurocognitive tests assessing attention, language, memory, and visuospatial functions were administered. Univariate and multivariate comparisons of cognitive tests were performed, and tests distinguishing between AD and DLB were subjected to correlational analyses with the core diagnostic symptoms. RESULTS: DLB patients performed worse than AD patients on test of visuoconstruction, but not visual perception and on all tests involving attention and executive functions, except verbal fluency. The multivariate model distinguished between DLB and AD with a sensitivity of 74% and a specificity of 82%. Tests where DLB performed worse than AD were highly correlated with degree of parkinsonism, but not with cognitive fluctuations or visual hallucinations. CONCLUSIONS: The cognitive profile in mild DLB can be useful in distinguishing AD from DLB. The strong relation between relative deficits in DLB and parkinsonism warrants further studies.

Neuroimaging Correlates of Frontotemporal Dementia Associated with SQSTM1 Mutations. - Luis, Elkin; Ortiz, Alexandra; Eudave, Luis; Ortega-Cubero, Sara; Borroni, Barbara; van der Zee, Julie; Gazzina, Stefano; Caroppo, Paola; Rubino, Elisa; D'Agata, Federico; Le Ber, Isabelle; Santana, Isabel; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Frontotemporal lobar degeneration (FTLD) is a progressive dementia characterized by focal atrophy of frontal and/or temporal lobes caused by mutations in the gene coding for sequestosome 1 (SQSTM1), among other genes. Rare SQSTM1 gene mutations have been associated with Paget's disease of bone, amyotrophic lateral sclerosis, and, more recently, frontotemporal lobar degeneration (FTLD). OBJECTIVE: The aim of the study was to determine whether a characteristic pattern of grey and white matter loss is associated with SQSTM1 dysfunction. METHODS: We performed a voxel-based morphometry (VBM) study in FTD subjects carrying SQSTM1 pathogenic variants (FTD/SQSTM1 mutation carriers; n = 10), compared with FTD subjects not carrying SQSTM1 mutations (Sporadic FTD; n = 20) and healthy controls with no SQSTM1 mutations (HC/SQSTM1 noncarriers; n = 20). The groups were matched according to current age, disease duration, and gender. RESULTS: After comparing FTD/SQSTM1 carriers with Sporadic FTD, a predominantly right cortical atrophy pattern was localized in the inferior frontal, medial orbitofrontal, precentral gyri, and the anterior insula. White matter atrophy was found in both medial and inferior frontal gyri, pallidum, and putamen. FTD/SQSTM1 carriers compared with HC/SQSTM1 noncarriers showed atrophy at frontal, temporal, and parietal lobes of both hemispheres whereas the MRI pattern found in Sporadic FTD compared with controls was frontal and left temporal lobe atrophy, extending toward parietal and occipital lobes of both hemispheres. CONCLUSIONS: These results suggest that fronto-orbito-insular regions including corticospinal projections as described in ALS are probably more susceptible to the damaging effect of SQSTM1 mutations delineatinga specific gene-linked atrophy pattern.

Neurophysiological assessment of Alzheimer's disease individuals by a single electroencephalographic marker. - Lizio, Roberta; Del Percio, Claudio; Marzano, Nicola; Soricelli, Andrea; Yener, Görsev G; Başar, Erol; Mundi, Ciro; De Rosa, Salvatore; Triggiani, Antonio Ivano; Ferri, Raffaele; Arnaldi, Dario; Nobili, Flavio Mariano; et al. (J Alzheimers Dis, 2016)
Here we presented a single electroencephalographic (EEG) marker for a neurophysiological assessment of Alzheimer's disease (AD) patients already diagnosed by current guidelines. The ability of the EEG marker to classify 127 AD individuals and 121 matched cognitively intact normal elderly (Nold) individuals was tested. Furthermore, its relationship to AD patients' cognitive status and structural brain integrity was examined. Low-resolution brain electromagnetic tomography (LORETA) freeware estimated cortical sources of resting state eyes-closed EEG rhythms. The EEG marker was defined as the ratio between the activity of parieto-occipital cortical sources of delta (2-4 Hz) and low-frequency alpha (8-10.5 Hz) rhythms. Results showed 77.2% of sensitivity in the recognition of the AD individuals; 65% of specificity in the recognition of the Nold individuals; and 0.75 of area under the receiver-operating characteristic curve. Compared to the AD subgroup with the EEG maker within one standard deviation of the Nold mean (EEG-), the AD subgroup with EEG+ showed lower global cognitive status, as revealed by Mini-Mental State Evaluation score, and more abnormal values of white-matter and cerebrospinal fluid normalized volumes, as revealed by structural magnetic resonance imaging. We posit that cognitive and functional status being equal, AD patients with EEG+ should receive special clinical attention due to a neurophysiological "frailty". EEG+ label can be also used in clinical trials (i) to form homogeneous groups of AD patients diagnosed by current guidelines and (ii) as end-point to evaluate intervention effects.
Keywords: Aged; Alzheimer Disease; Biomarkers; Brain Mapping; Case-Control Studies; Cognition Disorders; Electroencephalography; Female; Humans; Italy; Magnetic Resonance Imaging; Male; Middle Aged; Occipital Lobe; Rest; ROC Curve; Turkey

Neuropsychological Markers of Medial Perirhinal and Entorhinal Cortex Functioning are Impaired Twelve Years Preceding Diagnosis of Alzheimer's Dementia. - Hirni, Daniela I; Kivisaari, Sasa L; Krumm, Sabine; Monsch, Andreas U; Berres, Manfred; Oeksuez, Fatma; Reinhardt, Julia; Ulmer, Stephan; Kressig, Reto W; Stippich, Christoph; Taylor, Kirsten I (J Alzheimers Dis, 2016)
Neurofibrillary pathology in Alzheimer's dementia (AD) is associated with cognitive impairments and cortical thinning, and begins in medial perirhinal cortex (mPRC) before entering entorhinal cortex (ERC). Thus, mPRC dysfunction (e.g., semantic object memory impairments) may predate or accompany ERC (i.e., episodic memory) dysfunction in the preclinical course of typical AD. We developed formulae estimating mPRC and ERC integrity (i.e., cortical thickness) using common neuropsychological tests in 31 healthy individuals and 58 early AD patients. These formulae estimated the longitudinal courses of mPRC and ERC functioning in independent groups of 28 optimally healthy individuals who developed AD (NC-AD) over 2.8-13.4 years and 28 pairwise-matched, stable, healthy individuals (NC-NC). Mixed models demonstrated significantly worse NC-AD than NC-NC estimated mPRC and ERC functioning at the earliest observation, 12 years preceding diagnosis, and a significant decline 4 years preceding the AD diagnosis. These findings demonstrate that specific neuropsychological impairments occur early in the course of preclinical AD and that tasks measuring mPRC functioning may serve as additional, powerful markers of preclinical AD.

Non-Verbal Episodic Memory Deficits in Primary Progressive Aphasias are Highly Predictive of Underlying Amyloid Pathology. - Ramanan, Siddharth; Flanagan, Emma; Leyton, Cristian E; Villemagne, Victor L; Rowe, Christopher C; Hodges, John R; Hornberger, Michael (J Alzheimers Dis, 2016)
Diagnostic distinction of primary progressive aphasias (PPA) remains challenging, in particular for the logopenic (lvPPA) and nonfluent/agrammatic (naPPA) variants. Recent findings highlight that episodic memory deficits appear to discriminate these PPA variants from each other, as only lvPPA perform poorly on these tasks while having underlying amyloid pathology similar to that seen in amnestic dementias like Alzheimer's disease (AD). Most memory tests are, however, language based and thus potentially confounded by the prevalent language deficits in PPA. The current study investigated this issue across PPA variants by contrasting verbal and non-verbal episodic memory measures while controlling for their performance on a language subtest of a general cognitive screen. A total of 203 participants were included (25 lvPPA; 29 naPPA; 59 AD; 90 controls) and underwent extensive verbal and non-verbal episodic memory testing, with a subset of patients (n = 45) with confirmed amyloid profiles as assessed by Pittsburgh Compound B and PET. The most powerful discriminator between naPPA and lvPPA patients was a non-verbal recall measure (Rey Complex Figure delayed recall), with 81% of PPA patients classified correctly at presentation. Importantly, AD and lvPPA patients performed comparably on this measure, further highlighting the importance of underlying amyloid pathology in episodic memory profiles. The findings demonstrate that non-verbal recall emerges as the best discriminator of lvPPA and naPPA when controlling for language deficits in high load amyloid PPA cases.
Keywords: Aged; Alzheimer Disease; Amyloid; Aniline Compounds; Aphasia, Primary Progressive; Brain; Diagnosis, Differential; Female; Humans; Logistic Models; Male; Memory, Episodic; Neuropsychological Tests; Positron-Emission Tomography; Radiopharmaceuticals; Speech Perception; Thiazoles

Oculodentodigital dysplasia with massive brain calcification and a new mutation of GJA1 gene. - Tumminelli, Gemma; Di Donato, Ilaria; Guida, Valentina; Rufa, Alessandra; De Luca, Alessandro; Federico, Antonio (J Alzheimers Dis, 2016)
Oculodentodigital dysplasia (ODDD) [MIM 164200] is a rare disorder caused by mutations in the gap junction alpha 1 (GJA1) gene encoding for connexin 43 (Cx43). Typical signs include type III syndactyly, microphtalmia, microdontia, and neurological disturbances. We report a 59-year-old man having clinical symptoms and signs suggestive of ODDD, with some rarely reported features, that is the presence of gross calcifications of basal ganglia and cerebellar nuclei. Mutation analysis of GJA1 gene identified an unreported heterozygous missense mutation [NM_000165.3:c.124 G>C;p.(Glu42Gln)], which may be thought to alter the brain microvessels leading to massive calcifications, as in primary familial brain calcification.
Keywords: Basal Ganglia; Calcinosis; Connexin 43; Craniofacial Abnormalities; DNA Mutational Analysis; Eye Abnormalities; Fingers; Foot Deformities, Congenital; Humans; Male; Middle Aged; Mutation, Missense; Syndactyly; Tomography, X-Ray Computed; Tooth Abnormalities

Omega-3 Fatty Acid Status Enhances the Prevention of Cognitive Decline by B Vitamins in Mild Cognitive Impairment. - Oulhaj, Abderrahim; Jernerén, Fredrik; Refsum, Helga; Smith, A David; de Jager, Celeste A (J Alzheimers Dis, 2016)
A randomized trial (VITACOG) in people with mild cognitive impairment (MCI) found that B vitamin treatment to lower homocysteine slowed the rate of cognitive and clinical decline. We have used data from this trial to see whether baseline omega-3 fatty acid status interacts with the effects of B vitamin treatment. 266 participants with MCI aged ≥70 years were randomized to B vitamins (folic acid, vitamins B6 and B12) or placebo for 2 years. Baseline cognitive test performance, clinical dementia rating (CDR) scale, and plasma concentrations of total homocysteine, total docosahexaenoic and eicosapentaenoic acids (omega-3 fatty acids) were measured. Final scores for verbal delayed recall, global cognition, and CDR sum-of-boxes were better in the B vitamin-treated group according to increasing baseline concentrations of omega-3 fatty acids, whereas scores in the placebo group were similar across these concentrations. Among those with good omega-3 status, 33% of those on B vitamin treatment had global CDR scores >0 compared with 59% among those on placebo. For all three outcome measures, higher concentrations of docosahexaenoic acid alone significantly enhanced the cognitive effects of B vitamins, while eicosapentaenoic acid appeared less effective. When omega-3 fatty acid concentrations are low, B vitamin treatment has no effect on cognitive decline in MCI, but when omega-3 levels are in the upper normal range, B vitamins interact to slow cognitive decline. A clinical trial of B vitamins combined with omega-3 fatty acids is needed to see whether it is possible to slow the conversion from MCI to AD.
Keywords: Aged; Aged, 80 and over; Cognition; Cognitive Dysfunction; Disease Progression; Fatty Acids, Omega-3; Female; Humans; Male; Neuropsychological Tests; Treatment Outcome; Vitamin B Complex

The Online Environment: A Key Variable in the Ethical Response to Complementary and Alternative Medicine for Alzheimer's Disease. - Robillard, Julie M (J Alzheimers Dis, 2016)
Racine et al.'s Ethics Review highlights the challenges associated with the use of complementary and alternative medicine (CAM) in the context of early diagnosis of Alzheimer's disease (AD). As CAM are increasingly promoted and sold on the Internet, the unregulated online environment has the potential to significantly impact the health and well-being of the aging demographic, and in particular of individuals concerned about AD. In this response, the ethical challenges specific to the online environment are discussed and solutions are put forward to empower the aging population to maximize the benefits of the online environment while minimizing the potential harms of misinformation, conflict of interest, and other ethical concerns.
Keywords: Alzheimer Disease; Complementary Therapies; Humans

Pain Assessment in Elderly with Behavioral and Psychological Symptoms of Dementia. - Malara, Alba; De Biase, Giuseppe Andrea; Bettarini, Francesco; Ceravolo, Francesco; Di Cello, Serena; Garo, Michele; Praino, Francesco; Settembrini, Vincenzo; Sgrò, Giovanni; Spadea, Fausto; Rispoli, Vincenzo (J Alzheimers Dis, 2016)
BACKGROUND: Pain is under-detected and undertreated in people with dementia. The present study investigates the prevalence of pain in people with dementia hospitalized in nursing homes that are members of National Association of Third Age Residences (ANASTE) Calabria, and evaluates the association among pain, mood, and behavioral and psychological symptoms of dementia (BPSD). OBJECTIVE: The aim of this study is to define the prevalence of pain in people with dementia in long term care facilities using scales of self-reporting and observational tools and, particularly, to study the relationship between pain and BPSD. METHODS: A prospective observational study was carried out on 233 patients. Pain assessment was performed using self-reporting tools such as the Numeric Rating Scale (NRS) for patients with slight cognitive impairment or no cognitive impairment and observational tools such as Pain Assessment In Advanced Dementia Scale (PAINAD) for patients with moderate or severe cognitive impairment. Mood was evaluated through the Cornell Scale for Depression in Dementia (CSDD) while behavioral problems were assessed through the Cohen-Mansfield Agitation Inventory (CMAI) and Neuropsychiatric Inventory (NPI). RESULTS: Only 42.5% of patients evaluated by NRS provided a reliable answer; of these, 20.4% reported no pain. The percentage of pain evaluated by PAINAD was 51.8% . Analysis of data showed a statistically significant correlation between diagnosis of pain and depressive symptoms, assessed with CSDD (p = 0.0113), as well as by single items of NPI, such as anxiety (p = 0.0362) and irritability (p = 0.0034), and F1 profile (Aggression) of CMAI (p = 0.01). CONCLUSION: This study confirms that self-report alone is not sufficient to assess pain in elderly people with dementia; the observational tool is a necessary and suitable way of assessing pain in patients with cognitive impairment. If not adequately treated, chronic pain can cause depression, agitation, and aggression in patients with dementia.
Keywords: Affect; Aged, 80 and over; Analgesics; Anxiety; Dementia; Depression; Female; Humans; Italy; Logistic Models; Long-Term Care; Male; Multivariate Analysis; Nursing Homes; Pain; Pain Measurement; Prevalence; Prospective Studies; Psychiatric Status Rating Scales; Self Report; Severity of Illness Index

Palmomental Reflex a Relevant Sign in Early Alzheimer's Disease Diagnosis? - Gabelle, Audrey; Gutierrez, Laure-Anne; Dartigues, Jean-François; Ritchie, Karen; Touchon, Jacques; Berr, Claudine (J Alzheimers Dis, 2016)
BACKGROUND: Sophisticated and expensive biomarkers are proposed for the diagnostic of Alzheimer's disease (AD). The amyloid process seems to be early in AD, and brain amyloid load affects the frontal lobe. OBJECTIVE: To determine if certain simple clinical signs, especially frontal-related signs, could help reach an earlier and better diagnosis. METHODS: In the frame of the 3-City cohort, we conducted a nested case-control study comparing incident cases of AD to controls matched for age, gender, and education. The standardized neurological exam included extrapyramidal signs (akinesia, rigidity, rest tremor), pyramidal symptoms (spastic rigidity, Babinski reflex), primitive reflexes (snout, palmomental reflex grasping), and tremor (essential, intentional, head) at the time of diagnosis and two years before. RESULTS: We compared 106 incident AD subjects (mean age at diagnosis 82.2 (SD = 5.9); median MMSE at diagnosis = 23) to 208 matched controls. In patients younger than 80, palmomental reflexes were more frequent in AD than controls, two years before diagnosis (25.0 versus 7.0% , p = 0.03) and at time of diagnosis (30.3 versus 12.3% , p = 0.02). No difference was observed for other signs two years before diagnosis or for patients older than 80. CONCLUSION: Before diagnosis, the clinical examination of AD patients is not strictly normal; the primitive reflexes appear to be pathological. It might be in connection with the frontal amyloid load at an early stage of the disease. Clinical examination can reveal simple and interesting signs that deserve consideration as well as the other more invasive and expensive biomarkers.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cohort Studies; Early Diagnosis; Female; Follow-Up Studies; France; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Reflex

Patients with Mild Alzheimer's Disease Fail When Using Their Working Memory: Evidence from the Eye Tracking Technique. - Fernández, Gerardo; Manes, Facundo; Politi, Luis E; Orozco, David; Schumacher, Marcela; Castro, Liliana; Agamennoni, Osvaldo; Rotstein, Nora P (J Alzheimers Dis, 2016)
Patients with Alzheimer's disease (AD) develop progressive language, visuoperceptual, attentional, and oculomotor changes that can have an impact on their reading comprehension. However, few studies have examined reading behavior in AD, and none have examined the contribution of predictive cueing in reading performance. For this purpose we analyzed the eye movement behavior of 35 healthy readers (Controls) and 35 patients with probable AD during reading of regular and high-predictable sentences. The cloze predictability of words N - 1, and N + 1 exerted an influence on the reader's gaze duration. The predictabilities of preceding words in high-predictable sentences served as task-appropriate cues that were used by Control readers. In contrast, these effects were not present in AD patients. In Controls, changes in predictability significantly affected fixation duration along the sentence; noteworthy, these changes did not affect fixation durations in AD patients. Hence, only in healthy readers did predictability of upcoming words influence fixation durations via memory retrieval. Our results suggest that Controls used stored information of familiar texts for enhancing their reading performance and imply that contextual-word predictability, whose processing is proposed to require memory retrieval, only affected reading behavior in healthy subjects. In AD patients, this loss reveals impairments in brain areas such as those corresponding to working memory and memory retrieval. These findings might be relevant for expanding the options for the early detection and monitoring in the early stages of AD. Furthermore, evaluation of eye movements during reading could provide a new tool for measuring drug impact on patients' behavior.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Eye Movements; Female; Humans; Linear Models; Magnetic Resonance Imaging; Male; Memory Disorders; Memory, Short-Term; Mental Recall; Mental Status Schedule; Predictive Value of Tests; Semantics; Verbal Learning

Perfusion Neuroimaging Abnormalities Alone Distinguish National Football League Players from a Healthy Population. - Amen, Daniel G; Willeumier, Kristen; Omalu, Bennet; Newberg, Andrew; Raghavendra, Cauligi; Raji, Cyrus A (J Alzheimers Dis, 2016)
BACKGROUND: National Football League (NFL) players are exposed to multiple head collisions during their careers. Increasing awareness of the adverse long-term effects of repetitive head trauma has raised substantial concern among players, medical professionals, and the general public. OBJECTIVE: To determine whether low perfusion in specific brain regions on neuroimaging can accurately separate professional football players from healthy controls. METHOD: A cohort of retired and current NFL players (n = 161) were recruited in a longitudinal study starting in 2009 with ongoing interval follow up. A healthy control group (n = 124) was separately recruited for comparison. Assessments included medical examinations, neuropsychological tests, and perfusion neuroimaging with single photon emission computed tomography (SPECT). Perfusion estimates of each scan were quantified using a standard atlas. We hypothesized that hypoperfusion particularly in the orbital frontal, anterior cingulate, anterior temporal, hippocampal, amygdala, insular, caudate, superior/mid occipital, and cerebellar sub-regions alone would reliably separate controls from NFL players. Cerebral perfusion differences were calculated using a one-way ANOVA and diagnostic separation was determined with discriminant and automatic linear regression predictive models. RESULTS: NFL players showed lower cerebral perfusion on average (p < 0.01) in 36 brain regions. The discriminant analysis subsequently distinguished NFL players from controls with 90% sensitivity, 86% specificity, and 94% accuracy (95% CI 95-99). Automatic linear modeling achieved similar results. Inclusion of age and clinical co-morbidities did not improve diagnostic classification. CONCLUSION: Specific brain regions commonly damaged in traumatic brain injury show abnormally low perfusion on SPECT in professional NFL players. These same regions alone can distinguish this group from healthy subjects with high diagnostic accuracy. This study carries implications for the neurological safety of NFL players.

A Phase II Study of Fornix Deep Brain Stimulation in Mild Alzheimer's Disease. - Lozano, Andres M; Fosdick, Lisa; Chakravarty, M Mallar; Leoutsakos, Jeannie-Marie; Munro, Cynthia; Oh, Esther; Drake, Kristen E; Lyman, Christopher H; Rosenberg, Paul B; Anderson, William S; Tang-Wai, David F; Pendergrass, Jo Cara; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Deep brain stimulation (DBS) is used to modulate the activity of dysfunctional brain circuits. The safety and efficacy of DBS in dementia is unknown. OBJECTIVE: To assess DBS of memory circuits as a treatment for patients with mild Alzheimer's disease (AD). METHODS: We evaluated active "on" versus sham "off" bilateral DBS directed at the fornix-a major fiber bundle in the brain's memory circuit-in a randomized, double-blind trial (ClinicalTrials.gov NCT01608061) in 42 patients with mild AD. We measured cognitive function and cerebral glucose metabolism up to 12 months post-implantation. RESULTS: Surgery and electrical stimulation were safe and well tolerated. There were no significant differences in the primary cognitive outcomes (ADAS-Cog 13, CDR-SB) in the "on" versus "off" stimulation group at 12 months for the whole cohort. Patients receiving stimulation showed increased metabolism at 6 months but this was not significant at 12 months. On post-hoc analysis, there was a significant interaction between age and treatment outcome: in contrast to patients  CONCLUSION: DBS for AD was safe and associated with increased cerebral glucose metabolism. There were no differences in cognitive outcomes for participants as a whole, but participants aged≥65 years may have derived benefit while there was possible worsening in patients below age 65 years with stimulation.

Physical and Cognitive Stimulation Using an Exergame in Subjects with Normal Aging, Mild and Moderate Cognitive Impairment. - Ben-Sadoun, Grégory; Sacco, Guillaume; Manera, Valeria; Bourgeois, Jérémy; König, Alexandra; Foulon, Pierre; Fosty, Baptiste; Bremond, François; d'Arripe-Longueville, Fabienne; Robert, Philippe (J Alzheimers Dis, 2016)
BACKGROUND: The use of Serious exerGames (SeG) as enriched environments (EE), which promotes cognitive simulation with physical activity in a positive emotional context, has been proposed to represent a powerful method to slow down the decline due to neurodegenerative diseases (ND), such as Alzheimer's disease (AD). However, so far, no SeG targeting EE has been tested in ND subjects. OBJECTIVE: This study aimed at evaluating the usability and short-term training effects of X-Torp, an action SeG designed for elderly ND subjects with mild cognitive impairment (MCI) and AD. METHODS: X-Torp is a SeG played using the Microsoft® Kinect™. 10 ND subjects and 8 healthy elderly controls (HEC) were enrolled in a 1-month program with three training sessions per week. Usability was evaluated through game time, game performance, the aerobic intensity level reached, perceived emotions, and perceived usability. RESULTS: All participants successfully completed the training program. ND subjects played less and had a lower game performance compared to HEC. During the sessions, ND subjects maintained a light intensity of aerobic activity, while HEC maintained a moderate intensity. Both groups experienced only positive emotions, and reported a 'moderate' to 'high' perceived competence, a 'moderate' game difficulty, and a 'high' interest in the game. CONCLUSION: Usability results suggest that X-Torp represents a usable EE for healthy subjects and persons with MCI and AD. However, in order to reach moderate or high intensity of aerobic activity, X-Torp control modes should be adapted to become more physically stimulating.

PKC Activation Counteracts ADAM10 Deficit in HuD-Silenced Neuroblastoma Cells. - Marchesi, Nicoletta; Amadio, Marialaura; Colombrita, Claudia; Govoni, Stefano; Ratti, Antonia; Pascale, Alessia (J Alzheimers Dis, 2016)
Neuronal ELAV/Hu (nELAV) are RNA-binding proteins that mainly regulate gene expression by increasing the stability and/or translation rate of target mRNAs bearing ARE (adenine and uracil-rich elements) sequences. Among nELAV target transcripts there is ADAM10, an α-secretase involved in the non-amyloidogenic processing of the amyloid-β protein precursor (AβPP) which leads to the production of the neuroprotective sAβPPα peptide. The aim of this study was to evaluate if nELAV depletion affects ADAM10 expression in human SH-SY5Y neuroblastoma cells. We also studied the effects of Bryostatin-1, a molecule able to activate nELAV protein cascade. The specific HuD/nELAV gene silencing decreased both nELAV and ADAM10 protein contents; similar results were obtained by Aβ40 treatment in wild-type SH-SY5Y cells. In HuD-silenced cells, the exposure to Bryostatin-1 counteracted both nELAV and ADAM10 proteins downregulation, by restoring nELAV/ADAM10 basal levels. We also found that sAβPPα release, which seemed not to be compromised by Aβ40 challenge or HuD-silencing, was favored by Bryostatin-1. Overall, these findings strongly suggest that a deficiency in nELAV content negatively affects ADAM10 expression and may play a role in neurodegenerative diseases, which may benefit by molecules activating ELAV cascade.

Posterior Accumulation of Tau and Concordant Hypometabolism in an Early-Onset Alzheimer's Disease Patient with Presenilin-1 Mutation. - Smith, Ruben; Wibom, Moa; Olsson, Tomas; Hägerström, Douglas; Jögi, Jonas; Rabinovici, Gil D; Hansson, Oskar (J Alzheimers Dis, 2016)
It is unclear whether the distribution of tau pathology differs between cases with early-onset familial Alzheimer's disease (AD) and sporadic AD. We present positron emission tomography (PET) data from a young patient with a presenilin-1 mutation (Thr116Asn). 18F-flutemetamol PET showed a distribution of amyloid-β fibrils similar to sporadic AD. However, the pattern of tau pathology, revealed using 18F-AV1451 PET, showed higher uptake in posterior cingulate, precuneus, parietal and occipital cortices compared to late-onset sporadic AD. Further, the tau pathology, but not amyloid pathology, exhibited a very clear inverse relationship with 18F-fluorodeoxyglucose-metabolism, indicating neuronal hypometabolism in regions affected by tau aggregates.
Keywords: Adult; Age of Onset; Alzheimer Disease; Amyloid beta-Peptides; Aniline Compounds; Benzothiazoles; Brain; Brain Mapping; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Positron-Emission Tomography; Presenilin-1; Radiopharmaceuticals; tau Proteins

Postmortem Adult Human Microglia Proliferate in Culture to High Passage and Maintain Their Response to Amyloid-β. - Guo, Ling; Rezvanian, Aras; Kukreja, Lokesh; Hoveydai, Ramez; Bigio, Eileen H; Mesulam, M-Marsel; El Khoury, Joseph; Geula, Changiz (J Alzheimers Dis, 2016)
Microglia are immune cells of the brain that display a range of functions. Most of our knowledge about microglia biology and function is based on cells from the rodent brain. Species variation in the complexity of the brain and differences in microglia response in the primate when compared with the rodent, require use of adult human microglia in studies of microglia biology. While methods exist for isolation of microglia from postmortem human brains, none allow culturing cells to high passage. Thus cells from the same case could not be used in parallel studies and multiple conditions. Here we report a method, which includes use of growth factors such as granulocyte macrophage colony stimulating factor, for successful culturing of adult human microglia from postmortem human brains up to 28 passages without significant loss of proliferation. Such cultures maintained their phenotype, including uptake of the scavenger receptor ligand acetylated low density lipoprotein and response to the amyloid-β peptide, and were used to extend in vivo studies in the primate brain demonstrating that inhibition of microglia activation protects neurons from amyloid-β toxicity. Significantly, microglia cultured from brains with pathologically confirmed Alzheimer's disease displayed the same characteristics as microglia cultured from normal aged brains. The method described here provides the scientific community with a new and reliable tool for mechanistic studies of human microglia function in health from childhood to old age, and in disease, enhancing the relevance of the findings to the human brain and neurodegenerative conditions.

Potentially Inappropriate Prescribing Among People with Dementia in Primary Care: A Retrospective Cross-Sectional Study Using the Enhanced Prescribing Database. - Barry, Heather E; Cooper, Janine A; Ryan, Cristín; Passmore, A Peter; Robinson, A Louise; Molloy, Gerard J; Darcy, Carmel M; Buchanan, Hilary; Hughes, Carmel M (J Alzheimers Dis, 2016)
BACKGROUND: Little is known about prescribing appropriateness for community-dwelling people with dementia (PWD). OBJECTIVE: To estimate potentially inappropriate prescribing (PIP) prevalence among PWD in primary care in Northern Ireland, and to investigate associations between PIP, polypharmacy, age, and gender. METHODS: A retrospective cross-sectional study was conducted, using data from the Enhanced Prescribing Database. Patients were eligible if a medicine indicated for dementia management was dispensed to them during 1 January 2013-31 December 2013. Polypharmacy was indicated by use of ≥4 repeat medications from different drug groups. A subset of the Screening Tool of Older Persons Potentially Inappropriate Prescriptions (STOPP) criteria, comprising 36 indicators, was applied to the dataset. Overall prevalence of PIP and the prevalence per each STOPP criterion was calculated as a proportion of all eligible persons in the dataset. Logistic regression was used to investigate associations between PIP, polypharmacy, age, and gender. RESULTS: The study population comprised 6826 patients. Polypharmacy was observed in 81.5% (n = 5564) of patients. PIP prevalence during the study period was 64.4% (95% CI 63.2- 65.5; n = 4393). The most common instance of PIP was the use of anticholinergic/antimuscarinic medications (25.2%; 95% CI 24.2-26.2; n = 1718). In multivariable analyses, both polypharmacy and gender (being female) were associated with PIP, with odds ratios of 7.6 (95% CI 6.6-8.7) and 1.3 (95% CI 1.2-1.4), respectively. No association was observed between PIP and age, after adjustments for gender and polypharmacy. CONCLUSION: This study identified a high prevalence of PIP in community-dwelling PWD. Future interventions may need to focus on certain therapeutic categories and polypharmacy.

The Presence of Select Tau Species in Human Peripheral Tissues and Their Relation to Alzheimer's Disease. - Dugger, Brittany N; Whiteside, Charisse M; Maarouf, Chera L; Walker, Douglas G; Beach, Thomas G; Sue, Lucia I; Garcia, Angelica; Dunckley, Travis; Meechoovet, Bessie; Reiman, Eric M; Roher, Alex E (J Alzheimers Dis, 2016)
Tau becomes excessively phosphorylated in Alzheimer's disease (AD) and is widely studied within the brain. Further examination of the extent and types of tau present in peripheral tissues and their relation to AD is warranted given recent publications on pathologic spreading. Cases were selected based on the presence of pathological tau spinal cord deposits (n = 18). Tissue samples from sigmoid colon, scalp, abdominal skin, liver, and submandibular gland were analyzed by western blot and enzyme-linked immunosorbent assays (ELISAs) for certain tau species; frontal cortex gray matter was used for comparison. ELISAs revealed brain to have the highest total tau levels, followed by submandibular gland, sigmoid colon, liver, scalp, and abdominal skin. Western blots with antibodies recognizing tau phosphorylated at threonine 231(pT231), serine 396 and 404 (PHF-1), and an unmodified total human tau between residues 159 and 163 (HT7) revealed multiple banding patterns, some of which predominated in peripheral tissues. As submandibular gland had the highest levels of peripheral tau, a second set of submandibular gland samples were analyzed (n = 36; 19 AD, 17 non-demented controls). ELISAs revealed significantly lower levels of pS396 (p = 0.009) and pT231 (p = 0.005) in AD cases but not total tau (p = 0.18). Furthermore, pT231 levels in submandibular gland inversely correlated with Braak neurofibrillary tangle stage (p = 0.04), after adjusting for age at death, gender, and postmortem interval. These results provide evidence that certain tau species are present in peripheral tissues. Of potential importance, submandibular gland pT231 is progressively less abundant with increasing Braak neurofibrillary tangle stage.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Blotting, Western; Colon; Enzyme-Linked Immunosorbent Assay; Female; Frontal Lobe; Gray Matter; Humans; Immunohistochemistry; Liver; Male; Neurofibrillary Tangles; Phosphorylation; Severity of Illness Index; Sex Characteristics; Skin; Submandibular Gland; tau Proteins

Primary Progressive Aphasia in the Network of French Alzheimer Plan Memory Centers. - Magnin, Eloi; Démonet, Jean-François; Wallon, David; Dumurgier, Julien; Troussière, Anne-Cécile; Jager, Alain; Duron, Emmanuelle; Gabelle, Audrey; de la Sayette, Vincent; Volpe-Gillot, Lisette; Tio, Gregory; Evain, Sarah; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Few demographical data about primary progressive aphasia (PPA) are available, and most knowledge regarding PPA is based on tertiary centers' results. OBJECTIVE: Our aims were to describe demographical characteristics of the PPA population in a large sample of PPA patients from the network of French Alzheimer plan memory centers (Sample 1), and to describe the stratification of cerebrospinal fluid (CSF) biomarkers in two different samples of PPA patients (Samples 2 and 3). METHODS: All registered PPA patients in the French Alzheimer's disease (AD) databank (Sample 1: n = 2,035) and a subsample (Sample 2: n = 65) derived from a multicentric prospective cohort with CSF biomarker analysis were analyzed. A multicentric retrospective cohort from language expert tertiary centers (Sample 3: n = 97) with CSF biomarker analysis was added. Sample 3 was added to replicate the CSF results of the Sample 2 and to evaluate repartition of AD pathology in the three variant of PPA according to the latest classification. RESULTS: Non-Fluent/Agrammatic, Logopenic, and Unclassifiable PPA patients (NF/A-Logo-Unclass PPA) were older and more frequent than Semantic PPA patients (2.2 versus 0.8/100,000 inhabitants; p < 0.00001). Male predominance occurred after the age of 80 (p < 0.00001). A higher level of education was observed in the PPA population compared to a typical amnesic AD group. No demographical significant difference between PPA due to AD and not due to AD was observed. The Logopenic variant was most frequent with 85% of AD CSF biomarker profiles (35% in NF/A PPA; 20% in Semantic PPA). CONCLUSION: PPA occurs also in an elderly population, especially in male patients over 80. CSF biomarkers are useful to stratify PPA. The epidemiology of PPA should be further investigated to confirm gender and cognitive reserve role in PPA to better understand the factors and mechanisms leading to this language-predominant deficit during neurodegenerative diseases.

PRNP P39L Variant is a Rare Cause of Frontotemporal Dementia in Italian Population. - Oldoni, Emanuela; Fumagalli, Giorgio G; Serpente, Maria; Fenoglio, Chiara; Scarioni, Marta; Arighi, Andrea; Bruno, Giuseppe; Talarico, Giuseppina; Confaloni, Annamaria; Piscopo, Paola; Nacmias, Benedetta; Sorbi, Sandro; et al. (J Alzheimers Dis, 2016)
The missense P39L variant in the prion protein gene (PRNP) has recently been associated with frontotemporal dementia (FTD). Here, we analyzed the presence of the P39L variant in 761 patients with FTD and 719 controls and found a single carrier among patients. The patient was a 67-year-old male, with a positive family history for dementia, who developed apathy, short term memory deficit, and postural instability at 66. Clinical and instrumental workup excluded prion disease. At MRI, bilateral frontal lobe atrophy was present. A diagnosis of FTD was made, with a mainly apathetic phenotype. The PRNP P39L mutation may be an extremely rare cause of FTD (0.13%).
Keywords: Aged; Atrophy; Frontal Lobe; Frontotemporal Dementia; Genetic Predisposition to Disease; Humans; Italy; Language; Magnetic Resonance Imaging; Male; Memory Disorders; Memory, Short-Term; Neuropsychological Tests; Prion Proteins; Prions; Temporal Lobe

Progranulin Protein Levels in Cerebrospinal Fluid in Primary Neurodegenerative Dementias. - Morenas-Rodriguez, Estrella; Cervera-Carles, Laura; Vilaplana, Eduard; Alcolea, Daniel; Carmona-Iragui, María; Dols-Icardo, Oriol; Ribosa-Nogué, Roser; Muñoz-Llahuna, Laia; Sala, Isabel; Belén Sánchez-Saudinós, M; Blesa, Rafael; Clarimón, Jordi; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Progranulin is implicated in frontotemporal dementia (FTD), but its role in other neurodegenerative disorders is unknown. OBJECTIVE: To investigate the levels of progranulin (PGRN) in cerebrospinal fluid (CSF) in different neurodegenerative dementias and their correlation with levels in plasma in cognitively normal subjects. METHODS: We measured PGRN in CSF in 229 patients with amnestic mild cognitive impairment, Alzheimer's disease dementia, sporadic FTD, dementia with Lewy bodies, corticobasal syndrome, or progressive supranuclear palsy. We also measured PGRN in CSF and plasma in 74 cognitively normal individuals. We examined the correlation between PGRN levels in CSF and diagnosis, cortical thickness, genetic factors and other CSF biomarkers. We also investigated the correlation between plasma and CSF levels of PGRN in cognitively normal individuals. RESULTS: CSF levels did not differ across diagnoses or correlate with cortical thickness. Polymorphism rs5848 in GRN influenced CSF PGRN levels, but APOEɛ4 allele did not. Amyloid-β42, t-tau, p-tau, and YKL-40 levels correlated weakly with PGRN in CSF. We found a weak correlation (r = 0.362) between plasma and CSF PGRN levels in cognitively normal individuals. CONCLUSIONS: Our findings do not support a diagnostic value of CSF PGRN in neurodegenerative diseases. Our data confirm that levels of PGRN in plasma do not reflect accurately levels in CSF in cognitively normal controls. These data should be considered in clinical trials aiming to increase PGRN.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Biomarkers; Dementia; Female; Humans; Intercellular Signaling Peptides and Proteins; Male; Middle Aged; Neurodegenerative Diseases; Polymorphism, Single Nucleotide; tau Proteins

Promising Role of Neuromodulation in Predicting the Progression of Mild Cognitive Impairment to Dementia. - Naro, Antonino; Corallo, Francesco; De Salvo, Simona; Marra, Angela; Di Lorenzo, Giuseppe; Muscarà, Nunzio; Russo, Margherita; Marino, Silvia; De Luca, Rosaria; Bramanti, Placido; Calabrò, Rocco Salvatore (J Alzheimers Dis, 2016)
The differential diagnosis of mild cognitive impairment (MCI) and Alzheimer's disease (AD) is not always straightforward, and the rate of progression of MCI to dementia is not negligible. Thus, there is a need for para-clinical approaches that can improve the differential diagnosis and identify patients that are at risk of progression. There is a growing interest, at present, in the role of the deterioration of brain oscillations as a predictor of MCI-to-AD conversion. For this reason, we experimentally modulated γ-band oscillations (GBO) in a sample of MCI and AD patients and an age-matched healthy elderly group, using a transcranial alternating current stimulation (tACS) protocol that was applied to different cortical sites. We correlated the after-effects of tACS on the GBO and the neuropsychological data, in an attempt to differentiate MCI from AD patients and identify, among the MCI patients, those that could be at potential risk of MCI-to-dementia conversion. MCI patients showed a partial GBO increase and improvement in some neuropsychological tests whereas AD individuals did not show significant tACS after-effects. Notably, some MCI subjects lacked significant neuropsychological and electrophysiological after-effects, similar to AD individuals. In a two-year follow-up, such MCI individuals had converted into AD. Therefore, our data suggest that tACS may support the clinical differential diagnosis of MCI and AD and identify MCI patients who could be at risk of developing dementia. This prediction index may help the clinician to adopt a better prevention/follow-up strategy in such a disabling neurodegenerative disease.

Protein Kinase Activity Decreases with Higher Braak Stages of Alzheimer's Disease Pathology. - Rosenberger, Andrea F N; Hilhorst, Riet; Coart, Elisabeth; García Barrado, Leandro; Naji, Faris; Rozemuller, Annemieke J M; van der Flier, Wiesje M; Scheltens, Philip; Hoozemans, Jeroen J M; van der Vies, Saskia M (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is characterized by a long pre-clinical phase (20-30 years), during which significant brain pathology manifests itself. Disease mechanisms associated with pathological hallmarks remain elusive. Most processes associated with AD pathogenesis, such as inflammation, synaptic dysfunction, and hyper-phosphorylation of tau are dependent on protein kinase activity. The objective of this study was to determine the involvement of protein kinases in AD pathogenesis. Protein kinase activity was determined in postmortem hippocampal brain tissue of 60 patients at various stages of AD and 40 non-demented controls (Braak stages 0-VI) using a peptide-based microarray platform. We observed an overall decrease of protein kinase activity that correlated with disease progression. The phosphorylation of 96.7% of the serine/threonine peptides and 37.5% of the tyrosine peptides on the microarray decreased significantly with increased Braak stage (p-value <0.01). Decreased activity was evident at pre-clinical stages of AD pathology (Braak I-II). Increased phosphorylation was not observed for any peptide. STRING analysis in combination with pathway analysis and identification of kinases responsible for peptide phosphorylation showed the interactions between well-known proteins in AD pathology, including the Ephrin-receptor A1 (EphA1), a risk gene for AD, and sarcoma tyrosine kinase (Src), which is involved in memory formation. Additionally, kinases that have not previously been associated with AD were identified, e.g., protein tyrosine kinase 6 (PTK6/BRK), feline sarcoma oncogene kinase (FES), and fyn-associated tyrosine kinase (FRK). The identified protein kinases are new biomarkers and potential drug targets for early (pre-clinical) intervention.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cohort Studies; Female; Hippocampus; Humans; Male; Middle Aged; Phosphorylation; Protein Kinases; Protein-Serine-Threonine Kinases; Severity of Illness Index

Psychotropic Drug Prescription in Patients with Dementia: Nursing Home Residents Versus Patients Living at Home. - Jacquin-Piques, Agnès; Sacco, Guillaume; Tavassoli, Neda; Rouaud, Olivier; Bejot, Yannick; Giroud, Maurice; Robert, Philippe; Vellas, Bruno; Bonin-Guillaume, Sylvie (J Alzheimers Dis, 2016)
BACKGROUND: Psychotropic drugs are frequently prescribed in nursing homes (NH). Nonetheless, we hoped that institutionalization decreases the number of psychotropic drug classes prescribed, because NH residents may have more psychosocial interventions than patients living at home. OBJECTIVE: The aim was to compare the type and number of psychotropic drugs prescribed in elderly NH residents with dementia with those in community-living patients. METHODS: This cross-sectional study included elderly patients (at least 75 years old) with dementia recorded in the National Alzheimer's data Bank ("Banque Nationale Alzheimer") during the year 2012 and who were taking at least one psychotropic drug. Psychotropic drugs were classified as follows: antidepressant, anxiolytic, hypnotic, and antipsychotic drugs. Patients were classified into three categories of dementia severity according to the MMSE score. RESULTS: Among the 50,932 patients with dementia recorded in the BNA, 40.1% had at least one psychotropic drug prescribed. Most of the patients who were treated by at least one psychotropic drug class had antidepressant therapy (69.0%), whatever their residence type, and 16.1% were treated with antipsychotics. Among the study population, 51.9% of the NH residents and 67.4% of the patients living at home had only one psychotropic drug class prescribed. Living in a NH was significantly associated with the more frequent prescription of anxiolytic, hypnotic, and antipsychotic drugs, and with a greater number of psychotropic drug classes prescribed, whatever the severity of the dementia. CONCLUSION: We underlined the more frequent prescription of psychotropic drugs in NH residents regardless of MMSE scores.
Keywords: Aged; Aged, 80 and over; Chi-Square Distribution; Cross-Sectional Studies; Databases, Factual; Dementia; Drug Prescriptions; Female; Humans; Male; Nursing Homes; Psychotropic Drugs; Residence Characteristics

Purported Interactions of Amyloid-β and Glucocorticoids in Cytotoxicity and Genotoxicity: Implications in Alzheimer's Disease. - Bengoetxea, Xabier; de Cerain, Adela López; Azqueta, Amaya; Ramirez, Maria J (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a complex neurodegenerative disorder characterized by the presence of aggregates of the amyloid-β peptide (Aβ) that are believed to be neurotoxic. One of the purposed damaging mechanisms of Aβ is oxidative insult, which eventually could damage the cellular genome. Stress and associated increases in glucocorticoids (GCs) have been described as a risk factor for the development of AD, although the purported genotoxic effects of GCs have not been fully characterized. Therefore, it is possible to speculate about purported synergistic effects of GCs on the Aβ-driven genotoxic damage. This in vitro study addresses the single and combined cyto/genotoxic effects of Aβ and GCs in SH-SY5Y cells. Cytotoxicity was determined by the MTT assay, and the genotoxic effects were studied using the comet assay. A comet assay derivation allows for measuring the presence of the FPG-sensitive sites (mainly 8-oxoguanines) in the DNA, apart from the DNA strand breaks. Treatment with Aβ (10 μM, 72 h) induced cytotoxicity (35% decrease in cell viability) and DNA strand breaks, but had no significant effect on oxidative DNA damage (FPG sites). Corticosterone showed no effect on cell viability, genotoxicity, or reparation processes. Corticosterone was unable to neither reverse nor potentiate Aβ driven effects. The present results suggest the existence of alternative mechanisms for the Aβ driven damage, not involving oxidative damage of DNA. In addition, could be suggested that the interaction between Aβ and GCs in AD does not seem to involve DNA damage.

A Qualitative Impairment in Face Perception in Alzheimer's Disease: Evidence from a Reduced Face Inversion Effect. - Lavallée, Marie Maxime; Gandini, Delphine; Rouleau, Isabelle; Vallet, Guillaume T; Joannette, Maude; Kergoat, Marie-Jeanne; Busigny, Thomas; Rossion, Bruno; Joubert, Sven (J Alzheimers Dis, 2016)
Prevalent face recognition difficulties in Alzheimer's disease (AD) have typically been attributed to the underlying episodic and semantic memory impairment. The aim of the current study was to determine if AD patients are also impaired at the perceptual level for faces, more specifically at extracting a visual representation of an individual face. To address this question, we investigated the matching of simultaneously presented individual faces and of other nonface familiar shapes (cars), at both upright and inverted orientation, in a group of mild AD patients and in a group of healthy older controls matched for age and education. AD patients showed a reduced inversion effect (i.e., larger performance for upright than inverted stimuli) for faces, but not for cars, both in terms of error rates and response times. While healthy participants showed a much larger decrease in performance for faces than for cars with inversion, the inversion effect did not differ significantly for faces and cars in AD. This abnormal inversion effect for faces was observed in a large subset of individual patients with AD. These results suggest that AD patients have deficits in higher-level visual processes, more specifically at perceiving individual faces, a function that relies on holistic representations specific to upright face stimuli. These deficits, combined with their memory impairment, may contribute to the difficulties in recognizing familiar people that are often reported in patients suffering from the disease and by their caregivers.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Face; Facial Recognition; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Orientation; Pattern Recognition, Visual; Perceptual Disorders; Photic Stimulation; Psychiatric Status Rating Scales; Reaction Time; Statistics as Topic

Quantitative Neuroimaging Software for Clinical Assessment of Hippocampal Volumes on MR Imaging. - Ahdidan, Jamila; Raji, Cyrus A; DeYoe, Edgar A; Mathis, Jedidiah; Noe, Karsten Ø; Rimestad, Jens; Kjeldsen, Thomas K; Mosegaard, Jesper; Becker, James T; Lopez, Oscar (J Alzheimers Dis, 2016)
BACKGROUND: Multiple neurological disorders including Alzheimer's disease (AD), mesial temporal sclerosis, and mild traumatic brain injury manifest with volume loss on brain MRI. Subtle volume loss is particularly seen early in AD. While prior research has demonstrated the value of this additional information from quantitative neuroimaging, very few applications have been approved for clinical use. Here we describe a US FDA cleared software program, NeuroreaderTM, for assessment of clinical hippocampal volume on brain MRI. OBJECTIVE: To present the validation of hippocampal volumetrics on a clinical software program. METHOD: Subjects were drawn (n = 99) from the Alzheimer Disease Neuroimaging Initiative study. Volumetric brain MR imaging was acquired in both 1.5 T (n = 59) and 3.0 T (n = 40) scanners in participants with manual hippocampal segmentation. Fully automated hippocampal segmentation and measurement was done using a multiple atlas approach. The Dice Similarity Coefficient (DSC) measured the level of spatial overlap between NeuroreaderTM and gold standard manual segmentation from 0 to 1 with 0 denoting no overlap and 1 representing complete agreement. DSC comparisons between 1.5 T and 3.0 T scanners were done using standard independent samples T-tests. RESULTS: In the bilateral hippocampus, mean DSC was 0.87 with a range of 0.78-0.91 (right hippocampus) and 0.76-0.91 (left hippocampus). Automated segmentation agreement with manual segmentation was essentially equivalent at 1.5 T (DSC = 0.879) versus 3.0 T (DSC = 0.872). CONCLUSION: This work provides a description and validation of a software program that can be applied in measuring hippocampal volume, a biomarker that is frequently abnormal in AD and other neurological disorders.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Female; Hippocampus; Humans; Image Interpretation, Computer-Assisted; Magnetic Resonance Imaging; Male; Middle Aged; Software

Relative Alterations in Blood-Based Levels of Sestrin in Alzheimer's Disease and Mild Cognitive Impairment Patients. - Rai, Nitish; Kumar, Rahul; Desai, Gaurav Rajesh; Venugopalan, G; Shekhar, Shashank; Chatterjee, Prasun; Tripathi, Manjari; Upadhyay, Ashish Datt; Dwivedi, Sadanand; Dey, Aparajit B; Dey, Sharmistha (J Alzheimers Dis, 2016)
Sestrins (sesn) are highly conserved proteins that play an important neuroprotective role, in part as a consequence of their antioxidative capacity, which prevents reactive oxygen species formation. In this study, we evaluated the concentrations of sesn1 and sesn2 in the serum of 41 Alzheimer's disease (AD) patients, 27 mild cognitive impairment (MCI), and 60 elderly controls, by surface plasmon resonance, which was validated by using western blot. Moreover, the mRNA level of sestrins in all the study groups was determined by real time polymerase chain reaction. The results showed significant overexpression of serum sesn2 protein and mRNA levels in the AD group compared to MCI and elderly control groups. A difference in serum sesn2 concentration between MCI and the control group was also evident. ROC analysis showed highly sensitive, selective cutoff values for sens2 in the differentiation of AD, MCI, and controls. No significant difference in sesn1 level was observed among the study groups. This study highlights the important role of sesn2 in the progression of the AD, indicating its potential utility as a protein marker in this devastating disease.

Self-Perceived Quality of Life Among Patients with Alzheimer's Disease: Two Longitudinal Models of Analysis. - Conde-Sala, Josep L; Turró-Garriga, Oriol; Portellano-Ortiz, Cristina; Viñas-Diez, Vanesa; Gascón-Bayarri, Jordi; Reñé-Ramírez, Ramón (J Alzheimers Dis, 2016)
The objective was to analyze the factors that influence self-perceived quality of life (QoL) in patients with Alzheimer's disease (AD), contrasting two different longitudinal models. A total of 127 patients were followed up over 24 months. The instruments applied were: Quality of Life in Alzheimer's Disease scale (QoL-AD), Geriatric Depression Scale-15, Anosognosia Questionnaire-Dementia, Disability Assessment in Dementia, Neuropsychiatric Inventory, and the Mini-Mental State Examination. Two models for grouping patients were tested: 1) Baseline score on the QoL-AD (QoL-Baseline), and 2) Difference in QoL-AD score between baseline and follow-up (QoL-Change). Generalized estimating equations were used to analyze longitudinal data, and multinomial regression analyses were performed. Over the follow-up period the QoL-Baseline model showed greater variability between groups (Wald χ2 = 172.3, p < 0.001) than did the QoL-Change model (Wald χ2  = 1.7, p = 0.427). In the QoL-Baseline model the predictive factors were greater depression (odds ratio [OR] = 1.20; 95% CI: 1.00- 1.45) and lower functional ability (OR = 0.92; 95% CI: 0.85- 0.99) for the Low QoL group (< 33 QoL-AD), and less depression (OR = 0.68; 95% CI: 0.52- 0.88), more anosognosia (OR = 1.07; 95% CI: 1.01- 1.13), and fewer neuropsychiatric symptoms (OR = 0.95; 95% CI: 0.91- 0.99) for the High-QoL group (>37 QoL-AD). The model based on baseline scores (QoL-Baseline) was better than the QoL-Change model in terms of identifying trajectories and predictors of QoL in AD.

Self-Reported Traumatic Brain Injury and Mild Cognitive Impairment: Increased Risk and Earlier Age of Diagnosis. - LoBue, Christian; Denney, David; Hynan, Linda S; Rossetti, Heidi C; Lacritz, Laura H; Hart, John; Womack, Kyle B; Woon, Fu L; Cullum, C Munro (J Alzheimers Dis, 2016)
This study examined whether history of traumatic brain injury (TBI) is associated with increased risk and earlier onset of mild cognitive impairment (MCI). Subjects with MCI (n = 3,187) and normal cognition (n = 3,244) were obtained from the National Alzheimer's Coordinating Center database. TBI was categorized based on lifetime reported TBI with loss of consciousness (LOC) without chronic deficit. Logistic regression was used to examine TBI history as a predictor of MCI, adjusted for demographics, apolipoprotein E-ɛ4 (ApoE4), a composite vascular risk score, and history of psychiatric factors. ANCOVA was used to examine whether age at MCI diagnosis and estimated age of onset differed between those with (TBI+) and without (TBI-) a history of TBI. TBI history was a significant predictor (p <  0.01) and associated with increased odds of MCI diagnosis in unadjusted (OR = 1.25; 95% CI = 1.05-1.49) and adjusted models, accounting for age, education, ApoE4, and a composite vascular score (OR = 1.32; 95% CI = 1.10-1.58). This association, however, was largely attenuated (OR = 1.14; 95% CI = 0.94-1.37; p = 0.18) after adjustment for reported history of depression. MCI was diagnosed a mean of 2.3 years earlier (p <  0.001) in the TBI+ group, and although TBI+ subjects had an estimated mean of decline 1.7 years earlier, clinician-estimated age of onset failed to differ (p = 0.13) when gender and psychiatric factors were controlled. This is the first report of a possible role for TBI as a risk factor in MCI, but its association may be related to other factors such as gender and depression and requires further investigation.
Keywords: Age of Onset; Aged; Apolipoproteins E; Brain Injuries, Traumatic; Cognitive Dysfunction; Cohort Studies; Databases, Factual; Depression; Educational Status; Female; Humans; Logistic Models; Male; Risk Factors; Self Report; United States

Serum Adiponectin Levels, Neuroimaging, and Cognition in the Mayo Clinic Study of Aging. - Wennberg, Alexandra M V; Gustafson, Deborah; Hagen, Clinton E; Roberts, Rosebud O; Knopman, David; Jack, Clifford; Petersen, Ronald C; Mielke, Michelle M (J Alzheimers Dis, 2016)
BACKGROUND: Adiponectin, a protein involved in inflammatory pathways, may impact the development and progression of Alzheimer's disease (AD). Adiponectin levels have been associated with mild cognitive impairment (MCI) and AD; however, its association with Alzheimer-associated neuroimaging and cognitive outcomes is unknown. OBJECTIVE: Determine the cross-sectional association between plasma adiponectin and neuroimaging and cognitive outcomes in an older population-based sample. METHODS: Multivariable adjusted regression models were used to investigate the association between plasma adiponectin and hippocampal volume (HVa), PiB-PET, FDG PET, cortical thickness, MCI diagnosis, and neuropsychological test performance. Analyses included 535 non-demented participants aged 70 and older enrolled in the Mayo Clinic Study of Aging. RESULTS: Women had higher adiponectin than men (12,631 ng/mL versus 8,908 ng/mL, p < 0.001). Among women, higher adiponectin was associated with smaller HVa (B = -0.595; 95% CI -1.19, -0.005), poorer performance in language (B = -0.676; 95% CI -1.23, -0.121), and global cognition (B = -0.459; 95% CI -0.915, -0.002), and greater odds of a MCI diagnosis (OR = 6.23; 95% CI 1.20, 32.43). In analyses stratified by sex and elevated amyloid (PiB-PET SUVR >1.4), among women with elevated amyloid, higher adiponectin was associated with smaller HVa (B = -0.723; 95% CI -1.43, -0.014), poorer performance in memory (B = -1.02; 95% CI -1.73, -0.312), language (B = -0.896; 95% CI -1.58, -0.212), global cognition (B = -0.650; 95% CI -1.18, -0.116), and greater odds of MCI (OR = 19.34; 95% CI 2.72, 137.34). CONCLUSION: Higher plasma adiponectin was associated with neuroimaging and cognitive outcomes among women. Longitudinal analyses are necessary to determine whether higher adiponectin predicts neurodegeneration and cognitive decline.

Serum Uric Acid and Its Association with Longitudinal Cognitive Change Among Urban Adults. - Beydoun, May A; Canas, Jose-Atilio; Dore, Gregory A; Beydoun, Hind A; Rostant, Ola S; Fanelli-Kuczmarski, Marie T; Evans, Michele K; Zonderman, Alan B (J Alzheimers Dis, 2016)
Uric acid, a waste metabolite among humans, was linked to various cognitive outcomes. We describe sex and age-group specific associations of baseline serum uric acid (SUAbase) and significant change in SUA (ΔSUA: 1 versus 0 = decrease versus no change; 2 versus 0 = increase versus no change) with longitudinal annual rate of cognitive change among a large sample of urban adults. Data from the Healthy Aging in Neighborhoods of Diversity across the Life Span study, 2004-2009 (visit 1) and 2009-2013 (visit 2) were used. Of 3,720 adults selected at baseline (age range: 30-64 y), complete data were available for N = 1,487-1,602 with a mean repeat of 1.5-1.7 visits/participant. Cognitive test domains spanned attention, processing speed, learning/memory, executive function, visuo-spatial/visuo-construction ability, language/verbal, and global cognitive function. SUA was measured at both visits. Multiple mixed-effects regression analyses were conducted. In the total population, a higher SUAbase was associated with a faster annual rate of decline on a measure of visual memory/visuo-construction ability (the Benton Visual Retention Test) by γ= 0.07 with a standard error of 0.02, p < 0.001. Among older men, a significant increase in SUA was associated with slower decline on a test of attention/processing speed, namely Trailmaking test, Part A, measured in seconds to completion (γ= -6.91 ± 1.73, p < 0.001). In sum, a higher SUAbase was associated with faster cognitive decline over-time in a visual memory/visuo-construction ability test. ΔSUA had particular beneficial effects of an increasing ΔSUA on the domain of attention/processing speed among older men. More longitudinal studies are needed to examine cognitive domain-specific effects of over-time change in SUA within sex and age groups.

So Close Yet So Far: Executive Contribution to Memory Processing in Behavioral Variant Frontotemporal Dementia. - Bertoux, Maxime; Ramanan, Siddharth; Slachevsky, Andrea; Wong, Stephanie; Henriquez, Fernando; Musa, Gada; Delgado, Carolina; Flanagan, Emma; Bottlaender, Michel; Sarazin, Marie; Hornberger, Michael; Dubois, Bruno (J Alzheimers Dis, 2016)
BACKGROUND: Memory impairment in behavioral variant frontotemporal dementia (bvFTD) is traditionally considered to be mild and attributed to prefrontal cortex dysfunction. Recent studies, however, indicated that some patients can present with a memory impairment of the hippocampal type, showing storage and consolidation deficits in addition to the more executive/prefrontal related encoding and strategic difficulties. OBJECTIVE: This study aimed to study the relationship between executive functions (EF) and memory processes in bvFTD via a data-driven approach. METHOD: Participants consisted of 71 bvFTD (among which 60.6% had a lumbar puncture showing non-Alzheimer biomarker profile) and 60 controls (among which 45% had amyloid imaging showing a normal profile). EF were assessed by the Frontal Assessment Battery, semantic/lexical verbal fluency tests, and forward/backward digit spans. Patients were split into amnestic (n = 33) and non-amnestic (n = 38) subgroups based on normative data (total recall score) from the Free and Cued Selective Reminding Test (FCSRT). Relationships between FCSRT subscores and EF measures were explored through hierarchical clustering analysis, partial correlation analysis with an EF component, and automated linear modeling. RESULTS: Convergent findings across the statistical approaches show that, overall, memory performance was independent from EF in bvFTD whereas the relationship was stronger in controls. Indeed, in bvFTD, memory performance did not cluster with EF, was not correlated with the EF component, and was only partially (4% - 12.7%) predicted by EF. DISCUSSION: These findings show that executive dysfunctions cannot solely explain the memory deficits occurring in bvFTD. Indeed, some patients present with a genuine amnesia affecting storage and consolidation abilities, which are independent from executive dysfunctions. On the clinical level, this study highlights the importance of revising the neuropsychological diagnosis criteria for bvFTD.

Specific Binding of Cu(II) Ions to Amyloid-Beta Peptides Bound to Aggregation-Inhibiting Molecules or SDS Micelles Creates Complexes that Generate Radical Oxygen Species. - Tiiman, Ann; Luo, Jinghui; Wallin, Cecilia; Olsson, Lisa; Lindgren, Joel; Jarvet, Jϋri; Per, Roos; Sholts, Sabrina B; Rahimipour, Shai; Abrahams, Jan Pieter; Karlström, Amelie Eriksson; Gräslund, Astrid; et al. (J Alzheimers Dis, 2016)
Aggregation of the amyloid-beta (Aβ) peptide into insoluble plaques is a major factor in Alzheimer's disease (AD) pathology. Another major factor in AD is arguably metal ions, as metal dyshomeostasis is observed in AD patients, metal ions modulate Aβ aggregation, and AD plaques contain numerous metals including redox-active Cu and Fe ions. In vivo, Aβ is found in various cellular locations including membranes. So far, Cu(II)/Aβ interactions and ROS generation have not been investigated in a membrane environment. Here, we study Cu(II) and Zn(II) interactions with Aβ bound to SDS micelles or to engineered aggregation-inhibiting molecules (the cyclic peptide CP-2 and the ZAβ3(12-58)Y18L Affibody molecule). In all studied systems the Aβ N-terminal segment was found to be unbound, unstructured, and free to bind metal ions. In SDS micelles, Aβ was found to bind Cu(II) and Zn(II) with the same ligands and the same KD as in aqueous solution. ROS was generated in all Cu(II)/Aβ complexes. These results indicate that binding of Aβ to membranes, drugs, and other entities that do not interact with the Aβ N-terminal part, appears not to compromise the N-terminal segment's ability to bind metal ions, nor impede the capacity of N-terminally bound Cu(II) to generate ROS.

Standardized Uptake Value Ratio-Independent Evaluation of Brain Amyloidosis. - Chincarini, Andrea; Sensi, Francesco; Rei, Luca; Bossert, Irene; Morbelli, Silvia; Guerra, Ugo Paolo; Frisoni, Giovanni; Padovani, Alessandro; Nobili, Flavio (J Alzheimers Dis, 2016)
The assessment of in vivo18F images targeting amyloid deposition is currently carried on by visual rating with an optional quantification based on standardized uptake value ratio (SUVr) measurements. We target the difficulties of image reading and possible shortcomings of the SUVr methods by validating a new semi-quantitative approach named ELBA. ELBA involves a minimal image preprocessing and does not rely on small, specific regions of interest (ROIs). It evaluates the whole brain and delivers a geometrical/intensity score to be used for ranking and dichotomic assessment. The method was applied to adniimages 18F-florbetapir images from the ADNI database. Five expert readers provided visual assessment in blind and open sessions. The longitudinal trend and the comparison to SUVr measurements were also evaluated. ELBA performed with area under the roc curve (AUC) = 0.997 versus the visual assessment. The score was significantly correlated to the SUVr values (r = 0.86, p < 10-4). The longitudinal analysis estimated a test/retest error of ≃2.3%. Cohort and longitudinal analysis suggests that the ELBA method accurately ranks the brain amyloid burden. The expert readers confirmed its relevance in aiding the visual assessment in a significant number (85) of difficult cases. Despite the good performance, poor and uneven image quality constitutes the major limitation.

Stimulating the Activity of Amyloid-Beta Degrading Enzymes: A Novel Approach for the Therapeutic Manipulation of Amyloid-Beta Levels. - Kuruppu, Sanjaya; Rajapakse, Niwanthi W; Spicer, Alexander J; Parkington, Helena C; Smith, A Ian (J Alzheimers Dis, 2016)
Alzheimer's disease is a debilitating neurological disease placing significant burden on health care budgets around the world. It is widely believed that accumulation of amyloid-beta (Aβ) in the brain is a key event that initiates neurodegeneration, thus the clearance of Aβ from brain could be a key therapeutic strategy. Aβ exists in an equilibrium in healthy individuals, and recent research would suggest that dysfunction in the clearance pathways is the driving force behind its accumulation. One mechanism of clearance is proteolytic degradation by enzymes, and increasing the expression of these enzymes in animal models of Alzheimer's disease has indeed shown promising results. This approach could be challenging to translate into the clinic given the likely need for genetic manipulation. We hypothesize that stimulating the activity of these enzymes (as opposed to increasing expression) through pharmacological agents will enhance degradation or at least prevent amyloid deposition, and is therefore another potentially novel avenue to manipulate Aβ levels for therapeutic purposes. We discuss the recent research supporting this hypothesis as well as possible drawbacks to this approach.

Strategies for improving memory: a randomized trial of memory groups for older people, including those with mild cognitive impairment. - Kinsella, Glynda J; Ames, David; Storey, Elsdon; Ong, Ben; Pike, Kerryn E; Saling, Michael M; Clare, Linda; Mullaly, Elizabeth; Rand, Elizabeth (J Alzheimers Dis, 2016)
BACKGROUND: Governments are promoting the importance of maintaining cognitive health into older age to minimize risk of cognitive decline and dementia. Older people with amnestic mild cognitive impairment (aMCI) are particularly vulnerable to memory challenges in daily activities and are seeking ways to maintain independent living. OBJECTIVE: To evaluate the effectiveness of memory groups for improving memory strategies and memory ability of older people, especially those with aMCI. METHODS: 113 healthy older adults (HOA) and 106 adults with aMCI were randomized to a six-week memory group or a waitlist control condition. Outcome was evaluated through knowledge and use of memory strategies, memory ability (self-report and neuropsychological tests), and wellbeing. Assessments included a six-month follow-up. RESULTS: Using intention to treat analyses, there were intervention effects for HOA and aMCI groups in strategy knowledge (HOA: η2= 0.20; aMCI: η2= 0.06), strategy use (HOA: η2= 0.18; aMCI: η2= 0.08), and wellbeing (HOA: η2= 0.11; aMCI: η2= 0.05). There were also intervention effects in the HOA group, but not the aMCI group, in self-reported memory ability (η2= 0.06) and prospective memory tests (η2= 0.02). By six-month follow-up, gains were found on most HOA outcomes. In the aMCI group gains were found in strategy use, and by this stage, gains in prospective memory were also found. CONCLUSION: Memory groups can engage older people in techniques for maintaining cognitive health and improve memory performance, but more modest benefits are seen for older adults with aMCI.
Keywords: Aged; Aged, 80 and over; Aging; Cognitive Dysfunction; Cross-Over Studies; Female; Humans; Male; Memory, Episodic; Neuropsychological Tests; Self Report

Stroke, Vascular Dementia, and Alzheimer's Disease: Molecular Links. - Vijayan, Murali; Reddy, P Hemachandra (J Alzheimers Dis, 2016)
Stroke is a brain disease that occurs when blood flow stops, resulting in reduced oxygen supply to neurons. Stroke occurs at any time and at any age, but increases after the age of 55. It is the second leading cause of death and the third leading cause of disability-adjusted, life-years. The pathophysiology of ischemic stroke is complex and recent molecular, cellular, and animal models and postmortem brain studies have revealed that multiple cellular changes have been implicated, including oxidative stress/mitochondrial dysfunction, inflammatory responses, micro RNA alterations, and marked changes in brain proteins. These cellular changes provide new information for developing therapeutic strategies for ischemic stroke treatment. Research also revealed that stroke increases with a number of modifiable factors and most strokes can be prevented and/or controlled through pharmacological or surgical interventions and lifestyle changes. Ischemic stroke is the major risk factor for vascular dementia and Alzheimer's disease. This review summarizes the latest research findings on stroke, including causal factors and molecular links between stroke and vascular disease/Alzheimer's disease.

Subjective Memory Complaints in APOEɛ4 Carriers are Associated with High Amyloid-β Burden. - Zwan, Marissa D; Villemagne, Victor L; Doré, Vincent; Buckley, Rachel; Bourgeat, Pierrick; Veljanoski, Robyn; Salvado, Olivier; Williams, Rob; Margison, Laura; Rembach, Alan; Macaulay, S Lance; Martins, Ralph; et al. (J Alzheimers Dis, 2016)
BACKGROUND: APOEɛ4 genotype and aging have been identified as risk factors for Alzheimer's disease (AD). In addition, subjective memory complaints (SMC) might be a first clinical expression of the effect of AD pathology on cognitive functioning. OBJECTIVE: To assess whether APOEɛ4 genotype, age, SMC, and episodic memory are risk factors for high amyloid-β (Aβ) burden in cognitively normal elderly. METHODS: 307 cognitively normal participants (72.7 ± 6.8 years, 53% female, 55% SMC) from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study underwent amyloid PET and APOE genotyping. Logistic regression analyses were performed to determine the association of APOEɛ4 genotype, age, SMC, and episodic memory with Aβ pathology. RESULTS: Odds of high Aβ burden were greater at an older age (OR = 3.21; 95% CI = 1.68-6.14), when SMC were present (OR = 1.90; 95% CI = 1.03-3.48), and for APOEɛ4 carriers (OR = 7.49; 95% CI = 3.96-14.15), while episodic memory was not associated with odds of high Aβ burden. Stratified analyses showed that odds of SMC for high Aβ burden were increased in specifically APOEɛ4 carriers (OR = 4.58, 95% CI = 1.83-11.49) and younger participants (OR = 3.73, 95% CI = 1.39-10.01). CONCLUSION: Aging, APOEɛ4 genotype, and SMC were associated with high Aβ burden. SMC were especially indicative of high Aβ burden in younger participants and in APOEɛ4 carriers. These findings suggest that selection based on the presence of SMC, APOEɛ4 genotype and age may help identify healthy elderly participants with high Aβ burden eligible for secondary prevention trials.
Keywords: Aged; Aging; Amyloid beta-Peptides; Aniline Compounds; Apolipoprotein E4; Benzothiazoles; Brain; Cognition Disorders; Female; Genotyping Techniques; Heterozygote; Humans; Logistic Models; Male; Neuropsychological Tests; Positron-Emission Tomography; Radiopharmaceuticals; Thiazoles

A Systematic Review and Meta-Analysis of the Association between Helicobacterpylori Infection and Dementia. - Shindler-Itskovitch, Tali; Ravona-Springer, Ramit; Leibovitz, Arthur; Muhsen, Khitam (J Alzheimers Dis, 2016)
BACKGROUND: A positive association between Helicobacter pylori infection and dementia has been reported, yet findings are inconsistent. OBJECTIVE: To examine the association between H. pylori infection and dementia. METHODS: A literature search was performed using the databases OVID-Medline, Institute of Scientific Information Web of Science, and EMBASE. The meta-analysis was conducted using the random effects model. The primary analysis included studies in which the exposure variable was presence of H. pylori infection (yes versus no) and the outcome was incident dementia (yes versus no), which was pre-selected as the end-result of gradual cognitive decline overtime. Publication bias was explored using funnel plot and the Egger regression intercept. RESULTS: A total of 260 records were identified; 13 addressed cognition and/or dementia in relation to H. pylori infection, of which only seven were included in the meta-analysis. The primary analysis showed a significant positive association between H. pylori infection and dementia; pooled odds ratio 1.71 (95% CI 1.17-2.49) (pv = 0.01). No significant evidence of publication bias was found. CONCLUSIONS: H. pylori may play a role in the etiology of dementia. Identification of the biological mechanisms of such association is needed, as well as assessment of the impact of H. pylori therapy on the risk and progression of dementia.

Tau Accumulation in Primary Motor Cortex of Variant Alzheimer's Disease with Spastic Paraparesis. - Lyoo, Chul Hyoung; Cho, Hanna; Choi, Jae Yong; Hwang, Mi Song; Hong, Sang Kyoon; Kim, Yun Joong; Ryu, Young Hoon; Lee, Myung Sik (J Alzheimers Dis, 2016)
We studied topographic distribution of tau and amyloid-β in a patient with variant Alzheimer's disease with spastic paraparesis (VarAD) by comparing AD patients. The proband developed progressive memory impairment, dysarthria, and spastic paraparesis at age 23. Heterozygous missense mutation (L166P) was found in exon 6 of presenilin-1 gene. The proband showed prominently increased amyloid binding in striatum and cerebellum and asymmetrical tau binding in the primary sensorimotor cortex contralateral to the side more affected by spasticity. We suspect that upper motor neuron dysfunctions may be attributed to excessive abnormal tau accumulation rather than amyloid-β in the primary motor cortex.
Keywords: Adult; Aged; Alzheimer Disease; Aniline Compounds; Brain Mapping; Carbolines; Female; Humans; Male; Motor Cortex; Mutation, Missense; Paraparesis, Spastic; Positron-Emission Tomography; Presenilin-1; Radiopharmaceuticals; Stilbenes; tau Proteins

Timely Diagnosis for Alzheimer's Disease: A Literature Review on Benefits and Challenges. - Dubois, Bruno; Padovani, Alessandro; Scheltens, Philip; Rossi, Andrea; Dell'Agnello, Grazia (J Alzheimers Dis, 2016)
BACKGROUND: Timely diagnosis of Alzheimer's disease (AD) refers to a diagnosis at the stage when patients come to the attention of clinicians because of concerns about changes in cognition, behavior, or functioning and can be still free of dementia and functionally independent. OBJECTIVES: To comprehensively review existing scientific evidence on the benefits and potential challenges of making a timely diagnosis of AD. METHODS: Relevant studies were identified by searching electronic databases (Medline, Embase) and bibliographies for studies published in English between 1 January 2000 and 2 June 2014 on the consequences of a timely diagnosis of AD. RESULTS: Nine studies were identified that investigated the consequences of diagnosing AD at the initial stages; none were specifically focused on prodromal AD. A timely diagnosis potentially offers the opportunities of early intervention, implementation of coordinated care plans, better management of symptoms, patient safety, cost savings, and postponement of institutionalization. Barriers to making a timely diagnosis include stigma, suicide risk, lack of training, diagnostic uncertainty, shortage of specialized diagnostic services, and the reluctance of healthcare providers to make a diagnosis when no effective disease-modifying options are available. CONCLUSIONS: Despite its potential benefits, few published studies have explored the advantages or risks of a timely diagnosis of AD. In light of the cultural shift toward diagnosis at the initial stage of the disease continuum, when the patient does not yet have dementia, more investigations are needed to evaluate the benefits and address the barriers that may impede making a timely AD diagnosis.
Keywords: Alzheimer Disease; Databases, Bibliographic; Humans; Time Factors

Transcriptional Analysis of Blood Lymphocytes and Skin Fibroblasts, Keratinocytes, and Endothelial Cells as a Potential Biomarker for Alzheimer's Disease. - Mukhamedyarov, Marat A; Rizvanov, Albert A; Yakupov, Eduard Z; Zefirov, Andrey L; Kiyasov, Andrey P; Reis, Helton J; Teixeira, Antônio L; Vieira, Luciene B; Lima, Luciana M; Salafutdinov, Ilnur I; Petukhova, Elena O; Khaiboullina, Svetlana F; et al. (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a devastating and progressive form of dementia that is typically associated with a build-up of amyloid-β plaques and hyperphosphorylated and misfolded tau protein in the brain. Presently, there is no single test that confirms AD; therefore, a definitive diagnosis is only made after a comprehensive medical evaluation, which includes medical history, cognitive tests, and a neurological examination and/or brain imaging. Additionally, the protracted prodromal phase of the disease makes selection of control subjects for clinical trials challenging. In this study we have utilized a gene-expression array to screen blood and skin punch biopsy (fibroblasts, keratinocytes, and endothelial cells) for transcriptional differences that may lead to a greater understanding of AD as well as identify potential biomarkers. Our analysis identified 129 differentially expressed genes from blood of dementia cases when compared to healthy individuals, and four differentially expressed punch biopsy genes between AD subjects and controls. Additionally, we identified a set of genes in both tissue compartments that showed transcriptional variation in AD but were largely stable in controls. The translational products of these variable genes are involved in the maintenance of the Golgi structure, regulation of lipid metabolism, DNA repair, and chromatin remodeling. Our analysis potentially identifies specific genes in both tissue compartments that may ultimately lead to useful biomarkers and may provide new insight into the pathophysiology of AD.

Two Phase 2 Multiple Ascending-Dose Studies of Vanutide Cridificar (ACC-001) and QS-21 Adjuvant in Mild-to-Moderate Alzheimer's Disease. - Pasquier, Florence; Sadowsky, Carl; Holstein, Ann; Leterme, Ghislaine Le Prince; Peng, Yahong; Jackson, Nicholas; Fox, Nick C; Ketter, Nzeera; Liu, Enchi; Ryan, J Michael (J Alzheimers Dis, 2016)
Vanutide cridificar (ACC-001), an immunotherapeutic vaccine, is a potentially disease-modifying therapy that aims to reduce brain amyloid-β (Aβ) plaques in patients with Alzheimer's disease (AD). ACC-001 was evaluated in two phase 2a, multicenter, randomized, third party-unblinded, placebo-controlled, multiple ascending-dose studies of ACC-001 (3μg, 10μg, 30μg) with and without QS-21 adjuvant that enrolled patients with mild-to-moderate AD (n = 245). Patients were treated with up to five doses of study vaccine or placebo and followed for safety and tolerability (primary objective) and anti-Aβ IgG immunogenicity (secondary objective) up to 12 months after the last vaccination. Exploratory assessments included cognitive/functional measures, brain magnetic resonance imaging (MRI) volumetry, and pharmacodynamic markers in plasma and cerebrospinal fluid (CSF). The most frequent treatment-emergent adverse events (≥10%) were local injection reactions and headache. Amyloid-related imaging abnormalities with vasogenic edema occurred in two (0.8%) patients (ACC-001 30μg + QS-21; ACC-001 10μg). ACC-001 + QS-21 elicited consistently higher peak and sustained anti-Aβ IgG titers compared with ACC-001 alone. Plasma Aβx-40 was significantly higher in all ACC-001 + QS-21 groups versus placebo (weeks 16-56), with no evidence of dose response. Exploratory cognitive evaluations, volumetric brain MRI, and CSF biomarkers did not show differences or trends between treatment groups and placebo. ACC-001 with or without QS-21 adjuvant has an acceptable safety profile in patients with mild-to-moderate AD.
Keywords: Adjuvants, Immunologic; Aged; Alzheimer Disease; Amyloid beta-Peptides; Antipsychotic Agents; Dose-Response Relationship, Drug; Female; Follow-Up Studies; Humans; Interferon-gamma; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Peptide Fragments; Recombinant Fusion Proteins; Saponins; Single-Blind Method; Treatment Outcome

Unmet Needs of Community-Dwelling Primary Care Patients with Dementia in Germany: Prevalence and Correlates. - Eichler, Tilly; Thyrian, Jochen René; Hertel, Johannes; Richter, Steffen; Wucherer, Diana; Michalowsky, Bernhard; Teipel, Stefan; Kilimann, Ingo; Dreier, Adina; Hoffmann, Wolfgang (J Alzheimers Dis, 2016)
BACKGROUND: To provide an optimal care for persons with dementia (PWD), their individual unmet needs have to be identified and comprehensively addressed. OBJECTIVES: Present analyses aim to describe the number and types of unmet needs of German primary care patients screened positive for dementia and factors associated with the number of unmet needs. METHODS: DelpHi-MV (Dementia: life- and person-centered help in Mecklenburg-Western Pomerania) is a general practitioner-based, cluster-randomized controlled intervention trial. Analyses are based on the baseline data of 227 PWD (≥70 years, living at home) of the intervention group who had screened positive for dementia (DemTect<9) and received a standardized computer-assisted needs assessment. RESULTS: PWD had on average 8.77±5.04 unmet needs (Range = 0-31). More than 90% of the PWD had three or more unmet needs. Unmet needs were identified across all predefined 26 subcategories. The majority of unmet needs occurred in the domains "nursing treatment and care" (38%), "social counseling and legal support" (20%), and "pharmacological treatment and care" (15%). More impairment in the activities of daily living was the only factor that was significantly associated with a higher number of unmet needs, independent of age, gender, living situation, presence of an informal caregiver, cognitive impairment, and depression. CONCLUSIONS: Present results demonstrate that community-dwelling PWD had a broad range of varying unmet needs. These findings emphasize the importance of a comprehensive needs assessment that allows the identification of individual needs as the basis for a tailored intervention- such as Dementia Care Management- that can address these needs.
Keywords: Aged, 80 and over; Caregivers; Cross-Sectional Studies; Dementia; Depression; Female; Germany; Health Services Needs and Demand; Humans; Male; Needs Assessment; Prevalence

The Vanderbilt Memory & Aging Project: Study Design and Baseline Cohort Overview. - Jefferson, Angela L; Gifford, Katherine A; Acosta, Lealani Mae Y; Bell, Susan P; Donahue, Manus J; Davis, L Taylor; Gottlieb, JoAnn; Gupta, Deepak K; Hohman, Timothy J; Lane, Elizabeth M; Libon, David J; Mendes, Lisa A; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Vascular health factors frequently co-occur with Alzheimer's disease (AD). A better understanding of how systemic vascular and cerebrovascular health intersects with clinical and pathological AD may inform prevention and treatment opportunities. OBJECTIVE: To establish the Vanderbilt Memory & Aging Project, a case-control longitudinal study investigating vascular health and brain aging, and describe baseline methodology and participant characteristics. METHODS: From September 2012 to November 2014, 335 participants age 60- 92 were enrolled, including 168 individuals with mild cognitive impairment (MCI, 73±8 years, 41% female) and 167 age-, sex-, and race-matched cognitively normal controls (NC, 72±7 years, 41% female). At baseline, participants completed a physical and frailty examination, fasting blood draw, neuropsychological assessment, echocardiogram, cardiac MRI, and brain MRI. A subset underwent 24-hour ambulatory blood pressure monitoring and lumbar puncture for cerebrospinal fluid (CSF) collection. RESULTS: As designed, participant groups were comparable for age (p = 0.31), sex (p = 0.95), and race (p = 0.65). MCI participants had greater Framingham Stroke Risk Profile scores (p = 0.008), systolic blood pressure values (p = 0.008), and history of left ventricular hypertrophy (p = 0.04) than NC participants. As expected, MCI participants performed worse on all neuropsychological measures (p-values < 0.001), were more likely to be APOEɛ4 carriers (p = 0.02), and had enhanced CSF biomarkers, including lower Aβ42 (p = 0.02), higher total tau (p = 0.004), and higher p-tau (p = 0.02) compared to NC participants. CONCLUSION: Diverse sources of baseline and longitudinal data will provide rich opportunities to investigate pathways linking vascular and cerebrovascular health, clinical and pathological AD, and neurodegeneration contributing to novel strategies to delay or prevent cognitive decline.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Blood Pressure Monitoring, Ambulatory; Brain; Case-Control Studies; Cerebral Angiography; Cognitive Dysfunction; Echocardiography; Epidemiologic Research Design; Female; Follow-Up Studies; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Research Design

Vascular Health Indices and Cognitive Domain Function: Singapore Longitudinal Ageing Studies. - Lim, Shir Lynn; Gao, Qi; Nyunt, Ma Shwe Zin; Gong, Lingli; Lunaria, Josephine B; Lim, May Li; Ling, Audrey; Lam, Carolyn Su-Ping; Richards, Arthur Mark; Ling, Lieng Hsi; Ng, Tze Pin (J Alzheimers Dis, 2016)
BACKGROUND: Few studies have comprehensively evaluated the relationship between vascular disease and cognition of older adults without cardiac disease. OBJECTIVE: We explored the associations of structural atherosclerosis, vascular stiffness, and reactivity with global, memory, attention, language, visuospatial ability, and executive function in community-dwelling, non-demented older Asians without cardiac diseases. METHODS: Cognition was assessed by Mini-Mental State Examination (MMSE) (n = 308) and detailed neuropsychological tests (n = 155). Vascular measures included carotid intima-media thickness; aortic stiffness [carotid-femoral pulse wave velocity (CFPWV), aortic augmentation index (AI), and aortic pulse pressure (PP)]; carotid stiffness [elasticity modulus (Ep), beta index (β), arterial compliance (AC), carotid AI]; and endothelial function [reactive hyperemia index (RHI)]. Multivariable analyses controlled for potential confounding by demographics, apolipoprotein E genotype and cardiovascular risk factors. RESULTS: The participants' mean age was 63.0 ± 6.1 years. Inverse associations with MMSE were found for AC (β= 0.128, p = 0.019), Ep (β= -0.151, p = 0.008), β index (β= -0.122, p = 0.029), carotid stiffness z-score (β= -0.154, p = 0.007); with executive function for CFPWV (β= -0.209, p = 0.026), AC (β= 0.214, p = 0.005), Ep (β= -0.160, p = 0.050), β index (β= -0.165, p = 0.041), and both aortic (β= -0.229, p = 0.010) and carotid (β= -0.208, p = 0.010) stiffness z-scores; with verbal memory for AI (β= -0.229, p = 0.004) and aortic (β= -0.263, p = 0.004) stiffness z-score; with language for AI (β= -0.155, p = 0.025), aortic stiffness z-score (β= -0.196, p = 0.011). RHI positively correlated with visuospatial ability (β= 0.195, p = 0.013) and executive function (β= 0.151, p = 0.045). CONCLUSION: The results support a link between systemic vascular health and neurocognitive function in older Asian adults. Subclinical noninvasive measures of arterial stiffness and reactivity may identify individuals vulnerable to cognitive impairment.
Keywords: Aged; Blood Flow Velocity; Blood Pressure; Cardiovascular Diseases; Carotid Intima-Media Thickness; Cognitive Aging; Female; Humans; Longitudinal Studies; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Singapore; Vascular Stiffness

Vitamin D and Memory Decline: Two Population-Based Prospective Studies. - Kuźma, Elżbieta; Soni, Maya; Littlejohns, Thomas J; Ranson, Janice M; van Schoor, Natasja M; Deeg, Dorly J H; Comijs, Hannie; Chaves, Paulo H M; Kestenbaum, Bryan R; Kuller, Lewis H; Lopez, Oscar L; Becker, James T; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Vitamin D deficiency has been linked with dementia risk, cognitive decline, and executive dysfunction. However, the association with memory remains largely unknown. OBJECTIVE: To investigate whether low serum 25-hydroxyvitamin D (25(OH)D) concentrations are associated with memory decline. METHODS: We used data on 1,291 participants from the US Cardiovascular Health Study (CHS) and 915 participants from the Dutch Longitudinal Aging Study Amsterdam (LASA) who were dementia-free at baseline, had valid vitamin D measurements, and follow-up memory assessments. The Benton Visual Retention Test (in the CHS) and Rey's Auditory Verbal Learning Test (in the LASA) were used to assess visual and verbal memory, respectively. RESULTS: In the CHS, those moderately and severely deficient in serum 25(OH)D changed -0.03 SD (95% CI: -0.06 to 0.01) and -0.10 SD (95% CI: -0.19 to -0.02) per year respectively in visual memory compared to those sufficient (p = 0.02). In the LASA, moderate and severe deficiency in serum 25(OH)D was associated with a mean change of 0.01 SD (95% CI: -0.01 to 0.02) and -0.01 SD (95% CI: -0.04 to 0.02) per year respectively in verbal memory compared to sufficiency (p = 0.34). CONCLUSIONS: Our findings suggest an association between severe vitamin D deficiency and visual memory decline but no association with verbal memory decline. They warrant further investigation in prospective studies assessing different memory subtypes.
Keywords: Humans; Memory Disorders; Netherlands; Prospective Studies; United States; Vitamin D; Vitamin D Deficiency

Volumetric and shape analysis of the thalamus and striatum in amnestic mild cognitive impairment. - Leh, Sandra E; Kälin, Andrea M; Schroeder, Clemens; Park, Min Tae M; Chakravarty, M Mallar; Freund, Patrick; Gietl, Anton F; Riese, Florian; Kollias, Spyros; Hock, Christoph; Michels, Lars (J Alzheimers Dis, 2016)
Alterations in brain structures, including progressive neurodegeneration, are a hallmark in patients with Alzheimer's disease (AD). However, pathological mechanisms, such as the accumulation of amyloid and the proliferation of tau, are thought to begin years, even decades, before the initial clinical manifestations of AD. In this study, we compare the brain anatomy of amnestic mild cognitive impairment patients (aMCI, n = 16) to healthy subjects (CS, n = 22) using cortical thickness, subcortical volume, and shape analysis, which we believe to be complimentary to volumetric measures. We were able to replicate "classical" cortical thickness alterations in aMCI in the hippocampus, amygdala, putamen, insula, and inferior temporal regions. Additionally, aMCI showed significant thalamic and striatal shape differences. We observed higher global amyloid deposition in aMCI, a significant correlation between striatal displacement and global amyloid, and an inverse correlation between executive function and right-hemispheric thalamic displacement. In contrast, no volumetric differences were detected in thalamic, striatal, and hippocampal regions. Our results provide new evidence for early subcortical neuroanatomical changes in patients with aMCI, which are linked to cognitive abilities and amyloid deposition. Hence, shape analysis may aid in the identification of structural biomarkers for identifying individuals at highest risk of conversion to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Corpus Striatum; Female; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography; Thalamus

White Matter and Hippocampal Volume Predict the Risk of Dementia in Patients with Cerebral Small Vessel Disease: The RUN DMC Study. - van Uden, Ingeborg W M; van der Holst, Helena M; Tuladhar, Anil M; van Norden, Anouk G W; de Laat, Karlijn F; Rutten-Jacobs, Loes C A; Norris, David G; Claassen, Jurgen A H R; van Dijk, Ewoud J; Kessels, Roy P C; de Leeuw, Frank-Erik (J Alzheimers Dis, 2016)
BACKGROUND: The relationship between cerebral small vessel disease (SVD) and dementia has been studied without considering white matter (WM) volume, the microstructural integrity of the WM surrounding the SVD, and grey matter (GM). OBJECTIVE: We prospectively investigated the relationship between these structures and the risk of dementia, and formed a prediction model to investigate which characteristics (macro- or microstructural) explained most of the variance. METHODS: The RUN DMC study is a prospective cohort study among 503 non-demented participants with an age between 50 and 85 years at baseline, with baseline assessment in 2006 and follow-up assessment in 2012. Two were lost to follow-up (yielding a 99.6% response-rate). Cox regression analysis was used, to calculate hazard ratios for dementia, of baseline MRI characteristics. Tract-Based Spatial Statistics (TBSS) analysis was used to assess the added value of microstructural integrity of the WM. RESULTS: Mean age at baseline was 65.6 years (SD 8.8) and 56.8% was male. 43 participants developed dementia (8.6%), resulting in a 5.5-year cumulative risk of 11.1% (95% CI 7.7-14.6). Low WM and hippocampal volume are significant predictors for dementia. WM, WM hyperintensities, and hippocampal volume explained most of the variance. TBSS analyses showed no additional value of diffusion parameters. CONCLUSIONS: WM and hippocampal volume were the main predictors for the development of incident dementia at 5-year follow-up in elderly with SVD. There was no additional diagnostic value of the diffusion tensor imaging parameters on top of the macrostructural characteristics.
Keywords: Aged; Cerebral Small Vessel Diseases; Cohort Studies; Dementia; Diffusion Tensor Imaging; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Statistics, Nonparametric; White Matter

White Matter Changes are Associated with Ventricular Expansion in Aging, Mild Cognitive Impairment, and Alzheimer's Disease. - Coutu, Jean-Philippe; Goldblatt, Alison; Rosas, H Diana; Salat, David H (J Alzheimers Dis, 2016)
White matter lesions are highly prevalent in individuals with Alzheimer's disease (AD). Although these lesions are presumed to be of vascular origin and linked to small vessel disease in older adults, little information exists about their relationship to markers of classical AD neurodegeneration. Thus, we examined the link between these white matter changes (WMC) segmented on T1-weighted MRI and imaging markers presumed to be altered due to primary AD neurodegenerative processes. Tissue microstructure of WMC was quantified using diffusion tensor imaging and the relationship of WMC properties and volume to neuroimaging markers was examined in 219 cognitively healthy older adults and individuals with mild cognitive impairment and AD using data from the Alzheimer's Disease Neuroimaging Initiative. No significant group differences in WMC properties were found. However, there were strong associations between diffusivity of WMC and ventricular volume, volume of WMC and total WM volume. In comparison, group differences in parahippocampal white matter microstructure were found for all diffusion metrics and were largely explained by hippocampal volume. Factor analysis on neuroimaging markers suggested two independent sets of covarying degenerative changes, with potentially age- and vascular-mediated tissue damage contributing to one factor and classical neurodegenerative changes associated with AD contributing to a second factor. These data demonstrate two potentially distinct classes of degenerative change in AD, with one factor strongly linked to aging, ventricular expansion, and both volume and tissue properties of white matter lesions, while the other factor related to classical patterns of cortical and hippocampal neurodegeneration in AD.
Keywords: Aged; Aging; Alzheimer Disease; Cognitive Dysfunction; Diffusion Tensor Imaging; Factor Analysis, Statistical; Female; Hippocampus; Humans; Imaging, Three-Dimensional; Male; Mental Status Schedule; Neuropsychological Tests; White Matter

Within-Individual Variability: An Index for Subtle Change in Neurocognition in Mild Cognitive Impairment. - Roalf, David R; Quarmley, Megan; Mechanic-Hamilton, Dawn; Wolk, David A; Arnold, Steven E; Moberg, Paul J (J Alzheimers Dis, 2016)
BACKGROUND: The transition from mild cognitive impairment (MCI) to Alzheimer's disease is characterized by a decline in cognitive performance in many domains. Cognitive performance profiles in MCI are heterogeneous, however, and additional insights into markers of incipient dementia are needed. Typically, studies focus on average or mean performance, but ignore consistency of performance across domains. WIV (within-individual variability) provides an index of this consistency and is a potential marker of cognitive decline. OBJECTIVE: To use neurocognitive data from the Alzheimer's Disease Neuroimaging Initiative cohort to measure neurocognitive variability. METHODS: The utility of WIV was measured, in addition to global neurocognitive performance (GNP), for identifying AD and MCI. In addition, the association between changes in neurocognitive variability and diagnostic transition over 12 months was measured. RESULTS: As expected, variability was higher in AD and MCI as compared to healthy controls; GNP was lower in both groups as compared to healthy subjects. Global neurocognitive performance alone best distinguished those with dementia from healthy older adults. Yet, for individuals with MCI, including variability along with GNP improved diagnostic classification. Variability was higher at baseline in individuals transitioning from MCI to AD over a 12-month period. CONCLUSION: We conclude that variability offers complementary information about neurocognitive performance in dementia, particularly in individuals with MCI, and may provide beneficial information about disease transition.

Zinc-Mediated Binding of Nucleic Acids to Amyloid-β Aggregates: Role of Histidine Residues. - Khmeleva, Svetlana A; Radko, Sergey P; Kozin, Sergey A; Kiseleva, Yana Y; Mezentsev, Yuri V; Mitkevich, Vladimir A; Kurbatov, Leonid K; Ivanov, Alexis S; Makarov, Alexander A (J Alzheimers Dis, 2016)
Amyloid-β peptide (Aβ) plays a central role in Alzheimer's disease (AD) pathogenesis. Besides extracellular Aβ, intraneuronal Aβ (iAβ) has been suggested to contribute to AD onset and development. Based on reported in vitro Aβ-DNA interactions and nuclear localization of iAβ, the interference of iAβ with the normal DNA expression has recently been proposed as a plausible pathway by which Aβ can exert neurotoxicity. Employing the sedimentation assay, thioflavin T fluorescence, and dynamic light scattering we have studied effects of zinc ions on binding of RNA and single- and double-stranded DNA molecules to Aβ42 aggregates. It has been found that zinc ions significantly enhance the binding of RNA and DNA molecules to pre-formed β-sheet rich Aβ42 aggregates. Another type of Aβ42 aggregates, the zinc-induced amorphous aggregates, was demonstrated to also bind all types of nucleic acids tested. To evaluate the role of the Aβ metal-binding domain's histidine residues in Aβ-nucleic acid interactions mediated by zinc, Aβ16 mutants with substitutions H6R and H6A-H13A and rat Aβ16 lacking histidine residue 13 were used. The zinc-induced interaction of Aβ16 with DNA was shown to critically depend on histidine residues 6 and 13. However, the inclusion of H6R mutation in Aβ42 peptide did not affect DNA binding to Aβ42 aggregates. Since oxidative and/or nitrosative stresses implicated in AD pathogenesis are known to release zinc ions from metallothioneins in cytoplasm and cell nuclei, our findings suggest that intracellular zinc can be an important player in iAβ-nucleic acid interactions.

δ Scores are Exportable Across Cultural and Linguistic Boundaries. - Royall, Donald R; Palmer, Raymond F; Matsuoka, Teruyuki; Kato, Yuka; Taniguchi, Shogo; Ogawa, Mayu; Fujimoto, Hiroshi; Okamura, Aiko; Shibata, Keisuke; Nakamura, Kaeko; Nakaaki, Shutaro; Koumi, Hiroyuki; et al. (J Alzheimers Dis, 2016)
The latent variable "δ", can accurately diagnose dementia. Its generalizability across populations is unknown. We constructed a δ homolog ("dT2J") in data collected by the Texas Alzheimer's Research and Care Consortium (TARCC). From this, we calculated a composite d-score "d". We then tested d's generalizability across random subsets of TARCC participants and to a convenience sample of elderly Japanese persons with normal cognition (NC), mild cognitive impairment (MCI), and dementia (AD) (n = 176). dT2J was indicated by Instrumental Activities of Daily Living and psychometric measures. Embedded in this battery were the Mini-Mental Status Examination (MMSE) and an executive clock-drawing task (CLOX). Only MMSE and CLOX were available in both TARCC and the Japanese cohort. Therefore, a second composite variable, "T2J", was constructed solely from the factor loadings of CLOX and MMSE on d. The diagnostic accuracy of T2J was estimated in the validation sample, the remainder of the TARCC cohort, and in the Japanese sample. The areas under the receiver operating curve (AUC; ROC) for T2J were compared in each sample, and against d in TARCC. The AUCs for T2J were statistically indiscriminable within TARCC, and in Japanese persons. In Japanese persons, AUCs for T2J were 0.97 for the discrimination between AD versus NC, 0.86 for AD versus MCI, and 0.79 for NC versus MCI. The AUCs for T2J in Japanese persons were higher than any individual psychometric measure in that sample. Valid d-score composites can be abstracted from a subset of δ's indicators. Moreover, those composites are exportable across cultural and linguistic boundaries.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Cognitive Dysfunction; Cohort Studies; Culture; Executive Function; Female; Humans; Linguistics; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Psychometrics; Reproducibility of Results; ROC Curve; Texas

Alzheimer's Disease Normative Cerebrospinal Fluid Biomarkers Validated in PET Amyloid-β Characterized Subjects from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study. - Li, Qiao-Xin; Villemagne, Victor L; Doecke, James D; Rembach, Alan; Sarros, Shannon; Varghese, Shiji; McGlade, Amelia; Laughton, Katrina M; Pertile, Kelly K; Fowler, Christopher J; Rumble, Rebecca L; Trounson, Brett O; et al. (J Alzheimers Dis, 2015)
BACKGROUND: The cerebrospinal fluid (CSF) amyloid-β (Aβ)1-42, total-tau (T-tau), and phosphorylated-tau (P-tau181P) profile has been established as a valuable biomarker for Alzheimer's disease (AD). OBJECTIVE: The current study aimed to determine CSF biomarker cut-points using positron emission tomography (PET) Aβ imaging screened subjects from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study of aging, as well as correlate CSF analyte cut-points across a range of PET Aβ amyloid ligands. METHODS: Aβ pathology was determined by PET imaging, utilizing 11C-Pittsburgh Compound B, 18F-flutemetamol, or 18F-florbetapir, in 157 AIBL participants who also underwent CSF collection. Using an INNOTEST assay, cut-points were established (Aβ1-42 >544 ng/L, T-tau <407 ng/L, and P-tau181P <78 ng/L) employing a rank based method to define a "positive" CSF in the sub-cohort of amyloid-PET negative healthy participants (n = 97), and compared with the presence of PET demonstrated AD pathology. RESULTS: CSF Aβ1-42 was the strongest individual biomarker, detecting cognitively impaired PET positive mild cognitive impairment (MCI)/AD with 85% sensitivity and 91% specificity. The ratio of P-tau181P or T-tau to Aβ1-42 provided greater accuracy, predicting MCI/AD with Aβ pathology with ≥92% sensitivity and specificity. Cross-validated accuracy, using all three biomarkers or the ratio of P-tau or T-tau to Aβ1-42 to predict MCI/AD, reached ≥92% sensitivity and specificity. CONCLUSIONS: CSF Aβ1-42 levels and analyte combination ratios demonstrated very high correlation with PET Aβ imaging. Our study offers additional support for CSF biomarkers in the early and accurate detection of AD pathology, including enrichment of patient cohorts for treatment trials even at the pre-symptomatic stage.

Amyloid-β and Tau Dynamics in Human Brain Interstitial Fluid in Patients with Suspected Normal Pressure Hydrocephalus. - Herukka, Sanna-Kaisa; Rummukainen, Jaana; Ihalainen, Jouni; von Und Zu Fraunberg, Mikael; Koivisto, Anne M; Nerg, Ossi; Puli, Lakshman K; Seppälä, Toni T; Zetterberg, Henrik; Pyykkö, Okko T; Helisalmi, Seppo; Tanila, Heikki; et al. (J Alzheimers Dis, 2015)
Background: Amyloid-β (Aβ1-42), total tau (T-tau), and phosphorylated tau (P-tau181) in the cerebrospinal fluid (CSF) are the most promising biomarkers of Alzheimer's disease (AD). Still, little is known about the dynamics of these molecules in the living brain. In a transgenic mouse brain, soluble Aβ decreases with increasing age and advanced Aβ pathology as seen similarly in CSF. Objective: To assess the relationship between AD-related pathological changes in human brain tissue, ventricular and lumbar CSF, and brain interstitial fluid (ISF). Methods: Altogether 11 patients with suspected idiopathic normal pressure hydrocephalus underwent frontal cortical brain biopsy, 24-h intraventricular pressure monitoring, and a microdialysis procedure. AD-related biomarkers were analyzed from brain tissue, CSF, and ISF. Results: ISF T-tau levels decreased strongly within the first 12 h, then plateauing until the end of the experiment. Aβ1-42 and P-tau181 remained stable during the experiment (n = 3). T-tau and P-tau were higher in the ISF than in ventricular or lumbar CSF, while Aβ1-42 levels were within similar range in both CSF and ISF samples. ISF P-tau correlated with the ventricular CSF T-tau (r = 0.70, p = 0.017) and P-tau181 (r = 0.64, p = 0.034). Five patients with amyloid pathology in the brain biopsy tended to reveal lower ISF Aβ1-42 levels than those six without amyloid pathology. Conclusions: This is the first study to report ISF Aβ and tau levels in the human brain without significant brain injury. The set-up used enables sampling from the brain ISF for at least 24 h without causing adverse effects due to the microdialysis procedure to follow the dynamics of the key molecules in AD pathogenesis in the living brain at various stages of the disease.

AβPP-Transgenic 2576 Mice Mimic Cell Type-Specific Aspects of Acetyl-CoA-Linked Metabolic Deficits in Alzheimer's Disease. - Bielarczyk, Hanna; Jankowska-Kulawy, Agnieszka; Hofling, Corinna; Ronowska, Anna; Gul-Hinc, Sylwia; Rossner, Steffen; Schliebs, Reinhard; Pawelczyk, Tadeusz; Szutowicz, Andrzej (J Alzheimers Dis, 2015)
The pyruvate-derived acetyl-CoA is a principal direct precursor substrate for bulk energy synthesis in the brain. Deficits of pyruvate dehydrogenase in the neocortex are common features of Alzheimer's disease and other age-related encephalopathies in humans. Therefore, amyloid-β overload in brains of diverse transgenic Alzheimer's disease model animals was investigated as one of neurotoxic compounds responsible for pyruvate dehydrogenase inhibition yielding deficits of cholinergic neurotransmission and cognitive functions. Brains of aged, 14-16-month-old Tg2576 mice contained 0.6 μmol/kg levels of amyloid-β 1-42. Activities of pyruvate dehydrogenase complex, choline acetyltransferase, and several enzymes of acetyl-CoA and energy metabolism were found to be unchanged in both forebrain mitochondria and synaptosomes of Tg2576 mice, indicating preservation of structural integrity at least cholinergic neuronal cells. However, in transgenic brain synaptosomes, pyruvate utilization, mitochondrial levels, and cytoplasmic acetyl-CoA levels, as well as acetylcholine content and its quantal release, were all found to be decreased by 25-40% . On the contrary, activation of pyruvate utilization was detected and no alterations in acetyl-CoA content and citrate or α-ketoglutarate accumulation were observed in transgenic whole brain mitochondria. These data indicate that amyloid-β evoked deficits in acetyl-CoA are confined to mitochondrial and cytoplasmic compartments of Tg2576 nerve terminals, becoming early primary signals paving path for further stages of neurodegeneration. On the other hand, acetyl-CoA synthesis in mitochondrial compartments of glial cells seems to be activated despite amyloid-β accumulated in transgenic brains.

A Blood-Based, 7-Metabolite Signature for the Early Diagnosis of Alzheimer's Disease. - Olazarán, Javier; Gil-de-Gómez, Luis; Rodríguez-Martín, Andrés; Valentí-Soler, Meritxell; Frades-Payo, Belén; Marín-Muñoz, Juan; Antúnez, Carmen; Frank-García, Ana; Jiménez, Carmen Acedo; Gracia, Lorenzo Morlén; Torregrossa, Roberto Petidier; Guisasola, María Concepción; et al. (J Alzheimers Dis, 2015)
Accurate blood-based biomarkers of Alzheimer's disease (AD) could constitute simple, inexpensive, and non-invasive tools for the early diagnosis and treatment of this devastating neurodegenerative disease. We sought to develop a robust AD biomarker panel by identifying alterations in plasma metabolites that persist throughout the continuum of AD pathophysiology. Using a multicenter, cross-sectional study design, we based our analysis on metabolites whose levels were altered both in AD patients and in patients with amnestic mild cognitive impairment (aMCI), the earliest identifiable stage of AD. UPLC coupled to mass spectrometry was used to independently compare the levels of 495 plasma metabolites in aMCI (n = 58) and AD (n = 100) patients with those of normal cognition controls (NC, n = 93). Metabolite alterations common to both aMCI and AD patients were used to generate a logistic regression model that accurately distinguished AD from NC patients. The final panel consisted of seven metabolites: three amino acids (glutamic acid, alanine, and aspartic acid), one non-esterified fatty acid (22:6n-3, DHA), one bile acid (deoxycholic acid), one phosphatidylethanolamine [PE(36:4)], and one sphingomyelin [SM(39:1)]. Detailed analysis ruled out the influence of potential confounding variables, including comorbidities and treatments, on each of the seven biomarkers. The final model accurately distinguished AD from NC patients (AUC, 0.918). Importantly, the model also distinguished aMCI from NC patients (AUC, 0.826), indicating its potential diagnostic utility in early disease stages. These findings describe a sensitive biomarker panel that may facilitate the specific detection of early-stage AD through the analysis of plasma samples.

Buccal Cell Cytokeratin 14 Correlates with Multiple Blood Biomarkers of Alzheimer's Disease Risk. - Leifert, Wayne R; Nguyen, Tori; Rembach, Alan; Martins, Ralph; Rainey-Smith, Stephanie; Masters, Colin L; Ames, David; Rowe, Christopher C; Macaulay, S Lance; François, Maxime; Fenech, Michael F (J Alzheimers Dis, 2015)
Mild cognitive impairment (MCI) may reflect early stages of neurodegenerative disorders such as Alzheimer's disease (AD). Our hypothesis was that cytokeratin 14 (CK14) expression could be used with blood-based biomarkers such as homocysteine, vitamin B12, and folate to identify individuals with MCI or AD from the Australian Imaging, Biomarkers and Lifestyle (AIBL) flagship study of aging. Buccal cells from 54 individuals were analyzed by a newly developed method that is rapid, automated, and quantitative for buccal cell CK14 expression levels. CK14 was negatively correlated with plasma Mg2 + and LDL, while positively correlated with vitamin B12, red cell hematocrit/volume, and basophils in the MCI group and positively correlated with insulin and vitamin B12 in the AD group. The combined biomarker panel (CK14 expression, plasma vitamin B12, and homocysteine) was significantly lower in the MCI (p = 0.003) and AD (p = 0.0001) groups compared with controls. Receiver-operating characteristic curves yielded area under the curve (AUC) values of 0.829 for the MCI (p = 0.002) group and 0.856 for the AD (p = 0.0003) group. These complex associations of multiple related parameters highlight the differences between the MCI and AD cohorts and possibly an underlying metabolic pathology associated with the development of early memory impairment. The changes in buccal cell CK14 expression observed in this pilot study supports previous results suggesting the peripheral biomarkers and metabolic changes are not restricted to brain pathology alone in MCI and AD and could prove useful as a potential biomarker in identifying individuals with an increased risk of developing MCI and eventually AD.

Cognitive Impairment Precedes and Predicts Functional Impairment in Mild Alzheimer's Disease. - Liu-Seifert, Hong; Siemers, Eric; Price, Karen; Han, Baoguang; Selzler, Katherine J; Henley, David; Sundell, Karen; Aisen, Paul; Cummings, Jeffrey; Raskin, Joel; Mohs, Richard (J Alzheimers Dis, 2015)
BACKGROUND: The temporal relationship of cognitive deficit and functional impairment in Alzheimer's disease (AD) is not well characterized. Recent analyses suggest cognitive decline predicts subsequent functional decline throughout AD progression. OBJECTIVE: To better understand the relationship between cognitive and functional decline in mild AD using autoregressive cross-lagged (ARCL) panel analyses in several clinical trials. METHODS: Data included placebo patients with mild AD pooled from two multicenter, double-blind, Phase 3 solanezumab (EXPEDITION/2) or semagacestat (IDENTITY/2) studies, and from AD patients participating in the Alzheimer's Disease Neuroimaging Initiative (ADNI). Cognitive and functional outcomes were assessed using AD Assessment Scale-Cognitive subscale (ADAS-Cog), AD Cooperative Study-Activities of Daily Living instrumental subscale (ADCS-iADL), or Functional Activities Questionnaire (FAQ), respectively. ARCL panel analyses evaluated relationships between cognitive and functional impairment over time. RESULTS: In EXPEDITION, ARCL panel analyses demonstrated cognitive scores significantly predicted future functional impairment at 5 of 6 time points, while functional scores predicted subsequent cognitive scores in only 1 of 6 time points. Data from IDENTITY and ADNI programs yielded consistent results whereby cognition predicted subsequent function, but not vice-versa. CONCLUSIONS: Analyses from three databases indicated cognitive decline precedes and predicts subsequent functional decline in mild AD dementia, consistent with previously proposed hypotheses, and corroborate recent publications using similar methodologies. Cognitive impairment may be used as a predictor of future functional impairment in mild AD dementia and can be considered a critical target for prevention strategies to limit future functional decline in the dementia process.

Comprehensive Gene- and Pathway-Based Analysis of Depressive Symptoms in Older Adults. - Nho, Kwangsik; Ramanan, Vijay K; Horgusluoglu, Emrin; Kim, Sungeun; Inlow, Mark H; Risacher, Shannon L; McDonald, Brenna C; Farlow, Martin R; Foroud, Tatiana M; Gao, Sujuan; Callahan, Christopher M; Hendrie, Hugh C; et al. (J Alzheimers Dis, 2015)
Depressive symptoms are common in older adults and are particularly prevalent in those with or at elevated risk for dementia. Although the heritability of depression is estimated to be substantial, single nucleotide polymorphism-based genome-wide association studies of depressive symptoms have had limited success. In this study, we PERFORMED genome-wide gene- and pathway-based analyses of depressive symptom burden. Study participants included non-Hispanic Caucasian subjects (n = 6,884) from three independent cohorts, the Alzheimer's Disease Neuroimaging Initiative (ADNI), the Health and Retirement Study (HRS), and the Indiana Memory and Aging Study (IMAS). Gene-based meta-analysis identified genome-wide significant associations (ANGPT4 and FAM110A, q-value = 0.026; GRM7-AS3 and LRFN5, q-value = 0.042). Pathway analysis revealed enrichment of association in 105 pathways, including multiple pathways related to ERK/MAPK signaling, GSK3 signaling in bipolar disorder, cell development, and immune activation and inflammation. GRM7, ANGPT4, and LRFN5 have been previously implicated in psychiatric disorders, including the GRM7 region displaying association with major depressive disorder. The ERK/MAPK signaling pathway is a known target of antidepressant drugs and has important roles in neuronal plasticity, and GSK3 signaling has been previously implicated in Alzheimer's disease and as a promising therapeutic target for depression. Our results warrant further investigation in independent and larger cohorts and add to the growing understanding of the genetics and pathobiology of depressive symptoms in aging and neurodegenerative disorders. In particular, the genes and pathways demonstrating association with depressive symptoms may be potential therapeutic targets for these symptoms in older adults.

The Continuing Failure of Bexarotene in Alzheimer's Disease Mice. - Balducci, Claudia; Paladini, Alessandra; Micotti, Edoardo; Tolomeo, Daniele; La Vitola, Pietro; Grigoli, Emanuele; Richardson, Jill C; Forloni, Gianluigi (J Alzheimers Dis, 2015)
Alzheimer's disease (AD) is the most common form of dementia characterized by synaptic dysfunction, memory loss, neuroinflammation, and neuronal cell death. Amyloid-β (Aβ), recognized as the main culprit of AD, aggregates and accumulates in the extracellular compartment as neuritic plaques, after deregulation of its production or clearance. Apolipoprotein E (ApoE) plays a major role in Aβ clearance and its expression is transcriptionally regulated by the liver X receptor and retinoid X receptors (RXRs) system. Bexarotene (BEXA), an RXR agonist, that increases ApoE expression and microglia phagocytosis and has been proposed as a promising therapy for AD, resolving both the amyloid pathology and memory loss. Despite the first compelling report, however, multiple failures have been documented, raising concern about whether BEXA could in fact become a novel disease-modifying strategy for AD. To help clarify this, we investigated the effect of BEXA in vivo at multiple levels in TASTPM transgenic mice. Seven-day oral administration of BEXA to these mice did not achieve any significant memory improvement, plaque reduction, or enhancement of microglial cell activation. No differences were found when specifically investigating the microglial phagocytic state in vivo. In addition, a brain structural analysis with magnetic resonance did not detect any BEXA-mediated change in the volume reduction of the main affected brain areas in our mice. These results suggest that BEXA has no beneficial effect on the multi-factorial pathologic phenotype of AD mice.

A Critical Proton MR Spectroscopy Marker of Alzheimer's Disease Early Neurodegenerative Change: Low Hippocampal NAA/Cr Ratio Impacts APOE ɛ4 Mexico City Children and Their Parents. - Calderón-Garcidueñas, Lilian; Mora-Tiscareño, Antonieta; Sánchez, Gastón Melo; Rodríguez-Díaz, Joel; Torres-Jardón, Ricardo; Styner, Martin; Mukherjee, Partha S; Lin, Weili; Jewells, Valerie (J Alzheimers Dis, 2015)
Severe air pollution exposures produce systemic, respiratory, myocardial, and brain inflammation and Alzheimer's disease (AD) hallmarks in clinically healthy children. We tested whether hippocampal metabolite ratios are associated with contrasting levels of air pollution, APOE, and body mass index (BMI) in paired healthy children and one parent sharing the same APOE alleles. We used 1H-MRS to interrogate bilateral hippocampal single-voxel in 57 children (12.45 ± 3.4 years) and their 48 parents (37.5 ± 6.78 years) from a low pollution city versus Mexico City (MC). NAA/Cr, Cho/Cr, and mI/Cr metabolite ratios were analyzed. The right hippocampus NAA/Cr ratio was significantly different between cohorts (p = 0.007). The NAA/Cr ratio in right hippocampus in controls versus APOE ɛ4 MC children and in left hippocampus in MC APOE ɛ4 parents versus their children was significantly different after adjusting for age, gender, and BMI (p = 0.027 and 0.01, respectively). The NAA/Cr ratio is considered reflective of neuronal density/functional integrity/loss of synapses/higher pTau burden, thus a significant decrease in hippocampal NAA/Cr ratios may constitute a spectral marker of early neurodegeneration in young urbanites. Decreases in NAA/Cr correlate well with cognitive function, behavioral symptoms, and dementia severity; thus, since the progression of AD starts decades before clinical diagnosis, our findings support the hypothesis that under chronic exposures to fine particulate matter and ozone above the standards, neurodegenerative processes start in childhood and APOE ɛ4 carriers are at higher risk. Gene and environmental factors are critical in the development of AD and the identification and neuroprotection of young urbanites at high risk must become a public health priority.

Depression and Suicidal Ideation During Two Psychosocial Treatments in Older Adults with Major Depression and Dementia. - Kiosses, Dimitris N; Rosenberg, Paul B; McGovern, Amanda; Fonzetti, Pasquale; Zaydens, Hana; Alexopoulos, George S (J Alzheimers Dis, 2015)
BACKGROUND: Depression is prevalent in dementia and contributes to poor outcomes for patients and their families. Antidepressants have limited efficacy in older adults with major depression and dementia, and psychosocial interventions are under-investigated. OBJECTIVE: To examine the course, predictors and moderators of depression and suicidal ideation during 12 weeks of home-delivered Problem Adaptation Therapy (PATH) versus Supportive Therapy for Cognitively Impaired Older Adults (ST-CI) in 39 older adults with major depression and dementia. METHODS: Thirty-nine older adults with major depression, mild or moderate dementia, and disability participated in a randomized controlled trial that compared the efficacy of PATH versus ST-CI. Depression and suicidal ideation were assessed with Cornell Scale for Depression in Dementia Total Score and Suicide Item. RESULTS: PATH participants had significantly greater reduction in depression than ST-CI participants over 12 weeks of treatment. PATH participants with high social support had the greatest reduction in depression. Both treatments had comparable reduction in suicidal ideation. CONCLUSION: PATH is more effective in reducing depression in older adults with major depression and dementia compared to ST-CI. These results are clinically significant as antidepressants have limited efficacy in this population. Home-delivered psychosocial treatments may reduce suicidal ideation in this population.

Depressive Symptoms and Biomarkers of Alzheimer's Disease in Cognitively Normal Older Adults. - Donovan, Nancy J; Hsu, David C; Dagley, Alexander S; Schultz, Aaron P; Amariglio, Rebecca E; Mormino, Elizabeth C; Okereke, Olivia I; Rentz, Dorene M; Johnson, Keith A; Sperling, Reisa A; Marshall, Gad A (J Alzheimers Dis, 2015)
Even low levels of depressive symptoms are associated with an increased risk of cognitive decline in older adults without overt cognitive impairment (CN). Our objective was to examine whether very low, "subthreshold symptoms of depression" are associated with Alzheimer's disease (AD) biomarkers of neurodegeneration in CN adults and whether these associations are specific to particular depressive symptoms. We analyzed data from 248 community-dwelling CN older adults, including measurements of cortical amyloid burden, neurodegeneration markers of hippocampal volume (HV) and cerebral 18F-fluorodeoxyglucose (FDG) metabolism in a composite of AD-related regions and the 30-item Geriatric Depression Scale (GDS). Participants with GDS >10 were excluded. General linear regression models evaluated the cross-sectional relations of GDS to HV or FDG in separate backward elimination models. Predictors included GDS total score, age, gender, premorbid intelligence, a binary amyloid variable and its interaction with GDS. Principal component analyses of GDS item scores revealed three factors (the Dysphoria, Apathy-Anhedonia, and Anxiety-Concentration Factors). In secondary analyses, GDS total score was replaced with the three factor scores in repeated models. Higher GDS score (p = 0.03) was significantly associated with lower HV and was marginally related (p = 0.06) to FDG hypometabolism. In secondary models, higher Dysphoria (p = 0.02) and Apathy-Anhedonia (p = 0.05) were related to lower HV while higher Apathy-Anhedonia (p = 0.003) was the sole factor related to FDG hypometabolism. Amyloid was not a significant predictor in any model. In conclusion, very low-level dysphoria, apathy and anhedonia may point to neurodegeneration in AD-related regions but this association appears to be independent of amyloid burden.

Diabetes is Associated with Worse Executive Function in Both Eastern and Western Populations: Shanghai Aging Study and Mayo Clinic Study of Aging. - Zhao, Qianhua; Roberts, Rosebud O; Ding, Ding; Cha, Ruth; Guo, Qihao; Meng, Haijiao; Luo, Jianfeng; Machulda, Mary M; Shane Pankratz, V; Wang, Bei; Christianson, Teresa J H; Aakre, Jeremiah A; et al. (J Alzheimers Dis, 2015)
BACKGROUND AND OBJECTIVES: It remains unknown whether the association between diabetes mellitus (DM) and cognitive function differs in Eastern and Western populations. This study aimed to elucidate whether DM is associated with worse cognitive performance in both populations. METHODS: The Shanghai Aging Study (SAS) and the Mayo Clinic Study of Aging (MCSA) are two population-based studies with similar design and methodology in Shanghai, China and Rochester, MN, USA. Non-demented participants underwent cognitive testing, and DM was assessed from the medical record. Separate analyses were performed in SAS and MCSA regarding the association between DM and cognitive performance. RESULTS: A total of 3,348 Chinese participants in the SAS and 3,734 American subjects in the MCSA were included. Compared with MCSA subjects, SAS participants were younger, less educated, and had lower frequency of vascular disease, APOE ɛ4 carriers and obesity. Participants with DM (compared to non-DM participants) performed significantly worse on all the cognitive domains in both the SAS and MCSA. After adjustment for age, gender, education, and vascular covariates, DM was associated with worse performance in executive function (β=-0.15, p = 0.001 for SAS, and β=-0.10, p = 0.008 for MCSA) in the total sample and in the cognitively normal sub-sample. Furthermore, DM was associated with poor performance in visuospatial skills, language, and memory in the SAS, but not in the MCSA. CONCLUSIONS: Diabetes is associated with cognitive dysfunction and, in particular, exerts a negative impact on executive function regardless of race, age, and prevalence of vascular risk factors.

Differential Effects of Meal Challenges on Cognition, Metabolism, and Biomarkers for Apolipoprotein E ɛ4 Carriers and Adults with Mild Cognitive Impairment. - Hanson, Angela J; Bayer, Jennifer L; Baker, Laura D; Cholerton, Brenna; VanFossen, Brian; Trittschuh, Emily; Rissman, Robert A; Donohue, Michael C; Moghadam, Setareh H; Plymate, Stephen R; Craft, Suzanne (J Alzheimers Dis, 2015)
BACKGROUND: High intake of saturated fat (SF) and glycemic index (GI) foods is a risk factor for sporadic Alzheimer's disease. Meal challenges may elucidate mechanisms that contribute to this risk, enabling development of targeted interventions. OBJECTIVE: To assess cognitive and metabolic changes after a meal high in SF and GI calories (HIGH) versus a meal low in these macronutrients (LOW) in older adults with and without cognitive impairment, and with and without the apolipoprotein E4 risk factor. METHODS: 46 adults with either cognitive impairment (CI) or normal cognition (NC) ingested a LOW (25% total fat, 7% SF, GI <55) and a HIGH meal (50% total fat, 25% SF, GI >70) in a blinded random fashion. Participants then underwent cognitive testing and blood sampling for metabolic and Alzheimer's disease biomarkers. Data were analyzed using repeated measures ANOVA and Spearman correlations. RESULTS: E4-adults with NC demonstrated lower delayed memory scores after the HIGH compared to the LOW meal, whereas normal E4+ and CI E4- groups had higher scores after the HIGH meal (ANOVA p = 0.03). These findings were associated with meal-induced changes in glucose (p = 0.05), insulin (p = 0.004), triglycerides (p <  0.01), and plasma Aβ42 (p = 0.05). CONCLUSIONS: These preliminary data suggest that cognitive performance of adults without CI may worsen following high SF and sugar meals, whereas adults with CI or those at risk for CI due to E4 status may benefit acutely from such meals. Furthermore, plasma Aβ was affected by meal type, suggesting a relationship between metabolic response and amyloid regulation.

Long-Term Interrelationship between Brain Metabolism and Amyloid Deposition in Mild Cognitive Impairment. - Kemppainen, Nina; Joutsa, Juho; Johansson, Jarkko; Scheinin, Noora M; Någren, Kjell; Rokka, Johanna; Parkkola, Riitta; Rinne, Juha O (J Alzheimers Dis, 2015)
The aim of this longitudinal positron emission tomography (PET) study was to evaluate the interrelationship between brain metabolism and amyloid accumulation during the disease process from mild cognitive impairment (MCI) to Alzheimer's disease (AD). Nine MCI patients, who converted to AD between two and five years, and nine healthy subjects underwent [11C]PIB and [18F]FDG PET scans at baseline and at 5 years. [11C]PIB uptake was clearly higher in MCI patients at baseline compared to controls and spread extensively to the cerebral cortex during the conversion to AD. [18F]FDG uptake was reduced especially in the temporal-parietal regions in MCI compared to controls at baseline, and widely over the cortex at the 5-year follow-up. The reduction in metabolism during the follow-up was significant in the posterior brain regions. In addition, brain amyloid load was positively associated with metabolism in posterior brain regions in MCI, but not after conversion to AD. The results suggest that there are interactions between brain amyloid accumulation and metabolism during the AD process, including a possible compensatory upregulation of posterior brain metabolism in the early phase.

Mapping the Progression of Atrophy in Early- and Late-Onset Alzheimer's Disease. - Migliaccio, Raffaella; Agosta, Federica; Possin, Katherine L; Canu, Elisa; Filippi, Massimo; Rabinovici, Gil D; Rosen, Howard J; Miller, Bruce L; Gorno-Tempini, Maria Luisa (J Alzheimers Dis, 2015)
The term early-onset Alzheimer's disease (EOAD) identifies patients who meet criteria for AD, but show onset of symptoms before the age of 65. We map progression of gray matter atrophy in EOAD patients compared to late-onset AD (LOAD). T1-weighted MRI scans were obtained at diagnosis and one-year follow-up from 15 EOAD, 10 LOAD, and 38 age-matched controls. Voxel-based and tensor-based morphometry were used, respectively, to assess the baseline and progression of atrophy. At baseline, EOAD patients already showed a widespread atrophy in temporal, parietal, occipital, and frontal cortices. After one year, EOAD had atrophy progression in medial temporal and medial parietal cortices. At baseline, LOAD patients showed atrophy in the medial temporal regions only, and, after one year, an extensive pattern of atrophy progression in the same neocortical cortices of EOAD. Although atrophy mainly involved different lateral neocortical or medial temporal hubs at baseline, it eventually progressed along the same brain default-network regions in both groups. The cortical region showing a significant progression in both groups was the medial precuneus/posterior cingulate.

A Phase II Randomized Clinical Trial of a Nutritional Formulation for Cognition and Mood in Alzheimer's Disease. - Remington, Ruth; Bechtel, Cynthia; Larsen, David; Samar, Annemarie; Doshanjh, Laura; Fishman, Paul; Luo, Yuan; Smyers, Kathleen; Page, Robert; Morrell, Christopher; Shea, Thomas B (J Alzheimers Dis, 2015)
Background: Increasing evidence points toward the efficacy of nutritional modifications in delaying cognitive decline and mood/behavioral difficulties in Alzheimer's disease (AD). Nutritional supplementation with individual agents has shown varied results suggesting the need for combinatorial intervention. Objective: We set out to determine whether nutritional intervention could positively impact cognitive performance and behavioral difficulties for individuals diagnosed with AD. Methods: A double-blind, multi-site, phase II study (ClinicalTrials.gov NCT01320527; Alzheimer's Association Trialmatch) was conducted in which 106 individuals with AD were randomized to a nutraceutical formulation (NF; folate, alpha-tocopherol, B12, S-adenosyl methioinine, N-acetyl cysteine, acetyl-L-carnitine) or placebo for 3 or 6 months, followed by an open-label extension where participants received NF for 6 additional months. Results: The NF cohort improved versus the placebo cohort within 3 months (Clox-1 p = 0.0083, 95%CI [0.4481, 2.9343]; Dementia Rating Scale p = 0.0266, 95%CI [0.1722, 2.7171]). Caregivers reported non-significant improvements in Neuropsychiatric Inventory. Both cohorts improved or maintained baseline performance during open-label extensions. Activities of Daily Living did not change for either cohort. Conclusions: These findings extend phase I studies where NF maintained or improved cognitive performance and mood/behavior.

Variants in Antiviral Genes are Risk Factors for Cognitive Decline and Dementia. - Licastro, Federico; Raschi, Elena; Carbone, Ilaria; Porcellini, Elisa (J Alzheimers Dis, 2015)
A gene association study of factors regulating antiviral response such as interferon (IFN)-λ3, also known as IL-28B, mediator complex (Med) 23, and interferon regulatory factor (IRF) 7 with cognitive deterioration and Alzheimer's disease (AD) was performed. Differences in the TT genotype distribution of IL-28B single nucleotide polymorphism (SNP) between AD patients and controls were found. The GG genotype of Med23 gene appeared to influence the progression of the disease, being more frequent in the APOE ε4 negative elderly that developed AD during the five year follow-up. Leukocyte positivity for Epstein Barr virus (EBV) and human herpes virus (HHV)-6 DNA was analyzed. Med23 GG genotype correlated with the positivity to HHV-6 DNA. EBV and HHV-6 plasma IgG levels were also investigated and EBV IgG levels were increased in AD with the IRF7 GG genotype. A differential genetic background in genes regulating anti-virus responses was associated with an increased risk of cognitive decline and AD. EBV and HHV-6 appeared to be risk factors for AD in genetically susceptible elderly.

Advancing research diagnostic criteria for Alzheimer's disease: the IWG-2 criteria. - Dubois, Bruno; Feldman, Howard H; Jacova, Claudia; Hampel, Harald; Molinuevo, José Luis; Blennow, Kaj; DeKosky, Steven T; Gauthier, Serge; Selkoe, Dennis; Bateman, Randall; Cappa, Stefano; Crutch, Sebastian; et al. (Lancet Neurol, 2014)
In the past 8 years, both the International Working Group (IWG) and the US National Institute on Aging-Alzheimer's Association have contributed criteria for the diagnosis of Alzheimer's disease (AD) that better define clinical phenotypes and integrate biomarkers into the diagnostic process, covering the full staging of the disease. This Position Paper considers the strengths and limitations of the IWG research diagnostic criteria and proposes advances to improve the diagnostic framework. On the basis of these refinements, the diagnosis of AD can be simplified, requiring the presence of an appropriate clinical AD phenotype (typical or atypical) and a pathophysiological biomarker consistent with the presence of Alzheimer's pathology. We propose that downstream topographical biomarkers of the disease, such as volumetric MRI and fluorodeoxyglucose PET, might better serve in the measurement and monitoring of the course of disease. This paper also elaborates on the specific diagnostic criteria for atypical forms of AD, for mixed AD, and for the preclinical states of AD.
Keywords: Alzheimer Disease; Biomarkers; Humans; International Cooperation; Phenotype; Practice Guidelines as Topic; Societies, Medical

C9orf72 nucleotide repeat structures initiate molecular cascades of disease. - Haeusler, Aaron R; Donnelly, Christopher J; Periz, Goran; Simko, Eric A J; Shaw, Patrick G; Kim, Min-Sik; Maragakis, Nicholas J; Troncoso, Juan C; Pandey, Akhilesh; Sattler, Rita; Rothstein, Jeffrey D; Wang, Jiou (Nature, 2014)
A hexanucleotide repeat expansion (HRE), (GGGGCC)n, in C9orf72 is the most common genetic cause of the neurodegenerative diseases amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Here we identify a molecular mechanism by which structural polymorphism of the HRE leads to ALS/FTD pathology and defects. The HRE forms DNA and RNA G-quadruplexes with distinct structures and promotes RNA•DNA hybrids (R-loops). The structural polymorphism causes a repeat-length-dependent accumulation of transcripts aborted in the HRE region. These transcribed repeats bind to ribonucleoproteins in a conformation-dependent manner. Specifically, nucleolin, an essential nucleolar protein, preferentially binds the HRE G-quadruplex, and patient cells show evidence of nucleolar stress. Our results demonstrate that distinct C9orf72 HRE structural polymorphism at both DNA and RNA levels initiates molecular cascades leading to ALS/FTD pathologies, and provide the basis for a mechanistic model for repeat-associated neurodegenerative diseases.
Keywords: Amyotrophic Lateral Sclerosis; B-Lymphocytes; Base Sequence; Cell Nucleolus; DNA; DNA Repeat Expansion; Frontotemporal Dementia; G-Quadruplexes; HEK293 Cells; Humans; Models, Molecular; Neurons; Open Reading Frames; Phosphoproteins; Ribonucleoproteins; RNA; RNA-Binding Proteins; Stress, Physiological; Transcription, Genetic

Phase 3 trials of solanezumab for mild-to-moderate Alzheimer's disease. - Doody, Rachelle S; Thomas, Ronald G; Farlow, Martin; Iwatsubo, Takeshi; Vellas, Bruno; Joffe, Steven; Kieburtz, Karl; Raman, Rema; Sun, Xiaoying; Aisen, Paul S; Siemers, Eric; Liu-Seifert, Hong; et al. (N Engl J Med, 2014)
BACKGROUND: Alzheimer's disease is characterized by amyloid-beta plaques, neurofibrillary tangles, gliosis, and neuronal loss. Solanezumab, a humanized monoclonal antibody, preferentially binds soluble forms of amyloid and in preclinical studies promoted its clearance from the brain. METHODS: In two phase 3, double-blind trials (EXPEDITION 1 and EXPEDITION 2), we randomly assigned 1012 and 1040 patients, respectively, with mild-to-moderate Alzheimer's disease to receive placebo or solanezumab (administered intravenously at a dose of 400 mg) every 4 weeks for 18 months. The primary outcomes were the changes from baseline to week 80 in scores on the 11-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog11; range, 0 to 70, with higher scores indicating greater cognitive impairment) and the Alzheimer's Disease Cooperative Study-Activities of Daily Living scale (ADCS-ADL; range, 0 to 78, with lower scores indicating worse functioning). After analysis of data from EXPEDITION 1, the primary outcome for EXPEDITION 2 was revised to the change in scores on the 14-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog14; range, 0 to 90, with higher scores indicating greater impairment), in patients with mild Alzheimer's disease. RESULTS: Neither study showed significant improvement in the primary outcomes. The modeled difference between groups (solanezumab group minus placebo group) in the change from baseline was -0.8 points for the ADAS-cog11 score (95% confidence interval [CI], -2.1 to 0.5; P=0.24) and -0.4 points for the ADCS-ADL score (95% CI, -2.3 to 1.4; P=0.64) in EXPEDITION 1 and -1.3 points (95% CI, -2.5 to 0.3; P=0.06) and 1.6 points (95% CI, -0.2 to 3.3; P=0.08), respectively, in EXPEDITION 2. Between-group differences in the changes in the ADAS-cog14 score were -1.7 points in patients with mild Alzheimer's disease (95% CI, -3.5 to 0.1; P=0.06) and -1.5 in patients with moderate Alzheimer's disease (95% CI, -4.1 to 1.1; P=0.26). In the combined safety data set, the incidence of amyloid-related imaging abnormalities with edema or hemorrhage was 0.9% with solanezumab and 0.4% with placebo for edema (P=0.27) and 4.9% and 5.6%, respectively, for hemorrhage (P=0.49). CONCLUSIONS: Solanezumab, a humanized monoclonal antibody that binds amyloid, failed to improve cognition or functional ability. (Funded by Eli Lilly; EXPEDITION 1 and 2 ClinicalTrials.gov numbers, NCT00905372 and NCT00904683.).
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Antibodies, Monoclonal, Humanized; Apolipoproteins E; Biomarkers; Cognition; Double-Blind Method; Female; Humans; Intention to Treat Analysis; Male; Neuropsychological Tests; Severity of Illness Index; tau Proteins; Treatment Failure

Plasma phospholipids identify antecedent memory impairment in older adults. - Mapstone, Mark; Cheema, Amrita K; Fiandaca, Massimo S; Zhong, Xiaogang; Mhyre, Timothy R; MacArthur, Linda H; Hall, William J; Fisher, Susan G; Peterson, Derick R; Haley, James M; Nazar, Michael D; Rich, Steven A; et al. (Nat Med, 2014)
Alzheimer's disease causes a progressive dementia that currently affects over 35 million individuals worldwide and is expected to affect 115 million by 2050 (ref. 1). There are no cures or disease-modifying therapies, and this may be due to our inability to detect the disease before it has progressed to produce evident memory loss and functional decline. Biomarkers of preclinical disease will be critical to the development of disease-modifying or even preventative therapies. Unfortunately, current biomarkers for early disease, including cerebrospinal fluid tau and amyloid-β levels, structural and functional magnetic resonance imaging and the recent use of brain amyloid imaging or inflammaging, are limited because they are either invasive, time-consuming or expensive. Blood-based biomarkers may be a more attractive option, but none can currently detect preclinical Alzheimer's disease with the required sensitivity and specificity. Herein, we describe our lipidomic approach to detecting preclinical Alzheimer's disease in a group of cognitively normal older adults. We discovered and validated a set of ten lipids from peripheral blood that predicted phenoconversion to either amnestic mild cognitive impairment or Alzheimer's disease within a 2-3 year timeframe with over 90% accuracy. This biomarker panel, reflecting cell membrane integrity, may be sensitive to early neurodegeneration of preclinical Alzheimer's disease.
Keywords: Aged; Alzheimer Disease; Asparagine; Biomarkers; Carnitine; Cohort Studies; Dipeptides; Female; Humans; Longitudinal Studies; Lysophosphatidylcholines; Malates; Male; Memory Disorders; Metabolome; Mild Cognitive Impairment; Neuropsychological Tests; Phosphatidylcholines; Phosphatidylinositols; Phospholipids; Proline; Prospective Studies; Sensitivity and Specificity; Sphingomyelins; Ursodeoxycholic Acid

Ten-year effects of the advanced cognitive training for independent and vital elderly cognitive training trial on cognition and everyday functioning in older adults. - Rebok, George W; Ball, Karlene; Guey, Lin T; Jones, Richard N; Kim, Hae-Young; King, Jonathan W; Marsiske, Michael; Morris, John N; Tennstedt, Sharon L; Unverzagt, Frederick W; Willis, Sherry L (J Am Geriatr Soc, 2014)
OBJECTIVES: To determine the effects of cognitive training on cognitive abilities and everyday function over 10 years. DESIGN: Ten-year follow-up of a randomized, controlled single-blind trial (Advanced Cognitive Training for Independent and Vital Elderly (ACTIVE)) with three intervention groups and a no-contact control group. SETTING: Six U.S. cities. PARTICIPANTS: A volunteer sample of 2,832 persons (mean baseline age 73.6; 26% African American) living independently. INTERVENTION: Ten training sessions for memory, reasoning, or speed of processing; four sessions of booster training 11 and 35 months after initial training. MEASUREMENTS: Objectively measured cognitive abilities and self-reported and performance-based measures of everyday function. RESULTS: Participants in each intervention group reported less difficulty with instrumental activities of daily living (IADLs) (memory: effect size = 0.48, 99% confidence interval (CI) = 0.12-0.84; reasoning: effect size = 0.38, 99% CI = 0.02-0.74; speed of processing: effect size = 0.36, 99% CI = 0.01-0.72). At a mean age of 82, approximately 60% of trained participants, versus 50% of controls (P < .05), were at or above their baseline level of self-reported IADL function at 10 years. The reasoning and speed-of-processing interventions maintained their effects on their targeted cognitive abilities at 10 years (reasoning: effect size = 0.23, 99% CI = 0.09-0.38; speed of processing: effect size = 0.66, 99% CI = 0.43-0.88). Memory training effects were no longer maintained for memory performance. Booster training produced additional and durable improvement for the reasoning intervention for reasoning performance (effect size = 0.21, 99% CI = 0.01-0.41) and the speed-of-processing intervention for speed-of-processing performance (effect size = 0.62, 99% CI = 0.31-0.93). CONCLUSION: Each Advanced Cognitive Training for Independent and Vital Elderly cognitive intervention resulted in less decline in self-reported IADL compared with the control group. Reasoning and speed, but not memory, training resulted in improved targeted cognitive abilities for 10 years.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Cognition Disorders; Cognitive Therapy; Female; Follow-Up Studies; Humans; Independent Living; Male; Memory Disorders; Mental Processes; Single-Blind Method; United States

Two phase 3 trials of bapineuzumab in mild-to-moderate Alzheimer's disease. - Salloway, Stephen; Sperling, Reisa; Fox, Nick C; Blennow, Kaj; Klunk, William; Raskind, Murray; Sabbagh, Marwan; Honig, Lawrence S; Porsteinsson, Anton P; Ferris, Steven; Reichert, Marcel; Ketter, Nzeera; et al. (N Engl J Med, 2014)
BACKGROUND: Bapineuzumab, a humanized anti-amyloid-beta monoclonal antibody, is in clinical development for the treatment of Alzheimer's disease. METHODS: We conducted two double-blind, randomized, placebo-controlled, phase 3 trials involving patients with mild-to-moderate Alzheimer's disease--one involving 1121 carriers of the apolipoprotein E (APOE) ε4 allele and the other involving 1331 noncarriers. Bapineuzumab or placebo, with doses varying by study, was administered by intravenous infusion every 13 weeks for 78 weeks. The primary outcome measures were scores on the 11-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog11, with scores ranging from 0 to 70 and higher scores indicating greater impairment) and the Disability Assessment for Dementia (DAD, with scores ranging from 0 to 100 and higher scores indicating less impairment). A total of 1090 carriers and 1114 noncarriers were included in the efficacy analysis. Secondary outcome measures included findings on positron-emission tomographic amyloid imaging with the use of Pittsburgh compound B (PIB-PET) and cerebrospinal fluid phosphorylated tau (phospho-tau) concentrations. RESULTS: There were no significant between-group differences in the primary outcomes. At week 78, the between-group differences in the change from baseline in the ADAS-cog11 and DAD scores (bapineuzumab group minus placebo group) were -0.2 (P=0.80) and -1.2 (P=0.34), respectively, in the carrier study; the corresponding differences in the noncarrier study were -0.3 (P=0.64) and 2.8 (P=0.07) with the 0.5-mg-per-kilogram dose of bapineuzumab and 0.4 (P=0.62) and 0.9 (P=0.55) with the 1.0-mg-per-kilogram dose. The major safety finding was amyloid-related imaging abnormalities with edema among patients receiving bapineuzumab, which increased with bapineuzumab dose and APOE ε4 allele number and which led to discontinuation of the 2.0-mg-per-kilogram dose. Between-group differences were observed with respect to PIB-PET and cerebrospinal fluid phospho-tau concentrations in APOE ε4 allele carriers but not in noncarriers. CONCLUSIONS: Bapineuzumab did not improve clinical outcomes in patients with Alzheimer's disease, despite treatment differences in biomarkers observed in APOE ε4 carriers. (Funded by Janssen Alzheimer Immunotherapy and Pfizer; Bapineuzumab 301 and 302 ClinicalTrials.gov numbers, NCT00575055 and NCT00574132, and EudraCT number, 2009-012748-17.).
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Antibodies, Monoclonal, Humanized; Apolipoproteins E; Biomarkers; Brain; Cognition; Double-Blind Method; Edema; Female; Humans; Intention to Treat Analysis; Male; Middle Aged; Neuropsychological Tests; Phosphorylation; Positron-Emission Tomography; Severity of Illness Index; tau Proteins; Treatment Failure

Anti-amyloid β autoantibodies in cerebral amyloid angiopathy-related inflammation: implications for amyloid-modifying therapies. - Piazza, Fabrizio; Greenberg, Steven M; Savoiardo, Mario; Gardinetti, Margherita; Chiapparini, Luisa; Raicher, Irina; Nitrini, Ricardo; Sakaguchi, Hideya; Brioschi, Monica; Billo, Giuseppe; Colombo, Antonio; Lanzani, Francesca; et al. (Ann Neurol, 2013)
OBJECTIVE: Cerebral amyloid angiopathy-related inflammation (CAA-ri) is characterized by vasogenic edema and multiple cortical/subcortical microbleeds, sharing several aspects with the recently defined amyloid-related imaging abnormalities (ARIA) reported in Alzheimer's disease (AD) passive immunization therapies. Herein, we investigated the role of anti-amyloid β (Aβ) autoantibodies in the acute and remission phases of CAA-ri. METHODS: We used a novel ultrasensitive technique on patients from a retrospective multicenter case-control study, and evaluated the anti-Aβ autoantibody concentration in the cerebrospinal fluid (CSF) of 10 CAA-ri, 8 CAA, 14 multiple sclerosis, and 25 control subjects. Levels of soluble Aβ40, Aβ42, tau, P-181 tau, and APOE genotype were also investigated. RESULTS: During the acute phase of CAA-ri, anti-Aβ autoantibodies were specifically increased and directly correlated with Aβ mobilization, together with augmented tau and P-181 tau. Following clinical and radiological remission, autoantibodies progressively returned to control levels, and both soluble Aβ and axonal degeneration markers decreased in parallel. INTERPRETATION: Our data support the hypothesis that the pathogenesis of CAA-ri may be mediated by a selective autoimmune reaction against cerebrovascular Aβ, directly related to autoantibody concentration and soluble Aβ. The CSF dosage of anti-Aβ autoantibodies with the technique here described can thus be proposed as a valid alternative tool for the diagnosis of CAA-ri. Moreover, given the similarities between ARIA developing spontaneously and those observed during immunization trials, anti-Aβ autoantibodies can be considered as novel potential biomarkers in future amyloid-modifying therapies for the treatment of AD and CAA.
Keywords: Adult; Aged; Amyloid beta-Peptides; Apolipoproteins E; Autoantibodies; Brain; Case-Control Studies; Cerebral Amyloid Angiopathy; Female; Humans; Inflammation; Male; Middle Aged; Peptide Fragments; Phosphorylation; Retrospective Studies; Steroids; tau Proteins

Meta-analysis of 74,046 individuals identifies 11 new susceptibility loci for Alzheimer's disease. - Lambert, J C; Ibrahim-Verbaas, C A; Harold, D; Naj, A C; Sims, R; Bellenguez, C; DeStafano, A L; Bis, J C; Beecham, G W; Grenier-Boley, B; Russo, G; Thorton-Wells, T A; et al. (Nat Genet, 2013)
Eleven susceptibility loci for late-onset Alzheimer's disease (LOAD) were identified by previous studies; however, a large portion of the genetic risk for this disease remains unexplained. We conducted a large, two-stage meta-analysis of genome-wide association studies (GWAS) in individuals of European ancestry. In stage 1, we used genotyped and imputed data (7,055,881 SNPs) to perform meta-analysis on 4 previously published GWAS data sets consisting of 17,008 Alzheimer's disease cases and 37,154 controls. In stage 2, 11,632 SNPs were genotyped and tested for association in an independent set of 8,572 Alzheimer's disease cases and 11,312 controls. In addition to the APOE locus (encoding apolipoprotein E), 19 loci reached genome-wide significance (P < 5 × 10(-8)) in the combined stage 1 and stage 2 analysis, of which 11 are newly associated with Alzheimer's disease.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cohort Studies; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

TREM2 variants in Alzheimer's disease. - Guerreiro, Rita; Wojtas, Aleksandra; Bras, Jose; Carrasquillo, Minerva; Rogaeva, Ekaterina; Majounie, Elisa; Cruchaga, Carlos; Sassi, Celeste; Kauwe, John S K; Younkin, Steven; Hazrati, Lilinaz; Collinge, John; et al. (N Engl J Med, 2013)
BACKGROUND: Homozygous loss-of-function mutations in TREM2, encoding the triggering receptor expressed on myeloid cells 2 protein, have previously been associated with an autosomal recessive form of early-onset dementia. METHODS: We used genome, exome, and Sanger sequencing to analyze the genetic variability in TREM2 in a series of 1092 patients with Alzheimer's disease and 1107 controls (the discovery set). We then performed a meta-analysis on imputed data for the TREM2 variant rs75932628 (predicted to cause a R47H substitution) from three genomewide association studies of Alzheimer's disease and tested for the association of the variant with disease. We genotyped the R47H variant in an additional 1887 cases and 4061 controls. We then assayed the expression of TREM2 across different regions of the human brain and identified genes that are differentially expressed in a mouse model of Alzheimer's disease and in control mice. RESULTS: We found significantly more variants in exon 2 of TREM2 in patients with Alzheimer's disease than in controls in the discovery set (P=0.02). There were 22 variant alleles in 1092 patients with Alzheimer's disease and 5 variant alleles in 1107 controls (P<0.001). The most commonly associated variant, rs75932628 (encoding R47H), showed highly significant association with Alzheimer's disease (P<0.001). Meta-analysis of rs75932628 genotypes imputed from genomewide association studies confirmed this association (P=0.002), as did direct genotyping of an additional series of 1887 patients with Alzheimer's disease and 4061 controls (P<0.001). Trem2 expression differed between control mice and a mouse model of Alzheimer's disease. CONCLUSIONS: Heterozygous rare variants in TREM2 are associated with a significant increase in the risk of Alzheimer's disease. (Funded by Alzheimer's Research UK and others.).
Keywords: Aged; Alzheimer Disease; Animals; Brain; Exome; Genetic Variation; Genome-Wide Association Study; Genotype; Genotyping Techniques; Heterozygote; Humans; Membrane Glycoproteins; Mice; Mice, Inbred A; Mutation; Receptors, Immunologic; Risk Factors; RNA, Messenger; Sequence Analysis, DNA

An epigenetic blockade of cognitive functions in the neurodegenerating brain. - Gräff, Johannes; Rei, Damien; Guan, Ji-Song; Wang, Wen-Yuan; Seo, Jinsoo; Hennig, Krista M; Nieland, Thomas J F; Fass, Daniel M; Kao, Patricia F; Kahn, Martin; Su, Susan C; Samiei, Alireza; et al. (Nature, 2012)
Cognitive decline is a debilitating feature of most neurodegenerative diseases of the central nervous system, including Alzheimer's disease. The causes leading to such impairment are only poorly understood and effective treatments are slow to emerge. Here we show that cognitive capacities in the neurodegenerating brain are constrained by an epigenetic blockade of gene transcription that is potentially reversible. This blockade is mediated by histone deacetylase 2, which is increased by Alzheimer's-disease-related neurotoxic insults in vitro, in two mouse models of neurodegeneration and in patients with Alzheimer's disease. Histone deacetylase 2 associates with and reduces the histone acetylation of genes important for learning and memory, which show a concomitant decrease in expression. Importantly, reversing the build-up of histone deacetylase 2 by short-hairpin-RNA-mediated knockdown unlocks the repression of these genes, reinstates structural and synaptic plasticity, and abolishes neurodegeneration-associated memory impairments. These findings advocate for the development of selective inhibitors of histone deacetylase 2 and suggest that cognitive capacities following neurodegeneration are not entirely lost, but merely impaired by this epigenetic blockade.
Keywords: Acetylation; Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Disease Models, Animal; Epigenesis, Genetic; Gene Expression Regulation; Gene Knockdown Techniques; Hippocampus; Histone Deacetylase 2; Histones; Humans; Hydrogen Peroxide; Memory Disorders; Mice; Neurodegenerative Diseases; Neuronal Plasticity; Peptide Fragments; Phosphorylation; Promoter Regions, Genetic; Receptors, Glucocorticoid; RNA Polymerase II

Neuroinflammation, hyperphosphorylated tau, diffuse amyloid plaques, and down-regulation of the cellular prion protein in air pollution exposed children and young adults. - Calderón-Garcidueñas, Lilian; Kavanaugh, Michael; Block, Michelle; D'Angiulli, Amedeo; Delgado-Chávez, Ricardo; Torres-Jardón, Ricardo; González-Maciel, Angelica; Reynoso-Robles, Rafael; Osnaya, Norma; Villarreal-Calderon, Rodolfo; Guo, Ruixin; Hua, Zhaowei; et al. (J Alzheimers Dis, 2012)
Air pollution exposures have been linked to neuroinflammation and neuropathology. Autopsy samples of the frontal cortex from control (n = 8) and pollution-exposed (n = 35) children and young adults were analyzed by RT-PCR (n = 43) and microarray analysis (n = 12) for gene expression changes in oxidative stress, DNA damage signaling, NFκB signaling, inflammation, and neurodegeneration pathways. The effect of apolipoprotein E (APOE) genotype on the presence of protein aggregates associated with Alzheimer's disease (AD) pathology was also explored. Exposed urbanites displayed differential (>2-fold) regulation of 134 genes. Forty percent exhibited tau hyperphosphorylation with pre-tangle material and 51% had amyloid-β (Aβ) diffuse plaques compared with 0% in controls. APOE4 carriers had greater hyperphosphorylated tau and diffuse Aβ plaques versus E3 carriers (Q = 7.82, p = 0.005). Upregulated gene network clusters included IL1, NFκB, TNF, IFN, and TLRs. A 15-fold frontal down-regulation of the prion-related protein (PrP(C)) was seen in highly exposed subjects. The down-regulation of the PrP(C) is critical given its important roles for neuroprotection, neurodegeneration, and mood disorder states. Elevation of indices of neuroinflammation and oxidative stress, down-regulation of the PrP(C) and AD-associated pathology are present in young megacity residents. The inducible regulation of gene expression suggests they are evolving different mechanisms in an attempt to cope with the constant state of inflammation and oxidative stress related to their environmental exposures. Together, these data support a role for air pollution in CNS damage and its impact upon the developing brain and the potential etiology of AD and mood disorders.
Keywords: Adolescent; Adult; Age Factors; Air Pollution; Child; Child, Preschool; Cohort Studies; Down-Regulation; Encephalitis; Female; Frontal Lobe; Gene Regulatory Networks; Humans; Infant; Male; Mexico; Phosphorylation; Plaque, Amyloid; Prions; tau Proteins; Young Adult

An operational approach to National Institute on Aging-Alzheimer's Association criteria for preclinical Alzheimer disease. - Jack, Clifford R; Knopman, David S; Weigand, Stephen D; Wiste, Heather J; Vemuri, Prashanthi; Lowe, Val; Kantarci, Kejal; Gunter, Jeffrey L; Senjem, Matthew L; Ivnik, Robert J; Roberts, Rosebud O; Rocca, Walter A; et al. (Ann Neurol, 2012)
OBJECTIVE: A workgroup commissioned by the Alzheimer's Association (AA) and the National Institute on Aging (NIA) recently published research criteria for preclinical Alzheimer disease (AD). We performed a preliminary assessment of these guidelines. METHODS: We employed Pittsburgh compound B positron emission tomography (PET) imaging as our biomarker of cerebral amyloidosis, and (18) fluorodeoxyglucose PET imaging and hippocampal volume as biomarkers of neurodegeneration. A group of 42 clinically diagnosed AD subjects was used to create imaging biomarker cutpoints. A group of 450 cognitively normal (CN) subjects from a population-based sample was used to develop cognitive cutpoints and to assess population frequencies of the different preclinical AD stages using different cutpoint criteria. RESULTS: The new criteria subdivide the preclinical phase of AD into stages 1 to 3. To classify our CN subjects, 2 additional categories were needed. Stage 0 denotes subjects with normal AD biomarkers and no evidence of subtle cognitive impairment. Suspected non-AD pathophysiology (SNAP) denotes subjects with normal amyloid PET imaging, but abnormal neurodegeneration biomarker studies. At fixed cutpoints corresponding to 90% sensitivity for diagnosing AD and the 10th percentile of CN cognitive scores, 43% of our sample was classified as stage 0, 16% stage 1, 12 % stage 2, 3% stage 3, and 23% SNAP. INTERPRETATION: This cross-sectional evaluation of the NIA-AA criteria for preclinical AD indicates that the 1-3 staging criteria coupled with stage 0 and SNAP categories classify 97% of CN subjects from a population-based sample, leaving only 3% unclassified. Future longitudinal validation of the criteria will be important.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Aniline Compounds; Biomarkers; Brain; Cognition Disorders; Disease Progression; Female; Fluorodeoxyglucose F18; Humans; Longitudinal Studies; Male; Mental Status Schedule; National Institute on Aging (U.S.); Neuropsychological Tests; Positron-Emission Tomography; Thiazoles; United States

18F-THK523: a novel in vivo tau imaging ligand for Alzheimer's disease. - Fodero-Tavoletti, Michelle T; Okamura, Nobuyuki; Furumoto, Shozo; Mulligan, Rachel S; Connor, Andrea R; McLean, Catriona A; Cao, Diana; Rigopoulos, Angela; Cartwright, Glenn A; O'Keefe, Graeme; Gong, Sylvia; Adlard, Paul A; et al. (Brain, 2011)
While considerable effort has focused on developing positron emission tomography β-amyloid imaging radiotracers for the early diagnosis of Alzheimer's disease, no radiotracer is available for the non-invasive quantification of tau. In this study, we detail the characterization of (18)F-THK523 as a novel tau imaging radiotracer. In vitro binding studies demonstrated that (18)F-THK523 binds with higher affinity to a greater number of binding sites on recombinant tau (K18Δ280K) compared with β-amyloid(1-42) fibrils. Autoradiographic and histofluorescence analysis of human hippocampal serial sections with Alzheimer's disease exhibited positive THK523 binding that co-localized with immunoreactive tau pathology, but failed to highlight β-amyloid plaques. Micro-positron emission tomography analysis demonstrated significantly higher retention of (18)F-THK523 (48%; P < 0.007) in tau transgenic mice brains compared with their wild-type littermates or APP/PS1 mice. The preclinical examination of THK523 has demonstrated its high affinity and selectivity for tau pathology both in vitro and in vivo, indicating that (18)F-THK523 fulfils ligand criteria for human imaging trials.
Keywords: Alzheimer Disease; Analysis of Variance; Aniline Compounds; Animals; Autoradiography; Binding Sites; Brain; Female; Fluorodeoxyglucose F18; Humans; Immunohistochemistry; Male; Mice; Quinolines; Radiopharmaceuticals; tau Proteins

The diagnosis of dementia due to Alzheimer's disease: recommendations from the National Institute on Aging-Alzheimer's Association workgroups on diagnostic guidelines for Alzheimer's disease. - McKhann, Guy M; Knopman, David S; Chertkow, Howard; Hyman, Bradley T; Jack, Clifford R; Kawas, Claudia H; Klunk, William E; Koroshetz, Walter J; Manly, Jennifer J; Mayeux, Richard; Mohs, Richard C; Morris, John C; et al. (Alzheimers Dement, 2011)
The National Institute on Aging and the Alzheimer's Association charged a workgroup with the task of revising the 1984 criteria for Alzheimer's disease (AD) dementia. The workgroup sought to ensure that the revised criteria would be flexible enough to be used by both general healthcare providers without access to neuropsychological testing, advanced imaging, and cerebrospinal fluid measures, and specialized investigators involved in research or in clinical trial studies who would have these tools available. We present criteria for all-cause dementia and for AD dementia. We retained the general framework of probable AD dementia from the 1984 criteria. On the basis of the past 27 years of experience, we made several changes in the clinical criteria for the diagnosis. We also retained the term possible AD dementia, but redefined it in a manner more focused than before. Biomarker evidence was also integrated into the diagnostic formulations for probable and possible AD dementia for use in research settings. The core clinical criteria for AD dementia will continue to be the cornerstone of the diagnosis in clinical practice, but biomarker evidence is expected to enhance the pathophysiological specificity of the diagnosis of AD dementia. Much work lies ahead for validating the biomarker diagnosis of AD dementia.
Keywords: Alzheimer Disease; Biomarkers; Diagnosis, Differential; Diagnostic Imaging; Disease Progression; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; Societies, Medical; United States

Directed conversion of Alzheimer's disease patient skin fibroblasts into functional neurons. - Qiang, Liang; Fujita, Ryousuke; Yamashita, Toru; Angulo, Sergio; Rhinn, Herve; Rhee, David; Doege, Claudia; Chau, Lily; Aubry, Laetitia; Vanti, William B; Moreno, Herman; Abeliovich, Asa (Cell, 2011)
Directed conversion of mature human cells, as from fibroblasts to neurons, is of potential clinical utility for neurological disease modeling as well as cell therapeutics. Here, we describe the efficient generation of human-induced neuronal (hiN) cells from adult skin fibroblasts of unaffected individuals and Alzheimer's patients, using virally transduced transcription regulators and extrinsic support factors. hiN cells from unaffected individuals display morphological, electrophysiological, and gene expression profiles that typify glutamatergic forebrain neurons and are competent to integrate functionally into the rodent CNS. hiN cells from familial Alzheimer disease (FAD) patients with presenilin-1 or -2 mutations exhibit altered processing and localization of amyloid precursor protein (APP) and increased production of Aβ, relative to the source patient fibroblasts or hiN cells from unaffected individuals. Together, our findings demonstrate directed conversion of human fibroblasts to a neuronal phenotype and reveal cell type-selective pathology in hiN cells derived from FAD patients.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Cell Transdifferentiation; Cells, Cultured; Fibroblasts; Humans; Neurons; Presenilin-1; Presenilin-2; Regenerative Medicine; Skin

Neuronal activity regulates the regional vulnerability to amyloid-β deposition. - Bero, Adam W; Yan, Ping; Roh, Jee Hoon; Cirrito, John R; Stewart, Floy R; Raichle, Marcus E; Lee, Jin-Moo; Holtzman, David M (Nat Neurosci, 2011)
Amyloid-β (Aβ) plaque deposition in specific brain regions is a pathological hallmark of Alzheimer's disease. However, the mechanism underlying the regional vulnerability to Aβ deposition in Alzheimer's disease is unknown. Herein, we provide evidence that endogenous neuronal activity regulates the regional concentration of interstitial fluid (ISF) Aβ, which drives local Aβ aggregation. Using in vivo microdialysis, we show that ISF Aβ concentrations in several brain regions of APP transgenic mice before plaque deposition were commensurate with the degree of subsequent plaque deposition and with the concentration of lactate, a marker of neuronal activity. Furthermore, unilateral vibrissal stimulation increased ISF Aβ, and unilateral vibrissal deprivation decreased ISF Aβ and lactate, in contralateral barrel cortex. Long-term unilateral vibrissal deprivation decreased amyloid plaque formation and growth. Our results suggest a mechanism to account for the vulnerability of specific brain regions to Aβ deposition in Alzheimer's disease.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cerebral Cortex; Disease Models, Animal; Extracellular Fluid; Female; Lactic Acid; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microdialysis; Neurons; Plaque, Amyloid; Sensory Deprivation; Somatosensory Cortex

Toward defining the preclinical stages of Alzheimer's disease: recommendations from the National Institute on Aging-Alzheimer's Association workgroups on diagnostic guidelines for Alzheimer's disease. - Sperling, Reisa A; Aisen, Paul S; Beckett, Laurel A; Bennett, David A; Craft, Suzanne; Fagan, Anne M; Iwatsubo, Takeshi; Jack, Clifford R; Kaye, Jeffrey; Montine, Thomas J; Park, Denise C; Reiman, Eric M; et al. (Alzheimers Dement, 2011)
The pathophysiological process of Alzheimer's disease (AD) is thought to begin many years before the diagnosis of AD dementia. This long "preclinical" phase of AD would provide a critical opportunity for therapeutic intervention; however, we need to further elucidate the link between the pathological cascade of AD and the emergence of clinical symptoms. The National Institute on Aging and the Alzheimer's Association convened an international workgroup to review the biomarker, epidemiological, and neuropsychological evidence, and to develop recommendations to determine the factors which best predict the risk of progression from "normal" cognition to mild cognitive impairment and AD dementia. We propose a conceptual framework and operational research criteria, based on the prevailing scientific evidence to date, to test and refine these models with longitudinal clinical research studies. These recommendations are solely intended for research purposes and do not have any clinical implications at this time. It is hoped that these recommendations will provide a common rubric to advance the study of preclinical AD, and ultimately, aid the field in moving toward earlier intervention at a stage of AD when some disease-modifying therapies may be most efficacious.
Keywords: Alzheimer Disease; Biomarkers; Cognition Disorders; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; United States

APOE predicts amyloid-beta but not tau Alzheimer pathology in cognitively normal aging. - Morris, John C; Roe, Catherine M; Xiong, Chengjie; Fagan, Anne M; Goate, Alison M; Holtzman, David M; Mintun, Mark A (Ann Neurol, 2010)
OBJECTIVE: To examine interactions of apolipoprotein E (APOE) genotype with age and with in vivo measures of preclinical Alzheimer disease (AD) in cognitively normal aging. METHODS: Two hundred forty-one cognitively normal individuals, aged 45-88 years, had cerebral amyloid imaging studies with Pittsburgh Compound-B (PIB). Of the 241 individuals, 168 (70%) also had cerebrospinal fluid (CSF) assays of amyloid-beta(42) (Abeta(42)), tau, and phosphorylated tau (ptau(181)). All individuals were genotyped for APOE. RESULTS: The frequency of individuals with elevated mean cortical binding potential (MCBP) for PIB rose in an age-dependent manner from 0% at ages 45-49 years to 30.3% at 80-88 years. Reduced levels of CSF Abeta(42) appeared to begin earlier (18.2% of those aged 45-49 years) and increase with age in higher frequencies (50% at age 80-88 years) than elevations of MCBP. There was a gene dose effect for the APOE4 genotype, with greater MCBP increases and greater reductions in CSF Abeta(42) with increased numbers of APOE4 alleles. Individuals with an APOE2 allele had no increase in MCBP with age and had higher CSF Abeta(42) levels than individuals without an APOE2 allele. There was no APOE4 or APOE2 effect on CSF tau or ptau(181). INTERPRETATION: Increasing cerebral Abeta deposition with age is the pathobiological phenotype of APOE4. The biomarker sequence that detects Abeta deposition may first be lowered CSF Abeta(42), followed by elevated MCBP for PIB. A substantial proportion of cognitively normal individuals have presumptive preclinical AD.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Amyloid beta-Peptides; Aniline Compounds; Apolipoprotein E2; Apolipoprotein E4; Apolipoproteins E; Brain; Female; Follow-Up Studies; Genotype; Humans; Longitudinal Studies; Male; Middle Aged; Peptide Fragments; Phosphorylation; Plaque, Amyloid; tau Proteins; Thiazoles

Gamma-secretase activating protein is a therapeutic target for Alzheimer's disease. - He, Gen; Luo, Wenjie; Li, Peng; Remmers, Christine; Netzer, William J; Hendrick, Joseph; Bettayeb, Karima; Flajolet, Marc; Gorelick, Fred; Wennogle, Lawrence P; Greengard, Paul (Nature, 2010)
Accumulation of neurotoxic amyloid-beta is a major hallmark of Alzheimer's disease. Formation of amyloid-beta is catalysed by gamma-secretase, a protease with numerous substrates. Little is known about the molecular mechanisms that confer substrate specificity on this potentially promiscuous enzyme. Knowledge of the mechanisms underlying its selectivity is critical for the development of clinically effective gamma-secretase inhibitors that can reduce amyloid-beta formation without impairing cleavage of other gamma-secretase substrates, especially Notch, which is essential for normal biological functions. Here we report the discovery of a novel gamma-secretase activating protein (GSAP) that drastically and selectively increases amyloid-beta production through a mechanism involving its interactions with both gamma-secretase and its substrate, the amyloid precursor protein carboxy-terminal fragment (APP-CTF). GSAP does not interact with Notch, nor does it affect its cleavage. Recombinant GSAP stimulates amyloid-beta production in vitro. Reducing GSAP concentrations in cell lines decreases amyloid-beta concentrations. Knockdown of GSAP in a mouse model of Alzheimer's disease reduces levels of amyloid-beta and plaque development. GSAP represents a type of gamma-secretase regulator that directs enzyme specificity by interacting with a specific substrate. We demonstrate that imatinib, an anticancer drug previously found to inhibit amyloid-beta formation without affecting Notch cleavage, achieves its amyloid-beta-lowering effect by preventing GSAP interaction with the gamma-secretase substrate, APP-CTF. Thus, GSAP can serve as an amyloid-beta-lowering therapeutic target without affecting other key functions of gamma-secretase.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Benzamides; Cell Line; Disease Models, Animal; Gene Knockdown Techniques; Humans; Imatinib Mesylate; Mice; Peptide Fragments; Piperazines; Proteins; Pyrimidines; Receptor, Notch1; RNA Interference

Genetic evidence implicates the immune system and cholesterol metabolism in the aetiology of Alzheimer's disease. - Jones, Lesley; Holmans, Peter A; Hamshere, Marian L; Harold, Denise; Moskvina, Valentina; Ivanov, Dobril; Pocklington, Andrew; Abraham, Richard; Hollingworth, Paul; Sims, Rebecca; Gerrish, Amy; Pahwa, Jaspreet Singh; et al. (PLoS One, 2010)
BACKGROUND: Late Onset Alzheimer's disease (LOAD) is the leading cause of dementia. Recent large genome-wide association studies (GWAS) identified the first strongly supported LOAD susceptibility genes since the discovery of the involvement of APOE in the early 1990s. We have now exploited these GWAS datasets to uncover key LOAD pathophysiological processes. METHODOLOGY: We applied a recently developed tool for mining GWAS data for biologically meaningful information to a LOAD GWAS dataset. The principal findings were then tested in an independent GWAS dataset. PRINCIPAL FINDINGS: We found a significant overrepresentation of association signals in pathways related to cholesterol metabolism and the immune response in both of the two largest genome-wide association studies for LOAD. SIGNIFICANCE: Processes related to cholesterol metabolism and the innate immune response have previously been implicated by pathological and epidemiological studies of Alzheimer's disease, but it has been unclear whether those findings reflected primary aetiological events or consequences of the disease process. Our independent evidence from two large studies now demonstrates that these processes are aetiologically relevant, and suggests that they may be suitable targets for novel and existing therapeutic approaches.
Keywords: Alzheimer Disease; Apolipoproteins E; Cholesterol; Chromosome Mapping; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Immune System; Polymorphism, Single Nucleotide